3T-MRI in patients with pharmacoresistant epilepsy and a vagus nerve stimulator: a pilot study - Roesch, Julie; Hamer, Hajo; Mennecke, Angelika; Kasper, Burkhard; Engelhorn, Tobias; Dörfler, Arnd; Graf, Wolfgang (Epilepsy Research, 2015)
For safe 3T-MRI of patients with VNS (vagus nerve stimulator), specific conditions are mandatory. However, application of these conditions can lead to a loss of image quality. In this work, we evaluated the diagnostic value of 3T-MRI in VNS patients with pharmacoresistant epilepsy.Using a transmit-and-receive head coil and adapting our sequences to allow for low SAR (specific absorption rate), we examined 15 patients with pharmacoresistant epilepsy. Diagnostic quality was assessed by comparison of the SNR (signal to noise ratio) and CNR (contrast to noise ratio) of the hippocampus, the grey-white matter contrast and epileptogenic lesions to images of patients without VNS acquired with our routine 3T-MRI protocol and the 32-channel head coil.3T-MRI is feasible in VNS-patients. Image quality is adequate for detection and follow-up of epileptogenic lesions such as ganglioglioma or PNH (periventricular nodular heterotopia). Due to a significant reduction of SNR and CNR, the diagnostic value for subtle lesions may be decreased. Overall, the feasibility of 3T-MRI is beneficial in the diagnostic workup and follow-up of epilepsy-patients with VNS.
EVALuna2:22359

7 Tesla Hippocampal Subfield Analyses In Patients With Medically Refractory Epilepsy And Hippocampal Sclerosis - Roessler, K.; Roesch, Johannes; Coras, R.; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan; Mennecke, Angelika (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Abstract: Automatic Dementia Screening and Scoring by Applying Deep Learning on Clock-drawing Tests - Chen, Shuqing; Stromer, Daniel; Alnasser Alabdalrahim, Harb; Schwab, Stefan; Weih, Markus; Maier, Andreas (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-09

Accuracy of Dose-Saving Artificial-Intelligence-Based 3D Angiography (3DA) for Grading of Intracranial Artery Stenoses: Preliminary Findings - Lang, Stefan; Hölter, Philip; Schmidt, Manuel; Mrochen, Anne; Kuramatsu, Joji; Kaethner, Christian; Roser, Philipp; Kowarschik, Markus; Dörfler, Arnd (Diagnostics, 2023)
Background and purpose: Based on artificial intelligence (AI), 3D angiography (3DA) is a novel postprocessing algorithm for “DSA-like” 3D imaging of cerebral vasculature. Because 3DA requires neither mask runs nor digital subtraction as the current standard 3D-DSA does, it has the potential to cut the patient dose by 50%. The object was to evaluate 3DA’s diagnostic value for visualization of intracranial artery stenoses (IAS) compared to 3D-DSA. Materials and methods: 3D-DSA datasets of IAS (nIAS = 10) were postprocessed using conventional and prototype software (Siemens Healthineers AG, Erlangen, Germany). Matching reconstructions were assessed by two experienced neuroradiologists in consensus reading, considering image quality (IQ), vessel diameters (VD1/2), vessel-geometry index (VGI = VD1/VD2), and specific qualitative/quantitative parameters of IAS (e.g., location, visual IAS grading [low-/medium-/high-grade] and intra-/poststenotic diameters [dintra-/poststenotic in mm]). Using the NASCET criteria, the percentual degree of luminal restriction was calculated. Results: In total, 20 angiographic 3D volumes (n3DA = 10; n3D-DSA = 10) were successfully reconstructed with equivalent IQ. Assessment of the vessel geometry in 3DA datasets did not differ significantly from 3D-DSA (VD1: r = 0.994, p = 0.0001; VD2:r = 0.994, p = 0.0001; VGI: r = 0.899, p = 0.0001). Qualitative analysis of IAS location (3DA/3D-DSA:nICA/C4 = 1, nICA/C7 = 1, nMCA/M1 = 4, nVA/V4 = 2, nBA = 2) and the visual IAS grading (3DA/3D-DSA:nlow-grade = 3, nmedium-grade = 5, nhigh-grade = 2) revealed identical results for 3DA and 3D-DSA, respectively. Quantitative IAS assessment showed a strong correlation regarding intra-/poststenotic diameters (rdintrastenotic = 0.995, pdintrastenotic = 0.0001; rdpoststenotic = 0.995, pdpoststenotic = 0.0001) and the percentual degree of luminal restriction (rNASCET 3DA = 0.981; pNASCET 3DA = 0.0001). Conclusions: The AI-based 3DA is a resilient algorithm for the visualization of IAS and shows comparable results to 3D-DSA. Hence, 3DA is a promising new method that allows a considerable patient-dose reduction, and its clinical implementation would be highly desirable.
CRIS-Team Scopus Importer:2023-03-10
Keywords: 3D angiography; artificial intelligence; deep learning; dose reduction; flat-detector computed tomography (FD-CT); innovative postprocessing; intracranial artery stenosis

A common SCN1A splice-site polymorphism modifies the effect of carbamazepine on cortical excitability–a pharmacogenetic transcranial magnetic stimulation study - Menzler, Katja; Hermsen, Anke; Balkenhol, Katharina; Duddek, Caroline; Bugiel, Hannes; Bauer, Sebastian; Schorge, Stephanie; Reif, Philipp S.; Klein, Karl Martin; Haag, Anja; Oertel, Wolfgang H.; Hamer, Hajo; et al. (Epilepsia, 2014)
SCN1A encodes the alpha subunit of the voltage-gated sodium channel and plays a crucial role in several epilepsy syndromes. The common SCN1A splice-site polymorphism rs3812718 (IVS5N+5 G>A) might contribute to the pathophysiology underlying genetic generalized epilepsies and is associated with electrophysiologic properties of the channel and the effect of sodium-channel blocking antiepileptic drugs. We assessed the effects of the rs3812718 genotype on cortical excitability at baseline and after administration of carbamazepine in order to investigate the mechanism of this association.Paired-pulse transcranial magnetic stimulation (TMS) was applied in 92 healthy volunteers with the homozygous genotypes AA or GG of rs3812718 at baseline and after application of 400 mg of carbamazepine or placebo in a double-blind, randomized, crossover design. Resting motor threshold (RMT), short interval intracortical inhibition (SICI), intracortical facilitation (ICF), and cortical silent period (CSP) were determined.At baseline there was no significant difference in any TMS parameter. Genotype GG was associated with a higher carbamazepine-induced increase in CSP duration as compared to AA (multivariate analysis of covariance [MANCOVA], p = 0.013). An expected significant increase in RMT was genotype independent.We found that the rs3812718 genotype modifies the effect of carbamazepine on CSP duration (mainly reflecting modulation of ?-aminobutyric acid (GABA)ergic inhibition), but not on RMT (mainly reflecting modulation of voltage-gated sodium channels). This provides evidence that rs3812718 affects the pharmacoresponse to carbamazepine via an effect on GABAergic cortical interneurons. Our results also confirm that TMS is useful to investigate the effect of genetic variants on cortical excitability and pharmacoresponse.
EVALuna2:7257

A Costa Rican family affected with Charcot-Marie-Tooth disease due to the myelin protein zero (MPZ) p.Thr124Met mutation shares the Belgian haplotype - Leal, Alejandro; Berghoff, Corinna; Berghoff, Martin; Rojas-Araya, Melissa; Ortiz, Carolina; Heuss, Dieter; Del Valle, Gerardo; Rautenstrauß, Bernd (Revista De Biologia Tropical, 2014)
The p.Thr124Met mutation in the myelin protein zero (MPZ) causes the Charcot-Marie-Tooth disease type 2J, a peripheral neuropathy with additional symptoms as pupillary alterations and deafness. It was observed in several families around the world originating e. g. from Germany, Belgium, Japan, Italy and North America. Here we report Central American patients originating from a family in Costa Rica carrying this mutation. Clinical, electrophysiological and molecular analysis of patients and controls were performed, including gene and linked markers' sequencing. Carriers share almost the entire haplotype with two non related Belgian CMT patients. As a result of the haplotype analysis, based on ten markers (seven SNPs, two microsatellites and an intronic polyA stretch), the founder effect hypothesis for this allele migration is suggestive.
EVALuna2:22390

Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd (European Journal of Neurology, 2022)
Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either “known AF” (KAF), defined as AF confirmed before stroke onset, or “AF detected after stroke” (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke-triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3-month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre-stroke anticoagulation. OAC for secondary prevention was associated with favorable 3-month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype.
CRIS-Team Scopus Importer:2022-04-22
Keywords: acute ischemic stroke; atrial fibrillation detected after stroke; known atrial fibrillation; modified Rankin scale; oral anticoagulation; stroke recurrence

Acute ischemic stroke and transient ischemic attack: an update on recent practically relevant clinical trials - Staykov, Dimitre; Schwab, Stefan (Neurohospitalist, 2014)
EVALuna2:22365

Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

Adaptive Immune Response to and Survival Effect of Temozolomide- and Valproic Acid-induced Autophagy in Glioblastoma - Proske, Judith; Walter, Lisa; Bumes, Elisabeth; Hutterer, Markus; Vollmann-Zwerenz, Arabel; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E.; Seliger, Corinna; Hau, Peter; Uhl, Martin; Walter, Lisa (Anticancer Research, 2016)
The combination of radiotherapy, temozolomide and valproic acid (VPA) has shown some promise in retrospective analyses of patients with glioblastoma, although their mechanisms of action remain unknown.We investigated the in vitro and in vivo effects of pretreating glioma cells with temozolomide and VPA as an immunization strategy to boost an adaptive immune response in a syngeneic mouse model.Temozolomide and VPA induced autophagy in GL261 glioma cells, and caused tumor antigen-specific T-cells to become activated effector T-cells. Mice with a pre-existing glioma showed no improvement in clinical outcome when immunized with temozolomide- and VPA-treated glioma cells.Although temozolomide and VPA treatment of glioma cells can boost the adaptive immune response, in the context of a vaccine therapy, additional factors are necessary to eradicate the tumor and improve survival.
EVALuna2:22525

A deep learning-based histopathology classifier for Focal Cortical Dysplasia - Vorndran, Jörg; Neuner, Christoph; Coras, Roland; Hoffmann, Lucas; Geffers, Simon; Honke, Jonas; Herms, Jochen; Roeber, Sigrun; Hamer, Hajo; Brandner, Sebastian; Hartlieb, Till; Pieper, Tom; et al. (Neural Computing & Applications, 2023)
A light microscopy-based histopathology diagnosis of human brain specimens obtained from epilepsy surgery remains the gold standard to confirm the underlying cause of a patient’s focal epilepsy and further inform postsurgical patient management. The differential diagnosis of neocortical specimens in the realm of epilepsy surgery remains, however, challenging. Herein, we developed an open access, deep learning-based classifier to histopathologically assess whole slide microscopy images (WSI) and to automatically recognize various subtypes of Focal Cortical Dysplasia (FCD), according to the ILAE consensus classification update of 2022. We trained a convolutional neuronal network (CNN) with fully digitalized WSI of hematoxylin–eosin stainings obtained from 125 patients covering the spectrum of mild malformation of cortical development (mMCD), mMCD with oligodendroglial hyperplasia in epilepsy (MOGHE), FCD ILAE Type 1a, 2a and 2b using 414 formalin-fixed and paraffin-embedded archival tissue blocks. An additional series of 198 postmortem tissue blocks from 59 patients without neurological disorders served as control to train the CNN for homotypic frontal, temporal and occipital areas and heterotypic Brodmann areas 4 and 17, entorhinal cortex and dentate gyrus. Special stains and immunohistochemical reactions were used to comprehensively annotate the region of interest. We then programmed a novel tile extraction pipeline and graphical dashboard to visualize all areas on the WSI recognized by the CNN. Our deep learning-based classifier is able to compute 1000 × 1000 µm large tiles and recognizes 25 anatomical regions and FCD categories with an accuracy of 98.8% (F1 score = 0.82). Microscopic review of regions predicted by the network confirmed these results. This deep learning-based classifier will be made available as online web application to support the differential histopathology diagnosis in neocortical human brain specimens obtained from epilepsy surgery. It will also serve as blueprint to build a digital histopathology slide suite addressing all major brain diseases encountered in patients with surgically amenable focal epilepsy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Classification; Convolutional neuronal network; Cortex; Deep learning; Digital pathology; Epilepsy; FCD1; FCD2; mMCD; MOGHE

Adherence to antiepileptic drugs in children and adolescents: A retrospective study in primary care settings in Germany - Jacob, Louis; Hamer, Hajo; Kostev, Karel (Epilepsy and Behavior, 2017)
The goal of this study was to analyze adherence to antiepileptic drugs (AED) in children and adolescents treated in pediatric practices in Germany.The present study included patients aged between 2 and 17years who were diagnosed with epilepsy (ICD-10: G40) and had received at least two prescriptions of AED between January 2006 and December 2015 in 243 pediatric practices in Germany. The medication possession ratio (MPR) was used to estimate adherence, and patients with a MPR greater than 80% were considered adherent. The impact of patient and drug characteristics on adherence was analyzed using a multivariate logistic regression model.A total of 5214 patients were included. Mean age was 10.9years (SD=4.9years). The overall MPR was 88.8% (SD=34.1%), and 68.9% of patients were considered adherent. Children aged 5years or younger were more adherent to AED than those aged between 14 and 17years (OR=1.22, 95% CI: 1.07-1.39). Individuals living in western Germany were also found to be more adherent than those living in eastern Germany (OR=1.71, 95% CI: 1.55-1.88). Asthma as a comorbidity (OR=1.59, 95% CI: 1.29-1.96) was positively and attention-deficit hyperactivity disorder (OR=0.81, 95% CI: 0.71-0.93) negatively associated with treatment adherence. Finally, no significant association was found between adherence and the type of AED.Two-thirds of children and adolescents suffering from epilepsy in Germany were adherent to AED. Age, place of residence, and comorbidities were significantly associated with adherence.
EVALuna2:22556

Adherence to oral anticoagulation in secondary stroke prevention - the first year of direct oral anticoagulants - Sauer, Rolf; Sauer, Eva-Maria; Bobinger, Tobias; Blinzler, Christian; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Patients with ischemic stroke caused by atrial fibrillation (AF) have a high risk of recurrence without adequate secondary prevention with oral anticoagulation (OAC). We investigated adherence to OAC in the first year after introduction of direct oral anticoagulants.In 284 appropriate patients, the rate of anticoagulation (AC) at discharge, adherence at 90 days and 1 year, changes between substances, and predictors for adherence to AC were analyzed. Functional outcome was assessed using the modified Rankin Scale score.AC was initiated in 70.3% of survivors before discharge. In these patients, only 8.6% and 9.9% discontinued AC after 90 days and 1 year, respectively. In 22.1%, AC was recommended but not started before discharge. Only 53.2% of them received AC at 90 days, increasing to 67.5% at 1 year. A total of 7.6% of patients were deemed unsuitable for AC, none of them subsequently received AC. Overall, 85.4% of patients suitable for AC were treated at 1-year follow-up. No independent predictors for withholding AC were identified. Switching of medication occurred in only a minority of patients within the first year.AC is feasible in more than 90% patients with acute ischemic stroke and AF. When initiated during the acute hospital stay, AC is discontinued in only a minority of patients. However, if AC is recommended but not started during initial hospitalization the rate of AC treatment at 90 days and 1 year is much lower. Therefore, AC should be initiated within the acute hospital stay whenever possible.
EVALuna2:22269

Adjunctive retigabine in refractory focal epilepsy: Postmarketing experience at four tertiary epilepsy care centers in Germany - Nass, R. D.; Kurth, C.; Kull, A.; Graf, Wolfgang; Kasper, Burkhard; Hamer, Hajo; Strzelczyk, Adam; Elger, C. E.; Steinhoff, B. J.; Surges, R.; Rosenow, F. (Epilepsy and Behavior, 2016)
Retigabine (RTG, ezogabine) is the first potassium channel-opening anticonvulsant drug approved for adjunctive treatment of focal epilepsies. We report on the postmarketing clinical efficacy, adverse events, and retention rates of RTG in adult patients with refractory focal epilepsy.Clinical features before and during RTG treatment were retrospectively collected from patients treated at four German epilepsy centers in 2011 and 2012.A total of 195 patients were included. Daily RTG doses ranged from 100 to 1500 mg. Retigabine reduced seizure frequency or severity for 24.6% and led to seizure-freedom in 2.1% of the patients but had no apparent effect in 43.1% of the patients. Seizure aggravation occurred in 14.9%. The one-, two-, and three-year retention rates amounted to 32.6%, 7.2%, and 5.7%, respectively. Adverse events were reported by 76% of the patients and were mostly CNS-related. Blue discolorations were noted in three long-term responders. Three possible SUDEP cases occurred during the observation period, equalling an incidence rate of about 20 per 1000 patient years.Our results are similar to other pivotal trials with respect to the long-term, open-label extensions and recent postmarketing studies. Despite the limitations of the retrospective design, our observational study suggests that RTG leads to good seizure control in a small number of patients with treatment-refractory seizures. However, because of the rather high percentage of patients who experienced significant adverse events, we consider RTG as a drug of reserve.
EVALuna2:22452

Advances in stroke pharmacology - Zhou, Zhenhua; Lu, Jianfei; Liu, Wen-Wu; Manaenko, Anatol; Hou, Xianhua; Mei, Qiyong; Huang, Jun-Long; Tang, Jiping; Zhang, John H.; Yao, Honghong; Hu, Qin (Pharmacology & Therapeutics, 2018)
Stroke occurs when a cerebral blood vessel is blocked or ruptured, and it is the major cause of death and adult disability worldwide. Various pharmacological agents have been developed for the treatment of stroke either through interrupting the molecular pathways leading to neuronal death or enhancing neuronal survival and regeneration. Except for rtPA, few of these agents have succeeded in clinical trials. Recently, with the understanding of the pathophysiological process of stroke, there is a resurrection of research on developing neuroprotective agents for stroke treatment, and novel molecular targets for neuroprotection and neurorestoration have been discovered to predict or offer clinical benefits. Here we review the latest major progress of pharmacological studies in stroke, especially in ischemic stroke; summarize emerging potential therapeutic mechanisms; and highlight recent clinical trials. The aim of this review is to provide a panorama of pharmacological interventions for stroke and bridge basic and translational research to guide the clinical management of stroke therapy.
EVALuna2:213463

Advantages of magnetoencephalography, neuronavigation and intraoperative MRI in epilepsy surgery re-operations - Shawarba, Julia; Kaspar, Burkhard; Rampp, Stefan; Winter, Fabian; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2021)
Objective: Management of patients after failed epilepsy surgery is still challenging. Advanced diagnostic and intraoperative tools including magneto-encephalography (MEG) as well as neuronavigation and intraoperative magnetic resonance imaging (iopMRI) may contribute to a better postoperative seizure outcome in this patient group. Methods: We retrospectively analyzed consecutive patients after reoperation of failed epilepsy surgery for medically refractory epilepsy at the University of Erlangen between 1988 and 2017. Inclusion criteria for patients were available MEG, neuronavigation and iopMRI data. The Engel scale was used to categorize seizure outcome. Results: We report on 27 consecutive patients (13 female/14 male mean age at first surgery 29.4 years) who had operative revision of the first resection after failed epilepsy surgery. An improved seizure outcome postoperatively was observed in 78% of patients (p < 0.001) with 55% seizure free (Engel I) patients after a mean follow-up time of 4.9 years. In detail, 80% of lesional cases were seizure free compared to 59% of MRI negative patients. Localizing MEG spike activity in the vicinity of the first resection cavity was present in 12 of 27 patients (44%) corresponding to 83% (10/12) of MEG localizing spike patients having advanced seizure outcome after operative revision. Conclusion: Re-operation after failed surgery in refractory epilepsy may lead to a better seizure outcome in the majority of patients. Preoperative MEG may support the decision for surgery and may facilitate targeting epileptogenic tissue for re-resection by employing navigation and iopMR imaging.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Failed epilepsy surgery; intraoperative MR imaging; MEG; neuronavigation; reoperation; seizure outcome

Adverse event grading following CTCAE v3.0 underestimates hypertensive side effects in patients with glioma treated with Bevacizumab - Bumes, Elisabeth; Rzonsa, Sarah; Hutterer, Markus; Proescholdt, Martin; Bogdahn, Ulrich; Riemenschneider, Markus J.; Uhl, Martin; Wendl, Christina; Hau, Peter (Journal of Neuro-Oncology, 2016)
Anti-VEGF therapy with Bevacizumab (BEV) is widely used in cases of relapsed high-grade glioma (HGG). Arterial hypertension is a known side effect of anti-VEGF therapy. 42 Patients with relapsed HGG were treated with BEV 10 mg/kg on days 1 and 15 of 28-day cycles in addition to treatment with 40 mg TMZ daily until disease progression, based on magnetic resonance imaging and/or worsening of clinical status. In a retrospective analysis, hypertensive side effects were evaluated as the primary endpoint, while survival information in addition to toxicity was analyzed as secondary endpoint. Grading which employs the Common Terminology Criteria for Adverse Events (CTCAE) version 4.0 detected hypertensive events with a significantly higher sensitivity than CTCAE version 3.0. The rate of severe hypertensive events observed as CTCAE >= °3 were 9.5 % in version 3.0 and 45.2 % in version 4.0. The results presented here indicate that CTCAE version 3.0 may underreport the incidence and grade of BEV-induced hypertension within clinical trials. As hypertension has not only long-term, but also severe short-term side effects, we suggest that arterial hypertension under BEV should be scored according to CTCAE version 4.0 to avoid clinically relevant hypertension-related adverse events in these patients.
EVALuna2:22526

A Frameless Stereotactic Implantation Technique for Depth Electrodes in Refractory Epilepsy Using Intraoperative Magnetic Resonance Imaging - Roessler, Karl; Sommer, Bjoern; Merkel, Andreas; Rampp, Stefan; Gollwitzer, Stephanie; Hamer, Hajo; Buchfelder, Michael (World Neurosurgery, 2016)
Various complex techniques for depth electrode insertion in refractory epilepsy using preoperative imaging have been investigated. We evaluated a simple, accurate, cost-effective, and timesaving method using intraoperative magnetic resonance imaging (MRI).A neuronavigation-guided insertion tube attached to bone facilitated the placement of stereotactic percutaneous drill holes, bolt implantation, and frameless stereotactic insertion of depth electrodes. Image registration was carried out by head coil fiducials with trajectory planning and intraoperative electrode correction.In 6 patients with refractory epilepsy (3 women and 3 men; mean age, 30.0 years; range, 20-37 years), 58 depth electrodes (9-11 per patient) were placed. The mean length of the inserted electrodes was 37.3 mm ± 8.8 (mean ± SD) (range, 22.1-84.4 mm). The overall target point accuracy was 3.2 mm ± 2.2 (range, 0-8.6 mm), which was significantly different from the overall entry point accuracy of 1.4 mm ± 1.2 (P < 0.0001). All electrodes functioned perfectly, enabling high-quality stereo-electroencephalography recordings over a period of 7.3 days ± 0.5 (range, 7-8 days). The mean implantation time for 9-11 electrodes per patient was 115 minutes ± 36.3 (range, 75-160 minutes; 12 minutes for 1 electrode on average) including the intraoperative MRI (T1 three-dimensional magnetization-prepared rapid acquisition gradient echo, T2, and diffusion tensor imaging). There was no hemorrhage, infection, or neurologic deficit related to the procedure.Our frameless technique of depth electrode insertion using intraoperative MRI guidance is an accurate, reliable, cost-effective, and timesaving method for stereo-electroencephalography.
EVALuna2:22491

Afterdischarges elicited by cortical electric stimulation in humans: When do they occur and what do they mean? - Gollwitzer, Stephanie; Hopfengaertner, Ruediger; Roessler, Karl; Müller, Tamara; Olmes, David Gerhard; Lang, Johannes; Koehn, Julia; Onugoren, Muejgan Dogan; Heyne, Jana; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2018)
INTRODUCTION: Afterdischarges (ADs) are a common and unwanted byproduct of direct cortical stimulation during invasive electroencephalography (EEG) recordings. Brief pulse stimulation (BPS) can sometimes terminate ADs. This study investigated AD characteristics and their relevance for emergence of stimulation seizures. In addition, AD response to BPS was analyzed. MATERIAL AND METHODS: Invasive EEG recordings including mapping with direct cortical stimulation in patients with refractory epilepsy at the Erlangen Epilepsy Center were retrospectively reviewed. Afterdischarge defined as stimulation-induced rhythmic epileptiform discharges of more than a two-second duration were analyzed regarding incidence, localization, duration, propagation pattern, morphology, and seizure emergence. In addition, the influence of AD characteristics and stimulation settings on BPS success rate was studied. RESULTS: A number of 4261 stimulation trials in 20 patients were investigated. Afterdischarge occurred in 518 trials (14.2%) and lasted 12.4 s (standard deviation [SD]: 8.6 s) on average. We elicited ADs in the seizure onset zone (SOZ) (n = 64; 19.4%), the irritative zone (n = 105, 20.0%), and outside the irritative area (n = 222, 12.5%). Rhythmic spikes (30.5%) and spike-wave complexes (30.3%) represented predominant morphologies. Afterdischarge morphology in the SOZ and hippocampus differed from other areas with polyspikes and sequential spikes being the most common types there (p = 0.0005; p < 0.0001 respectively). Hippocampal ADs were particularly frequent (n = 50, 38.2%) and long-lasting (mean: 16.6, SD: 8.3 s). Brief pulse stimulation was applied in 18.1% of the AD trials (n = 94) and was successful in 37.4% (n = 40). Success rates were highest when BPS was delivered within 9.5 s (p = 0.0048) and in ADs of spike-wave morphology (p = 0.0004). Fifteen clinical seizures emerged from ADs (3.55%), mostly evolving from sequential spikes. Afterdischarges in patients with stimulation seizures appeared more widespread (p < 0.0001) and lasted longer (mean duration 7.0 s) than in those without (mean duration 21.0 s, p = 0.0054). CONCLUSION: Afterdischarges appear in the epileptogenic and nonepileptogenic cortex. Duration and propagation patterns can help to quantify the risk of stimulation seizures, with sequential spikes being most susceptible to seizure elucidation. The hippocampus is highly sensitive to AD release. Brief pulse stimulation is a safe and efficacious way to terminate ADs, especially when delivered quickly after AD onset.
EVALuna2:34938

Age-dependent clinical outcomes in primary versus oral anticoagulation-related intracerebral hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan T.; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Bobinger, Tobias; Müller, Tamara; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Huttner, Hagen (International Journal of Stroke, 2019)
Aims This study determined the influence of age on bleeding characteristics and clinical outcomes in primary spontaneous (non-OAC), vitamin K antagonist-related (VKA-) and non-vitamin K antagonist oral anticoagulant-related (NOAC-) ICH. Methods Pooled individual patient data of multicenter cohort studies were analyzed by logistic regression modelling and propensity-score-matching (PSM) to explore the influence of advanced age on clinical outcomes among non-OAC-, VKA-, and NOAC-ICH. Primary outcome measure was functional outcome at three months assessed by the modified Rankin Scale, dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6) functional outcome. Secondary outcome measures included mortality, hematoma characteristics, and frequency of invasive interventions. Results In VKA-ICH 33.5% (670/2001), in NOAC-ICH 44.2% (69/156) and in non-OAC-ICH 25.2% (254/1009) of the patients were >= 80 years. After adjustment for treatment interventions and relevant parameters, elderly ICH patients comprised worse functional outcome at three months (adjusted odds ratio (aOR) in VKA-ICH: 1.49 (1.21-1.84); p < 0.001; NOAC-ICH: 2.01 (0.95-4.26); p = 0.069; non-OAC-ICH: 3.54 (2.50-5.03); p < 0.001). Anticoagulation was significantly associated with worse functional outcome below the age of 70 years, (aOR: 2.38 (1.78-3.16); p < 0.001), but not in patients of >= 70 years (aOR: 1.21 (0.89-1.65); p = 0.217). The differences in initial ICH volume and extent of ICH enlargement between OAC-ICH and non-OAC-ICH gradually decreased with increasing patient age. Conclusions As compared to elderly ICH-patients, in patients <70 years OAC-ICH showed worse clinical outcomes compared to non-OAC-ICH because of larger baseline ICH-volumes and extent of hematoma enlargement. Treatment strategies aiming at neutralizing altered coagulation should be aware of these findings.
CRIS-Team WoS Importer:2020-01-28

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

A guideline for head volume conductor modeling in EEG and MEG - Vorwerk, Johannes; Cho, Jae-Hyun; Rampp, Stefan; Hamer, Hajo; Knoesche, Thomas R.; Wolters, Carsten H. (NeuroImage, 2014)
For accurate EEG/MEG source analysis it is necessary to model the head volume conductor as realistic as possible. This includes the distinction of the different conductive compartments in the human head. In this study, we investigated the influence of modeling/not modeling the conductive compartments skull spongiosa, skull compacta, cerebrospinal fluid (CSF), gray matter, and white matter and of the inclusion of white matter anisotropy on the EEG/MEG forward solution. Therefore, we created a highly realistic 6-compartment head model with white matter anisotropy and used a state-of-the-art finite element approach. Starting from a 3-compartment scenario (skin, skull, and brain), we subsequently refined our head model by distinguishing one further of the above-mentioned compartments. For each of the generated five head models, we measured the effect on the signal topography and signal magnitude both in relation to a highly resolved reference model and to the model generated in the previous refinement step. We evaluated the results of these simulations using a variety of visualization methods, allowing us to gain a general overview of effect strength, of the most important source parameters triggering these effects, and of the most affected brain regions. Thereby, starting from the 3-compartment approach, we identified the most important additional refinement steps in head volume conductor modeling. We were able to show that the inclusion of the highly conductive CSF compartment, whose conductivity value is well known, has the strongest influence on both signal topography and magnitude in both modalities. We found the effect of gray/white matter distinction to be nearly as big as that of the CSF inclusion, and for both of these steps we identified a clear pattern in the spatial distribution of effects. In comparison to these two steps, the introduction of white matter anisotropy led to a clearly weaker, but still strong, effect. Finally, the distinction between skull spongiosa and compacta caused the weakest effects in both modalities when using an optimized conductivity value for the homogenized compartment. We conclude that it is highly recommendable to include the CSF and distinguish between gray and white matter in head volume conductor modeling. Especially for the MEG, the modeling of skull spongiosa and compacta might be neglected due to the weak effects; the simplification of not modeling white matter anisotropy is admissible considering the complexity and current limitations of the underlying modeling approach.
EVALuna2:22293

Alemtuzumab as rescue therapy in a cohort of 50 relapsing-remitting MS patients with breakthrough disease on fingolimod: a multi-center observational study - Huhn, Konstantin; Bayas, Antonios; Doerck, Sebastian; Frank, Benedikt; Gerbershagen, Kathrin; Hellwig, Kerstin; Kallmann, Boris; Kleinschnitz, Christoph; Kleiter, Ingo; Lee, De-Hyung; Limmroth, Volker; Maeurer, Mathias; et al. (Journal of Neurology, 2018)
BACKGROUND: Relapsing-remitting multiple sclerosis (RRMS) requires efficient immunomodulatory treatment to reach "no evidence of disease activity" status at best. Alemtuzumab and fingolimod have proved to be efficient options in RRMS with active disease course. Yet, side effects and break-through disease may limit long-time treatment and necessitate switch of medication. Data on efficacy and safety of alemtuzumab following fingolimod treatment are limited, but useful for clinical practice. METHODS: Clinical and MRI data of 50 RRMS patients with a history of therapy switch from fingolimod to alemtuzumab were retrospectively analyzed. Data were acquired from nine large German MS Centers from 2013 to 2016 and analyzed using descriptive statistics. RESULTS: On average, patients with disease duration of 12.9 years and median EDSS of 3.0 at baseline switched to alemtuzumab after 68 weeks of fingolimod treatment. Thereafter, patients on alemtuzumab were followed for a mean of 64 weeks. The annualized relapse rate decreased from 2.2 in the year prior to 0.34 in the following year after switching to alemtuzumab and EDSS stabilized. In a subgroup of patients (n = 23), MRI data point to a reduction in enhancing (4.47 vs. 0.26) and new/enlarging T2 lesions (5.8 vs. 0.27) after treatment adjustment. Side effects were generally as expected from published data for alemtuzumab (autoimmunity 2/50, severe infections 1/50). One patient suffered combined lethal necrotizing leukoencephalopathy and hemolytic anemia. DISCUSSION: Therapy switch was highly effective in reducing clinical and MRI surrogates of disease activity and was mainly well tolerated within one year of follow-up. Hence, alemtuzumab constitutes a promising therapy in RRMS with refractory disease activity despite fingolimod treatment. Further studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.
EVALuna2:36319

ALLERGIC ASTHMA INDUCES THE ACCUMULATION OF SYNOVIAL RESIDENT EOSINOPHILS, TRIGGERING THE RESOLUTION OF INFLAMMATORY ARTHRITIS - Liu, Mao; Andreev, D.; Kachler, K.; Koelle, J.; Rauber, S.; Ramming, Andreas; Finotto, Susetta; Schett, G.; Bozec, A. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

alpha-Synuclein: a Modulator During Inflammatory CNS Demyelination - Kuhbandner, Kristina; Hoffmann, Alana; Alvarado, Maria Nazareth; Seyler, Lisa; Bäuerle, Tobias; Winkler, Jürgen; Linker, Ralf (Journal of Molecular Neuroscience, 2020)
Neuroinflammation and demyelination are hallmarks of several neurological disorders such as multiple sclerosis and multiple system atrophy. To better understand the underlying mechanisms of de- and regeneration in respective diseases, it is critical to identify factors modulating these processes. One candidate factor is alpha-Synuclein (aSyn), which is known to be involved in the pathology of various neurodegenerative diseases. Recently, we have shown that aSyn is involved in the modulation of peripheral immune responses during acute neuroinflammatory processes. In the present study, the effect of aSyn deficiency on de- and regenerative events in the CNS was analyzed by using two different demyelinating animal models: chronic MOG(35-55)-induced experimental autoimmune encephalomyelitis (EAE) and the cuprizone model. Histopathological analysis of spinal cord cross sections 8 weeks after EAE induction revealed a significant reduction of CNS inflammation accompanied by decreased myelin loss during late-stage inflammatory demyelination in aSyn-deficient mice. In contrast, after cuprizone-induced demyelination or remyelination following withdrawal of cuprizone, myelination and neuroinflammatory patterns were not affected by aSyn deficiency. These data provide further evidence for aSyn as regulator of peripheral immune responses under neuroinflammatory conditions, thereby also modulating degenerative events in late-stage demyelinating disease.
CRIS-Team WoS Importer:2020-04-07

Alterations of intracerebral connectivity in epilepsy patients with secondary bilateral synchrony - Hammen, T.; Reisert, M.; Juschkat, W.; Egger, K.; Urbach, H.; Zentner, J.; Beck, J.; Hamer, Hajo; Steinhoff, B. J.; Baumgartner, C.; Schulze-Bonhage, A.; Puhahn-Schmeiser, B. (Epilepsy Research, 2020)
Introduction: The aim of our study was to evaluate intracerebral network changes in epilepsy patients demonstrating secondary bilateral synchrony (SBS) in EEG by applying a new Diffusion Tensor Imaging (DTI) method using an energy-based global tracking algorithm. Materials and methods: 10 MRI negative epilepsy patients demonstrating SBS in 10–20 surface EEG were included. EEG findings were analyzed for irritative zones characterized by focal interictal epileptiform discharges (IEDs) triggering SBS. In addition, DTI including an energy-based global tracking algorithm was applied to analyze fiber tract alterations in irritative zones. To measure the deviation of a certain cortical connection in comparison to healthy controls, normalized differences of fiber tract streamline counts (SC) and their p-values were evaluated in comparison to corresponding fibers of the control group. Results: In 6 patients the irritative zone initiating SBS was located in the frontal lobe, in 3 patients in the temporal lobe and in 1 patient in the region surrounding the right central sulcus. All patients demonstrated significantly altered SC in brain lobes where the irritative zone triggering SBS was located (p ≤ 0.05). Seven out of 10 patients demonstrated SC alterations in tracts connecting brain lobes between the ipsilateral and the contralateral hemisphere (p ≤ 0.05). Conclusion: Our data demonstrate that alterations in fiber tracts in irritative zones triggering SBS are not necessarily associated with intracerebral lesions visible in high resolution MRI. Our study gives evidence that diffusion tensor imaging is a promising non-invasive additive tool for intracerebral network analyses even in MRI-negative epilepsy patients.
CRIS-Team Scopus Importer:2020-08-07
Keywords: contralateral propagation; diffusion tensor imaging; epilepsy patients; fiber tracts; intracerebral network changes; irritative zone; MRI negative; secondary bilateral synchrony; streamline counts

Altered autonomic responses to happy and fearful music in patients with a history of mild traumatic brain injury - Hilz, Max-Josef; Wang, Ruihao; Hoesl, K. M.; Muresanu, D. F.; Liu, M. (JOURNAL OF THE NEUROLOGICAL SCIENCES, 2019)
CRIS-Team WoS Importer:2020-03-24

Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury - Ruehl, Lena; Kuramatsu, Joji; Sembill, Jochen; Kallmünzer, Bernd; Madzar, Dominik; Gerner, Stefan; Giede-Jeppe, Antje; Balk, Stefanie; Müller, Tamara; Jäger, Jakob; Schwab, Stefan; Huttner, Hagen; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective This study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury. Methods We pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated >= 7 days. Patient selection and multivariable regression modelling were used to adjust for differences in intergroup comparison and for parameters associated with consciousness. Improvement of consciousness 5 days after treatment initiation was defined as primary outcome. Secondary outcomes included Glasgow Coma Scale (GCS) at day 5 and GCS at day 10, rate of ICU delirium, epileptic seizures and all-cause mortality at 90 days. Results Overall, 84 of 294 (28.6%) eligible patients received amantadine. Amantadine treatment was associated with improvement of consciousness at day 5 (amantadine: 86.9% vs control: 54.0%; absolute difference: 32.9 (20.0-44.2); adjusted OR (aOR): 5.71 (2.50-13.05), p<0.001). Secondary outcomes showed differences in GCS 5 days (9 (8-11) vs 6 (3-9), p<0.001) and GCS 10 days (10(8-11) vs 9(6-11),p=0.003) after treatment initiation. There were no significant differences regarding all-cause mortality (aOR: 0.89 (0.44-1.82), p=0.758) and ICU delirium (aOR: 1.39 (0.58-3.31), p=0.462). Rate of epileptic seizures after initiation of amantadine treatment was numerically higher in the amantadine group (amantadine: 10.7% vs control: 3.0%; absolute difference: 7.7 (0.3-16.4); aOR: 3.68 (0.86-15.71), p=0.079). Conclusions Amantadine treatment is associated with improved consciousness among patients with different types of non-traumatic brain injury in this observational cohort analysis. Epileptic seizures should be considered as potential side effects and randomised controlled trials are needed to confirm these findings.
CRIS-Team WoS Importer:2022-02-11

A multicenter, matched case-control analysis comparing burden-of-illness in Dravet syndrome to refractory epilepsy and seizure remission in patients and caregivers in Germany - Strzelczyk, Adam; Schubert-Bast, Susanne; Bast, Thomas; Bettendorf, Ulrich; Fiedler, Barbara; Hamer, Hajo; Herting, Arne; Kalski, Malin; Kay, Lara; Kieslich, Matthias; Klein, Karl Martin; Kluger, Gerhard; et al. (Epilepsia, 2019)
Objective: To compare direct and indirect costs and quality of life (QoL) of pediatric and adult patients with Dravet syndrome (DS), with drug-resistant epilepsy (DRE) and in seizure remission (SR), and their caregivers, in Germany. Methods: Questionnaire responses from 93 DS patients and their caregivers were matched by age and gender with responses from 93 DRE and 93 SR patients collected in independent studies, and were compared across main components of QoL, direct costs (patient visits, medication use, care level, medical equipment, and ancillary treatments), and indirect costs (quitting job, reduced working hours, missed days). Results: Mean total direct costs were highest for DS patients (€4864 [median €3564] vs €3049 [median €1506] for DRE [excluding outliers], P = 0.01; and €1007 [median €311], P < 0.001 for SR). Total lost productivity over 3 months was highest among caregivers of pediatric DS (€4757, median €2841), compared with those of DRE (€1541, P < 0.001; median €0) and SR patients (€891, P < 0.001; median €0). The proportions of caregivers in employment were similar across groups (62% DS, 63% DRE, and 63% SR) but DS caregivers were more likely to experience changes to their working situation, such as quitting their job (40% DS vs 16% DRE and 9% SR, P < 0.001 in both comparisons). KINDL scores were significantly lower for DS patients (62 vs 74 and 72, P < 0.001 in both comparisons), and lower than for the average German population (77). Pediatric caregiver EQ-5D scores across all cohorts were comparable with population norms, but more DS caregivers experienced moderate to severe depressive symptoms (24% vs 11% and 5%). Mean Beck Depression Inventory (BDI-II) score was significantly higher in DS caregivers than either of the other groups (P < 0.001). Significance: This first comparative study of Dravet syndrome to difficult-to-treat epilepsy and to epilepsy patients in seizure remission emphasizes the excess burden of DS in components of QoL and direct costs. The caregivers of DS patients have a greater impairment of their working lives (indirect costs) and increased depression symptoms.
CRIS-Team Scopus Importer:2019-07-09
Keywords: costs; depression; encephalopathy; quality of life; Severe myoclonic epilepsy of infants

A multicenter survey of clinical experiences with perampanel in real life in Germany and Austria - Steinhoff, Bernhard J.; Hamer, Hajo; Trinka, Eugen; Schulze-Bonhage, Andreas; Bien, Christian; Mayer, Thomas; Baumgartner, Christoph; Lerche, Holger; Noachtar, Soheyl (Epilepsy Research, 2014)
Perampanel (PER) has been approved by the European Medicines Agency (EMA) for adjunctive treatment of patients with partial-onset seizures from age 12 years on. It has been introduced to the market in Germany and Austria in 2012. This cross-sectional observational study summarizes the clinical experience of nine centers with adjunctive PER. Patients were consecutively followed from the initiation of PER on. Only patients with a minimum observational period of six months (in case of ongoing treatment) were recruited. Efficacy data reflect the preceding three months at last observation, tolerability data were assessed at the last observation carried forward. 281 patients were included. After six months 169 were still on PER so that a retention rate of 60% resulted. 43 patients were seizure-free for the preceding 3 months (15%). Overall incidence of adverse events was 52.0%. The leading adverse events were somnolence (24.6%) and dizziness (19.6%) followed by ataxia (3.9%), aggression (2.8%), nausea (2.5%) and irritability (2.1%). We conclude that adjunctive PER may lead to at least temporary freedom of seizures in some of these highly difficult-to-treat patients. Adverse events are not uncommon.
EVALuna2:22306

Analysis of CD4+ CD8+ double-positive T cells in blood, cerebrospinal fluid and multiple sclerosis lesions - Waschbisch, Anne; Sammet, Laura; Schröder, S.; Lee, D. -H.; Barrantes-Freer, A.; Stadelmann, C.; Linker, Ralf (Clinical and Experimental Immunology, 2014)
T cells with a CD4(+) CD8(+) double-positive (DP) phenotype are present in small numbers in the peripheral blood of healthy humans and may have anti-viral capacities. Here we investigate numbers and function of DP T cells in patients with relapsing-remitting multiple sclerosis (MS), either treatment-naive or under therapy with natalizumab. Flow cytometry analysis revealed that frequencies of circulating DP T cells in treatment-naive and natalizumab-treated MS patients are comparable to healthy controls. These cells have a memory phenotype with cytotoxic potential, express high levels of CD49d and are similarly functional in treatment-naive as well as natalizumab-treated MS patients. DP T cells were enriched in the cerebrospinal fluid, but do not invade acutely inflamed MS lesions. In conclusion, DP T cells are functional in MS and may play a role in the immune surveillance of the central nervous system, but do not display functional impairment under natalizumab therapy.
EVALuna2:22346

Anaplastic astrocytoma with piloid features, a novel molecular class of IDH wildtype glioma with recurrent MAPK pathway, CDKN2A/B and ATRX alterations - Reinhardt, Annekathrin; Stichel, Damian; Schrimpf, Daniel; Sahm, Felix; Korshunov, Andrey; Reuss, David E.; Koelsche, Christian; Huang, Kristin; Wefers, Annika K.; Hovestadt, Volker; Sill, Martin; Gramatzki, Dorothee; et al. (Acta Neuropathologica, 2018)
Tumors with histological features of pilocytic astrocytoma (PA), but with increased mitotic activity and additional high-grade features (particularly microvascular proliferation and palisading necrosis) have often been designated anaplastic pilocytic astrocytomas. The status of these tumors as a separate entity has not yet been conclusively demonstrated and molecular features have only been partially characterized. We performed DNA methylation profiling of 102 histologically defined anaplastic pilocytic astrocytomas. T-distributed stochastic neighbor-embedding (t-SNE) and hierarchical clustering analysis of these 102 cases against 158 reference cases from 12 glioma reference classes revealed that a subset of 83 of these tumors share a common DNA methylation profile that is distinct from the reference classes. These 83 tumors were thus denominated DNA methylation class anaplastic astrocytoma with piloid features (MC AAP). The 19 remaining tumors were distributed amongst the reference classes, with additional testing confirming the molecular diagnosis in most cases. Median age of patients with MC AAP was 41.5 years. The most frequent localization was the posterior fossa (74%). Deletions of CDKN2A/B (66/83, 80%), MAPK pathway gene alterations (49/65, 75%, most frequently affecting NF1, followed by BRAF and FGFR1) and mutations of ATRX or loss of ATRX expression (33/74, 45%) were the most common molecular alterations. All tumors were IDH1/2 wildtype. The MGMT promoter was methylated in 38/83 tumors (45%). Outcome analysis confirmed an unfavorable clinical course in comparison to PA, but better than IDH wildtype glioblastoma. In conclusion, we show that a subset of histologically defined anaplastic pilocytic astrocytomas forms a separate DNA methylation cluster, harbors recurrent alterations in MAPK pathway genes in combination with alterations of CDKN2A/B and ATRX, affects patients who are on average older than those diagnosed with PA and has an intermediate clinical outcome.
EVALuna2:34582

ANDEXANET ALFA VERSUS USUAL CARE IN PATIENTS WITH DOAC ASSOCIATED INTRACEREBRAL HEMORRHAGE: A PROPENSITY-SCORE BASED HISTORICAL COMPARISON OF PATIENTS FROM ANNEXA4 AND RETRACEII - Huttner, Hagen; Gerner, Stefan; Connolly, S.; Middeldorp, S.; Milling, T.; Beyer-Westendorf, J.; Altevers, J.; Andersohn, F.; Yue, P.; Stross, L.; Schwab, Stefan (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous

Angiographic CT with intravenous contrast injection compared with conventional rotational angiography in the diagnostic work-up of cerebral aneurysms - Gölitz, Philipp; Struffert, Tobias; Knossalla, F.; Saake, Marc; Ott, Sabine; Ganslandt, Oliver; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Noninvasive imaging of cerebral aneurysms is still considered inferior to conventional angiography. The purpose of this study was to evaluate the diagnostic accuracy of ivACT in the assessment of intracranial aneurysms compared with 3D-DSA. MATERIALS AND METHODS: We included 13 patients with 15 incidental unruptured saccular aneurysms scheduled for diagnostic angiographic work-up in our study. In each patient, we performed an ivACT and a conventional angiography including a 3D rotational run. During postprocessing, MPR images were generated for each technique. Maximal aneurysm diameter, neck diameter, aneurysm height, maximum width, bulge height, parent artery diameter, and angle between the parent artery and aneurysm apex were measured for each aneurysm. RESULTS: 3D-DSA and ivACT both provided images of high quality without artificial disturbances (ie, motion artifacts). Measurements of all parameters resulted in comparable values for both modalities with a strong correlation (P ≤ .001). CONCLUSIONS: ivACT is feasible for the noninvasive visualization of saccular cerebral aneurysms and may provide reliable diagnostic information for the assessment of aneurysm size and geometry comparable with conventional intra-arterial 3D rotational angiography. These preliminary results might be a first promising step to replacing conventional angiography in preinterventional aneurysm imaging.
CRIS-Team Scopus Importer:2022-08-05

Angiotensin IV is induced in experimental autoimmune encephalomyelitis but fails to influence the disease - Manzel, Arndt; Domenig, Oliver; Ambrosius, Bjoern; Kovacs, Agnes; Stegbauer, Johannes; Poglitsch, Marko; Mueller, Dominik N.; Gold, Ralf; Linker, Ralf (Journal of Neuroimmune Pharmacology, 2014)
In multiple sclerosis (MS) and its corresponding animal models, over-activity of the renin-angiotensin system (RAS) has been reported and pharmacological RAS blockade exerts beneficial effects. The RAS generates a number of bioactive angiotensins, thereby primarily regulating the body's sodium homeostasis and blood pressure. In this regard, angiotensin IV (AngIV), a metabolite of the RAS has been shown to modulate inflammatory responses. Here we studied potential implications of AngIV signalling in myelin oligodendrocyte glycoprotein (MOG) peptide induced murine experimental autoimmune encephalomyelitis (EAE), a close-to-MS animal model. Mass spectrometry revealed elevated plasma levels of AngIV in EAE. Expression of cognate AT4 receptors was detected in macrophages and T cells as major drivers of pathology in EAE. Yet, AngIV did not modulate macrophage or T cell functions in vitro or displayed detectable effects on neuroantigen specific immune responses in vivo. The data argue against a major contribution of AngIV signalling in the immunopathogenesis of MOG-EAE.
EVALuna2:22281

Antagonizing dabigatran by idarucizumab in cases of ischemic stroke or intracranial hemorrhage in Germany—Updated series of 120 cases - Kermer, Pawel; Eschenfelder, Christoph C.; Diener, Hans Christoph; Grond, Martin; Abdalla, Yasser; Abraham, Alexej; Althaus, Katharina; Becks, Gebhard; Berrouschot, Jörg; Berthel, Jörg; Bode, Felix J.; Burghaus, Lothar; et al. (International Journal of Stroke, 2020)
Background: Idarucizumab is a monoclonal antibody fragment with high affinity for dabigatran reversing its anticoagulant effects within minutes. Thereby, patients with acute ischemic stroke who are on dabigatran treatment may become eligible for thrombolysis with recombinant tissue-type plasminogen activator (rt-PA). In patients on dabigatran with intracerebral hemorrhage idarucizumab could prevent lesion growth. Aims: To provide insights into the clinical use of idarucizumab in patients under effective dabigatran anticoagulation presenting with signs of acute ischemic stroke or intracranial hemorrhage. Methods: Retrospective data collected from German neurological/neurosurgical departments administering idarucizumab following product launch from January 2016 to August 2018 were used. Results: One-hundred and twenty stroke patients received idarucizumab in 61 stroke centers. Eighty patients treated with dabigatran presented with ischemic stroke and 40 patients suffered intracranial bleeding (intracerebral hemorrhage (ICH) in n = 27). In patients receiving intravenous thrombolysis with rt-PA following idarucizumab, 78% showed a median improvement of 7 points in National Institutes of Health Stroke Scale. No bleeding complications were reported. Hematoma growth was observed in 3 out of 27 patients with ICH. Outcome was favorable with a median National Institutes of Health Stroke Scale improvement of 4 points and modified Rankin score 0–3 in 61%. Six out of 40 individuals (15%) with intracranial bleeding died during hospital stay. Conclusion: Administration of rt-PA after reversal of dabigatran activity with idarucizumab in case of acute ischemic stroke seems feasible, effective, and safe. In dabigatran-associated intracranial hemorrhage, idarucizumab appears to prevent hematoma growth and to improve outcome.
CRIS-Team Scopus Importer:2020-02-04
Keywords: dabigatran; Idarucizumab; intracranial hemorrhage; ischemic stroke; outcome; thrombolysis

Anticoagulant reversal, blood pressure levels, and anticoagulant resumption in patients with anticoagulation-related intracerebral hemorrhage - Kuramatsu, Joji; Gerner, Stefan; Schellinger, Peter D.; Glahn, Joerg; Endres, Matthias; Sobesky, Jan; Flechsenhar, Julia; Neugebauer, Hermann; Juettler, Eric; Grau, Armin; Palm, Frederick; Roether, Joachim; et al. (Journal of the American Medical Association, 2015)
Although use of oral anticoagulants (OACs) is increasing, there is a substantial lack of data on how to treat OAC-associated intracerebral hemorrhage (ICH).To assess the association of anticoagulation reversal and blood pressure (BP) with hematoma enlargement and the effects of OAC resumption.Retrospective cohort study at 19 German tertiary care centers (2006-2012) including 1176 individuals for analysis of long-term functional outcome, 853 for analysis of hematoma enlargement, and 719 for analysis of OAC resumption.Reversal of anticoagulation during acute phase, systolic BP at 4 hours, and reinitiation of OAC for long-term treatment.Frequency of hematoma enlargement in relation to international normalized ratio (INR) and BP. Incidence analysis of ischemic and hemorrhagic events with or without OAC resumption. Factors associated with favorable (modified Rankin Scale score, 0-3) vs unfavorable functional outcome.Hemorrhage enlargement occurred in 307 of 853 patients (36.0%). Reduced rates of hematoma enlargement were associated with reversal of INR levels <1.3 within 4 hours after admission (43/217 [19.8%]) vs INR of >=1.3 (264/636 [41.5%]; P < .001) and systolic BP <160 mm Hg at 4 hours (167/504 [33.1%]) vs >=160 mm Hg (98/187 [52.4%]; P < .001). The combination of INR reversal <1.3 within 4 hours and systolic BP of <160 mm Hg at 4 hours was associated with lower rates of hematoma enlargement (35/193 [18.1%] vs 220/498 [44.2%] not achieving these values; OR, 0.28; 95% CI, 0.19-0.42; P < .001) and lower rates of in-hospital mortality (26/193 [13.5%] vs 103/498 [20.7%]; OR, 0.60; 95% CI, 0.37-0.95; P = .03). OAC was resumed in 172 of 719 survivors (23.9%). OAC resumption showed fewer ischemic complications (OAC: 9/172 [5.2%] vs no OAC: 82/547 [15.0%]; P < .001) and not significantly different hemorrhagic complications (OAC: 14/172 [8.1%] vs no OAC: 36/547 [6.6%]; P = .48). Propensity-matched survival analysis in patients with atrial fibrillation who restarted OAC showed a decreased HR of 0.258 (95% CI, 0.125-0.534; P < .001) for long-term mortality. Functional long-term outcome was unfavorable in 786 of 1083 patients (72.6%).Among patients with OAC-associated ICH, reversal of INR <1.3 within 4 hours and systolic BP <160 mm Hg at 4 hours were associated with lower rates of hematoma enlargement, and resumption of OAC therapy was associated with lower risk of ischemic events. These findings require replication and assessment in prospective studies.clinicaltrials.gov Identifier: NCT01829581.
EVALuna2:22354

Antiplatelet Therapy in Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Antiplatelet Therapy in Primary Spontaneous and Oral Anticoagulation-Associated Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Stroke, 2018)
Background and Purpose- This study determined the influence of concomitant antiplatelet therapy (APT) on hematoma characteristics and outcome in primary spontaneous intracerebral hemorrhage (ICH), vitamin K antagonist (VKA)- and non-VKA oral anticoagulant-associated ICH. Methods- Data of retrospective cohort studies and a prospective single-center study were pooled. Functional outcome, mortality, and radiological characteristics were defined as primary and secondary outcomes. Propensity score matching and logistic regression analyses were performed to determine the association between single or dual APT and hematoma volume. Results- A total of 3580 patients with ICH were screened, of whom 3545 with information on APT were analyzed. Three hundred forty-six (32.4%) patients in primary spontaneous ICH, 260 (11.4%) in VKA-ICH, and 30 (16.0%) in non-VKA oral anticoagulant-associated ICH were on APT, and these patients had more severe comorbidities. After propensity score matching VKA-ICH patients on APT presented with less favorable functional outcome (modified Rankin Scale score, 0-3; APT, 48/202 [23.8%] versus no APT, 187/587 [31.9%]; P=0.030) and higher mortality (APT, 103/202 [51.0%] versus no APT, 237/587 [40.4%]; P=0.009), whereas no significant differences were present in primary spontaneous ICH and non-VKA oral anticoagulant-associated ICH. In VKA-ICH, hematoma volume was significantly larger in patients with APT (21.9 [7.4-61.4] versus 15.7 [5.7-44.5] mL; P=0.005). Multivariable regression analysis revealed an association of APT and larger ICH volumes (odds ratio, 1.80 [1.20-2.70]; P=0.005), which was more pronounced in dual APT and supratherapeutically anticoagulated patients. Conclusions- APT does not affect ICH characteristics and outcome in primary spontaneous ICH patients; however, it is associated with larger ICH volume and worse functional outcome in VKA-ICH, presumably by additive antihemostatic effects. Combination of anticoagulation and APT should, therefore, be diligently evaluated and restricted to the shortest possible time frame.
EVALuna2:34909

Anti-SARS-CoV-2 vaccination immune response in MS patients: interim results of a multicentre, prospective cohort study - Berthele, A.; Goedel, C.; Kallmann, B.; Kowarik, M.; Lehmann-Horn, K.; Marziniak, M.; Meyer, C.; Rauer, S.; Rothhammer, Veit; Sprenger, T.; Wildemann, B. C.; Schirduan, K. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Antiseizure medication and perceived “fair” cost allocation: A factorial survey among neurologists, persons with epilepsy, their relatives, and a control group - Stritzelberger, Jenny; Walther, Katrin; Olmes, David; Gollwitzer, Stefanie; Graf, Wolfgang; Welte, Tamara; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Kriwy, Peter; Hamer, Hajo (Epilepsia, 2022)
Objective: Because resources are limited in modern health care systems, the decision on the allocation of expensive drugs can be supported by a public consent. This study examines how various factors influence subjectively perceived “fair” pricing of antiseizure medication (ASM) among four groups including physicians, persons with epilepsy (PWEs), their relatives, and a control group. Methods: We conducted a factorial survey. Vignettes featured a fictional PWE receiving a fictional ASM. The characteristics of the fictional PWE, ASM, and epilepsy varied. Participants were asked to assess the subjectively appropriate annual cost of ASM treatment per year for each scenario. Results: Fifty-seven PWEs (mean age (SD) 37.7 ± 12.3, 45.6% female), 44 relatives (age 48.4 ± 15.7, 51.1% female), 46 neurologists (age 37.1 ± 9.6, 65.2% female), and 47 persons in the control group (age 31.2 ± 11.2, 68.1% female) completed the questionnaire. The amount of money that respondents were willing to spend for ASM treatment was higher than currently needed in Germany and increased with disease severity among all groups. All groups except for PWEs accepted higher costs of a drug with better seizure control. Physicians and the control group, but not PWEs and their relatives, tended to do so also for minor or no side effects. Physicians reduced the costs for unemployed patients and the control group spent less money for older patients. Significance: ASM effectiveness appears to justify higher costs. However, the control group attributed less money to older PWEs and physicians allocated fewer drug costs to unemployed PWEs.
CRIS-Team Scopus Importer:2022-08-19

Anti-seizure medication is not associated with an increased risk to develop cancer in epilepsy patients - Stritzelberger, Jenny; Lang, Johannes; Mueller, Tamara M.; Reindl, Caroline; Westermayer, Vivien; Kostev, Karel; Hamer, Hajo (Journal of Neurology, 2021)
Objective: Whether anti-seizure medication (ASM) increases the risk for cancer has been debated for decades. While for some ASM, a carcinoma-promoting effect has been suspected, carcinoma-protective effects have been shown for other ASM. However, the issue remains unresolved as data from preclinical and clinical studies have been inconsistent and contradictory. Methods: We collected anonymous patient data from practice neurologists throughout Germany between 2009 and 2018 using the IMS Disease Analyzer database (QuintilesIMS, Frankfurt, Germany). People with epilepsy (PWE) with an initial cancer diagnosis and antiepileptic therapy prior to the index date were 1:1 matched with a control group of PWE without cancer according to age, gender, index year, Charlson Comorbidity Index, and treating physician. For both groups, the risk to develop cancer under treatment with different ASMs was analyzed using three different models (ever use vs. never use (I), effect per one (II) and per five therapy years (III). Results: A total of 3152 PWE were included (each group, n = 1,576; age = 67.3 ± 14.0 years). The risk to develop cancer was not significantly elevated for any ASM. Carbamazepine was associated with a decreased cancer risk (OR Model I: 0.699, p <.0001, OR Model II: 0.952, p =.4878, OR Model III: 0.758, p <.0004). Significance: Our findings suggest that ASM use does not increase the risk of cancer in epilepsy patients.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiseizure medication; Carbamazepine; Carcinogenicity; Epilepsy

Apraxia and the representation of knowledge: where is the boundary between the cognitive and the motor domain? - Schenk, Thomas (Cortex, 2014)
EVALuna2:22284

A prospective, multicenter study of cardiac-based seizure detection to activate vagus nerve stimulation - Boon, Paul; Vonck, Kristl; Van Rijckevorsel, Kenou; El Tahry, Riem; Elger, Christian E.; Mullatti, Nandini; Schulze-Bonhage, Andreas; Wagner, Louis; Diehl, Beate; Hamer, Hajo; Reuber, Markus; Kostov, Hrisimir; et al. (Seizure-European Journal of Epilepsy, 2015)
This study investigates the performance of a cardiac-based seizure detection algorithm (CBSDA) that automatically triggers VNS (NCT01325623).Thirty-one patients with drug resistant epilepsy were evaluated in an epilepsy monitoring unit (EMU) to assess algorithm performance and near-term clinical benefit. Long-term efficacy and safety were evaluated with combined open and closed-loop VNS.Sixty-six seizures (n=16 patients) were available from the EMU for analysis. In 37 seizures (n=14 patients) a >=20% heart rate increase was found and 11 (n=5 patients) were associated with ictal tachycardia (iTC, 55% or 35bpm heart rate increase, minimum of 100bpm). Multiple CBSDA settings achieved a sensitivity of >=80%. False positives ranged from 0.5 to 7.2/h. 27/66 seizures were stimulated within ±2min of seizure onset. In 10/17 of these seizures, where triggered VNS overlapped with ongoing seizure activity, seizure activity stopped during stimulation. Physician-scored seizure severity (NHS3-scale) showed significant improvement for complex partial seizures (CPS) at EMU discharge and through 12 months (p<0.05). Patient-scored seizure severity (total SSQ score) showed significant improvement at 3 and 6 months. Quality of life (total QOLIE-31-P score) showed significant improvement at 12 months. The responder rate (>=50% reduction in seizure frequency) at 12 months was 29.6% (n=8/27). Safety profiles were comparable to prior VNS trials.The investigated CBSDA has a high sensitivity and an acceptable specificity for triggering VNS. Despite the moderate effects on seizure frequency, combined open- and closed-loop VNS may provide valuable improvements in seizure severity and QOL in refractory epilepsy patients.
EVALuna2:22375

Aryl Hydrocarbon Receptor Activation in Astrocytes by Laquinimod Ameliorates Autoimmune Inflammation in the CNS - Rothhammer, Veit; Kenison, Jessica E.; Li, Zahorong; Tjon, Emily; Takenaka, Maisa C.; Chao, Chun Cheih; Alves de Lima, Kalil; Borucki, Davis M.; Kaye, Joel; Quintana, Francisco J. (Neurology, Neuroimmunology and Neuroinflammation, 2021)
OBJECTIVE: MS is an autoimmune demyelinating disease of the CNS, which causes neurologic deficits in young adults and leads to progressive disability. The aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor, can drive anti-inflammatory functions in peripheral immune cells and also in CNS-resident cells. Laquinimod is a drug developed for the treatment of MS known to activate AHR, but the cellular targets of laquinimod are still not completely known. In this work, we analyzed the contribution of AHR activation in astrocytes to its beneficial effects in the experimental autoimmune encephalomyelitis (EAE) preclinical model of MS. METHODS: We used conditional knockout mice, in combination with genome-wide analysis of gene expression by RNA-seq and in vitro culture systems to investigate the effects of laquinimod on astrocytes. RESULTS: We found that AHR activation in astrocytes by laquinimod ameliorates EAE, a preclinical model of MS. Genome-wide RNA-seq transcriptional analyses detected anti-inflammatory effects of laquinimod in glial cells during EAE. Moreover, we established that the Delaq metabolite of laquinimod dampens proinflammatory mediator production while activating tissue-protective mechanisms in glia. CONCLUSIONS: Taken together, these findings suggest that AHR activation by clinically relevant AHR agonists may represent a novel therapeutic approach for the treatment of MS.
CRIS-Team Scopus Importer:2021-04-09

Aryl Hydrocarbon Receptor Plasma Agonist Activity Correlates With Disease Activity in Progressive MS - Tsaktanis, Thanos; Beyer, Tobias; Nirschl, Lucy; Linnerbauer, Mathias; Grummel, Verena; Bussas, Mathias; Tjon, Emily; Mühlau, Mark; Korn, Thomas; Hemmer, Bernhard; Quintana, Francisco J.; Rothhammer, Veit (Neurology, Neuroimmunology and Neuroinflammation, 2021)
OBJECTIVE: The relationship between serum aryl hydrocarbon receptor (AHR) agonistic activity levels with disease severity, its modulation over the course of relapsing-remitting MS (RRMS), and its regulation in progressive MS (PMS) are unknown. Here, we report the analysis of AHR agonistic activity levels in cross-sectional and longitudinal serum samples of patients with RRMS and PMS. METHODS: In a cross-sectional investigation, a total of 36 control patients diagnosed with noninflammatory diseases, 84 patients with RRMS, 35 patients with secondary progressive MS (SPMS), and 41 patients with primary progressive MS (PPMS) were included in this study. AHR activity was measured in a cell-based luciferase assay and correlated with age, sex, the presence of disease-modifying therapies, Expanded Disability Status Scale scores, and disease duration. In a second longitudinal investigation, we analyzed AHR activity in 13 patients diagnosed with RRMS over a period from 4 to 10 years and correlated AHR agonistic activity with white matter atrophy and lesion load volume changes. RESULTS: In RRMS, AHR ligand levels were globally decreased and associated with disease duration and neurologic disability. In SPMS and PPMS, serum AHR agonistic activity was decreased and correlated with disease severity. Finally, in longitudinal serum samples of patients with RRMS, decreased AHR agonistic activity was linked to progressive CNS atrophy and increased lesion load. CONCLUSIONS: These findings suggest that serum AHR agonist levels negatively correlate with disability in RRMS and PMS and decrease longitudinally in correlation with MRI markers of disease progression. Thus, serum AHR agonistic activity may serve as novel biomarker for disability progression in MS.
CRIS-Team Scopus Importer:2021-01-15

A single-center observational study on long-term neurodevelopmental outcomes in children with tuberous sclerosis complex - Mammadova, Dilbar; Vecko, Julia; Hofmann, Marlene; Schüssler, Stephanie; Deiters, Ludger; Canda, A.; Wieland, Anna; Gollwitzer, Stephanie; Hamer, Hajo; Trollmann, Regina (Orphanet Journal of Rare Diseases, 2023)
Background: Tuberous sclerosis complex (TSC) is a rare multisystem disorder caused by mutations in the TSC1 or TSC2 gene. More than 90% of patients with TSC develop neurological and/or neuropsychiatric manifestations. The aim of the present study was to determine the developmental and cognitive long-term outcomes of pediatric TSC patients. Methods: This cross-sectional, monocenter study included pediatric TSC patients who received multidisciplinary long-term care with a last visit between 2005 and 2019. Neurological manifestations and cognitive development (BSID, K-ABC) were analyzed in relation to age and type of mutation. Results: Thirty-five patients aged 13.5 ± 7.8 years were included in the study. Diagnosis was confirmed genetically in 65.7% of patients (TSC1, 26.1%; TSC2, 65.2%; NMI, 8.7%). Mean age at diagnosis was 1.3 ± 3.5 years; 74.3% of the patients had been diagnosed within the first year of life due to seizures (62.9%) or/and cardiac rhabdomyomas (28.6%). The most common TSC manifestations included structural brain lesions (cortical tubers, 91.4%; subependymal nodules, 82.9%), epilepsy (85.7%), and cardiac rhabdomyomas (62.9%). Mean age at seizure onset was 1.5 ± 2.3 years, with onset in 80.0% of patients within the first two years of life. Infantile spasms, which were the first seizure type in 23.3% of the patients, developed earlier (0.6 ± 0.4 years) than focal seizures (1.8 ± 2.5 years). Refractory epilepsy was present in 21 (70.0%) patients, mild or severe intellectual impairment in 66.6%, and autism spectrum disorders in 11.4%. Severe cognitive impairment (33.3%) was significantly associated with epilepsy type and age at seizure onset (p < 0.05). Conclusions: The results emphasized the phenotypic variability of pediatric-onset TSC and the high rate of neurological and neuropsychiatric morbidity. Early-onset refractory epilepsy was associated with impaired cognitive development. Children of all ages with TSC require multidisciplinary long-term care and individual early-intervention programs.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Antiseizure medication; Autism; Cognition; Rare disease; Refractory epilepsy; Tuberous sclerosis complex

A Single Injection of N-Oleoyldopamine, an Endogenous Agonist for Transient Receptor Potential Vanilloid-1, Induced Brain Hypothermia, but No Neuroprotective Effects in Experimentally Induced Cerebral Ischemia in Rats - De Rink, Maria Mercedes Tejada; Naumann, Ulrike; Kollmar, Rainer; Schwab, Stefan; Dietel, Barbara; Harada, Hideki; Tauchi, Miyuki (Therapeutic Hypothermia and Temperature Management, 2019)
Targeted temperature management, or therapeutic hypothermia, is a potent neuroprotective approach after ischemic brain injury. Hypothermia should be induced as soon as possible after the onset of acute stroke to assure better outcomes. Accordingly, drugs with a fast-acting hypothermic effect sustainable through the period of emergency transportation to hospital would have clinical advantages. Activation of the transient receptor potential vanilloid-1 (TRPV1) can induce hypothermia. Our immunohistochemical investigations confirmed that TRPV1 was distributed to perivascular and periventricular regions of the rat brain, where TRPV1 can be easily detected by TRPV1 agonists. An endogenous TRPV1 selective agonist, N-oleoyldopamine (OLDA), and a synthetic antagonist, AMG 9810, were injected intraperitoneally into healthy adult male Wister rats, and brain and core temperatures and gross motor activities were monitored. Comparison with baseline temperatures showed that TRPV1 injection immediately induced mild hypothermia (p < 0.05 in brain and p < 0.01 in body), and AMG 9810 induced immediate mild hyperthermia (not significant). However, the OLDA-induced hypothermia did not decrease lesion volume after middle carotid artery occlusion in rats. Relative to vehicle, OLDA yielded poorer outcomes and AMG 9810 yielded better outcomes in neurological scores and lesion size. Our study showed that, as an agonist of TRPV1, OLDA has suitable hypothermia-inducing properties, but did not decrease lesion volume. Therefore, the search for novel TRPV1 agonists and/or antagonists providing hypothermia and neuroprotection should continue. Further investigations should also target OLDA-induced transient hypothermia combined with long-term hypothermia maintenance with surface cooling, which mimics the anticipated clinical use of this class of drug.
CRIS-Team WoS Importer:2019-06-18

A Sphingosine-1-Phosphate Receptor Modulator Attenuated Secondary Brain Injury and Improved Neurological Functions of Mice after ICH - Bobinger, Tobias; Bäuerle, Tobias; Seyler, L.; von Hörsten, Stephan; Schwab, Stefan; Huttner, Hagen; Manaenko, A. (Oxidative Medicine and Cellular Longevity, 2020)
Background. Stroke activates the immune system and induces brain infiltration by immune cells, aggravating brain injury. Poststroke immunomodulation via (S1P-)receptor modulation is beneficial; however, the S1P-modulator in clinical use (FTY-720) is unspecific, and undesirable side effects have been reported. Previously, we tested effects of a novel selective S1P-receptor modulator, Siponimod, on ICH-induced brain injury in acute stage of the disease. In the current study, we investigated whether protective effects of Siponimod, evaluated in a short-term study, will protect the brain of ICH animals at long term as well. Methods. 134 C57BL/6N mice were divided into sham and ICH-operated groups. Collagenase model of ICH was employed. ICH animals were divided into Siponimod treated and nontreated. Dose- and time-dependent effects of Siponimod were investigated. Contraplay between development of brain injury and the number of lymphocytes infiltrating the brain was investigated by forelimb placing, T-Maze test, brain water content calculation, MRI scanning, and immunostaining. Results. Depending on the therapeutic strategy, Siponimod attenuated the development of brain edema, decreased ICH-induced ventriculomegaly and improved neurological functions of animals after ICH. It was associated with less lymphocytes in the brain of ICH animals. Conclusion. Siponimod is able to decrease the brain injury and improves neurological functions of animals after ICH.
CRIS-Team Scopus Importer:2020-10-09

Assessing comfort in the epilepsy monitoring unit: Psychometric testing of an instrument - Egger-Rainer, Andrea; Trinka, Eugen; Zimmermann, Georg; Arnold, Stephan; Boßelmann, Christian; Hamer, Hajo; Hengsberger, Anna; Lang, Johannes; Lerche, Holger; Noachtar, Soheyl; Pataraia, Ekaterina; Schulze-Bonhage, Andreas; et al. (Epilepsy & Behavior, 2020)
Purpose: The purpose of the study was to evaluate the psychometric properties of the newly developed Epilepsy Monitoring Unit Comfort Questionnaire (EMUCQ) according to the consensus-based standards for the selection of health measurements instruments (COSMIN). Moreover, we aimed to assess changes in comfort-levels. Methods: From October 2018 to November 2019, a total of 267 patients participated in a quantitative study in ten epilepsy centers in Austria and southern Germany. For basic item analysis, descriptive analysis and correlational analysis were computed. An exploratory factor analysis (EFA) was undertaken to detect the factor structure. Reliability was checked through internal consistency (Cronbach's alpha) and the measurement error. In the validity domain, convergent validity and structural validity were estimated. t-Tests were used to detect changes in comfort-levels. Results: Due to unfavorable statistical properties, two items were removed. Exploratory factor analysis showed a three-factorial solution. The EMUCQ was found to be a reliable instrument (Cronbach's alpha 0.77–0.81 for the subscales, 0.88 for the scale total comfort); convergent validity could be supported, too. Confirmatory factor analysis (CFA) supported the hypothesis that structural validity for the three subscales holds. The patients' comfort levels were lower at the end of the stay than at the beginning and lower in nonseizure-free patients compared with seizure-free patients. Conclusion: Validity and reliability are supported for the 42-item EMUCQ in the three-factorial solution. Owing to the item reduction and modifications made in the CFA, a new test should be carried out on a different sample.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Comfort; Epilepsy monitoring unit; Questionnaire; Validation study

Assessing the value of topiramate in refractory status epilepticus - Madzar, Dominik; Kuramatsu, Joji; Gerner, Stefan; Huttner, Hagen (Seizure-European Journal of Epilepsy, 2016)
The aim of this study was to assess factors associated with the use of topiramate (TPM) in refractory status epilepticus (RSE).We retrospectively reviewed RSE episodes over a 12-year period. Episodes treated with and without TPM were compared in terms of demographics, RSE characteristics, clinical course, and outcome in univariate and multivariate analyses. Subgroups defined by type of RSE were studied separately. Functional outcome was assessed with the modified Rankin Scale.Among 71 episodes, 17 (23.9%) were treated with TPM and seizure control was achieved in all of these. The results of unadjusted comparisons suggested a use of TPM in younger and healthier patients who received more perseverant treatment indicated by a higher number of antiepileptic drugs applied. In multivariate analysis adjusting for RSE duration, however, these associations lost significance. Furthermore, TPM was not a predictor of successful RSE termination in neither the overall cohort, nor in the subgroup of complex-partial RSE.After multivariate adjustment, no significant differences were observed between episodes treated with and without TPM in baseline characteristics, treatment, and outcome. Regarding the latter, this study does therefore not yield evidence for a particular efficacy of TPM in RSE.
EVALuna2:22475

Assessing viability of extracorporeal preserved muscle transplants using external field stimulation: a novel tool to improve methods prolonging bridge-to-transplantation time. - Taeger, Christian; Friedrich, Oliver; Dragu, Adrian; Weigand, Annika; Hobe, Frieder; Drechsler, Caroline; Geppert, Carol-Immanuel; Arkudas, Andreas; Münch, Frank; Buchholz, Rainer; Pollmann, Charlotte; Schramm, Axel; et al. (Scientific Reports, 2015)
Preventing ischemia-related cell damage is a priority when preserving tissue for transplantation. Perfusion protocols have been established for a variety of applications and proven to be superior to procedures used in clinical routine. Extracorporeal perfusion of muscle tissue though cumbersome is highly desirable since it is highly susceptible to ischemia-related damage. To show the efficacy of different perfusion protocols external field stimulation can be used to immediately visualize improvement or deterioration of the tissue during active and running perfusion protocols. This method has been used to show the superiority of extracorporeal perfusion using porcine rectus abdominis muscles perfused with heparinized saline solution. Perfused muscles showed statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. The combination of extracorporeal perfusion and external field stimulation may improve organ conservation research.

Association between cognition and gait in multiple sclerosis: A smartphone-based longitudinal analysis - Ibrahim, Alzhraa; Adler, Werner; Gaßner, Heiko; Rothhammer, Veit; Kluge, Felix; Eskofier, Björn (International Journal of Medical Informatics, 2023)
Background: Gait and cognition impairments are common problems among People with Multiple Sclerosis (PwMS). Previous studies have investigated cross-sectional associations between gait and cognition. However, there is a lack of evidence regarding the longitudinal association between these factors in PwMS. Therefore, the objective of this study was to explore this longitudinal relationship using smartphone-based data from the Floodlight study. Methods: Using the publicly available Floodlight dataset, which contains smartphone-based longitudinal data, we used a linear mixed model to investigate the longitudinal relationship between cognition, measured by the Symbol Digit Modalities Test (SDMT), and gait, measured by the 2 Minute Walking test (2 MW) step count and Five-U-Turn Test (FUTT) turning speed. Four mixed models were fitted to explore the association between: 1) SDMT and mean step count; 2) SDMT and variability of step count; 3) SDMT and mean FUTT turning speed; and 4) SDMT and variability of FUTT turningt speed. Results: After controlling for age, sex, weight, and height, there were significant correlations between SDMT and the variability of 2 MW step count, the mean of FUTT turning speed. No significant correlation was observed between SDMT and the 2 MW mean step count. Significance: Our findings support the evidence that gait and cognition are associated in PwMS. This may support clinicians to adjust treatment and intervention programs that address both gait and cognitive impairments.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Cognition; Gait; MS; Smartphone sensor

Association of Intraventricular Fibrinolysis With Clinical Outcomes in Intracerebral Hemorrhage: An Individual Participant Data Meta-Analysis. - Kuramatsu, Joji; Gerner, Stefan; Ziai, Wendy; Bardutzky, Juergen; Sembill, Jochen; Sprügel, Maximilian; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al. (Stroke, 2022)
BACKGROUND: In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes. METHODS: This individual participant data meta-analysis pooled 1501 patients from 2 randomized trials and 7 observational studies enrolled during 2004 to 2015. We compared IVF versus standard of care (including placebo) in patients treated with external ventricular drainage due to acute hydrocephalus caused by ICH with intraventricular hemorrhage. The primary outcome was functional disability evaluated by the modified Rankin Scale (mRS; range: 0-6, lower scores indicating less disability) at 6 months, dichotomized into mRS score: 0 to 3 versus mRS: 4 to 6. Secondary outcomes included ordinal-shift analysis, all-cause mortality, and intracranial adverse events. Confounding and bias were adjusted by random effects and doubly robust models to calculate odds ratios and absolute treatment effects (ATE). RESULTS: Comparing treatment of 596 with IVF to 905 with standard of care resulted in an ATE to achieve the primary outcome of 9.3% (95% CI, 4.4-14.1). IVF treatment showed a significant shift towards improved outcome across the entire range of mRS estimates, common odds ratio, 1.75 (95% CI, 1.39-2.17), reduced mortality, odds ratio, 0.47 (95% CI, 0.35-0.64), without increased adverse events, absolute difference, 1.0% (95% CI, -2.7 to 4.8). Exploratory analyses provided that early IVF treatment (≤48 hours) after symptom onset was associated with an ATE, 15.2% (95% CI, 8.6-21.8) to achieve the primary outcome. CONCLUSIONS: As compared to standard of care, the administration of IVF in patients with acute hydrocephalus caused by intracerebral and intraventricular hemorrhage was significantly associated with improved functional outcome at 6 months. The treatment effect was linked to an early time window <48 hours, specifying a target population for future trials.
EVALuna2:505459

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Association of prothrombin complex concentrate administration and hematoma enlargement in non-vitamin K antagonist oral anticoagulant-related intracerebral hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Endres, Matthias; Haeusler, Karl Georg; Vajkoczy, Peter; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos; Erbguth, Frank; Schellinger, Peter D.; et al. (Annals of Neurology, 2018)
To investigate parameters associated with hematoma enlargement in non-vitamin K antagonist oral anticoagulant (NOAC)-related intracerebral hemorrhage (ICH).This retrospective cohort study includes individual patient data for 190 patients with NOAC-associated ICH over a 5-year period (2011-2015) at 19 departments of neurology across Germany. Primary outcome was the association of prothrombin complex concentrate (PCC) administration with hematoma enlargement. Subanalyses were calculated for blood pressure management and its association with the primary outcome. Secondary outcomes include associations with in-hospital mortality and functional outcome at 3 months assessed using the modified Rankin Scale.The study population for analysis of primary and secondary outcomes consisted of 146 NOAC-ICH patients with available follow-up imaging. Hematoma enlargement occurred in 49/146 (33.6%) patients with NOAC-related ICH. Parameters associated with hematoma enlargement were blood pressure >= 160mmHg within 4 hours and-in the case of factor Xa inhibitor ICH-anti-Xa levels on admission. PCC administration prior to follow-up imaging was not significantly associated with a reduced rate of hematoma enlargement either in overall NOAC-related ICH or in patients with factor Xa inhibitor intake (NOAC: risk ratio [RR] = 1.150, 95% confidence interval [CI] = 0.632-2.090; factor Xa inhibitor: RR = 1.057, 95% CI = 0.565-1.977), regardless of PCC dosage given or time interval until imaging or treatment. Systolic blood pressure levels < 160mmHg within 4 hours after admission were significantly associated with a reduction in the proportion of patients with hematoma enlargement (RR = 0.598, 95% CI = 0.365-0.978). PCC administration had no effect on mortality and functional outcome either at discharge or at 3 months.In contrast to blood pressure control, PCC administration was not associated with a reduced rate of hematoma enlargement in NOAC-related ICH. Our findings support the need of further investigations exploring new hemostatic reversal strategies for patients with factor Xa inhibitor-related ICH. Ann Neurol 2018;83:186-196.
EVALuna2:22552

Association of seizure duration and outcome in refractory status epilepticus - Madzar, Dominik; Geyer, Anna; Knappe, Ruben U.; Gollwitzer, Stephanie; Kuramatsu, Joji; Gerner, Stefan; Hamer, Hajo; Huttner, Hagen (Journal of Neurology, 2016)
The aim of the study was to identify factors influencing long-term outcome and to evaluate the prognostic power of the Status Epilepticus Severity Score (STESS) in refractory status epilepticus (RSE). We retrospectively extracted data on baseline characteristics, RSE details, and hospital course including complications from all patients treated for RSE in our institution between January 2001 and January 2013. Functional outcome was assessed using the modified Rankin Scale (mRS) and was defined as good when either RSE did not lead to functional decline or when the resulting mRS score was 2 or below. Seventy-one episodes in 65 patients were analyzed. The median follow-up time was 12 weeks (IQR 6-35), two patients were lost to follow-up. Poor functional long-term outcome was observed in 42/69 (60.9%) episodes. In-hospital mortality occurred in 13/71 (18.3%) episodes. Multivariable analysis revealed that STESS >= 3, longer RSE duration, and sepsis were independently related to poor functional long-term outcome. Receiver operating characteristics (ROC) curve analyses confirmed the cut-off dichotomization into STESS >= 3 and STESS < 3 for optimal discrimination between good and poor outcome (AUC = 0.671, p = 0.002, YI = 0.368, NPV = 0.607, PPV = 0.756) and revealed an RSE duration of 10 days as a significant cut-off point associated with outcome (AUC = 0.712, p = 0.012, YI = 0.310; NPV = 0.545, PPV = 0.750). In conclusion, STESS and RSE duration represent relevant scores and parameters impacting long-term outcome after RSE. A shorter RSE duration is associated with better outcome and, therefore, rapid and adequate treatment for seizure termination should be enforced.
EVALuna2:22460

Association of Surgical Hematoma Evacuation vs Conservative Treatment With Functional Outcome in Patients With Cerebellar Intracerebral Hemorrhage - Kuramatsu, Joji; Biffi, Alessandro; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Leasure, Audrey; Sansing, Lauren; Matouk, Charles; Falcone, Guido J.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; et al. (Journal of the American Medical Association, 2019)
Importance: The association of surgical hematoma evacuation with clinical outcomes in patients with cerebellar intracerebral hemorrhage (ICH) has not been established. Objective: To determine the association of surgical hematoma evacuation with clinical outcomes in cerebellar ICH. Design, Setting, and Participants: Individual participant data (IPD) meta-analysis of 4 observational ICH studies incorporating 6580 patients treated at 64 hospitals across the United States and Germany (2006-2015). Exposure: Surgical hematoma evacuation vs conservative treatment. Main Outcomes and Measures: The primary outcome was functional disability evaluated by the modified Rankin Scale ([mRS] score range: 0, no functional deficit to 6, death) at 3 months; favorable (mRS, 0-3) vs unfavorable (mRS, 4-6). Secondary outcomes included survival at 3 months and at 12 months. Analyses included propensity score matching and covariate adjustment, and predicted probabilities were used to identify treatment-related cutoff values for cerebellar ICH. Results: Among 578 patients with cerebellar ICH, propensity score-matched groups included 152 patients with surgical hematoma evacuation vs 152 patients with conservative treatment (age, 68.9 vs 69.2 years; men, 55.9% vs 51.3%; prior anticoagulation, 60.5% vs 63.8%; and median ICH volume, 20.5 cm3 vs 18.8 cm3). After adjustment, surgical hematoma evacuation vs conservative treatment was not significantly associated with likelihood of better functional disability at 3 months (30.9% vs 35.5%; adjusted odds ratio [AOR], 0.94 [95% CI, 0.81 to 1.09], P = .43; adjusted risk difference [ARD], -3.7% [95% CI, -8.7% to 1.2%]) but was significantly associated with greater probability of survival at 3 months (78.3% vs 61.2%; AOR, 1.25 [95% CI, 1.07 to 1.45], P = .005; ARD, 18.5% [95% CI, 13.8% to 23.2%]) and at 12 months (71.7% vs 57.2%; AOR, 1.21 [95% CI, 1.03 to 1.42], P = .02; ARD, 17.0% [95% CI, 11.5% to 22.6%]). A volume range of 12 to 15 cm3 was identified; below this level, surgical hematoma evacuation was associated with lower likelihood of favorable functional outcome (volume ≤12 cm3, 30.6% vs 62.3% [P = .003]; ARD, -34.7% [-38.8% to -30.6%]; P value for interaction, .01), and above, it was associated with greater likelihood of survival (volume ≥15 cm3, 74.5% vs 45.1% [P < .001]; ARD, 28.2% [95% CI, 24.6% to 31.8%]; P value for interaction, .02). Conclusions and Relevance: Among patients with cerebellar ICH, surgical hematoma evacuation, compared with conservative treatment, was not associated with improved functional outcome. Given the null primary outcome, investigation is necessary to establish whether there are differing associations based on hematoma volume.
CRIS-Team Scopus Importer:2019-10-15

Associations of neutrophil-to-lymphocyte ratio with mortality in spontaneous intracerebral hemorrhage - Giede-Jeppe, A.; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Lücking, Hannes; Kuramatsu, J. B.; Huttner, Hagen; Hölter, Philip (2017)
EVALuna2:22568

Astrocyte-Derived Pleiotrophin Mitigates Late-Stage Autoimmune CNS Inflammation - Linnerbauer, Mathias; Lößlein, Lena; Farrenkopf, Daniel; Vandrey, Oliver; Tsaktanis, Thanos; Naumann, Ulrike; Rothhammer, Veit (Frontiers in Immunology, 2022)
Astrocytes are the most abundant glial cells in the central nervous system (CNS) with the capacity to sense and react to injury and inflammatory events. While it has been widely documented that astrocytes can exert tissue-degenerative functions, less is known about their protective and disease-limiting roles. Here, we report the upregulation of pleiotrophin (PTN) by mouse and human astrocytes in multiple sclerosis (MS) and its preclinical model experimental autoimmune encephalomyelitis (EAE). Using CRISPR-Cas9-based genetic perturbation systems, we demonstrate in vivo that astrocyte-derived PTN is critical for the recovery phase of EAE and limits chronic CNS inflammation. PTN reduces pro-inflammatory signaling in astrocytes and microglia and promotes neuronal survival following inflammatory challenge. Finally, we show that intranasal administration of PTN during the late phase of EAE successfully reduces disease severity, making it a potential therapeutic candidate for the treatment of progressive MS, for which existing therapies are limited.
CRIS-Team Scopus Importer:2022-01-28
Keywords: astrocytes; autoimmunity; CNS inflammation; multiple sclerosis; protective

Astrocyte phenotypes in acute multiple sclerosis lesions - Lößlein, Lena; Cirac, A.; Tsaktanis, Thanos; Linnerbauer, Mathias; Schuetz, O.; Beyer, T.; Quintana, F. J.; Rothhammer, Veit (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation - Lyrer, Flurina; Zietz, Annaelle; Seiffge, David J.; Koga, Masatoshi; Volbers, Bastian; Wilson, Duncan; Bonetti, Bruno; Schaedelin, Sabine; Gensicke, Henrik; Yoshimura, Sohei; Macha, Kosmas; Ambler, Gareth; et al. (Annals of Neurology, 2023)
Background: Atrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre-existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk. Methods: Individual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF-associated ischemic stroke. We compared the primary (ischemic stroke recurrence) and secondary outcome (all-cause death) among patients with AFDAS versus KAF and among anticoagulation-naïve versus previously anticoagulated patients using multivariable Cox, Fine-Gray models, and goodness-of-fit statistics to investigate the relative independent prognostic importance of AF-category and pre-existing anticoagulation. Results: Of 4,357 patients, 1,889 (43%) had AFDAS and 2,468 (57%) had KAF, while 3,105 (71%) were anticoagulation-naïve before stroke and 1,252 (29%) were previously anticoagulated. During 6,071 patient-years of follow-up, we observed 244 recurrent strokes and 661 deaths. Only pre-existing anticoagulation (but not KAF) was independently associated with a higher hazard for stroke recurrence in both Cox and Fine-Gray models. Models incorporating pre-existing anticoagulation showed better fit than those with AF category; adding AF-category did not result in better model fit. Neither pre-existing anticoagulation nor KAF were independently associated with death. Conclusion: Our findings challenge the notion that KAF and AFDAS are clinically relevant and distinct prognostic entities. Instead of attributing an independently high stroke recurrence risk to KAF, future research should focus on the causes of stroke despite anticoagulation to develop improved preventive treatments. ANN NEUROL 2023.
CRIS-Team Scopus Importer:2023-04-28

Attitudes toward epilepsy assessed by the SAPE questionnaire in Germany - Comparison of its psychometric properties and results in a web-based vs. face-to-face survey - May, Theodor W.; Pfaefflin, Margarete; Bien, Christian G.; Hamer, Hajo; Holtkamp, Martin; Rating, Dietz; Schulze-Bonhage, Andreas; Straub, Hans-Beatus; Strzelczyk, Adam; Thorbecke, Rupprecht (Epilepsy and Behavior, 2022)
Objective: The aims of this study were (1) to investigate psychometric properties of a new questionnaire (SAPE, Scales of the Attitudes toward People with Epilepsy) that assesses attitudes toward people with epilepsy (PWE) (2) to compare the effects of mode of survey administration (web-based vs. face-toface) on attitudes, and (3) to identify predictors of attitudes.Methods: A face-to-face and a web-based survey were performed in Germany. Weighting factors were used to achieve representative samples of the German population. Reliability and validity of the 6 scales of the SAPE (social distance, stereotypes, personal concerns, and emotional reactions differentiated by fear, anger, and pity) were evaluated and compared for both surveys. Epilepsy knowledge was also assessed. General linear models were performed to investigate predictors of attitudes toward PWE including the type of survey. Results: In total, 1001 participants of the web-based survey and 1026 participants of face-to-face survey were included. Psychometric analyses indicated satisfactory reliability and validity of the scales and differed only slightly between modes of survey. In both surveys, fears and concerns were more pronounced than stereotypes and social distance. However, mean values of two scales were slightly or moderately higher in the face-to-face survey indicating more negative attitudes toward PWE (p < 0.001). Fewer participants of the face-to-face survey reported personal experience with PWE, claiming to know what to do in case of a seizure and claiming to know that seizures can be treated successfully (p < 0.001). These variables proved to be important predictors of positive attitudes toward PWE, besides demographic factors (e.g. age < 65, female gender). When controlling for them, the differences remained significant only for the scales Social Distance (moderately) and Fear (slightly).Significance: In total, psychometric analyses show that web-based surveys using the SAPE may be an alternative to face-to-face surveys to assess attitudes toward PWE. This applies also to the scales Social Distance and Emotional Reactions that allow comparisons with other diseases, e.g. psychiatric disorders. Most scales differ only slightly between survey modes, except social distance. This indicates that single components of attitudes toward PWE may be dependent on the mode of survey or different characteristics of respondents.(c) 2022 Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2022-05-20

Attitudes toward persons with epilepsy as friends: Results of a factorial survey - Walther, Katrin; Kriwy, Peter; Stritzelberger, Jenny; Graf, Wolfgang; Gollwitzer, Stefanie; Lang, Johannes; Reindl, Caroline; Schwab, Stefan; Welte, Tamara; Hamer, Hajo (Epilepsia, 2023)
Objective: Discrimination against persons with epilepsy (PWEs) may persist. The aim of this study was to examine whether epilepsy is an obstacle to desired friendship.Methods: A factorial survey (vignettes), which is less biased by social desirability, was applied to PWEs, their relatives, and lay persons. The vignettes described a person who was varied by the dimensions of age (younger, same age, older), gender (male, female), disease (healthy, mild epilepsy, severe epilepsy [generalized toni-clonic seizures], diabetes), origin (German, non-German), contact (phone/internet, activities at home, activities outside), frequency of contacts (weekly, monthly), and distance (around the corner, 10 km away). Respondents rated their willingness to befriend the person on a 10-point Likert scale. Multivariate regression determined the contribution of each dimension on the judgment.Results: Participants were 64 PWEs (age = 37.1 +/- 14.0 years), 64 relatives of PWEs (age = 45.1 +/- 13.6 years), and 98 controls without contact with PWEs (age = 24.4 +/- 10.1 years). Controls were less interested in a friendship with a PWE with mild epilepsy (-3.4%) and even more avoided PWEs with severe epilepsy (-11.7%), whereas in PWEs with toni-clonic seizures, a mild form of epilepsy was actually conducive to friendship (+7.0%). Controls preferred females (+5.0%) and disliked younger people (-12.3%) and contacts via the internet or telephone (-7.3%). PWEs were also less interested in younger people (-5.8%), and relatives of PWEs had a lower preference for friendships with longer distance (-2.3%).Significance: PWEs still suffer from a risk of social avoidance, and this becomes more evident with generalized motor seizures.
CRIS-Team WoS Importer:2023-02-03

Automated ASPECT scoring in acute ischemic stroke: comparison of three software tools - Hölter, Philip; Mühlen, Iris; Gölitz, Philipp; Beuscher, Vanessa; Schwab, Stefan; Dörfler, Arnd (Neuroradiology, 2020)
Purpose: Various software applications offer support in the diagnosis of acute ischemic stroke (AIS), yet it remains unclear whether the performance of these tools is comparable to each other. Our study aimed to evaluate three fully automated software applications for Alberta Stroke Program Early CT (ASPECT) scoring (Syngo.via Frontier ASPECT Score Prototype V2, Brainomix e-ASPECTS® and RAPID ASPECTS) in AIS patients. Methods: Retrospectively, 131 patients with large vessel occlusion (LVO) of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy (EVT), were included. Pre-interventional non-enhanced CT (NECT) datasets were assessed in random order using the automated ASPECT software and by three experienced neuroradiologists in consensus. Interclass correlation coefficient (ICC), Bland-Altman, and receiver operating characteristics (ROC) were applied for statistical analysis. Results: Median ASPECTS of the expert consensus reading was 8 (7–10). Highest correlation was between the expert read and Brainomix (r = 0.871 (0.818, 0.909), p < 0.001). Correlation between expert read and Frontier V2 (r = 0.801 (0.719, 0.859), p < 0.001) and between expert read and RAPID (r = 0.777 (0.568, 0.871), p < 0.001) was high, respectively. There was a high correlation among the software tools (Frontier V2 and Brainomix: r = 0.830 (0.760, 0.880), p < 0.001; Frontier V2 and RAPID: r = 0.847 (0.693, 0.913), p < 0.001; Brainomix and RAPID: r = 0.835 (0.512, 0.923), p < 0.001). An ROC curve analysis revealed comparable accuracy between the applications and expert consensus reading (Brainomix: AUC = 0.759 (0.670–0.848), p < 0.001; Frontier V2: AUC = 0.752 (0.660–0.843), p < 0.001; RAPID: AUC = 0.734 (0.634–0.831), p < 0.001). Conclusion: Overall, there is a convincing yet developable grade of agreement between current ASPECT software evaluation tools and expert evaluation with regard to ASPECT assessment in AIS.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Acute ischemic stroke; Aspects; Diagnostics; Software anylsis

AUTOMATED PUPILLOMETRY FOR PREDICTION OF SPACE-OCCUPYING HEMISPHERIC INFARCTION AFTER ENDOVASCULAR TREATMENT - Köhn, Julia; Kobus, Franca; Kossel, Clara-Sophie; Borutta, Matthias; Kuramatsu, Joji; Schwab, Stefan (JOURNAL OF NEUROTRAUMA, 2022)
CRIS-Team WoS Importer:2022-09-02

Automated Pupillometry Identifies Absence of Intracranial Pressure Elevation in Intracerebral Hemorrhage Patients - Giede-Jeppe, Antje; Sprügel, Maximilian; Huttner, Hagen; Borutta, Matthias; Kuramatsu, Joji; Hölter, Philip; Engelhorn, Tobias; Schwab, Stefan; Koehn, Julia (Neurocritical Care, 2020)
Introduction Although automated pupillometry is increasingly used in critical care settings, predictive value of automatically assessed pupillary parameters during different intracranial pressure (ICP) levels and possible clinical implications are unestablished. Methods This retrospective cohort study at the neurocritical care unit of the University of Erlangen-Nuremberg (2016-2018) included 23 nontraumatic supratentorial (intracerebral hemorrhage) ICH patients without signs of abnormal pupillary function by manual assessment, i.e., absent light reflex. We assessed ICP levels by an external ventricular drain simultaneously with parameters of pupillary reactivity [i.e., maximum and minimum apertures, light reflex latency (Lat), constriction and redilation velocities (CV, DV), and percentage change of apertures (per-change)] using a portable pupillometer (NeurOptics (R)). Computed tomography (CT) scans were analyzed to determine lesion location, size, intraventricular hemorrhage, hydrocephalus, midline shift, and compression or absence of the basal cisterns. We performed receiver operating characteristics analysis to investigate associations of ICP levels with pupillary parameters and to determine best cutoff values for prediction of ICP elevation. After dichotomization of assessments according to ICP values (normal: < 20 mmHg, elevated: >= 20 mmHg), prognostic performance of the determined cutoff parameters of pupillary function versus of CT-imaging findings was analyzed by calculating sensitivity, specificity, positive and negative predictive values (logistic regression, corresponding ORs with 95% CIs). Results In 23 patients (11 women, median age 59.0 (51.0-69.0) years), 1,934 assessments were available for analysis. A total of 74 ICP elevations >= 20 mmHg occurred in seven patients. Best discriminative thresholds for ICP elevation were: CV < 0.8 mm/s (AUC 0.740), per-change < 10% (AUC 0.743), DV < 0.2 mm/s (AUC 0.703), and Lat > 0.3 s (AUC 0.616). Positive predictive value of all four parameters to indicate ICP elevation ranged between 7.2 and 8.3% only and was similarly low for CT abnormalities (9.1%). We found high negative predictive values of pupillary parameters [CV: 99.2% (95% CI 98.3-99.6), per-change: 98.7% (95% CI 97.8-99.2), DV: 98.0% (95% CI 97.0-98.7), Lat: 97.0% (95% CI 96.0-97.7)], and CT abnormalities [99.7% (95% CI 99.2-99.9)], providing evidence that both techniques adequately identified ICH patients without ICP elevation. Conclusions Our data suggest an association between noninvasively detected changes in pupillary reactivity and ICP levels in sedated ICH patients. Although automated pupillometry and neuroimaging seem not sufficient to noninvasively indicate ICP elevation, both techniques, however, adequately identified ICH patients without ICP elevation. This finding may facilitate routine management by saving invasive ICP monitoring or repeated CT controls in patients with specific automated pupillometry readings.
CRIS-Team WoS Importer:2021-01-08

Automatic dementia screening and scoring by applying deep learning on clock-drawing tests - Chen, Shuqing; Stromer, Daniel; Alnasser Alabdalrahim, Harb; Schwab, Stefan; Weih, Markus; Maier, Andreas (Scientific Reports, 2020)
Dementia is one of the most common neurological syndromes in the world. Usually, diagnoses are made based on paper-and-pencil tests and scored depending on personal judgments of experts. This technique can introduce errors and has high inter-rater variability. To overcome these issues, we present an automatic assessment of the widely used paper-based clock-drawing test by means of deep neural networks. Our study includes a comparison of three modern architectures: VGG16, ResNet-152, and DenseNet-121. The dataset consisted of 1315 individuals. To deal with the limited amount of data, which also included several dementia types, we used optimization strategies for training the neural network. The outcome of our work is a standardized and digital estimation of the dementia screening result and severity level for an individual. We achieved accuracies of 96.65% for screening and up to 98.54% for scoring, overcoming the reported state-of-the-art as well as human accuracies. Due to the digital format, the paper-based test can be simply scanned by using a mobile device and then be evaluated also in areas where there is a staff shortage or where no clinical experts are available.<br

Automatic multimodal detection for long-term seizure documentation in epilepsy - Fuerbass, F.; Kampusch, S.; Kaniusas, E.; Koren, J.; Pirker, S.; Hopfengaertner, R.; Stefan, Hermann; Kluge, T.; Baumgartner, C. (Clinical Neurophysiology, 2017)
This study investigated sensitivity and false detection rate of a multimodal automatic seizure detection algorithm and the applicability to reduced electrode montages for long-term seizure documentation in epilepsy patients.An automatic seizure detection algorithm based on EEG, EMG, and ECG signals was developed. EEG/ECG recordings of 92 patients from two epilepsy monitoring units including 494 seizures were used to assess detection performance. EMG data were extracted by bandpass filtering of EEG signals. Sensitivity and false detection rate were evaluated for each signal modality and for reduced electrode montages.All focal seizures evolving to bilateral tonic-clonic (BTCS, n=50) and 89% of focal seizures (FS, n=139) were detected. Average sensitivity in temporal lobe epilepsy (TLE) patients was 94% and 74% in extratemporal lobe epilepsy (XTLE) patients. Overall detection sensitivity was 86%. Average false detection rate was 12.8 false detections in 24h (FD/24h) for TLE and 22 FD/24h in XTLE patients. Utilization of 8 frontal and temporal electrodes reduced average sensitivity from 86% to 81%.Our automatic multimodal seizure detection algorithm shows high sensitivity with full and reduced electrode montages.Evaluation of different signal modalities and electrode montages paces the way for semi-automatic seizure documentation systems.
EVALuna2:22537

Automatic seizure detection in long-term scalp EEG using an adaptive thresholding technique: a validation study for clinical routine - Hopfengärtner, Rüdiger; Kasper, Burkhard; Graf, Wolfgang; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; Stefan, Hermann; Hamer, Hajo (Clinical Neurophysiology, 2014)
In a previous study we proposed a robust method for automatic seizure detection in scalp EEG recordings. The goal of the current study was to validate an improved algorithm in a much larger group of patients in order to show its general applicability in clinical routine.For the detection of seizures we developed an algorithm based on Short Time Fourier Transform, calculating the integrated power in the frequency band 2.5-12 Hz for a multi-channel seizure detection montage referenced against the average of Fz-Cz-Pz. For identification of seizures an adaptive thresholding technique was applied. Complete data sets of each patient were used for analyses for a fixed set of parameters.159 patients (117 temporal-lobe epilepsies (TLE), 35 extra-temporal lobe epilepsies (ETLE), 7 other) were included with a total of 25,278 h of EEG data, 794 seizures were analyzed. The sensitivity was 87.3% and number of false detections per hour (FpH) was 0.22/h. The sensitivity for TLE patients was 89.9% and FpH=0.19/h; for ETLE patients sensitivity was 77.4% and FpH=0.25/h.The seizure detection algorithm provided high values for sensitivity and selectivity for unselected large EEG data sets without a priori assumptions of seizure patterns.The algorithm is a valuable tool for fast and effective screening of long-term scalp EEG recordings.
EVALuna2:22295

Autonomic challenges suggest that Fingolimod induced cardiac autonomic changes might be reversible - Wang, Ruihao; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Hoesl, K.; Lee, De-Hyung; Linker, Ralf; Hilz, M. J. (2017)
EVALuna2:22573

Autonomic dysfunction in the neurological intensive care unit - Hilz, Max-Josef; Liu, Mao; Roy, Sankanika; Wang, Ruihao (Clinical Autonomic Research, 2019)
Autonomic dysfunction is common in neuro-critical care patients and may compromise the function of various organs. Among the many diseases causing or being associated with autonomic dysfunction are traumatic brain injury, cerebrovascular diseases, epilepsy, Guillain–Barré syndrome (GBS), alcohol withdrawal syndrome, botulism and tetanus, among many others. Autonomic dysfunction may afflict various organs and may involve hyper- or hypo-activity of the sympathetic or parasympathetic system. In this short overview, we address only a small number of neuro-intensive care diseases with autonomic dysfunction. In GBS, autonomic dysfunction is frequent and may account for increased mortality rates; rapid changes between sympathetic and parasympathetic hypo- or hyper-activity may cause life-threatening cardiovascular complications. Paroxysmal sympathetic hyperactivity occurs after brain injury, hypoxia and cerebrovascular and other events, causes paroxysmal tachycardia, hypertension, tachypnoea and hyperthermia and is associated with a poorer prognosis and prolonged intensive care treatment. Other, at times life-threatening autonomic complications with exaggerated sympathetic activity and compromised baroreflex sensitivity arise during the alcohol withdrawal syndrome triggered by abrupt cessation of alcohol consumption. Botulism and tetanus are examples of life-threatening autonomic dysfunction caused by bacterial neurotoxins. Common neurological diseases, such as epilepsy, stroke or subarachnoid haemorrhage, are also associated with autonomic dysfunction that can on occasion cause critical deterioration of disease severity and prognosis.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Alcohol withdrawal syndrome; Autonomic dysfunction; Botulism; Guillain–Barré-syndrome; Neurological intensive care medicine; Paroxysmal sympathetic hyperactivity; Tetanus

Barcoded viral tracing of single-cell interactions in central nervous system inflammation - Clark, Iain C.; Gutiérrez-Vázquez, Cristina; Wheeler, Michael A.; Li, Zhaorong; Rothhammer, Veit; Linnerbauer, Mathias; Sanmarco, Liliana M.; Guo, Lydia; Blain, Manon; Zandee, Stephanie E.J.; Chao, Chun Cheih; Batterman, Katelyn V.; et al. (Science, 2021)
Cell-cell interactions control the physiology and pathology of the central nervous system (CNS). To study astrocyte cell interactions in vivo, we developed rabies barcode interaction detection followed by sequencing (RABID-seq), which combines barcoded viral tracing and single-cell RNA sequencing (scRNA-seq). Using RABID-seq, we identified axon guidance molecules as candidate mediators of microglia-astrocyte interactions that promote CNS pathology in experimental autoimmune encephalomyelitis (EAE) and, potentially, multiple sclerosis (MS). In vivo cell-specific genetic perturbation EAE studies, in vitro systems, and the analysis of MS scRNA-seq datasets and CNS tissue established that Sema4D and Ephrin-B3 expressed in microglia control astrocyte responses via PlexinB2 and EphB3, respectively. Furthermore, a CNS-penetrant EphB3 inhibitor suppressed astrocyte and microglia proinflammatory responses and ameliorated EAE. In summary, RABID-seq identified microglia-astrocyte interactions and candidate therapeutic targets.
CRIS-Team Scopus Importer:2021-05-14

Baroreflex dysfunction is more severe in patients with a history of moderate or severe TBI than in patients after mild TBI - Hilz, Max-Josef; Roy, Sankanika; Wang, R.; Ammon, Fabian; Hoesl, K.; Markus, Jörg; Muresanu, D. (EUROPEAN JOURNAL OF NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-07-30

Baseline magnetic resonance imaging of the optic nerve provides limited predictive information on short-term recovery after acute optic neuritis - Berg, Sebastian; Kaschka, Iris; Utz, Kathrin S.; Huhn, Konstantin; Laemmer, Alexandra; Lämmer, Robert; Waschbisch, Anne; Kloska, Stephan; Lee, De-Hyung; Dörfler, Arnd; Linker, Ralf (PLoS ONE, 2015)
In acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.To evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.Clinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Department of Neurology with clinically definite optic neuritis between December 2010 and September 2012 were retrospectively reviewed including a follow up within 14 days.Both length of the Gd enhancing lesion (r = -0.38; p = 0.001) and the T2 lesion (r = -0.25; p = 0.03) of the optic nerve in acute optic neuritis showed a medium correlation with visual acuity after treatment. Although visual acuity pre-treatment was little but nonsignificantly lower if Gd enhancement of the optic nerve was detected via orbital MRI, improvement of visual acuity after adequate therapy was significantly better (0.40 vs. 0.24; p = 0.04). Intraorbitally located Gd enhancing lesions were associated with worse visual improvement compared to canalicular, intracranial and chiasmal lesions (0.35 vs. 0.54; p = 0.02).Orbital MRI is a broadly available, valuable tool for predicting the improvement of visual function. While the accurate individual prediction of long-term outcomes after appropriate therapy still remains difficult, lesion length of Gd enhancement and T2 lesion contribute to its prediction and a better short-term visual outcome may be associated with detection and localization of Gd enhancement along the optic nerve.
EVALuna2:21236

Bedside Catheter Hematoma Evacuation in Vitamin K Antagonist-Related Intracerebral Hemorrhage: A Safe and Feasible Approach - Volbers, Bastian; Niesen, Wolf Dirk; Amiri-Soltani, Samuel; Staykov, Dimitre; Shah, Mukesch Johannes; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Schwab, Stefan; Bardutzky, Jürgen (Frontiers in Neurology, 2020)
Background and Purpose: Although outcome in intracerebral hemorrhage (ICH) patients is generally not improved by surgical intervention, the use of minimally invasive surgery (MIS) has shown promising results. However, vitamin K antagonist (VKA)-related ICH patients are underrepresented in surgical treatment trials. We therefore assessed the safety and efficacy of a bedside MIS approach including local application of urokinase in VKA-related ICH. Methods: Patients with a VKA-related ICH > 20 ml who received bedside hematoma evacuation treatment (n = 21) at the University Medical Center Freiburg were retrospectively included for analysis and compared to a historical control group (n = 35) selected from an institutional database (University Medical Center Erlangen) according to identical inclusion criteria. Propensity score matching was performed to obtain comparable cohorts. The evolution of hematoma and peri-hemorrhagic edema (PHE) volumes, midline shift, and the occurrence of adverse events were analyzed. Furthermore, we assessed the modified Rankin Scale and NIHSS scores recorded at discharge. Results: Propensity score matching resulted in 16 patients per group with well-balanced characteristics. Median ICH volume at admission was 45.7 (IQR: 24.2–56.7) ml in the control group and 48.4 (IQR: 28.7–59.6) ml in the treatment group (p = 0.327). ICH volume at day 7 was less pronounced in the treatment group [MIS: 23.2 ml (IQR: 15.8–32.3) vs. control: 43.2 ml (IQR: 27.5–52.4); p = 0.013], as was the increase in midline shift up to day 7 [MIS: −3.75 mM (IQR: −4.25 to −2) vs. control: 1 mM (IQR: 0–2); p < 0.001]. No group differences were observed in PHE volume on day 7 [MIS: 42.4 ml (IQR: 25.0–72.3) vs. control: 31.0 ml (IQR: 18.8–53.8); p = 0.274] or mRS at discharge [MIS: 5 (IQR: 4–5) and 5 (IQR: 4–5); p = 0.949]. No hematoma expansion was observed. The catheter had to be replaced in 1 patient (6%). Conclusions: Bedside catheter-based hematoma evacuation followed by local thrombolysis with urokinase appears to be feasible and safe in cases of large VKA-related ICH. Further studies that assess the functional outcome associated with this technique are warranted. Clinical Trial Registration: DRKS00007908 (German Clinical Trial Register; www.drks.de).
CRIS-Team Scopus Importer:2020-09-11
Keywords: intracerebral hemorrhage; midline shift; minimally invasive surgery; peri-hemorrhagic edema; vitamin K antagonist

Bedside Ultrasound After Decompressive Craniectomy: A New Standard? - Bobinger, Tobias; Huttner, Hagen; Schwab, Stefan (Neurocritical Care, 2017)
EVALuna2:22522

Behandlung nach dem ersten Anfall? Pro - Hamer, Hajo (Der Nervenarzt, 2014)
EVALuna2:22330

Behavioural changes in patients with intellectual disability treated with brivaracetam - Andres, Elisa; Kerling, Frank; Hamer, Hajo; Winterholler, Martin (Acta Neurologica Scandinavica, 2018)
OBJECTIVE: The purpose of this study was to evaluate the tolerability and efficacy of brivaracetam (BRV) in residential patients at our epilepsy centre. PATIENTS AND METHODS: We assessed retrospectively 33 patients (14 females; mean age 38.2 years, with range 17-63 years) with intellectual disability (ID) and drug-resistant epilepsy using an industry-independent, non-interventional study design based on standardized daily seizure records. Mean seizure frequency was compared between the 3-month baseline period and subsequent 3-month treatment period. Evaluation, including calculation of retention rate, was carried out for the intervals 3-6 and 9-12 months after brivaracetam initiation. Responders were defined as having a 50% reduction in seizure frequency. The Clinical Global Impression scale (CGI) was applied to allow assessment of qualitative changes in seizure severity, and the Aggressive Behaviour Scale (ABS) gave further insights into challenging behaviour. RESULTS: The responder rate was 19%, and one non-responder attained an improvement in CGI score. The retention rate after 12 months was 37%. Brivaracetam treatment was stopped because of adverse events (n = 3), lack of efficacy (n = 8) or both (n = 6). Thirteen patients experienced behavioural changes, with aggressive behaviour being the commonest effect. We also observed ataxia (n = 2), gastrointestinal disorder (n = 3) and sedation (n = 2). The ABS showed deterioration, or new occurrence, of aggressive behaviour in 13 patients. CONCLUSIONS: Brivaracetam seems to be effective in a small number of patients suffering from difficult-to-treat epilepsy and intellectual disability. Challenging behaviour was documented in a relevant number of patients, with psychiatric illness being a risk factor for this.
EVALuna2:36386

Behavioural changes in patients with intellectual disability treated with perampanel - Andres, E.; Kerling, Frank; Hamer, Hajo; Kasper, Burkhard; Winterholler, Martin (Acta Neurologica Scandinavica, 2017)
The aim of this cross-sectional retrospective study was to assess the tolerability and efficacy of perampanel in patients with drug-resistant epilepsy who also suffered from intellectual disability (ID).We used an industry-independent, non-interventional retrospective evaluation based on standardized, daily seizure records. Twenty-seven patients with ID and drug-resistant epilepsy were started on perampanel between September 2012 and November 2015 after a 3-month observation period without perampanel treatment. Perampanel was given at a maximum dosage of 4-12 mg daily. Evaluation was carried out after 6, 12 and 24 months, including calculation of the retention rate. Mean seizure frequency was compared between the 3-month baseline period and subsequent 3-month treatment periods. The Clinical Global Impression scale was applied to assess qualitative changes in seizure severity, and the Aggressive Behaviour Scale (ABS) gave further insights into challenging behaviour.Perampanel was efficacious and well tolerated in five of 25 patients. In 18 patients, perampanel treatment was stopped, mainly because of adverse events (n=6), lack of efficacy (n=3) or both (n=9). Behavioural changes were documented in 15 of 27 patients, with aggressive behaviour being the commonest effect; we observed ataxia (n=6) and sedation (n=8) in further patients. The ABS showed worsening of aggressive behaviour in six patients.Perampanel was well tolerated and efficacious in one-fifth of our patients. We observed challenging behaviour, ataxia and sedation in a relevant number of patients with ID under perampanel treatment. Further studies are warranted to explore the tolerability of perampanel in patients with ID.
EVALuna2:22550

Beyond Functional Impairment: Redefining Favorable Outcome in Patients with Subarachnoid Hemorrhage - Custal, Christina; Koehn, Julia; Borutta, Matthias; Mrochen, Anne; Brandner, Sebastian; Eyupoglu, Ilker Y.; Lücking, Hannes; Hölter, Philip; Kuramatsu, Joji; Kornhuber, Johannes; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2021)
Background: For outcome assessment in patients surviving subarachnoid hemorrhage (SAH), the modified Rankin scale (mRS) represents the mostly established outcome tool, whereas other dimensions of outcome such as mood disorders and impairments in social life remain unattended so far. Objective: The aim of our study was to correlate 12-month functional and subjective health outcomes in SAH survivors. Methods: All SAH patients treated over a 5-year period received outcome assessment at 12 months, including functional scores (mRS and Barthel Index [BI]), subjective health measurement (EQ-5D), and whether they returned to work. Analyses - including utility-weighted mRS - were conducted to detect associations and correlations among different outcome measures, especially in patients achieving good functional outcome (i.e., mRS 0-2) at 12 months. Results: Of 351 SAH survivors, 287 (81.2%) achieved favorable functional outcome at 12 months. Contrary to the BI, the EQ-5D visual analog scale (VAS) showed a strong association with different mRS grades, accentuated in patients with favorable functional outcome. Despite favorable functional outcome, patients reported a high rate of impairments in activities (24.0%), pain (33.4%), and anxiety/depression (42.5%). Further, multivariable analysis revealed (i) impairments in activities (odds ratio [OR] [95% confidence interval CI]: 0.872 [0.817-0.930]), (ii) presence of depression or anxiety (OR [95% CI]: 0.836 [0.760-0.920]), and (iii) return to work (OR [95% CI]: 1.102 [0.1.013-1.198]) to be independently associated with self-reported subjective health. Conclusion: Established stroke scores mainly focusing on functional outcomes do poorly reflect the high rate of subjective impairments reported in SAH survivors, specifically in those achieving good functional outcome. Further studies are needed to investigate whether psychoeducational approaches aiming at improving coping mechanisms and perceived self-efficacy may result in higher subjective health in these patients.
CRIS-Team WoS Importer:2021-08-06

Biceps electromyography in dialeptic and automotor seizures with and without secondary generalization - Hagge, Mareike; Nunnemann, Sebastian; Bauer, Sebastian; Gollwitzer, Stephanie; Oertel, Wolfgang H.; Knake, Susanne; Rosenow, Felix; Hamer, Hajo (Clinical Neurophysiology, 2016)
Localization of seizure onset during presurgical video-EEG monitoring is indispensable for successful epilepsy surgery. Sometimes analysis of ictal EEG and video fails to identify this zone. Therefore, this study explored the hypothesis that ictal EMG recordings contribute to the lateralization or localization of focal epilepsy.All patients with automotor or dialeptic seizures with or without secondary generalization were prospectively included during presurgical video-EEG monitoring over a 5years study period. We analyzed characteristics of ictal biceps EMG and compared the results to EEG and video findings.79 patients with 185 seizures were included (51.9% male; 73.5% automotor and 26.5% dialeptic seizures; 24.3% seizures secondarily generalized). Even in dialeptic seizures, muscle tone increased bilaterally within seconds after EEG seizure onset (66.7%) without clinical movements. Bilateral "spindle-shaped" EMG activity during the automotor phase predicted secondary generalization in 88.7%. Increase of muscle activity in the contralateral side of the body in the beginning of the secondarily generalized tonic-clonic phase was detected in 78.1% after automotor seizures whereas this phenomenon was less pronounced after dialeptic seizures (69.2%). 38.5% of dialeptic seizures evolved into generalized tonic-unilateral clonic seizures.Ictal EMG recordings provide lateralizing signs especially in secondarily generalized automotor seizures. In addition, the study suggested that secondary generalization in automotor seizures is determined early already during the automotor phase. Dialeptic seizures can evolve only unilaterally into a tonic-clonic seizure while the other side of the body remains tonic.Ictal biceps EMG can provide further information regarding lateralization of epileptic seizures.
EVALuna2:22271

Biomechanical factors may explain why grasping violates Weber's law - Utz, Kathrin S.; Hesse, Constanze; Aschenneller, Nina; Schenk, Thomas (Vision research, 2015)
For grasping, Ganel, Chajut, and Algom (2008) demonstrated that the variability of the maximum grip aperture (MGA) does not increase with the size of the target object. This seems to violate Weber's law, a fundamental law of psychophysics. They concluded that the visual representations guiding grasping are distinct from representations used for perceptual judgments. Weber's law is however only relevant for one component of the measurable variability of MGA, namely the variability in the sensory system. We argue that when looking at the relationship between object size and grasping, the gain (often called slope) governing the relationship between target size and MGA can be used as an approximation to estimate the contribution of sensory noise to MGA variability. To test the idea that differences in gain modulate the relationship between target size and MGA variability, we examined grasping under a variety of conditions. We found that gain varied quite significantly across different tasks, but irrespective of gain Weber's law could not be found in any of the grasping tasks. Instead we repeatedly found an inverse relationship between variability and object size, i.e. variability decreased for bigger objects. This trend may reflect the reduced biomechanical freedom found for movements at the end an effector's effective range of motion. MGA variability may thus be dominated by non-sensory factors and therefore may constitute a poor choice to estimate the variability of the visual signals used by the brain to guide our grasping actions.
EVALuna2:22412

Blood biomarker changes following therapeutic hypothermia in ischemic stroke - Palà, Elena; Penalba, Anna; Bustamante, Alejandro; García-Berrocoso, Teresa; Lamana-Vallverdú, Marcel; Meisel, Christian; Meisel, Andreas; van der Worp, H. Bart; R Macleod, Malcolm; Kallmünzer, Bernd; Schwab, Stefan; Montaner, Joan (Brain and Behavior, 2023)
Introduction: Therapeutic hypothermia is a promising candidate for stroke treatment although its efficacy has not yet been demonstrated in patients. Changes in blood molecules could act as surrogate markers to evaluate the efficacy and safety of therapeutic cooling. Methods: Blood samples from 54 patients included in the EuroHYP-1 study (27 treated with hypothermia, and 27 controls) were obtained at baseline, 24 ± 2 h, and 72 ± 4 h. The levels of a panel of 27 biomarkers, including matrix metalloproteinases and cardiac and inflammatory markers, were measured. Results: Metalloproteinase-3 (MMP-3), fatty-acid-binding protein (FABP), and interleukin-8 (IL-8) increased over time in relation to the hypothermia treatment. Statistically significant correlations between the minimum temperature achieved by each patient in the hypothermia group and the MMP-3 level measured at 72 h, FABP level measured at 24 h, and IL-8 levels measured at 24 and 72 h were found. No differential biomarker levels were observed in patients with poor or favorable outcomes according to modified Rankin Scale scores. Conclusion: Although the exact roles of MMP3, FABP, and IL-8 in hypothermia-treated stroke patients are not known, further exploration is needed to confirm their roles in brain ischemia.
CRIS-Team Scopus Importer:2023-09-29
Keywords: biomarkers; hypothermia; ischemia; stroke

Blood Pressure and Anticoagulation Reversal Management during Off-Hours in Oral Anticoagulation-Associated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Cerebrovascular Diseases, 2020)
Background: Prevention of hematoma enlargement in oral anticoagulation-associated intracerebral hemorrhage (OAC-ICH) focuses on blood pressure (BP) reduction and OAC reversal. We investigated whether treatment efficiency and clinical outcomes differ between OAC-ICH patients admitted outside versus during regular working hours. Methods: Based on pooled data of multicenter cohort studies, we grouped OAC-ICH patients (vitamin K antagonist [VKA], non-vitamin K oral anticoagulant [NOAC]) according to on-vs. off-hour admission. Primary outcome was the functional outcome using the modified Rankin scale (mRS) dichotomized into favorable (mRS 0-3) and unfavorable (mRS 4-6) and mortality at 3 months. Secondary outcome measures included the occurrence of hematoma enlargement, the proportions of patients with systolic BP <140 mm Hg and with anticoagulation treatment achieving international normalized ratio (INR) levels <1.3 at 4 h. Propensity score matching (PSM) was performed to account for imbalances in baseline characteristics. Results: The study population consisted of 76/126 NOAC-ICH patients and 1,005/1,470 VKA patients presenting during off-hours. Functional outcome and mortality rates were not significantly different among PSM patients with VKA-ICH and NOAC-ICH during on-vs. off-hours (mRS 4-6 VKA-ICH: On-hour: 239/357 [66.9%] vs. 253/363 [69.7%] off-hour; p = 0.43; NOAC-ICH: On-hour 26/42 [61.9%] vs. off-hour: 37/57 [64.9%]; p = 0.76; mRS 6 VKA-ICH: On-hour: 127/357 [35.6%] vs. off-hour: 148/363 [40.8%]; p = 0.15;-NOAC-ICH: On-hour 17/42 [40.5%] vs. off-hour: 16/57 [28.1%]; p = 0.20). There were no differences detectable regarding the secondary outcome measures (i.e., hematoma enlargement, the proportion of patients who achieved systolic BP levels <140 mm Hg at 4 h as well as anticoagulation treatment achieving INR levels <1.3 at 4 h) in OAC patients. Conclusion: Our study implies that BP reduction and anticoagulation reversal management are well established and associated with similar rates of hematoma enlargement and clinical outcomes in on-vs. off-hour admitted OAC-ICH patients.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Clinical outcome; Intracerebral hemorrhage; Non-vitamin K oral anticoagulant; Off-hour; Oral anticoagulation; Vitamin K antagonist

Brain MRI Lesions are Related to Bowel Incontinence in Multiple Sclerosis - Fröhlich, Katharina; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Huhn, Konstantin; Schwab, Stefan; Hilz, Max-Josef; Seifert, Frank; Winder, Klemens (Journal of Neuroimaging, 2018)
BACKGROUND AND PURPOSE: Bowel incontinence in multiple sclerosis might be associated with specific lesion sites. This study intended to determine associations between bowel incontinence and cerebral multiple sclerosis lesions using a voxel-wise lesion symptom mapping analysis. METHODS: We conducted a retrospective study of multiple sclerosis patients with self-reported bowel incontinence and matched controls. Lesions were manually outlined on T2-weighted MRI scans and transformed into stereotaxic space. We performed a voxel-wise subtraction analysis subtracting the lesion overlap of patients without from patients with bowel incontinence. Finally, we compared the absence or presence of bowel incontinence between patients with and without lesions in a given voxel using the Liebermeister test. RESULTS: A total of 51 patients were included in the study. The analysis yielded associations between bowel incontinence and lesions in the supramarginal gyrus of the left secondary somatosensory cortex and another lesion cluster in the right parahippocampal gyrus and amygdala. CONCLUSIONS: Our analysis indicates associations between bowel incontinence and lesions in the left supramarginal gyral area contributing to integrating anorectal-visceral sensation and in the right parahippocampal gyrus and amygdala contributing to generating visceral autonomic arousal states. Moreover, our results suggest left hemispheric dominance of sensory visceral integration, while limbic areas of the right hemisphere seem to contribute to the autonomic component of the defecation process. A limitation of our study is the retrospective evaluation of the bowel incontinence status based on medical records. Further research should evaluate the bowel incontinence status in multiple sclerosis patients prospectively to overcome the limitations of the current study.
EVALuna2:36318

Can flat-detector CT after successful endovascular treatment predict long-term outcome in patients with large vessel occlusion? An Alberta Stroke Programme Early CT Score–based study - Knott, Michael; Hölter, Philip; Hock, Stefan; Mühlen, Iris; Gerner, Stefan; Sprügel, Maximilian; Huttner, Hagen; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Neurological Sciences, 2022)
Purpose: Recent studies postulate a high prognostic value of the Alberta Stroke Programme Early CT Score (ASPECTS) applied on non-contrast whole-brain flat-detector CT (FDCT) after successful endovascular treatment (EVT). The aim of this study was the evaluation of long-term patient outcome after endovascular treatment using postinterventional FDCT. Methods: Using a local database (Stroke Research Consortium in Northern Bavaria, STAMINA), 517 patients with successful endovascular treatment (modified Thrombolysis in Cerebral Infarction (mTICI) ≥ 2B) due to acute ischaemic stroke (AIS) and large vessel occlusion (LVO) of the anterior circulation were recruited retrospectively. In all cases, non-contrast FDCT after EVT was analysed with special focus at ASPECTS. These results were correlated with the functional outcome in long-term (modified Rankin Scale (mRS) shift from pre-stroke to 90 days after discharge). Results: A significant difference in FDCT-ASPECTS compared to the subgroup of favourable vs. unfavourable outcome (Δ mRS) (median ASPECTS 10 (10–9) vs. median ASPECTS 9 (10–7); p = 0,001) could be demonstrated. Multivariable regression analysis revealed FDCT-ASPECTS (OR 0.234, 95% CI − 0.102–0.008, p = 0.022) along with the NHISS at admission (OR 0.169, 95% CI 0.003–0.018, p = 0.008) as independent factors for a favourable outcome. Cut-off point for a favourable outcome (Δ mRS) was identified at an ASPECTS ≥ 8 (sensitivity 90.6%, specificity 35%). Conclusion: For patients with LVO and successful EVT, FDCT-ASPECTS was found to be highly reliable in predicting long-term outcome.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ASPECTS; Endovascular treatment; Flat-detector CT; Stroke

Can stapedius reflex testing objectively measure muscle function in Pompe patients? - Hilz, Max-Josef; Hoppe, Ulrich; Möller, Sebastian; Wang, Ruihao; Koehn, Julia (Clinical Case Reports, 2015)
We assessed the value of stapedius reflex testing as an objective measurement of striated muscle function in four patients with Pompe disease. Common tests of disease severity and efficacy of enzyme replacement therapy (ERT) yield highly variable results that depend on patient cooperation and day-to-day performance, whereas stapedius reflex thresholds improved in seven of eight ears after 2 years of ERT.
EVALuna2:19973

Cardiac stunning as first manifestation of multiple sclerosis: A case report reminding us not to overlook cardiovascular autonomic dysfunction in multiple sclerosis - Hilz, Max-Josef (Multiple sclerosis journal, 2016)
Autonomic dysfunction is common but frequently overlooked in multiple sclerosis (MS) patients. The case of a Tako-Tsubo cardiomyopathy on which this commentary is based shows that centrally triggered autonomic dysfunction may be the first life-threatening manifestation of MS.
EVALuna2:22462

Cardioembolic Stroke Risk and Recovery After Anticoagulation-Related Intracerebral Hemorrhage - Murphy, Meredith P.; Kuramatsu, Joji; Leasure, Audrey; Falcone, Guido J.; Kamel, Hooman; Sansing, Lauren H.; Kourkoulis, Christina; Schwab, Kristin; Elm, Jordan J.; Gurol, M. Edip; Huy Tran,; Greenberg, Steven M.; et al. (Stroke, 2018)
Background and Purpose- Whether to resume oral anticoagulation treatment after intracerebral hemorrhage (ICH) remains an unresolved question. Previous studies focused primarily on recurrent stroke after ICH. We sought to investigate the association between cardioembolic stroke risk, oral anticoagulation therapy resumption, and functional recovery among ICH survivors in the absence of recurrent stroke. Methods- We conducted a joint analysis of 3 observational studies: (1) the multicenter RETRACE study (German-Wide Multicenter Analysis of Oral Anticoagulation Associated Intracerebral Hemorrhage); (2) the Massachusetts General Hospital ICH study (n=166); and (3) the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage; n=131). We included 941 survivors of ICH in the setting of active oral anticoagulation therapy for prevention of cardioembolic stroke because of nonvalvular atrial fibrillation and without evidence of ischemic stroke and recurrent ICH at 1 year from the index event. We created univariable and multivariable models to explore associations between cardioembolic stroke risk (based on CHA2DS2-VASc scores) and functional recovery after ICH, defined as achieving modified Rankin Scale score of ≤3 at 1 year for participants with modified Rankin Scale score of >3 at discharge. Results- In multivariable analyses, the CHA2DS2-VASc score was associated with a decreased likelihood of functional recovery (odds ratio, 0.83 per 1 point increase; 95% CI, 0.79-0.86) at 1 year. Anticoagulation resumption was independently associated with a higher likelihood of recovery, regardless of CHA2DS2-VASc score (odds ratio, 1.89; 95% CI, 1.32-2.70). We found an interaction between CHA2DS2-VASc score and anticoagulation resumption in terms of association with increased likelihood of functional recovery (interaction P=0.011). Conclusions- Increasing cardioembolic stroke risk is associated with a decreased likelihood of functional recovery at 1 year after ICH, but this association was weaker among participants resuming oral anticoagulation therapy. These findings support, including recovery metrics, in future studies of anticoagulation resumption after ICH.
EVALuna2:34937

Cardiovagal responses to autonomic challenges are reduced after six months of Fingolimod-therapy in patients with multiple sclerosis - de Rojas Leal, Carmen; Wang, Ruihao; Roy, Sankanika; Liu, Mao; Canavese, F.; Hoesl, K.; Winder, K.; Lee, De-Hyung; Linker, Ralf; Hilz, M. J. (2017)
EVALuna2:22569

Cardiovascular autonomic dysfunction: A cause of acute COVID-19 complications and persistent post-COVID-19 complaints? - Hilz, Max-Josef (European Journal of Neurology, 2023)
CRIS-Team Scopus Importer:2023-02-24

Cardiovascular autonomic dysfunction in patients with posterior circulation ischemic stroke - Wang, Ruihao; Macha, Kosmas; Koehn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Kohrmann, Martin; Hilz, Max-Josef; Kallmünzer, Bernd (JOURNAL OF THE NEUROLOGICAL SCIENCES, 2021)
CRIS-Team WoS Importer:2021-12-03

CARDIOVASCULAR AUTONOMIC MODULATION THREE MONTHS POST STROKE IMPROVES IN PATIENTS WITH ISCHEMIA IN THE RIGHT MIDDLE CEREBRAL ARTERY TERRITORY - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, Klemens; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Cardiovascular autonomic regulation correlates with cognitive performance in patients with a history of traumatic brain injury - Wang, Ruihao; Muresanu, Dafin; Hösl, Katharina; Hilz, Max-Josef (Neurological Sciences, 2023)
Background and objective: Traumatic brain injury (TBI) may afflict brain areas contributing to both cardiovascular autonomic regulation and cognitive performance. To evaluate possible associations between both functions in patients with a history of TBI (post-TBI-patients), we determined correlations between cardiovascular autonomic regulation and cognitive function in post-TBI-patients. Methods: In 86 post-TBI-patients (33.1 ± 10.8 years old, 22 women, 36.8 ± 28.9 months after injury), we monitored RR intervals (RRI), systolic and diastolic blood pressures (BPsys, BPdia), and respiration (RESP) at rest. We calculated parameters of total cardiovascular autonomic modulation (RRI-standard-deviation (RRI-SD), RRI-coefficient-of-variation (RRI-CV), RRI-total-powers), sympathetic (RRI-low-frequency-powers (RRI-LF), normalized (nu) RRI-LF-powers, BPsys-LF-powers) and parasympathetic modulation (root-mean-square-of-successive-RRI-differences (RMSSD), RRI-high-frequency-powers (RRI-HF), RRI-HFnu-powers), sympathetic-parasympathetic balance (RRI-LF/HF-ratios), and baroreflex sensitivity (BRS). We used the Mini-Mental State Examination and Clock Drawing Test (CDT) to screen the general global and visuospatial cognitive function, and applied the standardized Trail Making Test (TMT)-A assessing visuospatial abilities and TMT-B assessing executive function. We calculated correlations between autonomic and cognitive parameters (Spearman’s rank correlation test; significance: P < 0.05). Results: CDT values positively correlated with age (P = 0.013). TMT-A values inversely correlated with RRI-HF-powers (P = 0.033) and BRS (P = 0.043), TMT-B values positively correlated with RRI-LFnu-powers (P = 0.015), RRI-LF/HF-ratios (P = 0.036), and BPsys-LF-powers (P = 0.030), but negatively with RRI-HFnu-powers (P = 0.015). Conclusions: In patients with a history of TBI, there is an association between decreased visuospatial and executive cognitive performance and reduced parasympathetic cardiac modulation and baroreflex sensitivity with relatively increased sympathetic activity. Altered autonomic control bears an increased cardiovascular risk; cognitive impairment compromises quality of life and living conditions. Thus, both functions should be monitored in post-TBI-patients.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Cardiovascular autonomic regulation; Cognitive performance; Correlations; Executive function; Traumatic brain injury; Visuospatial function

Cardiovascular fingolimod effects on rapid baroreceptor unloading are counterbalanced by baroreflex resetting - Hilz, Max-Josef; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Canavese, Francesca; Winder, Klemens; Hoesl, Katharina M.; Lee, De Hyung; Linker, Ralf A.; Wang, Ruihao (Neurological Sciences, 2021)
Background and purpose: Initial cardiovascular fingolimod effects might compromise baroreflex responses to rapid blood pressure (BP) changes during common Valsalva-like maneuvers. This study evaluated cardiovascular responses to Valsalva maneuver (VM)-induced baroreceptor unloading and loading upon fingolimod initiation. Patients and methods: Twenty-one patients with relapsing-remitting multiple sclerosis performed VMs before and 0.5, 1, 2, 3, 4, 5, and 6 hours after fingolimod initiation. We recorded heart rate (HR) as RR intervals (RRI), systolic and diastolic BP (BPsys, BPdia) during VM phase 1, VM phase 2 early, VM phase 2 late, and VM phase 4. Using linear regression analysis between decreasing BPsys and RRI values during VM phase 2 early, we determined baroreflex gain (BRG) reflecting vagal withdrawal and sympathetic activation upon baroreceptor unloading. To assess cardiovagal activation upon baroreceptor loading, we calculated Valsalva ratios (VR) between maximal and minimal RRIs after strain release. Analysis of variance or Friedman tests with post hoc analysis compared corresponding parameters at the eight time points (significance: p < 0.05). Results: RRIs at VM phase 1, VM phase 2 early, and VM phase 2 late were higher after than before fingolimod initiation, and maximal after 4 hours. Fingolimod did not affect the longest RRIs upon strain release, but after 3, 5, and 6 hours lowered the highest BPsys values during overshoot and all BPdia values, and thus reduced VRs. BRG was slightly higher after 3 and 5 hours, and significantly higher after 4 hours than before fingolimod initiation. Conclusions: VR-decreases 3–6 hours after fingolimod initiation are physiologic results of fingolimod-associated attenuations of BP and HR increases at the end of strain and do not suggest impaired cardiovagal activation upon baroreceptor loading. Stable and at the time of HR nadir significantly increased BRGs indicate improved responses to baroreceptor unloading. Thus, cardiovascular fingolimod effects do not impair autonomic responses to sudden baroreceptor loading or unloading but seem to be mitigated by baroreflex resetting.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Baroreflex gain; Baroreflex resetting; Cardiovascular fingolimod effects; Multiple sclerosis; Valsalva maneuver

Cardiovascular medication seems to promote recovery of autonomic dysfunction after stroke - Wang, Ruihao; Koehrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (Journal of Neurology, 2022)
Background Stroke may compromise cardiovascular-autonomic modulation (CAM). The longitudinal post-stroke CAM alterations remain unclear as previous studies excluded patients with cardiovascular medication. This study evaluated whether CAM dysfunction improves after several months in patients under typical clinical conditions, i.e., without excluding patients with cardiovascular medication. Methods In 82 ischemic stroke patients [33 women, 64.9 +/- 8.9 years, NIHSS-scores 2 (interquartile range 1-5)], we evaluated the applications of cardiovascular medication before stroke, during autonomic tests performed within 1 week, 3 and 6 months after stroke onset. We determined resting RR intervals (RRI), systolic, diastolic blood pressures (BPsys), respiration, parameters reflecting total CAM [RRI-standard deviation (RRI-SD), RRI-total powers], sympathetic [RRI-low-frequency powers (RRI-LF), BPsys-LF powers] and parasympathetic CAM [RMSSD, RRI-high-frequency powers (RRI-HF powers)], and baroreflex sensitivity. ANOVA or Friedman tests with post hoc analyses compared patient data with data of 30 healthy controls, significance was assumed for P < 0.05. Results More patients had antihypertensive medication after than before stroke. First-week CAM testing showed lower RRIs, RMSSD, RRI-SDs, RRI-total powers, RRI-HF powers, and baroreflex sensitivity, but higher BPsys-LF powers in patients than controls. After 3 and 6 months, patients had significantly higher RRIs, RRI-SDs, RRI-total powers, RMSSDs, RRI-HF powers, and baroreflex sensitivity, but lower BPsys-LF powers than in the 1st week; RMSSDs and RRI-HF powers no longer differed between patients and controls. However, 6-month values of RRIs, RRI-SDs, and baroreflex sensitivity were again lower in patients than controls. Conclusions Even mild strokes compromised cardiovagal modulation and baroreflex sensitivity. After 3 months, CAM had almost completely recovered. Recovery might be related to the mild stroke severity. Presumably, CAM recovery was also promoted by the increased application of cardiovascular medication. Yet, slight CAM dysfunction after 6 months suggests continuing autonomic vulnerability.
CRIS-Team WoS Importer:2022-06-24

Cavernoma-related epilepsy: Review and recommendations for management - Report of the Surgical Task Force of the ILAE Commission on Therapeutic Strategies - Rosenow, Felix; Alonso-Vanegas, Mario A.; Baumgartner, Christoph; Blümcke, Ingmar; Carreno, Maria; Gizewski, Elke R.; Hamer, Hajo; Knake, Susanne; Kahane, Philippe; Lueders, Hans O.; Mathern, Gary W.; Menzler, Katja; et al. (Epilepsia, 2013)
Cerebral cavernous malformations (CCMs) are well-defined, mostly singular lesions present in 0.4-0.9% of the population. Epileptic seizures are the most frequent symptom in patients with CCMs and have a great impact on social function and quality of life. However, patients with CCM-related epilepsy (CRE) who undergo surgical resection achieve postoperative seizure freedom in only about 75% of cases. This is frequently because insufficient efforts are made to adequately define and resect the epileptogenic zone. The Surgical Task Force of the Commission on Therapeutics of the International League Against Epilepsy (ILAE) and invited experts reviewed the pertinent literature on CRE. Definitions of definitive and probable CRE are suggested, and recommendations regarding the diagnostic evaluation and etiology-specific management of patients with CRE are made. Prospective trials are needed to determine when and how surgery should be done and to define the relations of the hemosiderin rim to the epileptogenic zone.© 2013 International League Against Epilepsy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cavernous hemangioma; Epilepsy surgery; Etiology; Outcome; Risk factors

CD133-Positive Membrane Particles in Cerebrospinal Fluid of Patients with Inflammatory and Degenerative Neurological Diseases - Bobinger, Tobias; May, Lisa-Sophie; Lücking, Hannes; Kloska, Stephan; Burkardt, Petra; Spitzer, Philipp; Maler, Juan M.; Corbeil, Denis; Huttner, Hagen (Frontiers in Cellular Neuroscience, 2017)
Background: Analysis of cerebrospinal fluid (CSF) is a frequently used diagnostic tool in a variety of neurological diseases. Recent studies suggested that investigating membrane particles enriched with the stem cell marker CD133 may offer new avenues for studying neurological disease. In this study, we evaluated the amount of membrane particle-associated CD133 in human CSF in neuroinflammatory and degenerative diseases. Methods: We compared the amount of membrane particle-associated CD133 in CSF samples collected from 45 patients with normal pressure hydrocephalus, parkinsonism, dementia, and cognitive impairment, chronic inflammatory diseases and 10 healthy adult individuals as controls. After ultracentrifugation of CSF, gel electrophoresis and immunoblotting using anti-CD133 monoclonal antibody 80B258 were performed. Antigen-antibody complexes were detected using chemiluminescence. Results: The amount of membrane particle-associated CD133 was significantly increased in patients with normal pressure hydrocephalus (p < 0.001), parkinsonism (p = 0.011) as well as in patients with chronic inflammatory disease (p = 0.008). Analysis of CSF of patients with dementia and cognitive impairment revealed no significant change compared with healthy individuals. Furthermore, subgroup analysis of patients with chronic inflammatory diseases demonstrated significantly elevated levels in individuals with relapsing-remitting multiple sclerosis (p = 0.023) and secondary progressive multiple sclerosis (SPMS; p = 0.010). Conclusion: Collectively, our study revealed elevated levels of membrane particle-associated CD133 in patients with normal pressure hydrocephalus, parkinsonism as well as relapsing-remitting and SPMS. Membrane glycoprotein CD133 may be of clinical value for several neurological diseases.
EVALuna2:22515

Central Autonomic Dysfunction Delays Recovery of Fingolimod Induced Heart Rate Slowing - Hilz, Max-Josef; Intravooth, Tassanai; Möller, Sebastian; Wang, Ruihao; Lee, De-Hyung; Koehn, Julia; Linker, Ralf (PLoS ONE, 2015)
In multiple sclerosis (MS) patients, Fingolimod may induce prolonged heart-rate slowing which might be caused by MS-related central autonomic lesions.To evaluate whether MS-patients with prolonged heart-rate slowing (> six hours) upon Fingolimod show cardiovascular-autonomic dysfunction before Fingolimod-initiation.Before Fingolimod-initiation, we recorded electrocardiographic RR-intervals (RRIs) and blood-pressure (BP) at rest, upon standing-up, during metronomic deep-breathing, Valsalva-maneuver, and "sustained-handgrip-exercise" in 21 patients with relapsing-remitting MS, and 20 healthy persons. We calculated sympathetic and parasympathetic cardiovascular parameters, including low- (LF) and high-frequency (HF) powers of RRI- and BP-oscillations, RRI-RMSSDs, RRI- and BP-changes during handgrip-exercise, parasympathetic heart-rate-slowing in relation to BP-overshoot after Valsalva-strain-release. We compared values of healthy persons and patients with and without prolonged heart-rate slowing after Fingolimod-initiation (ANOVA; significance: p<0.05).Upon Fingolimod-initiation, 7/21 patients had prolonged HR-slowing. Before Fingolimod, these patients had higher resting BP and higher BP increase during handgrip-exercise than had the other participants (p<0.05). They did not reduce parasympathetic HR-parameters upon standing-up. After Valsalva-strain-release, their parasympathetic HR-slowing in response to BP-overshoot was four times higher than in the other participants (p<0.05).The autonomic cardiovascular dysfunction in MS-patients with delayed HR-re-acceleration upon Fingolimod-initiation suggests that MS-related central autonomic lesions compromise HR-re-acceleration upon Fingolimod.German Clinical Trial Register DRKS00004548 http://drks-neu.uniklinik-freiburg.de/drks_web/setLocale_EN.do.
EVALuna2:22339

Cerebral aneurysm treatment using flow-diverting stents: in-vivo visualization of flow alterations by parametric colour coding to predict aneurysmal occlusion: preliminary results - Gölitz, Philipp; Struffert, Tobias; Roesch, Julie; Ganslandt, Oliver Thomas; Knossalla, Frauke; Dörfler, Arnd (European Radiology, 2015)
After deployment of flow-diverting stents (FDS), complete aneurysm occlusion is not predictable. This study investigated whether parametric colour coding (PCC) could allow in vivo visualization of flow alterations induced by FDS and identify favourable or adverse flow modulations.Thirty-six patients treated by FDS were analyzed. Preinterventional and postinterventional DSA-series were postprocessed by PCC and time-density curves (TDCs) were calculated. The parameters aneurysmal inflow, outflow, and relative time-to-peak (rTTP) were calculated. Preinterventional and postinterventional values were compared and related to occlusion rate.Postinterventional inflow showed a mean reduction of 37%, outflow of 51%, and rTTP a prolongation of 82%. Saccular aneurysm occlusion occurred if a reduction of at least 15% was achieved for inflow and 35% for outflow (sensitivity: 89%, specificity: 82%). Unchanged outflow and a slightly prolonged rTTP were associated with growth in one fusiform aneurysm.PCC allows visualization of flow alterations after FDS treatment, illustrating "flow diverting effects" by the TDC shape and indicating mainly aneurysmal outflow and lesser inflow changes. Quantifiable parameters (inflow, outflow, rTTP) can be obtained, thresholds for predicting aneurysm occlusion determined, and adverse flow modulations assumed. As a rapid intraprocedural tool, PCC might support the decision to implant more than one FDS.o After deployment of a flow-diverting stent, complete aneurysm occlusion is unpredictable. o Parametric colour coding offers new options for visualizing in vivo flow alterations non-invasively. o Quantifiable parameters, i.e., aneurysmal inflow/outflow can be obtained allowing prognostic stratification. o Rapid, intraprocedural application allows treatment monitoring, potentially contributing to patient safety.
EVALuna2:22356

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Cerebral lesion correlates of sympathetic cardiovascular activation in multiple sclerosis - Winder, Klemens; Linker, Ralf A.; Seifert, Frank; Wang, Ruihao; Lee, De Hyung; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, Max-Josef (Human Brain Mapping, 2019)
Cardiovascular autonomic dysfunction is common in multiple sclerosis (MS) and contributes significantly to disability. We hypothesized that cerebral MS-lesions in specific areas of the central autonomic network might account for imbalance of the sympathetic and parasympathetic cardiovascular modulation. Therefore, we used voxel-based lesion symptom mapping (VLSM) to determine associations between cardiovascular autonomic dysfunction and cerebral MS-related lesion sites. In 74 MS-patients (mean age 37.0 ± 10.5 years), we recorded electrocardiographic RR-intervals and systolic and diastolic blood pressure. Using trigonometric regressive spectral analysis, we assessed low (0.04–0.15 Hz) and high (0.15–0.5 Hz) frequency RR-interval-and blood pressure-oscillations and determined parasympathetically mediated RR-interval–high-frequency modulation, mainly sympathetically mediated RR-interval–low-frequency modulation, sympathetically mediated blood pressure-low-frequency modulation, and the ratios of sympathetic and parasympathetic RR-interval-modulation as an index of sympathetic-parasympathetic balance. Cerebral MS-lesions were analyzed on imaging scans. We performed a VLSM-analysis correlating parameters of autonomic dysfunction with cerebral MS-lesion sites. The VLSM-analysis showed associations between increased RR-interval low-frequency/high-frequency ratios and lesions most prominently in the left insular, hippocampal, and right frontal inferior opercular region, and a smaller lesion cluster in the right middle cerebellar peduncle. Increased blood pressure-low-frequency powers were associated with lesions primarily in the right posterior parietal white matter and again left insular region. Our data indicate associations between a shift of cardiovascular sympathetic-parasympathetic balance toward increased sympathetic modulation and left insular and hippocampal lesions, areas of the central autonomic network. The VLSM-analysis further distinguished between right inferior fronto-opercular lesions disinhibiting cardiac sympathetic activation and right posterior parietal lesions increasing sympathetic blood pressure modulation.
CRIS-Team Scopus Importer:2019-08-23
Keywords: autonomic dysfunction; insular lesion; multiple sclerosis; visceral arousal; voxel-based lesion symptom mapping

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Cerebrospinal fluid microRNAs are potential biomarkers of temporal lobe epilepsy and status epilepticus - Raoof, Rana; Jimenez-Mateos, Eva M.; Bauer, Sebastian; Tackenberg, Bjoern; Rosenow, Felix; Lang, Johannes; Onugoren, Muejgan Dogan; Hamer, Hajo; Huchtemann, Tessa; Koertvelyessy, Peter; Connolly, Niamh M. C.; Pfeiffer, Shona; et al. (Scientific Reports, 2017)
There is a need for diagnostic biomarkers of epilepsy and status epilepticus to support clinical examination, electroencephalography and neuroimaging. Extracellular microRNAs may be potentially ideal biomarkers since some are expressed uniquely within specific brain regions and cell types. Cerebrospinal fluid offers a source of microRNA biomarkers with the advantage of being in close contact with the target tissue and sites of pathology. Here we profiled microRNA levels in cerebrospinal fluid from patients with temporal lobe epilepsy or status epilepticus, and compared findings to matched controls. Differential expression of 20 microRNAs was detected between patient groups and controls. A validation phase included an expanded cohort and samples from patients with other neurological diseases. This identified lower levels of miR-19b in temporal lobe epilepsy compared to controls, status epilepticus and other neurological diseases. Levels of miR-451a were higher in status epilepticus compared to other groups whereas miR-21-5p differed in status epilepticus compared to temporal lobe epilepsy but not to other neurological diseases. Targets of these microRNAs include proteins regulating neuronal death, tissue remodelling, gliosis and inflammation. The present study indicates cerebrospinal fluid contains microRNAs that can support differential diagnosis of temporal lobe epilepsy and status epilepticus from other neurological and non-neurological diseases.
EVALuna2:22535

Cerebrovascular involvement in Fabry disease: current status of knowledge - Kolodny, Edwin; Fellgiebel, Andreas; Hilz, Max-Josef; Sims, Katherine; Caruso, Paul; Phan, Thanh G.; Politei, Juan; Manara, Renzo; Burlina, Alessandro (Stroke, 2015)
EVALuna2:22267

Cetuximab-Induced Aseptic Meningitis in a Patient with Colorectal Cancer: A Case Report and Review of Literature - Jäger, Jakob; Sprügel, Maximilian; Brunner, Tamara; Uhl, Martin; Schwab, Stefan; Vitali, Francesco; Wein, Axel; Volbers, Bastian (Case Reports in Neurology, 2022)
Cetuximab is a chimeric IgG1 monoclonal antibody against epidermal growth factor receptor. It is approved by the European medical agency for the treatment of RAS wild-type metastatic colorectal cancer and metastatic squamous cell cancer of the head and neck. Few cases of aseptic meningitis, primarily associated with the first administration of cetuximab in patients with squamous cell cancer, have been reported. So far, there was only 1 case in a patient with metastatic colorectal cancer. We report on a 50-year-old Caucasian patient with metastatic rectum carcinoma who suffered from headache, fever, and neck stiffness 3 h after the first administration of cetuximab (400 mg/m(2)). CSF examination revealed an excessive pleocytosis with a white blood cell count of 2,433/mu L. He was diagnosed with cetuximab-induced aseptic meningitis since clinical symptoms and CSF pleocytosis resolved within days, and further diagnostic workup revealed no infectious cause. Cetuximab-induced aseptic meningitis is a rare and severe drug reaction with predominance in treating squamous cell cancer of the head and neck. Clinical presentation and CSF findings suggest acute meningoencephalitis. In all reported cases, the course of the disease was benign and self-limited. Empiric antimicrobial and antiviral therapy are suggested until infectious causes can be ruled out. A lower dosage of cetuximab and a premedication including antihistamines and glucocorticosteroids may lower the risk of a re-occurrence if cetuximab therapy is continued.
CRIS-Team WoS Importer:2023-01-27

Characteristics and healthcare situation of adult patients with tuberous sclerosis complex in German epilepsy centers - Hamer, Hajo; Pfaefflin, Margarete; Baier, Hartmut; Boesebeck, Frank; Franz, Melanie; Holtkamp, Martin; Kurlemann, Gerhard; May, Theodorw.; Mayer, Thomas; Metzner, Mirjam; Steinhoff, Bernhard J.; Stodieck, Stefan; et al. (Epilepsy and Behavior, 2018)
The objective of the present study was to collect systematic data on the care of adult patients with tuberous sclerosis complex (TSC) in German epilepsy centers, to describe the characteristics of patients in this age group, and to clarify whether and how the recommended interdisciplinary care is implemented.This retrospective survey involved 12 major epilepsy centers in Germany. Aggregated data were collected based on an electronic questionnaire that addressed the sociodemographic data, characteristics of the epilepsy syndromes, and general healthcare setting of adult patients with TSC.The survey included 262 patients (mean age: 36.2±9.0years) with TSC, most of whom were reported to live in either a home for persons with a disability (37.0%), a residential care home (6.9%), or with their parents (31.1%). A further 13.0% were self-sustaining, and 8.8% were living with a partner. Most patients presented with focal (49.6%) or multifocal (33.2%) epilepsy, with complex partial, dialeptic, and automotor seizures in 66% of patients and generalized tonic-clonic seizures in 63%. Drug-refractory epilepsy was seen in 78.2% of patients, and 17.6% were seizure-free at the time of the survey. Of the 262 patients, presurgical diagnostics were performed in 27% and epilepsy surgery in 9%, which rendered 50% of these patients seizure-free. Renal screening had been performed in 56.1% within the last three years and was scheduled to be performed in 58.0%. Cases of renal angiomyolipoma were present in 46.9% of the patients. Dermatologic and pulmonary screenings were known to be planned for only few patients.Despite TSC being a multisystem disorder causing considerable impairment, every fifth adult patient is self-sustaining or living with a partner. In clinical practice, uncontrolled epilepsy and renal angiomyolipoma are of major importance in adult patients with TSC. Most patients suffer from focal or multifocal epilepsy, but epilepsy surgery is performed in less than 10% of these patients. Interdisciplinary TSC centers may help to optimize the management of patients with TSC regardless of age and ensure early and adequate treatment that also considers the advances in new therapeutic options.
EVALuna2:51820

Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Hagen, Manuel; Knappe, Ruben U.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Stroke, 2019)
Background and Purpose Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.
CRIS-Team WoS Importer:2019-06-18

Chronic Kidney Disease and Clinical Outcomes in Patients with Intracerebral Hemorrhage - Beuscher, Vanessa D.; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Lücking, Hannes; Lang, Stefan; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2020)
Background and Purpose: The influence of chronic kidney disease (CKD) on functional outcome in intracerebral hemorrhage (ICH) is scarcely investigated and reported findings are conflicting mostly because of nonaccounting for imbalances. Aim of the present study was to determine the impact of CKD on functional long-term outcome in ICH-patients. Methods: In this observational cohort study of spontaneous ICH-patients admitted to our Department of Neurology between 2006 and 2015 we investigated retrospectively as primary outcome the dichotomized functional status (modified-Rankin-Scale = 0-3-versus-4-6) at 12 months according to renal function (CKD versus non-CKD), including categorial estimates of the glomerular filtration rate subanalyses. Confounding was addressed by propensity-score(ps)-matching and adjusted multivariable regression analyses. Results: We identified 1076 eligible ICH-patients, of which 131 (12.2%) suffered from CKD on hospital admission. Confounders associated with CKD consisted of hypertension (P = .023), Diabetes mellitus (P = .001), prior ischemic stroke and/or transitory ischemic attack (TIA) (P = .021), congestive heart failure (P < .01), impaired liver function (P < .01), antiplatelet therapy (P = .01), poorer premorbid functional status (P < .01), and deep ICH-location (P = .006). After balancing for confounding, patients with CKD showed a significantly decreased rate of favorable functional outcome at 12 months (CKD:29 of 111(26.1%)-versus-non-CKD:78 of 206 (37.9%); P = .035). Subanalyses showed that stages of CKD were evenly associated with mortality at 12 months (GFR category G3a, OR:2.811; CI (1.130-6.994); P = .026; GFR category G3b, OR:1.874; CI (.694-5.058); P = .215; GFR category G4, OR:10.316; CI (1.976-53.856); P = .006; GFR category G5, OR:8.989; CI (1.900-42.518); P = .006). Conclusions: As compared to ICH-patients without CKD, those with CKD show increased rates of mortality and worse functional outcomes even after statistical correction for imbalanced baseline characteritsics. This finding is presumably linked to comorbidity and warrants further investigation in prospective studies.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Chronic kidney disease; critical care; intracerebral hemorrhage; mortality; outcome

Classification of paroxysmal events and the four-dimensional epilepsy classification system - Luders, Hans; Vaca, Guadalupe Fernandez-Baca; Akamatsu, Naoki; Amina, Shahram; Arzimanoglou, Alexis; Baumgartner, Christoph; Benbadis, Selim R.; Bleasel, Andrew; Bermeo-Ovalle, Adriana; Bozorgi, Alireza; Carreno, Mar; Devereaux, Michael; et al. (Epileptic Disorders, 2019)
This educational review describes the classification of paroxysmal events and a four-dimensional epilepsy classification system. Paroxysmal events are classified as epileptic and non-epileptic paroxysmal events. Non-epileptic events are, in turn, classified as psychogenic and organic paroxysmal events. The following four dimensions are used to classify epileptic paroxysmal events: ictal semiology, the epileptogenic zone, etiology, and comorbidities. Efforts are made to keep these four dimensions as independent as possible. The review also includes 12 educational vignettes and three more detailed case reports classified using the 2017 classification of the ILAE and the four-dimensional epilepsy classification. In addition, a case is described which is classified using the four-dimensional epilepsy classification with different degrees of precision by an emergency department physician, a neurologist, and an epileptologist. [Published with video sequences on www.epilepticdisorders.com].
EVALuna2:204546

Clinical and Imaging Characteristics in Noac-Related Intracerebral Hemorrhage. - Gerner, Stefan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clinical features, pathogenesis, and treatment of myasthenia gravis: a supplement to the Guidelines of the German Neurological Society - Melzer, Nico; Ruck, Tobias; Fuhr, Peter; Gold, Ralf; Hohlfeld, Reinhard; Marx, Alexander; Melms, Arthur; Tackenberg, Bjoern; Schalke, Berthold; Schneider-Gold, Christiane; Zimprich, Fritz; Meuth, Sven G.; et al. (Journal of Neurology, 2016)
Myasthenia gravis (MG) is an autoimmune antibody-mediated disorder of neuromuscular synaptic transmission. The clinical hallmark of MG consists of fluctuating fatigability and weakness affecting ocular, bulbar and (proximal) limb skeletal muscle groups. MG may either occur as an autoimmune disease with distinct immunogenetic characteristics or as a paraneoplastic syndrome associated with tumors of the thymus. Impairment of central thymic and peripheral self-tolerance mechanisms in both cases is thought to favor an autoimmune CD4(+) T cell-mediated B cell activation and synthesis of pathogenic high-affinity autoantibodies of either the IgG1 and 3 or IgG4 subclass. These autoantibodies bind to the nicotinic acetylcholine receptor (AchR) itself, or muscle-specific tyrosine-kinase (MuSK), lipoprotein receptor-related protein 4 (LRP4) and agrin involved in clustering of AchRs within the postsynaptic membrane and structural maintenance of the neuromuscular synapse. This results in disturbance of neuromuscular transmission and thus clinical manifestation of the disease. Emphasizing evidence from clinical trials, we provide an updated overview on immunopathogenesis, and derived current and future treatment strategies for MG divided into: (a) symptomatic treatments facilitating neuromuscular transmission, (b) antibody-depleting treatments, and
EVALuna2:22518

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Clinical relevance of source location in frontal lobe epilepsy and prediction of postoperative long-term outcome - Mu, Jie; Rampp, Stefan; Carrette, Evelien; Roessler, Karl; Sommer, Bjoern; Schmitt, Friedhelm Carl; De Tiege, Xavier; Hamer, Hajo; Boon, Paul; Pauli, Elisabeth; Blümcke, Ingmar; Zhou, Dong; et al. (Seizure-European Journal of Epilepsy, 2014)
To evaluate the value of magnetoencephalography (MEG) source localization in localization of epileptic activities and predicting surgical outcome in frontal lobe epilepsies (FLE).Forty-six patients with presurgical MEG evaluation and intractable FLE surgery (28 male patients) were analyzed retrospectively with a mean follow-up of 5 years. Dipole analysis was performed for MEG source imaging (MSI). The localization of dipole clusters in relation to the dominant hemisphere, lesions, resection cavity and functional cortex were analyzed. The predictive value of MSI in respect to clinical outcome with long-term postoperative follow up was evaluated.Interictal focal epileptic activities were found in 82.6% (38/46) patients with monofocal activity 81.6% (31/38) and multifocal activities 18.4% (7/38). Seizure free rate was 47.9% at the mean follow-up of 5.0 ± 4.0 years (median 11.5, range 2-57). Seizure recurrence mainly occurred in the first 1 year after surgery. In the monofocal epileptic activity group, 58.1% (18/31) of the patients were seizure free, predicitng postoperative seizure freedom better than multifocal localization 0% (0/7) (p=0.028). Dipole clusters were completely resected in 70.9% of monofocal activity patients, which had higher seizure free rates compared to partial resection (p=0.002). In patients with surgery in the dominant hemisphere, seizure control was less likely (p=0.006).MSI contributes to the clinical prediction of postoperative outcome in FLE patients. MSI may non-invasively disclose early epileptogenic lesions, pointing to a resectable lesion, and it then facilitates shortcut route of presurgical evaluation.
EVALuna2:7256

Clinical/scientific notes - Möller, Sebastian; Hilz, Max-Josef; Blinzler, C.; Köhn, Julia; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (Neurology, 2012)
CRIS-Team Scopus Importer:2022-08-05

Clinical, serological and genetic predictors of response to immunotherapy in anti-IgLON5 disease - Grueter, Thomas; Moellers, Franziska E.; Tietz, Anja; Dargvainiene, Justina; Melzer, Nico; Heidbreder, Anna; Strippel, Christine; Kraft, Andrea; Hoeftberger, Romana; Schoeberl, Florian; Thaler, Franziska S.; Wickel, Jonathan; et al. (Brain, 2022)
In a large cohort of anti-IgLON5 disease patients, Gruter et al. reveal early inflammatory CSF changes, subacute relapses, and association of HLA-DRB1*10:01 with higher autoantibody titre, consistent with a primary autoimmune nature of the disease. Immunotherapy is effective if initiated early, prior to major neurodegeneration.
CRIS-Team WoS Importer:2023-01-06

Clinical Studies Targeting Stroke and Ischemic Insults - Lundbye, Justin; Lyden, Patrick D.; Polderman, Kees H.; Schwab, Stefan (Therapeutic Hypothermia and Temperature Management, 2017)
EVALuna2:33131

CLIPPERS with longitudinally extensive transverse myelitis: Role of T versus B cells - Olmes, David G.; Metz, Imke; Lee, De-Hyung; Rosenwald, Andreas; Dörfler, Arnd; Brueck, Wolfgang; Linker, Ralf (Journal of the Neurological Sciences, 2018)
EVALuna2:35521

Cognitive functions over the course of 1 year in multiple sclerosis patients treated with disease modifying therapies - Utz, Kathrin S.; Lee, De-Hyung; Laemmer, Alexandra; Waschbisch, Anne; Linker, Ralf; Schenk, Thomas (Therapeutic Advances in Neurological Disorders, 2016)
Disease-modifying therapies (DMTs) are applied to delay or prevent disease progression in multiple sclerosis (MS). While this has mostly been proven for physical symptoms, available studies regarding long-term effects of DMTs on cognitive functions are rare and sometimes inconsistent due to methodological shortcomings. Particularly in the case of fingolimod, comprehensive data on cognitive functions are not yet available. Therefore, we set out to reliably assess cognitive functions in patients with relapsing-remitting MS (RRMS) treated with DMTs over 1 year.Cognitive functions were assessed with eight tests at three timepoints: baseline, 6-month follow up and 12-month follow up. First, we investigated whether the stability of cognitive functions (i.e. not falling below the 5% cut-off in more than one test) over 1 year in RRMS patients (n = 41) corresponds to the stability in healthy individuals (n = 40) of a previous study. Second, we compared the percentage of declined and improved patients in the different tests. Third, we compared patients treated with fingolimod (n = 22) with patients treated with natalizumab (n = 11) with regard to cognitive stability. Fourth, based on the patient data, the Reliable Change Index was applied to compute cut-offs for reliable cognitive change.Approximately 75% of RRMS patients treated with DMTs remained stable over the course of 1 year. The Paced Auditory Serial Addition Test (PASAT) and the Spatial Recall Test (SPART), produced improvements in 12.5% and 30.6%, respectively, probably due to practice effects. Patients treated with fingolimod did not differ from patients treated with natalizumab with regard to cognitive stability.Cognitive functions remain relatively stable under DMT treatment over 1 year, irrespective of the type of medication. Furthermore, the tests PASAT and SPART should be interpreted cautiously in studies examining performance changes over time. The provided RCI norms may help clinicians to determine whether a difference in two measurements observed in a RRMS patient is reliable.
EVALuna2:22528

Cognitive impairment correlates with autonomic dysfunction in patients with a history of traumatic brain injury - Hilz, Max-Josef; de Rojas Leal, Carmen; Roy, Sankanika; Liu, Mao; Hoesl, Katharina M.; Winder, Klemens; Wang, Ruihao (2018)
EVALuna2:201954

Comment on 2018 ESC/ESH Guidelines for the management of arterial hypertension - Haeusler, Karl Georg; Huttner, Hagen; Kuramatsu, Joji (European Heart Journal, 2019)
CRIS-Team Scopus Importer:2019-07-26

Comparative Socioeconomic Study Of Patients In Germany With Dravet Syndrome, Refractory Epilepsy Or Epilepsy In Seizure Remission, And Their Caregivers - Strzelczyk, A.; Schubert-Bast, S.; Bast, T.; Bettendorf, U.; Hamer, Hajo; Herting, A.; Kalski, M.; Kay, L.; Kieslich, M.; Klein, K. M.; Kluger, G.; Kurlemann, G.; et al. (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Comparison of scoring tools for the prediction of in-hospital mortality in status epilepticus - Reindl, Caroline; Knappe, Ruben U.; Sprügel, Maximilian; Sembill, Jochen; Müller, Tamara; Hamer, Hajo; Huttner, Hagen; Madzar, Dominik (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: Several scoring tools have been developed for the prognostication of outcome after status epilepticus (SE). In this study, we compared the performances of STESS (Status Epilepticus Severity Score), mSTESS (modified STESS), EMSE-EAL (Epidemiology-based Mortality Score in Status Epilepticus- Etiology, Age, Level of Consciousness) and END-IT (Encephalitis-NCSE-Diazepam resistance-Image abnormalities-Tracheal intubation) in predicting in-hospital mortality after SE. METHOD: Data collected retrospectively from a cohort of 287 patients with SE were used to calculate STESS, mSTESS, EMSE-EAL, and END-IT scores. The differences between the scores' performances were determined by means of area under the ROC curve (AUC) comparisons and McNemar testing. RESULTS: The in-hospital mortality rate was 11.8%. The AUC of STESS (0.628; 95% confidence interval (CI), 0.529-0.727) was similar to that of mSTESS (0.620; 95% CI, 0.510-0.731), EMSE-EAL (0.556; 95% CI, 0.446-0.665), and END-IT (0.659; 95% CI, 0.550-0.768; p > .05 for each comparison) in predicting in-hospital mortality. STESS with a cutoff of 3 was found to have lowest specificity and number of correctly classified episodes. EMSE-EAL with a cutoff at 40 had highest specificity and showed a trend towards more correctly classified episodes while sensitivity tended to be low. END-IT with a cutoff of 3 had the most balanced sensitivity-specificity ratio. CONCLUSIONS: EMSE-EAL is as easy to calculate as STESS and tended towards higher diagnostic accuracy. Adding information on premorbid functional status to STESS did not enhance outcome prediction. END-IT was not superior to other scores in prediction of in-hospital mortality despite including information of diagnostic work-up and response to initial treatment.
EVALuna2:201931

Comparison of Two Automated Computed Tomography Perfusion Applications to Predict the Final Infarct Volume After Thrombolysis in Cerebral Infarction 3 Recanalization - Mühlen, Iris; Sprügel, Maximilian; Hölter, Philip; Hock, Stefan; Knott, Michael; Huttner, Hagen; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (Stroke, 2022)
Background: Several automated computed tomography perfusion software applications have been developed to provide support in the definition of ischemic core and penumbra in acute ischemic stroke. However, the degree of interchangeability between software packages is not yet clear. Our study aimed to evaluate 2 commonly used automated perfusion software applications (Syngo.via and RAPID) for the indication of ischemic core with respect to the follow-up infarct volume (FIV) after successful recanalization and with consideration of the clinical impact. Methods: Retrospectively, 154 patients with large vessel occlusion of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy with a consequent Thrombolysis in Cerebral Infarction 3 result within 2 hours after computed tomography perfusion, were included. Computed tomography perfusion core volumes were assessed with both software applications with different thresholds for relative cerebral blood flow (rCBF). The results were compared with the FIV on computed tomography within 24 to 36 hours after recanalization. Bland-Altman was applied to display the levels of agreement and to evaluate systematic differences. Results: Highest correlation between ischemic core volume and FIV without significant differences was found at a threshold of rCBF<38% for the RAPID software (r=0.89, P<0.001) and rCBF<25% for the Syngo software (r=0.87, P<0.001). Bland-Altman analysis revealed best agreement in these settings. In the vendor default settings (rCBF<30% for RAPID and rCBF<20% for Syngo) correlation between ischemic core volume and FIV was also high (RAPID: r=0.88, Syngo: r=0.86, P<0.001), but mean differences were significant (P<0.001). The risk of critical overestimation of the FIV was higher with rCBF<38% (RAPID) and rCBF<25% (Syngo) than in the default settings. Conclusions: By adjusting the rCBF thresholds, comparable results with reliable information on the FIV after complete recanalization can be obtained both with the RAPID and Syngo software. Keeping the software specific default settings means being more inclusive in patient selection, but forgo the highest possible accuracy in the estimation of the FIV.
CRIS-Team WoS Importer:2022-05-13

COMPASS 31 bladder sub-scores correlate with uroflow parameters in patients with relapsing-remitting multiple sclerosis - Wang, Ruihao; Fröhlich, Kilian; Winder, Klemens; Singer, W.; Lee, D.; Linker, R.; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Compromised cardiovascular autonomic modulation in patient with acute ischemic stroke improves after three & six months - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Köhn, Julia; Siedler, Gabriela; Winder, Klemens; Gerner, Stefan; Schwab, Stefan; Koehrmann, M.; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2021)
CRIS-Team WoS Importer:2021-07-23

Consensus statement on the definition of neurogenic supine hypertension in cardiovascular autonomic failure by the American Autonomic Society (AAS) and the European Federation of Autonomic Societies (EFAS) : Endorsed by the European Academy of Neurology (EAN) and the European Society of Hypertension (ESH) - Fanciulli, Alessandra; Jordan, Jens; Biaggioni, Italo; Calandra-Buonaura, Giovanna; Cheshire, William P.; Cortelli, Pietro; Eschlboeck, Sabine; Grassi, Guido; Hilz, Max-Josef; Kaufmann, Horacio; Lahrmann, Heinz; Mancia, Giuseppe; et al. (Clinical Autonomic Research, 2018)
PURPOSE: Patients suffering from cardiovascular autonomic failure often develop neurogenic supine hypertension (nSH), i.e., high blood pressure (BP) in the supine position, which falls in the upright position owing to impaired autonomic regulation. A committee was formed to reach consensus among experts on the definition and diagnosis of nSH in the context of cardiovascular autonomic failure. METHODS: As a first and preparatory step, a systematic search of PubMed-indexed literature on nSH up to January 2017 was performed. Available evidence derived from this search was discussed in a consensus expert round table meeting in Innsbruck on February 16, 2017. Statements originating from this meeting were further discussed by representatives of the American Autonomic Society and the European Federation of Autonomic Societies and are summarized in the document presented here. The final version received the endorsement of the European Academy of Neurology and the European Society of Hypertension. RESULTS: In patients with neurogenic orthostatic hypotension, nSH is defined as systolic BP ≥ 140 mmHg and/or diastolic BP ≥ 90 mmHg, measured after at least 5 min of rest in the supine position. Three severity degrees are recommended: mild, moderate and severe. nSH may also be present during nocturnal sleep, with reduced-dipping, non-dipping or rising nocturnal BP profiles with respect to mean daytime BP values. Home BP monitoring and 24-h-ambulatory BP monitoring provide relevant information for a customized clinical management. CONCLUSIONS: The establishment of expert-based criteria to define nSH should standardize diagnosis and allow a better understanding of its epidemiology, prognosis and, ultimately, treatment.
EVALuna2:213464

Consensus statements and recommendations from the ESO-Karolinska Stroke Update Conference, Stockholm 11-13 November 2018 - Ahmed, Niaz; Audebert, Heinrich; Turc, Guillaume; Cordonnier, Charlotte; Christensen, Hanne; Sacco, Simona; Sandset, Else Charlotte; Ntaios, George; Charidimou, Andreas; Toni, Danilo; Pristipino, Christian; Köhrmann, Martin; et al. (European Stroke Journal, 2019)
The purpose of the European Stroke Organisation-Karolinska Stroke Update Conference is to provide updates on recent stroke therapy research and to give an opportunity for the participants to discuss how these results may be implemented into clinical routine. The meeting started 22 years ago as Karolinska Stroke Update, but since 2014 it is a joint conference with European Stroke Organisation. Importantly, it provides a platform for discussion on the European Stroke Organisation guidelines process and on recommendations to the European Stroke Organisation guidelines committee on specific topics. By this, it adds a direct influence from stroke professionals otherwise not involved in committees and work groups on the guideline procedure. The discussions at the conference may also inspire new guidelines when motivated. The topics raised at the meeting are selected by the scientific programme committee mainly based on recent important scientific publications. This year's European Stroke Organisation-Karolinska Stroke Update Meeting was held in Stockholm on 11-13 November 2018. There were 11 scientific sessions discussed in the meeting including two short sessions. Each session except the short sessions produced a consensus statement (Full version with background, issues, conclusions and references are published as web-material and at and ) and recommendations which were prepared by a writing committee consisting of session chair(s), scientific secretary and speakers. These statements were presented to the 250 participants of the meeting. In the open meeting, general participants commented on the consensus statement and recommendations and the final document were adjusted based on the discussion from the general participants Recommendations (grade of evidence) were graded according to the 1998 Karolinska Stroke Update meeting with regard to the strength of evidence. Grade A Evidence: Strong support from randomised controlled trials and statistical reviews (at least one randomised controlled trial plus one statistical review). Grade B Evidence: Support from randomised controlled trials and statistical reviews (one randomised controlled trial or one statistical review). Grade C Evidence: No reasonable support from randomised controlled trials, recommendations based on small randomised and/or non-randomised controlled trials evidence.
CRIS-Team WoS Importer:2019-09-24

Contrast-enhanced angiographic computed tomography for detection of aneurysm remnants after clipping: a comparison with digital subtraction angiography in 112 clipped aneurysms - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver Thomas; Lang, Stefan; Knossalla, Frauke; Dörfler, Arnd (Neurosurgery, 2014)
For preclusion of remnants after aneurysm clipping, a reliable, noninvasive imaging technique is desirable.To evaluate the reliability of optimized angiographic computed tomography with intravenous contrast agent injection (ivACT) in detecting remnants after aneurysmal clipping compared with digital subtraction angiography (DSA), the gold standard.We included 84 patients with 112 clipped cerebral aneurysms of the anterior circulation. For treatment, 116 clips of cobalt and 57 clips of titanium alloy were used. In each patient, we performed an ivACT with dual rotational acquisition and a DSA. Data from ivACT were postprocessed with a dual-volume technique with newly implemented reconstructions modes. Aneurysm remnants were measured, classified, and correlated with DSA by 2 raters.In total, 12 remnants were revealed by DSA, meaning a prevalence of 11%. IvACT demonstrated a sensitivity of 75% to 92% and a specificity of 99% in detecting remnants up to a minimal size of 0.7 × 0.3 mm. Classification of remnants by ivACT was identical to that by DSA, and assessment of size showed a significant correlation with DSA (P < .001). No significant differences between cobalt and titanium alloy were revealed concerning artifacts.Optimized ivACT with enhanced postprocessing demonstrated high sensitivity and specificity in detecting remnants after aneurysm clipping in the anterior circulation. Classification and assessment of remnant size and detection of relevant parent artery stenosis showed high accuracy of ivACT compared with DSA. Our results indicate that ivACT might become a noninvasive alternative to DSA for postsurgical control.
EVALuna2:22328

Cooling in intracerebral hemorrhage (CINCH) trial: Protocol of a randomized German-Austrian clinical trial - Kollmar, Rainer; Juettler, Eric; Huttner, Hagen; Dörfler, Arnd; Staykov, Dimitre; Kallmünzer, Bernd; Schmutzhard, Erich; Schwab, Stefan; Broessner, Gregor (International Journal of Stroke, 2012)
Background: Intracerebral hemorrhage accounts for up to 15% of all strokes and is frequently associated with poor functional outcome and high mortality. So far, there is no clear evidence for a specific therapy, apart from general stroke unit or neurointensive care and management of secondary complications. Promising experimental and pilot clinical data support the use of therapeutic hypothermia after intracerebral hemorrhage. Aims: The study aims to determine if therapeutic hypothermia improves survival rates and reduces cerebral lesion volume after large intracerebral hemorrhage compared with conventional treatment. Material and methods: The Cooling in IntraCerebral Hemorrhage trial is a prospective, multicenter, interventional, randomized, parallel, two-arm (1:1) phase II trial with blinded end-point adjudication. Enrolment: 50 patients (age: 18 to 65 years) with large (25 to 64ml on cranial computertomography), primary intracerebral hemorrhage of the basal ganglia or thalamus within 6 to 18h after symptom onset are randomly allocated to therapeutic hypothermia for eight-days or conventional temperature management. In the therapeutic hypothermia group, a target temperature of 35·0°C is achieved by endovascular catheters and followed by slow controlled rewarming. Data analysis is based on the intent-to-treat population. The primary outcome measure of the study is the development in total lesion volume on cranial computertomography (intracerebral hemorrhage plus perihemorrhagic edema on day 8±0·5 and day 11±0·5 after intracerebral hemorrhage) and the mortality after 30 days. Secondary end-points are the in-hospital mortality, mortality, and functional outcome (modified Rankin Scale and Barthel-Index) after 90 and 180 days. Safety measures include any adverse events associated with therapeutic hypothermia. Discussion: In the face of a lack of evidence-based therapies for patients with large intracerebral hemorrhage, new promising approaches are desperately needed, but need evaluation in randomized controlled trials. Conclusion: The results of Cooling in IntraCerebral Hemorrhage trial are believed to directly influence future therapy of large intracerebral hemorrhage. © 2012 The Authors. International Journal of Stroke © 2012 World Stroke Organization.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Edema; Hypothermia; Intracerebral hemorrhage; Neuroprotection; Stroke

Coregistrating magnetic source and magnetic resonance imaging for epilepsy surgery in focal cortical dysplasia - Kasper, Burkhard; Roessler, Karl; Hamer, Hajo; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Rösch, Julie; Mennecke, Angelika; Wellmer, Joerg; Sommer, Bjoern; Lorber, Bogdan; Lang, Johannes D.; et al. (NeuroImage: Clinical, 2018)
Background: Epilepsy surgery for focal cortical dysplasia type II (FCD II) offers good chances for seizure freedom, but remains a challenge with respect to lesion detection, defining the epileptogenic zone and the optimal resection strategy. Integrating results from magnetic source imaging from magnetoencephalography (MEG) with magnetic resonance imaging (MRI) including MRI postprocessing may be useful for optimizing these goals. Methods: We here present data from 21 adult FCD II patients, investigated during a 10 year period and evaluated including magnetic source imaging. 16 patients had epilepsy surgery, i.e. histopathologically verified FCD II, and a long follow up. We present our analysis of epileptogenic zones including MEG in relation to structural data according to MRI data and relate these results to surgical outcomes. Results: FCD II in our cohort was characterized by high MEG yield and localization accuracy and MEG showed impact on surgical success-rates. MEG source localizations were detected in 95.2% of patients and were as close as 12.3 ± 8,1 mm to the MRI-lesion. After a mean follow up of >3 years, we saw >80% Engel I outcomes, with more favourable outcomes when the MEG source was completely resected (Fishers exact test 0,033). Conclusion: We argue for a high value of conducting a combined MEG-MRI approach in the presurgical workup and the resection strategy in patients with FCD II related epilepsy.
EVALuna2:35523

Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05

Correction to: Gap Analysis Regarding Prognostication in Neurocritical Care: A Joint Statement from the German Neurocritical Care Society and the Neurocritical Care Society - Wartenberg, Katja E.; Hwang, David Y.; Haeusler, Karl Georg; Muehlschlegel, Susanne; Sakowitz, Oliver W.; Madžar, Dominik; Hamer, Hajo; Rabinstein, Alejandro A.; Greer, David M.; Hemphill, J. Claude; Meixensberger, Juergen; Varelas, Panayiotis N. (Neurocritical Care, 2019)
This article was updated to correct the spelling of Karl Georg Haeusler.
CRIS-Team Scopus Importer:2019-08-30

Correction to: Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons (Neurological Sciences, (2020), 41, 9, (2521-2529), 10.1007/s10072-020-04349-x) - Köhn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2021)
The article “Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons”, written by Julia Koehn, Ruihao Wang, Carmen de Rojas Leal, Bernd Kallmünzer, Klemens Winder, Martin Köhrmann, Rainer Kollmar, Stefan Schwab and Max J. Hilz, was originally published Online First without Open Access. After publication in volume 41, issue 9, page 2521–2529 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http:// creat iveco mmons. org/ licen ses/ by/4.0. The original article has been corrected.
CRIS-Team Scopus Importer:2021-07-16

Correlation between clinical severity and extent of autonomic cardiovascular impairment in the acute phase of subarachnoid hemorrhage - Borutta, Matthias; Gerner, Stefan T.; Möser, Philip; Hölter, Philip; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen B.; Schwab, Stefan; Kuramatsu, Joji; Köhn, Julia (Journal of Neurology, 2022)
Background and aim: To assess associations between clinical severity and possible dysfunction of autonomic cardiovascular modulation within the acute phase after spontaneous subarachnoid hemorrhage (SAH). Methods: In this prospective observational study, in 51 patients with spontaneous SAH, Hunt-and-Hess scores (H&H) were assessed and cardiovascular autonomic modulation was monitored within 24 h after SAH-onset. From 5 min time-series of R–R-intervals (RRI) and blood-pressure (BP) recordings, we calculated autonomic parameters including time-domain [RRI-coefficient-of-variation (RRI-CV) and square-root-of-the-mean-squared-differences-of-successive-RRIs (RMSSD)] and frequency-domain parameters [low- and high-frequency-powers of RRI- and BP-modulation (RRI-LF-, RRI-HF-, SBP-LF-powers) and RRI-total-powers]. Data were compared to those of 20 healthy volunteers. Results: RRI- and BP-values did not differ between groups. Yet, parameters of sympathetic (RRI-LF-powers 141.0 (18.9–402.4) ms2 vs 442.3 (246.8–921.2) ms2, p = 0.001) and total autonomic modulation (RRI-CV 2.4 (1.2–3.7) ms2 vs 3.7 (3.1–5.3) ms2, p = 0.001) were significantly lower in patients than in controls. Subgroup analyses (patients with H&H < 3 vs H&H ≥ 3) and Spearman-rank-correlations revealed increasing loss of sympathetic (RRI-LF-powers 338.6 (179.7–710.4) ms2 vs 72.1 (10.1–175.9) ms2, p = 0.001, rho = − 0.524) and total autonomic modulation (RRI-CV 3.5 (2.3–5.4) ms2 vs 1.6 (1.0–2.8) ms2, p < 0.001, rho = − 0.519) with higher H&H-scores. Multiple-logistic-regression underlined the significant influence of H&H-scores on sympathetic (RRI-LF-powers, p = 0.033) and total autonomic modulation (RRI-CV, p = 0.040) compared to possible confounders (e.g., age, intubation). Conclusion: Within the acute phase, spontaneous SAH induces a decrease in sympathetic and total autonomic cardiovascular modulation. Higher H&H-scores were associated with increasing autonomic dysfunction and may therefore augment the risk of cardiovascular complications and poor clinical outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autonomic nervous system; Heart rate variability; Hunt and Hess; Subarachnoid hemorrhage

Corrigendum: “Electrodiagnostic assessment of the autonomic nervous system: A consensus statement endorsed by the American Autonomic Society, American Academy of Neurology, and the International Federation of Clinical Neurophysiology” (Clinical Neurophysiology (2021) 132(2) (666–682), (S138824572030585X), (10.1016/j.clinph.2020.11.024)) - Cheshire, William P.; Freeman, Roy; Gibbons, Christopher H.; Cortelli, Pietro; Wenning, Gregor K.; Hilz, Max-Josef; Spies, Judith M.; Lipp, Axel; Sandroni, Paola; Wada, Naoki; Mano, Tadaaki; Kim, Hyun Ah; et al. (Clinical Neurophysiology, 2021)
The authors would like to inform you that the name of the 11th author, Tadaaki Mano, was incorrectly stated as Akiko Mano in their published article. The correct details updated as above. The authors apologise for this error.
CRIS-Team Scopus Importer:2021-03-26

Corrigendum: Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-dimensional Projections of Three-dimensional Diffusion MRI Data - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja Wolfgang (Frontiers in Neurology, 2017)
[This corrects the article on p. 239 in vol. 6, PMID: 26635717.].
EVALuna2:22534

Corticosteroids in patients with vestibular neuritis: An updated meta-analysis - Bogdanova, Anna; Dlugaiczyk, Julia; Heckmann, Josef Georg; Schwab, Stefan (Acta Neurologica Scandinavica, 2022)
Vestibular neuritis is a common neuro-otological entity. Therapeutically, corticosteroids are advised, although the evidence is limited. The objective of this review is to update meta-analyses of clinical trials that address the question of whether patients with vestibular neuritis treated with corticosteroids show better recovery than control patients. The electronic databases Medline, Scopus and Cochrane were searched for clinical trials for the years 1970-2020 without language restriction. Data were extracted, and outcome parameters were subjected to conventional and cumulative meta-analysis using a commercially available software program (). Finally, 15 trials with 363 participants in the treatment and 489 in the control groups were identified and could be included. Eight studies were judged to be at high risk of bias. The odds ratio (OR) for good outcome in the acute phase was 3.1 (95% CI 1.2-7.8; p = .015) in favour of steroid treatment leading to the number needed to treat (NNT) = 6 (95% CI 4-23). The odds ratio (OR) for restoration of vestibular function in the follow-up was 2.4 (95% CI 1.3-4.4; p = .004) for the benefit of steroid treatment resulting in a NNT = 7 (95% CI 5-18). The results of the cumulative statistics did not differ. The risk of adverse effects was higher in patients treated with steroids with an OR of 10.9 (95% CI 1.3-93.8; p = .015) and an estimated number needed to harm (NNH) = 4 (95% CI 3-19). The advantage for corticosteroids remained when differentiating between patients who participated in randomized or non-randomized clinical trials. Steroid treatment in vestibular neuritis resulted in a statistically significant benefit compared to control therapies. However, broad heterogeneity of the studies, mostly low-grade quality of studies, high risk of bias and broad confidence intervals put the findings into perspective allowing only a careful judgement of some benefit of corticosteroids. The findings, however, support the call for an adequately powered and well-designed randomized controlled trial to re-evaluate the effectiveness of corticosteroids.
CRIS-Team WoS Importer:2022-09-09

Costs of epilepsy and cost-driving factors in children, adolescents, and their caregivers in Germany - Riechmann, Janna; Strzelczyk, Adam; Reese, Jens P.; Boor, Rainer; Stephani, Ulrich; Langner, Cornelia; Neubauer, Bernd A.; Oberman, Bettina; Philippi, Heike; Rochel, Michael; Seeger, Juergen; Seipelt, Peter; et al. (Epilepsia, 2015)
To provide first data on the cost of epilepsy and cost-driving factors in children, adolescents, and their caregivers in Germany.A population-based, cross-sectional sample of consecutive children and adolescents with epilepsy was evaluated in the states of Hessen and Schleswig-Holstein (total of 8.796 million inhabitants) in all health care sectors in 2011. Data on socioeconomic status, course of epilepsy, and direct and indirect costs were recorded using patient questionnaires.We collected data from 489 children and adolescents (mean age ± SD 10.4 ± 4.2 years, range 0.5-17.8 years; 264 [54.0%] male) who were treated by neuropediatricians (n = 253; 51.7%), at centers for social pediatrics ("Sozialpaediatrische Zentren," n = 110, 22.5%) and epilepsy centers (n = 126; 25.8%). Total direct costs summed up to EUR1,619 ± EUR4,375 per participant and 3-month period. Direct medical costs were due mainly to hospitalization (47.8%, EUR774 ± EUR3,595 per 3 months), anticonvulsants (13.2%, EUR213 ± EUR363), and ancillary treatment (9.1%, EUR147 ± EUR344). The total indirect costs amounted to EUR1,231 ± EUR2,830 in mothers and to EUR83 ± EUR593 in fathers; 17.4% (n = 85) of mothers and 0.6% (n = 3) of fathers reduced their working hours or quit work because of their child's epilepsy. Independent cost-driving factors were younger age, symptomatic cause, and polytherapy with anticonvulsants. Older age, active epilepsy, symptomatic cause, and polytherapy were independent predictors of higher antiepileptic drug (AED) costs, whereas younger age, longer epilepsy duration, symptomatic cause, disability, and parental depression were independent predictors for higher indirect costs.Treatment of children and adolescents with epilepsy is associated with high direct costs due to frequent inpatient admissions and high indirect costs due to productivity losses in mothers. Direct costs are age-dependent and higher in patients with symptomatic epilepsy and polytherapy. Indirect costs are higher in the presence of a child's disability and parental depression.
EVALuna2:22370

Could the 2017 ILAE and the four-dimensional epilepsy classifications be merged to a new “Integrated Epilepsy Classification”? - Rosenow, Felix; Akamatsu, Naoki; Bast, Thomas; Bauer, Sebastian; Baumgartner, Christoph; Benbadis, Selim; Bermeo-Ovalle, Adriana; Beyenburg, Stefan; Bleasel, Andrew; Bozorgi, Alireza; Brázdil, Milan; Carreño, Mar; et al. (Seizure-European Journal of Epilepsy, 2020)
Over the last few decades the ILAE classifications for seizures and epilepsies (ILAE-EC) have been updated repeatedly to reflect the substantial progress that has been made in diagnosis and understanding of the etiology of epilepsies and seizures and to correct some of the shortcomings of the terminology used by the original taxonomy from the 1980s. However, these proposals have not been universally accepted or used in routine clinical practice. During the same period, a separate classification known as the “Four-dimensional epilepsy classification” (4D-EC) was developed which includes a seizure classification based exclusively on ictal symptomatology, which has been tested and adapted over the years. The extensive arguments for and against these two classification systems made in the past have mainly focused on the shortcomings of each system, presuming that they are incompatible. As a further more detailed discussion of the differences seemed relatively unproductive, we here review and assess the concordance between these two approaches that has evolved over time, to consider whether a classification incorporating the best aspects of the two approaches is feasible. To facilitate further discussion in this direction we outline a concrete proposal showing how such a compromise could be accomplished, the “Integrated Epilepsy Classification”. This consists of five categories derived to different degrees from both of the classification systems: 1) a “Headline” summarizing localization and etiology for the less specialized users, 2) “Seizure type(s)”, 3) “Epilepsy type” (focal, generalized or unknown allowing to add the epilepsy syndrome if available), 4) “Etiology”, and 5) “Comorbidities & patient preferences”.
CRIS-Team Scopus Importer:2020-03-17
Keywords: 2017 ILAE classification; Classification; Classification merger; Epilepsy classification; Four-dimensional epilepsy; Integrated epilepsy classsifcation; Semiological seizure classification

Critique of the 2017 epileptic seizure and epilepsy classifications - Lüders, Hans; Akamatsu, Naoki; Amina, Shahram; Baumgartner, Christoph; Benbadis, Selim; Bermeo-Ovalle, Adriana; Bleasel, Andrew; Bozorgi, Alireza; Carreño, Mar; Devereaux, Michael; Fernandez-Baca Vaca, Guadalupe; Francione, Stefano; et al. (Epilepsia, 2019)
This article critiques the International League Against Epilepsy (ILAE) 2015-2017 classifications of epilepsy, epileptic seizures, and status epilepticus. It points out the following shortcomings of the ILAE classifications: (1) they mix semiological terms with epileptogenic zone terminology; (2) simple and widely accepted terminology has been replaced by complex terminology containing less information; (3) seizure evolution cannot be described in any detail; (4) in the four-level epilepsy classification, level two (epilepsy category) overlaps almost 100% with diagnostic level one (seizure type); and (5) the design of different classifications with distinct frameworks for newborns, adults, and patients in status epilepticus is confusing. The authors stress the importance of validating the new ILAE classifications and feel that the decision of Epilepsia to accept only manuscripts that use the ILAE classifications is premature and regrettable.
CRIS-Team Scopus Importer:2019-05-07
Keywords: classification; epileptogenic zone; etiology; semiology

CT-derived left ventricular global strain: a head-to-head comparison with speckle tracking echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Mansour, H.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (International Journal of Cardiovascular Imaging, 2019)
We assessed CT-derived left ventricular strain in a cohort of patients referred for transcatheter aortic valve implantation (TAVI) and validated it against 2 dimensional speckle tracking echocardiography as the gold standard. 65 consecutive patients with symptomatic aortic valve stenosis referred for CT imaging prior to TAVI were included in this analysis. For all patients, retrospectively ECG-gated multi-phase functional CT data sets acquired with identical reconstruction parameters were available. All data sets were acquired using a third generation dual source system. In all patients, multiphase reconstructions in increments of 10% of the cardiac cycle were rendered (slice thickness 0.75, increment 0.5 mm, medium smooth reconstruction kernel) and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). Additional functional reconstructions for dynamic assessment and quantification of strain were processed. Multiplanar reconstructions (MPR) of the left ventricle similar to standard echocardiographic 4, 2 and apical 3 chamber views were rendered in CT. Similar to echocardiographic longitudinal strain, the perimeter of the left ventricle was manually traced within the myocardium and peak maximal shortening as a parameter representing longitudinal strain was calculated for each view and averaged to obtain a marker for global longitudinal strain (CT perimeter-derived strain). Furthermore, for quantification of 3-dimensional strain, endocardial and epicardial borders of myocardium were marked in six short axis views and peak maximum 3- dimensional strain of the myocardium was calculated in standard six basal, six mid and four apical segments. 3-dimensional strain values of the 16 standard segments as well as perimeter-derived strain values in the three standard windows were averaged to obtain global strain. Echocardiography was performed in all patients before CT data acquisition. Digital loops were acquired from three apical views (four-, two-, and three chamber views). For assessment of 2 dimensional global longitudinal strain (GLS), recordings were processed with acoustic-tracking software allowing offline semiautomated speckle-based strain analyses. The mean age of all 65 patients was 81 ± 5 years. The mean echocardiographic ejection fraction and mean echocardiographic GLS were 50 ± 12% and −13.6 ± 4.5%, respectively. The mean CT-derived peak 3-dimensional global strain and mean peak strain derived by perimeter was 43.2 ± 13.5% and −11.2 ± 3.5%, respectively. Both CTderived global 3D-strain and perimeter derived strain showed a significant correlation to GLS derived by echocardiography (r = −0.8, p < 0.0001 for 3D strain and r = 0.71, p < 0.0001 for perimeter-derived strain). Bland-Altman analysis showed a systematic underestimation (i. e. worse strain values) of CT perimeter-derived strain compared to GLS by echocardiography (mean difference −2.4% with 95% limits of agreement between 4% to −9%). ROC Curve analysis assuming a normal GLS when less than −18% showed that a CT-derived peak 3-dimensional global strain cut-off-value of 45% has a sensitivity of 91% and a specificity of 60% for detecting normal left ventricular strain (AUC 0.81, p = 0.001). For CT perimeter-derived strain, a cut-off value of −12%—assuming a normal echocardiographic GLS when less than −18%—achieved a sensitivity of 82% and a specificity of 61% (AUC of 0.82, p = 0.001) for detecting abnormal left ventricular strain. Using dedicated software, assessment of CT-derived left ventricular strain is feasible and comparable to strain derived by echocardiographic 2 dimensional speckle tracking.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Cardiac CT angiography; Echocardiography; Left ventricular global strain; Speckle tracking

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve implantation: a head-to-head comparison with echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Schuhbaeck, A.; Röther, Jens; Feyrer, R.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

CT-derived left ventricular global strain in aortic valve stenosis patients: A comparative analysis pre and post transcatheter aortic valve implantation - Ammon, Fabian; Bittner, D.; Röther, Jens; Mekkhala, N.; Hell, M.; Schuhbaeck, A.; Gitsioudis, Gitsios; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: We assessed the potential of CT strain to detect changes in myocardial function in patients referred for TAVI pre and post intervention. PATIENTS AND METHODS: 25 consecutive patients with symptomatic aortic valve stenosis in whom TAVI had been performed were included in this analysis. Functional CT data sets acquired before and 3 to 6 months after TAVI were available. Multiphase reconstructions in increments of 10% of the cardiac cycle were rendered and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). For quantification of left ventricular strain, multiplanar reconstructions of the left ventricle in standard 4 chamber, 2 chamber as well as apical 3 chamber views were rendered. The perimeter of the left ventricle was traced dynamically through the cardiac cycle. Peak strain was calculated for each patient pre and post intervention. Furthermore, for quantification of 3-dimensional maximum principal strain, 2 volumetric regions of interests (VOI) were placed per each basal, mid and apical segment of the previously mentioned MPRs and peak maximal principal strain was calculated. Maximum principal strain as well as perimeter-derived longitudinal strain values in the three standard windows were averaged to obtain global strain. RESULTS: 25 patients were included in this analysis (mean age 78 ± 9 years, 13 males). Peak global maximum principal strain was significantly higher at follow-up compared to baseline (0.46 ± 0.19 vs. 0.59 ± 0.18, respectively, p = 0.001). Similarly global longitudinal strain derived by perimeter was significantly lower - implying better contraction - compared to baseline (-8.6% ± 2.8% vs. -9.8% ± 2.6%, respectively, p = 0.006). CONCLUSION: Using dedicated software, assessment of CT derived left ventricular strain is feasible. In patients treated with transcatheter aortic valve replacement, CT-derived parameters of global myocardial strain improve onshort-term follow-up.
EVALuna2:35994

Current and historical individual data about exposure of workers in the rayon industry to carbon disulfide and their validity in calculating the cumulative dose - Göen, Thomas; Schramm, Axel; Baumeister, Thomas; Uter, Wolfgang; Drexler, Hans (International Archives of Occupational and Environmental Health, 2014)
The objective of the study was to investigate how exposure to carbon disulfide (CS2) in a rayon-manufacturing plant has changed within two decades and whether it is possible to calculate valid data for the individual cumulative exposure.The data for CS2 concentration in air and biological exposure monitoring (2-thio-1,3-thiaxolidine-4-carboxylic acid (TTCA) in urine) from two cross-sectional studies, performed in 1992 (n = 362) and 2009 (n = 212) in a German rayon-manufacturing plant, were compared to data obtained from company-internal measurements between the studies.Using the data from the cross-sectional studies and company-internal data, cumulative external exposure and the cumulative internal exposure were calculated for each worker. External and internal CS2 exposure of the employees decreased from 1992 (medians 4.0 ppm and 1.63 mgTTCA/g creatinine) to 2009 (medians 2.5 ppm and 0.86 mg/g). However, company-internal CS2 data do not show a straight trend for this period. The annual medians of the company-internal measurement of external exposure to CS2 have varied between 2.7 and 8.4 ppm, in which median values exceeded 5 ppm generally since 2000. The annual medians for the company-internal biomonitoring assessment ranged between 1.2 and 2.8 mg/g creatinine. The cumulative CS2 exposure ranged from 8.5 to 869.5 ppm years for external exposure and between 1.30 and 176.2 mg/g creatinine years for the internal exposure. Significant correlations were found between the current air pollution and the internal exposure in 2009 but also between the cumulative external and internal CS2 exposure.Current exposure data, usually collected in cross-sectional studies, rarely allow a reliable statement on the cumulative dose, because of higher exposure in the past and of fluctuating courses of exposure. On the other hand, company-internal exposure data may be affected by non-representative measurement strategies. Some verification of the reliability of cumulative exposure data may be possible by testing the correlation between cumulative exposure data of external assessment and biological monitoring.
EVALuna2:5395

Current value of intraoperative electrocorticography (iopECoG) - Roessler, Karl; Heynold, Elisabeth; Buchfelder, Michael; Stefan, Hermann; Hamer, Hajo (Epilepsy & Behavior, 2019)
Objective: Intraoperative electrocorticography (iopECoG) can contribute to delineate the resection borders of the anticipated epileptogenic zone in epilepsy surgery. However, it has several caveats that should be considered to avoid incorrect interpretation during intraoperative monitoring.
CRIS-Team WoS Importer:2019-04-04

Dabigatran Plasma Levels in Acute Cerebrovascular Events - Volbers, Bastian; Köhrmann, Martin; Kallmünzer, Bernd; Kurka, Natalia; Breuer, Lorenz; Ringwald, Juergen; Schwab, Stefan (Journal of Stroke and Cerebrovascular Diseases, 2016)
Oral anticoagulation with dabigatran was shown to be effective for stroke prevention in patients with nonvalvular atrial fibrillation without the need for laboratory monitoring. However, a recent publication based on data of the Randomized Evaluation of Long-Term Anticoagulation Therapy study reported that ischemic stroke and bleeding outcomes are correlated with dabigatran plasma concentration (DPC). DPC was determined at a prespecified time point and correlated with cardiovascular events at any time during follow-up. Because of the known variability of DPC, among others depending on renal function, this approach might compromise data evaluation. We report on dabigatran plasma levels in acute cerebrovascular events.Consecutive patients with acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) while taking dabigatran were retrospectively identified if admission DPC was available. DPC was determined using the diluted thrombin time (Hemoclot (HYPHEN BioMed, Neuville sur Oise, France)). Creatinine clearance (CrCl) was determined by measuring creatinine in plasma and 24-hour urine.Fifteen AIS and 4 ICH patients were included. Median DPC on admission was significantly higher in ICH patients than in AIS patients (135 ng/mL [interquartile range IQR 79-218] and 69.1 ng/mL [IQR 20.6-85.0], respectively; P = .035). Increased CrCl (values above published normal range) was correlated with lower median DPC (60 ng/mL [IQR 10-69] versus 100 ng/mL [IQR 79-157] in patients with normal CrCl, P = .01).Higher DPC was found in ICH patients than in AIS patients in temporal proximity to the event. Both decreased and increased renal functions seem to have an important influence on DPC.
EVALuna2:15996

Data-driven re-referencing of intracranial EEG based on independent component analysis (ICA) - Michelmann, Sebastian; Treder, Matthias S.; Griffiths, Benjamin; Kerren, Casper; Roux, Frederic; Wimber, Maria; Rollings, David; Sawlani, Vijay; Chelvarajah, Ramesh; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; Hamer, Hajo; et al. (Journal of Neuroscience Methods, 2018)
BACKGROUND: Intracranial recordings from patients implanted with depth electrodes are a valuable source of information in neuroscience. They allow for the unique opportunity to record brain activity with high spatial and temporal resolution. A common pre-processing choice in stereotactic EEG (S-EEG) is to re-reference the data with a bipolar montage. In this, each channel is subtracted from its neighbor, to reduce commonalities between channels and isolate activity that is spatially confined. NEW METHOD: We challenge the assumption that bipolar reference effectively performs this task. To extract local activity, the distribution of the signal source of interest, interfering distant signals, and noise need to be considered. Referencing schemes with fixed coefficients can decrease the signal to noise ratio (SNR) of the data, they can lead to mislocalization of activity and consequently to misinterpretation of results. We propose to use Independent Component Analysis (ICA), to derive filter coefficients that reflect the statistical dependencies of the data at hand. RESULTS: We describe and demonstrate this on human S-EEG recordings. In a simulation with real data, we quantitatively show that ICA outperforms the bipolar referencing operation in sensitivity and importantly in specificity when revealing local time series from the superposition of neighboring channels. COMPARISON WITH EXISTING METHOD(S): We argue that ICA already performs the same task that bipolar referencing pursues, namely undoing the linear superposition of activity and will identify activity that is local. CONCLUSIONS: When investigating local sources in human S-EEG, ICA should be preferred over re-referencing the data with a bipolar montage.
EVALuna2:201937

Deficits in cognitive estimation in patients with right-frontal and right-temporal lobe epilepsy Neuropsychologische Schätzdefizite bei rechtsfrontaler und rechtstemporaler Epilepsie - Schwarz, Michael; Benkowitsch, Edith; Schneider, Katrin; Walther, Katrin; Hamer, Hajo (Zeitschrift für Neuropsychologie, 2021)
Background: Previous studies revealed a right-hemispheric dominance for cognitive estimation processes. Objectives: This study explored estimation impairments in patients with focal temporal and frontal lobe epilepsies. Methods: 109 patients (right frontal, left frontal, right temporal-mesial, right temporal-neocortical, left temporal-mesial, left temporal-neocortical) and a control group with 67 subjects were included. All subjects underwent an extensive neuropsychological assessment including the Test zum kognitiven Schätzen (TKS; Brand et al., 2002). Hypothesis: It was expected that right-hemispheric lesions would be associated with impairments in cognitive estimation. Results: Patients with right-frontal and right-temporal mesial focus showed significant estimation deficits compared to the other groups. Conclusion: This study shows that the right hemisphere dominantly participates in cognitive estimation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cognitive estimation; epilepsy; frontal lobe; hippocampus; laterality; temporal lobe

Delayed action does not always require the ventral stream: a study on a patient with visual form agnosia - Hesse, Constanze; Schenk, Thomas (Cortex, 2014)
It has been suggested that while movements directed at visible targets are processed within the dorsal stream, movements executed after delay rely on the visual representations of the ventral stream (Milner & Goodale, 2006). This interpretation is supported by the observation that a patient with ventral stream damage (D.F.) has trouble performing accurate movements after a delay, but performs normally when the target is visible during movement programming. We tested D.F.'s visuomotor performance in a letter-posting task whilst varying the amount of visual feedback available. Additionally, we also varied whether D.F. received tactile feedback at the end of each trial (posting through a letter box vs posting on a screen) and whether environmental cues were available during the delay period (removing the target only vs suppressing vision completely with shutter glasses). We found that in the absence of environmental cues patient D.F. was unaffected by the introduction of delay and performed as accurately as healthy controls. However, when environmental cues and vision of the moving hand were available during and after the delay period, D.F.'s visuomotor performance was impaired. Thus, while healthy controls benefit from the availability of environmental landmarks and/or visual feedback of the moving hand, such cues seem less beneficial to D.F. Taken together our findings suggest that ventral stream damage does not always impact the ability to make delayed movements but compromises the ability to use environmental landmarks and visual feedback efficiently.
EVALuna2:22298

Demyelinating disease and anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies: a case report - Waschbisch, Anne; Kallmünzer, Bernd; Schwab, Stefan; Gölitz, Philipp; Vincent, Angela; Lee, De Hyung; Linker, Ralf (BMC Research Notes, 2014)
Anti-N-methyl-D-aspartate receptor immunoglobulin G antibodies directed against the GluN1 subunit are considered highly specific for anti-N-methyl-D-aspartate receptor encephalitis, a severe clinical syndrome characterized by seizures, psychiatric symptoms, orofacial dyskinesia and autonomic dysfunction.Here we report a 33 year old Caucasian male patient with clinically definite multiple sclerosis who was found to be positive for anti-N-methyl-D-aspartate receptor antibodies. Rituximab therapy was initiated. On the 18 months follow-up visit the patient was found to be clinically stable, without typical signs of anti-N-methyl-D-aspartate receptor encephalitis.Our findings add to the growing evidence for a possible association between anti-N-methyl-D-aspartate receptor encephalitis and demyelinating diseases.
EVALuna2:22345

Dexamethasone in Patients with Spontaneous Intracerebral Hemorrhage: An Updated Meta-Analysis - Wintzer, Stephanie; Heckmann, Josef Georg; Huttner, Hagen; Schwab, Stefan (Cerebrovascular Diseases, 2020)
Background: Spontaneous intracerebral hemorrhage (ICH) is a frequent cerebrovascular disorder and still associated with high mortality and poor clinical outcomes. The purpose of this review was to update a 15-year-old former meta-Analysis on randomized clinical trials (RCTs) addressing the question of whether ICH patients treated with dexamethasone have better outcomes than controls. Methods: The electronic databases PubMed, SCOPUS, and Cochrane as well as web platforms on current clinical trials were searched for the years 1970-2020 without constriction on language. Data were extracted and outcomes were pooled for conventional and cumulative meta-Analysis using a commercial software program (www.Meta-Analysis.com). Results: Finally, 7 RCTs were identified and analyzed including 248 participants in the dexamethasone groups and 242 in the control groups. Five studies showed a high risk of bias. The overall relative risk (RR) for death was 1.32 (95% confidence interval [CI] 0.99-1.76; p = 0.06) and did not differ significantly between the 2 groups. After exclusion of studies with high risk of bias, the RR for death was 1.37 (95% CI 0.54-3.42; p = 0.51). The RR for poor outcome did not differ significantly between the 2 groups analyzed for all included studies (RR = 0.69; 95% CI 0.47-1; p = 0.05) and after exclusion of studies with high risk of bias (RR = 0.7; 95% CI 0.45-1.08; p = 0.11). The RR for complications did not differ significantly including all studies (RR = 1.29; 95% CI 0.77-2.17; p = 0.34) and after exclusion of studies with high risk of bias (RR = 1.27; 95% CI 0.18-8.89; p = 0.81). The cumulative statistics delivered no other results; however, it pointed out fewer complications over time in the dexamethasone group. Conclusion: Clear evidence of a beneficial or negative effect of dexamethasone is still lacking. Modern RCTs or observational studies with propensity design are necessary to evaluate the efficacy and safety of treatment with dexamethasone in patients with ICH.
CRIS-Team Scopus Importer:2020-10-02

Diagnosis of spontaneous cervical artery dissection may be associated with increased prevalence of posttraumatic stress disorder - Speck, Verena; Noble, Adam; Kollmar, Rainer; Schenk, Thomas (Journal of Stroke and Cerebrovascular Diseases, 2014)
Receiving information that one has a dissected cervical artery, which can cause a stroke at any time, is obviously traumatic, but details about the psychiatric and psychosocial sequelae are not known. We investigated the prevalence of and risk factors for posttraumatic stress disorder (PTSD) in patients with spontaneous cervical artery dissection (CD) and the impact of PTSD on their psychosocial functioning.Patients admitted because of CD between 2006 and 2010 were retrospectively examined using a diagnostic PTSD measure (Posttraumatic Diagnostic Scale). Patients between 2011 and 2012 were examined prospectively. To identify potential predictors for PTSD, we examined all patients' stress coping strategies (brief COPE inventory), anxiety and depression (Hospital Anxiety and Depression Scale), impairment by preventive medication, time since diagnosis and their neurologic (modified Rankin Scale) and cognitive status. To identify the psychosocial impact of PTSD, we examined quality of life (Short-Form 36).Data of 47 retrospectively contacted patients and 15 prospectively examined patients were included. Twenty-eight patients (45.2%) met the diagnostic criteria for PTSD. A significantly reduced health-related quality of life (HRQoL) was found in 27 patients (43.5%) for mental health and in 8 patients (12.9%) for physical health. Results of logistic regression analysis revealed that the use of maladaptive coping strategies was predictive of the disorder (P < .0001). Age, sex, mRS score, impairment caused by medication, and time since diagnosis were not predictive for PTSD. The presence of PTSD itself was the only significant predictor for reduced mental HRQol (P = .0004). Age, sex, mRS score, impairment caused by medication, and total Hospital Anxiety and Depression Scale score were not predictive for reduced mental HRQoL.PTSD seems to occur frequently in patients with CD and is associated with reduced mental HRQoL. Because the presence of a maladaptive coping style is correlated with PTSD, teaching patients better coping skills might be helpful.
EVALuna2:22243

Diagnostic value of prehospital ECG in acute stroke patients - Bobinger, Tobias; Kallmnzer, Bernd; Kopp, Markus; Kurka, Natalia; Heider, Stefan; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Neurology, 2017)
To investigate the diagnostic yield of prehospital ECG monitoring provided by emergency medical services in the case of suspected stroke.Consecutive patients with acute stroke admitted to our tertiary stroke center via emergency medical services and with available prehospital ECG were prospectively included during a 12-month study period. We assessed prehospital ECG recordings and compared the results to regular 12-lead ECG on admission and after continuous ECG monitoring at the stroke unit.Overall, 259 patients with prehospital ECG recording were included in the study (90.3% ischemic stroke, 9.7% intracerebral hemorrhage). Atrial fibrillation (AF) was detected in 25.1% of patients, second-degree or greater atrioventricular block in 5.4%, significant ST-segment elevation in 5.0%, and ventricular ectopy in 9.7%. In 18 patients, a diagnosis of new-onset AF with direct clinical consequences for the evaluation and secondary prevention of stroke was established by the prehospital recordings. In 2 patients, the AF episodes were limited to the prehospital period and were not detected by ECG on admission or during subsequent monitoring at the stroke unit. Of 126 patients (48.6%) with relevant abnormalities in the prehospital ECG, 16.7% received medical antiarrhythmic therapy during transport to the hospital, and 6.4% were transferred to a cardiology unit within the first 24 hours in the hospital.In a selected cohort of patients with stroke, the in-field recordings of the ECG detected a relevant rate of cardiac arrhythmia. The results can add to the in-hospital evaluation and should be considered in prehospital care of acute stroke.
EVALuna2:22506

Diagnostik Lumbar Puncture - Step by Step - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
EVALuna2:204469

Die Relevanz der neuen DIVI-Empfehlung zur Struktur und Ausstattung von Intensivstationen für die Neuromedizin - Waydhas, Christian; Hoffmann, Florian; van den Hooven, Thomas; Markewitz, Andreas; Riessen, Reimer; Schwab, Stefan; Unterberg, Andreas (Der Nervenarzt, 2023)
EVALuna2:536993

Dietary fatty acids and susceptibility to multiple sclerosis - Haase, Stefanie; Haghikia, Aiden; Gold, Ralf; Linker, Ralf (Multiple sclerosis journal, 2018)
The gut microbiome as well as dietary habits have recently been established as environmental contributors to the pathogenesis of multiple sclerosis (MS), a T-cell-mediated autoimmune disease of the central nervous system (CNS).To summarize recent findings on the Janus-faced effects of dietary short-chain fatty acids (SCFAs) and long-chain fatty acids (LCFAs) on T-cell immunity with a special focus on the gut and the microbiome as an interface linking diet and T-cell responses during MS.Review article.The autoimmune basis of MS most likely stems from an imbalance between pro-inflammatory T helper cell (Th)1 and Th17 cells and anti-inflammatory or regulatory mechanisms including regulatory T cells (Treg). Hence, the rationale of currently available therapeutic interventions is to either suppress pathogenic Th1/Th17 and/or to foster Treg responses. Dietary fatty acids are often discussed for their detrimental role in MS. However, recent studies investigating saturated fatty acids in animal models of MS revealed harmful as well as beneficial effects depending on their aliphatic chain length.Dietary SCFAs constitute interesting candidates as safe and potent add-on therapy in the immunomodulatory treatment armamentarium for relapsing-remitting MS.
EVALuna2:22562

Dietary Fatty Acids Directly Impact Central Nervous System Autoimmunity via the Small Intestine - Haghikia, Aiden; Joerg, Stefanie; Duscha, Alexander; Berg, Johannes; Manzel, Arndt; Waschbisch, Anne; Hammer, Anna; Lee, De-Hyung; May, Caroline; Wilck, Nicola; Balogh, Andras; Ostermann, Annika I.; et al. (Immunity, 2015)
Growing empirical evidence suggests that nutrition and bacterial metabolites might impact the systemic immune response in the context of disease and autoimmunity. We report that long-chain fatty acids (LCFAs) enhanced differentiation and proliferation of T helper 1 (Th1) and/or Th17 cells and impaired their intestinal sequestration via p38-MAPK pathway. Alternatively, dietary short-chain FAs (SCFAs) expanded gut T regulatory (Treg) cells by suppression of the JNK1 and p38 pathway. We used experimental autoimmune encephalomyelitis (EAE) as a model of T cell-mediated autoimmunity to show that LCFAs consistently decreased SCFAs in the gut and exacerbated disease by expanding pathogenic Th1 and/or Th17 cell populations in the small intestine. Treatment with SCFAs ameliorated EAE and reduced axonal damage via long-lasting imprinting on lamina-propria-derived Treg cells. These data demonstrate a direct dietary impact on intestinal-specific, and subsequently central nervous system-specific, Th cell responses in autoimmunity, and thus might have therapeutic implications for autoimmune diseases such as multiple sclerosis.
EVALuna2:22371

Differential influence of hippocampal subfields to memory formation: insights from patients with temporal lobe epilepsy - Coras, Roland; Pauli, Elisabeth; Li, Jinmei; Schwarz, Michael; Roessler, Karl; Buchfelder, Michael; Hamer, Hajo; Stefan, Hermann; Blümcke, Ingmar (Brain, 2014)
To clarify the anatomical organization of human memory remains a major challenge in clinical neuroscience. Experimental data suggest dentate gyrus granule cells play a major role in memory acquisition, i.e. pattern separation and rapid pattern completion, whereas hippocampal CA1 neurons are implicated in place memory and autobiographical memory retrieval. Patients with temporal lobe epilepsy present with a broad spectrum of memory impairment, which can be assessed during clinical examination. Although long seizure histories may contribute to a pathophysiological reorganization of functional connectivity, surgical resection of the epileptic hippocampus offers a unique possibility to anatomically study the differential contribution of hippocampal subfields to compromised learning and memory in humans. Herein, we tested the hypothesis of hippocampal subfield specialization in a series of 100 consecutive patients with temporal lobe epilepsy submitted to epilepsy surgery. Memory profiles were obtained from intracarotid amobarbital testing and non-invasive verbal memory assessment before surgery, and correlated with histopathologically quantified cell loss pattern in hippocampal subfields obtained from the same patients using the new international consensus classification for hippocampal sclerosis proposed by the International League against Epilepsy (HS ILAE). Interestingly, patients with CA1 predominant cell loss (HS ILAE Type 2; n = 13) did not show declarative memory impairment and were indistinguishable from patients without any hippocampal cell loss (n = 19). In contrast, 63 patients with neuronal loss affecting all hippocampal subfields including CA1, CA4 and dentate gyrus (HS ILAE Type 1), or predominant cell loss in CA4 and partially affecting also CA3 and dentate gyrus (HS ILAE Type 3, n = 5) showed significantly reduced declarative memory capacities (intracarotid amobarbital testing: P < 0.001; verbal memory: P < 0.05). Our results suggested an alternative model of how memory processing can be organized amongst hippocampal subfields, and that CA1 pyramidal cells are less critically involved in declarative human memory acquisition compared to dentate gyrus granule cells or CA4/CA3 pyramidal cells.
EVALuna2:7242

Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter

Directional coupling of slow and fast hippocampal gamma with neocortical alpha/beta oscillations in human episodic memory - Griffiths, Benjamin J.; Parish, George; Roux, Frederic; Michelmann, Sebastian; van der Plas, Mircea; Kolibius, Luca D.; Chelvarajah, Ramesh; Rollings, David T.; Sawlani, Vijay; Hamer, Hajo; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Episodic memories hinge upon our ability to process a wide range of multisensory information and bind this information into a coherent, memorable representation. On a neural level, these 2 processes are thought to be supported by neocortical alpha/beta desynchronization and hippocampal theta/gamma synchronization, respectively. Intuitively, these 2 processes should couple to successfully create and retrieve episodic memories, yet this hypothesis has not been tested empirically. We address this by analyzing human intracranial electroencephalogram data recorded during 2 associative memory tasks. We find that neocortical alpha/beta (8 to 20 Hz) power decreases reliably precede and predict hippocampal "fast" gamma (60 to 80 Hz) power increases during episodic memory formation; during episodic memory retrieval, however, hippocampal "slow" gamma (40 to 50 Hz) power increases reliably precede and predict later neocortical alpha/beta power decreases. We speculate that this coupling reflects the flow of information from the neocortex to the hippocampus during memory formation, and hippocampal pattern completion inducing information reinstatement in the neocortex during memory retrieval.
EVALuna2:204498

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

Direct oral anticoagulants versus Vitamin K antagonists after a recent ischemic stroke or TIA- a pooled individual patient data analysis - Seiffge, David; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Direct oral anticoagulants versus vitamin K antagonists after recent ischemic stroke in patients with atrial fibrillation - Seiffge, David J.; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (Annals of Neurology, 2019)
Objective: We compared outcomes after treatment with direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) and a recent cerebral ischemia. Methods: We conducted an individual patient data analysis of seven prospective cohort studies. We included patients with AF and a recent cerebral ischemia (<3 months before starting oral anticoagulation) and a minimum follow-up of 3 months. We analyzed the association between type of anticoagulation (DOAC versus VKA) with the composite primary endpoint (recurrent ischemic stroke [AIS], intracerebral hemorrhage [ICH], or mortality) using mixed-effects Cox proportional hazards regression models; we calculated adjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: We included 4,912 patients (median age, 78 years [interquartile range IQR, 71–84]; 2,331 [47.5%] women; median National Institute of Health Stroke Severity Scale at onset, 5 [IQR, 2–12]); 2,256 (45.9%) patients received VKAs and 2,656 (54.1%) DOACs. Median time from index event to starting oral anticoagulation was 5 days (IQR, 2–14) for VKAs and 5 days (IQR, 2–11) for DOACs (p = 0.53). There were 262 acute ischemic strokes (AISs; 4.4%/year), 71 intracranial hemorrrhages (ICHs; 1.2%/year), and 439 deaths (7.4%/year) during the total follow-up of 5,970 patient-years. Compared to VKAs, DOAC treatment was associated with reduced risks of the composite endpoint (HR, 0.82; 95% CI, 0.67–1.00; p = 0.05) and ICH (HR, 0.42; 95% CI, 0.24–0.71; p < 0.01); we found no differences for the risk of recurrent AIS (HR, 0.91; 95% CI, 0.70–1.19; p = 0.5) and mortality (HR, 0.83; 95% CI, 0.68–1.03; p = 0.09). Interpretation: DOAC treatment commenced early after recent cerebral ischemia related to AF was associated with reduced risk of poor clinical outcomes compared to VKA, mainly attributed to lower risks of ICH. ANN NEUROL 2019.
CRIS-Team Scopus Importer:2019-05-17

Disability-Adjusted Life-Years Associated with Intracerebral Hemorrhage and Secondary Injury - Haupenthal, David; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (JAMA Network Open, 2021)
Importance: Intracerebral hemorrhage (ICH) contributes significantly to the global burden of disease. Objective: To examine the association of ICH and secondary injury with disability-adjusted life-years (DALYs) for the individual patient. Design, Setting, and Participants: This cohort study was conducted using data from the Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage study. Consecutive patients admitted to a single tertiary care center from January 1, 2006, to December 31, 2015, were included. The sample comprised patients with oral anticoagulation-associated ICH (OAC-ICH) or primary spontaneous ICH (non-OAC-ICH). Statistical analysis was conducted from October 1 to December 31, 2020. Exposures: ICH occurrence and secondary injury. Main Outcomes and Measures: DALYs, years of life lost (YLL), and years lived with disability (YLD) were analyzed by hematoma location, ICH volume, and secondary injury (ie, hematoma expansion [HE], intraventricular hemorrhage [IVH], and perihemorrhagic edema [PHE]). Results: Among 1322 patients with ICH, 615 (46.5%) were women and the mean (SD) age at hospital admission was 71 (13) years; ICH was associated with a mean (SD) of 9.46 (8.08) DALYs, 5.72 (8.29) YLL, and 3.74 (5.95) YLD. There were statistically significant differences in mean (SD) DALYs by extent of hematoma volume (< 10 mL ICH: 7.05 [6.79] DALYs; 10-30 mL ICH: 9.91 [8.35] DALYs; >30 mL ICH: 12.42 [8.47] DALYs; P <.001) and ICH location (deep location: 10.60 [8.35] DALYs; lobar location: 8.18 [7.63] DALYs; cerebellum: 8.14 [6.80] DALYs; brainstem: 12.63 [9.21] DALYs; P <.001). Regarding population-level disease burden of secondary injuries after ICH, there was a statistically significant difference in mean (SD) by injury type, with 0.94 (3.19) DALYs for HE, 2.45 (4.16) DALYs for IVH, and 1.96 (2.66) DALYs for PHE (P <.001) among the entire ICH cohort. Regarding individual-level exposure to secondary injuries after ICH, there were a mean (SD) 7.14 (6.62) DALYs for HE, 4.58 (4.75) DALYs for IVH, and 3.35 (3.28) DALYs for PHE among patients with ICH affected by secondary injuries. Conclusions and Relevance: These findings suggest that there is a high burden of disability associated with ICH and secondary injuries, and the findings may guide public health strategies. The study findings further suggest that IVH and PHE may be relevant for the overall outcome of patients with ICH, that DALYs may represent a viable outcome parameter for studies to evaluate treatment outcomes in ICH research, and that IVH and PHE may represent potential treatment targets..
CRIS-Team Scopus Importer:2021-07-30

Disseminated Multifocal Intracerebral Bleeding Events in Three Coronavirus Disease 2019 Patients on Extracorporeal Membrane Oxygenation As Rescue Therapy. - Bihlmaier, Karl; Coras, Roland; Willam, Carsten; Grampp, Steffen; Jabari, Samir; Eichhorn, Philip; Haller, Florian; Kuramatsu, Joji; Schwab, Stefan; Castellanos, Ixchel; Birkholz, Torsten; Schüttler, Jürgen; et al. (Critical Care Explorations, 2020)
Objectives: To describe three coronavirus disease 2019 patients suffering from acute respiratory distress syndrome under venovenous extracorporeal membrane oxygenation therapy and tight anticoagulation monitoring presenting a novel pattern of multifocal brain hemorrhage in various degrees in all cerebral and cerebellar lobes. Design: Clinical observation of three patients. Post mortem examinations. Setting: Two ICUs at the University Hospital Erlangen. Patients: Three patients (medium age 56.6 yr, two male with hypertension and diabetes, one female with no medical history) developed severe acute respiratory distress syndrome on the basis of a severe acute respiratory syndrome coronavirus 2 infection. All required mechanical ventilation and venovenous extracorporeal membrane oxygenation support. Interventions: Clinical observation, CT, data extraction from electronic medical records, and post mortem examinations. Main Results: We report on an unusual multifocal bleeding pattern in the white matter in three cases with severe acute respiratory distress syndrome due to coronavirus disease 2019 undergoing venovenous extracorporeal membrane oxygenation therapy. Bleeding pattern with consecutive herniation was found in CT scans as well as in neuropathologic post mortem examinations. Frequency for this unusual brain hemorrhage in coronavirus disease 2019 patients with extracorporeal membrane oxygenation therapy at our hospital is currently 50%, whereas bleeding events in extracorporeal membrane oxygenation patients generally occur at 10-15%. Conclusions: Multifocality and high frequency of the unusual white matter hemorrhage pattern suggest a coherence to coronavirus disease 2019. Neuropathological analyses showed circumscribed thrombotic cerebrovascular occlusions, which eventually led to microvascular and later on macrovascular disseminated bleeding events. However, signs of cerebrovascular inflammation could not be detected. Polymerase chain reaction analyses of brain tissue or cerebrospinal fluid remained negative. Increased susceptibility for fatal bleeding events should be taken into consideration in terms of systemic anticoagulation strategies in coronavirus disease 2019.
EVALuna2:313697
Keywords: acute respiratory distress syndrome; cerebral microhemorrhage; coronavirus disease 2019; extracorporeal membrane oxygenation; intracerebral bleeding

Distinct Effects of Chronic Dopaminergic Stimulation on Hippocampal Neurogenesis and Striatal Doublecortin Expression in Adult Mice - Salvi, Rachele; Steigleder, Tobias; Schlachetzki, Johannes; Waldmann, Elisabeth; Schwab, Stefan; Winner, Beate; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Neuroscience, 2016)
While adult neurogenesis is considered to be restricted to the hippocampal dentate gyrus (DG) and the subventricular zone (SVZ), recent studies in humans and rodents provide evidence for newly generated neurons in regions generally considered as non-neurogenic, e.g., the striatum. Stimulating dopaminergic neurotransmission has the potential to enhance adult neurogenesis in the SVZ and the DG most likely via D2/D3 dopamine (DA) receptors. Here, we investigated the effect of two distinct preferential D2/D3 DA agonists, Pramipexole (PPX), and Ropinirole (ROP), on adult neurogenesis in the hippocampus and striatum of adult naïve mice. To determine newly generated cells in the DG incorporating 5-bromo-2'-deoxyuridine (BrdU) a proliferation paradigm was performed in which two BrdU injections (100 mg/kg) were applied intraperitoneally within 12 h after a 14-days-DA agonist treatment. Interestingly, PPX, but not ROP significantly enhanced the proliferation in the DG by 42% compared to phosphate buffered saline (PBS)-injected control mice. To analyze the proportion of newly generated cells differentiating into mature neurons, we quantified cells co-expressing BrdU and Neuronal Nuclei (NeuN) 32 days after the last of five BrdU injections (50 mg/kg) applied at the beginning of 14-days DA agonist or PBS administration. Again, PPX only enhanced neurogenesis in the DG significantly compared to ROP- and PBS-injected mice. Moreover, we explored the pro-neurogenic effect of both DA agonists in the striatum by quantifying neuroblasts expressing doublecortin (DCX) in the entire striatum, as well as in the dorsal and ventral sub-regions separately. We observed a significantly higher number of DCX(+) neuroblasts in the dorsal compared to the ventral sub-region of the striatum in PPX-injected mice. These results suggest that the stimulation of hippocampal and dorsal striatal neurogenesis may be up-regulated by PPX. The increased generation of neural cells, both in constitutively active and quiescent neurogenic niches, might be related to the proportional higher D3 receptor affinity of PPX, non-dopaminergic effects of PPX, or altered motor behavior.
EVALuna2:5538

Distinct forebrain regions define a dichotomous astrocytic profile in multiple system atrophy - Schneider, Yanni; Gauer, Carina; Andert, Marie; Hoffmann, Alana; Riemenschneider, M. J.; Krebs, W.; Chalmers, Nicholas; Lötzsch, C.; Naumann, Ulrike; Xiang, Wei; Rothhammer, Veit; Beckervordersandforth, Ruth; et al. (Acta Neuropathologica Communications, 2024)
The growing recognition of a dichotomous role of astrocytes in neurodegenerative processes has heightened the need for unraveling distinct astrocytic subtypes in neurological disorders. In multiple system atrophy (MSA), a rare, rapidly progressing atypical Parkinsonian disease characterized by increased astrocyte reactivity. However the specific contribution of astrocyte subtypes to neuropathology remains elusive. Hence, we first set out to profile glial fibrillary acidic protein levels in astrocytes across the human post mortem motor cortex, putamen, and substantia nigra of MSA patients and observed an overall profound astrocytic response. Matching the post mortem human findings, a similar astrocytic phenotype was present in a transgenic MSA mouse model. Notably, MSA mice exhibited a decreased expression of the glutamate transporter 1 and glutamate aspartate transporter in the basal ganglia, but not the motor cortex. We developed an optimized astrocyte isolation protocol based on magnetic-activated cell sorting via ATPase Na+/K+ transporting subunit beta 2 and profiled the transcriptomic landscape of striatal and cortical astrocytes in transgenic MSA mice. The gene expression profile of astrocytes in the motor cortex displayed an anti-inflammatory signature with increased oligodendroglial and pro-myelinogenic expression pattern. In contrast, striatal astrocytes were defined by elevated pro-inflammatory transcripts accompanied by dysregulated genes involved in homeostatic functions for lipid and calcium metabolism. These findings provide new insights into a region-dependent, dichotomous astrocytic response—potentially beneficial in the cortex and harmful in the striatum—in MSA suggesting a differential role of astrocytes in MSA-related neurodegenerative processes.
CRIS-Team Scopus Importer:2024-01-12

DIVI-Recommendations on the infrastruture of adult intensive care units - Waydhas, Christian; Riessen, Reimer; Markewitz, Andreas; Hoffmann, Florian; Frey, Lorenz; Boettiger, Bernd W.; Brenner, Sebastian; Brenner, Thorsten; Deffner, Teresa; Deininger, Matthias Manfred; Janssens, Uwe; Kluge, Stefan; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2023)
This document on the Structure and Equipment for Intensive Care Units of the German Association for Intensive and Emergency Care (DIVI) aims at providing guidance and recommendations for the requirements of (infra)structure, personal, and organization of intensive care units. The recommendations are based on a systematic literature search and a formal consensus process from a group of multi-disciplinary and multiprofessional specialists from the DIVI. The recommendations comprise a 3-staged level of intensive care units, a 3-staged level of care with respect to severity of illness, the staffing requirement of physicians, nurses, physiotherapists, pharmacists, psychologists, and other specialists. Furthermore, proposals concerning the equipment and the construction of ICUs are supplied.
CRIS-Team WoS Importer:2023-05-26

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

Do all patients in the epilepsy monitoring unit experience the same level of comfort? A quantitative exploratory secondary analysis - Egger-Rainer, Andrea; Hettegger, Sophie Martina; Feldner, Raphael; Arnold, Stephan; Bosselmann, Christian; Hamer, Hajo; Hengsberger, Anna; Lang, Johannes; Lorenzl, Stefan; Lerche, Holger; Noachtar, Soheyl; Pataraia, Ekaterina; et al. (Journal of Advanced Nursing, 2021)
Aims To find out which variables may be associated with comfort of patients in an epilepsy monitoring unit. Design Exploratory, quantitative study design. Methods Data were collected from October 2018 to November 2019 in Austria and Southern Germany. A total of 267 patients of 10 epilepsy centres completed the Epilepsy Monitoring Unit Comfort Questionnaire which is based on Kolcaba's General Comfort Questionnaire. Secondary data analysis were conducted by using descriptive statistics and an exploratory model building approach, including different linear regression models and several sensitivity analyses. Results Total comfort scores ranged from 83 to 235 points. Gender, occupation and centre turned out to be possible influential variables. On average, women had a total comfort score 4.69 points higher than men, and retired persons 28.2 points higher than high school students >= 18 years. Comfort scores of younger patients were lower than those of older patients. However, age did not show a statistically significant effect. The same could be observed in marital status and educational levels. Conclusion When implementing comfort measures, nurses must be aware of variables which could influence the intervention negatively. Especially, high school students >= 18 years should be supported by epilepsy specialist nurses, in order to reduce uncertainty, anxiety and discomfort. But, since the identified variables account only for a small proportion of the inter-individual variability in comfort scores, further studies are needed to find out additional relevant aspects and to examine centre-specific effects more closely. Impact Nurses ensure patient comfort during a hospital stay. However, there are variables that may impair the effectiveness of the nursing measures. Our study showed that the experience of comfort was highly individual and could be explained by sociodemographic variables only to a limited extent. Nurses must be aware that additional factors, such as the situation in the individual setting, may be relevant.
CRIS-Team WoS Importer:2021-12-03

Does participation in art classes influence performance on two different cognitive tasks? - Schindler, Manuel; Maihöfner, Christian; Bolwerk, Anne; Lang, Frieder (Aging & Mental Health, 2017)
OBJECTIVES: Effects of two mentally stimulating art interventions on processing speed and visuo-spatial cognition were compared in three samples. METHOD: In a randomized 10-week art intervention study with a pre-post follow-up design, 113 adults (27 healthy older adults with subjective memory complaints, 50 healthy older adults and 36 healthy younger adults) were randomly assigned to one of two groups: visual art production or cognitive art evaluation, where the participants either produced or evaluated art. ANOVAs with repeated measures were computed to observe effects on the Symbol-Digit Test, and the Stick Test. RESULTS: Significant Time effects were found with regard to processing speed and visuo-spatial cognition. Additionally, there was found a significant Time × Sample interaction for processing speed. The effects proved robust after testing for education and adding sex as additional factor. CONCLUSION: Mental stimulation by participation in art classes leads to an improvement of processing speed and visuo-spatial cognition. Further investigation is required to improve understanding of the potential impact of art intervention on cognitive abilities across adulthood.
EVALuna2:36362

Doppler pulsatility index in spontaneous intracerebral hemorrhage - Kiphuth, Ines C.; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (European neurology, 2013)
Background and Purpose: Elevated intracranial pressure (ICP) as a result of intracerebral hemorrhage (ICH) and perihematomal edema often leads to tissue shift, which can be identified in cross-sectional imaging and presents a known predictor of functional outcome. Pulsatility indices (PIs) of the intracranial arteries as measured by transcranial Doppler sonography (TCD) may serve as surrogate parameters for ICP. This study aims to investigate whether PI correlates with ICP and midline shift and serves as a reliable predictor of functional outcome in patients with ICH. Methods: Within a 1-year period between April 2009 and April 2010, 136 patients with acute spontaneous, supratentorial ICH were admitted to our tertiary care hospital. One-hundred and twenty-four patients fulfilled the inclusion criteria and were eligible for analysis. TCD and transcranial duplex sonography were performed on admission and at least once more during hospital stay. Functional outcome was assessed 6 months after discharge. Correlation analyses, logistic regression analyses and receiver operating characteristic curves were calculated. Results: One-hundred and twenty-four patients were included in the analysis. Six-month mortality amounted to 39.5%. The ICH score and PIs of the middle cerebral artery were independent predictors of outcome 6 months after discharge. Conclusions: Early PI monitoring by TCD correlated with ICP and may be used to predict the outcome after 6 months. Copyright © 2013 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Functional outcome; Intracerebral hemorrhage; Midline shift; Pulsatility index; Transcranial duplex sonography

Do we understand the pathophysiology of gastrointestinal symptoms in patients with Fabry disease? - Hilz, Max-Josef; Arbustini, Eloisa; Dagna, Lorenzo; Gasbarrini, Antonio; Goizet, Cyril; Lacombe, Didier; Liguori, Rocco; Manna, Raffaele; Politei, Juan; Spada, Marco; Burlina, Alessandro (2018)
EVALuna2:201958

Dressing Apraxia as Initial Manifestation of Creutzfeldt-Jakob Disease - Heckmann, Josef G.; Vachalova, Ivana; Vynogradova, Irina; Schwab, Stefan (Tremor and Other Hyperkinetic Movements, 2020)
Background: Creutzfeldt-Jakob disease (CJD) is a rare prion disease characterized by rapidly progressive dementia.
CRIS-Team WoS Importer:2020-07-24

Dual-Center, Dual-Platform Microrna Profiling Identifies Plasma Biomarkers of Adult Temporal Lobe Epilepsy - Raoof, R.; Bauer, S.; El Naggar, H.; Brennan, G.; Hill, T.; Brindley, E.; Connolly, N.; Mcardle, H.; Spain, E.; Forster, R.; Prehn, J.; Hamer, Hajo; et al. (2018)
EVALuna2:201943

Dysmorphic neurons as cellular source for phase-amplitude coupling in Focal Cortical Dysplasia Type II - Rampp, Stefan; Rössler, Karl; Hamer, Hajo; Illek, Margit; Buchfelder, Michael; Dörfler, Arnd; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Kölble, Konrad; Peixoto-Santos, Jose Eduardo; Blümcke, Ingmar; et al. (Clinical Neurophysiology, 2021)
Objective: Reliable localization of the epileptogenic zone is necessary for successful epilepsy surgery. Neurophysiological biomarkers include ictal onsets and interictal spikes. Furthermore, the epileptic network shows oscillations with potential localization value and pathomechanistic implications. The cellular origin of such markers in invasive EEG in vivo remains to be clarified. Methods: In the presented pilot study, surgical brain samples and invasive EEG recordings of seven patients with surgically treated Focal Cortical Dysplasia (FCD) type II were coregistered using a novel protocol. Dysmorphic neurons and balloon cells were immunohistochemically quantified. Evaluated markers included seizure onset, spikes, and oscillatory activity in delta, theta, gamma and ripple frequency bands, as well as sample entropy and phase-amplitude coupling between delta, theta, alpha and beta phase and gamma amplitude. Results: Correlations between histopathology and neurophysiology provided evidence for a contribution of dysmorphic neurons to interictal spikes, fast gamma activity and ripples. Furthermore, seizure onset and phase-amplitude coupling in areas with dysmorphic neurons suggests preserved connectivity is related to seizure initiation. Balloon cells showed no association. Conclusions: Phase-amplitude coupling, spikes, fast gamma and ripples are related to the density of dysmorphic neurons and localize the seizure onset zone. Significance: The results of our pilot study provide a new powerful tool to address the cellular source of abnormal neurophysiology signals to leverage current and novel biomarkers for the localization of epileptic activity in the human brain.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Electrophysiological markers; Epilepsy; Focal cortical dysplasia; Invasive EEG

Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461

Early postoperative tumor progression predicts clinical outcome in glioblastoma-implication for clinical trials - Merkel, Andreas; Soeldner, Dorothea; Wendl, Christina; Urkan, Dilek; Kuramatsu, Joji; Seliger, Corinna; Proescholdt, Martin; Eyupoglu, Ilker Y.; Hau, Peter; Uhl, Martin (Journal of Neuro-Oncology, 2017)
Molecular markers define the diagnosis of glioblastoma in the new WHO classification of 2016, challenging neuro-oncology centers to provide timely treatment initiation. The aim of this study was to determine whether a time delay to treatment initiation was accompanied by signs of early tumor progression in an MRI before the start of radiotherapy, and, if so, whether this influences the survival of glioblastoma patients. Images from 61 patients with early post-surgery MRI and a second MRI just before the start of radiotherapy were examined retrospectively for signs of early tumor progression. Survival information was analyzed using the Kaplan-Meier method, and a Cox multivariate analysis was performed to identify independent variables for survival prediction. 59 percent of patients showed signs of early tumor progression after a mean time of 24.1 days from the early post-surgery MRI to the start of radiotherapy. Compared to the group without signs of early tumor progression, which had a mean time of 23.3 days (p = 0.685, Student's t test), progression free survival was reduced from 320 to 185 days (HR 2.3; CI 95% 1.3-4.0; p = 0.0042, log-rank test) and overall survival from 778 to 329 days (HR 2.9; CI 95% 1.6-5.1; p = 0.0005). A multivariate Cox regression analysis revealed that the Karnofsky performance score, O-6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation, and signs of early tumor progression are prognostic markers of overall survival. Early tumor progression at the start of radiotherapy is associated with a worse prognosis for glioblastoma patients. A standardized baseline MRI might allow for better patient stratification.
EVALuna2:22524

Early prediction of delayed cerebral ischemia in subarachnoid hemorrhage based on quantitative EEG: A prospective study in adults - Gollwitzer, S.; Groemer, Teja W.; Rampp, Stefan; Hagge, Mareike; Olmes, D.; Huttner, Hagen; Schwab, Sibylle; Madzar, D.; Hopfengaertner, R.; Hamer, Hajo (Clinical Neurophysiology, 2015)
Delayed cerebral infarction (DCI) has a significant impact on mortality and morbidity of patients with subarachnoid hemorrhage (SAH). The aim of this study was to define quantitative EEG (qEEG) parameters for the early and reliable prediction of DCI and compare the validity and time course of qEEG to standard procedures.12 consecutive unselected SAH patients (8 female, mean age 52 years, Hunt-and-Hess grade I-IV) were prospectively examined. Continuous six channel EEG monitoring was started within 48 h after admission (mean duration 5.2 days; range: 2-12 days). All raw and unselected EEG signal underwent automated artifact rejection, Short Time Fast Fourier Transformation and a detrending procedure in order to analyze regional spectral power changes in different frequency bands. According to clinical standards, transcranial Doppler sonography (TCD) was performed at least on alternate days and repeat cerebral computer tomography (CCT) as needed.6 patients (50%) developed vasospasm/DCI. Decrease of ?40% in power persisting over ?5h in the alpha band and ?6h in the theta band marked the optimal cut-off to detect DCI (sensitivity 89%, specificity 77% for alpha). EEG changes preceded detection of vasospasm/DCI in standard procedures by 2.3d ays. Changes in the beta and delta band as well as in the alpha/delta ratio demonstrated lower correlation with imminent DCI.Focal reduction in alpha power may represent a valid, observer independent, non-invasive and continuous marker for vasospasm/DCI in SAH patients.qEEG indicates imminent ischemia earlier than established diagnostic tools, such as TCD.
EVALuna2:22268

Eculizumab use in neuromyelitis optica spectrum disorders: real-world evidence from Germany and Austria - Ringelstein, M.; Asseyer, S.; Lindenblatt, G.; Fischer, K.; Pul, R.; Ozalp, S. -H.; Lohmann, L.; Giglhuber, K.; Haeussler, V.; Karenfort, M.; Hellwig, K.; Paul, F.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Effectiveness of Lumbar Cerebrospinal Fluid Drain Among Patients With Aneurysmal Subarachnoid Hemorrhage: A Randomized Clinical Trial. - Wolf, Stefan; Mielke, Dorothee; Barner, Christoph; Malinova, Vesna; Kerz, Thomas; Wostrack, Maria; Czorlich, Patrick; Salih, Farid; Engel, Doortje C.; Ehlert, Angelika; Staykov, Dimitre; Alturki, Abdulrahman Y.; et al. (JAMA Neurology, 2023)
IMPORTANCE: After aneurysmal subarachnoid hemorrhage, the use of lumbar drains has been suggested to decrease the incidence of delayed cerebral ischemia and improve long-term outcome. OBJECTIVE: To determine the effectiveness of early lumbar cerebrospinal fluid drainage added to standard of care in patients after aneurysmal subarachnoid hemorrhage. DESIGN, SETTING, AND PARTICIPANTS: The EARLYDRAIN trial was a pragmatic, multicenter, parallel-group, open-label randomized clinical trial with blinded end point evaluation conducted at 19 centers in Germany, Switzerland, and Canada. The first patient entered January 31, 2011, and the last on January 24, 2016, after 307 randomizations. Follow-up was completed July 2016. Query and retrieval of data on missing items in the case report forms was completed in September 2020. A total of 20 randomizations were invalid, the main reason being lack of informed consent. No participants meeting all inclusion and exclusion criteria were excluded from the intention-to-treat analysis. Exclusion of patients was only performed in per-protocol sensitivity analysis. A total of 287 adult patients with acute aneurysmal subarachnoid hemorrhage of all clinical grades were analyzable. Aneurysm treatment with clipping or coiling was performed within 48 hours. INTERVENTION: A total of 144 patients were randomized to receive an additional lumbar drain after aneurysm treatment and 143 patients to standard of care only. Early lumbar drainage with 5 mL per hour was started within 72 hours of the subarachnoid hemorrhage. MAIN OUTCOMES AND MEASURES: Primary outcome was the rate of unfavorable outcome, defined as modified Rankin Scale score of 3 to 6 (range, 0 to 6), obtained by masked assessors 6 months after hemorrhage. RESULTS: Of 287 included patients, 197 (68.6%) were female, and the median (IQR) age was 55 (48-63) years. Lumbar drainage started at a median (IQR) of day 2 (1-2) after aneurysmal subarachnoid hemorrhage. At 6 months, 47 patients (32.6%) in the lumbar drain group and 64 patients (44.8%) in the standard of care group had an unfavorable neurological outcome (risk ratio, 0.73; 95% CI, 0.52 to 0.98; absolute risk difference, -0.12; 95% CI, -0.23 to -0.01; P = .04). Patients treated with a lumbar drain had fewer secondary infarctions at discharge (41 patients [28.5%] vs 57 patients [39.9%]; risk ratio, 0.71; 95% CI, 0.49 to 0.99; absolute risk difference, -0.11; 95% CI, -0.22 to 0; P = .04). CONCLUSION AND RELEVANCE: In this trial, prophylactic lumbar drainage after aneurysmal subarachnoid hemorrhage lessened the burden of secondary infarction and decreased the rate of unfavorable outcome at 6 months. These findings support the use of lumbar drains after aneurysmal subarachnoid hemorrhage. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01258257.
EVALuna2:536995

Effect of helium preconditioning on neurological decompression sickness in rats - Zhang, Rongjia; Yu, Yongchao; Manaenko, Anatol; Bi, Hongda; Zhang, Ning; Zhang, Ling; Zhang, Ting; Ye, Zhouheng; Sun, Xuejun (Journal of Applied Physiology, 2019)
Decompression sickness (DCS) occurs because of an excessively rapid and extensive reduction of the ambient pressure. Bubble-induced spinal cord ischemia is generally considered as a part of neurological DCS pathogenesis. Because helium preconditioning (HPC) recently demonstrated beneficial properties against ischemic damage, we hypothesized that HPC may decrease the neurological deficits of DCS in rats. Seventy-five male Sprague-Dawley rats were divided into a non-HPC group ( n = 25) and a HPC group ( n = 25) and 25 naive animals that were euthanized for histological examination ( n = 5) or anesthetized for baseline somatosensory evoked potential (SSEP) recordings ( n = 20). To induce DCS, rats were compressed with air to a pressure of 709 kPa for 60 min and decompressed at a rate of 203 kPa/min. HPC was administered as three episodes of 79% helium-21% oxygen mixture inhalation for 5 min interspersed with 5 min of air breathing. We found that HPC resulted in significantly decreased DCS incidence and delay of DCS onset. HPC also improved animal performance on the grip test after decompression and significantly ameliorated decompression-induced decrease of platelet number. Furthermore, the incidence of abnormal SSEP waves and histological spinal lesions was significantly reduced by HPC. We conclude that HPC can decrease the occurrence of DCS and ameliorate decompression-induced neurological deficits. NEW & NOTEWORTHY Helium preconditioning ameliorates decompression-induced neurological deficits in rats. Helium breathing before air dives may prevent neurological deficit and attenuate symptoms after decompression.
CRIS-Team Scopus Importer:2019-05-02
Keywords: decompression sickness; helium preconditioning; neurological deficit; somatosensory evoked potential; spinal cord injury

Effect of the German Act on the reform of the market for medicinal products (AMNOG) on the quality of neurological and psychiatric treatment - Hamer, Hajo; Meyer-Lindenberg, A. (Der Nervenarzt, 2016)
EVALuna2:22464

Effects of a 4-Step Standard Operating Procedure for the Treatment of Fever in Patients With Acute Stroke - Lee, Hanna; Hedtmann, Günter; Schwab, Stefan; Kollmar, Rainer (Frontiers in Neurology, 2021)
Background and Purpose: Fever in the acute phase of stroke leads to an unfavorable clinical outcome and increased mortality. However, no specific form of effective fever treatment has been established, so far. We analyzed the effectiveness of our in-house standard operating procedure (SOP) of fever treatment. Methods: This SOP was analyzed for a period of 33 weeks. Patients with cerebral ischemia (ischemic stroke, transient ischemic attack) or cerebral hemorrhage (intracerebral, subarachnoid) and body temperature elevation of ≥ 37.5°C within the first 6 days after admission were eligible for inclusion in the analysis. The results of SOP group, who's data have been collected prospectively were then compared with a historical control group that had been treated conventionally 1 year earlier in the same period. The data of control group have been collected in retrospect. The primary endpoint was the total duration of the fever for the first 6 days after admission to the stroke unit. Results: A total of 130 patients (mean age of 78 ± 12) received 370 antipyretic interventions. Sequential application of paracetamol (n = 245), metamizole (n = 53) and calf compress (n = 15) led to significant reduction in body temperature. In patients who did not respond to these applications, normothermia could be achieved after infusion of the cooled saline solution. Normothermia could be achieved within 120 min in more than 90% of the cases treated by the SOP. The SOP reduced the fever duration in the 6 days significantly, from 12.2 ± 2.7 h [95% confidence interval (CI) for mean] in the control group to 3.9 ± 1.0 h (95% CI) in the SOP group (p < 0.001). The SOP was rated to be reasonable and effective. Conclusion: Our in-house SOP is cost-efficient and effective for fever treatment in stroke patients, that can be implemented by local health care professionals.
CRIS-Team Scopus Importer:2021-04-02
Keywords: acute stroke; fever; fever treatment; hyperthermia; standard operating procedure

Effects of clobazam for treatment of refractory status epilepticus - Madzar, Dominik; Geyer, Anna; Knappe, Ruben U.; Gollwitzer, Stephanie; Kuramatsu, Joji; Gerner, Stefan; Hamer, Hajo; Huttner, Hagen (BMC Neurology, 2016)
Clobazam (CLB) is a well characterized antiepileptic drug (AED) that differs from other benzodiazepines by its basic chemical structure and pharmacodynamic properties. Only one previous study examined the efficacy of CLB as add-on therapy in refractory status epilepticus (RSE).We analyzed RSE episodes treated in our institution between 2001 and 2012. Successful treatment with CLB was scored if CLB was the last AED added to therapy before RSE termination. We assessed the differences between patients with and without CLB and correlated CLB with outcome. Among patients treated with CLB, we studied responders and non-responders and compared our CLB cohort with recently published data.CLB was part of the AED regimen in 24/70 (34.3 %) RSE episodes. In six of these (25.0 %) RSE resolution was attributed to CLB. Baseline characteristics of episodes with and without CLB treatment showed no significant differences and RSE termination rates were very similar (83.3 % vs. 80.4 %). CLB was administered in clinically more complex RSE with longer RSE duration and worse outcome, but CLB was not related independently to outcome. Comparison of our results with previously published data revealed that baseline characteristics as well as CLB maintenance doses and time of treatment initiation were similar in both cohorts. CLB was less frequently the last AED added to RSE therapy in our patients indicating a lower treatment success rate than previously reported.CLB represents a reasonable AED and promising add-on agent for treatment of RSE. However, rates of successful CLB response were substantially lower than in a recently published study. Differing RSE characteristics and treatment strategies may account for the discrepancy between study results, as RSE etiologies and seizures types associated with unfavorable prognosis were more common in our cohort, while anesthetics tended to be less frequently applied to achieve seizure control.
EVALuna2:22479

Efficacy and feasibility of home-based training for individuals with homonymous visual field defects - Aimola, Lina; Lane, Alison R.; Smith, Daniel T.; Kerkhoff, Georg; Ford, Gary A.; Schenk, Thomas (Neurorehabilitation and Neural Repair, 2014)
Homonymous visual field defects (HVFDs) are one of the most common consequences of stroke. Compensatory training encourages affected individuals to develop more efficient eye movements to improve function. However, training is typically supervised, which can be time consuming and costly.To develop and evaluate the efficacy and feasibility of an unsupervised reading and exploration computer training for individuals with HVFDs.Seventy individuals with chronic HVFDs were randomly assigned to 1 of 2 groups: intervention or control. The former received 35 hours of reading and exploration training, and the latter received 35 hours of control training. Visual and attentional abilities were assessed before and after training using perimetry, visual search, reading, activities of daily living, the Test of Everyday Attention, and a Sustained Attention to Response task.Eighteen individuals failed to complete the training; analyses were conducted on the remaining 28 intervention and 24 control group participants. Individuals in the intervention group demonstrated significant improvements in the primary outcomes of exploration (12.87%, 95% confidence interval [CI] = 8.44% to 17.30%) and reading (18.45%, 95% CI = 9.93% to 26.97%), which were significantly greater than those observed following the control intervention (exploration = 4.80%, 95% CI = 0.09% to 9.51%; reading = 1.95%, 95% CI = -4.78% to 8.68%). Participants in the intervention group also reported secondary subjective improvements, although these were not matched by objective gains in tasks simulating activities of daily living.Home-based compensatory training is an inexpensive accessible rehabilitation option for individuals with HVFDs, which can result in objective benefits in searching and reading, as well as improving quality of life.
EVALuna2:22242

Efficacy and safety of alemtuzumab versus fingolimod in RRMS after natalizumab cessation - Pfeuffer, Steffen; Schmidt, Rene; Straeten, Frederike Anne; Pul, Refik; Kleinschnitz, Christoph; Wieshuber, Marinus; Lee, De-Hyung; Linker, Ralf; Doerck, Sebastian; Straeten, Vera; Windhagen, Susanne; Pawlitzki, Marc; et al. (Journal of Neurology, 2019)
Background: Natalizumab (NTZ) was the first approved monoclonal antibody for the treatment of relapsing-remitting multiple sclerosis (RRMS). Despite proven and sustained efficacy, its use is limited by the risk of progressive multifocal leukoencephalopathy (PML). Moreover, some patients show ongoing disease activity under NTZ, requiring a switch to another disease-modifying treatment (DMT). However, evidence regarding the optimal DMT for treatment of active RRMS after NTZ-cessation is still scarce. Objective: To evaluate efficacy and safety outcomes of ALEM vs FTY treatment after cessation of NTZ. Methods: We retrospectively identified patients at 12 German neurology centers and analyzed risks for disease activity, adverse events, disability progression, and treatment discontinuation. Results: 195 patients were identified and 144 underwent final analysis (FTY: 101; ALEM: 42). The hazard ratio for clinical relapses was 2.24 favoring ALEM (95% CI 1.12–4.50; p = 0.015). The hazard ratio for adverse events was 7.78 (95% CI 1.04–57.95; p = 0.006) and 2.41 for MRI progression (95% CI 1.26–4.60; p = 0.004). The odds ratio for disability progression after 12 months was 4.84 (95% CI 1.74–13.47, p = 0.003). Differences remained after adjusting for possible confounders (e.g., age, sex, baseline disability, NTZ treatment duration, washout time). Conclusion: Our findings indicated particular advantages of ALEM compared to FTY in patients stopping NTZ.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Alemtuzumab; Fingolimod; Immunomodulatory therapy; Natalizumab; Progressive multifocal leukoencephalopathy; Remitting-relapsing multiple sclerosis

Efficacy and safety of combined intraventricular fibrinolysis with lumbar drainage for prevention of permanent shunt dependency after intracerebral hemorrhage with severe ventricular involvement: A randomized trial and individual patient data meta-analysi - Staykov, Dimitre; Kuramatsu, Joji; Bardutzky, Juergen; Volbers, Bastian; Gerner, Stefan; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Annals of Neurology, 2017)
Intraventricular hemorrhage (IVH) is a negative prognostic factor in intracerebral hemorrhage (ICH) and is associated with permanent shunt dependency in a substantial proportion of patients post-ICH. IVH treatment by intraventricular fibrinolysis (IVF) was recently linked to reduced mortality rates in the CLEAR III study and IVF represents a safe and effective strategy to hasten clot resolution that may reduce shunt rates. Additionally, promising results from observational studies reported reductions in shunt dependency for a combined treatment approach of IVF plus lumbar drains (LDs). The present randomized, controlled trial investigated efficacy and safety of a combined strategy-IVF plus LD versus IVF alone-on shunt dependency in patients with ICH and severe IVH.This randomized, open-label, parallel-group study included patients aged 18 to 85 years, prehospital modified Rankin Scale <=3, ICH volume < 60ml, Glasgow Coma Scale of <9, and severe IVH with tamponade of the third and fourth ventricles requiring placement of external ventricular drainage (EVD). Over a 3-year recruitment period, patients were allocated to either standard treatment (control group receiving IVF consisting of 1mg of recombinant human tissue plasminogen activator every 8 hours until clot clearance of third and fourth ventricles) or a combined treatment approach of IVF and-upon clot clearance of third and fourth ventricles-subsequent placement of an LD for drainage of cerebrospinal fluid (CSF; intervention group). The primary endpoint consisted of permanent shunt placement indicated after a total of three unsuccessful EVD clamping attempts or need for CSF drainage longer than 14 days in both groups. Secondary endpoints included IVF- and LD-related safety, such as bleeding or infections, and functional outcome at 90 and 180 days. Conducted endpoint analyses used individual patient data meta-analyses. The study was registered at clinicaltrials.gov (NCT01041950).The trial was stopped upon predefined interim analysis after 30 patients because of significant efficacy of tested intervention. The primary endpoint was analyzed without dropouts and was reached in 43% (7 of 16) of the control group versus 0% (0 of 14) of the intervention group (p = 0.007). Meta-analyses were based on overall 97 patients, 45 patients receiving IVF plus LD versus 42 with IVF only. Meta-analyses on shunt dependency showed an absolute risk reduction of 24% for the intervention (LD, 2.2% [1 of 45] vs no-LD, 26.2% [11 of 42]; odds ratio [OR] = 0.062; confidence interval [CI], 0.011-0.361; p = 0.002). Secondary endpoints did not show significant differences for CSF infections (OR = 0.869;CI, 0.445-1.695; p = 0.680) and functional outcome at 90 days (OR = 0.478; CI, 0.190-1.201; p = 0.116), yet bleeding complications were significantly reduced in favor of the intervention (OR = 0.401; CI, 0.302-0.532; p < 0.001).The present trial and individual patient data meta-analyses provide evidence that, in patients with severe IVH, as compared to IVF alone, a combined approach of IVF plus LD treatment is feasible and safe and significantly reduces rates of permanent shunt dependency for aresorptive hydrocephalus post-ICH. ANN NEUROL 2017;81:93-103.
EVALuna2:22478

Electrodiagnostic assessment of the autonomic nervous system: A consensus statement endorsed by the American Autonomic Society, American Academy of Neurology, and the International Federation of Clinical Neurophysiology - Cheshire, William P.; Freeman, Roy; Gibbons, Christopher H.; Cortelli, Pietro; Wenning, Gregor K.; Hilz, Max-Josef; Spies, Judith M.; Lipp, Axel; Sandroni, Paola; Wada, Naoki; Mano, Akiko; Ah Kim, Hyun; et al. (Clinical Neurophysiology, 2021)
Evaluation of disorders of the autonomic nervous system is both an art and a science, calling upon the physician's most astute clinical skills as well as knowledge of autonomic neurology and physiology. Over the last three decades, the development of noninvasive clinical tests that assess the function of autonomic nerves, the validation and standardization of these tests, and the growth of a large body of literature characterizing test results in patients with autonomic disorders have equipped clinical practice further with a valuable set of objective tools to assist diagnosis and prognosis. This review, based on current evidence, outlines an international expert consensus set of recommendations to guide clinical electrodiagnostic autonomic testing. Grading and localization of autonomic deficits incorporates scores from sympathetic cardiovascular adrenergic, parasympathetic cardiovagal, and sudomotor testing, as no single test alone is sufficient to diagnose the degree or distribution of autonomic failure. The composite autonomic severity score (CASS) is a useful score of autonomic failure that is normalized for age and gender. Valid indications for autonomic testing include generalized autonomic failure, regional or selective system syndromes of autonomic impairment, peripheral autonomic neuropathy and ganglionopathy, small fiber neuropathy, orthostatic hypotension, orthostatic intolerance, syncope, neurodegenerative disorders, autonomic hyperactivity, and anhidrosis.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Autonomic; Autonomic nervous system diseases; Denervation; Diabetic autonomic neuropathy; Hypotension; Orthostatic; Tilt table test; Valsalva Maneuver

Emotional and Autonomic Processing of Olfactory Stimuli Is Compromised in Patients with a History of Mild Traumatic Brain Injury - Hilz, Max-Josef; Wang, Ruihao; Liu, Mao; Muresanu, Dafin; Flanagan, Steven; Winder, Klemens; Hoesl, Katharina; Hummel, Thomas (Journal of Neurotrauma, 2019)
Patients with a history of mild traumatic brain injury (post-mTBI patients) may have enduring cardiovascular-autonomic dysregulation and emotional problems. Olfactory stimulation (OS) triggers emotional and cardiovascular-autonomic responses that might be compromised in post-mTBI patients. We therefore evaluated these responses to OS in post-mTBI patients. In 17 post-mTBI patients (interval since mTBI: 32.4 +/- 6.8 months) and 17 age- and sex-matched controls, we recorded respiration, electrocardiographic RR intervals, and systolic and diastolic blood pressures (BPsys, BPdia) before and during pleasant vanilla stimulation and unpleasant hydrogen sulphide (H2S) stimulation. Participants rated OS-related pleasantness, arousal, intensity, and familiarity on 9-point Likert scales. Analyses of variance (ANOVAs) with post hoc analyses compared parameters within each group before and during OS. To assess associations between pleasantness, arousal, intensity, and familiarity, we correlated OS scores within groups (significance: p < 0.05). Baseline parameters were similar between groups. Only in controls, vanilla stimulation significantly lowered BPsys and BPdia, whereas H2S stimulation lowered RR intervals. Vanilla-related pleasantness scores were lower, intensity scores were higher in patients than controls. During vanilla stimulation, pleasantness scores correlated negatively with arousal scores in controls, whereas familiarity scores correlated positively with intensity scores in patients. During H2S stimulation, familiarity scores correlated negatively with pleasantness scores in controls, whereas pleasantness scores correlated negatively with arousal scores in mTBI patients. Post-mTBI patients could not change BP or RR intervals during OS but perceived vanilla stimuli as less pleasant and more intense than did controls. Associations between pleasantness, arousal, intensity, and familiarity differed between groups suggesting different activation of the olfactory network and the central autonomic network upon OS. Subtle lesions within these networks might cause persistent changes in emotional and cognitive odor perception and cardiovascular responses.
CRIS-Team WoS Importer:2019-08-30

Endogenous endophthalmitis complicating Streptococcus equi subspecies zooepidemicus meningitis: a case report - Madžar, Dominik; Hagge, Mareike; Möller, Sebastian; Regensburger, Martin; Lee, De Hyung; Schwab, Stefan; Jantsch, Jonathan (BMC Research Notes, 2015)
Streptococcus equi subspecies zooepidemicus (Streptococcus zooepidemicus) is a rare cause of meningitis in humans. Humans mainly get infected by contact with an animal source or by ingestion of unpasteurized dairy products. In rare cases, bacterial meningitis can be complicated by endogenous endophthalmitis which is frequently associated with a poor visual prognosis.A 73 year old male Caucasian patient presented with clinical signs indicative of bacterial meningitis. Blood and cerebrospinal fluid cultures yielded beta-hemolytic, catalase-negative cocci. The strain was identified as Streptococcus zooepidemicus. The patient was likely infected by contact with a sick horse. Under antibiotic treatment, his general condition improved rapidly. Early after hospital admission, however, he began seeing a black spot in his left eye's central visual field. An ophthalmological examination revealed signs of endogenous endophthalmitis and so the patient underwent vitrectomy. Despite treatment, the visual acuity of his left eye remained severely impaired. He showed no further neurological deficits at hospital discharge.Meningitis caused by Streptococcus zooepidemicus is rare with only 27 previously published adult cases in the literature. Of note, this report constitutes the third description of endogenous endophthalmitis associated with Streptococcus zooepidemicus meningitis. Thus, endogenous endophthalmitis may represent a comparatively common complication of meningitis caused by this microorganism.
EVALuna2:22366

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

Endovascular treatment of large vessel occlusion acute ischemic stroke: Is there a place for hypothermia? - Macha, Kosmas; Schwab, Stefan (European Journal of Neurology, 2021)
CRIS-Team WoS Importer:2021-06-25

Enhancing Safety in Epilepsy Surgery (EASINESS): Study Protocol for a Retrospective, Multicenter, Open Registry - Drexler, Richard; Ben-Haim, Sharona; Bien, Christian G.; Borger, Valeri; Cardinale, Francesco; Carpentier, Alexandre; Cendes, Fernando; Chandra, Sarat; Clusmann, Hans; Colon, Albert; Curtis, Marco De; Delev, Daniel; et al. (Frontiers in Neurology, 2021)
Introduction: Optimizing patient safety and quality improvement is increasingly important in surgery. Benchmarks and clinical quality registries are being developed to assess the best achievable results for several surgical procedures and reduce unwarranted variation between different centers. However, there is no clinical database from international centers for establishing standardized reference values of patients undergoing surgery for mesial temporal lobe epilepsy. Design: The Enhancing Safety in Epilepsy Surgery (EASINESS) study is a retrospectively conducted, multicenter, open registry. All patients undergoing mesial temporal lobe epilepsy surgery in participating centers between January 2015 and December 2019 are included in this study. The patient characteristics, preoperative diagnostic tools, surgical data, postoperative complications, and long-term seizure outcomes are recorded. Outcomes: The collected data will be used for establishing standardized reference values ("benchmarks") for this type of surgical procedure. The primary endpoints include seizure outcomes according to the International League Against Epilepsy (ILAE) classification and defined postoperative complications. Discussion: The EASINESS will define robust and standardized outcome references after amygdalohippocampectomy for temporal lobe epilepsy. After the successful definition of benchmarks from an international cohort of renowned centers, these data will serve as reference values for the evaluation of novel surgical techniques and comparisons among centers for future clinical trials. Clinical Trial Registration:This study is indexed at clinicaltrials.gov (NT 04952298).
CRIS-Team WoS Importer:2022-01-28

Epidemiology of epilepsy in old age. German version Epidemiologie der Epilepsie im höheren Lebensalter - Lang, Johannes; Hamer, Hajo (Zeitschrift für Epileptologie, 2022)
Background: Epilepsy is a common neurological disease affecting all ages. The increasing frequency of symptomatic epilepsies with age is partly due to cerebrovascular and neurodegenerative diseases. Better knowledge of the epidemiology of epilepsy in old age improves our understanding of the disease as well as the therapeutic and sociomedical challenges for the individual and society. Objective: What do we currently know about the epidemiology of the epilepsies in old age and how should this be classified? Material and methods: A MEDLINE search in PubMed was conducted using the terms “epilepsy”, “elderly” and “incidence” or “prevalence” or “epidemiology” and relevant publications were analyzed. Results: The point prevalence of epilepsy of older age is 0.5–0.8% of the population and affects approximately 500,000 people in Germany. The highest age-adjusted prevalence is reported to lie beyond the age of 75 years. In recent decades, the prevalence climbed further among the 75-year-olds to be twice as high as among the adult working population. The incidence shows a significant increase among patients 65 years and older, reaches its maximum at around 80–85 years of age and is somewhat higher in men. Conclusion: Reasons for the high incidence and prevalence of epilepsy in old age are the age-related incidence of potentially epilepsy-associated diseases combined with a longer long-term survival for these diseases due to better medical care and an increase in life expectancy. The change in the age pyramid with a higher (and in the coming decades further increasing) proportion of old people, will further increase the rise of epilepsy of older age.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Aged; Elderly; Incidence; Prevalence; Seizures

Erectile dysfunction (ED) after ischemic stroke: association between prevalence and site of lesion - Koehn, Julia; Crodel, Carl; Deutsch, Martina; Kolominsky-Rabas, Peter; Hoesl, Katharina M.; Köhrmann, Martin; Schwab, Stefan; Hilz, Max-Josef (Clinical Autonomic Research, 2015)
Stroke may cause or worsen erectile dysfunction (ED). Post-stroke ED prevalence and association with stroke location are not well established. Therefore, we assessed post-stroke ED prevalence in relation to ischemic lesion locations and stroke severity.In 57 men (62.6 ± 10.5 years) who had ischemic stroke within 24 months prior to evaluation, we used the five-item International Index of Erectile Function questionnaire (IIEF5) to evaluate ED prevalence after stroke and retrospectively 3 months prior to stroke. IIEF5 scores range from 5 to 25; scores below 22 indicate ED. We estimated stroke severity upon hospital admission, using the National Institute of Health Stroke Scale (NIHSS), and determined stroke location from cranial computed tomography or magnetic resonance imaging. We compared pre- and post-stroke results with those of 22 control persons (61.7 ± 11.2 years), calculated correlations between IIEF5 scores and NIHSS scores, and compared ED prevalence with stroke locations (significance: p < 0.05).ED was reported by 45/57 patients after stroke, 26/57 patients before stroke, and 6/22 control persons. Patients' IIEF5 values were significantly lower [median 16 interquartile range (IQR) 3.5-20.5] after than before stroke (median 23, IQR 19.0-24.0) and lower than in controls (median 24, IQR 19.8-25.0). Pre- and post-stroke IIEF5 scores did not correlate with the patients' NIHSS scores at stroke onset (p > 0.05). ED was associated with middle cerebral artery infarction in 27/34, posterior cerebral artery infarction in 4/5, anterior cerebral artery infarction in 1/1, basal ganglia infarction in 3/3, brain stem infarction in 8/10, cerebellar infarction in 2/5, and lesions in more than one region in 1/1 patients.Disruption of the central network assuring erection might contribute to increased ED severity and prevalence after stroke. Anti-erectile effects of functional and psychological impairment or medication added after stroke may also contribute to ED but must be evaluated in larger patients groups.
EVALuna2:22368

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

Etomidate activates epileptic high frequency oscillations - Rampp, Stefan; Heers, M.; Schoenherr, M.; Schmitt, F. C.; Hopfengaertner, R.; Stefan, Hermann; et al. (Clinical Neurophysiology, 2014)
The short acting anesthetic etomidate has been shown to provoke epileptic spikes and rarely seizures. Influence of etomidate on the occurrence of epileptic HFO (high frequency oscillations) however is unknown. An HFO inducing effect of etomidate would allow further validation of the substance as a provocation measure in presurgical evaluation as well as provide insights into the common mechanisms of HFO, spike and seizure generation.We retrospectively analyzed EEG data from four patients who underwent etomidate activation during invasive video-EEG monitoring with subdural strip electrodes. Spikes were manually selected in raw data, HFO in band pass filtered data (80-250Hz). Rate and spatial distribution of HFO and spikes in three segments were compared: immediately after etomidate administration, as well as during slow wave sleep and while awake.Rates of HFO and spikes increased significantly after etomidate administration: Overall average rates of spikes were 9.7/min during sleep, 10/min while awake and 61.4/min after etomidate. Average HFO rates were 9.5/min during sleep, 8.3/min while awake and 24.4/min after etomidate (p<0.001, non-parametric ANOVA). Spatial distributions of HFO and spikes after administration of etomidate were consistent with the seizure onset zone (SOZ) and area of resection when available (SOZ: two patients; resection: one patient; no information: one patient). Except for spurious events, no additional HFO and spike foci were seen with activation.Etomidate administration activates spikes and HFO. Spatial distributions do not extend beyond electrodes showing spikes and HFO without Etomidate and seem consistent with the epileptic network.Etomidate activation is a safe procedure to provoke not only epileptic spikes but also HFO, which were shown to have a high specificity for the SO
EVALuna2:16662

EuroHYP-1: European multicenter, randomized, phase III clinical trial of therapeutic hypothermia plus best medical treatment vs. best medical treatment alone for acute ischemic stroke - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Demotes, Jacques; Durand-Zaleski, Isabelle; Gebhardt, Bernd; Gluud, Christian; Kollmar, Rainer; Krieger, Derk W.; Lees, Kennedy R.; Molina, Carlos; Montaner, Joan; et al. (International Journal of Stroke, 2014)
Cooling reduced infarct size and improved neurological outcomes in animal studies modeling ischemic stroke, and also improved outcome in randomized clinical trials in patients with hypoxic-ischemic brain injury after cardiac arrest. Cooling awake patients with ischemic stroke has been shown feasible in phase II clinical trials.To determine whether systemic cooling to a target body temperature between 34·0 and 35·0°C, started within six-hours of symptom onset and maintained for 24 h, improves functional outcome at three-months in patients with acute ischemic stroke.International, multicenter, phase III, randomized, open-label clinical trial with blinded outcome assessment in 1500 patients aged 18 years or older with acute ischemic stroke and a National Institutes of Health Stroke Scale score of 6 up to and including 18. In patients randomized to hypothermia, cooling to a target body temperature of 34-35°C will be started within six-hours after symptom onset with rapid intravenous infusion of refrigerated normal saline or a surface cooling technique and maintained for 24 h with a surface or endovascular technique. Patients randomized to hypothermia will receive pethidine and buspirone to prevent shivering and discomfort.Score on the modified Rankin Scale at 91 days, as analyzed with ordinal logistic regression and expressed as a common odds ratio.With 750 patients per intervention group, this trial has 90% power to detect 7% absolute improvement at the 5% significance level. The full trial protocol is available at http://www.eurohyp1.eu. ClinicalTrials.gov Identifier: NCT01833312.
EVALuna2:22308

EUROHYP-1: EUROPEAN, MULTICENTRE, RANDOMISED, PHASE III CLINICAL TRIAL OF THERAPEUTIC HYPOTHERMIA PLUS BEST MEDICAL TREATMENT VS BEST MEDICAL TREATMENT ALONE FOR ACUTE ISCHAEMIC STROKE - Petersson, J.; Van Der Worp, H. B.; Macleod, M. R.; Kollmar, R.; Krieger, D. W.; Staykov, D.; Szabo, I.; Kallmünzer, Bernd; Schwab, Stefan (2018)
EVALuna2:36384

European Cooperative Acute Stroke Study-4: Extending the time for thrombolysis in emergency neurological deficits ECASS-4: ExTEND - Amiri, Hemasse; Bluhmki, Erich; Bendszus, Martin; Eschenfelder, Christoph C.; Donnan, Geoffrey A.; Leys, Didier; Molina, Carlos; Ringleb, Peter A.; Schellinger, Peter D.; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; et al. (International Journal of Stroke, 2016)
Thrombolytic therapy with recombinant tissue plasminogen activator (rt-PA) is an effective and approved therapy for acute ischemic stroke within 4.5 h of onset except for USA, Canada, Croatia, and Moldovia with a current 3 h label. We hypothesized that ischemic stroke patients selected with significant penumbral mismatch on magnetic resonance imaging (MRI) at 4.5-9 h after onset of stroke will have improved clinical outcomes when given intravenous rt-PA (alteplase) compared to placebo.ECASS-4: ExTEND is an investigator driven, phase 3, randomized, multi-center, double-blind, placebo-controlled study. Ischemic stroke patients presenting within 4.5 and 9 h of stroke onset, who fulfil clinical requirements (National Institutes of Health Stroke Score (NIHSS) 4-26 and pre-stroke modified Rankin Scale (mRS) 0-1) will undergo MRI. Patients who meet imaging criteria (infarct core volume <100 ml, perfusion lesion: infarct core mismatch ratio >1.2 and perfusion lesion minimum volume of 20 ml) additionally will be randomized to either rt-PA or placebo.The primary outcome measure will be the categorical shift in the mRS at day 90. Clinical secondary outcomes will be disability at day 90 dichotomized as favorable outcome mRS 0-1 at day 90. Tertiary endpoints include reduction in the NIHSS by 11 or more points or reaching 0-1 at day 90, reperfusion and recanalization at 24 h post stroke as well as depression, life quality, and cognitive impairment at day 90. Safety endpoints will include symptomatic intracranial hemorrhage (ICH) and death.
EVALuna2:22431

European expert consensus recommendations for neurological therapeutic goals for patients with Fabry disease - Hilz, Max-Josef; Baron, R.; Elliott, P.; Germain, D.; Spada, M.; Viana-Baptista, M.; Wanner, C.; Burlina, A. P. (2018)
EVALuna2:201952

European expert consensus statement on therapeutic goals in Fabry disease - Wanner, Christoph; Arad, Michael; Baron, Ralf; Burlina, Alessandro; Elliott, Perry M.; Feldt-Rasmussen, Ulla; Fomin, Victor V.; Germain, Dominique P.; Hughes, Derralynn A.; Jovanovic, Ana; Kantola, Ilkka; Linhart, Ales; et al. (Molecular Genetics and Metabolism, 2018)
Background: Fabry disease, an inherited lysosomal storage disorder, causes multi-organ pathology resulting in substantial morbidity and a reduced life expectancy. Although Fabry disease is an X-linked disorder, both genders may be affected, but generally to a lesser extent in females. The disease spectrum ranges from classic early-onset disease to non-classic later-onset phenotypes, with complications occurring in multiple organs or being confined to a single organ system depending on the stage of the disease. The impact of therapy depends upon patient- and disease-specific factors and timing of initiation. Methods: A European panel of experts collaborated to develop a set of organ-specific therapeutic goals for Fabry disease, based on evidence identified in a recent systematic literature review and consensus opinion. Results: A series of organ-specific treatment goals were developed. For each organ system, optimal treatment strategies accounted for inter-patient differences in disease severity, natural history, and treatment responses as well as the negative burden of therapy and the importance of multidisciplinary care. The consensus therapeutic goals and proposed patient management algorithm take into account the need for early disease-specific therapy to delay or slow the progression of disease as well as non-specific adjunctive therapies that prevent or treat the effects of organ damage on quality of life and long-term prognosis. Conclusions: These consensus recommendations help advance Fabry disease management by considering the balance between anticipated clinical benefits and potential therapy-related challenges in order to facilitate individualized treatment, optimize patient care and improve quality of life.
EVALuna2:207471

Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02

Everolimus in adult tuberous sclerosis complex patients with epilepsy: Too late for success? A retrospective study - Stockinger, Jakob; Strzelczyk, Adam; Nemecek, Andrea; Cicanic, Michal; Bösebeck, Frank; Brandt, Christian; Hamer, Hajo; Intravooth, Tassanai; Steinhoff, Bernhard J. (Epilepsia, 2021)
Objective: There is evidence that everolimus (EVE) significantly reduces seizure frequency in epilepsy patients with tuberous sclerosis complex (TSC). Given that TSC-related proliferative processes are more dynamic during brain development, seizure outcomes of patients treated with EVE may be age-related and may be less convincing in adult patients. The aim of this study was to assess the effectiveness and the safety profile of EVE in adults in clinical practice. Methods: We performed a multicenter retrospective chart review of TSC subjects with active epilepsy who started EVE in adulthood (≥18 years of age) at seven German epilepsy centers. The primary endpoint was the retention rate after 6 months. Results: A total of 45 subjects with a mean age of 31.6 ± 11.1 years at EVE start fulfilled the inclusion criteria. Retention rate after 6 months was 98% (43/44 evaluable subjects). Response rate (seizure reduction ≥ 50%) was 33% (14/43 evaluable subjects; four completely seizure-free). We did not find a significant relationship between epilepsy outcome parameters and patient age at EVE start. Adverse events were reported in 19 subjects and were judged to be serious in six patients. Three patients died during the observation period. Significance: Evidence suggests that EVE is an effective add-on treatment for epilepsy in adult TSC patients, surprisingly without any age limit to individual benefit. A strong age-dependent effect within the period of adulthood seems unlikely. Even if there was no proof of a causal relationship between deaths and EVE intake, patients with EVE should be carefully monitored, especially for infections and stomatitis.
CRIS-Team Scopus Importer:2021-02-12
Keywords: disease-modifying therapy; epilepsy; everolimus; tuberous sclerosis complex

Evidence-based guidelines for the management of large hemispheric infarction : a statement for health care professionals from the Neurocritical Care Society and the German Society for Neuro-intensive Care and Emergency Medicine - Torbey, Michel T.; Boesel, Julian; Rhoney, Denise H.; Rincon, Fred; Staykov, Dimitre; Amar, Arun P.; Varelas, Panayiotis N.; Juettler, Eric; Olson, Daiwai; Huttner, Hagen; Zweckberger, Klaus; Sheth, Kevin N.; et al. (Neurocritical Care, 2015)
Large hemispheric infarction (LHI), also known as malignant middle cerebral infarction, is a devastating disease associated with significant disability and mortality. Clinicians and family members are often faced with a paucity of high quality clinical data as they attempt to determine the most appropriate course of treatment for patients with LHI, and current stroke guidelines do not provide a detailed approach regarding the day-to-day management of these complicated patients. To address this need, the Neurocritical Care Society organized an international multidisciplinary consensus conference on the critical care management of LHI. Experts from neurocritical care, neurosurgery, neurology, interventional neuroradiology, and neuroanesthesiology from Europe and North America were recruited based on their publications and expertise. The panel devised a series of clinical questions related to LHI, and assessed the quality of data related to these questions using the Grading of Recommendation Assessment, Development and Evaluation guideline system. They then developed recommendations (denoted as strong or weak) based on the quality of the evidence, as well as the balance of benefits and harms of the studied interventions, the values and preferences of patients, and resource considerations.
EVALuna2:22397

Evidence for postnatal neurogenesis in the human amygdala - Röder, Sebastian; Burkardt, Petra; Rost, Fabian; Rode, Julian; Brusch, Lutz; Coras, Roland; Englund, Elisabet; Håkansson, Karl; Possnert, Göran; Salehpour, Mehran; Primetzhofer, Daniel; Csiba, László; et al. (Communications Biology, 2022)
The human amygdala is involved in processing of memory, decision-making, and emotional responses. Previous studies suggested that the amygdala may represent a neurogenic niche in mammals. By combining two distinct methodological approaches, lipofuscin quantification and 14C-based retrospective birth dating of neurons, along with mathematical modelling, we here explored whether postnatal neurogenesis exists in the human amygdala. We investigated post-mortem samples of twelve neurologically healthy subjects. The average rate of lipofuscin-negative neurons was 3.4%, representing a substantial proportion of cells substantially younger than the individual. Mass spectrometry analysis of genomic 14C-concentrations in amygdala neurons compared with atmospheric 14C-levels provided evidence for postnatal neuronal exchange. Mathematical modelling identified a best-fitting scenario comprising of a quiescent and a renewing neuronal population with an overall renewal rate of >2.7% per year. In conclusion, we provide evidence for postnatal neurogenesis in the human amygdala with cell turnover rates comparable to the hippocampus.
CRIS-Team Scopus Importer:2022-04-29

Extended Multimodal Flat Detector CT Imaging in Acute Ischemic Stroke: A Pilot Study - Hölter, Philip; Lang, Stefan; Beuscher, Vanessa; Kallmünzer, Bernd; Manhart, Michael; Schwab, Stefan; Dörfler, Arnd (Journal of Digital Imaging, 2023)
By using Flat detector computed tomography (FD-CT), a one-stop-shop approach in the diagnostic workup of acute ischemic stroke (AIS) might be achieved. Although information on upstream vessels is warranted, dedicated FD-CT protocols which include the imaging of the cervical vasculature are still lacking. We aimed to prospectively evaluate the implementation of a new multimodal FD-CT protocol including cervical vessel imaging in AIS patients. In total, 16 patients were included in this study. Eight patients with AIS due to large vessel occlusion (LVO) prospectively received a fully multimodal FD-CT imaging, including non-enhanced flat detector computed tomography (NE-FDCT), dynamic perfusion flat detector computed tomography (FD-CTP) and flat detector computed tomography angiography (FD-CTA) including cervical imaging. For comparison of time metrics and image quality, eight AIS patients, which received multimodal CT imaging, were included retrospectively. Although image quality of NE-FDCT and FD-CTA was rated slightly lower than NE-CT and CTA, all FD-CT datasets were of diagnostic quality. Intracerebral hemorrhage exclusion and LVO detection was reliably possible. Median door-to-image time was comparable for the FD-CT group and the control group (CT:30 min, IQR27-58; FD-CT:44.5 min, IQR31-55, p = 0.491). Door-to-groin-puncture time (CT:79.5 min, IQR65-90; FD-CT:59.5 min, IQR51-67; p = 0.016) and image-to-groin-puncture time (CT:44 min, IQR30-50; FD-CT:14 min, IQR12-18; p < 0.001) were significantly shorter, when patients were directly transferred to the angiosuite, where FD-CT took place. Our study indicates that using a new fully multimodal FD-CT approach including imaging of cervical vessels for first-line imaging in AIS patients is feasible and comparable to multimodal CT imaging with substantial potential to streamline the stroke workflow.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Flat Detector Computed Tomography; Interventional; Stroke; Workflow

Extending the time window for intravenous thrombolysis in acute ischemic stroke using magnetic resonance imaging-based patient selection - Ringleb, Peter; Bendszus, Martin; Bluhmki, Erich; Donnan, Geoffrey; Eschenfelder, Christoph; Fatar, Marc; Kessler, Christof; Molina, Carlos; Leys, Didier; Muddegowda, Girish; Poli, Sven; Schellinger, Peter; et al. (International Journal of Stroke, 2019)
Background: Intravenous thrombolysis with alteplase within a time window up to 4.5 h is the only approved pharmacological treatment for acute ischemic stroke. We studied whether acute ischemic stroke patients with penumbral tissue identified on magnetic resonance imaging 4.5–9 h after symptom onset benefit from intravenous thrombolysis compared to placebo. Methods: Acute ischemic stroke patients with salvageable brain tissue identified on a magnetic resonance imaging were randomly assigned to receive standard dose alteplase or placebo. The primary end point was disability at 90 days assessed by the modified Rankin scale, which has a range of 0–6 (with 0 indicating no symptoms at all and 6 indicating death). Safety end points included death, symptomatic intracranial hemorrhage, and other serious adverse events. Results: The trial was stopped early for slow recruitment after the enrollment of 119 (61 alteplase, 58 placebo) of 264 patients planned. Median time to intravenous thrombolysis was 7 h 42 min. The primary endpoint showed no significant difference in the modified Rankin scale distribution at day 90 (odds ratio alteplase versus placebo, 1.20; 95% CI, 0.63–2.27, P = 0.58). One symptomatic intracranial hemorrhage occurred in the alteplase group. Mortality at 90 days did not differ significantly between the two groups (11.5 and 6.8%, respectively; P = 0.53). Conclusions: Intravenous alteplase administered between 4.5 and 9 h after the onset of symptoms in patients with salvageable tissue did not result in a significant benefit over placebo. (Supported by Boehringer Ingelheim, Germany; ISRCTN 71616222).
CRIS-Team Scopus Importer:2019-05-02
Keywords: Alteplase; endovascular; intravenous thrombolysis; magnetic resonance imaging; thrombolysis; time window

Extending thrombolysis to 4·5–9 h and wake-up stroke using perfusion imaging: a systematic review and meta-analysis of individual patient data - Johnston, C.; Burns, R.; McNeil, John; Tress, Brian M.; Campbell, Bruce C.V.; Williams, M.; Ma, Henry; Ringleb, Peter A.; Parsons, Mark W.; Churilov, Leonid; Bendszus, Martin; Hsu, Chung; et al. (Lancet, 2019)
Background: Stroke thrombolysis with alteplase is currently recommended 0–4·5 h after stroke onset. We aimed to determine whether perfusion imaging can identify patients with salvageable brain tissue with symptoms 4·5 h or more from stroke onset or with symptoms on waking who might benefit from thrombolysis. Methods: In this systematic review and meta-analysis of individual patient data, we searched PubMed for randomised trials published in English between Jan 1, 2006, and March 1, 2019. We also reviewed the reference list of a previous systematic review of thrombolysis and searched ClinicalTrials.gov for interventional studies of ischaemic stroke. Studies of alteplase versus placebo in patients (aged ≥18 years) with ischaemic stroke treated more than 4·5 h after onset, or with wake-up stroke, who were imaged with perfusion-diffusion MRI or CT perfusion were eligible for inclusion. The primary outcome was excellent functional outcome (modified Rankin Scale [mRS] score 0–1) at 3 months, adjusted for baseline age and clinical severity. Safety outcomes were death and symptomatic intracerebral haemorrhage. We calculated odds ratios, adjusted for baseline age and National Institutes of Health Stroke Scale score, using mixed-effects logistic regression models. This study is registered with PROSPERO, number CRD42019128036. Findings: We identified three trials that met eligibility criteria: EXTEND, ECASS4-EXTEND, and EPITHET. Of the 414 patients included in the three trials, 213 (51%) were assigned to receive alteplase and 201 (49%) were assigned to receive placebo. Overall, 211 patients in the alteplase group and 199 patients in the placebo group had mRS assessment data at 3 months and thus were included in the analysis of the primary outcome. 76 (36%) of 211 patients in the alteplase group and 58 (29%) of 199 patients in the placebo group had achieved excellent functional outcome at 3 months (adjusted odds ratio [OR] 1·86, 95% CI 1·15–2·99, p=0·011). Symptomatic intracerebral haemorrhage was more common in the alteplase group than the placebo group (ten [5%] of 213 patients vs one [<1%] of 201 patients in the placebo group; adjusted OR 9·7, 95% CI 1·23–76·55, p=0·031). 29 (14%) of 213 patients in the alteplase group and 18 (9%) of 201 patients in the placebo group died (adjusted OR 1·55, 0·81–2·96, p=0·66). Interpretation: Patients with ischaemic stroke 4·5–9 h from stroke onset or wake-up stroke with salvageable brain tissue who were treated with alteplase achieved better functional outcomes than did patients given placebo. The rate of symptomatic intracerebral haemorrhage was higher with alteplase, but this increase did not negate the overall net benefit of thrombolysis. Funding: None.
CRIS-Team Scopus Importer:2019-07-16

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

Eyeball pressure stimulation induces subtle sympathetic activation in patients with a history of moderate or severe traumatic brain injury - Wang, Ruihao; Hoesl, Katharina M.; Ammon, Fabian; Markus, Jörg; Koehn, Julia; Roy, Sankanika; Liu, Mao; de Rojas Leal, Carmen; Muresanu, Dafin; Flanagan, Steven R.; Hilz, Max-Josef (Clinical Neurophysiology, 2018)
OBJECTIVE: After traumatic brain injury (TBI), there may be persistent central-autonomic-network (CAN) dysfunction causing cardiovascular-autonomic dysregulation. Eyeball-pressure-stimulation (EPS) normally induces cardiovagal activation. In patients with a history of moderate or severe TBI (post-moderate-severe-TBI), we determined whether EPS unveils cardiovascular-autonomic dysregulation. METHODS: In 51 post-moderate-severe-TBI patients (32.7 ± 10.5 years old, 43.1 ± 33.4 months post-injury), and 30 controls (29.1 ± 9.8 years), we recorded respiration, RR-intervals (RRI), systolic and diastolic blood-pressure (BPsys, BPdia), before and during EPS (120 sec; 30 mmHg), using an ocular-pressure-device (Okulopressor®). We calculated spectral-powers of mainly sympathetic low (LF: 0.04-0.15 Hz) and parasympathetic high (HF: 0.15-0.5 Hz) frequency RRI-fluctuations, sympathetically mediated LF-powers of BPsys, and calculated normalized (nu) LF- and HF-powers of RRI. We compared parameters between groups before and during EPS by repeated-measurement-analysis-of-variance with post-hoc analysis (significance: p < 0.05). RESULTS: At rest, sympathetically mediated LF-BPsys-powers were significantly lower in the patients than the controls. During EPS, only controls significantly increased RRIs and parasympathetically mediated HFnu-RRI-powers, but decreased LF-RRI-powers, LFnu-RRI-powers, and LF-BPsys-powers; in contrast, the patients slightly though significantly increased BPsys upon EPS, without changing any other parameter. CONCLUSIONS: In post-moderate-severe-TBI patients, autonomic BP-modulation was already compromised at rest. During EPS, our patients failed to activate cardiovagal modulation but slightly increased BPsys, indicating persistent CAN dysregulation. SIGNIFICANCE: Our findings unveil persistence of subtle cardiovascular-autonomic dysregulation even years after TBI.
EVALuna2:36357

Eyeball Pressure Stimulation Unveils Subtle Autonomic Cardiovascular Dysfunction in Persons with a History of Mild Traumatic Brain Injury - Hilz, Max-Josef; Aurnhammer, Felix; Flanagan, Steven R.; Intravooth, Tassanai; Wang, Ruihao; Hoesl, Katharina M.; Pauli, Elisabeth; Koehn, Julia (Journal of Neurotrauma, 2015)
After mild traumatic brain injury (mTBI), patients have increased long-term mortality rates, persisting even beyond 13 years. Pathophysiology is unclear. Yet, central autonomic network dysfunction may contribute to cardiovascular dysregulation and increased mortality. Purely parasympathetic cardiovascular challenge by eyeball pressure stimulation (EP), might unveil subtle autonomic dysfunction in post-mTBI patients. We investigated whether mild EP shows autonomic cardiovascular dysregulation in post-mTBI patients. In 24 patients (34 ± 12 years; 5-86 months post-injury) and 27 controls (30 ± 11 years), we monitored respiration, electrocardiographic RR intervals (RRI), systolic and diastolic blood pressure (BPsys, BPdia) before and during 2 min of 30 mm Hg EP, applied by an ophthalmologic ocular pressure device (Okulopressor(®)). We calculated spectral powers of RRI in the mainly sympathetic low frequency (LF; 0.04-0.15 Hz) and parasympathetic high frequency (HF; 0.15-0.5 Hz) ranges, and of BP in the sympathetic LF range, the RRI-LF/HF ratio as index of the sympathetic-parasympathetic balance, normalized (nu) RRI-LF- and HF-powers, and LF- and HF-powers after natural logarithmic transformation (ln). Parameters before and during EP in post-mTBI patients and controls were compared by repeated measurement analysis of variance with post hoc analysis (p < 0.05). During EP, BPsys and BPdia increased in post-mTBI patients. Only in controls but not in post-mTBI patients, EP increased RRI-HFnu-powers and decreased RRI-LF-powers, RRI-LFnu-powers, BPsys-LF-powers, BPsys-lnLF-powers and BPdia-lnLF-powers. RRI-LF/HF ratios slightly increased in post-mTBI patients but slightly decreased in controls upon EP. Even with only mild EP, our controls showed normal EP responses and shifted sympathetic-parasympathetic balance towards parasympathetic predominance. In contrast, our post-mTBI patients could not increase parasympathetic heart rate modulation but increased BP upon EP, indicating a paradox sympathetic activation. The findings support the hypothesis that central autonomic dysfunction might contribute to an increased cardiovascular risk, even years after mTBI.
EVALuna2:22373

Factors associated with occurrence and outcome of super-refractory status epilepticus - Madzar, Dominik; Knappe, Ruben U.; Reindl, Caroline; Giede-Jeppe, Antje; Sprügel, Maximilian; Beuscher, Vanessa; Gollwitzer, Stephanie; Hamer, Hajo; Huttner, Hagen (Seizure-European Journal of Epilepsy, 2017)
Super-refractory status epilepticus (SRSE) represents a challenging medical condition with high morbidity and mortality. In this study, we aimed to establish variables related to SRSE development and outcome.We retrospectively screened our databases for refractory SE (RSE) and SRSE episodes between January 2001 and January 2015. Baseline demographics, SE characteristics, and variables reflecting the clinical course were compared in order to identify factors independently associated with SRSE occurrence. Within the SRSE cohort, predictors of in-hospital mortality as well as good functional outcome in survivors to discharge were established through univariate and multivariable analyses.A total of 131 episodes were included, among those 46 (35.1%) meeting the criteria of SRSE. Comparison of RSE and SRSE episodes revealed a lower premorbid mRS score (odds ratio (OR) per mRS point, 0.769; p=0.039) and non-convulsive SE (NCSE) in coma (OR, 4.216; p=0.008) as independent predictors of SRSE. SRSE in-hospital mortality was associated with age (OR, 1.091 per increasing year; p=0.020) and worse premorbid functional status (OR, 1.938 per mRS point; p=0.044). Good functional outcome in survivors was independently related to shorter SRSE duration (OR, 0.714 per day; p=0.038).Better premorbid functional status and NCSE in coma as worst seizure type indicate a role of acute underlying etiologies in the development of SRSE. In-hospital mortality in SRSE is determined by nonmodifiable factors, while functional outcome in survivors depends on seizure duration underscoring the need of achieving rapid seizure termination.
EVALuna2:22567

Fatal Liver and Bone Marrow Toxicity by Combination Treatment of Dichloroacetate and Artesunate in a Glioblastoma Multiforme Patient: Case Report and Review of the Literature - Uhl, Martin; Schwab, Stefan; Efferth, Thomas (Frontiers in Oncology, 2016)
A 52-year-old male patient was treated with standard radiochemotherapy with temozolomide for glioblastoma multiforme (GBM). After worsening of his clinical condition, further tumor-specific treatment was unlikely to be successful, and the patient seeked help from an alternative practitioner, who administered a combination of dichloroacetate (DCA) and artesunate (ART). A few days later, the patient showed clinical and laboratory signs of liver damage and bone marrow toxicity (leukopenia, thrombocytopenia). Despite successful restoration of laboratory parameters upon symptomatic treatment, the patient died 10 days after the infusion. DCA bears a well-documented hepatotoxic risk, while ART can be considered as safe concerning hepatotoxicity. Bone marrow toxicity can appear upon ART application as reduced reticulocyte counts and disturbed erythropoiesis. It can be assumed that the simultaneous use of both drugs caused liver injury and bone marrow toxicity. The compassionate use of DCA/ART combination therapy outside of clinical trials cannot be recommended for GBM treatment.
EVALuna2:22527

Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-Dimensional Projections of Three-Dimensional Diffusion MRI Data. - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja W. (Frontiers in Neurology, 2015)
This study was conducted to assess the feasibility and diagnostic accuracy of brain artery territory recognition based on geoprojected two-dimensional maps of diffusion MRI data in stroke patients. In this retrospective study, multiplanar diffusion MRI data of ischemic stroke patients was used to create a two-dimensional map of the entire brain. To guarantee correct representation of the stroke, a computer-aided brain artery territory diagnosis was developed and tested for its diagnostic accuracy. The test recognized the stroke-affected brain artery territory based on the position of the stroke in the map. The performance of the test was evaluated by comparing it to the reference standard of each patient’s diagnosed stroke territory on record. This study was designed and conducted according to Standards for Reporting of Diagnostic Accuracy (STARD). The statistical analysis included diagnostic accuracy parameters, cross-validation, and Youden Index optimization. After cross-validation on a cohort of 91 patients, the sensitivity of this territory diagnosis was 81% with a specificity of 87%. With this, the projection of strokes onto a two-dimensional map is accurate for representing the affected stroke territory and can be used to provide a static and printable overview of the diffusion MRI data. The projected map is compatible with other two-dimensional data such as EEG and will serve as a useful visualization tool.
Keywords: computer-aided detection and diagnosis; diffusion-weighted imaging; dimensionality reduction; magnetic resonance imaging; stroke territories; validation; visualization

Feasibility of certified quality management in a comprehensive stroke care network using telemedicine: STENO project - Handschu, Rene; Scibor, Mateusz; Wacker, Angela; Stark, David Rianto; Köhrmann, Martin; Erbguth, Frank; Oschmann, Patrick; Schwab, Stefan; Marquardt, Lars (International Journal of Stroke, 2014)
Stroke care networks with and without telemedicine have been established in several countries over the last decade to provide specialized stroke expertise to patients in rural areas. Acute consultation is a first step in the management of stroke, but not the only one. Methods of standardization of care and treatment are much needed. So far, quality management systems have only been used for single stroke units. To the best of our knowledge, we are the first stroke network worldwide to aim for certification of a network-wide quality management system.The Stroke Network Using Telemedicine in Northern Bavaria (STENO), currently with 20 associated medical institutions, is one of the world's largest stroke networks, caring for over 5000 stroke patients each year. In 2010, we initiated the implementation of a network-wide 'total' quality management system according to ISO standard 9001:2008 in cooperation with the German Stroke Society and a third-party certification organization (LGA InterCert).Certification according to ISO 9001:2008 was awarded in March 2011 and maintained over a complete certification cycle of 3 years without major deviation from the norm in three external third-party audits. Thrombolysis rate significantly increased from 8·2% (2009) to 12·8% (2012).Certified quality management within a large stroke network using telemedicine is possible and might improve stroke care procedures and thrombolysis rates. Outcome studies comparing conventional stroke care and telestroke care are inevitable.
EVALuna2:22263

Fenfluramine in clinical practice: new therapy option for Dravet and Lennox–Gastaut syndromes - Muhle, Hiltrud; Kurlemann, Gerhard; Lehmann, Irene; Hamer, Hajo; Mayer, Thomas; Potschka, Heidrun; Schubert-Bast, Susanne; Strzelczyk, Adam; Pringsheim, Milka (Clinical Epileptology, 2024)
Fenfluramine is an antiseizure medication for the treatment of Dravet and Lennox–Gastaut syndromes. This review summarizes the literature on the efficacy and tolerability of fenfluramine and presents recommendations for practical therapeutic management. With regular monitoring, this medication is generally well tolerated and to date has shown no cardiac side effects such as valve insufficiency or pulmonary hypertension in the clinical development program. However, children may experience a loss of appetite and should be closely monitored for weight loss, and sedation was observed in several overweight patients due to rapid dosage titration; therefore, a slower dosage increase than recommended might be needed for children and adults. Drug interactions should be considered before and during therapy, and dosage reductions are necessary when the medication is used in combination with stiripentol. Furthermore, bromide levels could increase with this medication. Contact with the patient or their relatives is important to determine the general state of health, potential movement disturbances, and seizure frequency so as to allow for timely dosage adjustments during the titration phase.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Anti-seizure medication; Developmental and epileptic encephalopathy; Drug interactions; Epilepsy

Fibrinolysis Treatment for Cerebral Intraventricular Hemorrhage: A Temporal and Spatial Voxel-Based Analysis - Strinitz, Marc; Kuramatsu, Joji; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Seifert, Frank (Journal of Neuroimaging, 2016)
A voxel-based statistical approach on computer tomographic data in patients with intracerebral hemorrhage (ICH) and acute intraventricular hemorrhage (IVH) was used to evaluate spatial and temporal patterns of intraventricular blood in patients treated with intraventricular fibrinolysis (IVF) or without.IVH shapes were systematically assessed three dimensionally in patients with supratentorial ICH at three intervals of time (day of admission, day 4 ± 1, day 7+). The boundaries of the intraventricular blood clot were delineated on computed tomography (CT) scans using dedicated software. The CT scan and the IVH shape were transferred into stereotaxic space. In a second step, voxel-based statistics on group level were used to correlate the distribution of intraventricular blood with the interval and the treatment group.Altogether 45 patients, 29 with IVF therapy and 16 without, were eligible to be included into this study. We found significant (false discovery rate [FDR] correction, q < .05) reduction of the intraventricular blood between day of admission and day 7 + for the third and fourth ventricle and parts of both lateral ventricles. In addition, we were able to show a significant difference between the IVF therapy and the conventionally treated group at day 4 ± 1 for the third ventricle.The data indicate that voxel-based analysis on group level can be used to compare the time course and the distribution of intraventricular hemorrhage. This technique could be an interesting tool for future research on ICH with IVH.
EVALuna2:22457

Fingolimod does not seem to alter autonomic modulation of bladder in patients with relapsing-remitting multiple sclerosis - Hilz, Max-Josef; Winder, Klemens; Linker, Ralf; Lee, De-Hyung; Wang, Ruihao (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Fingolimod effects in neuroinflammation: Regulation of astroglial glutamate transporters? - Lee, De-Hyung; Seubert, Silvia; Huhn, Konstantin; Brecht, Lukas; Rötger, Caroline; Waschbisch, Anne; Schlachetzki, Johannes; Klausmeyer, Alice; Melms, Arthur; Wiese, Stefan; Winkler, Jürgen; Linker, Ralf (PLoS ONE, 2017)
Fingolimod is an oral sphingosine-1-phosphate-receptor modulator which reduces the recirculation of immune cells and may also directly target glial cells. Here we investigate effects of fingolimod on expression of astroglial glutamate transporters under pro-inflammatory conditions. In astrocyte cell culture, the addition of pro-inflammatory cytokines led to a significant downregulation of glutamate transporters glutamate transporter-1 (slc1a2/SLC1A2) and glutamate aspartate transporter (slc1a3/SLC1A3) expression on the mRNA or protein level. In this setting, the direct application of fingolimod-1 phosphate (F1P) on astrocytes did not change expression levels of slc1a2 and slc1a3 mRNA. The analysis of both transporters on the protein level by Western Blot and immunocytochemistry did also not reveal any effect of F1P. On a functional level, the addition of conditioned supernatants from F1P treated astrocytes to neuronal cell culture did not result in increased neurite growth. In experimental autoimmune encephalomyelitis as a model of multiple sclerosis, fingolimod treatment reduced T cell and macrophages/microglia mediated inflammation and also diminished astrocyte activation. At the same time, fingolimod restored the reduced expression of slc1a2 and slc1a3 in the inflamed spinal cord on the mRNA level and of SLC1A2 and SLC1A3 on the protein level, presumably via indirect, anti-inflammatory mechanisms. These findings provide further evidence for a predominantly peripheral effect of the compound in neuroinflammation.
EVALuna2:22494

Fingolimod induced reduction in cardiac autonomic regulation is fully reversible after lingolimod discontinuation - Hilz, Max-Josef; Wang, Ruihao; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Hoesl, K.; Lee, De-Hyung; Linker, Ralf (2017)
EVALuna2:35713

Fingolimod initiation in multiple sclerosis patients is associated with potential beneficial cardiovascular autonomic effects - Hilz, Max J.; Wang, Ruihao; de Rojas Leal, Carmen; Liu, Mao; Canavese, Francesca; Roy, Sankanika; Hoesl, Katharina M.; Winder, Klemens; Lee, De-Hyung; Linker, Ralf (Therapeutic Advances in Neurological Disorders, 2017)
Fingolimod slows heart rate (HR) due to vagomimetic effects and might cause additional cardiovascular autonomic changes. While the time course of HR changes is well described, the extent and course of cardiovascular autonomic changes upon fingolimod initiation has not yet been evaluated. This study, therefore, intended to assess cardiovascular autonomic changes during the first 6 h after fingolimod initiation.In 21 patients with relapsing-remitting multiple sclerosis (RRMS), we recorded respiration (RESP), electrocardiographic RR interval (RRI), systolic and diastolic blood pressure (BPsys, BPdia) at rest, before and 0.5, 1, 2, 3, 4, 5, and 6 h after fingolimod initiation. We calculated parameters of total autonomic modulation [RRI standard deviation (RRI-SD), RRI coefficient of variation (RRI-CV), RRI-total powers], mainly sympathetic cardiac modulation [RRI low frequency (LF) powers], sympathetic BP modulation (BPsys-LF powers), parasympathetic modulation [square root of the mean squared difference of successive RRIs (RMSSD), RRI high frequency (HF) powers], sympatho-vagal cardiac balance (RRI-LF/HF ratios), and baroreflex sensitivity (BRS). We compared parameters between the eight measurements [analysis of variance (ANOVA) or Friedman test with post-hoc analysis; significance: p < 0.05].After fingolimod initiation, RESP, BPsys, and BPsys-LF powers remained unchanged while RRIs, RRI-CV, RRI-SD, RRI-total powers, RRI-LF powers, RMSSD, RRI-HF powers, and BRS increased after 1 h and rose to peak values occurring after 5, 1, 2, 2, 1, 4, 4, and 4 h, respectively. After 3 h, BPdia had decreased significantly and was lowest after 5 h. RRI-LF/HF ratios decreased to a nadir after 4 h.The increases in parasympathetic and overall cardiac autonomic modulation and in BRS seen with fingolimod initiation are theoretically beneficial for the MS patient's cardiovascular system. However, long-term studies must show whether these effects persist or are attenuated (e.g. due to S1P1 receptor down-regulation upon continued fingolimod therapy).
EVALuna2:22503

First clinical postmarketing experiences in the treatment of epilepsies with brivaracetam: A retrospective observational multicentre study - Menzler, Katja; Mross, Peter Michael; Rosenow, Felix; Schubert-Bast, Susanne; Willems, Laurent Maximilian; Zahnert, Felix; Immisch, Ilka; Fuest, Sven; Von Podewils, Felix; Kunz, Rhina; Hirsch, Martin; Müller, Tamara; et al. (BMJ Open, 2019)
Objectives Brivaracetam (BRV) is the latest approved antiepileptic drug and acts as a synaptic vesicle protein 2A ligand. The aim of the present study was to evaluate the efficacy and tolerability of BRV in the clinical setting. Design Retrospective, observational multicentre study. Setting We retrospectively collected clinical data of patients who received BRV in 10 epilepsy centres using a questionnaire that was answered by the reporting neurologist. Participants Data of 615 epilepsy patients treated with BRV were included in the study. Primary and secondary outcome measures Efficacy regarding seizure frequency and tolerability of BRV were evaluated. Descriptive statistics complemented by X 2 contingency tests and effect sizes were performed. Results Overall, 44% of the patients had a decreased, 38% a stable and 18% an increased seizure frequency. 17% of patients achieved seizure freedom after initiation of BRV. The seizure frequency decreased in 63% of 19 patients with BRV monotherapy. 27% reported adverse effects, but only 10% of patients with monotherapy. Brivaracetam was significantly more often associated with decreased seizure frequency in levetiracetam (LEV) naïve patients (p=0.012), but BRV also led to a decreased seizure frequency in 42% of patients who had been treated with LEV before, including 17% of patients who were completely seizure free. Adverse effects under LEV improved in 62% and deteriorated in 2% of patients after the switch to BRV. At latest follow-up (mean±SD = 26.3±6.5 months), 68% were still on BRV. Conclusions The present study shows that results of the phase III studies on BRV match data from real life clinical settings. Brivaracetam seems to be a useful alternative in patients who have suffered adverse effects while taking LEV.
CRIS-Team Scopus Importer:2019-11-15
Keywords: adverse events; brivaracetam; efficacy; levetiracetam; monotherapy; tolerability

First epileptic Seizure - Strzelczyk, Adam; Hamer, Hajo (Deutsche Medizinische Wochenschrift, 2022)
Epileptische Anfalle sind ein haufiges klinisches Phanomen und die Lebenszeitpravalenz betragt bis zu 5%. Hierbei kommt es zu einer abnormalen exzessiven oder synchronen neuronalen Aktivitat im Gehirn, die sich klinisch in einer Sprachstorung, vermindertem Bewusstsein oder motorischen Entau ss erungen manifestieren kann.
CRIS-Team WoS Importer:2022-04-01

Flow-diverting stents allow efficient treatment of unruptured, intradural dissecting aneurysms of the vertebral artery: An explanatory approach using in vivo flow analysis - Gölitz, Philipp; Struffert, Tobias; Eyüpoglu, Ilker Yasin; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Interventional Neuroradiology, 2016)
Our study aimed to evaluate the efficiency of flow-diverting stents (FDS) in treating unruptured, intradural dissecting aneurysms of the vertebral artery (VADAs). Additionally, the effect of FDS on the aneurysmal flow pattern was investigated by performing in vivo flow analysis using parametric color coding (PCC).We evaluated 11 patients with unruptured, intradural VADAs, treated with FDS. Pre- and postinterventional DSA-series were postprocessed by PCC, and time-density curves were calculated. The parameters aneurysmal inflow-velocity, outflow-velocity and relative time-to-peak (rTTP) were calculated. Pre- and postinterventional values were compared and correlated with the occlusion rate after six months.Follow-up DSA detected 10 aneurysms occluded, meaning an occlusion rate of 91%. No procedure-related morbidity and mortality was found. Flow analyses revealed a significant reduction of aneurysmal inflow- velocity and prolongation of rTTP after FDS deployment. Concerning aneurysm occlusion, the postinterventional outflow-velocity turned out to be a marginally statistically significant predictor. A definite threshold value (-0.7 density change/s) could be determined for the outflow-velocity that allows prediction of complete aneurysm occlusion with high sensitivity and specificity (100%).Using FDS can be considered an efficient and safe therapy option in treating unruptured, intradural VADA. From in vivo flow analyses the postinterventional aneurysmal outflow-velocity turned out to be a potential predictor for later complete aneurysm occlusion. Here, it might be possible to determine a threshold value that allows prediction of aneurysm occlusion with high specificity and sensitivity. As fast, applicable and easy-to-handle tool, PCC could be used for procedural monitoring and might contribute to further treatment optimization.
EVALuna2:22441

FOCAL CORTICAL DYSPLASIA TYPE II IS MEG, MULTIMODAL NEURONAVIGATION AND INTRAOPERATIVE MR IMAGING HELPFUL FOR SURGERY? - Roessler, K.; Kasper, Burkhard; Heynold, Elisabeth; Coras, R.; Rampp, Stefan; Sommer, B.; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (2017)
EVALuna2:7380

Frameless stereotactic functional neuronavigation combined with intraoperative magnetic resonance imaging as a strategy in highly eloquent located tumors causing epilepsy - Sommer, Bjoern; Grummich, Peter; Hamer, Hajo; Blümcke, Ingmar; Coras, Roland; Buchfelder, Michael; Roessler, Karl (Stereotactic and Functional Neurosurgery, 2014)
Background: Intractable epilepsy due to tumors located in highly eloquent brain regions is often considered surgically inaccessible because of a high risk of postoperative neurological deterioration. Intraoperative MRI and functional navigation contribute to overcome this problem. Objectives: To retrospectively investigate the long-term results and impact of functional neuronavigation and 1.5-tesla intraoperative MRI on patients who underwent surgery of tumors associated with epilepsy located close to or within eloquent brain areas. Methods: Nineteen patients (9 female, 10 male, mean age 41.4 ± 13.4 years, 11 low-grade and 8 high-grade glial tumors) were evaluated preoperatively using BOLD imaging, diffusion-tensor imaging tractography and magnetoencephalography. Functional data were implemented into neuronavigation in this multimodal approach. Results: In 14 of 19 patients (74%), complete resection was achieved, and in 5 patients significant tumor volume reduction was accomplished. Eight of 14 (57%) complete resections were achieved only by performing an intraoperative image update. Neurological deterioration was found permanently in 2 patients. After a mean follow-up of 43.8 ± 23.8 months, 15 patients (79%) became seizure free (Engel class Ia). Conclusions: Despite the highly eloquent location of tumors causing intractable epilepsy, our multimodal approach led to complete resection in more than two-thirds of patients with an acceptable neurological morbidity and excellent long-term seizure control. © 2013 S. Karger AG, Basel.
EVALuna2:7222

From amaurotic idiocy to biochemically defined lipid storage diseases: the first identification of GM1-Gangliosidosis - Kasper, Burkhard S.; Thomas, Christian; Albers, Anne; Kasper, Ekkehard M.; Sandhoff, Konrad (Free Neuropathology, 2023)
On February 23rd 1936, a boy-child (“Kn”) died in an asylum near Munich after years of severe congenital disease, which had profoundly impaired his development leading to inability to walk, talk and see as well as to severe epilepsy. While a diagnosis of “Little’s disease” was made during life, his postmortem brain investigation at Munich neuropathology (“Deutsche Forschungsanstalt für Psychiatrie”) revealed the diagnosis of “amaurotic idiocy” (AI). AI, as exemplified by Tay-Sachs-Disease (TSD), back then was not yet understood as a specific inborn error of metabolism encompassing several disease entities. Many neuropathological studies were performed on AI, but the underlying processes could only be revealed by new scientific techniques such as biochemical analysis of nervous tissue, deciphering AI as nervous system lipid storage diseases, e.g. GM2-gangliosidosis. In 1963, Sandhoff & Jatzkewitz published an article on a “biochemically special form of AI” reporting striking differences when comparing their biochemical observations of hallmark features of TSD to tissue composition in a single case: the boy Kn. This was the first description of “GM1-Gangliosidosis”, later understood as resulting from genetically determined deficiency in beta-galactosidase. Here we present illustrative materials from this historic patient, including selected diagnostic slides from the case “Kn” in virtual microscopy, original records and other illustrative material available. Finally, we present results from genetic analysis performed on archived tissue proving beta-galactosidase-gene mutation, verifying the 1963 interpretation as correct. This synopsis shall give a first-hand impression of this milestone finding in neuropathology.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Amaurotic idiocy; Beta-galactosidase; GM1-gangliosidosis; Lipid storage disease; Tay-Sachs-Disease

From theory to practice: Critical points in the 2017 ILAE classification of epileptic seizures and epilepsies - Palmini, André; Akamatsu, Naoki; Bast, Thomas; Bauer, Sebastian; Baumgartner, Christoph; Benbadis, Selim; Bermeo-Ovalle, Adriana; Beyenburg, Stefan; Bleasel, Andrew; Bozorgi, Alireza; Brázdil, Milan; Carreño, Mar; et al. (Epilepsia, 2020)
CRIS-Team Scopus Importer:2020-02-28

Functional dissociation between cognitive estimation and object naming in focal temporal and frontal lobe epilepsies - Braun, Isabella; Schwarz, Michael; Walther, Katrin; Stemmler, Mark; Kasper, Burkhard; Hamer, Hajo (International Journal of Epilepsy, 2018)

Functional Long-Term Outcome after Left- versus Right-Sided Intracerebral Hemorrhage - Beuscher, Vanessa D.; Kuramatsu, Joji; Gerner, Stefan; Kohn, Julia; Lücking, Hannes; Kloska, Stephan; Huttner, Hagen (Cerebrovascular Diseases, 2017)
Hemispheric location might influence outcome after intracerebral hemorrhage (ICH). INTERACT suggested higher short-term mortality in right hemispheric ICH, yet statistical imbalances were not addressed. This study aimed at determining the differences in long-term functional outcome in patients with right- vs. left-sided ICH with a priori-defined sub-analysis of lobar vs. deep bleedings.Data from a prospective hospital registry were analyzed including patients with ICH admitted between January 2006 and August 2014. Data were retrieved from institutional databases. Outcome was assessed using the modified Rankin Scale (mRS) score. Outcome measures (long-term mortality and functional outcome at 12 months) were correlated with ICH location and hemisphere, and the imbalances of baseline characteristics were addressed by propensity score matching.A total of 831 patients with supratentorial ICH (429 left and 402 right) were analyzed. Regarding clinical baseline characteristics in the unadjusted overall cohort, there were differences in disfavor of right-sided ICH (antiplatelets: 25.2% in left ICH vs. 34.3% in right ICH; p < 0.01; previous ischemic stroke: 14.7% in left ICH vs. 19.7% in right ICH; p = 0.057; and presence/extent of intraventricular hemorrhage: 45.0% in left ICH vs. 53.0% in right ICH; p = 0.021; Graeb-score: 0 [0-4] in left ICH vs. 1 [0-5] in right ICH; p = 0.017). While there were no differences in mortality and in the proportion of patients with favorable vs. unfavorable outcome (mRS 0-3: 142/375 [37.9%] in left ICH vs. 117/362 [32.3%] in right ICH; p = 0.115), patients with left-sided ICH showed excellent outcome more frequently (mRS 0-1: 64/375 [17.1%] in left ICH vs. 43/362 [11.9%] in right ICH; p = 0.046) in the unadjusted analysis. After adjusting for confounding variables, a well-balanced group of patients (n = 360/hemisphere) was compared showing no differences in long-term functional outcome (mRS 0-3: 36.4% in left ICH vs. 33.9% in right ICH; p = 0.51). Sub-analyses of patients with deep vs. lobar ICH revealed also no differences in outcome measures (mRS 0-3: 53/151 [35.1%] in left deep ICH vs. 53/165 [32.1%] in right deep ICH; p = 0.58).Previously described differences in clinical end points among patients with left- vs. right-hemispheric ICH may be driven by different baseline characteristics rather than by functional deficits emerging from different hemispheric functions affected. After statistical corrections for confounding variables, there was no impact of hemispheric location on functional outcome after ICH.
EVALuna2:22480

Further evidence for plasma progranulin as a biomarker in bipolar disorder - Kittel-Schneider, Sarah; Weigl, Johannes; Volkert, Julia; Gessner, Alexandra; Schmidt, Brigitte; Hempel, Susanne; Kiel, Tilman; Olmes, David G.; Bartl, Jasmin; Weber, Heike; Kopf, Juliane; Reif, Andreas (Journal of Affective Disorders, 2014)
A recent study suggested that progranulin (encoded by the fronto-temporal dementia risk gene GRN) plasma levels are decreased in bipolar disorder (BD). Replication of this finding is however lacking.Progranulin plasma levels of bipolar patients (n=104) and healthy controls (n=80) were measured by enzyme-linked immunosorbent assay (ELISA). Participants were also genotyped for three single nucleotide polymorphisms (SNPs) in the GRN gene (rs2879096, rs4792938 and rs5848), and the effect of genetic variation on progranulin levels was examined.Plasma progranulin levels were decreased in BD (ANCOVA, p=0.001). Furthermore, age was significantly and positively correlated with plasma progranulin (Pearson?s correlation, r=0.269, p<0.001). Also, lithium treatment but no other medication had a significant effect on progranulin plasma levels (ANCOVA, p=0.007). Specifically in BD, the GRN SNP rs5848 was associated with progranulin plasma levels (Kruskal-Wallis test, p<0.005).Subgroup analysis regarding bipolar I vs. bipolar II subtype and polarity of the episode at sampling (manic vs. depressed vs. mixed vs. rapid cycling vs. euthymic) could only be performed with limited validity due to the relatively small sample size. The suitability of peripheral progranulin as a biomarker for BD is limited due to the overlap between patients and controls.The findings strengthen the evidence for progranulin being involved in pathomechanisms of bipolar disorder, and suggest a genetic determinant of progranulin concentrations that is relevant specifically in bipolar patients.
EVALuna2:22294

GAD Antibodies as Key Link Between Chronic Intestinal Pseudoobstruction, Autonomic Neuropathy, and Limb Stiffness in a Nondiabetic Patient: A CARE-Compliant Case Report and Review of the Literature - Maier, Andrea; Mannartz, Vera; Wasmuth, Hermann; Trautwein, Christian; Neumann, Ulf-Peter; Weis, Joachim; Grosse, Joachim; Fuest, Matthias; Hilz, Max-Josef; Schulz, Joerg B.; Haubrich, Christina (Medicine, 2015)
Chronic intestinal pseudoobstruction (CIP) can be a severe burden and even a life-threatening disorder. Typically, several years of uncertainty are passing before diagnosis. We are reporting the case of a young woman with a decade of severe, progressive gastrointestinal dysmotility. Unusually, she had also developed an autonomic neuropathy, and a stiff limb syndrome.In addition to achalasia and CIP the young woman also developed neuropathic symptoms: orthostatic intolerance, urinary retention, a Horner syndrome, and lower limb stiffness. Careful interdisciplinary diagnostics excluded underlying infectious, rheumatoid, metabolic or tumorous diseases.The detection of GAD (glutamic acid decarboxylase) antibodies, however, seemed to link CIP, autonomic neuropathy, and limb stiffness and pointed at an autoimmune origin of our patient's complaints. This was supported by the positive effects of intravenous immunoglobulin. In response to this therapy the body weight had stabilized, orthostatic tolerance had improved, and limb stiffness was reversed.The case suggested that GAD antibodies should be considered in CIP also in nondiabetic patients. This may support earlier diagnosis and immunotherapy.
EVALuna2:22374

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

Gap Analysis Regarding Prognostication in Neurocritical Care: A Joint Statement from the German Neurocritical Care Society and the Neurocritical Care Society - Wartenberg, Katja E.; Hwang, David Y.; Häusler, Karl Georg; Muehlschlegel, Susanne; Sakowitz, Oliver W.; Madžar, Dominik; Hamer, Hajo; Rabinstein, Alejandro A.; Greer, David M.; Hemphill, J. Claude; Meixensberger, Juergen; Varelas, Panayiotis N. (Neurocritical Care, 2019)
Background/Objective: Prognostication is a routine part of the delivery of neurocritical care for most patients with acute neurocritical illnesses. Numerous prognostic models exist for many different conditions. However, there are concerns about significant gaps in knowledge regarding optimal methods of prognostication. Methods: As part of the Arbeitstagung NeuroIntensivMedizin meeting in February 2018 in Würzburg, Germany, a joint session on prognostication was held between the German NeuroIntensive Care Society and the Neurocritical Care Society. The purpose of this session was to provide presentations and open discussion regarding existing prognostic models for eight common neurocritical care conditions (aneurysmal subarachnoid hemorrhage, intracerebral hemorrhage, acute ischemic stroke, traumatic brain injury, traumatic spinal cord injury, status epilepticus, Guillain–Barré Syndrome, and global cerebral ischemia from cardiac arrest). The goal was to develop a qualitative gap analysis regarding prognostication that could help inform a future framework for clinical studies and guidelines. Results: Prognostic models exist for all of the conditions presented. However, there are significant gaps in prognostication in each condition. Furthermore, several themes emerged that crossed across several or all diseases presented. Specifically, the self-fulfilling prophecy, lack of accounting for medical comorbidities, and absence of integration of in-hospital care parameters were identified as major gaps in most prognostic models. Conclusions: Prognostication in neurocritical care is important, and current prognostic models are limited. This gap analysis provides a summary assessment of issues that could be addressed in future studies and evidence-based guidelines in order to improve the process of prognostication.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Comorbidities; Outcome predictors; Prognostication; Self-fulfilling prophecy

Gaps Between Aims and Achievements in Therapeutic Modification of Neuronal Damage ("Neuroprotection") - Wiendl, Heinz; Elger, Christian; Foerstl, Hans; Hartung, Hans-Peter; Oertel, Wolfgang; Reichmann, Heinz; Schwab, Stefan (Neurotherapeutics, 2015)
The term "neuroprotection" is often misused, overused, or misunderstood. A reasonable definition of neuroprotection refers to the preservation of "neuronal structure and/or function." Although our knowledge about the cellular and molecular mechanisms of neurodegeneration has expanded, experimental systems and animal models that mimic the process or allow translation into clinical success remain limited. This editorial discusses reasons for this gap and strategies to close it. Experimental models can only mirror certain aspects of disease mechanisms in humans. Therefore, findings in these models need to be linked with patient data to improve real-life relevance. Successful neuroprotection depends on finding the right "window of opportunity" which varies from very short (stroke) to very long (Alzheimer's disease), necessitating the need to focus on strategies for very early disease recognition. This need challenges the strategies to be chosen, trial approaches and methodologies, and the allocation of resources. Additionally, outcome measures are often not well suited to assess neuroprotection. To this end, surrogate measures, including biomarkers, are useful endpoints to demonstrate evidence of target directed therapeutic utility. Finally, studies have shown that neuroprotection is not likely to succeed when targeting only one pathway. These obstacles have reduced the level of enthusiasm for neuroprotection in certain disease areas (e.g., stroke). Academia, industry, regulatory authorities, funding agencies and patient organizations have to cooperate to a greater extent in order to overcome these impediments and to encourage nonclassical concepts. These concepts will be interdisciplinary in order to achieve meaningful disease modification.
EVALuna2:22435

General Trends in Prices and Prescription Patterns of Anticonvulsants in Germany between 2000 and 2017: Analysis of National and Cohort-Based Data - Willems, Laurent M.; Hamer, Hajo; Knake, Susanne; Rosenow, Felix; Reese, Jens Peter; Strzelczyk, Adam (Applied Health Economics and Health Policy, 2019)
Objective: Our aim was to explore trends in price evolution and prescription volumes of anticonvulsants (AEDs, antiepileptic drugs) in Germany between 2000 and 2017. Method: This study used data from annual reports on mean prescription frequency and prices of defined daily doses (DDD) of AEDs in Germany to analyze nationwide trends. Interrupted time series (ITS) analysis was employed to test for significant effects of several statutory healthcare reforms in Germany on AED price evolution. These data were compared to cohort-based prescription patterns of four German cohort studies from 2003, 2008, 2013, and 2016 that included a total of 1368 patients with focal and generalized epilepsies. Results: Analysis of national prescription data between 2000 and 2017 showed that mean prices per DDD of third-generation AEDs decreased by 65% and mean prices of second-generation AEDs decreased by 36%, whereas mean prices of first-generation AEDs increased by 133%. Simultaneously, mean prescription frequency of third- generation AEDs increased by 2494%, while there was a substantial decrease in the use of first- (− 55%) and second- (− 16%) generation AEDs. ITS analysis revealed that in particular the introduction of mandatory rebates on drugs in 2003 affected prices of frequently used newer AEDs. These findings are consistent with data from cohort studies of epilepsy patients showing a general decrease of prices for frequently used AEDs in monotherapy by 62% and in combination therapies by 68%. The analysis suggests that overall expenses for AEDs remained stable despite an increase in the prescription of “newer” and “non-enzyme-inducing” AEDs for epilepsy patients. Conclusion: Between 2000 and 2017, a distinct decline in AED prices can be observed that seems predominately caused by a governmentally obtained price decline of third- and second-generation drugs. These observations seem to be the result of a German statutory cost containment policy applied across all health-care sectors. The increasing use of third-generation AEDs to the disadvantage of “old” and “enzyme-inducing” AEDs reflects the preferences of physicians and patients with epilepsy and follows national treatment guidelines.
CRIS-Team Scopus Importer:2019-06-18

Genital ulcers as diagnostic clue for acute myeloid leukaemia - Schröder, Sina; Krause, Stefan; Erfurt-Berge, Cornelia (International Wound Journal, 2018)
Acute myeloid leukaemia is a myeloid neoplasm with an extremely varying clinical appearance. Skin lesions are common for specific subtypes of acute myeloid leukaemia but are often misinterpreted. Here, we present a case of acute myeloid leukaemia in a young woman exhibiting genital ulcerations and gingival erosions.
EVALuna2:34278

Genomic DNA methylation distinguishes subtypes of human focal cortical dysplasia - Kobow, Katja; Ziemann, Mark; Kaipananickal, Harikrishnan; Khurana, Ishant; Mühlebner, Angelika; Feucht, Martha; Hainfellner, Johannes A.; Czech, Thomas; Aronica, Eleonora; Pieper, Tom; Holthausen, Hans; Kudernatsch, Manfred; et al. (Epilepsia, 2019)
Objectives: Focal cortical dysplasia (FCD) is a major cause of drug-resistant focal epilepsy in children, and the clinicopathological classification remains a challenging issue in daily practice. With the recent progress in DNA methylation–based classification of human brain tumors we examined whether genomic DNA methylation and gene expression analysis can be used to also distinguish human FCD subtypes. Methods: DNA methylomes and transcriptomes were generated from massive parallel sequencing in 15 surgical FCD specimens, matched with 5 epilepsy and 6 nonepilepsy controls. Results: Differential hierarchical cluster analysis of DNA methylation distinguished major FCD subtypes (ie, Ia, IIa, and IIb) from patients with temporal lobe epilepsy patients and nonepileptic controls. Targeted panel sequencing identified a novel likely pathogenic variant in DEPDC5 in a patient with FCD type IIa. However, no enrichment of differential DNA methylation or gene expression was observed in mechanistic target of rapamycin (mTOR) pathway–related genes. Significance: Our studies extend the evidence for disease-specific methylation signatures toward focal epilepsies in favor of an integrated clinicopathologic and molecular classification system of FCD subtypes incorporating genomic methylation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: diagnostic biomarker; epigenetic; focal cortical dysplasia; focal epilepsy; mTOR pathway

German Validation of the Composite Autonomic Symptom Score 31 - Wang, Ruihao; Canavese, Francesca; Intravooth, Tassanai; Singer, Wolfgang; Hilz, Max-Josef (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Glucocorticoid modulation of synaptic plasticity in the human temporal cortex of epilepsy patients: Does chronic stress contribute to memory impairment? - Brandner, Sebastian; Schröter, Sarah; Çalışkan, Gürsel; Salar, Seda; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Schwarz, Michael; Buchfelder, Michael; Maslarova, Anna (Epilepsia, 2021)
Objective: Memory impairment is common in patients with temporal lobe epilepsy and seriously affects life quality. Chronic stress is a recognized cofactor in epilepsy and can also impair memory function. Furthermore, increased cortisol levels have been reported in epilepsy patients. Animal models have suggested that aggravating effects of stress on memory and synaptic plasticity were mediated via glucocorticoids. The aim of this study was, therefore, to investigate the effect of glucocorticoid receptor (GR) modulation on synaptic plasticity in the human cortex of epilepsy patients. Methods: We performed field potential recordings in acute slices from the temporal neocortex of patients who underwent surgery for drug-resistant temporal lobe epilepsy. Synaptic plasticity was investigated by a theta-burst stimulation (TBS) protocol for induction of long-term potentiation (LTP) in the presence of GR modulators. Results: LTP was impaired in temporal cortex from epilepsy patients. Pretreatment of the slices with the GR antagonist mifepristone (RU486) improved LTP induction, suggesting that LTP impairment was due to baseline GR activation in the human cortex. The highly potent GR agonist dexamethasone additionally weakened synaptic strength in an activity-dependent manner when applied after TBS. Significance: Our results show a direct negative glucocorticoid effect on synaptic potentiation in the human cortex and imply chronic activation of GRs. Chronic stress may therefore contribute to memory impairment in patients with temporal lobe epilepsy. Furthermore, the activity-dependent acute inhibitory effect of dexamethasone suggests a mechanism of synaptic downscaling by which postictally increased cortisol levels may prevent pathologic plasticity upon seizures.
CRIS-Team Scopus Importer:2021-10-29
Keywords: dexamethasone; epilepsy; human cortex; long-term potentiation; stress

Glutathione PEGylated liposomal methylprednisolone (2B3-201) attenuates CNS inflammation and degeneration in murine myelin oligodendrocyte glycoprotein induced experimental autoimmune encephalomyelitis - Lee, De-Hyung; Roetger, Caroline; Appeldoorn, Chantal C. M.; Reijerkerk, Arie; Gladdines, Werner; Gaillard, Pieter J.; Linker, Ralf (Journal of Neuroimmunology, 2014)
Methylprednisolone (MP) pulses are the mainstay for relapse therapy in multiple sclerosis (MS). To improve the efficacy of treatment and reduce the side effects of MP, a long circulating brain-targeted formulation was developed; glutathione polyethylene glycol (PEG)ylated liposomal MP (2B3-201). Here we investigate the efficacy of 2B3-201 in murine myelin oligodendrocyte induced experimental autoimmune encephalomyelitis (MOG-EAE), an animal model mimicking inflammatory features and neurodegenerative aspects of MS. After disease onset, mice were randomized to receive either saline, three injections of free MP (high dose MP, 100mg/kg i.v.), two injections of free MP (low dose MP, 10mg/kg; i.v.), or two injections of 2B3-201 (10mg/kg i.v.). Treatment with a low dose of 2B3-201 significantly reduced the severity of EAE as compared to saline control, similar to treatment with high dose free MP, while a low dose of free MP was not effective. In a histological analysis of the spinal cord, treatment with 2B3-201 significantly decreased T cell as well as macrophage/microglia infiltration in the CNS by about 50%. Moreover, application of a low dose of 2B3-201 or a high dose of free MP reduced the amount of astrocyte activation as well as the extent of axonal loss and also demyelination in spinal cord lesions as compared to low dose MP or sham treatment. In summary, in the murine MOG-EAE model of MS, a glutathione PEGylated liposomal formulation of MP (2B3-201) is clinically and histologically as effective as free MP at one tenth of the dosage as well as at a lower application frequency and clearly more effective than the same dosage of free MP. These positive proof-of-concept efficacy studies warrant further development of 2B3-201 for the treatment of neuroinflammatory conditions such as MS.
EVALuna2:22300

Good outcome of brain stem progressive multifocal leukoencephalopathy in an immunosuppressed renal transplant patient: Importance of early detection and rapid immune reconstitution - Sauer, Rolf; Gölitz, Philipp; Jacobi, Johannes; Schwab, Stefan; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2017)
Progressive multifocal leukoencephalopathy (PML) is a rare, opportunistic and often fatal disease of the CNS which may occur under immunosuppression in transplant patients. Brain stem PML is associated with a particularly bad prognosis. Here, we present a case of a renal transplant patient treated with mycophenolate mofetil (MMF) and tacrolimus who developed brain stem PML with limb ataxia, dysarthria and dysphagia. Diagnosis was established by typical MRI features and detection of JCV-DNA in the CSF. Immune reconstitution after stopping MMF and tacrolimus led to a complete and sustained remission of symptoms with improvement of the brain stem lesion over a follow-up over 20months. In summary, early detection of PML and consequent treatment may improve neurological outcomes even in brain stem disease with a notorious bad prognosis.
EVALuna2:22499

Granulocyte colony-stimulating factor does not promote neurogenesis after experimental intracerebral haemorrhage - Kallmünzer, Bernd; Tauchi, Miyuki; Schlachetzki, Johannes; Machold, Kristin; Schmidt, Ariana; Winkler, Jürgen; Schwab, Stefan; Kollmar, Rainer (International Journal of Stroke, 2014)
Hematopoietic growth factors have been suggested to induce neuroprotective and regenerative effects in various animal models of cerebral injury. However, the pathways involved remain widely unexplored.This study aimed to investigate effects of local and systemic administration of granulocyte colony-stimulating factor on brain damage, functional recovery, and cerebral neurogenesis in an intracerebral haemorrhage whole blood injection model in rats.Eight-week-old male Wistar rats (n = 100) underwent induction of striatal intracerebral haemorrhage by autologous whole blood injection or sham procedure and were randomly assigned to either (a) systemic treatment with granulocyte colony-stimulating factor (60 ?g/kg) for five-days; (b) single intracerebral injection of granulocyte colony-stimulating factor (60 ?g/kg) into the cavity; or (c) application of vehicle for five-days. Bromodeoxyuridine-labelling and immunohistochemistry were used to analyze proliferation and survival of newly born cells in the sub-ventricular zone and the hippocampal dentate gyrus. Moreover, functional deficits and lesion volume were assessed until day 42 after intracerebral haemorrhage.Differences in lesion size or hemispheric atrophy between granulocyte colony-stimulating factor-treated and control groups did not reach statistical significance. Neither systemic, nor local granulocyte colony-stimulating factor administration induced neurogenesis within the dentate gyrus or the sub-ventricular zone. The survival of newborn cells in these regions was prevented by intracerebral granulocyte colony-stimulating factor application. A subtle benefit in functional recovery at day 14 after intracerebral haemorrhage induction was observed after granulocyte colony-stimulating factor treatment.There was a lack of neuroprotective or neuroregenerative effects of granulocyte colony-stimulating factor in the present rodent model of intracerebral haemorrhage. Conflicting results from functional outcome assessment require further research.
EVALuna2:22279

Guidelines on dermatomyositis–excerpt from the interdisciplinary S2k guidelines on myositis syndromes by the German Society of Neurology - Sunderkoetter, Cord; Nast, Alexander; Worm, Margitta; Dengler, Reinhard; Doerner, Thomas; Ganter, Horst; Hohlfeld, Reinhard; Melms, Arthur; Melzer, Nico; Roesler, Kai; Schmidt, Jens; Sinnreich, Michael; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
The present guidelines on dermatomyositis (DM) represent an excerpt from the interdisciplinary S2k guidelines on myositis syndromes of the German Society of Neurology (available at www.awmf.org). The cardinal symptom of myositis in DM is symmetrical proximal muscle weakness. Elevated creatine kinase, CRP or ESR as well as electromyography and muscle biopsy also provide important diagnostic clues. Pharyngeal, respiratory, cardiac, and neck muscles may also be affected. Given that approximately 30% of patients also develop interstitial lung disease, pulmonary function tests should be part of the diagnostic workup. Although the cutaneous manifestations in DM are variable, taken together, they represent a characteristic and crucial diagnostic criterion for DM. Approximately 5-20% of individuals exhibit typical skin lesions without any clinically manifest muscle involvement (amyopathic DM). About 30% of adult DM cases are associated with a malignancy. This fact, however, should not delay the treatment of severe myositis. Corticosteroids are the therapy of choice in myositis (1-2 mg/kg). Additional immunosuppressive therapy is frequently required (azathioprine, for children methotrexate). In case of insufficient therapeutic response, the use of intravenous immunoglobulins is justified. The benefit of rituximab has not been conclusively ascertained yet. Acute therapeutic management is usually followed by low-dose maintenance therapy for one to three years. Skin lesions do not always respond sufficiently to myositis therapy. Effective treatment for such cases consists of topical corticosteroids and sometimes also calcineurin inhibitors. Systemic therapies shown to be effective include antimalarial agents (also in combination), methotrexate, and corticosteroids. Intravenous immunoglobulins or rituximab may also be helpful. UV protection is an important prophylactic measure.
EVALuna2:22517

Gut immune cell trafficking: inter-organ communication and immune-mediated inflammation - Zundler, Sebastian; Günther, Claudia; Kremer, Andreas E.; Rothhammer, Veit; Neurath, Markus; Zaiss, Mario (Nature Reviews Gastroenterology & Hepatology, 2022)
Immune cell trafficking is a complex and tightly regulated process that is indispensable for the body’s fight against pathogens. However, it is also increasingly acknowledged that dysregulation of cell trafficking contributes to the pathogenesis of immune-mediated inflammatory diseases (IMIDs) in gastroenterology and hepatology, such as inflammatory bowel disease and primary sclerosing cholangitis. Moreover, altered cell trafficking has also been implicated as a crucial step in the immunopathogenesis of other IMIDs, such as rheumatoid arthritis and multiple sclerosis. Over the past few years, a central role of the gut in mediating these disorders has progressively emerged, and the partly microbiota-driven imprinting of particular cell trafficking phenotypes in the intestine seems to be crucially involved. Therefore, this Review highlights achievements in understanding immune cell trafficking to, within and from the intestine and delineates its consequences for immune-mediated pathology along the gut–liver, gut–joint and gut–brain axes. We also discuss implications for current and future therapeutic approaches that specifically interfere with homing, retention, egress and recirculation of immune cells.
CRIS-Team Scopus Importer:2022-08-26

Have attitudes toward epilepsy improved in Germany over the last 50 years? - Thorbecke, Rupprecht; Pfäfflin, Margarete; Bien, Christian G.; Hamer, Hajo; Holtkamp, Martin; Rating, Dietz; Schulze-Bonhage, Andreas; Straub, Hans Beatus; Strzelczyk, Adam; May, Theodor W. (Epilepsy and Behavior, 2023)
Objective: In Germany, six previous representative surveys on attitudes toward epilepsy (AE) have been conducted between 1967 and 2008 using the four original Caveness questions (CQs) from 1949 to 1980. The aims of this study were (1) to investigate changes in AE over the time span of 50 years, including the current survey in 2018 (2) to investigate the first-time emotional reactions measured with the Scales of Attitudes toward People with Epilepsy (SAPE) (3) to identify predictors of AE. Methods: A representative face-to-face survey with CQ, in addition with the SAPE scales of Social Distance, Stereotypes, Personal Concerns, and Emotional Reactions was carried out in Germany in 2018. One thousand and twenty-six persons who ever had heard of epilepsy participated. Respondents who answered “don't know” in the CQs were subsequently asked to answer only yes/no. The analysis of trends from 1967 to 2018 was based on the pooled data of the surveys. The four CQs in the 2018 survey were included in the SAPE item pool and an exploratory principal axis factor analysis was performed. General linear models were performed to identify predictors. Results: For all four CQs, the trend of improved AE was significant over the past 50 years. In the 2018 survey, excluding the “don't know” answer option increased the proportion of negative responses for contact of one's own children with a person with epilepsy (PWE) from 6.9% to 11.4% and for the marriage of one's own children with a PWE from 13.9% to 23.8%. When encountering a PWE, 30.1% would feel insecure or uncomfortable and nearly 60% were concerned that the PWE might be injured in case of a seizure. Knowing what to do in case of a seizure, knowing that seizures can be treated successfully, personal contact with a PWE along with younger age, and higher education were found to be the strongest predictors for positive AE identified by multivariate analyses. Exploratory principal axis factor analysis revealed that three of the four CQs items loaded > 0.30 at the factors of Social Distance and Stereotypes of SAPE but none on the factors measuring emotional reactions. Significance: AE measured by CQs have markedly improved in Germany over the last 50 years. Germany is to our knowledge the only country with such a long-term trend investigation in AE. Negative AE may be underestimated by survey questions with “don't know” answer option. Emotional aspects of attitudes are underexposed resp. neglected in the CQs, which are used worldwide for measuring AE. Additional tools like SAPE can close this gap. The identified predictors may help to derive interventions against negative AE.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Caveness; Emotional reaction; Long-term trends; Social distance; Stereotypes

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

Hematoma enlargement characteristics in deep versus lobar intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Sprügel, Maximilian; Röder, Sebastian; Madžar, Dominik; Hagen, Manuel; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Annals of Clinical and Translational Neurology, 2020)
Objective: Hematoma enlargement (HE) is associated with clinical outcomes after supratentorial intracerebral hemorrhage (ICH). This study evaluates whether HE characteristics and association with functional outcome differ in deep versus lobar ICH. Methods: Pooled analysis of individual patient data between January 2006 and December 2015 from a German-wide cohort study (RETRACE, I + II) investigating ICH related to oral anticoagulants (OAC) at 22 participating centers, and from one single-center registry (UKER-ICH) investigating non-OAC-ICH patients. Altogether, 1954 supratentorial ICH patients were eligible for outcome analyses, which were separately conducted or controlled for OAC, that is, vitamin-K-antagonists (VKA, n = 1186) and non-vitamin-K-antagonist-oral-anticoagulants (NOAC, n = 107). Confounding was addressed using propensity score matching, cox regression modeling and multivariate modeling. Main outcomes were occurrence, extent, and timing of HE (>33%/>6 mL) and its association with 3-month functional outcome. Results: Occurrence of HE was not different after deep versus lobar ICH in patients with non-OAC-ICH (39/356 [11.0%] vs. 36/305 [11.8%], P = 0.73), VKA-ICH (249/681 [36.6%] vs. 183/505 [36.2%], P = 0.91), and NOAC-ICH (21/69 [30.4%] vs. 12/38 [31.6%], P = 0.90). HE extent did not differ after non-OAC-ICH (deep:+59% [40–122] vs. lobar:+74% [37–124], P = 0.65), but both patients with VKA-ICH and NOAC-ICH showed greater HE extent after deep ICH [VKA-ICH, deep: +94% [54–199] vs. lobar: +56% [35–116], P < 0.001; NOAC-ICH, deep: +74% [56–123] vs. lobar: +40% [21–49], P = 0.001). Deep compared to lobar ICH patients had higher HE hazard during first 13.5 h after onset (Hazard ratio [HR]: 1.85 [1.03–3.31], P = 0.04), followed by lower hazard (13.5–26.5 h, HR: 0.46 [0.23–0.89], P = 0.02), and equal hazard thereafter (HR: 0.96 [0.56–1.65], P = 0.89). Odds ratio for unfavorable outcome was higher after HE in deep (4.31 [2.71–6.86], P < 0.001) versus lobar ICH (2.82 [1.71–4.66], P < 0.001), and only significant after small-medium (1st volume-quarter, deep: 3.09 [1.52–6.29], P < 0.01; lobar: 3.86 [1.35–11.04], P = 0.01) as opposed to large-sized ICH (4th volume-quarter, deep: 1.09 [0.13–9.20], P = 0.94; lobar: 2.24 [0.72–7.04], P = 0.17). Interpretation: HE occurrence does not differ among deep and lobar ICH. However, compared to lobar ICH, HE after deep ICH is of greater extent in OAC-ICH, occurs earlier and may be of greater clinical relevance. Overall, clinical significance is more apparent after small–medium compared to large-sized bleedings.
CRIS-Team Scopus Importer:2020-03-17

Hematoma Expansion and Clinical Outcomes in Patients With Factor-Xa Inhibitor-Related Atraumatic Intracereoral Hemorrhage Treated Within the ANNEXA-4 Trial Versus Real-World Usual Care - Huttner, Hagen; Gerner, Stefan; Kuramatsu, Joji; Connolly, Stuart J.; Beyer-Westendorf, Jan; Demchuk, Andrew M.; Middeldorp, Saskia; Zotova, Elena; Altevers, Julia; Andersohn, Frank; Christoph, Mary J.; Yue, Patrick; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: It is unestablished whether andexanet alfa, compared with guideline-based usual care including prothrombin complex concentrates, is associated with reduced hematoma expansion (HE) and mortality in patients with factor-Xa inhibitor-related intracerebral hemorrhage (ICH). We compared the occurrence of HE and clinical outcomes in patients treated either with andexanet alfa or with usual care during the acute phase of factor-Xa inhibitor-related ICH.
CRIS-Team WoS Importer:2022-02-04

Hematoma expansion in intracerebral hemorrhage – the right target? - Haupenthal, David; Schwab, Stefan; Kuramatsu, Joji (Neurological Research and Practice, 2023)
Background: The avoidance of hematoma expansion is the most important therapeutic goal during acute care of patients with intracerebral hemorrhage. Hematoma expansion occurs in up to 20–40% of patients and leads to poorer patient outcome in one of the most severe sub-types of stroke. Main text: At current, randomized controlled trials have failed to provide evidence for interventions that effectively improve functional outcome in patients with intracerebral hemorrhage. Hence, hematoma expansion may serve as important surrogate target that appears causally linked with a poorer prognosis. Therefore, reduction of hematoma expansion rates will eventually translate to improved patient outcome overall. Recent years have shed light on the importance of early and aggressive treatment in order to reduce the risk for hematoma expansion in these patients. Time measures and imaging markers have been identified that may allow patient selection at very high risk for hematoma expansion. Conclusions: Refinements in patient selection may increase chance for randomized trials to show true benefit. Therefore, this current review article will critically evaluate and discuss available evidence associated with hematoma expansion in patients with intracerebral hemorrhage.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blood pressure management; Hematoma enlargement; Hematoma expansion; Hemostatic therapies; Intracerebral hemorrhage

Heparin for prophylaxis of venous thromboembolism in intracerebral haemorrhage - Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2019)
Objective: To determine the occurrence of intracranial haemorrhagic complications (IHC) on heparin prophylaxis (low-dose subcutaneous heparin, LDSH) in primary spontaneous intracerebral haemorrhage (ICH) (not oral anticoagulation-associated ICH, non-OAC-ICH), vitamin K antagonist (VKA)-associated ICH and non-vitamin K antagonist oral anticoagulant (NOAC)-associated ICH. Methods: Retrospective cohort study (RETRACE) of 22 participating centres and prospective single-centre study with 1702 patients with VKA-associated or NOAC-associated ICH and 1022 patients with non-OAC-ICH with heparin prophylaxis between 2006 and 2015. Outcomes were defined as rates of IHC during hospital stay among patients with non-OAC-ICH, VKA-ICH and NOAC-ICH, mortality and functional outcome at 3 months between patients with ICH with and without IHC. Results: IHC occurred in 1.7% (42/2416) of patients with ICH. There were no differences in crude incidence rates among patients with VKA-ICH, NOAC-ICH and non-OAC-ICH (log-rank p=0.645; VKA-ICH: 27/1406 (1.9%), NOAC-ICH 1/130 (0.8%), non-OAC-ICH 14/880 (1.6%); p=0.577). Detailed analysis according to treatment exposure (days with and without LDSH) revealed no differences in incidence rates of IHC per 1000 patient-days (LDSH: 1.43 (1.04-1.93) vs non-LDSH: 1.32 (0.33-3.58), conditional maximum likelihood incidence rate ratio: 1.09 (0.38-4.43); p=0.953). Secondary outcomes showed differences in functional outcome (modified Rankin Scale=4-6: IHC: 29/37 (78.4%) vs non-IHC: 1213/2048 (59.2%); p=0.019) and mortality (IHC: 14/37 (37.8%) vs non-IHC: 485/2048 (23.7%); p=0.045) in disfavour of patients with IHC. Small ICH volume (OR: volume <4.4 mL: 0.18 (0.04-0.78); p=0.022) and low National Institutes of Health Stroke Scale (NIHSS) score on admission (OR: NIHSS <4: 0.29 (0.11-0.78); p=0.014) were significantly associated with fewer IHC. Conclusions: Heparin administration for venous thromboembolism (VTE) prophylaxis in patients with ICH appears to be safe regarding IHC among non-OAC-ICH, VKA-ICH and NOAC-ICH in this observational cohort analysis. Randomised controlled trials are needed to verify the safety and efficacy of heparin compared with other methods for VTE prevention.
CRIS-Team Scopus Importer:2019-05-02
Keywords: cerebrovascular disease; critical care; intracerebral heamorrhage; stroke

High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272

High salt drives Th17 responses in experimental autoimmune encephalomyelitis without impacting myeloid dendritic cells - Joerg, Stefanie; Kissel, Jan; Manzel, Arndt; Kleinewietfeld, Markus; Haghikia, Aiden; Gold, Ralf; Mueller, Dominik N.; Linker, Ralf (Experimental Neurology, 2016)
Recently, we have shown that high dietary salt intake aggravates T helper cell (Th) 17 responses and neuroinflammation. Here, we employed in vitro assays for myeloid dendritic cell (mDC) maturation, DC cytokine production, T cell activation and ex vivo analyses in murine experimental autoimmune encephalomyelitis (EAE) to investigate whether the salt effect on Th17 cells is further mediated through DCs in vivo. In cell culture, an excess of 40mM sodium chloride did neither affect the generation, maturation nor the function of DCs, but, in different assays, significantly increased Th17 differentiation. During the initiation phase of MOG35-55 EAE, we did not observe altered DC frequencies or co-stimulatory capacities in lymphoid organs, while IL-17A production and Th17 cells in the spleen were significantly increased. Complementary ex vivo analyses of the spinal cord during the effector phase of EAE showed increased frequencies of Th17 cells, but did not reveal differences in phenotypes of CNS invading DCs. Finally, adaption of transgenic mice harboring a MOG specific T cell receptor to a high-salt diet led to aggravated clinical disease only after active immunization. Wild-type mice adapted to a high-salt diet in the effector phase of EAE, bypassing the priming phase of T cells, only displayed mildly aggravated disease. In summary, our data argue for a direct effect of NaCl on Th17 cells in neuroinflammation rather than an effect primarily exerted via DCs. These data may further fuel our understanding on the dietary impact on different immune cell subsets in autoimmune diseases, such as multiple sclerosis.
EVALuna2:22455

Hippocampal neurons code individual episodic memories in humans - Kolibius, Luca D.; Roux, Frederic; Parish, George; Ter Wal, Marije; Van Der Plas, Mircea; Chelvarajah, Ramesh; Sawlani, Vijay; Rollings, David T.; Lang, Johannes; Gollwitzer, Stephanie; Walther, Katrin; Hopfengärtner, Rüdiger; et al. (Nature Human Behaviour, 2023)
The hippocampus is an essential hub for episodic memory processing. However, how human hippocampal single neurons code multi-element associations remains unknown. In particular, it is debated whether each hippocampal neuron represents an invariant element within an episode or whether single neurons bind together all the elements of a discrete episodic memory. Here we provide evidence for the latter hypothesis. Using single-neuron recordings from a total of 30 participants, we show that individual neurons, which we term episode-specific neurons, code discrete episodic memories using either a rate code or a temporal firing code. These neurons were observed exclusively in the hippocampus. Importantly, these episode-specific neurons do not reflect the coding of a particular element in the episode (that is, concept or time). Instead, they code for the conjunction of the different elements that make up the episode.
CRIS-Team Scopus Importer:2023-10-20

Histopathological Findings in Brain Tissue Obtained during Epilepsy Surgery - Blümcke, Ingmar; Spreafico, R.; Haaker, G.; Coras, R.; Kobow, K.; Bien, C. G.; Pfaefflin, M.; Elger, C.; Widman, G.; Schramm, J.; Becker, Albert; Braun, K. P.; et al. (New England Journal of Medicine, 2017)
Detailed neuropathological information on the structural brain lesions underlying seizures is valuable for understanding drug-resistant focal epilepsy.We report the diagnoses made on the basis of resected brain specimens from 9523 patients who underwent epilepsy surgery for drug-resistant seizures in 36 centers from 12 European countries over 25 years. Histopathological diagnoses were determined through examination of the specimens in local hospitals (41%) or at the German Neuropathology Reference Center for Epilepsy Surgery (59%).The onset of seizures occurred before 18 years of age in 75.9% of patients overall, and 72.5% of the patients underwent surgery as adults. The mean duration of epilepsy before surgical resection was 20.1 years among adults and 5.3 years among children. The temporal lobe was involved in 71.9% of operations. There were 36 histopathological diagnoses in seven major disease categories. The most common categories were hippocampal sclerosis, found in 36.4% of the patients (88.7% of cases were in adults), tumors (mainly ganglioglioma) in 23.6%, and malformations of cortical development in 19.8% (focal cortical dysplasia was the most common type, 52.7% of cases of which were in children). No histopathological diagnosis could be established for 7.7% of the patients.In patients with drug-resistant focal epilepsy requiring surgery, hippocampal sclerosis was the most common histopathological diagnosis among adults, and focal cortical dysplasia was the most common diagnosis among children. Tumors were the second most common lesion in both groups. (Funded by the European Union and others.).
EVALuna2:7385

Home-based telerehabilitation after stroke - Keidel, M.; Vauth, F.; Richter, J.; Hoffmann, B.; Soda, H.; Griewing, B.; Scibor, M. (Der Nervenarzt, 2017)
The use of modern information and telecommunication technologies enables telerehabilitation of neurological deficits in the domestic environment. The current state of studies on rehabilitative teletherapy for improvement of motor function and mobility deficits due to stroke is reviewed. Two neurolinguistic proof of concept studies investigating the efficacy of online interactive telespeech therapy are reported, which compared virtual screen to screen interactive telerehabilitation of aphasia after stroke and dysarthrophonia in Parkinson's disease to conventional face to face rehabilitation. The results of the studies indicate that the neurological rehabilitation of motor and communicative deficits in the domestic environment of patients by means of teletherapy is just as efficient as conventional rehabilitation. Under home-based telerehabilitation patient transfer becomes unnecessary. Rehabilitative Teletherapy is a posthospital component of a cross-sector supply chain for patients with handicaps or impairments due to stroke and other neurological diseases.
EVALuna2:36309

Hyponatremia is an independent predictor of in-hospital mortality in spontaneous intracerebral hemorrhage - Kuramatsu, Joji; Bobinger, Tobias; Volbers, Bastian; Staykov, Dimitre; Lücking, Hannes; Kloska, Stephan; Köhrmann, Martin; Huttner, Hagen (Stroke, 2014)
Hyponatremia is the most frequent electrolyte disturbance in critical care. Across various disciplines, hyponatremia is associated with increased mortality and longer hospital stay, yet in intracerebral hemorrhage (ICH) no data are available. This the first study that investigated the prevalence and clinical associations of hyponatremia in patients with ICH.This observational study included all consecutive spontaneous ICH patients (n=464) admitted during a 5-year period to the Department of Neurology. Patient characteristics, in-hospital measures, mortality, and functional outcome (90 days and 1 year) were analyzed to determine the effects of hyponatremia (Na<135 mEq/L). Multivariable regression analyses were calculated for factors associated with hyponatremia and predictors of in-hospital mortality.The prevalence of hyponatremia on hospital admission was 15.6% (n=66). Normonatremia was achieved and maintained in almost all hyponatremia patients<48 hours. In-hospital mortality was roughly doubled in hyponatremia compared with nonhyponatremia patients (40.9%; n=27 versus 21.1%; n=75), translating into a 2.5-fold increased odds ratio (P<0.001). Multivariable analyses identified hyponatremia as an independent predictor of in-hospital mortality (odds ratio, 2.2; 95% confidence interval, 1.05-4.62; P=0.037). Within 90 days after ICH, hyponatremia patients surviving hospital stay were also at greater risk of death (odds ratio, 4.8; 95% confidence interval, 2.1-10.6; P<0.001); thereafter, mortality rates were similar.Hyponatremia was identified as an independent predictor of in-hospital mortality with a fairly high prevalence in spontaneous ICH patients. The presence of hyponatremia at hospital admission is related to an increased short-term mortality in patients surviving acute care, possibly reflecting a preexisting condition that is linked to worse outcome due to greater comorbidity. Correction of hyponatremia does not seem to compensate its influence on mortality, which strongly warrants future research.
EVALuna2:22304

Identification of a rare presenilin 1 single amino acid deletion mutation (F175del) with unusual amyloid-β processing effects - Vöglein, Jonathan; Willem, Michael; Trambauer, Johannes; Schönecker, Sonja; Dieterich, Marianne; Biskup, Saskia; Giudici, Camilla; Utz, Kathrin; Oberstein, Timo; Brendel, Matthias; Rominger, Axel; Danek, Adrian; et al. (Neurobiology of Aging, 2019)
We report the novel presenilin 1 (PSEN1) single amino acid deletion mutation F175del. Comprehensive clinical work-up, including cerebral MRI, FDG-PET, and CSF analysis, was performed in a male who had developed forgetfulness at the age of 39. Alzheimer's disease dementia was diagnosed according to established criteria. The index patient manifested rapid progressive dementia, seizures, and myoclonus, and a Pisa syndrome as a side effect of donepezil treatment. The PSEN1 mutation F175del was found on genetic testing. It was rendered very likely pathogenic as amyloid-β (Aβ) peptide 42 was elevated in a cell culture model compared to presenilin 1 wild-type controls. An additional, unusual increase in Aβ39 indicates a rarely observed product line deviation in the generation of the shorter Aβ species. Our observations extend the range of PSEN1 mutations to be considered in familial dementia. We demonstrate that deletion of a single conserved amino acid, which is very rare compared to missense mutations as the common cause for PSEN1-associated Alzheimer's disease, can lead to an unusual profile of Aβ species.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Alzheimer's disease; Autosomal dominant; Genetics; Novel mutation; PSEN1

ILAE neuroimaging task force highlight: Subcortical laminar heterotopia - Kasper, Burkhard S.; Archer, John; Bernhardt, Boris C.; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Concha, Luis; Federico, Paolo; Gaillard, William; Kobayashi, Eliane; Ogbole, Godwin; Vaudano, Anna Elisabetta; et al. (Epileptic Disorders, 2024)
The ILAE Neuroimaging Task Force publishes educational case reports that highlight basic aspects of neuroimaging in epilepsy consistent with the ILAE's educational mission. Subcortical laminar heterotopia, also known as subcortical band heterotopia (SBH) or “double cortex,” is an intriguing and rare congenital malformation of cortical development. SBH lesions are part of a continuum best designated as agyria-pachygyria-band-spectrum. The malformation is associated with epilepsy that is often refractory, as well as variable degrees of developmental delay. Moreover, in an increasing proportion of cases, a distinct molecular-genetic background can be found. Diagnosing SBH can be a major challenge for many reasons, including more subtle lesions, and “non-classic” or unusual MRI-appearances. By presenting an illustrative case, we address the challenges and needs of diagnosing and treating SBH patients in epilepsy, especially the value of high-resolution imaging and specialized MRI-protocols.<br
Keywords: double cortex; epilepsy; neuroimaging; subcortical band heterotopia; subcortical laminar heterotopia

Immunological and clinical consequences of splenectomy in a multiple sclerosis patient treated with natalizumab - Lee, De-Hyung; Waschbisch, Anne; Laemmer, Alexandra B.; Dörfler, Arnd; Schwab, Stefan; Linker, Ralf (Journal of Neuroinflammation, 2013)
Objective: Here we report a case of a splenectomized white woman with natalizumab-associated progressive multifocal leukoencephalopathy (PML), occurring as early as after 11 infusions and provide blood fluorescence-activated cell sorting (FACS) analyses before and after natalizumab treatment.Design: This is a report of a single case with immunological studies.Methods: Methods comprised neurologic examination, magnetic resonance imaging, and cerebrospinal fluid (CSF) studies as well as immune cell FACS analyses from blood.Results: Diagnosis of PML was established after positive John Cunningham virus (JCV) DNA was detected in the CSF. An immune reconstitution inflammatory syndrome was treated with repeated cycles of steroid pulses and intravenous immunoglobulins. Reduced numbers of memory B cells, which might play an important role in antiviral immune response, were detected in the blood. Moreover the percentage of CD19+ B cells was elevated in our post-splenectomy patient as compared to a control cohort of multiple sclerosis (MS) patients under natalizumab therapy.Conclusion: Splenectomy may increase the risk for the development of natalizumab-associated PML via effects on the B cell compartment. It may be regarded as a risk factor in MS patients independent from the duration of disease. © 2013 Lee et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CD19 positive B cells; Multiple sclerosis; Natalizumab; Progressive multifocal leukoencephalopathy; Splenectomy

Impact of combined sodium chloride and saturated long-chain fatty acid challenge on the differentiation of T helper cells in neuroinflammation - Hammer, Anna; Schliep, Anne; Joerg, Stefanie; Haghikia, Aiden; Gold, Ralf; Kleinewietfeld, Markus; Mueller, Dominik N.; Linker, Ralf (Journal of Neuroinflammation, 2017)
BACKGROUND: There has been a marked increase in the incidence of autoimmune diseases like multiple sclerosis (MS) in the last decades which is most likely driven by a change in environmental factors. Here, growing evidence suggests that ingredients of a Western diet like high intake of sodium chloride (NaCl) or saturated fatty acids may impact systemic immune responses, thus increasing disease susceptibility. Recently, we have shown that high dietary salt or long-chain fatty acid (LCFA) intake indeed aggravates T helper (Th) cell responses and neuroinflammation. METHODS: Naïve CD4+ T cells were treated with an excess of 40 mM NaCl and/or 250 μM lauric acid (LA) in vitro to analyze effects on Th cell differentiation, cytokine secretion, and gene expression. We employed ex vivo analyses of the model disease murine experimental autoimmune encephalomyelitis (EAE) to investigate whether salt and LCFA may affect disease severity and T cell activation in vivo. RESULTS: LCFA, like LA, together with NaCl enhance the differentiation of Th1 and Th17 cells as well as pro-inflammatory cytokine and gene expression in vitro. In cell culture, we observed an additive effect of LA and hypertonic extracellular NaCl (NaCl + LA) in Th17 differentiation assays as well as on IL-17, GM-CSF, and IL-2 gene expression. In contrast, NaCl + LA reduced Th2 frequencies. We employed EAE as a model of Th1/Th17 cell-mediated autoimmunity and show that the combination of a NaCl- and LA-rich diet aggravated the disease course and increased T cell infiltration into the central nervous system (CNS) to the same extent as dietary NaCl. CONCLUSIONS: Our findings demonstrate a partially additive effect of NaCl and LA on Th cell polarization in vitro and on Th cell responses in autoimmune neuroinflammation. These data may help to better understand the pathophysiology of autoimmune diseases such as MS.
EVALuna2:35525

Impact of early benefit assessment on patients with epilepsy in Germany: Current healthcare provision and therapeutic needs - Strzelczyk, Adam; Hamer, Hajo (Der Nervenarzt, 2016)
Epilepsy is one of the most common chronic neurological diseases and represents a significant burden for patients, their families and society. In more than 75 % of patients anticonvulsant therapy consists of valproate, carbamazepine, lamotrigine or levetiracetam. There is a need for polytherapy in drug-refractory patients and they suffer from negative effects on quality of life and employment that is associated with high indirect costs. To allow a comprehensive treatment in this patient group, access to new anticonvulsants with novel modes of action is needed; however, all applications for new antiepileptic drugs failed to prove added benefits during the Pharmaceutical Market Restructuring Act (AMNOG) in Germany. One of the main reasons is the mandatory definition of a standard comparative therapy. It remains unclear whether there will be studies in the future which will fulfill the requirements of the current version of AMNOG. Observational studies after approval and marketing of new antiepileptic drugs could be better alternatives to prove added benefits for individual patients in the current German healthcare system.
EVALuna2:22465

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Impact of Hypothermia Initiation and Duration on Perihemorrhagic Edema Evolution After Intracerebral Hemorrhage - Volbers, Bastian; Herrmann, Sabrina; Willfarth, Wolfgang; Lücking, Hannes; Kloska, Stephan; Dörfler, Arnd; Huttner, Hagen; Kuramatsu, Joji; Schwab, Stefan; Staykov, Dimitre (Stroke, 2016)
Intracerebral hemorrhage (ICH) causes high morbidity and mortality. Recently, perihemorrhagic edema (PHE) has been suggested as an important prognostic factor. Therapeutic hypothermia may be a promising therapeutic option to treat PHE. However, no data exist about the optimal timing and duration of therapeutic hypothermia in ICH. We examined the impact of therapeutic hypothermia timing and duration on PHE evolution.In this retrospective, single-center, case-control study, we identified patients with ICH treated with mild endovascular hypothermia (target temperature 35°C) from our institutional database. Patients were grouped according to hypothermia initiation (early: days 1-2 and late: days 4-5 after admission) and hypothermia duration (short: 4-8 days and long: 9-15 days). Patients with ICH matched for ICH volume, age, ICH localization, and intraventricular hemorrhage were identified as controls. Relative PHE, temperature, and intracranial pressure course were analyzed. Clinical outcome on day 90 was assessed using the modified Rankin scale (0-3=favorable and 4-6=poor).Thirty-three patients with ICH treated with hypothermia and 37 control patients were included. Early hypothermia initiation led to relative PHE decrease between admission and day 3, whereas median relative PHE increased in control patients (-0.05 [interquartile range, -0.4 to 0.07] and 0.07 [interquartile range, -0.07 to 0.26], respectively; P=0.007) and patients with late hypothermia initiation (0.22 [interquartile range 0.12-0.27]; P=0.037). After day 3, relative PHE increased in all groups without difference. Outcome was not different between patients treated with hypothermia and controls.Early hypothermia initiation after ICH onset seems to have an important impact on PHE evolution, whereas our data suggest only limited impact later than day 3 after onset.
EVALuna2:22477

Impact of Microbiome–Brain Communication on Neuroinflammation and Neurodegeneration - Stolzer, Iris; Scherer, Eveline; Süß, Patrick; Rothhammer, Veit; Winner, Beate; Neurath, Markus; Günther, Claudia (International Journal of Molecular Sciences, 2023)
The gut microbiome plays a pivotal role in maintaining human health, with numerous studies demonstrating that alterations in microbial compositions can significantly affect the development and progression of various immune-mediated diseases affecting both the digestive tract and the central nervous system (CNS). This complex interplay between the microbiota, the gut, and the CNS is referred to as the gut–brain axis. The role of the gut microbiota in the pathogenesis of neurodegenerative diseases has gained increasing attention in recent years, and evidence suggests that gut dysbiosis may contribute to disease development and progression. Clinical studies have shown alterations in the composition of the gut microbiota in multiple sclerosis patients, with a decrease in beneficial bacteria and an increase in pro-inflammatory bacteria. Furthermore, changes within the microbial community have been linked to the pathogenesis of Parkinson’s disease and Alzheimer’s disease. Microbiota–gut–brain communication can impact neurodegenerative diseases through various mechanisms, including the regulation of immune function, the production of microbial metabolites, as well as modulation of host-derived soluble factors. This review describes the current literature on the gut–brain axis and highlights novel communication systems that allow cross-talk between the gut microbiota and the host that might influence the pathogenesis of neuroinflammation and neurodegeneration.
CRIS-Team Scopus Importer:2023-11-03
Keywords: gut–brain-axis; microbial dysbiosis; neurodegenerative diseases

Impact of Perihemorrhagic Edema on Short-Term Outcome After Intracerebral Hemorrhage - Volbers, Bastian; Willfarth, Wolfgang; Schwab, Sibylle; Kuramatsu, J. B.; Huttner, Hagen; Struffert, Tobias; Dörfler, Arnd; Staykov, S. (Neurocritical Care, 2016)
Intracerebral hemorrhage (ICH) is a devastating disease with ICH volume being the main predictor of poor outcome. The prognostic role of perihemorrhagic edema (PHE) is still unclear; however, available data are mainly derived from analyses during the first days after symptom onset. As PHE growth may continue up to 14 days after ICH, we evaluated PHE over a longer period of time and investigated its impact on short-term clinical outcome.In this monocentric retrospective cohort study, patients with spontaneous supratentorial ICH were identified from our institutional data base. Different time points of CT scans were merged to time clusters for better comparison (day 1, 2-3, 4-6, 7-9, 10-12). Absolute volumes of ICH and PHE were obtained using a validated semiautomatic volumetric algorithm. Clinical outcome at discharge was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor).220 patients (83 with favorable, 137 with poor outcome) were included in the final analysis. Mean ICH volume on admission was 22.8 [standard deviation (SD) 24.6] cm(3). Mean absolute PHE volume on admission was 22.5 (SD 20.8) cm(3) and increased to a mean peak volume of 38.1 (SD 31.4) cm(3) during 6.7 (SD 4.1) days on average. Besides GCS on admission, functional status before ICH, peak hematoma volume, lobar localization and fever burden, and high peak PHE volume predicted poor outcome at discharge [OR 0.977 (95 % CI 0.957-0.998)] in the multivariable analysis.PHE may have a negative impact on short-term functional outcome after ICH and therefore represent a possible treatment target.
EVALuna2:22273

Impact of Recent Studies for the Treatment of Intracerebral Hemorrhage - Sembill, Jochen; Huttner, Hagen; Kuramatsu, Joji (Current Neurology and Neuroscience Reports, 2018)
PURPOSE OF REVIEW: The present review will cover most recent and important studies on acute treatment of intracerebral hemorrhage (ICH). RECENT FINDINGS: Overly pessimistic prognostication in ICH may deny meaningful recovery achieved by specialized neurocritical care. Hematoma enlargement represents the most important target of acute ICH care, which is reduced by aggressive blood pressure management (targeting a systolic blood pressure of 140 mmHg) and appropriate hemostatic treatment especially in anticoagulation-associated ICH (INR reversal using prothrombin complex concentrates, eventually idarucizumab, andexanet, or tranexamic acid). Surgical treatment strategies involving fibrinolytics either used for direct hematoma lysis or used for intraventricular clot removal with/without additional lumbar drainage show great promise. Further novel treatment strategies are underway and need validation or evaluation strongly warranting well-designed future ICH research. Several randomized and large-sized observational studies have considerably expanded the field and the evidence on how to treat acute ICH patients. Yet, the one breakthrough intervention to improve functional outcome is still missing, though various treatment concepts possibly interacting with one another have been evaluated and such treatment bundle may improve patients' outcome.
EVALuna2:201936

IMPACT OF STATINS ON HEMATOMA CHARACTERISTICS, PERIHEMORRHAGIC EDEMA, SEIZURES AND FUNCTIONAL RECOVERY AFTER INTRACEREBRAL HEMORRHAGE - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Saam, Justina; Gerner, Stefan; Balk, Stefanie; Hamer, Hajo; Lücking, Hannes; Hölter, Philip; Nolte, C.; Scheitz, J.; et al. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Impact of Statins on Hematoma, Edema, Seizures, Vascular Events, and Functional Recovery After Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Saam, Justina; Sembill, Jochen; Gerner, Stefan; Balk, Stefanie; Hamer, Hajo; Lücking, Hannes; Hölter, Philip; Nolte, Christian H.; Scheitz, Jan F.; et al. (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of statins on hematoma characteristics, perihemorrhagic edema (PHE), cardiovascular events, seizures, and functional recovery in patients with intracerebral hemorrhage (ICH) is insufficiently studied. METHODS: Patients with ICH of the prospective UKER-ICH (Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage) study (URL: https://www.clinicaltrials.gov; Unique identifier: NCT03183167) were analyzed by multivariable regression modeling and propensity score matching, and PHE volumes were volumetrically assessed. Outcomes comprised hematoma characteristics, the impact of continuation, discontinuation, and initiation of statins on peak PHE extent, and the influence of statin treatment on the occurrence of seizures, cardiovascular adverse events, and functional recovery after ICH. RESULTS: A total of 1275 patients with ICH with information on statin treatment were analyzed. Statin treatment on hospital admission (21.7%) was associated with higher rates of lobar versus nonlobar ICH (odds ratio, 1.57 [1.03-2.40]; P=0.038). Initiation of statins after ICH was associated with increased peak PHE (β=0.12, SE=0.06, P=0.008), whereas continuation versus discontinuation of prior statin treatment was not significantly associated with edema formation (P>0.10). There were no significant differences in the incidence of remote symptomatic seizures according to statin exposure during follow-up (statins: 11.5% versus no statins: 7.8%, subdistribution hazard ratio: 1.15 [0.80-1.66]; P=0.512). Patients on statins revealed less cardiovascular adverse events and more frequently functional recovery after 12 months (functional recovery: 57.7% versus 45.0%, odds ratio 1.67 [1.09-2.56]; P=0.019). CONCLUSIONS: Among statin users, lobar ICH occurs more frequently as compared with nonstatin users. While continuation of prior statin treatment appears to be safe regarding PHE formation, the initiation of statins during the first days after ICH may increase PHE extent. However, statins should be initiated thereafter (eg, at hospital discharge) to prevent cardiovascular events and potentially improve functional recovery.
CRIS-Team Scopus Importer:2021-03-19
Keywords: edema; hematoma; incidence; odds ratio; seizures

Impact of the coronavirus disease 2019 pandemic on stroke teleconsultations in Germany in the first half of 2020 - Vollmuth, Christoph; Miljukov, Olga; Abu-Mugheisib, Mazen; Angermaier, Anselm; Barlinn, Jessica; Busetto, Loraine; Grau, Armin J.; Guenther, Albrecht; Gumbinger, Christoph; Hubert, Nikolai; Hüttemann, Katrin; Klingner, Carsten; et al. (European Journal of Neurology, 2021)
Background and purpose: The effects of the coronavirus disease 2019 (COVID-19) pandemic on telemedical care have not been described on a national level. Thus, we investigated the medical stroke treatment situation before, during, and after the first lockdown in Germany. Methods: In this nationwide, multicenter study, data from 14 telemedical networks including 31 network centers and 155 spoke hospitals covering large parts of Germany were analyzed regarding patients' characteristics, stroke type/severity, and acute stroke treatment. A survey focusing on potential shortcomings of in-hospital and (telemedical) stroke care during the pandemic was conducted. Results: Between January 2018 and June 2020, 67,033 telemedical consultations and 38,895 telemedical stroke consultations were conducted. A significant decline of telemedical (p < 0.001) and telemedical stroke consultations (p < 0.001) during the lockdown in March/April 2020 and a reciprocal increase after relaxation of COVID-19 measures in May/June 2020 were observed. Compared to 2018–2019, neither stroke patients' age (p = 0.38), gender (p = 0.44), nor severity of ischemic stroke (p = 0.32) differed in March/April 2020. Whereas the proportion of ischemic stroke patients for whom endovascular treatment (14.3% vs. 14.6%; p = 0.85) was recommended remained stable, there was a nonsignificant trend toward a lower proportion of recommendation of intravenous thrombolysis during the lockdown (19.0% vs. 22.1%; p = 0.052). Despite the majority of participating network centers treating patients with COVID-19, there were no relevant shortcomings reported regarding in-hospital stroke treatment or telemedical stroke care. Conclusions: Telemedical stroke care in Germany was able to provide full service despite the COVID-19 pandemic, but telemedical consultations declined abruptly during the lockdown period and normalized after relaxation of COVID-19 measures in Germany.
CRIS-Team Scopus Importer:2021-04-02
Keywords: COVID-19; SARS-CoV-2; stroke; survey; telemedicine

Impact of timing of continuous intravenous anesthetic drug treatment on outcome in refractory status epilepticus - Madzar, Dominik; Reindl, Caroline; Giede-Jeppe, Antje; Bobinger, Tobias; Sprügel, Maximilian; Knappe, Ruben U.; Hamer, Hajo; Huttner, Hagen (Critical Care, 2018)
BACKGROUND: Patients in refractory status epilepticus (RSE) may require treatment with continuous intravenous anesthetic drugs (cIVADs) for seizure control. The use of cIVADs, however, was recently associated with poor outcome in status epilepticus (SE), raising the question of whether cIVAD therapy should be delayed for attempts to halt seizures with repeated non-anesthetic antiepileptic drugs. In this study, we aimed to determine the impact of differences in therapeutic approaches on RSE outcome using timing of cIVAD therapy as a surrogate for treatment aggressiveness. METHODS: This was a retrospective cohort study over 14 years (n = 77) comparing patients with RSE treated with cIVADs within and after 48 h after RSE onset, and functional status at last follow-up was the primary outcome (good = return to premorbid baseline or modified Rankin Scale score of less than 3). Secondary outcomes included discharge functional status, in-hospital mortality, RSE termination, induction of burst suppression, use of thiopental, duration of RSE after initiation of cIVADs, duration of mechanical ventilation, and occurrence of super-refractory SE. Analysis was performed on the total cohort and on subgroups defined by RSE severity according to the Status Epilepticus Severity Score (STESS) and by the variables contained therein. RESULTS: Fifty-three (68.8%) patients received cIVADs within the first 48 h. Early cIVAD treatment was independently associated with good outcome (adjusted risk ratio [aRR] 3.175, 95% confidence interval [CI] 1.273-7.918; P = 0.013) as well as lower chance of both induction of burst suppression (aRR 0.661, 95% CI 0.507-0.861; P = 0.002) and use of thiopental (aRR 0.446, 95% CI 0.205-0.874; P = 0.043). RSE duration after cIVAD initiation was shorter in the early cIVAD cohort (hazard ratio 1.796, 95% CI 1.047-3.081; P = 0.033). Timing of cIVAD use did not impact the remaining secondary outcomes. Subgroup analysis revealed early cIVAD impact on the primary outcome to be driven by patients with STESS of less than 3. CONCLUSIONS: Patients with RSE treated with cIVADs may benefit from early initiation of such therapy.
EVALuna2:201933

Impacts of microbiome metabolites on immune regulation and autoimmunity - Haase, Stefanie; Haghikia, Aiden; Wilck, Nicola; Mueller, Dominik N.; Linker, Ralf (Immunology, 2018)
A vast number of studies have demonstrated a remarkable role for the gut microbiota and their metabolites in the pathogenesis of inflammatory diseases, including multiple sclerosis (MS). Recent studies in experimental autoimmune encephalomyelitis, an animal model of MS, have revealed that modifying certain intestinal bacterial populations may influence immune cell priming in the periphery, resulting in dysregulation of immune responses and neuroinflammatory processes in the central nervous system (CNS). Conversely, some commensal bacteria and their antigenic products can protect against inflammation within the CNS. Specific components of the gut microbiome have been implicated in the production of pro-inflammatory cytokines and subsequent generation of Th17 cells. Similarly, commensal bacteria and their metabolites can also promote the generation of regulatory T-cells (Treg), contributing to immune suppression. Short-chain fatty acids may induce Treg either by G-protein-coupled receptors or inhibition of histone deacetylases. Tryptophan metabolites may suppress inflammatory responses by acting on the aryl hydrocarbon receptor in T-cells or astrocytes. Interestingly, secretion of these metabolites can be impaired by excess consumption of dietary components, such as long-chain fatty acids or salt, indicating that the diet represents an environmental factor affecting the complex crosstalk between the gut microbiota and the immune system. This review discusses new aspects of host-microbiota interaction and the immune system with a special focus on MS as a prototype T-cell-mediated autoimmune disease of the CNS.
EVALuna2:201904

Impaired renal function in stroke patients with atrial fibrillation - Sauer, Eva-Maria; Sauer, Rolf; Kallmuenzer, Bernd; Blinzler, Christian; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2014)
Stroke patients with atrial fibrillation (AF) are prone to have comorbidities such as impaired renal function. Because poly-pharmacotherapy is often required in those patients, renal function is important to consider in light of renally cleared medications such as direct oral anticoagulants. In this study, we analyzed frequency and predictors for impaired renal function and its impact on functional outcome in stroke patients with underlying AF.We analyzed 272 patients with acute ischemic stroke and AF of our prospective, observational stroke database. Estimated glomerular filtration rate (eGFR) was calculated on admission and during hospitalization from the equation of the Modification Diet for Renal Disease. Outcome measures included mortality and functional outcome at 90 days, assessed as modified Rankin Scale (mRS) score.On admission, impaired renal function was found in 41.5% (n = 113) and was associated with worse 90-day outcome (mRS score <= 2: 26.5% versus 45.9%, P = .001) and a higher mortality rate (23.9% versus 14.5%, P = .043). Multivariate logistic regression identified older age and history of myocardial infarction as independent predictors of renal dysfunction on admission (P < .05). Normalization of eGFR during hospitalization was achieved in 55.8%.In patients with acute ischemic stroke and AF, impaired renal function on admission is frequent and associated with worse outcome. Normalization of eGFR can often be achieved during hospitalization, but in everyday life, fluctuations of renal function because of infection or dehydration have to be considered. Careful monitoring of renal status is indispensable and should influence drug treatment decisions.
EVALuna2:22248

Impairment of autonomic cardiovascular modulation is more pronounced in focal epilepsy patients with than without limbic system lesions - Zhuravlev, D.; Lebedeva, M.; Lebedeva, A.; Teplyshova, A.; Rider, F.; Semenovykh, N.; Yakovlev, A.; Guekht, A.; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Implant for Augmentation of Cerebral Blood Flow Trial-1 (ImpACT-1). A single-arm feasibility study evaluating the safety and potential benefit of the Ischemic Stroke System for treatment of acute ischemic stroke - Khurana, Dheeraj; Kaul, Subhash; Schneider, Dietmar; Csanyi, Attila; Adam, Ilona; Ichaporia, Nasli R.; Griewing, Bernd; Csiba, Laszlo; Valikovics, Attila; Puri, Vinod; Diener, Hans Christoph; Schwab, Stefan; et al. (PLoS ONE, 2019)
BACKGROUND: The Ischemic Stroke System is a novel device designed to deliver stimulation to the sphenopalatine ganglion(SPG).The SPG sends parasympathetic innervations to the anterior cerebral circulation. In rat stroke models, SPG stimulation results in increased cerebral blood flow, reduced infarct volume, protects the blood brain barrier, and improved neurological outcome. We present here the results of a prospective, multinational, single-arm, feasibility study designed to assess the safety, tolerability, and potential benefit of SPG stimulation inpatients with acute ischemic stroke(AIS). METHODS: Patients with anterior AIS, baseline NIHSS 7-20 and ability to initiate treatment within 24h from stroke onset, were implanted and treated with the SPG stimulation. Patients were followed up for 90 days. Effect was assessed by comparing the patient outcome to a matched population from the NINDS rt-PA trial placebo patients. RESULTS: Ninety-eight patients were enrolled (mean age 57years, mean baseline NIHSS 12 and mean treatment time from stroke onset 19h). The observed mortality rate(12.2%), serious adverse events (SAE)incidence(23.5%) and nature of SAE were within the expected range for the population. The modified intention to treat cohort consisted of 84 patients who were compared to matched patients from the NINDS placebo arm. Patients treated with SPG stimulation had an average mRS lower by 0.76 than the historical controls(CMH test p = 0.001). CONCLUSION: The implantation procedure and the SPG stimulation, initiated within 24hr from stroke onset, are feasible, safe, and tolerable. The results call for a follow-up randomized trial (funded by BrainsGate; clinicaltrials.gov number, NCT03733236).
CRIS-Team Scopus Importer:2019-07-30

Improved resection in lesional temporal lobe epilepsy surgery using neuronavigation and intraoperative MR imaging: Favourable long term surgical and seizure outcome in 88 consecutive cases - Roessler, Karl; Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Buchfelder, Michael (Seizure-European Journal of Epilepsy, 2014)
To investigate the value of intraoperative MR imaging (iopMRI) combined with neuronavigation to avoid intraoperative underestimation of the resection amount during surgery of lesional temporal lobe epilepsy (LTLE) patients.We retrospectively investigated 88 patients (40 female, 48 male, mean age 37.2yrs, from 12 to 69yrs, 41 left sided lesions) with LTLE operated at our department, including 40.9% gangliogliomas (GG), 26.1% cavernomas (CM), 10.2% dysembryoplastic neuroepithelial tumours (DNT) and 11.4% focal cortical dysplasias (FCD), excluding hippocampal sclerosis.Complete resection was achieved in 85 of 88 patients (96.6%), as proven by postoperative MRI 6 months after surgery. In contrast, the routine first iopMR imaging before closure revealed radical resection in only 66 of these 88 patients (75%). After re-intervention, the second iopMR imaging demonstrated complete resection in 19 more patients. Thus, as a direct effect of iopMRI and neuronavigation, overall resection rate was increased by 21.6%. An excellent seizure outcome Engel Class I was found in 76.1% of patients during a mean follow-up of 26.4 months, irrespective of histological entity (74% in CM, 75% in GG, 78% in DNT and 60% in FCD). No severe postoperative complications occurred; permanent superior visual field defects were detected in 10.2% and permanent dysphasia/dyscalculia in 1.1%.Refined surgery using neuronavigation combined with iopMR imaging in LTLE surgery led to radical resection in 96.6% of the patients, due to immediate correction of underestimated resection in 21.6% of patients. This protocol resulted in a favourable seizure outcome and a low complication rate.
EVALuna2:7229

Improvement and stabilization of cardiovascular autonomic modulation three months after acute ischemic stroke - Wang, Ruihao; Macha, Kosmas; Köhn, Julia; Marsch, Armin; Winder, K.; Gerner, Stefan; Koehrmann, M.; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Incidence and relative risk of stroke in the diabetic and the non-diabetic population between 1998 and 2014: A community-based stroke register - Icks, Andrea; Claessen, Heiner; Kvitkina, Tatjana; Narres, Maria; Weingaertner, Michael; Schwab, Stefan; Kolominsky-Rabas, Peter (PLoS ONE, 2017)
One major objective of the St. Vincent Declaration was to reduce excess risk of stroke in people with diabetes mellitus. The aim of this study is to estimate the trend of incidence and relative risk of stroke in the diabetic and the non-diabetic populations in Germany over a 17-year period. We estimated age-sex standardised incidence rates of all stroke and ischaemic stroke in people with and without diabetes based on an ongoing prospective community-based stroke register covering 105,000 inhabitants. Time trends were analysed using Poisson regression. In total, 3,111 individuals (diabetes: 28.4%, men 46.9%, mean age 73.1 years (SD 13.2)) had a first stroke, 84.9% of which were ischaemic stroke. Among people with diabetes we observed a significant reduction in all stroke incidence by 1.5% per year (relative risk: 0.985; 95% confidence interval 0.972-0.9995) Likewise, this incidence tended to decrease for ischaemic stroke by 1% per year (0.993; 0.979-1.008). In contrast, the incidence rate for all stroke remained nearly stable among people without diabetes (1.003; 0.993-1.013) and for ischaemic stroke (1.002; 0.991-1.013). The relative risk comparing diabetic and non-diabetic population decreased for all stroke (two percent annual reduction) but not for ischaemic stroke. Time trends were similar for both sexes regarding all and ischaemic strokes. We found a reduction in risk of stroke in the diabetic population while this rate did not materially change in the non-diabetic population.
EVALuna2:33129

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

Increased intima-media thickness in rayon workers after long-term exposure to carbon disulfide - Schramm, Axel; Uter, Wolfgang; Brandt, Meike; Göen, Thomas; Köhrmann, Martin; Baumeister, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
Long-term exposure to carbon disulfide (CS2) is associated with increased cardiovascular mortality. However, previous studies on actual vascular changes showed heterogeneous results. Intima-media thickness of the carotid arteries (IMT) represents an established marker of atherosclerosis and a reasonable surrogate marker for cardiovascular risk. IMT was examined in a large cohort of CS2 exposed workers and the association with cumulative CS2 exposure analysed.In a cross-sectional examination, 290 exposed and 137 non-exposed workers in a German rayon-manufacturing plant were assessed. Individual cumulative exposure was calculated from this assessment combined with the results of two cross-sectional studies in 1992 and 1999 and department-specific annual means of ambient (CECS2) and individual biological (CETTCA) monitoring results obtained 1992-2009. Furthermore, cumulative duration of working in CS2-exposed departments (CEYEARS) was calculated. Examination included assessment of a broad set of known cardiovascular risk factors and IMT measurement of the carotid arteries on both sides. Multiple linear regression analyses were performed with IMT as outcome and three variants of cumulative exposure (duration of exposure, cumulative CS2, and cumulative TTCA) as well as categorised maximum CS2 exposure, all adjusted for cardiovascular risk factors.All models of cumulative exposure showed a significant increase in IMT in the group with the highest level of exposure: CEYEARS > 20 years, ? = 0.045 mm; CECS2 > 270 ppm × years, ? = 0.052 mm; CETTCA > 33 mg/g creatinine × years, ? = 0.038 mm. Alternatively, addressing maximum exposure, workers with CS2 exposure of >10 ppm in at least 3 years exhibited a significant IMT increase (? = 0.068 mm).Long-term CS2 exposure is an independent risk factor concerning IMT changes. The amount of IMT increase, in a similar range as that associated with other cardiovascular risk factors, might be clinically relevant.
EVALuna2:5493

Increased prevalence of posttraumatic stress disorder in patients after transient ischemic attack - Kiphuth, Ines C.; Utz, Kathrin S.; Noble, Adam J.; Köhrmann, Martin; Schenk, Thomas (Stroke, 2014)
A transient ischemic attack (TIA) involves temporary neurological symptoms but leaves a patient symptom-free. Patients are faced with an increased risk for future stroke, and the manifestation of the TIA itself might be experienced as traumatizing. We aimed to investigate the prevalence of posttraumatic stress disorder (PTSD) after TIA and its relation to patients' psychosocial outcome.Patients with TIA were prospectively studied, and 3 months after the diagnosis, PTSD, anxiety, depression, quality of life, coping strategies, and medical knowledge were assessed via self-rating instruments.Of 211 patients with TIA, data of 108 patients were complete and only those are reported. Thirty-two (29.6%) patients were classified as having PTSD. This rate is 10× as high as in the general German population. Patients with TIA with PTSD were more likely to show signs of anxiety and depression. PTSD was associated with the use of maladaptive coping strategies, subjectively rated high stroke risk, as well as with younger age. Finally, PTSD and anxiety were associated with decreased mental quality of life.The experience of TIA increases the risk for PTSD and associated anxiety, depression, and reduced mental quality of life. Because a maladaptive coping style and a subjectively overestimated stroke risk seem to play a crucial role in this adverse progression, the training of adaptive coping strategies and cautious briefing about the realistic stroke risk associated with TIA might be a promising approach. Despite the great loss of patients to follow-up, the results indicate that PTSD after TIA requires increased attention.
EVALuna2:22311

Increase of angiotensin II type 1 receptor auto-antibodies in Huntington's disease - Lee, De-Hyung; Heidecke, Harald; Schroeder, Alexandra; Paul, Friedemann; Wachter, Rolf; Hoffmann, Rainer; Ellrichmann, Gisa; Dragun, Duska; Waschbisch, Anne; Stegbauer, Johannes; Klotz, Peter; Gold, Ralf; et al. (Molecular Neurodegeneration, 2014)
In the recent years, a role of the immune system in Huntington's disease (HD) is increasingly recognized. Here we investigate the presence of T cell activating auto-antibodies against angiotensin II type 1 receptors (AT1R) in all stages of the disease as compared to healthy controls and patients suffering from multiple sclerosis (MS) as a prototype neurologic autoimmune disease.As compared to controls, MS patients show higher titers of anti-AT1R antibodies, especially in individuals with active disease. In HD, anti-AT1R antibodies are more frequent than in healthy controls or even MS and occur in 37.9% of patients with relevant titers >= 20 U/ml. In a correlation analysis with clinical parameters, the presence of AT1R antibodies in the sera of HD individuals inversely correlated with the age of onset and positively with the disease burden score as well as with smoking and infection.These data suggest a dysfunction of the adaptive immune system in HD which may be triggered by different stimuli including autoimmune responses, infection and possibly also smoking.
EVALuna2:22303

Influence of antithrombotic pre-treatment and time window on hemorrhagic complications of ivt in ischemic stroke - Macha, Kosmas; Hölter, Philip; Sembill, Jochen; Hock, Stefan; Siedler, Gabriela; Mühlen, Iris; Haupenthal, David; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Influence of Early Enteral Nutrition on Clinical Outcomes in Neurocritical Care Patients With Intracerebral Hemorrhage - Peng, Jianhua; Volbers, Bastian; Sprugel, Maximilian I.; Hölter, Philip; Engelhorn, Tobias; Jiang, Yong; Kuramatsu, Joji; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Gerner, Stefan (Frontiers in Neurology, 2021)
Objective: Early enteral nutrition (EEN) represents the current standard of care for patients treated in general intensive care units (ICU). Specific nutritional recommendations for patients receiving dedicated neurocritical care are not established. This study investigated associations of EEN with clinical outcomes for patients suffering from intracerebral hemorrhage treated at a neurological ICU (NICU).
CRIS-Team WoS Importer:2021-05-14

Influence of image reconstruction parameters on diagnostic performance of on-site CT-derived FFR: Comparison with invasively measured FFR - Ammon, Fabian; Röther, Jens; Hell, M.; Schuhbaeck, A.; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Influence of new versus traditional antiepileptic drugs on course and outcome of status epilepticus - Reindl, Caroline; Sprügel, Maximilian; Sembill, Jochen; Müller, Tamara; Hagen, Manuel; Gerner, Stefan; Kuramatsu, Joji; Hamer, Hajo; Huttner, Hagen; Madžar, Dominik (Seizure-European Journal of Epilepsy, 2020)
Purpose: New antiepileptic drugs (AEDs) are increasingly applied in second-line therapy of status epilepticus (SE). In our study, we analyzed the impact of the choice of second-line AEDs on the course and prognosis of SE. Methods: This retrospective single- center study used data of an 8 year cohort of SE in adults from 2007 to 2014. Based on the year of market introduction with a cutoff at 1990, we classified AEDs as traditional or new. Prescription pattern associated differences in prognosis were measured through univariate and multivariable analysis of 3 endpoints: occurrence of refractory SE (RSE), functional outcome in survivors to discharge (good: mRS at discharge <3 or identical to admission mRS; otherwise poor), and in-hospital mortality. Results: From 362 SE episodes during the study period, 222 episodes were included into the study, among those 150 episodes treated with new and 72 with traditional AEDs. Use of new AEDs increased during the study period. After adjustment for confounders, treatment with new AEDs was on the one hand associated with higher rate of RSE occurrence (OR 1.95, 95 % CI 1.05–3.62, p = 0.03), but, on the other hand, also with better functional outcome at discharge (OR 2.64, 95 % CI 1.16–6.00, p = 0.02), while it was not an independent predictor of in- hospital mortality (OR 0.88, 95 % CI 0.33–2.33, p = 0.80). Conclusion: Our observation that new AEDs may be associated with a higher rate of RSE development and relatively better functional outcome when adjusted for the premorbid mRS needs confirmation in prospective studies.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Anticonvulsant; Antiepileptic drug; Established status epilepticus; Functional outcome; Mortality; Refractoriness; Status epilepticus; Treatment

Influence of Prior Nicotine and Alcohol Use on Functional Outcome in Patients after Intracerebral Hemorrhage - Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Beuscher, Vanessa D.; Giede-Jeppe, Antje; Stocker, Margarete; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2018)
Background: The influence of prior nicotine or alcohol use (legal drug use [LDU]) on outcome measures after intracerebral hemorrhage (ICH) is insufficiently established. We investigated drug-specific associations with (1) neuroradiologic and clinical parameters and (2) functional long-term outcome after ICH. Methods: This observational cohort study analyzed consecutive spontaneous patients with ICH (n = 554) from our prospective institutional registry over a 5-year study period (January 2010 to December 2014). We compared no-LDU patients with LDU patients, and patients using only nicotine, only alcohol, or both. To account for baseline imbalances, we reanalyzed cohorts after propensity score matching. Results: Prevalence of prior LDU was 197 of 554 (35.6%), comprising 94 of 554 (17.0%) with only nicotine use, 33 of 554 (6.0%) with only alcohol use, and 70 of 554 (12.6%) with alcohol and nicotine use. LDU patients were younger (65 [56-73] versus 75 [67-82], P < .01), less often female (n = 61 of 197 [31.0%] versus n = 188 of 357 [52.7%], P < .01), had more often prior myocardial infarction (n = 29 of 197 [14.7%] versus n = 24 of 357 [6.7%], P < .01), and in-hospital complications (sepsis or systemic inflammatory response syndrome: n = 95 of 197 [48.2%] versus n = 98 of 357 [27.5%], P < .01; pneumonia: n = 89 of 197 [45.2%] versus n = 110 of 357 [30.8%], P < .01). Except for an increased risk of pneumonia (odds ratio 2.22, confidence interval [1.04-4.75], P = .04) in patients using both nicotine and alcohol, we detected no significant differences upon reanalysis after propensity score matching of neuroradiologic or clinical parameters, complications, or long-term outcome between patients with and without LDU (mortality: n = 48 of 150 [32.0%] versus n = 45 of 150 [30.0%], P = .71; favorable outcome [modified Rankin Scale 0-3]: n = 56 of 150 [37.3%] versus n = 53 of 150 [35.3%], P = .72). Conclusions: Prior nicotine use, alcohol use, and their combination were associated with significant differences in baseline characteristics. However, adjusting for unevenly balanced baseline parameters revealed no differences in functional long-term outcome after ICH.
EVALuna2:34918

Influence of the Extent of Intraventricular Hemorrhage on Functional Outcome and Mortality in Intracerebral Hemorrhage - Röder, Sebastian; Sprügel, Maximilian; Sembill, Jochen; Giede-Jeppe, Antje; Macha, Kosmas; Madžar, Dominik; Lücking, Hannes; Gerner, Stefan; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2019)
Background and Objective: Intraventricular hemorrhage (IVH) is a verified independent prognostic parameter in patients with intracerebral hemorrhage (ICH). However, the impact of the extent of IVH on clinical outcomes is unestablished. Methods: We analyzed 1,112 consecutive primary ICH patients of the UKER-ICH cohort (NCT03183167) and hypothesized that there is no difference in outcome between patients without IVH and patients with minor IVH not leading to obstructive hydrocephalus. Propensity score matching and multivariable analyses were performed to account for imbalances in baseline characteristics. Primary outcome was defined as functional outcome 3 months after ICH -assessed using the modified Rankin Scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable outcome (mRS = 4-6). Secondary outcomes included mortality at 3 months and a Graeb score-based threshold analysis for association of the extent of IVH with unfavorable clinical outcome. Results: Among the 461 out of 1,112 (41.5%) ICH patients with IVH, 191 out of 461 (41.4%) showed IVH without obstructive hydrocephalus and no requirement of external ventricular drain (EVD) placement. After adjusting for baseline imbalances we found no difference in functional outcome at 3 months between patients without IVH (No-IVH) and patients with IVH not requiring EVD (IVH-w/o-EVD): mRS 0-3: No-IVH 64/161 (39.8%) vs. IVH-w/o-EVD 53/170 (31.2%); p = 0.103. However, there was a trend toward a higher mortality in IVH-w/o-EVD patients (mRS 6: No IVH 40/161 [24.8%] vs. IVH-w/o-EVD 57/170 [33.5%]; p = 0.083). Multivariable analysis revealed that a Graeb score >2 was independently associated with unfavorable outcome (mRS 4-6: OR 3.16 [1.54-6.48]; p = 0.002), and higher mortality (mRS 6: OR 2.57 [1.40-4.74]; p = 0.002) in IVH patients. Conclusions: Small amounts of intraventricular blood (Graeb score ≤2) not leading to obstructive hydrocephalus are not associated with unfavorable outcome or death after ICH. Thus, IVH per se should not be considered a binary variable in outcome prediction for ICH patients.
CRIS-Team Scopus Importer:2019-07-02

Influence on Outcome and Treatment of Intracerebral Hematoma in Patients with Atraumatic Subarachnoid Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Reichl, Jonathan; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Engelhorn, Tobias; Schwab, Stefan; Huttner, Hagen (CEREBROVASCULAR DISEASES, 2019)
CRIS-Team WoS Importer:2020-02-21

Initiating anticoagulant therapy after ICH is associated with patient characteristics and treatment recommendations - Sembill, Jochen; Wieser, Claudia; Sprügel, Maximilian; Gerner, Stefan; Giede-Jeppe, Antje; Reindl, Caroline; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Neurology, 2018)
The proportion of patients with intracerebral hemorrhage (ICH) and concomitant indication for oral anticoagulant (OAC) therapy is increasing. Although recent studies documented a favorable risk-benefit profile of OAC initiation, deciding whether, when, and which OAC should be started remains controversial. We investigated (1) OAC recommendations, its implementation, and adherence and (2) factors associated with OAC initiation after ICH. This prospective observational study analyzed consecutive ICH patients (n = 246) treated at the neurological and neurosurgical department of the University-Hospital Erlangen, Germany over a 21-month inclusion period (05/2013-01/2015). We analyzed the influence of patient characteristics, in-hospital measures, and functional status on treatment recommendations and on OAC initiation during 12-month follow-up. In-hospital mortality of 24.8% (n = 61/246) left 185 patients discharged alive of which 34.1% (n = 63/185) had OAC indication. In these patients, OAC initiation was clearly recommended in only 49.2% (n = 31/63) and associated with favorable [modified Rankin Scale (mRS) = 0-3] functional discharge status [OR 7.18, CI (1.05-49.13), p = 0.04], less frequent heart failure [OR 0.19, CI (0.05-0.71), p = 0.01], and younger age [OR 0.95, CI (0.90-1.00), p = 0.05]. OAC was more often started if clearly recommended [n = 19/31 (61.3%) versus (no recommendation) n = 4/26 (15.4%), p < 0.001; (clearly not recommended, n = 6)] and associated with younger age [67 (58-74) versus 79 (73-83), p < 0.001], favorable functional outcome [n = 10/23 (43.5%) versus n = 5/40 (12.5%), p = 0.01], decreased mortality [n = 6/23 (26.1%) versus n = 19/40 (47.5%), p = 0.06], and functional improvement [n = 13/17 (76.5%) versus n = 7/21 (33.3%), p = 0.01]. We observed no differences in rates of intracranial complications [thromboembolism, n = 3/23 (13.0%) versus n = 4/40 (10.0%), p = 1.00; hemorrhage, n = 1/23 (4.3%) versus n = 3/40 (7.5%), p = 1.00]. Clear treatment recommendations by attending stroke physicians significantly influence OAC initiation after ICH. OAC were more frequently recommended and started in younger patients with better functional recovery independent from intracranial complications. This might represent an important determinant of observed beneficial associations, hinting towards an indication bias which might affect observational analyses.
EVALuna2:34916

In response to commentary on cavernoma-related epilepsy: review and recommendations for management-report of the surgical task force of the ILAE commission on therapeutic strategies - Rosenow, Felix; Alonso-Vanegas, Mario A.; Baumgartner, Christoph; Blümcke, Ingmar; Carreno, Mar; Gizewski, Elke R.; Hamer, Hajo; Knake, Susanne; Kahane, Philippe; Lueders, Hans O.; Mathern, Gary W.; Menzler, Katja; et al. (Epilepsia, 2014)
EVALuna2:7236

Insular multiple sclerosis lesions are associated with erectile dysfunction - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Journal of Neurology, 2018)
Erectile function (EF) is frequently compromised in men with multiple sclerosis (MS). Functional neuroimaging in healthy men identified a network of brain areas, such as the insula, visual and somatosensory association areas, cingulate gyrus, prefrontal cortex, as well as subcortical regions, contributing to EF. This study intended to determine associations between EF deterioration during MS and cerebral MS-associated lesion sites. In 31 men with MS (mean age 38.2 ± 11.2 years), we evaluated MS-related EF deterioration by comparing scores of the 5-item International Index of Erectile Function-5 questionnaire (IIEF5) at the time of study and retrospectively, 3 months prior to MS diagnosis, by calculating score differences as DeltaIIEF5 (DeltaIIEF5 score < 0 indicated EF deterioration). To assess the impact of confounding factors of EF, patient age, disease duration, disease severity, depressiveness, bladder and bowel symptoms, and total cerebral MS lesion volume were correlated with DeltaIIEF5 scores (Spearman rank correlation) and compared between patients with and without EF deterioration (t tests or Mann-Whitney U test). MS lesions were assessed on T2-weighted magnetic resonance imaging (MRI; 1.5 or 3 T). We determined the lesion overlap (prevalence of identical lesion sites among patients), subtracted lesion overlaps in patients without EF deterioration from overlaps in patients with EF deterioration, and compared DeltaIIEF5 scores voxel-wise between patients with and without lesions in a given voxel (t test; significance: p < 0.05). In 14 patients (45.2%), DeltaIIEF5 scores indicated EF deterioration. DeltaIIEF5 scores were not associated with age (ρ = 0.06; p = 0.74), disease duration (ρ = 0.26; p = 0.15), disease severity (ρ = - 0.19; p = 0.31), depressiveness (ρ = 0.07; p = 0.72), bladder symptoms (ρ = - 0.11; p = 0.57), bowel symptoms (ρ = 0.17; p = 0.37), and total lesion volume (ρ = - 0.13; p = 0.47). The voxel-wise analysis showed associations between EF deterioration and MS lesions primarily in the bilateral, and predominantly left juxtacortical insular region. In conclusion, MS lesions particularly in the left insular region, which is activated with sexual arousal, contribute to erectile dysfunction.
EVALuna2:34021

Integration of functional neuronavigation and intraoperative MRI in surgery for drug-resistant extratemporal epilepsy close to eloquent brain areas - Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard S.; Blümcke, Ingmar; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2013)
Object. The authors performed a retrospective study to assess the impact of functional neuronavigation and intraoperative MRI (iMRI) on surgery of extratemporal epileptogenic lesions on postsurgical morbidity and seizure control. Methods. Twenty-five patients (14 females and 11 males) underwent extratemporal resections for drug-resistant epilepsy close to speech/motor brain areas or adjacent to white matter tracts. The mean age at surgery was 34 years (range 12-67 years). The preoperative mean disease duration was 13.2 years. To avoid awake craniotomy, cortical motor-sensory representation was mapped during preoperative evaluation in 14 patients and speech representation was mapped in 15 patients using functional MRI. In addition, visualization of the pyramidal tract was performed in 11 patients, of the arcuate fascicle in 7 patients, and of the visual tract in 6 patients using diffusion tensor imaging. The mean minimum distance of tailored resection between the eloquent brain areas was 5.6mm. During surgery, blood oxygen level-dependent imaging and diffusion tensor imaging data were integrated into neuronavigation and displayed through the operating microscope. The postoperative mean follow-up was 44.2 months. Results. In 20% of these patients, further intraoperative resection was performed because of intraoperatively documented residual lesions according to iMRI findings. At the end of resection, the final iMRI scans confirmed achievement of total resection of the putative epileptogenic lesion in all patients. Postoperatively, transient complications and permanent complications were observed in 20% and 12% of patients, respectively. Favorable postoperative seizure control (Engel Classes I and II) was achieved in 84% and seizure freedom in 72% of these consecutive surgical patients. Conclusions. By using functional neuronavigation and iMRI for treatment of epileptogenic brain lesions, the authors achieved a maximum extent of resection despite the lesions' proximity to eloquent brain cortex and fiber tracts in all cases. The authors' results underline possible benefits of this technique leading to a favorable seizure outcome with acceptable neurological deficit rates in difficult-to-treat extratemporal epilepsy. © AANS, 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Eloquent brain area; Extratemporal epilepsy; Functional neuronavigation; Intraoperative MRI; Seizure outcome; Surgery

INTEGRATION OF MULTIMODAL IMAGING AND INTRAOPERATIVE MR IN RESECTIVE SURGERY FOR MEDICALLY REFRACTORY EPILEPSY: THE ERLANGEN EXPERIENCE OF 415 PATIENTS - Sommer, B.; Roessler, K.; Hofmann, Andrea; Coras, R.; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (2016)
EVALuna2:33851

Interferon Beta and vitamin d synergize to induce immunoregulatory receptors on peripheral blood monocytes of multiple sclerosis patients - Waschbisch, Anne; Sanderson, Nicholas; Krumbholz, Markus; Vlad, George; Theil, Diethilde; Schwab, Stefan; Mäurer, Mathias Eckhard; Derfuss, Tobias (PLoS ONE, 2014)
Immunoglobulin-like transcript (ILT) 3 and 4 are inhibitory receptors that modulate immune responses. Their expression has been reported to be affected by interferon, offering a possible mechanism by which this cytokine exerts its therapeutic effect in multiple sclerosis, a condition thought to involve excessive immune activity. To investigate this possibility, we measured expression of ILT3 and ILT4 on immune cells from multiple sclerosis patients, and in post-mortem brain tissue. We also studied the ability of interferon beta, alone or in combination with vitamin D, to induce upregulation of these receptors in vitro, and compared expression levels between interferon-treated and untreated multiple sclerosis patients. In vitro interferon beta treatment led to a robust upregulation of ILT3 and ILT4 on monocytes, and dihydroxyvitamin D3 increased expression of ILT3 but not ILT4. ILT3 was abundant in demyelinating lesions in postmortem brain, and expression on monocytes in the cerebrospinal fluid was higher than in peripheral blood, suggesting that the central nervous system milieu induces ILT3, or that ILT3 positive monocytes preferentially enter the brain. Our data are consistent with involvement of ILT3 and ILT4 in the modulation of immune responsiveness in multiple sclerosis by both interferon and vitamin D.
EVALuna2:22287

Interictal Electrical Source Imaging. - Rampp, Stefan; Müller-Voggel, Nadia; Hamer, Hajo; Dörfler, Arnd; Brandner, Sebastian; Buchfelder, Michael (Journal of Clinical Neurophysiology, 2024)
Interictal electrical source imaging (ESI) determines the neuronal generators of epileptic activity in EEG occurring outside of seizures. It uses computational models to take anatomic and neuronal characteristics of the individual patient into account. The presented article provides an overview of application and clinical value of interictal ESI in patients with pharmacoresistant focal epilepsies undergoing evaluation for surgery. Neurophysiological constraints of interictal data are discussed and technical considerations are summarized. Typical indications are covered as well as issues of integration into clinical routine. Finally, an outlook on novel markers of epilepsy for interictal source analysis is presented. Interictal ESI provides diagnostic performance on par with other established methods, such as MRI, PET, or SPECT. Although its accuracy benefits from high-density recordings, it provides valuable information already when applied to EEG with only a limited number of electrodes with complete coverage. Novel oscillatory markers and the integration of frequency coupling and connectivity may further improve accuracy and efficiency.
EVALuna2:547206

Interictal epileptiform discharges affect memory in an Alzheimer's disease mouse model - Soula, Marisol; Maslarova, Anna; Harvey, Ryan E.; Valero, Manuel; Brandner, Sebastian; Hamer, Hajo; Fernández-Ruiz, Antonio; Buzsáki, György (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Interictal epileptiform discharges (IEDs) are transient abnormal electrophysiological events commonly observed in epilepsy patients but are also present in other neurological diseases, such as Alzheimer's disease (AD). Understanding the role IEDs have on the hippocampal circuit is important for our understanding of the cognitive deficits seen in epilepsy and AD. We characterize and compare the IEDs of human epilepsy patients from microwire hippocampal recording with those of AD transgenic mice with implanted multilayer hippocampal silicon probes. Both the local field potential features and firing patterns of pyramidal cells and interneurons were similar in the mouse and human. We found that as IEDs emerged from the CA3-1 circuits, they recruited pyramidal cells and silenced interneurons, followed by post-IED suppression. IEDs suppressed the incidence and altered the properties of physiological sharp-wave ripples, altered their physiological properties, and interfered with the replay of place field sequences in a maze. In addition, IEDs in AD mice inversely correlated with daily memory performance. Together, our work implies that IEDs may present a common and epilepsy-independent phenomenon in neurodegenerative diseases that perturbs hippocampal-cortical communication and interferes with memory.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Alzheimer model; interictal epileptiform discharges; memory; replay; sharp wave ripples

Interictal magnetoencephalography used in magnetic resonance imaging-negative patients with epilepsy - Wu, Xueqing; Rampp, Stefan; Buchfelder, Michael; Kuwert, Torsten; Blümcke, Ingmar; Zhou, D.; Stefan, Herrmann; Dörfler, Arnd (Acta Neurologica Scandinavica, 2013)
Purpose: This study aims to investigate the contributions of magnetoencephalography (MEG) in magnetic resonance imaging (MRI)-negative patients. Methods: A total of 18 MRI-negative patients diagnosed with refractory epilepsy, subjected to MEG investigation, and subsequently underwent surgery were selected for retrospective analysis. A 1.5-tesla Magnetom Sonata with an eight-channel head array coil was used. MEG data were obtained using a 74/248-channel system. Results: A total of 16 patients (16/18) had positive MEG results, comprising 12 patients with monofocal localizations, five with multifocal localizations, and one with unremarkable results in MEG. In addition, 12 patients had indicative single photon-emission computed tomography (SPECT), five had indicative fluorodeoxyglucose positron emission tomography (FDG-PET), and all the patients had intracranial electroencephalography (EEG) (14 with subdural electrodes and four with electrocorticography). The intracranial EEG recordings of nine patients were guided by MEG informative results. Among these 18 patients, 10 exhibited good postoperative outcomes (Engel I and II), four of which were completely seizure-free. All these ten patients had clear monofocal localization in MEG, including nine with accordant indicative metabolic changes in either SPECT or FDG-PET, or both. None of the five patients with multifocal localizations achieved good postoperative outcomes. Conclusion: For cases with negative MRI findings, epilepsy surgery may be an alternative option for pharmaco-resistant patients if epileptogenic focus localizations by MEG are present in multimodal evaluation. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Magnetic resonance imaging; Magnetoencephalography; Non-lesional epilepsy; Outcome

Interrelation of depression, sexual dysfunction and disease severity in patients with multiple sclerosis - Hoesl, K.; Roy, Sankanika; Wang, Ruihao; Intravooth, Tassanai; Deutsch, Martina; Winder, K.; Lee, De-Hyung; Linker, Ralf; Hilz, M. J. (2017)
EVALuna2:22574

Intranasal delivery of a small-molecule ErbB inhibitor promotes recovery from acute and late-stage CNS inflammation - Linnerbauer, Mathias; Lößlein, Lena; Vandrey, Oliver; Tsaktanis, Thanos; Beer, Alexander; Naumann, Ulrike; Panier, Franziska; Beyer, Tobias; Nirschl, Lucy; Kuramatsu, Joji; Winkler, Jürgen; Quintana, Francisco J.; et al. (JCI Insight, 2022)
Multiple sclerosis (MS) is an autoimmune inflammatory disease of the CNS that is characterized by demyelination and axonal degeneration. Although several established treatments reduce relapse burden, effective treatments to halt chronic progression are scarce. Single-cell transcriptomic studies in MS and its animal models have described astrocytes and their spatial and functional heterogeneity as important cellular determinants of chronic disease. We combined CNS single-cell transcriptome data and small-molecule screens in primary mouse and human astrocytes to identify glial interactions, which could be targeted by repurposing FDA-approved small-molecule modulators for the treatment of acute and late-stage CNS inflammation. Using hierarchical in vitro and in vivo validation studies, we demonstrate that among selected pathways, blockade of ErbB by the tyrosine kinase inhibitor afatinib efficiently mitigates proinflammatory astrocyte polarization and promotes tissue-regenerative functions. We found that i.n. delivery of afatinib during acute and late-stage CNS inflammation ameliorates disease severity by reducing monocyte infiltration and axonal degeneration while increasing oligodendrocyte proliferation. We used unbiased screening approaches of astrocyte interactions to identify ErbB signaling and its modulation by afatinib as a potential therapeutic strategy for acute and chronic stages of autoimmune CNS inflammation.
CRIS-Team Scopus Importer:2022-04-22

Intraoperative Magnetic-Resonance Tomography and Neuronavigation During Resection of Focal Cortical Dysplasia Type II in Adult Epilepsy Surgery Offers Better Seizure Outcomes - Roessler, Karl; Kasper, Burkhard; Heynold, Elisabeth; Coras, Roland; Sommer, Bjoern; Rampp, Stefan; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (World Neurosurgery, 2018)
Focal cortical dysplasia (FCD) is one important cause of drug-resistant epilepsy potentially curable by epilepsy surgery. We investigated the options of using neuronavigation and intraoperative magnetic-resonance tomographical imaging (MRI) to avoid residual epileptogenic tissue during resection of patients with FCD II to improve seizure outcome.Altogether, 24 patients with FCD II diagnosed by MRI (16 female, 8 male; mean age 34 ± 10 years) suffered from drug-resistant electroclinical and focal epilepsy for a mean of 20.7 ± 5 years. Surgery was performed with preoperative stereoelectroencephalography (in 15 patients), neuronavigation, and intraoperative 1.5T-iopMRI in all 24 investigated patients.In 75% of patients (18/24), a complete resection was performed. In 89% (16/18) of completely resected patients, we documented an Engel I seizure outcome after a mean follow-up of 42 months. All incompletely resected patients had a worse outcome (Engel II-III, P < 0.0002). Patients with FCD IIB had also significant better seizure outcome compared with patients diagnosed as having FCD IIA (82% vs. 28%, P < 0.02). In 46% (11/24) of patients, intraoperative second-look surgeries due to residual lesions detected during the intraoperative MRI were performed. In these 11 patients, there were significant more completely seizure free patients (73% vs. 38% Engel IA), compared with 13 patients who finished surgery after the first intraoperative MRI (P < 0.05).Excellent seizure outcome after surgery of patients with FCD II positively correlated with the amount of resection, histologic subtype, and the use of intraoperative MRI, especially when intraoperative second-look surgeries were performed.
EVALuna2:7382

Intraoperative use of high-field MRI in hypothalamic hamartomas associated with epilepsy: clinico-pathological presentation of five adult patients - Sommer, Bjoern; Schlaffer, Sven-Martin; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael (Acta Neurochirurgica, 2014)
Hypothalamic harmartomas (HHs) are either occasionally associated with medically intractable epileptic syndromes or precocious puberty. Due to the extraordinary location and the expansive intra-axial growth, surgical resection is difficult and challenging without causing severe neurological, hypothalamic or endocrinological deficits, which account for higher mortality and morbidity.We present a series of five adult patients with drug-resistant epilepsy who had been operated on for HH using neuronavigation and intraoperative 1.5-T magnetic resonance imaging (MRI). In this retrospective investigation, we compared our surgical strategy and postoperative results to existing series.During surgery, we identified remnant HH in the first intraoperative MRI control scan in three out of five patients. After re-segmentation of the residual lesion using neuronavigation, complete resection was achieved in two of the three patients as confirmed by final intraoperative and late follow-up MRI, raising the rate of total resections to four out of five patients. Two patients died during the observation period. One patient suffered from a permanent third nerve palsy and one from a transient monoparesis of the left arm. New endocrinological disturbances included diabetes insipidus centralis in two and secondary hypothyroidism and hypogonadism in one patient. Four out of five patients had favourable seizure control (Engel I or II) after 64.8 (34-83) months of mean follow-up.Neuronavigation and intraoperative MRI are valuable tools to encounter difficulties while performing surgery in patients with HHs. Intraoperative resection control increases the amount of maximum resection.
EVALuna2:7252

Intraventricular fibrinolysis does not increase perihemorrhagic edema after intracerebral hemorrhage - Volbers, Bastian; Wagner, Irina; Willfarth, Wolfgang; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (Stroke, 2013)
BACKGROUND AND PURPOSE - : Additional intraventricular hemorrhage leads to higher mortality and worse functional outcome after intracerebral hemorrhage (ICH). Intraventricular fibrinolysis (IVF) with recombinant tissue plasminogen activator (rtPA) is an emerging treatment strategy for such patients. However, experimental studies suggest that rtPA may exert proedematous effects and lead to increased perihemorrhagic edema (PHE) after ICH. We aimed to compare the course of PHE after ICH between patients who received IVF with rtPA and controls matched for ICH volume. METHODS - : Patients were identified retrospectively from our institutional ICH database. Sixty-four patients with ICH and intraventricular hemorrhage who were treated with IVF were compared with 64 controls, who did not receive IVF, matched for ICH volume. The course of PHE was assessed on computed tomography scans (day 1, days 2 and 3, days 4-6, 7-9, and 10-12) using a threshold-based semiautomatic volumetric algorithm. Relative PHE was calculated as a ratio of PHE volume and initial ICH volume. RESULTS - : The matching algorithm resulted in similar mean ICH volumes in both groups (20.01±17.5 mL, IVF vs 20.08±17.1 mL, control). Intraventricular hemorrhage volume was larger in the IVF group (26.8±19.2 mL vs 9.2±13.4 mL). The mean total rtPA dose used for IVF was 8±6 mg. PHE increased over time in both groups until day 12. At all investigated time points, there was no significant difference in relative PHE between the IVF group and controls (F=0.39; P=0.844). CONCLUSIONS - : IVF with rtPA did not lead to a relevant increase in PHE after ICH. rtPA doses used in the current study seem to be safe regarding PHE. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: intracerebral hemorrhage; intraventricular fibrinolysis; intraventricular hemorrhage; perihemorrhagicedema; recombinant tissue-type plasminogen activator; semiautomatic volumetry; X-ray computed tomography

Intraventricular fibrinolysis has no effects on shunt dependency and functional outcome in endovascular-treated aneurysmal SAH - Gerner, Stefan; Kuramatsu, Joji; Abel, Henning; Kloska, Stephan; Lücking, Hannes; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Neurocritical Care, 2014)
Intraventricular fibrinolysis (IVF) in subarachnoid hemorrhage (SAH) is an emerging strategy aiming to hasten clot lysis, treat hydrocephalus, and reduce permanent shunt rates. Because of clinical heterogeneity of investigated patient effects of IVF on permanent shunt incidence and functional outcome are widely debated. The present study is the first to investigate solely endovascular-treated SAH patients.Overall, 88 consecutive patients with aneurysmal SAH requiring external ventricular drain placement and endovascular aneurysm closure were included. Functional outcome and shunt dependency were assessed 90 days after event. A matched controlled sub-analysis was carried out to investigate the effects of IVF treatment (n = 14; matching criteria: age, neuro-status and imaging). Multivariate modeling was performed to identify independent predictors for permanent shunt dependency.In IVF-patients neurological status was significantly poorer [Hunt&Hess: IVF = 4(3-5) vs. non-IVF = 3(1-5); p = 0.035] and the extent of ventricular hemorrhage was increased [Graeb Score: IVF = 7(6-8) vs. non-IVF = 3(1-4); p <= 0.001]. Consecutive matched controlled sub-analysis revealed no significant therapeutic effect of IVF with respect to shunt dependency rate and functional outcome. Multivariate analysis revealed Graeb score [OR = 1.34(1.02-1.76); p = 0.035] and sepsis [OR = 11.23(2.28-55.27); p = 0.003] as independent predictors for shunt dependency, whereas IVF did not exert significant effects (p = 0.820).In endovascular-treated SAH patients IVF neither reduced permanent shunt dependency nor influenced functional outcome. Despite established effects on intraventricular clot resolution IVF appears less powerful in SAH as compared to ICH. Given the reported positive effects of lumbar drainage (LD) in SAH, a prospective analysis of a combined treatment approach of IVF and subsequent lumbar drain sOeems warranted aiming to reduce permanent shunting and improve functional outcome.
EVALuna2:22283

Invasiveness and Clinical Outcomes of Off-Hour Admissions in Patients with Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Kuramatsu, Joji; Lücking, Hannes; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2019)
BACKGROUND: Whether time of hospital admission-during or outside regular working hours-affects functional outcome in intracerebral hemorrhage (ICH) is unestablished as previous analyses have focused on mortality only. We here investigate whether on- versus off-hour hospital admission in ICH is associated with levels of invasiveness and clinical outcomes. METHODS: Based on the UKER registry (NCT03183167) we grouped ICH-patients according to on- versus off-hour hospital admission. Primary outcome measures was functional outcome after 3 months using the modified Rankin scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6). Multivariate regression analyses were used to adjust for baseline imbalances, and subgroup analyses were performed to explore associations of on- versus off-hour admission with invasiveness of therapeutic interventions. RESULTS: A total of 438/1269 (34.5%) of ICH-patients were admitted during regular working hours. Mortality rates were not significantly different among patients with on- versus off-hour admission. On-hour patients showed a significantly larger proportion of patients with favorable outcome (on-hour: mRS = 0-3 after 3 months: 176/416 (42.3%) versus off-hour: 265/784 (33.8%); P = .004). Analysis of invasive therapeutic interventions revealed that likelihood of favorable outcome was significantly increased among on-hour admitted patients who did not require neurosurgical interventions (no external ventricular drain n = 349, OR: 1.67[1.13-2.48], P < .05; no hematoma evacuation surgery n = 423, OR: 1.51[1.07-2.14], P < .05). CONCLUSION: This study verified an "off-hour effect" in ICH that relates to functional outcome, rather than mortality, and which may be linked to different levels of invasive therapeutic interventions in patients admitted during off-hour.
EVALuna2:206735

Invasive stimulation procedures and EEG diagnostics in epilepsy - Schulze-Bonhage, A.; Hamer, Hajo; Hirsch, M.; Hagge, Mareike (Der Nervenarzt, 2016)
Stimulation has been performed experimentally and in small case series to treat epilepsy since the 1970s. Since the introduction of vagus nerve stimulation in 1997 and intracranial stimulation methods in 2011 into patient care, invasive stimulation has become a rapidly developing but infrequently used therapeutic option in Europe. Whereas vagus nerve stimulation is frequently used, particularly in the USA, intracranial stimulation differs in its regional availability. In order to improve the efficacy of stimulation, develop criteria for its use and assure low complication rates, a concentration on experienced centers and multicenter data acquisition and sharing are needed.Invasive electroencephalographic (EEG) monitoring with subdural electrodes and especially with stereotactically implanted depth electrodes have been used increasingly more often for presurgical evaluation in recent years. They are applied when non-invasive diagnostics show insufficient results to exactly identify the location and extent of the epileptogenic zone or cannot be adequately distinguished from eloquent cortex areas. Complications include intracranial hemorrhage, infections and increased intracranial pressure but lasting deficits or even death are rare (<=2 %). The outcome of invasive monitoring is inferior to non-invasive monitoring because of the higher degree of complexity of the cases; however, it is far superior to the seizure-free rates achieved by anticonvulsant drug treatment alone.
EVALuna2:22470

Investigation of subdural electrode displacement in invasive epilepsy surgery workup using neuronavigation and intraoperative MRI - Sommer, Bjoern; Rampp, Stefan; Dörfler, Arnd; Stefan, Hermann; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2018)
OBJECTIVES: One of the main obstacles of electrode implantation in epilepsy surgery is the electrode shift between implantation and the day of explantation. We evaluated this possible electrode displacement using intraoperative MRI (iopMRI) data and CT/MRI reconstruction. METHODS: Thirteen patients (nine female, four male, median age 26 ± 9.4 years) suffering from drug-resistant epilepsy were examined. After implantation, the position of subdural electrodes was evaluated by 3.0 T-MRI and thin-slice CCT for 3D reconstruction. Localization of electrodes was performed with the volume-rendering technique. Post-implantation and pre-explantation 1.5 T-iopMRI scans were coregistered with the 3D reconstructions to determine the extent of electrode dislocation. RESULTS: Intraoperative MRI at the time of explantation revealed a relevant electrode shift in one patient (8%) of 10 mm. Median electrode displacement was 1.7 ± 2.6 mm with a coregistration error of 1.9 ± 0.7 mm. The median accuracy of the neuronavigation system was 2.2 ± 0.9 mm. Six of twelve patients undergoing resective surgery were seizure free (Engel class 1A, median follow-up 37.5 ± 11.8 months). CONCLUSION: Comparison of pre-explantation and post-implantation iopMRI scans with CT/MRI data using the volume-rendering technique resulted in an accurate placement of electrodes. In one patient with a considerable electrode dislocation, the surgical approach and extent was changed due to the detected electrode shift. ABBREVIATIONS: ECoG: electrocorticography; EZ: epileptogenic zone; iEEG: invasive EEG; iopMRI: intraoperative MRI; MEG: magnetoencephalography; PET: positron emission tomography; SPECT: single photon emission computed tomography; 3D: three-dimensional.
EVALuna2:201939

Involvement of obliquus capitis inferior muscle in dystonic head tremor - Schramm, Axel; Huber, D.; Möbius, Cornelia; Muenchau, A.; Kohl, Zacharias; Baeumer, T. (Parkinsonism & Related Disorders, 2017)
Head tremor is a common feature in cervical dystonia (CD) and often less responsive to botulinum neurotoxin (BoNT) treatment than dystonic posturing. Ultrasound allows accurate targeting of deeper neck muscles.In 35 CD patients with dystonic head tremor the depth and thickness of the splenius capitis (SPL), semispinalis capitis and obliquus capitis inferior muscles (OCI) were assessed using ultrasound. Ultrasound guided EMG recordings were performed from the SPL and OCI.Burst-like tremor activity was present in both OCI in 25 and in one in 10 patients. In 18 patients, tremor activity was present in one SPL and in 2 in both SPL. Depth and thickness of OCI, SPL and semispinalis capitis muscles were very variable.Muscular activity underlying tremulous CD is most commonly present in OCI. Due to the variability of muscle thickness, we suggest ultrasound guided BoNT injections into OCI.
EVALuna2:22566

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation - Stoll, Svenja; Macha, Kosmas; Marsch, Armin; Gerner, Stefan; Siedler, Gabriela; Fröhlich, Kilian; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Neurology, 2020)
Background: Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods: Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as “appropriate”, “underdosed” and “overdosed” in conformity with the European Medicines Agency labelling. The effect of underdosing on the functional factor Xa plasma level on admission, the clinical stroke severity and the functional outcome after 3 months were investigated. Results: 254 patients with cerebral ischemia while on Factor Xa inhibitors were included. The dose regimen of the Factor Xa inhibitor was appropriate in 166 patients (65%), underdosed in 67 patients (26%) and overdosed in 21 patients (8%). Underdosing was associated with female sex, diabetes mellitus and higher CHA2DS2–Vasc scores. Underdosing independently predicted lower anti-Xa plasma levels on admission [median 69.4 ng/ml (IQR 0.0–121.6) vs. 129.2 ng/ml (65.5–207.2); p < 0.001], was associated with higher NIHSS scores on admission [median 5 (IQR 1–10) vs. 3 (1–7); p = 0.041] and worse functional outcome after 3 months (favorable outcome 26.9% vs. 46.9%; p = 0.025). Conclusion: One in three patients with ischemic stroke during treatment with oral Xa inhibitors used inappropriate dose regimens. Underdosing was associated with lower functional plasma levels, higher clinical stroke severity and worse functional outcome.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atrial fibrillation; Direct oral anticoagulants; Dose reduction; Plasma levels; Stroke

Ischemic stroke associated with the use of a synthetic cannabinoid (spice) - Möller, Sebastian; Luecke, Caroline; Struffert, Tobias; Schwarze, Bernhard; Gerner, Stefan; Schwab, Stefan; Köhrmann, Martin; Machold, Kristin; Philipsen, Alexandra; Mueller, Helge H. (Asian Journal of Psychiatry, 2017)
Synthetic cannabinoids, i.e. "spice", are psychoactive drugs with increasing use worldwide. Spice may have harmful neuropsychiatric and physical side effects. Here, we present the case of a 25-year-old man with ischemic stroke after smoking spice on the previous evening. Diagnostic work-up was negative for other common causes of stroke. Toxicology screen unveiled the cannabimimetic ADB-FUBINACA in the drug sample and in patient's urine. The cardiac sympathomimetic effect of spice might have triggered an unnoticed episode of tachyarrhythmia and resulted in stroke via cardioembolic etiology. Thus, in absence of other risk factors, a careful patient history of spice use is recommended for patients with acute neurological deficits.
EVALuna2:22545

Ischemic Stroke despite Oral Anticoagulant Therapy in Patients with Atrial Fibrillation - Seiffge, David J.; De Marchis, Gian Marco; Koga, Masatoshi; Paciaroni, Maurizio; Wilson, Duncan; Cappellari, Manuel; Macha, Kosmas; Tsivgoulis, Georgios; Ambler, Gareth; Arihiro, Shoji; Bonati, Leo H.; Bonetti, Bruno; et al. (Annals of neurology, 2020)
Objective: It is not known whether patients with atrial fibrillation (AF) with ischemic stroke despite oral anticoagulant therapy are at increased risk for further recurrent strokes or how ongoing secondary prevention should be managed. Methods: We conducted an individual patient data pooled analysis of 7 prospective cohort studies that recruited patients with AF and recent cerebral ischemia. We compared patients taking oral anticoagulants (vitamin K antagonists [VKA] or direct oral anticoagulants [DOAC]) prior to index event (OACprior) with those without prior oral anticoagulation (OACnaive). We further compared those who changed the type (ie, from VKA or DOAC, vice versa, or DOAC to DOAC) of anticoagulation (OACchanged) with those who continued the same anticoagulation as secondary prevention (OACunchanged). Time to recurrent acute ischemic stroke (AIS) was analyzed using multivariate competing risk Fine–Gray models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We included 5,413 patients (median age = 78 years [interquartile range (IQR) = 71–84 years]; 5,136 [96.7%] had ischemic stroke as the index event, median National Institutes of Health Stroke Scale on admission = 6 [IQR = 2–12]). The median CHA2DS2-Vasc score (congestive heart failure, hypertension, age≥ 75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65–74 years, sex category) was 5 (IQR = 4–6) and was similar for OACprior (n = 1,195) and OACnaive (n = 4,119, p = 0.103). During 6,128 patient-years of follow-up, 289 patients had AIS (4.7% per year, 95% CI = 4.2–5.3%). OACprior was associated with an increased risk of AIS (HR = 1.6, 95% CI = 1.2–2.3, p = 0.005). OACchanged (n = 307) was not associated with decreased risk of AIS (HR = 1.2, 95% CI = 0.7–2.1, p = 0.415) compared with OACunchanged (n = 585). Interpretation: Patients with AF who have an ischemic stroke despite previous oral anticoagulation are at a higher risk for recurrent ischemic stroke despite a CHA2DS2-Vasc score similar to those without prior oral anticoagulation. Better prevention strategies are needed for this high-risk patient group. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-03-10

Is Hypothermia Helpful in Severe Subarachnoid Hemorrhage? An Exploratory Study on Macro Vascular Spasm, Delayed Cerebral Infarction and Functional Outcome after Prolonged Hypothermia - Kuramatsu, Joji; Kollmar, Rainer; Gerner, Stefan; Madzar, Dominik; Pisarcikova, Andrea; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (Cerebrovascular Diseases, 2015)
Therapeutic hypothermia (TH) is an established treatment after cardiac arrest and growing evidence supports its use as neuroprotective treatment in stroke. Only few and heterogeneous studies exist on the effect of hypothermia in subarachnoid hemorrhage (SAH). A novel approach of early and prolonged TH and its influence on key complications in poor-grade SAH, vasospasm and delayed cerebral ischemia (DCI) was evaluated.This observational matched controlled study included 36 poor-grade (Hunt and Hess Scale >3 and World Federation of Neurosurgical Societies Scale >3) SAH patients. Twelve patients received early TH (<48 h after ictus), mild (35°C), prolonged (7 ± 1 days) and were matched to 24 patients from the prospective SAH database. Vasospasm was diagnosed by angiography, macrovascular spasm serially evaluated by Doppler sonography and DCI was defined as new infarction on follow-up CT. Functional outcome was assessed at 6 months by modified Rankin Scale (mRS) and categorized as favorable (mRS score 0-2) versus unfavorable (mRS score 3-6) outcome.Angiographic vasospasm was present in 71.0% of patients. TH neither influenced occurrence nor duration, but the degree of macrovascular spasm as well as peak spastic velocities were significantly reduced (p < 0.05). Frequency of DCI was 87.5% in non-TH vs. 50% in TH-treated patients, translating into a relative risk reduction of 43% and preventive risk ratio of 0.33 (95% CI 0.14-0.77, p = 0.036). Favorable functional outcome was twice as frequent in TH-treated patients 66.7 vs. 33.3% of non-TH (p = 0.06).Early and prolonged TH was associated with a reduced degree of macrovascular spasm and significantly decreased occurrence of DCI, possibly ameliorating functional outcome. TH may represent a promising neuroprotective therapy possibly targeting multiple pathways of DCI development, notably macrovascular spasm, which strongly warrants further evaluation of its clinical impact.
EVALuna2:22357

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

It is all about timing: decompressive hemicraniectomy for malignant middle-cerebral-artery infarction - Macha, Kosmas; Schwab, Stefan (Arquivos De Neuro-Psiquiatria, 2023)
CRIS-Team Scopus Importer:2023-06-30

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Körperliche Aktivität und Prävention der Alzheimerdemenz: Übersicht über aktuelle Evidenz und Überlegungen zur Machbarkeit einer Interventionsstudie - Weih, Markus; Abu-Omar, Karim; Esselmann, H; Gelbrich, Götz; Lewczuk, Piotr; Rütten, Alfred; Wiltfang, Jens; Kornhuber, Johannes (Fortschritte der Neurologie - Psychiatrie, 2009)

Lacosamide in patients with intellectual disability and refractory epilepsy - Kleist, Anika; Kerling, Frank; Hamer, Hajo; Winterholler, Martin (Acta Neurologica Belgica, 2019)
The objective of this study was to evaluate the tolerability and efficacy of lacosamide (LCM) in residential patients at our epilepsy centre. We assessed retrospectively 80 patients (mean age 36.2 years, range 18–63 years; 29 female) with intellectual disability (ID) and drug-resistant epilepsy using an industry-independent, non-interventional study design based on standardised seizure records. Evaluation, including calculation of retention rate, was carried out for the intervals 3–6, 9–12 and 21–24 months after LCM initiation. The Clinical Global Impression scale (CGI) was used to allow assessment of qualitative changes in seizure severity and clinical status. CGI improved for 61% of the patients. The responder rate was 48%; ten patients (13%) became seizure free. The response was not related to the degree of ID. The retention rates after 12 and 24 months were 71% and 65%, and were significantly lower in patients taking other sodium-channel blockers (SCBs; 76% vs. 55%). The occurrence of adverse events (AEs) was related to the administration of concomitant SCBs (48% with SCBs vs. 26% without). Sedation (15%), ataxia (13%), vertigo (11%), and nausea (9%) were the commonest AEs. While 60% of our patients had concomitant psychiatric diagnosis, we found no relevant effect of this on challenging behaviour. Adjunctive LCM may provide an antiepileptic treatment option for patients with ID with or without additional psychiatric diagnosis. The occurrence of AEs and the LCM retention rate were affected by concomitant SCB use but not by psychiatric comorbidity.
CRIS-Team Scopus Importer:2019-09-10
Keywords: Antiepileptic drug; Intellectual disability; Lacosamide; Refractory epilepsy

Large diameter hemicraniectomy does not improve long-term outcome in malignant infarction - Lehrieder, Dominik; Müller, Hans Peter; Kassubek, Jan; Hecht, Nils; Thomalla, Götz; Michalski, Dominik; Gattringer, Thomas; Wartenberg, Katja E.; Schultze-Amberger, Jörg; Huttner, Hagen; Kuramatsu, Joji; Wunderlich, Silke; et al. (Journal of Neurology, 2023)
Introduction: In malignant cerebral infarction decompressive hemicraniectomy has demonstrated beneficial effects, but the optimum size of hemicraniectomy is still a matter of debate. Some surgeons prefer a large-sized hemicraniectomy with a diameter of more than 14 cm (HC > 14). We investigated whether this approach is associated with reduced mortality and an improved long-term functional outcome compared to a standard hemicraniectomy with a diameter of less than 14 cm (HC ≤ 14). Methods: Patients from the DESTINY (DEcompressive Surgery for the Treatment of malignant INfarction of the middle cerebral arterY) registry who received hemicraniectomy were dichotomized according to the hemicraniectomy diameter (HC ≤ 14 cm vs. HC > 14 cm). The primary outcome was modified Rankin scale (mRS) score ≤ 4 after 12 months. Secondary outcomes were in-hospital mortality, mRS ≤ 3 and mortality after 12 months, and the rate of hemicraniectomy-related complications. The diameter of the hemicraniectomy was examined as an independent predictor of functional outcome in multivariable analyses. Results: Among 130 patients (32.3% female, mean (SD) age 55 (11) years), the mean hemicraniectomy diameter was 13.6 cm. 42 patients (32.3%) had HC > 14. There were no significant differences in the primary outcome and mortality by size of hemicraniectomy. Rate of complications did not differ (HC ≤ 14 27.6% vs. HC > 14 36.6%, p = 0.302). Age and infarct volume but not hemicraniectomy diameter were associated with outcome in multivariable analyses. Conclusion: In this post-hoc analysis, large hemicraniectomy was not associated with an improved outcome or lower mortality in unselected patients with malignant middle cerebral artery infarction. Randomized trials should further examine whether individual patients could benefit from a large-sized hemicraniectomy. Clinical trial registration information: German Clinical Trials Register (URL: https://www.drks.de ; Unique Identifier: DRKS00000624).
CRIS-Team Scopus Importer:2023-05-26
Keywords: Functional outcome; Hemicraniectomy; Malignant stroke; Middle cerebral artery infarction; Size of hemicraniectomy

Lesion correlates of secondary paroxysmal dyskinesia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Huhn, Konstantin; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Schwab, Stefan; Seifert, Frank (Journal of Neurology, 2018)
Secondary paroxysmal dyskinesia is a rare but life-quality-compromising symptom in multiple sclerosis (MS) and might be associated with particular MS lesions. The present study intended to determine associations between paroxysmal dyskinesia and the MS-associated lesion site using a voxelwise lesion analysis. We conducted a retrospective study and sought MS patients with documented paroxysmal dyskinesia and controls without paroxysmal dyskinesia matched for age, disease severity, and disease duration in a local database. The MS lesions were analysed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T), manually outlined, and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of paroxysmal dyskinesia voxelwise between patients with and without lesions in a given voxel using the Liebermeister test with 4000 permutations. From 15,869 MS patient records screened, we identified 25 patients with paroxysmal dyskinesia. The voxelwise analysis in 22 subjects yielded associations between paroxysmal dyskinesia and MS lesions in the internal capsule, the basal ganglia, and another prominent lesion cluster in the posterior periventricular white matter. Our voxelwise analysis shows associations between paroxysmal dyskinesia and MS lesions in the internal capsule and basal ganglia, areas contributing to motor sequence programming. This association in another lesion site located in the posterior thalamic radiation suggests that lesions in subcortical sensory pathways may also contribute to paroxysmal dyskinesia in MS.
EVALuna2:34912

Lesion mapping of stroke-related erectile dysfunction - Winder, Klemens; Seifert, Frank; Köhrmann, Martin; Crodel, Carl; Kloska, Stephan; Dörfler, Arnd; Hoesl, Katharina M.; Schwab, Stefan; Hilz, Max-Josef (Brain, 2017)
Acute ischaemic stroke in brain areas contributing to male sexual function may impair erectile function depending on the lesion site. This study intended to determine associations between stroke-related erectile dysfunction and cerebral ischaemic lesion sites using voxel-based lesion mapping. In 52 males (mean age 60.5 ± 10.5 years) with first-ever ischaemic strokes, we assessed erectile function after and retrospectively 3 months prior to the stroke using scores of the 5-item International Index of Erectile Function-5 questionnaire. We assessed cardiovascular risk factors and determined clinical stroke severity and infarct volumes as well as total brain volume by neuroimaging. We calculated correlations between patient age, clinical stroke severity, infarct volumes as well as brain volumes and the difference between erectile dysfunction scores before and after stroke. Moreover, we compared patient age, prevalence of cardiovascular risk factors, clinical stroke severity, infarct volumes and brain volumes of patients with unchanged and deteriorated erectile function after stroke. The infarcts were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed subtraction analyses of lesions. In a voxel-based lesion analysis, the difference between erectile dysfunction scores before and after stroke was correlated with the lesion site using t-test statistics. Finally, we conducted a region of interest-based multivariate linear regression analysis that was adjusted for potential confounding factors including patient age, clinical stroke severity, imaging modality, lesion size and brain volume. In 32 patients (61.5%) erectile dysfunction scores declined after the stroke and therefore had stroke-related erectile dysfunction. Deterioration of erectile dysfunction scores was not associated with patient age, clinical stroke severity, infarct volume, brain volume, and cardiovascular risk factors. The voxel-wise subtraction analysis showed associations between stroke-related erectile dysfunction and lesion sites in the right occipito-parietal cortex and thalamus, as well as in the left insula and adjacent temporo-parietal areas. Using voxel-wise t-test statistics, we showed associations between deterioration of erectile function and lesion sites in the right occipital and thalamic region, and the left parietal association area. The linear regression analysis showed that stroke-related erectile dysfunction remained associated with lesions of the right occipital and left parietal association areas after adjusting for confounding factors. In conclusion, our voxel-wise analysis indicates that deteriorating erectile function after stroke is associated with lesions in the right occipito-parietal and thalamic areas integrating visual and somatosensory information, as well as lesions in the left insular and adjacent parieto-temporal areas contributing to generating and mapping visceral arousal states.
EVALuna2:22497

Lessons learned from transcutaneous vagus nerve stimulation (tVNS) - Hamer, Hajo; Bauer, Sebastian (Epilepsy Research, 2019)
Transcutaneous vagus nerve stimulation (tVNS) is a newly developed method which intends to overcome the disadvantage of surgical implantation of the stimulation device. The tVNS device is designed to stimulate the auricular branch of the vagus nerve via a bipolar electrode attached to the skin of the left ear conch. A randomized, double-blind controlled trial assessed efficacy and safety over 20 weeks of tVNS (n=39) vs. active control tVNS (n=37) in patients with drug-resistant epilepsy. While the mean seizure reduction per 28 days at end of treatment (2.9% reduction from baseline in the control group vs 23.4% in the active group) did not reach statistical significance, there was a significant reduction in seizure frequency (34 %) in patients in the tVNS group at the end of the treatment period (20 weeks). TVNS was well-tolerated. The results justify further trials with longer observation periods and possibly at earlier stages of epilepsy.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Epilepsy; Seizures; Transcutaneous vagus nerve stimulation; Treatment

Letter by Kallmünzer et al Regarding Article, "safety of Intravenous Thrombolysis among Patients Taking Direct Oral Anticoagulants: A Systematic Review and Meta-Analysis" - Kallmünzer, Bernd; Pott, Michael; Schwab, Stefan (Stroke, 2020)
CRIS-Team Scopus Importer:2020-07-17

Limbic encephalitis with mGluR5 antibodies and immunotherapy-responsive prosopagnosia - Pruess, Harald; Rothkirch, Marcus; Kopp, Ute; Hamer, Hajo; Hagge, Mareike; Sterzer, Phillipp; Saschenbrecker, Sandra; Stoecker, Winfried; Harms, Lutz; Endres, Matthias (Neurology, 2014)
EVALuna2:22302

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Linear projection-based CEST parameter estimation - Glang, Felix; Fabian, Moritz S.; German, Alexander; Khakzar, Katrin; Mennecke, Angelika; Liebert, Andrzej; Herz, Kai; Liebig, Patrick; Kasper, Burkhard S.; Schmidt, Manuel; Zuazua Iriondo, Enrique; Nagel, Armin M.; et al. (NMR in Biomedicine, 2022)
Isolated evaluation of multi-parametric in vivo CEST MRI often requires complex computational processing for both correction of B0 and B1 inhomogeneity and contrast generation. For that, sufficiently densely sampled Z-spectra need to be acquired. The list of acquired frequency offsets largely determines the total CEST acquisition time, while potentially representing redundant information. In this work, a linear projection-based multi parametric CEST evaluation method is introduced that offers fast B0 and B1 inhomogeneity correction, contrast generation and feature selection for CEST data, enabling reduction of the overall measurement time. To that end, CEST data acquired at 7T in 6 healthy subjects and in one brain tumor patient were conventionally evaluated by interpolation-based inhomogeneity correction and Lorentzian curve fitting. Linear regression was used to obtain coefficient vectors that directly map uncorrected data to corrected Lorentzian target parameters. L1 regularization was applied to find subsets of the originally acquired CEST measurements that still allow for such a linear projection mapping. The linear projection method allows fast and interpretable mapping from acquired raw data to contrast parameters of interest, generalizing from healthy subject training data to unseen healthy test data and to the tumor patient dataset. The L1 regularization method shows that a fraction of the acquired CEST measurements is sufficient to preserve tissue contrasts, offering up to 2.8-fold reduction of scan time. Similar observations as for the 7T data can be made for data from a clinical 3T scanner. Being a fast and interpretable computation step, the proposed method is complementary to neural networks, which have been recently employed for similar purposes. The scan time acceleration offered by the L1 regularization (‘CEST-LASSO’) constitutes a step towards better applicability of multi parametric CEST protocols in clinical context.<br
Keywords: chemical exchange saturation transfer (CEST); feature selection; LASSO; APT; NOE; linear projection

Liquorpunktion – Schritt für Schritt - Siedler, Gabriela; Kallmünzer, Bernd; Schwab, Stefan (Deutsche Medizinische Wochenschrift, 2019)
Performing a diagnostic lumbar puncture is an essential clinical skill for the clinician. The procedure is of high importance for both, the emergency care for patients with suspected infection of the cerebral nervous system or subarachnoidal hemorrhage, as well as the elective diagnostic work up of chronic disease including multiple sclerosis and dementia. Furthermore the technique's principles are applied for spinal anesthesia or the intrathecal administration of drugs. This article describes a Standard Operating Procedure for the lumbar puncture step by step. Based on the latest evidence, it particularly focusses on clinically relevant questions and practical aspects.
CRIS-Team Scopus Importer:2019-10-08
Keywords: atraumatic needle; cerebrospinal fluid analysis; diagnostic lumbar puncture; post-lumbar; puncture headache

Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Rösch, Julie; Müller, Nadia; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Dörfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in the pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent the Wada test. We analyzed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13 and 35 Hz was localized applying Dynamic Imaging of Coherent Sources Beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event-related desynchronization of beta power in MEG was seen within the language-dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa = 1, p < 0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa = 0.71, p = 0.024), while the agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with the lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in the pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: beta power decrease; epilepsy; epilepsy surgery; functional magnetic resonance imaging (fMRI); intracarotid sodium amobarbital procedure (IAT); language lateralization; magnetoencephalography (MEG); Wada test

Longer-term effects of intravenous immunoglobulin treatment in chronic inflammatory demyelinating polyneuropathy: Who benefits? - Terhoeven, Pauline; Seybold, Julia; Utz, Katrin; Nickel, Franziska; Lee, De-Hyung; Linker, Ralf (Journal of the Neurological Sciences, 2020)
Intravenous immunoglobulins (IVIg) represent an established cornerstone for the immunotherapy of chronic inflammatory demyelinating polyneuropathy (CIDP). Efficacy of IVIg for CIDP was proven in a large phase III trial. Yet, data on longer-term efficacy and effects in distinct subgroups are scarce. Our trial investigates the long-term efficacy of IVIg treatment in CIDP patients. In this observational real-world study, we retrospectively analyzed 49 CIDP patients receiving continuous IVIg treatment with a mean initial dosage of 87 g (1 g/kg body weight) every 4 weeks over a mean time of 45 months between 2010 and 2018. INCAT-Scores before the start of treatment and at the end of the observation period were compared. Over the observation period, IVIg treatment led to a median improvement of one INCAT score point. Subgroup analyses revealed a more pronounced improvement of INCAT scores in female CIDP patients, individuals with relapsing disease courses, patients with more pronounced motor impairment (higher initial INCAT scores) and in the cohort without need for concomitant other immunotherapies. These data argue for sustained beneficial effects of longer-term immunotherapy with IVIg in CIDP, particularly in females and relapsing disease forms with higher disease activity.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Chronic inflammatory demyelinating polyneuropathy; Immunotherapy; Intravenous immunoglobulins; Long-term effect; Polyneuritis

Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI - Mennecke, Angelika; Nagel, Armin Michael; Huhn, Konstantin; Linker, Ralf; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2021)
Background Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type Prospective. Subjects Twenty-nine relapsing-remitting MS patients with an acute relapse were included. Field Strength/Sequence A 3D density-adapted radial sodium sequence at 3 T using a dual-tuned (Na-23/H-1) head coil. Assessment Full-brain images of the tissue sodium concentration (TSC1, n = 29) and a sodium inversion recovery sequence (SIR1, n = 20) at the beginning of the anti-inflammatory therapy and on medium-term follow-up visits (days 27-99, n = 12 [TSC], n = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1CE+) and without change in T1-weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests nTSC and nSIR were compared regarding the type of lesion and the time point using a one-way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1-nTSC2 over nSIR1. A P-value At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T(1)n and the T1CE+ lesions in comparison to the normal-appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level 2 Technical Efficacy Stage 4
CRIS-Team WoS Importer:2021-07-23

Long-term antithrombotic treatment in intracranial hemorrhage survivors with atrial fibrillation - Korompoki, Eleni; Filippidis, Filippos T.; Nielsen, Peter B.; Del Giudice, Angela; Lip, Gregory Y. H.; Kuramatsu, Joji; Huttner, Hagen; Fang, Jiming; Schulman, Sam; Marti-Fabregas, Joan; Gathier, Celine S.; Viswanathan, Anand; et al. (Neurology, 2017)
To perform a systematic review and meta-analysis of studies reporting recurrent intracranial hemorrhage (ICH) and ischemic stroke (IS) in ICH survivors with atrial fibrillation (AF) during long-term follow-up.A comprehensive literature search including MEDLINE, EMBASE, Cochrane library, clinical trials registry was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. We considered studies capturing outcome events (ICH recurrence and IS) for >=3 months and treatment exposure to vitamin K antagonists (VKAs), antiplatelet agents (APAs), or no antithrombotic medication (no-ATM). Corresponding authors provided aggregate data for IS and ICH recurrence rate between 6 weeks after the event and 1 year of follow-up for each treatment exposure. Meta-analyses of pooled rate ratios (RRs) were conducted with the inverse variance method.Seventeen articles met inclusion criteria. Seven observational studies enrolling 2,452 patients were included in the meta-analysis. Pooled RR estimates for IS were lower for VKAs compared to APAs (RR = 0.45, 95% confidence interval [CI] 0.27-0.74, p = 0.002) and no-ATM (RR = 0.47, 95% CI 0.29-0.77, p = 0.002). Pooled RR estimates for ICH recurrence were not significantly increased across treatment groups (VKA vs APA: RR = 1.34, 95% CI 0.79-2.30, p = 0.28; VKA vs no-ATM: RR = 0.93, 95% CI 0.45-1.90, p = 0.84).In observational studies, anticoagulation with VKA is associated with a lower rate of IS than APA or no-ATM without increasing ICH recurrence significantly. A randomized controlled trial is needed to determine the net clinical benefit of anticoagulation in ICH survivors with AF.
EVALuna2:22565

Long-term effects of zonisamide in adult patients with intellectual disability - Eck, Kattrinna; Rauch, Christophe; Kerling, Frank; Hamer, Hajo; Winterholler, Martin (Acta Neurologica Scandinavica, 2021)
Objective This study aimed to evaluate the tolerability and efficacy of zonisamide (ZNS) in adult patients with drug-resistant epilepsy and intellectual disability (ID) at our epilepsy centre.
CRIS-Team WoS Importer:2021-05-21

Long-term Fingolimod therapy increases sympathetic cardiovascular modulation - Wang, Ruihao; Hilz, Max-Josef; Roy, Sankanika; Liu, Mao; de Rojas Leal, Carmen; Hoesl, Katharina M.; Winder, Klemens; Lee, De-Hyung; Linker, Ralf (2018)
EVALuna2:35519

Long-term outcome after epilepsy surgery in older adults - Lang, Johannes D.; Grell, Laura; Hagge, Mareike; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Graf, Wolfgang; Schwarz, Michael; Coras, Roland; Blümcke, Ingmar; Sommer, Bjoern; Roessler, Karl; Buchfelder, Michael; et al. (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: The incidence of epilepsy in older adults is growing, as does the incidence of comorbidities. Therefore, when it comes to epilepsy surgery in medically intractable epilepsy, age is often seen as a limiting factor. To investigate the outcome after epilepsy surgery in a population of older adults, we compared the benefit for patients aged 50-59 years with those aged 60 years and older in respect of efficacy and safety. METHOD: Patients aged ≥50 years with medically intractable epilepsy who underwent epilepsy surgery from 1990 to 2013 were selected from the database of a German epilepsy center. All of them received a standardised and detailed presurgical diagnostic evaluation. Follow-up included at least four scheduled visits with EEG, MRI and neuropsychological testing. Outcome was assessed using the Engel outcome scale. RESULTS: 79 patients aged between 50 and 67 years were followed-up for a median of 4.7 years (2-16 years). 68% of patients were free of disabling seizures (Engel class I, ≥60 years: 75%) and 58% were seizure-free (Engel class IA, ≥60 years: 70%). 90% of our patients suffered from temporal lobe epilepsy (TLE), 9% from frontal lobe epilepsy (FLE) and one occipital lobe epilepsy (OLE). After surgery, 9% discontinued or tapered their medication. Permanent surgical complications occurred in 10% of cases and transient neurological deficits were seen in 11%. Older patients had a higher risk for postoperative hygroma (≥60 years 15%; <60 years 8%) and were more prone to postoperative memory deficits (≥60 years 45%), especially after resection of the dominant temporal lobe. Verbal and figural memory testing did not differ significantly between the groups. CONCLUSIONS: The results support the view that in selected older patients, epilepsy surgery shows equal or even higher success rates as compared to younger patients. However, patients of older age may be at greater risk for postoperative hygroma and memory deficits, especially after dominant temporal lobe resections.
EVALuna2:34593

Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin

Lymphocytopenia Is an Independent Predictor of Unfavorable Functional Outcome in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Madzar, Dominik; Sembill, Jochen; Lücking, Hannes; Kloska, Stephan; Keil, Toni; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2016)
Stroke-associated immunosuppression is an increasingly recognized factor triggering infections and thus potentially influencing outcome after stroke. Specifically, lymphocytopenia after intracerebral hemorrhage (ICH) has only been addressed in small-sized retrospective studies of mixed intracranial bleedings. This cohort study investigated the natural course of lymphocytopenia, parameters associated with lymphocytopenia on admission (LOA) and during stay, and evaluated the clinical impact of lymphocytopenia in solely ICH patients.This observational study included 855 consecutive patients with ICH. Patient demographics, clinical and neuroradiological data as well as laboratory and in-hospital measures were retrieved from institutional prospective databases. Functional 3-month outcome was assessed by mailed questionnaires. Lymphocytopenia was defined as <1.0 (10(9)/L) and was correlated with patient's characteristics and outcome.Prevalence of LOA was 27.3%. Patients with LOA showed significant associations with poorer neurological status (18 [10-32] versus 13 [5-24]; P<0.001), larger hematoma volume (18.5 [6.2-46.2] versus 12.8 [4.4-37.8]; P=0.006), and unfavorable outcome (74.7% versus 63.3%; P=0.0018). Natural course of lymphocyte count during hospital stay revealed a lymphocyte nadir of 1.1 (0.80-1.53 [10(9)/L]) at day 5. Focusing on patients with day-5-lymphocytopenia, compared with patients with LOA, revealed increased rates of infections (63 [71.6] versus 113 [48.5]; P<0.001) and poorer functional outcome at 3 months (76 [86.4] versus 175 [75.1); P=0.029). Adjusting for baseline confounders, multivariable logistic and receiver operating characteristics analyses documented independent associations of day-5-lymphocytopenia with unfavorable outcome (day-5-lymphocytopenia: odds ratio, 2.017 [95% confidence interval, 1.029-3.955], P=0.041; LOA: odds ratio, 1.391 [0.795-2.432], P=0.248; receiver operating characteristics: day-5-lymphocytopenia: area under the curve=0.673, P<0.0001, Youden's index=0.290; LOA: area under the curve=0.513, P=0.676, Youden's index=0.084), whereas receiver operating characteristics analyses revealed no association of age or hematoma volume with day-5-lymphocytopenia (age: area under the curve=0.540, P=0.198, Youden's index=0.106; volume: area under the curve=0.550, P=0.0898, Youden's index=0.1224).Lymphocytopenia is frequently present in patients with ICH and may represent an independent parameter associated with unfavorable functional outcome. Developing lymphocytopenia affected outcome even stronger than LOA, a finding that may open up new therapeutic avenues in specific subsets of patients with ICH.
EVALuna2:22442

Macrophages in neuroinflammation: role of the renin-angiotensin-system - Hammer, Anna; Stegbauer, Johannes; Linker, Ralf (Pflügers Archiv: European Journal of Physiology, 2017)
Macrophages are essential players of the innate immune system which are involved in the initiation and progression of various inflammatory and autoimmune diseases including neuroinflammation. In the past few years, it has become increasingly clear that the regulation of macrophage responses by the local tissue milieu is also influenced by mediators which were first discovered as regulators in the nervous or also cardiovascular system. Here, the renin-angiotensin system (RAS) is a major focus of current research. Besides its classical role in blood pressure control, body fluid, and electrolyte homeostasis, the RAS may influence (auto)immune responses, modulate T cells, and particularly act on macrophages via different signaling pathways. Activation of classical RAS pathways including angiotensin (Ang) II and AngII type 1 (AT1R) receptors may drive pro-inflammatory macrophage responses in neuroinflammation via regulation of chemokines. More recently, alternative RAS pathways were described, such as binding of Ang-(1-7) to its receptor Mas. Signaling via Mas pathways may counteract some of the AngII/AT1R-mediated effects. In macrophages, the Ang-(1-7)/Mas exerts beneficial effects on neuroinflammation via modulating macrophage polarization, migration, and T cell activation in vitro and in vivo. These data delineate a pivotal role of the RAS in inflammation of the nervous system and identify RAS modulation as a potential new target for immunotherapy with a special focus on macrophages.
EVALuna2:22498

MAdCAM-1-Mediated Intestinal Lymphocyte Homing Is Critical for the Development of Active Experimental Autoimmune Encephalomyelitis - Kuhbandner, Kristina; Hammer, Anna; Haase, Stefanie; Terbrack, Elisa; Hoffmann, Alana; Schippers, Angela; Wagner, Norbert; Hussain, Rehana Z.; Miller-Little, William A.; Koh, Andrew Y.; Stoolman, Joshua S.; Segal, Benjamin M.; et al. (Frontiers in Immunology, 2019)
Lymphocyte homing into the intestine is mediated by binding of leukocytes to mucosal addressin cell adhesion molecule 1 (MAdCAM-1), expressed on endothelial cells. Currently, the immune system of the gut is considered a major modulator not only of inflammatory bowel disease, but also of extra-intestinal autoimmune disorders, including multiple sclerosis (MS). Despite of intense research in this field, the exact role of the intestine in the pathogenesis of (neuro-) inflammatory disease conditions remains to be clarified. This prompted us to investigate the role of MAdCAM-1 in immunological processes in the intestine during T cell-mediated autoimmunity of the central nervous system (CNS). Using the experimental autoimmune encephalomyelitis model of MS, we show that MAdCAM-1-deficient (MAdCAM-1-KO) mice are less susceptible to actively MOG35-55-induced disease. Protection from disease was accompanied by decreased numbers of immune cells in the lamina propria and Peyer's patches as well as reduced immune cell infiltration into the spinal cord. MOG35-55-recall responses were intact in other secondary lymphoid organs of MAdCAM-1-KO mice. The composition of specific bacterial groups within the microbiome did not differ between MAdCAM-1-KO mice and controls, while MAdCAM-1-deficiency severely impaired migration of MOG35-55-activated lymphocytes to the gut. Our data indicate a critical role of MAdCAM-1 in the development of CNS inflammation by regulating lymphocyte homing to the intestine, and may suggest a role for the intestinal tract in educating lymphocytes to become encephalitogenic.
CRIS-Team WoS Importer:2019-05-03

Magnetoencephalography for epileptic focus localization in a series of 1000 cases. - Rampp, Stefan; Stefan, Hermann; Wu, Xintong; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard S.; Schwab, Stefan; Blümcke, Ingmar; Rössler, Karl; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
EVALuna2:204465

Magnetoencephalography for epileptic focus localization in a series of 1000 cases - Rampp, Stefan; Stefan, Hermann; Wu, Xueqing; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard; Schwab, Stefan; Dörfler, Arnd; Blümcke, Ingmar; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
CRIS-Team Scopus Importer:2019-10-08
Keywords: epilepsy; epilepsy surgery; long-term outcome; magnetic source imaging; magnetoencephalography

Magnetoencephalography-guided surgery in frontal lobe epilepsy using neuronavigation and intraoperative MR imaging - Sommer, Bjoern; Roessler, Karl; Rampp, Stefan; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Buchfelder, Michael (Epilepsy Research, 2016)
Especially in hidden lesions causing drug-resistant frontal lobe epilepsy (FLE), the localization of the epileptic zone EZ can be a challenge. Magnetoencephalography (MEG) can raise the chances for localization of the (EZ) in combination with electroencephalography (EEG). We investigated the impact of MEG-guided epilepsy surgery with the aid of neuronavigation and intraoperative MR imaging (iopMRI) on seizure outcome of FLE patients.Twenty-eight patients (15 females, 13 males; mean age 31.0±11.1 years) underwent surgery in our department. All patients underwent presurgical MEG monitoring (two-sensor Magnes II or whole head WH3600 MEG system; 4-D Neuroimaging, San Diego, CA, USA). Of those, six patients (group 1) with MRI-negative FLE were operated on before 2002 with intraoperative electrocorticography (ECoG) and invasive EEG mapping only. Eleven patients with MRI-negative FLE (group 2) and eleven with lesional FLE (group 3) underwent surgery using 1.5T-iopMRI and neuronavigation, including intraoperative visualization of the MEG localizations in 22 and functional MR imaging (for motor and speech areas) as well as DTI fiber tracking (for language and pyramidal tracts) in 13 patients.In the first group, complete resection of the defined EZ including the MEG localization according to the latest postoperative MRI was achieved in four out of six patients. Groups two and three had complete removal of the MEG localizations in 20/22 (91%, 10 of 11 each). Intraoperative MRI revealed incomplete resection of the MEG localizations of four patients (12%; two in both groups), leading to successful re-resection. Transient and permanent neurological deficits alike occurred in 7.1%, surgery-associated complications in 11% of all patients. In the first group, excellent seizure outcome (Engel Class IA) was achieved in three (50%), in the second in 7 patients (61%) and third group in 8 patients (64%, two iopMRI-based re-resections). Mean follow-up was 70.3 months (from 12 to 284 months).In our series, MEG-guided resection using neuronavigation and iopMR imaging led to promising seizure control rates. Even in non-lesional FLE, seizure control rates and the probability of complete resection of the MEG localizations was similar to lesional FLE using multimodal navigation.
EVALuna2:7339

MANAGEMENT OF INSUFFICIENT FUNCTIONAL ANTITHROMBOTIC ACTIVITY DURING TREATMENT WITH DIRECT ORAL ANTICOAGULANTS FOR STROKE PREVENTION - Macha, Kosmas; Stoll, Svenja; Siedler, Gabriela; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Management of oral anticoagulation after intracerebral hemorrhage - Kuramatsu, Joji; Huttner, Hagen (International Journal of Stroke, 2019)
Background The most recent years have significantly expanded knowledge regarding risks and benefits of resuming oral anticoagulation (OAC) after intracerebral hemorrhage (ICH). No randomized data is yet available, though several large observational studies and meta-analyses have investigated the impact of resuming OAC on thromboembolic versus hemorrhagic complications in these high-risk patients after ICH. Aims The present review will summarize the most important studies conducted over the last years and will focus on relevant factors help guiding on decision-making on whether to start OAC after ICH. Summary of review Several important factors (demographic, co-morbidities, clinical characteristics) need to be considered before individual decision-making for or against OAC is employed. Existing observational data suggest that patients after ICH with indication for long-term oral anticoagulation benefit from OAC given significant reductions of thromboembolic events without significantly increasing bleeding complications. Studies even suggest that thereby also clinical outcomes may be improved. Prospective trials currently recruiting patients will clarify whether OAC after ICH - or left atrial appendage closure as a meaningful alternative - is of clinical net-benefit. Conclusions Large sized and well-executed investigations (moderate quality of evidence) are showing that OAC resumption after ICH decreases thromboembolic complications and long-term mortality without significantly increasing bleeding complications. Further, data suggest that resumption may be safer in non-lobar ICH compared to lobar ICH, but overall, thoughtful selection, strict blood pressure control, and precise communication are paramount before starting a patient on OAC after ICH.
CRIS-Team WoS Importer:2019-04-02

Management of Stroke in Patients with Left Ventricular Assist Devices - Giede-Jeppe, Antje; Röder, Sebastian; Macha, Kosmas; Huttner, Hagen; Gerner, Stefan; Fröhlich, Kilian; Heim, Christian; Schwab, Stefan; Kallmünzer, Bernd (Journal of Stroke and Cerebrovascular Diseases, 2020)
Introduction: The number of patients with left ventricular assist devices (LVAD) is rapidly growing in industrialized countries. While cerebrovascular events comprise a significant complication, data on stroke etiology, clinical management and functional outcome are scarce. Methods: Consecutive LVAD patients with ischemic or hemorrhagic stroke receiving treatment at an university stroke center between 2010 and 2018 were included into an institutional registry. Clinical characteristics, causes, management and functional outcome of stroke occurring within this cohort are reported. Acceptable functional outcome was defined as mRS 0-3. Results: N = 30 acute strokes occurred in 20 patients (77% ischemic, 23% hemorrhagic, mean age 57 ± 13 years, 10% female, 8 patients (40%) had more than one event). 87% of all events happened with non-pulsatile devices, on average 9 (IQR 3-22) months after the implantation. All patients used oral anticoagulation with a Vitamin-K antagonist in combination with anti-platelets. The international normalized ratio (INR)-values were outside the therapeutic range in 39% of ischemic strokes and in 57% of hemorrhagic strokes. Ischemic strokes were predominantly of cardioembolic origin (92%) and of mild to moderate clinical severity (median NIHSS 6 (IQR 4-10). None qualified to receive intravenous thrombolysis or intra-arterial endovascular therapy. 61% of IS-patients showed an acceptable functional outcome after three months. 4/7 patients with hemorrhagic stroke received immediate reversal of anticoagulation without any thrombotic complications. Conclusion: The majority of LVAD patients with ischemic stroke had an acceptable functional outcome after three months. Future clinical research is warranted to improve therapeutic strategies for acute care and stroke prevention.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Functional outcome; Intracerebral hemorrhage; Ischemic stroke; Left ventricular assist devices

Management of supine hypertension in patients with neurogenic orthostatic hypotension: scientific statement of the American Autonomic Society, European Federation of Autonomic Societies, and the European Society of Hypertension - Jordan, Jens; Fanciulli, Alessandra; Tank, Jens; Calandra-Buonaura, Giovanna; Cheshire, William P.; Cortelli, Pietro; Eschlboeck, Sabine; Grassi, Guido; Hilz, Max-Josef; Kaufmann, Horacio; Lahrmann, Heinz; Mancia, Giuseppe; et al. (Journal of Hypertension, 2019)
: Supine hypertension commonly occurs in patients with neurogenic orthostatic hypotension due to autonomic failure. Supine hypertension promotes nocturnal sodium excretion and orthostatic hypotension, thus, interfering with quality of life. Perusal of the literature on essential hypertension and smaller scale investigations in autonomic failure patients also suggest that supine hypertension may predispose to cardiovascular and renal disease. These reasons provide a rationale for treating supine hypertension. Yet, treatment of supine hypertension, be it through nonpharmacological or pharmacological approaches, may exacerbate orthostatic hypotension when patients get up during the night. Fall-related complications may occur. More research is needed to define the magnitude of the deleterious effects of supine hypertension on cardiovascular, cerebrovascular, and renal morbidity and mortality. Integration of more precise cardiovascular risk assessment, efficacy, and safety data, and the prognosis of the underlying condition causing autonomic failure is required for individualized management recommendations.
CRIS-Team Scopus Importer:2019-07-26

Management of therapeutic anticoagulation in patients with intracerebral haemorrhage and mechanical heart valves - Kuramatsu, Joji; Sembill, Jochen; Gerner, Stefan; Sprügel, Maximilian; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (European Heart Journal, 2018)
Aims Evidence is lacking regarding acute anticoagulation management in patients after intracerebral haemorrhage (ICH) with implanted mechanical heart valves (MHVs). Our objective was to investigate anticoagulation reversal and resumption strategies by evaluating incidences of haemorrhagic and thromboembolic complications, thereby defining an optimal time-window when to restart therapeutic anticoagulation (TA) in patients with MHV and ICH. Methods and results We pooled individual patient- data (n = 2504) from a nationwide multicentre cohort-study (RETRACE, conducted at 22 German centres) and eventually identified MHV-patients (n = 137) with anticoagulation-associated ICH for outcome analyses. The primary outcome consisted of major haemorrhagic complications analysed during hospital stay according to treatment exposure (restarted TA vs. no-TA). Secondary outcomes comprised thromboembolic complications, the composite outcome (haemorrhagic and thromboembolic complications), timing of TA, and mortality. Adjusted analyses involved propensity-score matching and multivariable cox-regressions to identify optimal timing of TA. In 66/137 (48%) of patients TA was restarted, being associated with increased haemorrhagic (TA = 17/66 (26%) vs. no-TA = 4/71 (6%); P < 0.01) and a trend to decreased thromboembolic complications (TA = 1/66 (2%) vs. no-TA = 7/71 (10%); P = 0.06). Controlling treatment crossovers provided an incidence rate-ratio [hazard ratio (HR) 10.31, 95% confidence interval (CI) 3.67-35.70; P < 0.01] in disadvantage of TA for haemorrhagic complications. Analyses of TA-timing displayed significant harm until Day 13 after ICH (HR 7.06, 95% CI 2.33-21.37; P < 0.01). The hazard for the composite-balancing both complications, was increased for restarted TA until Day 6 (HR 2.51, 95% CI 1.10-5.70; P = 0.03). Conclusion Restarting TA within less than 2 weeks after ICH in patients with MHV was associated with increased haemorrhagic complications. Optimal weighing-between least risks for thromboembolic and haemorrhagic complications-provided an earliest starting point of TA at Day 6, reserved only for patients at high thromboembolic risk.
EVALuna2:34917

Manufacturer switch of anti-seizure drugs may not increase the risk of seizure recurrence in Children: A nationwide study of prescription data in Germany - Lang, Johannes; Kostev, Karel; Reindl, Caroline; Müller, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Westermayer, Vivien; Trollmann, Regina; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: Several publications on the exchangeability of antiepileptic drugs in clinical settings revealed an increased risk for seizure recurrence after changing the manufacturer of anti-seizure drugs (ASD) in adults, possibly due to a decline of adherence. It is unclear whether this holds true in children and adolescents. Methods: Patient data of children and adolescents (<18 years) were collected anonymously from 236 German pediatricians and pediatric neurologists between January 2011 and December 2018 using the IMS® Disease Analyzer database (IQVIA, Frankfurt, Germany). Patients with epilepsy were included if at least 2 prescriptions within 360 days and 1 within 180 days prior to the index date were available. The cohort was separated into a seizure group and seizure-free controls. Both groups were matched 1:1 according to age, gender, insurance status, and treating pediatrician. The risk for seizure recurrence after a manufacturer switch of the same ASD at the last prescription before the index date was analyzed using a multivariate regression model. Results: A total of 678 children and adolescents with epilepsy were included (each group: n = 339; age: 9.6 ± 4.4 years). Comparing both groups, the risk for seizures recurrence was not increased after a manufacturer switch had occurred. Albeit changes during the last prescription before the index date had occurred more often in the seizure-free group, neither change of branded and generic products nor substances reached significance. Only change of ASD strength showed a significantly reduced odds ratio for seizures (OR 0.40, 95% CI 0.24–0.65, p < 0.001). Significance: In contrast to the available evidence in adults, changing the manufacturer did not appear to increase the risk for seizure recurrence in previously seizure-free children and adolescents with epilepsy.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Anti-seizure drugs; Manufacturer changes; Relapse seizures

MEG in frontal epilepsy - Rampp, Stefan; Kasper, Burkhard; Brandner, Sebastian; Hamer, Hajo; Buchfelder, Michael (Zeitschrift für Epileptologie, 2022)
Magnetoencephalography (MEG) offers considerable advantages for presurgical localization diagnostics of frontal and generalized extratemporal epilepsy. A number of retrospective and prospective studies show a significant impact on the planning of invasive recordings and epilepsy surgical procedures with marked improvement of postoperative seizure control. This article provides a concise overview of the current state of the evidence.
CRIS-Team WoS Importer:2022-02-04

MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Roessler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07

MEG Node Degree for Focus Localization: Comparison with Invasive EEG - Rampp, Stefan; Kaltenhaeuser, Martin; Müller-Voggel, Nadia; Dörfler, Arnd; Kasper, Burkhard S.; Hamer, Hajo; Brandner, Sebastian; Buchfelder, Michael (Biomedicines, 2023)
Epilepsy surgery is a viable therapy option for patients with pharmacoresistant focal epilepsies. A prerequisite for postoperative seizure freedom is the localization of the epileptogenic zone, e.g., using electro- and magnetoencephalography (EEG/MEG). Evidence shows that resting state MEG contains subtle alterations, which may add information to the workup of epilepsy surgery. Here, we investigate node degree (ND), a graph-theoretical parameter of functional connectivity, in relation to the seizure onset zone (SOZ) determined by invasive EEG (iEEG) in a consecutive series of 50 adult patients. Resting state data were subjected to whole brain, all-to-all connectivity analysis using the imaginary part of coherence. Graphs were described using parcellated ND. SOZ localization was investigated on a lobar and sublobar level. On a lobar level, all frequency bands except alpha showed significantly higher maximal ND (mND) values inside the SOZ compared to outside (ratios 1.11-1.20, alpha 1.02). Area-under-the-curve (AUC) was 0.67-0.78 for all expected alpha (0.44, ns). On a sublobar level, mND inside the SOZ was higher for all frequency bands (1.13-1.38, AUC 0.58-0.78) except gamma (1.02). MEG ND is significantly related to SOZ in delta, theta and beta bands. ND may provide new localization tools for presurgical evaluation of epilepsy surgery.
CRIS-Team WoS Importer:2023-03-24
Keywords: MEG; epilepsy; epilepsy surgery; connectivity; graph theory; focus localization

Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031

Metformin inhibits proliferation and migration of glioblastoma cells independently of TGF-?2 - Seliger, Corinna; Meyer, Anne-Louise; Renner, Kathrin; Leidgens, Verena; Moeckel, Sylvia; Jachnik, Birgit; Dettmer, Katja; Tischler, Ulrike; Gerthofer, Valeria; Rauer, Lisa; Uhl, Martin; Proescholdt, Martin; et al. (Cell Cycle, 2016)
To this day, glioblastoma (GBM) remains an incurable brain tumor. Previous research has shown that metformin, an oral anti-diabetic drug, may decrease GBM cell proliferation and migration especially in brain tumor initiating cells (BTICs). As transforming growth factor ? 2 (TGF-?2) has been reported to promote high-grade glioma and is inhibited by metformin in other tumors, we explored whether metformin directly interferes with TGF-?2-signaling. Functional investigation of proliferation and migration of primary BTICs after treatment with metformin+/-TGF-?2 revealed that metformin doses as low as 0.01 mM metformin thrice a day were able to inhibit proliferation of susceptible cell lines, whereas migration was impacted only at higher doses. Known cellular mechanisms of metformin, such as increased lactate secretion, reduced oxygen consumption and activated AMPK-signaling, could be confirmed. However, TGF-?2 and metformin did not act as functional antagonists, but both rather inhibited proliferation and/or migration, if significant effects were present. We did not observe a relevant influence of metformin on TGF-?2 mRNA expression (qRT-PCR), TGF-?2 protein expression (ELISA) or SMAD-signaling (Western blot). Therefore, it seems that metformin does not exert its inhibitory effects on GBM BTIC proliferation and migration by altering TGF-?2-signaling. Nonetheless, as low doses of metformin are able to reduce proliferation of certain GBM cells, further exploration of predictors of BTICs' susceptibility to metformin appears justified.
EVALuna2:22529

MicroRNAs in epilepsy: pathophysiology and clinical utility - Henshall, David C.; Hamer, Hajo; Pasterkamp, R. Jeroen; Goldstein, David B.; Kjems, Jorgen; Prehn, Jochen H. M.; Schorge, Stephanie; Lamottke, Kai; Rosenow, Felix (Lancet Neurology, 2016)
Temporal lobe epilepsy is a common and frequently intractable seizure disorder. Its pathogenesis is thought to involve large-scale alterations to the expression of genes controlling neurotransmitter signalling, ion channels, synaptic structure, neuronal death, gliosis, and inflammation. Identification of mechanisms coordinating gene networks in patients with temporal lobe epilepsy will help to identify novel therapeutic targets and biomarkers. MicroRNAs (miRNAs) are a family of small non-coding RNAs that control the expression levels of multiple proteins by decreasing mRNA stability and translation, and could therefore be key regulatory mechanisms and therapeutic targets in epilepsy.In the past 5 years, studies have found changes in miRNA levels in the hippocampus of patients with temporal lobe epilepsy and in neural tissues from animal models of epilepsy. Early functional studies showed that silencing of brain-specific miR-134 using antisense oligonucleotides (antagomirs) had potent antiseizure effects in animal models, whereas genetic deletion of miR-128 produced fatal epilepsy in mice. Levels of certain miRNAs were also found to be altered in the blood of rodents after seizures. In the past 18 months, functional studies have identified nine novel miRNAs that appear to influence seizures or hippocampal pathology. Their targets include transcription factors, neurotransmitter signalling components, and modulators of neuroinflammation. New approaches to manipulate miRNAs have been tested, including injection of mimics (agomirs) to enhance brain levels of miRNAs. Altered miRNA expression has also been reported in other types of refractory epilepsy and our understanding of how miRNA levels are controlled has grown, with studies on DNA methylation indicating epigenetic regulation. Biofluids (blood) of patients with epilepsy have shown differences in quantity of circulating miRNAs, implying diagnostic biomarker potential. WHERE NEXT?: Recent functional studies need to be replicated to build a robust evidence base. The specific cell types in which miRNAs execute their functions and their primary targets have to be identified, to fully explain the phenotypic effects of modulating miRNAs. Delivery of large molecules such as antisense inhibitors or mimics to the brain poses a challenge, and the multi-targeting effects of miRNAs create additional risks of unanticipated side effects. Potential genetic variation in miRNAs should be explored as the basis for disease susceptibility. The latest findings provide a rich source of new miRNA targets, but substantial challenges remain before their role in the pathogenesis, diagnosis, and treatment of epilepsy can be translated into clinical practice.
EVALuna2:22485

Microscopic polyangiitis after alemtuzumab treatment in relapsing-remitting MS - Sauer, Eva-Maria; Schliep, Stefan; Manger, Bernhard; Lee, De-Hyung; Linker, Ralf (Neurology, Neuroimmunology and Neuroinflammation, 2018)
EVALuna2:35512

Mild prolonged hypothermia for large intracerebral hemorrhage - Staykov, Dimitre; Wagner, Irina; Volbers, Bastian; Dörfler, Arnd; Schwab, Stefan; Kollmar, Rainer (Neurocritical Care, 2013)
Background: Perihemorrhagic edema (PHE) develops after intracerebral hemorrhage (ICH). It can worsen the clinical situation by its additional mass effect. Therapeutic hypothermia (TH) might be an effective method to control PHE, but has not been sufficiently studied in ICH patients. Methods: We report data on n = 25 consecutive patients with large supratentorial ICH (volume > 25 ml) who were treated by mild TH of 35 C for 8-10 days. Body temperature was controlled by endovascular cooling catheters. We followed the clinical course during hospital stay and measured volumes of ICH and PHE in regularly performed serial cranial computed tomography. Outcome was assessed after 3 and 12 months. These data were compared to a historical group of n = 25 patients with large ICH. Results: While PHE continuously increased in the historical control group up to day 10, PHE volumes in the hypothermia group remained stable. There was a significant difference from day 3 after symptom onset. Shivering (36 %) and pneumonia (96 %) were the most frequent complications during TH. Mortality rate was 8.3 % in TH versus 16.7 % in the control group after 3 months and 28 versus 44 % after 1 year. Conclusions: These data support the promising results of our first case series on TH in large ICH. TH prevents the development of PHE and its complications. Side effects of TH appeared often, but could be treated sufficiently. Therefore, TH might represent a new therapy for PHE after large ICH, but has to be further tested in randomized trials. © 2012 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypothermia; Intracerebral hemorrhage; Perihemorrhagic edema

Mitochondria in Ischemic Stroke: New Insight and Implications - Liu, Fan; Lu, Jianfei; Manaenko, Anatol; Tang, Junjia; Hu, Qin (Aging and Disease, 2018)
Stroke is the leading cause of death and adult disability worldwide. Mitochondrial dysfunction has been regarded as one of the hallmarks of ischemia/reperfusion (I/R) induced neuronal death. Maintaining the function of mitochondria is crucial in promoting neuron survival and neurological improvement. In this article, we review current progress regarding the roles of mitochondria in the pathological process of cerebral I/R injury. In particular, we emphasize on the most critical mechanisms responsible for mitochondrial quality control, as well as the recent findings on mitochondrial transfer in acute stroke. We highlight the potential of mitochondria as therapeutic targets for stroke treatment and provide valuable insights for clinical strategies.
EVALuna2:213459

MODIFIED SUBPIAL - Roessler, K.; Kasper, Burkhard; Coras, R.; Sommer, B.; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael (2017)
EVALuna2:7378

Modulation of cytokine production by drugs with antiepileptic or mood stabilizer properties in anti-CD3- and anti-Cd40-stimulated blood in vitro - Himmerich, Hubertus; Bartsch, Stefanie; Hamer, Hajo; Mergl, Roland; Schönherr, Jeremias; Petersein, Charlotte; Munzer, Alexander; Kirkby, Kenneth Clifford; Bauer, Katrin; Sack, Ulrich (Oxidative Medicine and Cellular Longevity, 2014)
Increased cytokine production possibly due to oxidative stress has repeatedly been shown to play a pivotal role in the pathophysiology of epilepsy and bipolar disorder. Recent in vitro and animal studies of valproic acid (VPA) report antioxidative and anti-inflammatory properties, and suppression of interleukin (IL)-6 and tumor necrosis factor (TNF)-?. We tested the effect of drugs with antiepileptic or mood stabilizer properties, namely, primidone (PRM), carbamazepine (CBZ), levetiracetam (LEV), lamotrigine (LTG), VPA, oxcarbazepine (OXC), topiramate (TPM), phenobarbital (PB), and lithium on the production of the following cytokines in vitro: interleukin (IL)-1?, IL-2, IL-4, IL-6, IL-17, IL-22, and TNF-?. We performed a whole blood assay with stimulated blood of 14 healthy female subjects. Anti-human CD3 monoclonal antibody OKT3, combined with 5C3 antibody against CD40, was used as stimulant. We found a significant reduction of IL-1 and IL-2 levels with all tested drugs other than lithium in the CD3/5C3-stimulated blood; VPA led to a decrease in IL-1?, IL-2, IL-4, IL-6, IL-17, and TNF-? production, which substantiates and adds knowledge to current hypotheses on VPA's anti-inflammatory properties.
EVALuna2:22301

Monitoring of direct oral anticoagulants plasma levels for secondary stroke prevention - Siedler, Gabriela; Macha, Kosmas; Stoll, Svenja; Plechschmidt, Johannes; Wang, Ruihao; Gerner, Stefan; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Thrombosis and Haemostasis, 2022)
Background: Patients with atrial fibrillation have a relevant risk for ischemic stroke despite the recommended use of direct oral anticoagulants (DOAC). The risk correlates with the functional DOAC plasma levels in clinical trials, but the value of their measurement in community use remains undetermined. Objectives: We aim to investigate the clinical implications and the prognostic value of DOAC plasma level measurement during steady state. Methods: In this observational clinical cohort study among patients with ischemic stroke and atrial fibrillation, 397 individuals on oral anticoagulants for secondary stroke prevention were included between 2016 and 2020. The functional DOAC plasma levels were measured during steady state. Early stroke recurrence within 3 months was recorded as the main outcome parameter. Results: Three hundred ninety-seven patients (201 female, mean age 78 [±9] years, median CHA2DS2VASc-Score 6 [interquartile range 5–7]) were included. Mean DOAC plasma trough level was 95.9 (±66.9) ng/ml. A high glomerular filtration rate (GFR) was an independent predictor of lower levels in a multivariate model (R coefficient: −0.174, P =.014). During follow-up, 10 patients (3%) suffered from early ischemic stroke recurrence despite the use of DOAC, while 10 clinically relevant bleeding complications occurred (3%). Ischemic stroke recurrence was associated with numerical lower plasma levels for patients on apixaban and dabigatran after propensity score matching. Conclusions: Monitoring of DOAC plasma levels could help to identify patients with increased risk for stroke recurrence and should be considered for certain subgroups, including patients with high GFR.
CRIS-Team Scopus Importer:2022-03-18
Keywords: atrial fibrillation; cardioembolic stroke; direct oral anticoagulants; ischemic stroke; secondary prevention

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

Multicenter Validation of the max-ICH Score in Intracerebral Hemorrhage - Sembill, Jochen; Castello, Juan P.; Sprügel, Maximilian; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Biffi, Alessandro; Kuramatsu, Joji; Hölter, Philip (Annals of Neurology, 2020)
Objective: Outcome prognostication unbiased by early care limitations (ECL) is essential for guiding treatment in patients presenting with intracerebral hemorrhage (ICH). The aim of this study was to determine whether the max-ICH (maximally treated ICH) Score provides improved and clinically useful prognostic estimation of functional long-term outcomes after ICH. Methods: This multicenter validation study compared the prognostication of the max-ICH Score versus the ICH Score regarding diagnostic accuracy (discrimination and calibration) and clinical utility using decision curve analysis. We performed a joint investigation of individual participant data of consecutive spontaneous ICH patients (n = 4,677) from 2 retrospective German-wide studies (RETRACE I + II; anticoagulation-associated ICH only) conducted at 22 participating centers, one German prospective single-center study (UKER-ICH; nonanticoagulation-associated ICH only), and 1 US-based prospective longitudinal single-center study (MGH; both anticoagulation- and nonanticoagulation-associated ICH), treated between January 2006 and December 2015. Results: Of 4,677 included ICH patients, 1,017 (21.7%) were affected by ECL (German cohort: 15.6% [440 of 2,377]; MGH: 31.0% [577 of 1,283]). Validation of long-term functional outcome prognostication by the max-ICH Score provided good and superior discrimination in patients without ECL compared with the ICH Score (area under the receiver operating curve [AUROC], German cohort: 0.81 [0.78–0.83] vs 0.74 [0.72–0.77], p < 0.01; MGH: 0.85 [0.81–0.89] vs 0.78 [0.74–0.82], p < 0.01), and for the entire cohort (AUROC, German cohort: 0.84 [0.82–0.86] vs 0.80 [0.77–0.82], p < 0.01; MGH: 0.83 [0.81–0.85] vs 0.77 [0.75–0.79], p < 0.01). Both scores showed no evidence of poor calibration. The clinical utility investigated by decision curve analysis showed, at high threshold probabilities (0.8, aiming to avoid false-positive poor outcome attribution), that the max-ICH Score provided a clinical net benefit compared with the ICH Score (14.1 vs 2.1 net predicted poor outcomes per 100 patients). Interpretation: The max-ICH Score provides valid and improved prognostication of functional outcome after ICH. The associated clinical net benefit in minimizing false poor outcome attribution might potentially prevent unwarranted care limitations in patients with ICH. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-12-25

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Multiple Sclerosis relapses are not associated with exercise - Tallner, Alexander; Waschbisch, Anne; Wenny, Ingrid; Schwab, Stefan; Hentschke, Christian; Pfeifer, Klaus; Mäurer, Mathias (Multiple Sclerosis Journal, 2012)

Multisensory deficit of hedonic perception in Parkinson's Disease - Martini, Max; Utz, Katrin; Mrochen, Anne; Klucken, Jochen; Renner, Bertold; Winkler, Jürgen; Marxreiter, Franz (2019)
EVALuna2:213355

Music induces different cardiac autonomic arousal effects in young and older persons - Hilz, Max-Josef; Stadler, Peter; Gryc, Thomas; Nath, Juliane; Habib-Romstoeck, Leila; Stemper, Brigitte; Buechner, Susanne; Wong, Samuel; Koehn, Julia (Autonomic Neuroscience-Basic & Clinical, 2014)
Autonomic arousal-responses to emotional stimuli change with age. Age-dependent autonomic responses to music-onset are undetermined.To determine whether cardiovascular-autonomic responses to "relaxing" or "aggressive" music differ between young and older healthy listeners.In ten young (22.8±1.7 years) and 10 older volunteers (61.7±7.7 years), we monitored respiration (RESP), RR-intervals (RRI), and systolic and diastolic blood pressure (BPsys, BPdia) during silence and 180second presentations of two "relaxing" and two "aggressive" classical-music excerpts. Between both groups, we compared RESP, RRI, BPs, spectral-powers of mainly sympathetic low-frequency (LF: 0.04-0.15Hz) and parasympathetic high-frequency (HF: 0.15-0.5Hz) RRI-oscillations, RRI-LF/HF-ratios, RRI-total-powers (TP-RRI), and BP-LF-powers during 30s of silence, 30s of music-onset, and the remaining 150s of music presentation (analysis-of-variance and post-hoc analysis; significance: p<0.05).During silence, both groups had similar RRI, LF/HF-ratios and LF-BPs; RESP, LF-RRI, HF-RRI, and TP-RRI were lower, but BPs were higher in older than younger participants. During music-onset, "relaxing" music decreased RRI in older and increased BPsys in younger participants, while "aggressive" music decreased RRI and increased BPsys, LF-RRI, LF/HF-ratios, and TP-RRI in older, but increased BPsys and RESP and decreased HF-RRI and TP-RRI in younger participants. Signals did not differ between groups during the last 150s of music presentation.During silence, autonomic modulation was lower - but showed sympathetic predominance - in older than younger persons. Responses to music-onset, particularly "aggressive" music, reflect more of an arousal- than an emotional-response to music valence, with age-specific shifts of sympathetic-parasympathetic balance mediated by parasympathetic withdrawal in younger and by sympathetic activation in older participants.
EVALuna2:22324

Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons - Koehn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2020)
Introduction: Noninvasive temperature modulation by localized neck cooling might be desirable in the prehospital phase of acute hypoxic brain injuries. While combined head and neck cooling induces significant discomfort, peripheral vasoconstriction, and blood pressure increase, localized neck cooling more selectively targets blood vessels that supply the brain, spares thermal receptors of the face and skull, and might therefore cause less discomfort cardiovascular side effects compared to head- and neck cooling. The purpose of this study is to assess the effects of noninvasive selective neck cooling on cardiovascular parameters and cerebral blood flow velocity (CBFV). Methods: Eleven healthy persons (6 women, mean age 42 ± 11 years) underwent 90 min of localized dorsal and frontal neck cooling (EMCOOLS Brain.Pad™) without sedation. Before and after cooling onset, and after every 10 min of cooling, we determined rectal, tympanic, and neck skin temperatures. Before and after cooling onset, after 60- and 90-min cooling, we monitored RR intervals (RRI), systolic, diastolic blood pressures (BPsys, BPdia), laser Doppler skin blood flow (SBF) at the index finger pulp, and CBFV at the proximal middle cerebral artery (MCA). We compared values before and during cooling by analysis of variance for repeated measurements with post hoc analysis (significance: p < 0.05). Results: Neck skin temperature dropped significantly by 9.2 ± 4.5 °C (minimum after 40 min), while tympanic temperature decreased by only 0.8 ± 0.4 °C (minimum after 50 min), and rectal temperature by only 0.2 ± 0.3 °C (minimum after 60 min of cooling). Index finger SBF decreased (by 83.4 ± 126.0 PU), BPsys and BPdia increased (by 11.2 ± 13.1 mmHg and 8.0 ± 10.1 mmHg), and heart rate slowed significantly while MCA-CBFV remained unchanged during cooling. Conclusions: While localized neck cooling prominently lowered neck skin temperature, it had little effect on tympanic temperature but significantly increased BP which may have detrimental effects in patients with acute brain injuries.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Blood pressure increase; Cerebral blood flow velocity; Hypothermia; Neck cooling

Neprilysin is a Mediator of Alternative Renin-Angiotensin-System Activation in the Murine and Human Kidney - Domenig, Oliver; Manzel, Arndt; Grobe, Nadja; Koenigshausen, Eva; Kaltenecker, Christopher C.; Kovarik, Johannes J.; Stegbauer, Johannes; Gurley, Susan B.; Van Oyen, Dunja; Antlanger, Marlies; Bader, Michael; Motta-Santos, Daisy; et al. (Scientific Reports, 2016)
Cardiovascular and renal pathologies are frequently associated with an activated renin-angiotensin-system (RAS) and increased levels of its main effector and vasoconstrictor hormone angiotensin II (Ang II). Angiotensin-converting-enzyme-2 (ACE2) has been described as a crucial enzymatic player in shifting the RAS towards its so-called alternative vasodilative and reno-protective axis by enzymatically converting Ang II to angiotensin-(1-7) (Ang-(1-7)). Yet, the relative contribution of ACE2 to Ang-(1-7) formation in vivo has not been elucidated. Mass spectrometry based quantification of angiotensin metabolites in the kidney and plasma of ACE2 KO mice surprisingly revealed an increase in Ang-(1-7), suggesting additional pathways to be responsible for alternative RAS activation in vivo. Following assessment of angiotensin metabolism in kidney homogenates, we identified neprilysin (NEP) to be a major source of renal Ang-(1-7) in mice and humans. These findings were supported by MALDI imaging, showing NEP mediated Ang-(1-7) formation in whole kidney cryo-sections in mice. Finally, pharmacologic inhibition of NEP resulted in strongly decreased Ang-(1-7) levels in murine kidneys. This unexpected new role of NEP may have implications for the combination therapy with NEP-inhibitors and angiotensin-receptor-blockade, which has been shown being a promising therapeutic approach for heart failure therapy.
EVALuna2:22474

Neue Klassifikation epileptischer Anfälle: Eine kritische Bewertung der Änderungen - Schulze-Bonhage, Andreas; Hamer, Hajo; Krämer, Günter (Der Nervenarzt, 2019)
In the new classification of epileptic seizures by the International League Against Epilepsy (ILAE), a multitude of changes are recommended particularly for seizures of focal origin. In addition to aspects of the nomenclature, this involves the introduction of different levels of classification with respect to the state of consciousness and the evolution to a bilateral tonic-clonic seizure, the inclusion of the first semiological seizure element in the classification and a new operationalization of the state of consciousness. This leads partly to specification in the description but in some areas also to counterintuitive changes in the classification. The advantages and disadvantages of this reorganization for the clinical practice are critically discussed with reference to the most important modifications.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Bilateral tonic-clonic seizure; Consciousness; Focal origin; Generalized origin; Semiology

Neural and endothelial control of the microcirculation in diabetic peripheral neuropathy - Kilo, Sonja; Berghoff, Martin; Hilz, Max-Josef; Freeman, Roy L. (Neurology, 2000)
Objective: To examine the role played by endothelium-dependent and endothelium-independent vasodilation of the cutaneous microcirculation and their relationship to neural microcirculatory control in type 1 and type 2 diabetic patients. Methods: Acetylcholine and sodium nitroprusside were iontophoresed using a dose-response technique. Endothelium-dependent, endothelium-independent, and C-fiber-mediated vasodilation were measured with a laser Doppler device. Results: Endothelium-dependent vasodilation of the forearm cutaneous microcirculation was attenuated in diabetic subjects. The response was less in type 2 diabetic subjects than in controls (p < 0.005). In contrast, there was no significant difference between type 1 diabetic subjects and controls. There was no significant abnormality in endothelium-independent vasodilation in either diabetic group. The C-fiber-mediated axon reflex in the forearm was impaired in both type 1 and type 2 diabetics, which is consistent with a small-fiber neuropathy (p < 0.005). The duration of diabetes in type 2 diabetics was a significant predictor of the maximum endothelium-mediated vasodilation. Conclusion: Changes in cutaneous blood flow are seen relatively early in the course of diabetic peripheral neuropathy and are characterized by endothelial and neural but not smooth muscle dysfunction. The presence of significant C-fiber impairment in both diabetic groups, together with significantly greater dysfunction in endothelium-dependent vasodilation in type 2 diabetics, suggests that the endothelial function and nitric oxide may play a greater role in the pathogenesis of diabetic peripheral neuropathy in type 2 diabetic patients.
Keywords: diabetic neuropathy; nitric oxide; endothelium; axon reflex

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic Correlates of Angioedema in stroke patients with thrombolysis - Winder, K.; Kallmünzer, Bernd; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, F.; Fröhlich, Kilian (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Neuroanatomic Correlates of Female Sexual Dysfunction in Multiple Sclerosis - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Annals of Neurology, 2016)
This study intended to determine associations between alterations of female sexual arousal as well as vaginal lubrication and the site of cerebral multiple sclerosis (MS) lesions.In 44 women with MS (mean age: 36.5 ± 9.9 years), we assessed their medical history and evaluated sexual function using the Female Sexual Function Index scores for arousal and vaginal lubrication. We determined potential confounding factors of sexual dysfunction: age; disease duration; physical disability; depression; bladder or urinary dysfunction; and total volume of cerebral lesions. Arousal and lubrication scores were correlated with one another and with potential confounding factors. Cerebral MS lesions were recorded on imaging scans. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating cerebral sites of MS lesions with arousal and lubrication scores.Decreased arousal scores correlated with decreased lubrication scores; decreased lubrication scores were associated with bladder or urinary symptoms. Arousal and lubrication scores were not associated with any other variables. Multivariate VLSM analysis, including arousal and lubrication scores as covariables of interest, showed right occipital lesions associated with impaired arousal and left insular lesions associated with decreased lubrication. Impaired lubrication remained associated with left insular lesions after adjustment for bladder or urinary dysfunction.Our data indicate that impaired female sexual arousal is associated with MS lesions in the occipital region, integrating visual information and modulating attention toward visual input. Impaired lubrication correlated with lesions in the left insular region, contributing to mapping and generating visceral arousal states. Ann Neurol 2016;80:490-498.
EVALuna2:22501

Neuroanatomic correlates of poststroke hyperglycemia - Winder, Klemens; Seifert, Frank; Ohnemus, Tessa; Sauer, Eva-Maria; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Annals of Neurology, 2015)
A study was undertaken to determine associations between ischemic stroke sites and poststroke hyperglycemia (PSH).Nondiabetic patients with first ever ischemic stroke confirmed by imaging were prospectively included. Blood glucose level (BGL), National Institute of Health Stroke Scale (NIHSS) score, and clinical parameters were assessed on admission. BGL was dichotomized for elevated versus normal levels using a cutoff value of >7.0 mmol/l. Clinical parameters were correlated with BGL and were compared between patient groups with elevated versus normal glucose values. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating sites of ischemic lesions with PSH.Of 1,281 stroke patients screened, 229 (mean age = 66.3 ± 15.9 years) met the inclusion criteria. Patients with elevated BGL were older, had higher NIHSS scores, and had larger infarcts compared to those without elevated glucose levels. Spearman rank analysis showed correlations between BGL and age, infarct size, heart rate (HR), and NIHSS scores (p <= 0.05). The VLSM analysis adjusted for these confounding factors demonstrated associations between PSH and damaged voxels in right hemispheric insular and opercular areas.The data indicate that damage in the right insulo-opercular areas contributes to PSH. The association between sympathetically mediated increase of HR and BGL suggests disinhibition of sympathetic outflow as a possible mechanism for PSH.
EVALuna2:22352

Neurocritical care in Germany: need for guidance - Huttner, Hagen; Schwab, Stefan (Neurocritical Care, 2014)
EVALuna2:22285

Neuroendocrine changes in patients with spontaneous supratentorial intracerebral hemorrhage - Huttner, Hagen; Kiphuth, Ines-Christine; Teuber, Linda; Lücking, Hannes; Kloska, Stephan; Staykov, Dimitre; Kuramatsu, Joji; Mauer, Christoph; Breuer, Lorenz; Dörfler, Arnd; Köhrmann, Martin (Neurocritical Care, 2013)
Background: Neuroendocrine changes have been reported after ischemic stroke, subarachnoid hemorrhage, and brain trauma. As there are no corresponding data in patients with intracerebral hemorrhage (ICH) we analyzed various neuroendocrine parameters to investigate possible alterations in hormone profiles of patients with ICH. Methods: Twenty patients with ICH were prospectively enrolled in the study. Patients were a priori parted into two groups: Ten non-ventilated patients treated on the stroke-unit (hemorrhage volumes <20 ml, "small ICH"), and 10 ventilated patients treated on the neurocritical care unit (hematoma volumes >20 ml with possible additional ventricular involvement ("large ICH"). Neuroendocrine parameters were compared between both groups referring to reference values. The following parameters were obtained over a period of 9 days in 20 patients with spontaneous supratentorial ICH: thyrotropin, free thiiodothyronine and thyroxine, human growth hormone, insulin-like growth factor 1, luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, adrenocorticotropic hormone, and cortisol. Results: Small ICH patients were in a median 71 (54-88) years old and had a mean ICH volume of 9.5 ± 6.5 ml, whereas large ICH patients were 65 (47-80) years old and showed a mean volume of 56 ± 30.2 ml. None of the patients revealed pathological alterations for thyrotropin, free thiiodothyronine, thyroxine, human growth hormone, insulin-like growth factor 1, and testosterone. There was only a mild decrease of adrenocorticotropic hormone and cortisol on day 3 in large ICH patients. Small ICH patients showed pathologically elevated levels of luteinizing and follicle-stimulating hormone throughout the observation period. Large ICH patients showed a marked increase of prolactin that developed during the course. Conclusions: Overall, neuroendocrine changes in ICH patients are not as profound as reported for ischemic stroke or subarachnoid hemorrhage. The clinical significance of increased LH and FSH levels in small ICH is unclear, whereas elevation of prolactin in large ICH was anticipated. Future randomized controlled trials should also focus on neuroendocrine parameters to clarify the impact of possible hormonal alterations on functional outcome. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hormone profile; Intracerebral hemorrhage; Neuroendocrine

Neurointensive care medicine-from where, where to? - Stummer, W.; Schwab, Stefan; Fink, G. R. (Der Nervenarzt, 2018)
EVALuna2:201956

Neuromodulation of Electrically Induced Hyperalgesia in the Trigeminocervical System - Reindl, Caroline; Seifert, Frank; Nickel, Franziska; Maihoefner, Christian (Pain Practice, 2016)
Trigeminal and cervical afferents converge on neurons of the trigeminocervical complex and may significantly alter the function of these neurons. This interaction may have implications for the pathophysiology and treatment of primary headache disorders. Therefore, the aim of this work was to study pain modulatory mechanisms within the trigeminocervical complex.We used an electrical pain model challenging pro- and antinociceptive systems in 19 healthy volunteers.Transcutaneous supraorbital noxious electrical low-frequency stimulation (0.5 Hz), known to induce both hyperalgesia due to central sensitization (as a marker of pain facilitation) and habituation (as a marker of pain inhibition), was combined with different noxious stimulation paradigms applied to the innervation territory of upper cervical afferents. We investigated the effects of concurrent stimulation in the cervical/extratrigeminal system on habituation profiles, hyperalgesic area, pain, and detection thresholds in the trigeminal system.It was previously shown that conditioning 20-Hz noxious electrical stimuli may provoke centrally mediated sensory decline that possesses heterotopic antihyperalgesic properties. Occipital and forearm costimulation at a frequency of 20 Hz had no significant modulating effect on supraorbital pain adaptation, hyperalgesic area, or pain perception. Effects for trigeminal stimulation were independent of occipital stimulus intensity. Furthermore, for single occipital stimulation at 0.5 and 20 Hz, no somatosensory changes could be demonstrated within the trigeminal system.Trigeminal nociception stayed unchanged despite of occipital costimulation.
EVALuna2:22473

Neuromyelitis optica presenting with relapses under treatment with natalizumab: a case report - Lee, De Hyung; Laemmer, Alexandra B.; Waschbisch, Anne; Struffert, Tobias; Maihöfner, Christian; Schwab, Stefan; Linker, Ralf (Journal of Medical Case Reports, 2014)
Neuromyelitis optica is an inflammatory demyelinating disease of the central nervous system. To date, optimal therapeutic approaches for neuromyelitis optica have yet to be defined. Natalizumab is highly effective in relapsing-remitting multiple sclerosis and might be considered as an option.Here, we describe a 67-year-old Caucasian man with definite neuromyelitis optica with detection of anti-aquaporin-4 antibodies over the course of the disease. After initially discussing the diagnosis of multiple sclerosis at an outside hospital, our patient received interferon beta 1a as well as repeated corticosteroid pulses without success. Under subsequent therapy with natalizumab, he continued to present relapses. It was not until discontinuation of natalizumab, repeated cycles of plasma exchanges and initiation of therapy with rituxan that the disease course started to stabilize. Although B cells were completely depleted, our patient experienced another severe myelitis relapse during further follow-up and an additional immunosuppressive therapy with cyclophosphamide was started. Under this regimen, no further relapses occurred over the next 24 months.This case adds further evidence to the previously discussed notion that natalizumab, while highly effective in multiple sclerosis, may not work sufficiently in neuromyelitis optica. It further advocates for repetitive testing of anti-aquaporin-4 antibodies before and after treatment initiation.
EVALuna2:22348

Neuropathologie und Ätiologie fokaler Epilepsien - Blümcke, Ingmar; Hamer, Hajo (Der Nervenarzt, 2012)
In 2010 the International League against Epilepsy published a new classification of epilepsies. A major advance of this classification system is the acknowledgment of a genetic or pathologic-anatomic basis of epilepsy as important predictors of outcome (cause matters). This applies in particular to structural-metabolic lesions, which were frequently recognized in surgical specimens obtained from patients with drug-resistant focal epilepsy, i.e. hippocampal sclerosis, glioneuronal tumors, focal cortical dysplasias, vascular malformations, ischemia, intracerebral hemorrhage, glial scars or inflammation. A better understanding and classification of the etiopathology as well as the underlying molecular mechanisms will help to anticipate and appreciate the clinical course of a disease as well as to develop new and targeted drug treatment. Surgically available human brain tissue will be most helpful to support this approach but will also need careful neuropathological evaluation with accurate classification systems and use of terminology. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumors; Dysplasia; Hippocampal sclerosis; Seizure

Neutrophil-to-lymphocyte ratio as an independent predictor for unfavorable functional outcome in aneurysmal subarachnoid hemorrhage - Giede-Jeppe, Antje; Reichl, Jonathan; Sprügel, Maximilian; Lücking, Hannes; Hölter, Philip; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Huttner, Hagen; Gerner, Stefan (Journal of Neurosurgery, 2019)
OBJECTIVEStroke-associated immunosuppression and inflammation are increasingly recognized as factors triggering infections and thus potentially influencing outcome after stroke. Several studies have demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes for patients with ischemic stroke or intracerebral hemorrhage. Thus far, in patients with subarachnoid hemorrhage the association between NLR and outcome is insufficiently established. The authors sought to investigate the association between NLR on admission and functional outcome in aneurysmal subarachnoid hemorrhage (aSAH).METHODSThis observational study included all consecutive aSAH patients admitted to a German tertiary center over a 5-year period (2008-2012). Data regarding patient demographics and clinical, laboratory, and in-hospital measures, as well as neuroradiological data, were retrieved from institutional databases. Functional outcome was assessed at 3 and 12 months using the modified Rankin Scale (mRS) score and categorized into favorable (mRS score 0-2) and unfavorable (mRS score 3-6). Patients' radiological and laboratory characteristics were compared between aSAH patients with favorable and those with unfavorable outcome at 3 months. In addition, multivariate analysis was conducted to investigate parameters independently associated with favorable outcome. Receiver operating characteristic (ROC) curve analysis was undertaken to identify the best cutoff for NLR to discriminate between favorable and unfavorable outcome in these patients. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on outcome measures.RESULTSOverall, 319 patients with aSAH were included. Patients with unfavorable outcome at 3 months were older, had worse clinical status on admission (Glasgow Coma Scale score and Hunt and Hess grade), greater amount of subarachnoidal and intraventricular hemorrhage (modified Fisher Scale grade and Graeb score), and higher rates of infectious complications (pneumonia and sepsis). A significantly higher NLR on admission was observed in patients with unfavorable outcome according to mRS score (median [IQR] NLR 5.8 [3.0-10.0] for mRS score 0-2 vs NLR 8.3 [4.5-12.6] for mRS score 3-6; p < 0.001). After adjustments, NLR on admission remained a significant predictor for unfavorable outcome in SAH patients (OR [95% CI] 1.014 [1.001-1.027]; p = 0.028). In ROC analysis, an NLR of 7.05 was identified as the best cutoff value to discriminate between favorable and unfavorable outcome (area under the curve = 0.614, p < 0.001, Youden's index = 0.211; mRS score 3-6: 94/153 [61.4%] for NLR ≥ 7.05 vs 67/166 [40.4%] for NLR < 7.05; p < 0.001). Subanalysis of patients with NLR levels ≥ 7.05 vs < 7.05, performed using 2 propensity score-matched cohorts (n = 133 patients in each group), revealed an increased proportion of patients with unfavorable functional outcome at 3 months in patients with NLR ≥ 7.05 (mRS score 3-6 at 3 months: NLR ≥ 7.05 82/133 [61.7%] vs NLR < 7.05 62/133 [46.6%]; p = 0.014), yet without differences in mortality at 3 months (NLR ≥ 7.05 37/133 [27.8%] vs NLR < 7.05 27/133 [20.3%]; p = 0.131).CONCLUSIONSAmong aSAH patients, NLR represents an independent parameter associated with unfavorable functional outcome. Whether the impact of NLR on functional outcome is related to preexisting comorbidities or represents independent causal relationships in the context of stroke-associated immunosuppression should be investigated in future studies.
EVALuna2:204508

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor for In-Hospital Mortality in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Beuscher, Vanessa D.; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2017)
Stroke-associated immunosuppression and inflammation are increasingly recognized as factors that trigger infections and thus, potentially influence the outcome after stroke. Several studies demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes in patients with ischemic stroke. However, little is known about the impact of NLR on short-term mortality in intracerebral hemorrhage (ICH).This observational study included 855 consecutive ICH-patients. Patient demographics, clinical, laboratory, and in-hospital measures as well as neuroradiological data were retrieved from institutional databases. Functional 3-months-outcome was assessed and categorized as favorable (modified Rankin Scale [mRS] 0-3) and unfavorable (mRS 4-6). We (i) studied the natural course of NLR in ICH, (ii) analyzed parameters associated with NLR on admission (NLROA), and (iii) evaluated the clinical impact of NLR on mortality and functional outcome.The median NLROA of the entire cohort was 4.66 and it remained stable during the entire hospital stay. Patients with NLR >=4.66 showed significant associations with poorer neurological status (National Institute of Health Stroke Scale [NIHSS] 18 [9-32] vs. 10 [4-21]; p < 0.001), larger hematoma volume on admission (17.6 [6.9-47.7] vs. 10.6 [3.8-31.7] mL; p = 0.001), and more frequently unfavorable outcome (mRS 4-6 at 3 months: 317/427 [74.2%] vs. 275/428 [64.3%]; p = 0.002). Patients with an NLR under the 25th percentile (NLR <2.606) - compared to patients with NLR >2.606 - presented with a better clinical status (NIHSS 12 [5-21] vs. 15 [6-28]; p = 0.005), lower hematoma volumes on admission (10.6 [3.6-30.1] vs. 15.1 [5.7-42.3] mL; p = 0.004) and showed a better functional outcome (3 months mRS 0-3: 82/214 [38.3%] vs. 185/641 [28.9%]; p = 0.009). Patients associated with high NLR (>=8.508 = above 75th-percentile) showed the worst neurological status on admission (NIHSS 21 [12-32] vs. 12 [5-23]; p < 0.001), larger hematoma volumes (21.0 [8.6-48.8] vs. 12.2 [4.1-34.9] mL; p < 0.001), and higher proportions of unfavorable functional outcome at 3 months (mRS 4-6: 173/214 vs. 418/641; p < 0.001). Further, NLR was linked to more frequently occurring infectious complications (pneumonia 107/214 vs. 240/641; p = 0.001, sepsis: 78/214 vs. 116/641; p < 0.001), and increased c-reactive-protein levels on admission (p < 0.001; R2 = 0.064). Adjusting for the above-mentioned baseline confounders, multivariable logistic analyses revealed independent associations of NLROA with in-hospital mortality (OR 0.967, 95% CI 0.939-0.997; p = 0.029).NLR represents an independent parameter associated with increased mortality in ICH patients. Stroke physicians should focus intensely on patients with increased NLR, as these patients appear to represent a population at risk for infectious complications and increased short-mortality. Whether these patients with elevated NLR may benefit from a close monitoring and specially designed therapies should be investigated in future studies.
EVALuna2:22531

Neutrophil-to-lymphocyte ratio is associated with increased cerebral blood flow velocity in acute bacterial meningitis - Giede-Jeppe, Antje; Atay, Selim; Koehn, Julia; Mrochen, Anne; Lücking, Hannes; Hölter, Philip; Volbers, Bastian; Huttner, Hagen B.; Hueske, Lena; Bobinger, Tobias (Scientific Reports, 2021)
In community-acquired bacterial meningitis (CABM) intracranial vascular alterations are devastating complications which are triggered by neuroinflammation and result in worse clinical outcome. The Neutrophil-to-Lymphocyte ratio (NLR) represents a reliable parameter of the inflammatory response. In this study we analyzed the association between NLR and elevated cerebral blood flow velocity (CBFv) in CABM-patients. This study included all (CABM)-patients admitted to a German tertiary center between 2006 and 2016. Patients’ demographics, in-hospital measures, neuroradiological data and clinical outcome were retrieved from institutional databases. CBFv was assessed by transcranial doppler (TCD). Patients’, radiological and laboratory characteristics were compared between patients with/without elevated CBFv. Multivariate-analysis investigated parameters independently associated with elevated CBFv. Receiver operating characteristic(ROC-)curve analysis was undertaken to identify the best cut-off for NLR to discriminate between increased CBFv. 108 patients with CABM were identified. 27.8% (30/108) showed elevated CBFv. Patients with elevated CBFv and normal CBFv, respectively had a worse clinical status on admission (Glasgow Coma Scale: 12 [9–14] vs. 14 [11–15]; p = 0.005) and required more often intensive care (30/30 [100.0%] vs. 63/78 [80.8%]; p = 0.01).The causative pathogen was S. pneumoniae in 70%. Patients with elevated CBFv developed more often cerebrovascular complications with delayed cerebral ischemia (DCI) within hospital stay (p = 0.031). A significantly higher admission-NLR was observed in patients with elevated CBFv (median [IQR]: elevated CBFv:24.0 [20.4–30.2] vs. normal CBFv:13.5 [8.4–19.5]; p < 0.001). Multivariate analysis, revealed NLR to be significantly associated with increased CBFv (Odds ratio [95%CI] 1.042 [1.003–1.084]; p = 0.036). ROC-analysis identified a NLR of 20.9 as best cut-off value to discriminate between elevated CBFv (AUC = 0.713, p < 0.0001, Youden's Index = 0.441;elevated CBFv: NLR ≥ 20.9 19/30[63.5%] vs. normal CBFv: NLR > 20.9 15/78[19.2%]; p < 0.001). Intracranial vascular complications are common among CABM-patients and are a risk factor for unfavorable outcome at discharge. Elevated NLR is independently associated with high CBFv and may be useful in predicting patients’ prognosis.
CRIS-Team Scopus Importer:2021-06-18

New aspects in the field of epilepsy - Rosenow, F.; Klein, K. M.; Strzelczyk, A.; Hamer, Hajo; Menzler, K.; Bauer, S.; Knake, S. (Der Nervenarzt, 2014)
Regarding epilepsy several new developments can be reported. The International League Against Epilepsy (ILAE) has suggested a new definition of epilepsy, for the first time including a definition of epilepsy resolution. Progress in the diagnosis relates to new genetic findings, improvements in magnetic resonance imaging (MRI) and the increasing use of stereo electroencephalograms (sEEG). Regarding treatment there are new clinically relevant data on the pathophysiology and prevention of sudden unexpected death in epilepsy (SUDEP). Zonisamide has been approved by the European Medicines Agency (EMA) for monotherapy in adults with focal seizures and combination therapy in children aged >= 6 years. Retigabin and perampanel have been approved but are currently taken off the market in Germany (only) because the Gemeinsamer Bundesausschuss (GBA, Joint Federal Committee) did not find any additional therapeutic value as compared to lamotrigine due to a lack of data. A decision regarding a new application for perampanel is pending. Regarding surgical treatment novel ablation techniques (e.g. stereotactic radiofrequency and laser ablation as well as focussed ultrasound ablation) and brain stimulation paradigms are under investigation. Experimental studies, generously supported by the European Union (EU) and the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) are focusing on (opto-)genetic (e.g. using lentoviral transfection), epigenetic (e.g. micro-RNA-related) approaches and on the investigation of neuronal micronetworks.
EVALuna2:22382

New role for the (pro)renin receptor in T-cell development - Geisberger, Sabrina; Maschke, Ulrike; Gebhardt, Matthias; Kleinewietfeld, Markus; Manzel, Arndt; Linker, Ralf; Chidgey, Ann; Dechend, Ralf; Nguyen, Genevieve; Daumke, Oliver; Muller, Dominik N.; Wright, Mark D.; et al. (Blood, 2015)
The (pro)renin receptor (PRR) was originally thought to be important for regulating blood pressure via the renin-angiotensin system. However, it is now emerging that PRR has instead a generic role in cellular development. Here, we have specifically deleted PRR from T cells. T-cell-specific PRR-knockout mice had a significant decrease in thymic cellularity, corresponding with a 100-fold decrease in the number of CD4(+) and CD8(+) thymocytes, and a large increase in double-negative (DN) precursors. Gene expression analysis on sorted DN3 thymocytes indicated that PRR-deficient thymocytes have perturbations in key cellular pathways essential at the DN3 stage, including transcription and translation. Further characterization of DN T-cell progenitors leads us to propose that PRR deletion affects thymocyte survival and development at multiple stages; from DN3 through to DN4, double-positive, and single-positive CD4 and CD8. Our study thus identifies a new role for PRR in T-cell development.
EVALuna2:22337

Nimodipine fosters remyelination in a mouse model of multiple sclerosis and induces microglia-specific apoptosis - Schampel, Andrea; Volovitch, Oleg; Koeniger, Tobias; Scholz, Claus-Juergen; Joerge, Stefanie; Linker, Ralf; Wischmeyer, Erhard; Wunsch, Marie; Hell, Johannes W.; Erguen, Sueleyman; Kuerten, Stefanie (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Despite continuous interest in multiple sclerosis (MS) research, there is still a lack of neuroprotective strategies, because the main focus has remained on modulating the immune response. Here we performed in-depth analysis of neurodegeneration in experimental autoimmune encephalomyelitis (EAE) and in in vitro studies regarding the effect of the well-established L-type calcium channel antagonist nimodipine. Nimodipine treatment attenuated clinical EAE and spinal cord degeneration and promoted remyelination. Surprisingly, we observed calcium channel-independent effects on microglia, resulting in apoptosis. These effects were cell-type specific and irrespective of microglia polarization. Apoptosis was accompanied by decreased levels of nitric oxide (NO) and inducible NO synthase (iNOS) in cell culture as well as decreased iNOS and reactive oxygen species levels in EAE. In addition, increased numbers of Olig2(+)APC(+) oligodendrocytes were detected. Overall, nimodipine application seems to generate a favorable environment for regenerative processes and therefore could be a treatment option for MS, because it combines features of immunomodulation with beneficial effects on neuroregeneration.
EVALuna2:22492

No evidence of disease activity status over 3 years in a real-world cohort of relapsing remitting MS patients in Germany - Huhn, Konstantin; Senger, Daniela; Utz, Kathrin S.; Schmidt, Manuel; Fröhlich, Katharina; Waschbisch, Anne; Seifert, Frank; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf A. (Multiple Sclerosis and Related Disorders, 2019)
BACKGROUND: Over the last decade, therapy of relapsing remitting multiple sclerosis (RRMS) has evolved with the approval of several new treatment concepts. Thus, treatment goals have become more ambitious aiming at "no evidence of disease activity" (NEDA). As NEDA-3, this concept comprises freedom of clinical disease progression and relapses as well as inflammatory MRI activity. So far, data on NEDA status mainly stem from post-hoc analyses of drug approval studies. Yet, less is known about the significance of NEDA in "real-world" clinical settings. Hence, our study aims at investigation of NEDA in a heterogeneous cohort of relapsing MS patients. METHODS: This is a retrospective single-center study at the Department of Neurology of the University Hospital Erlangen, Germany, including data of 306 patients with relapsing forms of MS (RMS) or clinical isolated syndrome (CIS) from 2009 to 2016. Inclusion required sufficient clinical information and in house cranial MRI follow-up data sets at baseline and at follow-up after one year with a potential extension to two and three year follow-up, if possible. NEDA-3 status, its correlation to clinical features, associated medication and NEDA failure (EDA) were analyzed. RESULTS: In a cohort of RMS patients at the early stages of the disease (median EDSS 1.5, mean disease duration 30 months) at baseline, 45% retained NEDA-3 status after one year. This percentage decreased in year two (29%) and three (21%) of follow-up. MRI criteria were responsible for loss of NEDA status in 64% of cases and CIS patients were more likely to sustain NEDA status. Therapy with monoclonal antibodies appeared superior in sustaining NEDA status as compared to injectables or oral treatment options. DISCUSSION: In our real-world analysis, we confirm the potential of NEDA for the evaluation and surveillance of MS disease activity, progression and therapy efficacy. Despite highly efficient immunomodulatory treatment, NEDA-3 was only preserved in a minority of patients. Monoclonal antibodies may yield best NEDA rates. Further studies are warranted to evaluate the value of the NEDA concept in real-world settings beyond standardized clinical studies.
EVALuna2:36277

Nonadherence to antiepileptic drugs in Germany: A retrospective, population-based study - Gollwitzer, Stephanie; Kostev, Karel; Hagge, Mareike; Lang, Johannes; Graf, Wolfgang; Hamer, Hajo (Neurology, 2016)
To assess the effect of patient and drug characteristics on medication adherence in people with epilepsy (PWE) in a large cohort representative of the German population.Information was obtained from the Disease Analyzer database that collects anonymous demographic and medical data from practice computer systems throughout Germany. From 2010 to 2013, adult PWE were retrospectively analyzed regarding demographic characteristics, comorbidities, and treatment with antiepileptic drugs (AED). Adherence was measured using the medication possession ratio (MPR). Individuals with an MPR <80% were classified as nonadherent. Multivariate regression models were applied to assess the association of different factors with adherence by calculating adjusted odds ratios (OR) with 95% confidence intervals.A total of 31,317 PWE were included. The mean MPR was 81.1% (SD 25.7%) with 64.7% of patients showing good adherence (MPR >80%). Patient-related factors associated with good adherence to AED treatment were West German residence (OR 1.23, p < 0.0001) and learning disability (OR 1.80, p < 0.0001). Adherence was higher in patients treated with new than old (OR 1.52, p < 0.0001) and branded than generic AED (OR 1.44, p < 0.0001). Among the most common AED, levetiracetam achieved best adherence (OR 2.85, p < 0.0001), valproate lowest. Two or more daily dosages reduced adherence (TID vs QD: OR 0.84, p = 0.005; BID vs QD: OR 0.86, p = 0.011).One third of PWE treated with AED in Germany showed poor adherence, which was related to demographic characteristics and drug properties. Administration of new, well-tolerated drugs in simple dosage regimens improved AED compliance.
EVALuna2:22472

Noncompliance of patients with driving restrictions due to uncontrolled epilepsy - Willems, Laurent M.; Reif, Philipp S.; Knake, Susanne; Hamer, Hajo; Willems, Constantin; Kraemer, Guenter; Rosenow, Felix; Strzelczyk, Adam (Epilepsy & Behavior, 2019)
Epilepsies are a common and chronic neurological disorder characterized by sustained risk of recurrent seizures. Because of paroxysmal and often unpredictable occurrence of seizures, patients with uncontrolled epilepsy are subject to disease-specific restrictions in daily life, such as their career choice or specific work limitations. According to German law and many other European and international guidelines, driving is strictly prohibited in patients with uncontrolled epilepsy so as to increase active and passive safety in public road traffic. Nevertheless. a significant percentage of patients probably do not comply with these legal restrictions and drive on a regular basis. For this study, we analyzed a representative German cohort with 302 patients (mean age: 45.0 years +/- 16.4; 48% male) with established epilepsy to identify the number of patients driving without permission. Overall, 58.6% (n = 177) of patients had a driving license, 71.1% (n 69/97) of patients were in seizure remission, and 52.7% (n = 108/205) of patients had uncontrolled epilepsy. Among patients in seizure remission, 54.6% (n = 53/97) reported regular driving while, among patients with uncontrolled epilepsy, 15.1% (n = 31/205) reported driving on a regular basis. No patient in the cohort stated driving without a valid license. Permanent employment, freelance work, the absence of a relevant disability, and living alone were identified as significant risk factors, which underlines the already existing evidence for the importance of a possible restricted access to the labor market as motive for disregarding legal driving restrictions.
CRIS-Team WoS Importer:2019-04-04

Noninvasive Collateral Flow Velocity Imaging in Acute Ischemic Stroke: Intraindividual Comparison of 4D-CT Angiography with Digital Subtraction Angiography - Mühlen, Iris; Kloska, Stephan P.; Gölitz, Philipp; Breuer, Lorenz; Ditt, Hendrik; Dörfler, Arnd; Hölter, Philip (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose The collateral status can be defined not only by its morphological extent but also by the velocity of collateral filling characterized by the relative filling time delay (rFTD). The aim of our study was to compare different methods of noninvasive visualization of rFTD derived from 4D-CT angiography (4D-CTA) with digital substraction angiography (DSA) and to investigate the correlation between functional and morphological collateral status on timing-invariant CTA.
CRIS-Team WoS Importer:2019-09-20

Non-invasive EEG evaluation in epilepsy diagnosis - Rosenow, Felix; Klein, Karl Martin; Hamer, Hajo (Expert review of neurotherapeutics, 2015)
The EEG is an invaluable tool in the diagnosis of epilepsy which guides clinical management. It helps to determine if attacks are of epileptic origin, allows the estimation of the recurrence risk after a first seizure, aids in the diagnosis of the epilepsy syndrome and represents the gold standard in the presurgical evaluation of epilepsy. The EEG can also detect subclinical seizures as a cause of coma. In this review we discuss the sensitivity and specificity of the EEG, present the EEG findings and their significance in different epilepsy syndromes including focal and generalized epilepsies and describe the application of activation procedures.
EVALuna2:22395

Non-specific gastrointestinal features: Could it be Fabry disease? - Hilz, Max-Josef; Arbustini, Eloisa; Dagna, Lorenzo; Gasbarrini, Antonio; Goizet, Cyril; Lacombe, Didier; Liguori, Rocco; Manna, Raffaele; Politei, Juan; Spada, Marco; Burlina, Alessandro (Digestive and Liver Disease, 2018)
Non-specific gastrointestinal symptoms, including pain, diarrhoea, nausea, and vomiting, can be the first symptoms of Fabry disease. They may suggest more common disorders, e.g. irritable bowel syndrome or inflammatory bowel disease. The confounding clinical presentation and rarity of Fabry disease often cause long diagnostic delays and multiple misdiagnoses. Therefore, specialists involved in the clinical evaluation of non-specific upper and lower gastrointestinal symptoms should recognize Fabry disease as a possible cause of the symptoms, and should consider Fabry disease as a possible differential diagnosis. When symptoms or family history suggest Fabry disease, in men, low alpha-galactosidase A enzyme levels, and in women, specific Fabry mutations confirm the diagnosis. In addition to symptomatic treatments, disease-specific enzyme replacement therapy with recombinant human alpha-galactosidase A enzyme or chaperone therapy (migalastat) in patients with amenable mutations can improve the disease, including gastrointestinal symptoms, and should be initiated as early as possible after Fabry disease has been confirmed; starting enzyme replacement therapy at as young an age as possible after diagnosis improves long-term clinical outcomes. Improved diagnostic tools, such as a modified gastrointestinal symptom rating scale, may facilitate diagnosing Fabry disease in patients with gastrointestinal symptoms of unknown cause and thus assure timely initiation of disease-specific treatment.
EVALuna2:201940

No sex differences in long-term functional outcome after intracerebral hemorrhage - De Ridder, Inger; Kuramatsu, Joji; Gerner, Stefan; Madzar, Dominik; Lücking, Hannes; Kloska, Stephan; Dippel, Diederik; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2017)
Background There is conflicting evidence about the influence of sex on outcome after spontaneous intracerebral hemorrhage (sICH) and the majority of the research focused on mortality and short-term outcome only. We investigated sex differences in long-term functional outcome after sICH. Methods We used data from a prospective hospital registry and included all consecutive patients with ICH admitted to our institution between January 2006 and July 2014. Functional outcome was assessed by modified Rankin Scale evaluated 3 and 12 months after ICH. We explored the influence of sex on long-term functional outcome using multivariable regression models and additionally by means of propensity score matching. Results We analyzed 823 patients, of whom 380 (46%) women. Women were on average three years older (p < 0.001), men had more often deep hematomas (p = 0.01). Unadjusted mortality rates were significantly increased in women at three months (42% vs. 35%; odds ratio (OR): 1.35; 95% confidence interval (CI): 1.02-1.80). After adjusting for baseline prognostic factors there were no differences between men and women in short- and long-term mortality (OR = 1.01; 95% CI = 0.66-1.54 and OR = 1.04; 95%CI = 0.69-1.57, respectively) and short- and long-term unfavorable outcome (OR = 1.02; 95%CI = 0.67-1.55 and OR = 0.96; 95% CI = 0.62-1.48, respectively). Conclusion We found no sex-related differences in long-term functional outcome in patients with sICH. The apparently worse functional outcome in women can be explained by differences in age.
EVALuna2:22516

Novel multiple sclerosis susceptibility loci implicated in epigenetic regulation - Andlauer, Till F. M.; Buck, Dorothea; Antony, Gisela; Bayas, Antonios; Bechmann, Lukas; Berthele, Achim; Chan, Andrew; Gasperi, Christiane; Gold, Ralf; Graetz, Christiane; Haas, Juergen; Hecker, Michael; et al. (Science Advances, 2016)
We conducted a genome-wide association study (GWAS) on multiple sclerosis (MS) susceptibility in German cohorts with 4888 cases and 10,395 controls. In addition to associations within the major histocompatibility complex (MHC) region, 15 non-MHC loci reached genome-wide significance. Four of these loci are novel MS susceptibility loci. They map to the genes L3MBTL3, MAZ, ERG, and SHMT1. The lead variant at SHMT1 was replicated in an independent Sardinian cohort. Products of the genes L3MBTL3, MAZ, and ERG play important roles in immune cell regulation. SHMT1 encodes a serine hydroxymethyltransferase catalyzing the transfer of a carbon unit to the folate cycle. This reaction is required for regulation of methylation homeostasis, which is important for establishment and maintenance of epigenetic signatures. Our GWAS approach in a defined population with limited genetic substructure detected associations not found in larger, more heterogeneous cohorts, thus providing new clues regarding MS pathogenesis.
EVALuna2:22548

Obstructive Sleep-Disordered Breathing Is More Common than Central in Mild Familial Dysautonomia - Hilz, Max-Josef; Möller, Sebastian; Buechner, Susanne; Czarkowska, Hanna; Ayappa, Indu; Axelrod, Felicia B.; Rapoport, David M. (Journal of Clinical Sleep Medicine, 2016)
In familial dysautonomia (FD) patients, sleep-disordered breathing (SDB) might contribute to their high risk of sleep-related sudden death. Prevalence of central versus obstructive sleep apneas is controversial but may be therapeutically relevant. We, therefore, assessed sleep structure and SDB in FD-patients with no history of SDB.11 mildly affected FD-patients (28 ± 11 years) without clinically overt SDB and 13 controls (28 ± 10 years) underwent polysomnographic recording during one night. We assessed sleep stages, obstructive and central apneas (>= 90% air flow reduction) and hypopneas (> 30% decrease in airflow with >= 4% oxygen-desaturation), and determined obstructive (oAI) and central (cAI) apnea indices and the hypopnea index (HI) as count of respective apneas/hypopneas divided by sleep time. We obtained the apnea-hypopnea index (AHI4%) from the total of apneas and hypopneas divided by sleep time. We determined differences between FD-patients and controls using the U-test and within-group differences between oAIs, cAIs, and HIs using the Friedman test and Wilcoxon test.Sleep structure was similar in FD-patients and controls. AHI4% and HI were significantly higher in patients than controls. In patients, HIs were higher than oAIs and oAIs were higher than cAIs. In controls, there was no difference between HIs, oAIs, and cAIs. Only patients had apneas and hypopneas during slow wave sleep.In our FD-patients, obstructive apneas were more common than central apneas. These findings may be related to FD-specific pathophysiology. The potential ramifications of SDB in FD-patients suggest the utility of polysomnography to unveil SDB and initiate treatment.A commentary on this article appears in this issue on page 1583.
EVALuna2:22543

On Admission Lymphopenia in ICH Patients Is Associated with Increased Mortality and Poor Functional Outcome - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Lücking, Hannes; Kloska, Stephan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22586

Operative variations in temporal lobe epilepsy surgery and seizure and memory outcome in 226 patients suffering from hippocampal sclerosis - Roessler, Karl; Kasper, Burkhard; Shawarba, Julia; Walther, Katrin; Coras, Roland; Brandner, Sebastian; Winter, Fabian; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (Neurological Research, 2021)
Objective: The aim of this retrospective cohort study was to assess seizure and memory outcomes following temporal lobe surgery in patients suffering from medically refractory temporal lobe epilepsy (TLE) and hippocampal sclerosis (HS). Methods: A retrospective monocentric data analysis was performed in consecutive patients who were operated on during 2002–2018. In the first decennium, standard temporal lobe resections (TLR) were predominately performed, and later, antero-temporal lobe resections (ATLR) were mainly performed. Seizure and memory outcomes over time were assessed according to ILAE/Engel classification and the Berlin Amnesia Test (BTA), respectively. Results: Altogether, 231 surgeries were performed on 226 patients (mean age, 40 years [range, 10–68 years]; male: female, 1:1.4; mean seizure duration, 25 years; and mean follow-up duration, 4.75 years [range, 1–16]). Recently, outcomes of 78.3% of the patients in the total cohort were classified as Engel class I, with 54.9% of patients being completely seizure free. The recent cohort of ATLR since 2012 showed significant more completely seizure-free patients than before 2012 (Engel IA 46.6% versus 67.7%, p < 0.0025, χ 2), although the Kaplan Meier analysis of all patients favors TLR for better seizure outcome (61% ATLR vs 73% TLR seizure free after 5 yrs, log rank p < 0.001). Verbal memory improved significantly in non-dominant patients. Minor neurological complications were noted (permanent severe complications, 0.4%; temporary severe complications, 4.8%). Conclusion: Significant improvements in seizure and memory outcomes were observed over time, with surgical technique and seizure duration as important prognostic factors. Early admittance for surgery may favor an excellent seizure outcome in patients undergoing temporal lobe resection for HS.
CRIS-Team Scopus Importer:2021-07-02
Keywords: amygdalo-hippocampectomy; antero-temporal resection; Hippocampal sclerosis; seizure outcome; standard temporal lobe resection; temporal lobe epilepsy

Optical coherence tomography in patients with a history of juvenile multiple sclerosis reveals early retinal damage - Huhn, K.; Lämmer, Robert; Oberwahrenbrock, T.; Laemmer, A.; Waschbisch, Anne; Gosar, D.; Brandt, A.; Paul, Friedemann; Linker, R. A.; Lee, D. -H. (European Journal of Neurology, 2015)
Some 3%-10% of patients with multiple sclerosis (MS) experience disease onset before the age of 18 years ('early' onset MS, EOMS). Optical coherence tomography is a non-invasive method to measure retinal nerve fibre layer thickness (RNFLT) and total macular volume (TMV) and may be useful to differentiate axonal and neuronal damage in the retina of patients with a history of EOMS. Here RNFLT and TMV in EOMS patients after a mean disease duration of 11.6 years were compared with patients with age- or disease-duration-matched later onset MS (LOMS) and healthy controls (HCs).In this observational cross-sectional study at two German academic MS centres, RNFLT and TMV were measured by spectral-domain optical coherence tomography in 32 HCs, 36 EOMS (mean age at onset 15.5 ± 2.0 years) and 58 LOMS patients.In comparison with HCs, EOMS patients displayed a significant reduction of RNFLT and TMV independently of a history of optic neuritis. In particular, RNFLT loss in EOMS was similar to that in LOMS and TMV loss was slightly higher compared with disease-duration-matched LOMS. In a generalized estimating model, the EOMS group also displayed a similar correlation between disease duration and RNFLT or TMV loss to LOMS patients.These data argue for a significant amount of axonal and neuronal damage in the retina of EOMS patients and may provide a structural basis for the observation that EOMS patients reach states of irreversible disability at a younger age than patients with LOMS.
EVALuna2:21183

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Optimized angiographic CT using intravenous contrast injection: a noninvasive imaging option for the follow-up of coiled aneurysms? - Gölitz, Philipp; Struffert, Tobias; Kaschka, Iris; Roessler, Karl; Knossalla, F.; Dörfler, Arnd (American Journal of Neuroradiology, 2014)
Because recanalization of coiled cerebral aneurysms is reported to occur, follow-up imaging is mandatory, ideally noninvasively. Our study aimed to evaluate the accuracy of an optimized angiographic CT by using intravenous contrast material injection in the assessment of coiled cerebral aneurysms, compared with MR angiography and digital subtraction angiography, the criterion standard.We included 69 patients with 76 coiled cerebral aneurysms. In each patient, we performed an angiographic CT with intravenous contrast material injection with a dual rotational acquisition, a time-of-flight MR angiography, and a DSA. The angiographic CT with intravenous contrast material injection data was postprocessed by using newly implemented reconstructions modes and a dual-volume technique. An aneurysm occlusion rate was assessed in angiographic CT with intravenous contrast material injection and MRA; remnants were measured and correlated with DSA, respectively.Twenty-eight remnants were revealed by DSA with a mean size of 3.1 × 3.1 mm. Angiographic CT with intravenous contrast material injection demonstrated a sensitivity of 93% and a specificity of 96% in remnant detection. MRA showed almost identical accuracy (sensitivity of 93%, specificity of 100%). Assessment of remnant size by angiographic CT with intravenous contrast material injection and by MRA revealed a high significant correlation with DSA, respectively (P < .001).Optimized angiographic CT with intravenous contrast material injection and MRA demonstrated accuracy comparable with that of DSA in the follow-up of coiled aneurysms, respectively. The assessment of remnant size showed a high correlation with DSA for both techniques. Due to the lack of radiation exposure, MRA seems to be the preferred technique. However, angiographic CT with intravenous contrast material injection can be considered a reliable, noninvasive alternative in patients with MR imaging contraindications or in cases of compromising artifacts due to metal implants (ie, clips).
EVALuna2:22327

Optimized Flat-Detector CT in Stroke Imaging: Ready for First-Line Use? - Eckert, Matthias; Gölitz, Philipp; Lücking, Hannes; Struffert, Tobias; Knossalla, Frauke; Dörfler, Arnd (Cerebrovascular Diseases, 2017)
Using flat-detector CT (FD-CT) for stroke imaging has the advantage that both diagnostic imaging and endovascular therapy can be performed directly within the Angio Suite without any patient transfer and time delay. Thus, stroke management could be speeded up significantly, and patient outcome might be improved. But as precondition for using FD-CT as primary imaging modality, a reliable exclusion of intracranial hemorrhage (ICH) has to be possible. This study aimed to investigate whether optimized native FD-CT, using a newly implemented reconstruction algorithm, may reliably detect ICH in stroke patients. Additionally, the potential to identify ischemic changes was evaluated.Cranial FD-CT scans were obtained in 102 patients presenting with acute ischemic stroke (n = 32), ICH (n = 45) or transient ischemic attack (n = 25). All scans were reconstructed with a newly implemented half-scan cone-beam algorithm. Two experienced neuroradiologists, unaware of clinical findings, evaluated independently the FD-CTs screening for hemorrhage or ischemic signs. The findings were correlated to CT, and rater and inter-rater agreement was assessed.FD-CT demonstrated high sensitivity (95-100%) and specificity (100%) in detecting intracerebral and intraventricular hemorrhage (IVH). Overall, interobserver agreement (? = 0.92) was almost perfect and rater agreement to CT highly significant (r = 0.81). One infratentorial ICH and 10 or 11 of 22 subarachnoid hemorrhages (SAHs) were missed of whom 7 were perimesencephalic. The sensitivity for detecting acute ischemic signs was poor in blinded readings (0 or 25%, respectively).Optimized FD-CT, using a newly implemented reconstruction algorithm, turned out as a reliable tool for detecting supratentorial ICH and IVH. However, detection of infratentorial ICH and perimesencephalic SAH is limited. The potential of FD-CT in detecting ischemic changes is poor in blinded readings. Thus, plain FD-CT seems insufficient as a standalone modality in acute stroke, but within a multimodal imaging approach primarily using the FD technology, native FD-CT seems capable to exclude reliably supratentorial hemorrhage. Currently, FD-CT imaging seems not yet ready for wide adoption, replacing regular CT, and should be reserved for selected patients. Furthermore, prospective evaluations are necessary to validate this approach in the clinical setting.
EVALuna2:22513

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation - Polymeris, Alexandros A.; Macha, Kosmas; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Cappellari, Manuel; Schaedelin, Sabine; Zietz, Annaelle; Peters, Nils; Seiffge, David J.; Haupenthal, David; Gaßmann, Luise; et al. (Annals of Neurology, 2021)
Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged >= 85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged >= 85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all-cause death. We used simple, adjusted, and weighted Cox regression to account for confounders. We calculated the net benefit of DOAC versus VKA by balancing stroke reduction against the weighted ICH risk. Results In total, 5,984 of 6,267 (95.5%) patients were eligible for analysis. Of those, 1,380 (23%) were aged >= 85 years and 3,688 (62%) received a DOAC. During 6,874 patient-years follow-up, the impact of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome did not differ between patients aged >= 85 (HR >= 85y = 0.65, 95%-CI [0.52, 0.81]) and < 85 years (HR<85y = 0.79, 95%-CI [0.66, 0.95]) in simple (p(interaction) = 0.129), adjusted (p(interaction) = 0.094) or weighted (p(interaction) = 0.512) models. Analyses on recurrent stroke, ICH and death separately were consistent with the primary analysis, as were sensitivity analyses using age dichotomized at 90 years and as a continuous variable. DOAC had a similar net clinical benefit in patients aged >= 85 (+1.73 to +2.66) and < 85 years (+1.90 to +3.36 events/100 patient-years for ICH-weights 1.5 to 3.1). Interpretation The favorable profile of DOAC over VKA in patients with AF and recent stroke was maintained in the oldest old. ANN NEUROL 2021
CRIS-Team WoS Importer:2021-12-10

Oral Anticoagulation and Functional Outcome after Intracerebral Hemorrhage - Biffi, Alessandro; Kuramatsu, Joji; Leasure, Audrey; Kamel, Hooman; Kourkoulis, Christina; Schwab, Kristin; Ayres, Alison M.; Elm, Jordan; Gurol, M. Edip; Greenberg, Steven M.; Viswanathan, Anand; Anderson, Christopher D.; et al. (Annals of Neurology, 2017)
Oral anticoagulation treatment (OAT) resumption is a therapeutic dilemma in intracerebral hemorrhage (ICH) care, particularly for lobar hemorrhages related to amyloid angiopathy. We sought to determine whether OAT resumption after ICH is associated with long-term outcome, accounting for ICH location (ie, lobar vs nonlobar).We meta-analyzed individual patient data from: (1) the multicenter RETRACE study (n = 542), (2) a U.S.-based single-center ICH study (n = 261), and (3) the Ethnic/Racial Variations of Intracerebral Hemorrhage study (n = 209). We determined whether, within 1 year from ICH, OAT resumption was associated with: (1) mortality, (2) favorable functional outcome (modified Rankin Scale = 0-3), and (3) stroke incidence. We separately analyzed nonlobar and lobar ICH cases using propensity score matching and Cox regression models.We included 1,012 OAT-related ICH survivors (633 nonlobar and 379 lobar). Among nonlobar ICH survivors, 178/633 (28%) resumed OAT, whereas 86/379 (23%) lobar ICH survivors did. In multivariate analyses, OAT resumption after nonlobar ICH was associated with decreased mortality (hazard ratio [HR] = 0.25, 95% confidence interval [CI] = 0.14-0.44, p < 0.0001) and improved functional outcome (HR = 4.22, 95% CI = 2.57-6.94, p < 0.0001). OAT resumption after lobar ICH was also associated with decreased mortality (HR = 0.29, 95% CI = 0.17-0.45, p < 0.0001) and favorable functional outcome (HR = 4.08, 95% CI = 2.48-6.72, p < 0.0001). Furthermore, OAT resumption was associated with decreased all-cause stroke incidence in both lobar and nonlobar ICH (both p < 0.01).These results suggest novel evidence of an association between OAT resumption and outcome following ICH, regardless of hematoma location. These findings support conducting randomized trials to explore risks and benefits of OAT resumption after ICH. Ann Neurol 2017;82:755-765.
EVALuna2:22551

Oscillations support short latency co-firing of neurons during human episodic memory formation - Roux, Frédéric; Parish, George; Chelvarajah, Ramesh; Rollings, David T.; Sawlani, Vijay; Hamer, Hajo; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; Ter Wal, Marije J.; Kolibius, Luca; Staresina, Bernhard P.; Wimber, Maria; et al. (eLife, 2022)
Theta and gamma oscillations in the medial temporal lobe are suggested to play a critical role for human memory formation via establishing synchrony in neural assemblies. Arguably, such synchrony facilitates efficient information transfer between neurons and enhances synaptic plasticity, both of which benefit episodic memory formation. However, to date little evidence exists from humans that would provide direct evidence for such a specific role of theta and gamma oscillations for episodic memory formation. Here, we investigate how oscillations shape the temporal structure of neural firing during memory formation in the medial temporal lobe. We measured neural firing and local field potentials in human epilepsy patients via micro-wire electrode recordings to analyze whether brain oscillations are related to co-incidences of firing between neurons during successful and unsuccessful encoding of episodic memories. The results show that phase-coupling of neurons to faster theta and gamma oscillations correlates with co-firing at short latencies ( 20-30 ms) and occurs during successful memory formation. Phase-coupling at slower oscillations in these same frequency bands, in contrast, correlates with longer co-firing latencies and occurs during memory failure. Thus, our findings suggest that neural oscillations play a role for the synchronization of neural firing in the medial temporal lobe during the encoding of episodic memories.
CRIS-Team Scopus Importer:2022-12-23
Keywords: human; memory; neural firing; neuroscience; oscillations; single units; spikes; STDP

Osteopontin attenuates inflammation via JAK2/STAT1 pathway in hyperglycemic rats after intracerebral hemorrhage - Gong, Lei; Manaenko, Anatol; Fan, Ruiming; Huang, Lei; Enkhjargal, Budbazar; Mcbride, Devin W.; Ding, Yan; Tang, Jiping; Xiao, Xiaoqiu; Zhang, John H. (Neuropharmacology, 2018)
Acute intracerebral hemorrhage (ICH) complicated by hyperglycemia is associated with aggravation of post-stroke inflammation, leading to exacerbation of brain edema and predicting poor neurological outcomes and higher mortality of patients. Osteopontin (OPN) is a neuroprotective glycoprotein, which is able to attenuate brain injury induced by hemorrhagic stroke. In the current study we investigated whether OPN will decrease the inflammatory post-ICH response as well as attenuate brain edema and neurological deficits in hyperglycemic rats. We employed a collagenase model of ICH on male Sprague-Dawley rats (n = 148) rats and 50% of Dextrose was injected intraperitoneally (i.p) 3 h after ICH (ICH + HG). Intranasal administration of recombinant OPN (rOPN) was performed 1 h after ICH. The development of brain injury was evaluated by brain water content (BWC) and neurological deficits, western blot and immunohistochemistry study. Small interfering ribonucleic acid (siRNA) for integrin-β1 receptor and a JAK2 agonist, Coumermycin A1 (C-A1), were used for detailed investigation of the molecular pathway. The administration of OPN (3 μg) significantly improved neurobehavior and increased expression of OPN and integrin-β1 receptor in the brain followed with decrease of neutrophil infiltration, JAK2, STAT1, TNF-a, IL-1b, MMP-9 and brain edema in the ICH + HG + OPN rats compared with ICH + HG rats. The effects of OPN were reversed by the intervention of intergrin-β1 siRNA and C-A1. In conclusion, rOPN attenuated ICH-induced brain inflammation in hyperglycemic rats, leading to attenuation of brain edema and improving neurological functions. Effects of rOPN were mediated at least partly by integrin-β1 induced inhibition of JAK2/STAT1 pathway.
EVALuna2:213462

Pain in Fabry Disease: Practical Recommendations for Diagnosis and Treatment - Politei, Juan M.; Bouhassira, Didier; Germain, Dominique P.; Goizet, Cyril; Guerrero-Sola, Antonio; Hilz, Max-Josef; Hutton, Elspeth J.; Karaa, Amel; Liguori, Rocco; Ueceyler, Nurcan; Zeltzer, Lonnie K.; Burlina, Alessandro (Cns Neuroscience & Therapeutics, 2016)
Patients with Fabry disease (FD) characteristically develop peripheral neuropathy at an early age, with pain being a crucial symptom of underlying pathology. However, the diagnosis of pain is challenging due to the heterogeneous and nonspecific symptoms. Practical guidance on the diagnosis and management of pain in FD is needed.In 2014, experts met to discuss recent advances on this topic and update clinical guidance.Emerging disease-specific tools, including FabryScan, Fabry-specific Pediatric Health and Pain Questionnaire, and Würzburg Fabry Pain Questionnaire, and more general tools like the Total Symptom Score can aid diagnosis, characterization, and monitoring of pain in patients with FD. These tools can be complemented by more objective and quantifiable sensory testing. In male and female patients of any age, pain related to FD can be an early indication to start disease-specific enzyme replacement therapy before potentially irreversible organ damage to the kidneys, heart, or brain occurs.To improve treatment outcomes, pain should be diagnosed early in unrecognized or newly identified FD patients. Treatment should include: (a) enzyme replacement therapy controlling the progression of underlying pathology; (b) adjunctive, symptomatic pain management with analgesics for chronic neuropathic and acute nociceptive, and inflammatory or mixed pain; and (c) lifestyle modifications.
EVALuna2:22448

Paradoxical kinesia in Parkinson's disease revisited: Anticipation of temporal constraints is critical - Distler, Michael; Schlachetzki, Johannes; Kohl, Zacharias; Winkler, Jürgen; Schenk, Thomas (Neuropsychologia, 2016)
Slowness of movement, called bradykinesia is the cardinal symptom of Parkinson's disease. Under distinct but not yet well-defined circumstances, patients with Parkinson's disease are able to overcome bradykinesia. One common hypothesis for this phenomenon termed paradoxical kinesia in Parkinson's disease postulates that the presentation of external sensory triggers is pivotal to elicit significant increase of motor velocity. In the present study, we examined an alternative hypothesis, namely that an internal cue in the absence of sensory cues are linked to paradoxical kinesia. To test this alternative hypothesis, patients with Parkinson's disease and healthy age-matched controls (n=9 per group) performed two movement tasks. In the stationary-object prehension task, subjects had to pick up a stationary target object. For the escaping-object task, the participants had to pick up the target object before it moved out of reach. The time available to reach for the object was adjusted individually to ensure comparable difficulty across participants. Reaction time, movement duration, and maximum velocity were assessed for both movement tasks. In Parkinson's disease patients and healthy controls, anticipation of the imminent movement of a target object significantly decreased reaction time, movement duration, and increased maximum movement velocity. The increase of maximum movement velocity in the escape-condition was significantly more pronounced for Parkinson's disease patients as compared to healthy controls. We provide evidence that internal cues such as temporal constraints are sufficient to diminish the cardinal clinical symptom of bradykinesia in Parkinson's disease. Our results suggest that expectations rather than sensory cues are critical for the emergence of paradoxical kinesia and we discuss the implications of our findings for an account of paradoxical kinesia.
EVALuna2:33521

Parametric color coding of digital subtraction angiography in the evaluation of carotid cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Lücking, Hannes; Roesch, J.; Knossalla, F.; Ganslandt, Oliver; Deuerling-Zheng, Y.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Purpose: Angiographic assessment of carotid cavernous fistulas (CCFs) can be complex. Our purpose was to examine whether the use of parametric color coding in the postprocessing of DSA series is advantageous in the evaluation of CCFs. Methods: We enrolled 16 patients with angiographically proven CCFs. Endovascular treatment was performed in 14 cases. For postprocessing of digital subtraction angiography (DSA) series, a newly implemented algorithm of parametric color coding was used, turning sequential images of two-dimensional (2D)-DSA series into a single color-coded image. Angiographic data of initial, interventional, and postinterventional 2D-DSA series were compared with color-coded images. Whether parametric color coding could facilitate evaluation of fistula architecture and provide a more precise estimation of fistula venous drainage patterns as well as whether flow analysis could reveal objective changes during and after treatment were investigated. Results: In 56 % of the cases, parametric color coding was observed to facilitate visualization of fistula angioarchitecture. Estimation of fistula drainage flow patterns was considered to be improved in 31 % of the cases. For assessment of hemodynamic changes during and after treatment, parametric color coding was assumed to be helpful in 21 % of the cases, especially because revealing flow changes that were not visible on 2D-DSA series were now visible. Conclusions: Parametric color coding is a fast application tool that might provide additional support in the angiographic evaluation of CCFs. Visualization of complex fistula architecture could be facilitated, and flow analysis might improve assessment of venous drainage patterns, thereby increasing overall diagnostic confidence. During and after treatment, hemodynamic changes that were not visible on 2D-DSA series could now be depicted. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cerebrovascular disease; Digital subtraction angiography; Endovascular treatment; Image postprocessing

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Parenchymatous hemorrhage is associated with unfavorable longterm outcome in patients with atraumatic subarachnoid hemorrhage - Gerner, Stefan; Kuramatsu, J.; Reichl, J.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Dörfler, Arnd; Struffert, Tobias; Schwab, Sibylle; Huttner, Hagen (2017)
EVALuna2:34024

Partial pharmacologic blockade shows sympathetic connection between blood pressure and cerebral blood flow velocity fluctuations - Hilz, Max-Josef; Wang, Ruihao; Marthol, Harald; Liu, Mao; Tillmann, Alexandra; Riss, Stephan; Hauck, Paulina; Hoesl, Katharina M.; Wasmeier, Gerald; Stemper, Brigitte; Köhrmann, Martin (Journal of the Neurological Sciences, 2016)
Cerebral autoregulation (CA) dampens transfer of blood pressure (BP)-fluctuations onto cerebral blood flow velocity (CBFV). Thus, CBFV-oscillations precede BP-oscillations. The phase angle (PA) between sympathetically mediated low-frequency (LF: 0.03-0.15Hz) BP- and CBFV-oscillations is a measure of CA quality. To evaluate whether PA depends on sympathetic modulation, we assessed PA-changes upon sympathetic stimulation with and without pharmacologic sympathetic blockade. In 10 healthy, young men, we monitored mean BP and CBFV before and during 120-second cold pressor stimulation (CPS) of one foot (0°C ice-water). We calculated mean values, standard deviations and sympathetic LF-powers of all signals, and PAs between LF-BP- and LF-CBFV-oscillations. We repeated measurements after ingestion of the adrenoceptor-blocker carvedilol (25mg). We compared parameters before and during CPS, without and after carvedilol (analysis of variance, post-hoc t-tests, significance: p<0.05). Without carvedilol, CPS increased BP, CBFV, BP-LF- and CBFV-LF-powers, and shortened PA. Carvedilol decreased resting BP, CBFV, BP-LF- and CBFV-LF-powers, while PAs remained unchanged. During CPS, BPs, CBFVs, BP-LF- and CBFV-LF-powers were lower, while PAs were longer with than without carvedilol. With carvedilol, CPS no longer shortened resting PA. Sympathetic activation shortens PA. Partial adrenoceptor blockade abolishes this PA-shortening. Thus, PA-measurements provide a subtle marker of sympathetic influences on CA and might refine CA evaluation.
EVALuna2:22459

Patient preferences for disease-modifying drugs in multiple sclerosis therapy: a choice-based conjoint analysis - Utz, Kathrin S.; Hoog, Jana; Wentrup, Andreas; Berg, Sebastian; Laemmer, Alexandra; Jainsch, Britta; Waschbisch, Anne; Lee, De-Hyung; Linker, Ralf; Schenk, Thomas (Therapeutic Advances in Neurological Disorders, 2014)
With an increasing number of disease-modifying treatments (DMTs) for multiple sclerosis (MS), patient preferences will gain importance in the decision-making process. We assessed patients' implicit preferences for oral versus parenteral DMTs and identified factors influencing patients' treatment preference.Patients with relapsing-remitting MS (n = 156) completed a questionnaire assessing treatment preferences, whereby they had to decide between pairs of hypothetical treatment scenarios. Based on this questionnaire a choice-based conjoint analysis was conducted.Treatment frequency and route of administration showed a stronger influence on patient preference compared with frequency of mild side effects. The latter attribute was more important for treatment-naïve patients compared with DMT-experienced patients. The higher the Extended Disability Status Scale score, the more likely pills, and the less likely fewer side effects were preferred. Pills were preferred over injections by 93% of patients, when treatment frequency and frequency of side effects were held constant. However, preference switched to injections when pills had to be taken three times daily and injections only once per week. Injections were also preferred when pills were associated with frequent side effects.Our results suggest that route of administration and treatment frequency play an important role in the patients' preference for a given DMT.
EVALuna2:22318

Patient-relevant therapy goals and benefits in the treatment of epilepsy - Klein, Toni Maria; Blome, Christine; Westermayer, Vivien; Cuny, Jeanne; Hamer, Hajo (QUALITY OF LIFE RESEARCH, 2021)
CRIS-Team WoS Importer:2021-12-03

PD-L1 positive astrocytes attenuate inflammatory functions of PD-1 positive microglia in models of autoimmune neuroinflammation - Linnerbauer, Mathias; Beyer, Tobias; Nirschl, Lucy; Farrenkopf, Daniel; Lößlein, Lena; Vandrey, Oliver; Peter, Anne; Tsaktanis, Thanos; Kebir, Hania; Laplaud, David; Oellinger, Rupert; Engleitner, Thomas; et al. (Nature Communications, 2023)
Multiple Sclerosis (MS) is a chronic autoimmune inflammatory disorder of the central nervous system (CNS). Current therapies mainly target inflammatory processes during acute stages, but effective treatments for progressive MS are limited. In this context, astrocytes have gained increasing attention as they have the capacity to drive, but also suppress tissue-degeneration. Here we show that astrocytes upregulate the immunomodulatory checkpoint molecule PD-L1 during acute autoimmune CNS inflammation in response to aryl hydrocarbon receptor and interferon signaling. Using CRISPR-Cas9 genetic perturbation in combination with small-molecule and antibody-mediated inhibition of PD-L1 and PD-1 both in vivo and in vitro, we demonstrate that astrocytic PD-L1 and its interaction with microglial PD-1 is required for the attenuation of autoimmune CNS inflammation in acute and progressive stages in a mouse model of MS. Our findings suggest the glial PD-L1/PD-1 axis as a potential therapeutic target for both acute and progressive MS stages.
CRIS-Team Scopus Importer:2023-09-22

Peak perihemorrhagic edema correlates with functional outcome in intracerebral hemorrhage - Volbers, Bastian; Giede-Jeppe, Antje; Gerner, Stefan; Sembill, Jochen; Kuramatsu, Joji; Lang, Stefan; Lücking, Hannes; Staykov, Dimitre; Huttner, Hagen (Neurology, 2018)
Objective To evaluate the association of perihemorrhagic edema (PHE) evolution and peak edema extent with day 90 functional outcome in patients with intracerebral hemorrhage (ICH) and identify pathophysiologic factors influencing edema evolution. Methods This retrospective cohort study included patients with spontaneous supratentorial ICH between January 2006 and January 2014. ICH and PHE volumes were studied using a validated semiautomatic volumetric algorithm. Multivariable logistic regression and propensity score matching (PSM) accounting for age, ICH volume, and location were used for assessing measures associated with functional outcome and PHE evolution. Clinical outcome on day 90 was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor). Results A total of 292 patients were included. Median age was 70 years (interquartile range [IQR] 62-78), median ICH volume on admission 17.7 mL (IQR 7.9-40.2). Besides established factors for functional outcome, i.e., ICH volume and location, age, intraventricular hemorrhage, and NIH Stroke Scale score on admission, multivariable logistic regression revealed peak PHE volume (odds ratio [OR] 0.984 [95% confidence interval (CI) 0.973-0.994]) as an independent predictor of day 90 outcome. Peak PHE volume was independently associated with initial PHE increase up to day 3 (OR 1.060 [95% CI 1.018-1.103]) and neutrophil to lymphocyte ratio on day 6 (OR 1.236 [95% CI 1.034-1.477; PSM cohort, n = 124]). Initial PHE increase (PSM cohort, n = 224) was independently related to hematoma expansion (OR 3.647 [95% CI 1.533-8.679]) and fever burden on days 2-3 (OR 1.456 [95% CI 1.103-1.920]). Conclusion Our findings suggest that peak PHE volume represents an independent predictor of functional outcome after ICH. Inflammatory processes and hematoma expansion seem to be involved in PHE evolution and may represent important treatment targets.
EVALuna2:34919

Peak Troponin I Levels Are Associated with Functional Outcome in Intracerebral Hemorrhage - Gerner, Stefan; Auerbeck, Katrin; Sprügel, Maximilian; Sembill, Jochen; Madzar, Dominik; Gölitz, Philipp; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2018)
Background: Troponin I is a widely used and reliable marker of myocardial damage and its levels are routinely measured in acute stroke care. So far, the influence of troponin I elevations during hospital stay on functional outcome in patients with atraumatic intracerebral hemorrhage (ICH) is unknown. Methods: Observational single-center study including conservatively treated ICH patients over a 9-year period. Patients were categorized according to peak troponin I level during hospital stay (<= 0.040, 0.041-0.500, > 0.500 ng/mL) and compared regarding baseline and hematoma characteristics. Multivariable analyses were performed to investigate independent associations of troponin levels during hospital stay with functional outcome -assessed using the modified Rankin Scale (mRS; favorable 0-3/unfavorable 4-6) -and mortality after 3 and 12 months. To account for possible con-founding propensity score (PS)-matching (1: 1; caliper 0.1) was performed accounting for imbalances in baseline characteristics to investigate the impact of troponin I values on outcome. Results: Troponin elevations (> 0.040 ng/mL) during hospital stay were observed in 308 out of 745 (41.3%) patients and associated with poorer status on admission (Glasgow Coma Scale/National Institute of Health Stroke Scale). Multivariable analysis revealed troponin I levels during hospital stay to be independently associated with unfavorable outcome after 12 months (risk ratio [95% CI]: 1.030 [1.009-1.051] per increment of 1.0 ng/mL; p = 0.005), but not with mortality. After PS-matching, patients with troponin I elevation (= 0.040 ng/mL) versus those without had a significant higher rate of -unfavorable outcome after 3 and 12 months (mRS 4-6 at 3 months: < 0.04 ng/mL: 159/265 [60.0%] versus = 0.04 ng/mL: 199/266 [74.8%]; p < 0.001; at 12 months: < 0.04 ng/mL: 141/248 [56.9%] versus <= 0.04 ng/mL: 179/251 [71.3%]; p = 0.001). Conclusions: Troponin I elevations during hospital stay occur frequently in ICH patients and are independently associated with functional outcome after 3 and 12 months but not with mortality. (c) 2018 S. Karger AG, Basel
EVALuna2:34936

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

Perihemorrhagic edema revisiting hematoma volume, location and surface - Sprügel, Maximilian; Kuramatsu, J. B.; Volbers, Bastian; Koelbl, K.; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Perihemorrhagic edema: Revisiting hematoma volume, location, and surface - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Gerner, Stefan; Sembill, Jochen; Madžar, Dominik; Bobinger, Tobias; Kölbl, Kathrin; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (Neurology, 2019)
OBJECTIVE: To determine the influence of intracerebral hemorrhage (ICH) location and volume and hematoma surface on perihemorrhagic edema evolution. METHODS: Patients with ICH of the prospective Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage (UKER-ICH) cohort study (NCT03183167) between 2010 and 2013 were analyzed. Hematoma and edema volume during hospital stay were volumetrically assessed, and time course of edema evolution and peak edema correlated to hematoma volume, location, and surface to verify the strength of the parameters on edema evolution. RESULTS: Overall, 300 patients with supratentorial ICH were analyzed. Peak edema showed a high correlation with hematoma surface (R2 = 0.864, p < 0.001) rather than with hematoma volumes, regardless of hematoma location. Smaller hematomas with a higher ratio of hematoma surface to volume showed exponentially higher relative edema (R2 = 0.755, p < 0.001). Multivariable logistic regression analysis revealed a cutoff ICH volume of 30 mL, beyond which an increase of total mass lesion volume (combined volume of hematoma and edema) was not associated with worse functional outcome. Specifically, peak edema was associated with worse functional outcome in ICH <30 mL (odds ratio [OR] 2.63, 95% confidence interval [CI] 1.68-4.12, p < 0.001), contrary to ICH ≥30 mL (OR 1.20, 95% CI 0.88-1.63, p = 0.247). There were no significant differences between patients with lobar and those with deep ICH after adjustment for hematoma volumes. CONCLUSIONS: Peak perihemorrhagic edema, although influencing mortality, is not associated with worse functional outcomes in ICH volumes >30 mL. Although hematoma volume correlates with peak edema extent, hematoma surface is the major parameter for edema evolution. The effect of edema on functional outcome is therefore more pronounced in smaller and irregularly shaped hematomas, and these patients may particularly benefit from edema-modifying therapies.
CRIS-Team Scopus Importer:2019-09-27

Perioperative changes in cortical excitability, mood, and quality of life in patients with primary hyperparathyroidism: a pilot study using transcranial magnetic stimulation - Hermsen, A.; Eienbröker, A.; Haag, A.; Mylius, V.; Hamer, Hajo; Menzler, K.; Karakas, E.; Rosenow, F. (European Journal of Endocrinology, 2014)
Serum calcium (Ca(2)(+)) and parathyroid hormone (PTH), amongst others, modify cortical excitability. Alterations in cortical excitability were shown in patients with epilepsy as well as hyper- or hypoparathyroidism. In patients with primary hyperparathyroidism (pHPT), preoperative elevated serum calcium and parathyroidectomy (PTx) may affect mood and quality of life. We hypothesized that perioperative changes in Ca(2)(+) and PTH in pHPT will affect cortical excitability and improve subjective health.Transcranial magnetic stimulation (TMS) was performed before and after surgery in 15 pHPT patients. We measured resting motor threshold, cortical silent period (CSP), short intracortical inhibition, and intracortical facilitation. Health questionnaires were administered before, 1 day and 6 months after PTx, along with the disease-specific Pasieka's parathyroid assessment of symptoms (PAS), which was, to our knowledge, its first use in German.SURGERY WAS SUCCESSFUL IN ALL PATIENTS. TMS-MEASUREMENTS REMAINED UNCHANGED WHEN ANALYZING ALL PATIENTS IN THIS PILOT STUDY. POSTOPERATIVELY, DEPRESSION DECLINED (P=0.05) AND QUALITY OF LIFE IMPROVED SIGNIFICANTLY (P=0.001) IN THE SF-36-SUBSCALES: vitality, social functioning, mental health and subjective health transition (post-hoc analysis). The PAS proved early relief of disease-specific symptoms (P<0.001).We found unchanged cortical excitability comparing pre- and post-PTx in this pilot study. Mood and quality of life improved postoperatively. The German PAS is valuable in detecting disease-specific changes early after PTx.
EVALuna2:22381

Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299

PERIPHERAL PULSE MEASUREMENTS FOR THE DETECTION OF SILENT ATRIAL FIBRILLATION: RESULTS FROM THE PROSPECTIVE, CONTROLLED TRIAL "KNOW YOUR PULSE POST STROKE" - Kallmünzer, Bernd; Macha, Kosmas; Wang, Ruihao; Siedler, Gabriela; Stoll, Svenja; Marsch, Armin; Gerner, Stefan; Winder, Klemens; Koehn, J.; Schwab, Stefan; Koehrmann, M. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Persistence with antiepileptic drugs in epilepsy patients treated in neurological practices in Germany - Jacob, Louis; Hamer, Hajo; Kostev, Karel (Epilepsy and Behavior, 2017)
The goal of this study was to analyze the persistence with antiepileptic drugs (AED) and associated factors in patients followed in neurological practices in Germany.This study included patients aged 18years or over who received two initial diagnoses of epilepsy and a first prescription of AED between 2007 and 2015 in a neurological practice (index date). The main outcome measure was the rate of AED persistence within five years of the index date. Kaplan-Meier analyses were performed to study treatment persistence as a function of age. A Cox proportional hazards regression model was used to estimate the relationship between non-persistence and demographic/clinical variables.A total of 8192 patients followed in neurological practices were included. After five years of follow-up, 41.1% (<=40years), 45.2%, (41-60years) and 50.1% (>60years) of patients followed in neurological practices were persistent (log-rank p-value<0.001). A negative association was found between discontinuation and age (<=40years vs. >60years: OR=1.19, 95% CI: 1.09-1.31; 41-60years vs. >60years: OR=1.10, 95% CI: 1.01-1.19). Furthermore, patients receiving old AED (OR=1.16, 95% CI: 1.01-1.34) or gabapentin (OR=1.46, 95% CI: 1.16-1.83) and those diagnosed with depression (OR=1.12, 95% CI: 1.03-1.21) were at a higher risk of non-persistence, whereas those receiving levetiracetam (OR=0.69, 95% CI: 0.60-0.80) or lamotrigine (OR=0.88, 95% CI: 0.79-0.97) and those with dementia (OR=0.74, 95% CI: 0.65-0.83) were at a lower risk.The rate of epilepsy patients persistent with AED was low after five years of treatment. Age, gender, co-morbidities, and drug characteristics were associated with this persistence.
EVALuna2:22554

Phase-amplitude coupling measures for determination of the epileptic network: A methodological comparison - Ali, Ryshum; Gollwitzer, Stephanie; Reindl, Caroline; Hamer, Hajo; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael; Hastreiter, Peter; Rampp, Stefan (Journal of Neuroscience Methods, 2022)
CRIS-Team WoS Importer:2022-05-13
Keywords: EEG; Epilepsy; Phase-Amplitude Coupling

Phenobarbital in super-refractory status epilepticus (PIRATE): A retrospective, multicenter analysis - Kunst, Stefan; Rojo, Mikel L.; Schmidbauer, Moritz O.; Pelz, Johann; Mueller, Annekatrin; Minnerup, Jens; Meyer, Lennart; Madžar, Dominik; Reindl, Caroline; Madlener, Marie; Malter, Michael; Neumann, Bernhard; et al. (Epilepsia, 2023)
Objective: Super-refractory status epilepticus (SRSE) is an enduring or recurring SE after 24 h or more of general anesthesia. This study aimed to evaluate the efficacy and safety of phenobarbital (PB) for the treatment of SRSE.
CRIS-Team WoS Importer:2023-05-12

Physical Activity in Multiple Sclerosis: A Comparative Study of Vitamin D, BDNF and Regulatory T Cell Populations - Waschbisch, Anne; Wenny, Ingrid; Tallner, Alexander; Schwab, Stefan; Pfeifer, Klaus; Mäurer, Mathias (European neurology, 2012)

Physical and mental health comorbidities of patients with epilepsy in Germany – A retrospective cohort study - Uepping, Peter; Hamer, Hajo; Scholten, Jerome; Kostev, Karel (Epilepsy & Behavior, 2021)
Aims: The aim of this study was to estimate the prevalence of physical and psychological comorbidities in patients with epilepsy in Germany in order to better understand the complex clinical picture and its consequences. Methods: This retrospective cohort study included adult individuals with a diagnosis of epilepsy between January 2018 and December 2018 (index date). Patients with epilepsy were matched 1:1 with patients without epilepsy by age, sex, and physician. The study outcomes included the associations between epilepsy and different physical and mental disorders documented within 365 days after the index date as well as multimorbidity defined as at least two, three, four, and five different diagnoses. The present study used multivariate logistic regression models with all study disorders as dependent variables and epilepsy as an impact variable. Results: After 1:1 matching, the present study included 7942 patients with and 7942 patients without epilepsy (mean age: 58.0 years; 49.7% female). Epilepsy was significantly positively associated with nine disorders, and the strongest associations were with mental retardation (Odds Ratio (OR): 21.11 (95% Confidence Intervals (CI): 12.52–35.59)), cerebrovascular diseases (OR: 3.14 (95% CI: 2.80–3.55)), and dementia (OR: 1.72 (95% CI: 1.47–2.01)). Epilepsy was associated with significantly increased odds of multimorbidity. Conclusion: In summary, individuals with epilepsy have an increased prevalence of comorbidities that increase with age. Further research should be undertaken in this area, including the etiology of comorbidities.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Cohort study; Comorbidity; Epilepsy; Multimorbidity

Physiological effects of cigarette smoking in the limbic system revealed by 3 tesla magnetic resonance spectroscopy - Mennecke, Angelika; Gossler, Andrea; Hammen, Thilo; Dörfler, Arnd; Stadlbauer, Andreas; Roesch, Julie; Kornhuber, Johannes; Bleich, Stefan; Dölken, Marc; Thürauf, Norbert (Journal of Neural Transmission, 2014)
Several studies and recent models of effects of nicotine, the main addictive and psychoactive component in tobacco, point to action of the drug on the limbic system during maintenance of addiction, either direct or indirect via projections from the ventral tegmental area. The objective of this study was to demonstrate physiological effects of cigarette smoking on the hippocampus and the grey matter of the dorsal anterior cingulate cortex in the human brain with regard to addiction and withdrawal. This aim was achieved by group comparisons of results of magnetic resonance spectroscopy between non-smokers, smokers and smokers during withdrawal. 12 smokers and 12 non-smokers were measured with single voxel proton magnetic resonance spectroscopy for total N-acetyl aspartate, glutamate and glutamine, choline-containing compounds, myo-inositol and total creatine in the right and the left hippocampus and in the right and the left dorsal anterior cingulate cortex. Smokers were examined twice, first during regular cigarette smoking and second on the third day of nicotine withdrawal. The ratios to total creatine were used for better reliability. In our study, Glx/tCr was significantly increased and tCho/tCr was significantly decreased in the left cingulate cortex in smokers compared to non-smokers (p = 0.01, both). Six out of seven smokers showed normalization of the Glx/tCr in the left cingulate cortex during withdrawal. Although these results are preliminary due to the small sample size, our results confirm the assumption that cigarette smoking interferes directly or indirectly with the glutamate circuit in the dorsal anterior cingulate cortex.
EVALuna2:22826

Pivotal Role for CD16+ Monocytes in Immune Surveillance of the Central Nervous System - Waschbisch, Anne; Schröder, Sina; Schraudner, Dana; Sammet, Laura; Weksler, Babette; Melms, Arthur; Pfeifenbring, Sabine; Stadelmann, Christine; Schwab, Stefan; Linker, Ralf A. (Journal of Immunology, 2016)
Monocytes represent a heterogeneous population of primary immune effector cells. At least three different subsets can be distinguished based on expression of the low-affinity Fc?RIII: CD14(++)CD16 -: classical monocytes, CD14(++)CD16(+) intermediate monocytes, and CD14(+)CD16 ++: non-classical monocytes. Whereas CD16 -: classical monocytes are considered key players in multiple sclerosis (MS), little is known on CD16(+) monocytes and how they contribute to the disease. In this study, we examined the frequency and phenotype of monocyte subpopulations in peripheral blood, cerebrospinal fluid (CSF), and brain biopsy material derived from MS patients and controls. Furthermore, we addressed a possible monocyte dysfunction in MS and analyzed migratory properties of monocyte subsets using human brain microvascular endothelial cells. Our ex vivo studies demonstrated that CD16(+) monocyte subpopulations are functional but numerically reduced in the peripheral blood of MS patients. CD16(+) monocytes with an intermediate-like phenotype were found to be enriched in CSF and dominated the CSF monocyte population under noninflammatory conditions. In contrast, an inversed CD16(+) to CD16 -: CSF monocyte ratio was observed in MS patients with relapsing-remitting disease. Newly infiltrating, hematogenous CD16(+) monocytes were detected in a perivascular location within active MS lesions, and CD16(+) monocytes facilitated CD4(+) T cell trafficking in a blood -: brain barrier model. Our findings support an important role of CD16(+) monocytes in the steady-state immune surveillance of the CNS and suggest that CD16(+) monocytes shift to sites of inflammation and contribute to the breakdown of the blood-brain barrier in CNS autoimmune diseases.
EVALuna2:22432

Pivotal role of choline metabolites in remyelination - Skripuletz, Thomas; Manzel, Arndt; Gropengieer, Karoline; Schaefer, Nora; Gudi, Viktoria; Singh, Vikramjeet; Tejedor, Laura Salinas; Joerg, Stefanie; Hammer, Anna; Voss, Elke; Vulinovic, Franca; Degen, Diane; et al. (Brain, 2015)
Neuroprotective approaches for central nervous system regeneration have not been successful in clinical practice so far and compounds that enhance remyelination are still not available for patients with multiple sclerosis. The objective of this study was to determine potential regenerative effects of the substance cytidine-5'-diphospho (CDP)-choline in two different murine animal models of multiple sclerosis. The effects of exogenously applied CDP-choline were tested in murine myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis. In addition, the cuprizone-induced mouse model of de- and remyelination was used to specifically test the hypothesis that CDP-choline directly increases remyelination. We found that CDP-choline ameliorated the disease course of experimental autoimmune encephalomyelitis and exerted beneficial effects on myelin, oligodendrocytes and axons. After cuprizone-induced demyelination, CDP-choline effectively enhanced myelin regeneration and reversed motor coordination deficits. The increased remyelination arose from an increase in the numbers of proliferating oligodendrocyte precursor cells and oligodendrocytes. Further in vitro studies suggest that this process is regulated by protein kinase C. We thus identified a new mechanism to enhance central nervous system remyelination via the choline pathway. Due to its regenerative action combined with an excellent safety profile, CDP-choline could become a promising substance for patients with multiple sclerosis as an add-on therapy.
EVALuna2:22341

Plectin-related scapuloperoneal myopathy with treatment-responsive myasthenic syndrome - Argente-Escrig, H.; Schultheis, D.; Kamm, L.; Schowalter, M.; Thiel, C.; Türk, M.; Clemen, C. S.; Muelas, N.; Castañón, M. J.; Wiche, G.; Herrmann, H.; Vilchez, J. J.; et al. (Neuropathology and Applied Neurobiology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Pointing in visual periphery: is DF's dorsal stream intact? - Hesse, Constanze; Ball, Keira; Schenk, Thomas (PLoS ONE, 2014)
Observations of the visual form agnosic patient DF have been highly influential in establishing the hypothesis that separate processing streams deal with vision for perception (ventral stream) and vision for action (dorsal stream). In this context, DF's preserved ability to perform visually-guided actions has been contrasted with the selective impairment of visuomotor performance in optic ataxia patients suffering from damage to dorsal stream areas. However, the recent finding that DF shows a thinning of the grey matter in the dorsal stream regions of both hemispheres in combination with the observation that her right-handed movements are impaired when they are performed in visual periphery has opened up the possibility that patient DF may potentially also be suffering from optic ataxia. If lesions to the posterior parietal cortex (dorsal stream) are bilateral, pointing and reaching deficits should be observed in both visual hemifields and for both hands when targets are viewed in visual periphery. Here, we tested DF's visuomotor performance when pointing with her left and her right hand toward targets presented in the left and the right visual field at three different visual eccentricities. Our results indicate that DF shows large and consistent impairments in all conditions. These findings imply that DF's dorsal stream atrophies are functionally relevant and hence challenge the idea that patient DF's seemingly normal visuomotor behaviour can be attributed to her intact dorsal stream. Instead, DF seems to be a patient who suffers from combined ventral and dorsal stream damage meaning that a new account is needed to explain why she shows such remarkably normal visuomotor behaviour in a number of tasks and conditions.
EVALuna2:22322

Position paper of a German interdisciplinary round table on future designs of trials on adjunctive treatment with antiseizure drugs - Hamer, Hajo; Holtkamp, Martin; Kaiser, Thomas; Fey, Susanne; Rozinat, Klaus; Mayer, Thomas; Schulze-Bonhage, Andreas (Seizure-European Journal of Epilepsy, 2020)
Purpose: Current trials on adjunctive treatment with antiseizure drugs often do not reveal results which are relevant for clinical practice. Method: Therefore, an interdisciplinary group of German experts discussed a new framework for future antiseizure drug (ASD) trials in adults. This group included members of the executive board of the German Society of Epileptology, of the German institutes for health technology assessment (HTA), of patient organizations and of drug manufacturers. Agreement was reached by consensus decision making after intensive discussion of the findings of a narrative review of the current literature. Results: The group jointly recommends that ASD trials in adults should be based on and include relevant patient groups, e.g. elderly patients and patients with relevant co-morbidities, should adopt a study duration of at least 12 months, should avoid placebo arms, should include active comparators of clinical relevance, may be designed as open label trials with blinded outcome measurements, should focus on patient relevant outcomes that reflect the impact of benefits and harms of treatments on daily living, such as seizure freedom and seizure severity as well as retention rate, functional outcomes and quality of life as compound measures, and should avoid arbitrary and non-sensitive primary endpoints such as dichotomized changes in seizure frequency. Conclusions: This paper focused on improved head-to-head trials on adjunctive treatment with antiseizure drugs. The group welcomes any further work and discussion to enhance future studies which can be applied to the entire spectrum of potentially meaningful study populations and outcomes.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Active comparator; Antiseizure drugs/ASD; Outcome; Placebo; Trials

Possible second motor neuron damage in neuromyelitis optica - Laemmer, A. B.; Maihöfner, Christian; Gölitz, Philipp; Schwab, Sibylle; Lee, D. H.; Linker, R. A.; Schramm, Axel (Clinical Neurophysiology, 2014)
EVALuna2:22245

Posterior circulation ischemic stroke not involving the brainstem is associated with cardiovascular autonomic dysfunction - Wang, Ruihao; Kohrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (European Journal of Neurology, 2022)
Background and purpose Ischemic stroke may induce cardiovascular autonomic dysfunction, but most previous studies have included patients with anterior circulation ischemic stroke or brainstem stroke. It remains unclear whether posterior circulation ischemic stroke (PCIS) without brainstem involvement also compromises cardiovascular autonomic modulation (CAM). Therefore, we aimed to assess CAM in PCIS patients with and without brainstem involvement. Methods In four subgroups of 61 PCIS patients (14 occipital lobe, 16 thalamic, 12 cerebellar, and 19 brainstem strokes) and 30 healthy controls, we recorded RR intervals (RRIs), systolic (SBP) and diastolic blood pressure (DBP), and respiration at supine rest during the first week after stroke onset. We calculated parameters reflecting total CAM (RRI-standard deviation [RRI-SD], RRI-total powers), predominantly sympathetic CAM (RRI-low-frequency [LF] powers and SBP-LF powers] and parasympathetic CAM (root mean square of successive RRI differences [RMSSD], RRI-high-frequency [HF] powers), sympathetic-parasympathetic balance (RRI-LF/HF ratios), and baroreflex sensitivity (BRS). Values were compared among the four PCIS groups and controls using one-way ANOVA Kruskal-Wallis tests, with post-hoc analyses. Significance was assumed for p < 0.05. Results In each PCIS subgroup, values for RRI, RRI-SD, RMSSD, RRI-HF powers, and BRS were significantly lower, while SBP-LF powers were higher than in the controls. Only in patients with occipital lobe stroke were RRI-LF/HF ratios significantly higher than in controls. Otherwise, autonomic variables did not differ among the four PCIS subgroups. Conclusions During the first week after stroke onset, our PCIS patients with occipital lobe, thalamic, cerebellar, or brainstem strokes all had reduced cardiovagal modulation, compromised baroreflex, and increased peripheral sympathetic modulation. The RRI-LF/HF ratios suggest that sympathetic predominance is slightly more prominent after occipital lobe stroke. PCIS may trigger cardiovascular autonomic dysfunction even without brainstem involvement.
CRIS-Team WoS Importer:2022-06-24

Post-Stroke Cardiovascular Complications and Neurogenic Cardiac Injury: JACC State-of-the-Art Review - Sposato, Luciano A.; Hilz, Max-Josef; Aspberg, Sara; Murthy, Santosh B.; Bahit, M. Cecilia; Hsieh, Cheng Yang; Sheppard, Mary N.; Scheitz, Jan F. (Journal of the American College of Cardiology, 2020)
Over 1.5 million deaths worldwide are caused by neurocardiogenic syndromes. Furthermore, the consequences of deleterious brain-heart interactions are not limited to fatal complications. Cardiac arrhythmias, heart failure, and nonfatal coronary syndromes are also common. The brain-heart axis is implicated in post-stroke cardiovascular complications known as the stroke-heart syndrome, sudden cardiac death, and Takotsubo syndrome, among other neurocardiogenic syndromes. Multiple pathophysiological mechanisms with the potential to be targeted with novel therapies have been identified in the last decade. In the present state-of-the-art review, we describe recent advances in the understanding of anatomical and functional aspects of the brain-heart axis, cardiovascular complications after stroke, and a comprehensive pathophysiological model of stroke-induced cardiac injury.
CRIS-Team Scopus Importer:2020-12-04
Keywords: cardiovascular; inflammation; MACE; neurocardiogenic; stroke

Potential of Sodium MRI as a Biomarker for Neurodegeneration and Neuroinflammation in Multiple Sclerosis - Huhn, Konstantin; Engelhorn, Tobias; Linker, Ralf A.; Nagel, Armin Michael (Frontiers in Neurology, 2019)
In multiple sclerosis (MS), experimental and ex vivo studies indicate that pathologic intra-and extracellular sodium accumulation may play a pivotal role in inflammatory as well as neurodegenerative processes. Yet, in vivo assessment of sodium in the microenvironment is hard to achieve. Here, sodium magnetic resonance imaging ((NaMRI)-Na-23) with its non-invasive properties offers a unique opportunity to further elucidate the effects of sodium disequilibrium in MS pathology in vivo in addition to regular proton based MRI. However, unfavorable physical properties and low in vivo concentrations of sodium ions resulting in low signal-to-noise-ratio (SNR) as well as low spatial resolution resulting in partial volume effects limited the application of (NaMRI)-Na-23. With the recent advent of high-field MRI scanners and more sophisticated sodium MRI acquisition techniques enabling better resolution and higher SNR, (NaMRI)-Na-23 revived. These studies revealed pathologic total sodium concentrations in MS brains now even allowing for the (partial) differentiation of intra-and extracellular sodium accumulation. Within this review we (1) demonstrate the physical basis and imaging techniques of (NaMRI)-Na-23 and (2) analyze the present and future clinical application of (NaMRI)-Na-23 focusing on the field of MS thus highlighting its potential as biomarker for neuroinflammation and -degeneration.
CRIS-Team WoS Importer:2019-02-22

Pre- and Postictal Changes in the Innate Immune System: Cause or Effect? - Lang, Johannes; Olmes, David G.; Proske, Manuel; Hagge, Mareike; Dogan Onugoren, Mujgan; Rothhammer, Veit; Schwab, Stefan; Hamer, Hajo (European neurology, 2021)
Introduction: Recent studies have shown that inflammatory processes might play a role in epileptogenesis. Their role in ictogenesis is much less clear. The aim of this study was to investigate peri-ictal changes of the innate immune system by analyzing changes of immune cells, as well as pro- and anti-inflammatory cytokines. Methods: Patients with active epilepsy admitted for video-EEG monitoring for presurgical evaluation were included. Blood was sampled every 20 min for 5 h on 3 consecutive days until a seizure occurred. After a seizure, additional samples were drawn immediately, as well as 1 and 24 h later. To analyze the different populations of peripheral blood mononuclear cells, all samples underwent FACS for CD3, CD4, CD8, CD56, CD14, CD16, and CD19. For cytokine analysis, we used a custom bead-based multiplex immunoassay for IFN-gamma, IL-1 beta, IL-1RA, IL-4, IL-6, IL-10, IL-12, IL-17, MCP-1, MIP-1 alpha, and TNF alpha. Results: Fourteen patients with focal seizures during the sampling period were included. Natural killer (NK) cells showed a negative correlation (rho = -0.3362, p = 0.0195) before seizure onset and an immediate increase to 1.95-fold afterward. T helper (T-H) and B cells decreased by 2 and 8%, respectively, in the immediate postictal interval. Nonclassical and intermediate monocytes decreased not until 1 day after the seizures, and cytotoxic T (T-C) cells showed a long-lasting postictal increase by 4%. IL-10 and MCP-1 increased significantly after seizures, and IL-12 decreased in the postictal phase. Discussion/Conclusion: Our study argues for a role of the innate immune system in the pre- and postictal phases. NK cells might be involved in preictal changes or be altered as an epiphenomenon in the immediate preictal interval.
CRIS-Team WoS Importer:2021-07-09

Prediction of Recurrent Ischemic Stroke Using Registry Data and Machine Learning Methods: The Erlangen Stroke Registry - Vodencarevic, Asmir; Weingärtner, Michael; Caro, J. Jaime; Ukalovic, Dubravka; Zimmermann-Rittereiser, Marcus; Schwab, Stefan; Kolominsky-Rabas, Peter (Stroke, 2022)
BACKGROUND: There have been multiple efforts toward individual prediction of recurrent strokes based on structured clinical and imaging data using machine learning algorithms. Some of these efforts resulted in relatively accurate prediction models. However, acquiring clinical and imaging data is typically possible at provider sites only and is associated with additional costs. Therefore, we developed recurrent stroke prediction models based solely on data easily obtained from the patient at home. METHODS: Data from 384 patients with ischemic stroke were obtained from the Erlangen Stroke Registry. Patients were followed at 3 and 12 months after first stroke and then annually, for about 2 years on average. Multiple machine learning algorithms were applied to train predictive models for estimating individual risk of recurrent stroke within 1 year. Double nested cross-validation was utilized for conservative performance estimation and models' learning capabilities were assessed by learning curves. Predicted probabilities were calibrated, and relative variable importance was assessed using explainable artificial intelligence techniques. RESULTS: The best model achieved the area under the curve of 0.70 (95% CI, 0.64-0.76) and relatively good probability calibration. The most predictive factors included patient's family and housing circumstances, rehabilitative measures, age, high calorie diet, systolic and diastolic blood pressures, percutaneous endoscopic gastrotomy, number of family doctor's home visits, and patient's mental state. CONCLUSIONS: Developing fairly accurate models for individual risk prediction of recurrent ischemic stroke within 1 year solely based on registry data is feasible. Such models could be applied in a home setting to provide an initial risk assessment and identify high-risk patients early.
CRIS-Team Scopus Importer:2022-07-08
Keywords: ischemic stroke; machine learning; probability; recurrence; registries

Predictive Value Of Preoperative Magnetoencephalography (MEG) For Seizure Outcome In Surgery Of Long Term Epilepsy Associated Tumors - Roessler, K.; Heynold, Elisabeth; Kasper, Burkhard; Coras, R.; Blumcke, I.; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Predictors of New Cerebral Microbleeds in Patients with Antiplatelet Drug Therapy - Wobith, Maria; Mayer, Christian; Belke, Marcus; Haag, Anja; Gerstner, Anja; Teepker, Michael; Strzelczyk, Adam; Werner, Rita; Hamer, Hajo; Rosenow, Felix; Menzler, Katja; Knake, Susanne (Journal of Stroke and Cerebrovascular Diseases, 2016)
Cerebral microbleeds (CMB) are associated with an increased risk for ischemic and especially hemorrhagic stroke. The aim of the present study is to identify patients at high risk for the development of new CMB after initiation of an antiplatelet drug therapy.Patients received magnetic resonance imaging (MRI) within 1 week after initiation of an antiplatelet drug treatment due to a first ischemic stroke (n = 58) and after a follow-up period of 6 months (n = 40). We documented the presence and the number of CMB at baseline and follow-up and analyzed the influence of possible risk factors including vascular risk factors, stroke etiology, and number of CMB at baseline using stepwise logistic regression and Spearman's correlation coefficient. We compared progression rates of CMB in relation to each risk factor using the Mann-Whitney U-test.The logistic regression model could correctly predict the presence of CMB in 70.7% of patients at baseline and 80% at follow-up. The model correctly identified 85% of patients with new CMB. We observed progression of CMB in 40% of the patients. The overall progression rate was .8 CMB per patient. The progression rate was significantly influenced by age more than 70 years and atherothrombotic stroke. The number of new CMB correlated significantly with the number of CMB at baseline.We found several predictors of CMB after initiation of antiplatelet drug therapy. The results help to identify patients who need closer monitoring and thorough control of risk factors in order to lower the risk of new CMB and associated complications.
EVALuna2:22489

Presence of Concomitant Systemic Cancer is Not Associated with Worse Functional Long-Term Outcome in Patients with Intracerebral Hemorrhage - Spuergel, Maximilian I.; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Hartwich, Julius; Giede-Jeppe, Antje; Madzar, Dominik; Beuscher, Vanessa D.; Lücking, Hannes; Struffert, Tobias; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2017)
Data on clinical characteristics and outcome of patients with intracerebral hemorrhage (ICH) and concomitant systemic cancer disease are very limited.Nine hundred and seventy three consecutive primary ICH patients were analyzed using our prospective institutional registry over a period of 9 years (2006-2014). We compared clinical and radiological parameters as well as outcome - scored using the modified Rankin Scale (mRS) and analyzed in a dichotomized fashion as favorable outcome (mRS = 0-3) and unfavorable outcome (mRS = 4-6) - of ICH patients with and without cancer. Relevant imbalances in baseline clinical and radiological characteristics were adjusted using propensity score (PS) matching.Prevalence of systemic cancer among patients with ICH was 8.5% (83/973). ICH patients with cancer were older (77 [70-82] vs. 72 [63-80] years; p = 0.002), had more often prior renal dysfunction (19/83 [22.9%] vs.107/890 [12.0%]; p = 0.005), and smaller hemorrhage volumes (10.1 [4.8-24.3] vs. 15.3 [5.4-42.9] mL; p = 0.017). After PS-matching there were no significant differences neither in mortality nor in functional outcome both at 3 months (mortality: 33/81 [40.7%] vs. 55/158 [34.8%]; p = 0.368; mRS = 0-3: 28/81 [34.6%] vs. 52/158 [32.9%]; p = 0.797) and 12 months (mortality: 39/78 [50.0%] vs. 70/150 [46.7%]; p = 0.633; mRS = 0-3: 25/78 [32.1%] vs. 53/150 [35.3%]; p = 0.620) among patients with and without concomitant systemic cancer. ICH volume tended to be highest in patients with hematooncologic malignancy and smallest in urothelial cancer.Patients with ICH and concomitant systemic cancer on average are older; however, they show smaller ICH volumes compared to patients without cancer. Yet, mortality and functional outcome is not different in ICH patients with and without cancer. Thus, the clinical history or the de novo diagnosis of concomitant malignancies in ICH patients should not lead to unjustified treatment restrictions.
EVALuna2:22553

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Prevalence, utilization, and costs of antiepileptic drugs for epilepsy in Germany – a nationwide population-based study in children and adults - Hamer, Hajo; Dodel, Richard; Strzelczyk, Adam; Balzer-Geldsetzer, Monika; Reese, Jens-Peter; Schöffski, Oliver; Graf, Wolfgang; Schwab, Stefan; Knake, Susanne; Oertel, Wolfgang; Rosenow, Felix; Kostev, Karel (Journal of Neurology, 2012)
<h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);"> Nationwide analyses of drug use can provide a prevalence estimate of the underlying disease and can help in understanding the characteristics of treatment. This study aimed for such analyses regarding the utilization of antiepileptic drugs (AED) for epilepsy in Germany. In 2009, all 4,115,705 AED prescriptions of all German patients with statutory health insurance (70,011,508 persons) were retrospectively analyzed. The IMS® LRx database served as data source, which accesses nationwide pharmacy data centers processing all German prescription data. To establish the age and sex-specific percentage of patients taking AED because of epilepsy, we used a second database, Disease Analyzer®, which covered a representative sample of the German population (7.2 million patients) and contained ICD10 codes alongside with prescription data. The period prevalence of patients taking AED because of epilepsy was 9.1/1,000 (children/adolescents: 5.2/1,000; elderly: 12.5/1,000). Of the patients, 83.1 % took at least one of four AED: valproate (29.8 %), carbamazepine (26.4 %), lamotrigine (21.4 %), and levetiracetam (16.9 %). Oxcarbazepine and sultiame were popular with pediatricians. Elderly patients frequently received phenytoin and primidone. More than half of the patients were treated by family physicians; 68 % took AED in monotherapy and 7.9 % received >2 AED (children/adolescents: 12.5 %). The costs for AED prescribed for epilepsy amounted to €285.1 Mio (median AED costs/patient: €158/a). The German 2009 prevalence of epileptic patients taking AED was 9.1/1,000. Family physicians cared for the majority of patients. Prevalence and prescribing patterns changed with age. Costs of AED against epilepsy added up to 1 % of total medication costs in Germany.
WiSo-Import:2015-03-26:4184
Keywords: Epilepsy; Prevalence; Antiepileptic drugs; Costs; Children; Elderly

Prognostic Accuracy of CTP Summary Maps in Patients with Large Vessel Occlusive Stroke and Poor Revascularization after Mechanical Thrombectomy-Comparison of Three Automated Perfusion Software Applications - Mühlen, Iris; Borutta, Matthias; Siedler, Gabriela; Engelhorn, Tobias; Hock, Stefan; Knott, Michael; Hölter, Philip; Volbers, Bastian; Schwab, Stefan; Dörfler, Arnd (Tomography, 2022)
Background: Innovative automated perfusion software solutions offer support in the management of acute stroke by providing information about the infarct core and penumbra. While the performance of different software solutions has mainly been investigated in patients with successful recanalization, the prognostic accuracy of the hypoperfusion maps in cases of futile recanalization has hardly been validated. Methods: In 39 patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation and poor revascularization (thrombolysis in cerebral infarction (TICI) 0-2a) after mechanical thrombectomy (MT), hypoperfusion analysis was performed using three different automated perfusion software solutions (A: RAPID, B: Brainomix e-CTP, C: Syngo.via). The hypoperfusion volumes (HV) as Tmax > 6 s were compared with the final infarct volumes (FIV) on follow-up CT 36-48 h after futile recanalization. Bland-Altman analysis was applied to display the levels of agreement and to evaluate systematic differences. Based on the median hypoperfusion intensity ratio (HIR, volumetric ratio of tissue with a Tmax > 10 s and Tmax > 6 s) patients were dichotomized into high- and low-HIR groups. Subgroup analysis with favorable (<0.6) and unfavorable (>= 0.6) HIR was performed with respect to the FIV. HIR was correlated to clinical baseline and outcome parameters using Pearson's correlation. Results: Overall, there was good correlation without significant differences between the HVs and the FIVs with package A (r = 0.78, p < 0.001) being slightly superior to B and C. However, levels of agreement were very wide for all software applications in Bland-Altman analysis. In cases of large infarcts exceeding 150 mL the performance of the automated software solutions generally decreased. Subgroup analysis revealed the FIV to be generally underestimated in patients with HIR >= 0.6 (p < 0.05). In the subgroup with favorable HIR, however, there was a trend towards an overestimation of the FIV. Nevertheless, packages A and B showed good correlation between the HVs and FIVs without significant differences (p > 0.2), while only package C significantly overestimated the FIV (-54.6 +/- 56.0 mL, p = 0.001). The rate of modified Rankin Scale (mRS) 0-3 after 3 months was significantly higher in favorable vs. unfavorable HIR (42.1% vs. 13.3%, p = 0.02). Lower HIR was associated with higher Alberta Stroke Program Early CT Score (ASPECTS) at presentation and on follow-up imaging, lower risk of malignant edema, and better outcome (p < 0.05). Conclusion: Overall, the performance of the automated perfusion software solutions to predict the FIV after futile recanalization is good, with decreasing accuracy in large infarcts exceeding 150 mL. However, depending on the HIR, FIV can be significantly over- and underestimated, with Syngo showing the widest range. Our results indicate that the HIR can serve as valuable parameter for outcome predictions and facilitate the decision whether or not to perform MT in delicate cases.
CRIS-Team WoS Importer:2022-07-08

Programmed Cell Death after Intracerebral Hemorrhage - Bobinger, Tobias; Burkardt, Petra; Huttner, Hagen; Manaenko, Anatol (Current Neuropharmacology, 2018)
BACKGROUND: Intracerebral hemorrhage (ICH) accounts for up to 15% of all strokes and is characterized by high rates of mortality and morbidity. The post-ICH brain injury can be distinguished in 1) primary, which are caused by disruption and mechanical deformation of brain tissue due to hematoma growth and 2) secondary, which are induced by microglia activation, mitochondrial dysfunction, neurotransmitter and inflammatory mediator release. Although these events typically lead to necrosis, the occurrence of programmed cell death has also been reported after ICH. METHODS: We reviewed recent publications describing advance in pre- and clinic ICH research. RESULTS: At present, treatment of ICH patients is based on oral anticoagulant reversal, management of blood pressure and other medical complications. Several pre-clinical studies showed promising results and demonstrated that anti-oxidative and anti-inflammatory treatments reduced neuronal cell death, however, to date, all of these attempts have failed in randomized controlled clinical trials. Yet, the time frame of administration may be crucial in translation from animal to clinical studies. Furthermore, the latest pre-clinical research points toward the existence of other, apoptosisunrelated forms kinds of programmed cell death. CONCLUSION: Our review summarizes current knowledge of pathways leading to programmed cell death after ICH in addition to data from clinical trials. Some of the pre-clinical results have not yet demonstrated clinical confirmation, however they significantly contribute to our understanding of post-ICH pathology and can contribute to development of new therapeutic approaches, decreasing mortality and improving ICH patients' quality of life.
EVALuna2:36546

PROPHYLACTIC AND PROLONGED HYPOTHERMIA IN POOR-GRADESAH REDUCES DEGREE OF VASOSPASM AND RATE OF DELAYED CEREBRAL INFARCTIONS - Kuramatsu, J. B.; Kollmar, Rainer; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22484

Propionic Acid Rescues High-Fat Diet Enhanced Immunopathology in Autoimmunity via Effects on Th17 Responses - Haase, Stefanie; Mäuerer, Jonas; Duscha, Alexander; Lee, De-Hyung; Balogh, Andras; Gold, Ralf; Mueller, Dominik N.; Haghikia, Aiden; Linker, Ralf A. (Frontiers in Immunology, 2021)
High-fat diets (HFD) are linked to obesity and associated comorbidities and induce pathogenic T helper (Th) 17 cells while decreasing regulatory T cells (Treg). This pro-inflammatory environment also aggravates immunopathology in experimental autoimmune encephalomyelitis (EAE) as a prototype model of T cell mediated autoimmunity. The strong association of HFD to obesity as well as the increasing risk of autoimmunity in the Western world stresses the importance to identify compounds that counteract this metabolically induced pro-inflammatory state in humans. One prominent candidate is the short-chain fatty acid propionate (PA) that was recently identified as potent therapy in the autoimmune disease multiple sclerosis by enhancing Treg cell frequencies and functionality. Mice were fed a HFD rich lauric acid (LA) and treated either with water or PA during MOG35-55-EAE. We analyzed Treg and Th17 cell frequencies in different tissues, antigen-specific cell proliferation and cytokine secretion, investigated Treg cell functionality by suppression assays and IL-10 signaling blockade and employed Western blotting to investigate the involvement of p38-MAPK signaling. Finally, we performed an explorative study in obese and non-obese MS patients, investigating fecal PA concentrations as well as peripheral Th17 and Treg frequencies before and after 90 days of daily PA intake. As compared to controls, mice on a HFD displayed a more severe course of EAE with enhanced demyelination and immune cell infiltration in the spinal cord. PA treatment prevented this disease enhancing effect of HFD by inhibiting Th17 mediated inflammatory processes in the gut and the spleen. Blocking experiments and signaling studies revealed p38-MAPK and IL-10 signaling as important targets linking the beneficial effects of PA treatment and reduced inflammation due to enhanced Treg frequency and functionality. An explorative study in a small group of MS patients revealed reduced PA concentrations in fecal samples of obese MS patients compared to the non-obese group, coinciding with increased Th17 but decreased Treg cells in obese patients. Importantly, PA intake could restore the Treg-Th17 homeostasis. Our data thus identify Th17 responses as an important target for the beneficial effects of PA in HFD and obesity in addition to the recently identified potential of PA as a Treg inducing therapy in T cell mediated autoimmunity.
CRIS-Team Scopus Importer:2021-06-25
Keywords: EAE; high-fat diet; immunosuppression; multiple sclerosis; propionic acid

Propofol-related urine discoloration in a patient with fatal atypical intracerebral hemorrhage treated with hypothermia - Regensburger, Martin; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (SpringerPlus, 2014)
Introduction: Mild therapeutic hypothermia is an increasingly recognised treatment option to reduce perihemorrhagic edema in severe intracerebral hemorrhage. Case description: We report the case of a 77-year old woman with atypical intracerebral hemorrhage that was treated with mild hypothermia in addition to osmotic therapy. The patient’s urine subsequently showed a green discoloration. Urine discoloration was completely reversible upon discontinuation of propofol. Discussion and evaluation: Propofol-related urine discoloration may have been provoked by hypothermia. Due to the benign nature of this side effect, propofol should be stopped and gastrointestinal function should be supported. Conclusion: More studies are needed to show a causal role of hypothermia and related decreased enzymatic function.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Enterohepatic circulation; Hypothermia; Intracerebral hemorrhage; Liver enzyme function; Urine discoloration

Proposal: different types of alteration and loss of consciousness in epilepsy - Lueders, Hans; Amina, Shahram; Bailey, Christopher; Baumgartner, Christoph; Benbadis, Selim; Bermeo, Adriana; Carreno, Maria; Devereaux, Michael; Diehl, Beate; Eccher, Matthew; Edwards, Jonathan; Fastenau, Philip; et al. (Epilepsia, 2014)
There are at least five types of alterations of consciousness that occur during epileptic seizures: auras with illusions or hallucinations, dyscognitive seizures, epileptic delirium, dialeptic seizures, and epileptic coma. Each of these types of alterations of consciousness has a specific semiology and a distinct pathophysiologic mechanism. In this proposal we emphasize the need to clearly define each of these alterations/loss of consciousness and to apply this terminology in semiologic descriptions and classifications of epileptic seizures. The proposal is a consensus opinion of experienced epileptologists, and it is hoped that it will lead to systematic studies that will allow a scientific characterization of the different types of alterations/loss of consciousness described in this article.
EVALuna2:22297

Proposal of a rating scale to recognize Fabry disease in patients with nonspecific gastrointestinal symptoms - Hilz, Max-Josef; Arbustini, Eloisa; Dagna, Lorenzo; Gasbarrini, Antonio; Goizet, Cyril; Lacombe, Didier; Liguori, Rocco; Manna, Raffaele; Politei, Juan; Spada, Marco; Burlina, Alessandro (2018)
EVALuna2:201957

Protective Functions of Reactive Astrocytes Following Central Nervous System Insult - Linnerbauer, Mathias; Rothhammer, Veit (Frontiers in Immunology, 2020)
Astrocytes play important roles in numerous central nervous system disorders including autoimmune inflammatory, hypoxic, and degenerative diseases such as Multiple Sclerosis, ischemic stroke, and Alzheimer’s disease. Depending on the spatial and temporal context, activated astrocytes may contribute to the pathogenesis, progression, and recovery of disease. Recent progress in the dissection of transcriptional responses to varying forms of central nervous system insult has shed light on the mechanisms that govern the complexity of reactive astrocyte functions. While a large body of research focuses on the pathogenic effects of reactive astrocytes, little is known about how they limit inflammation and contribute to tissue regeneration. However, these protective astrocyte pathways might be of relevance for the understanding of the underlying pathology in disease and may lead to novel targeted approaches to treat autoimmune inflammatory and degenerative disorders of the central nervous system. In this review article, we have revisited the emerging concept of protective astrocyte functions and discuss their role in the recovery from inflammatory and ischemic disease as well as their role in degenerative disorders. Focusing on soluble astrocyte derived mediators, we aggregate the existing knowledge on astrocyte functions in the maintenance of homeostasis as well as their reparative and tissue-protective function after acute lesions and in neurodegenerative disorders. Finally, we give an outlook of how these mediators may guide future therapeutic strategies to tackle yet untreatable disorders of the central nervous system.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Alzheimer’s disease; astrocytes; astrogliosis; ischemic stroke; multiple sclerosis; neurodegeneration; neuroinflammation; protective

Psychogenic nonepileptic seizures: clinical characteristics and outcome - Volbers, Bastian; Walther, Katrin; Kurzbuch, Katrin; Erdmann, Laura; Gollwitzer, Stephanie; Lang, Johannes; Onugoren, Muejgan Dogan; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Brain and Behavior, 2022)
Background: Clinical characteristics, outpatient situation, and outcome in patients with psychogenic nonepileptic seizures (PNES) remain to be elucidated. Methods: Patients diagnosed with PNES after video-electroencephalography (EEG) monitoring (VEM) 03/2000–01/2016 at the Erlangen Epilepsy Center were surveyed between June 2016 and February 2017. Primary outcome was PNES cessation defined as no PNES episodes within > = 12 months prior to the interview. Secondary outcome variables included quality of life (QoL) and dependency. Sensitivity analysis included patients with proven PNES during VEM without comorbid epilepsy. Results: Ninety-nine patients were included (median age 38 (interquartile range (IQR 29–52)) years; 68 (69%) females, follow-up 4 (IQR 2.1–7.7) years). Twenty-eight (28%) patients suffered from comorbid epilepsy. Twenty-five (25%) patients reported PNES cessation. Older age at symptom onset (odds ratio (OR) related to PNES cessation: 0.95 (95% CI 0.90–0.99)), comorbid epilepsy (OR 0.16 (95% CI 0.03–0.83)), anxiety disorder (OR 0.15 (95% CI 0.04–0.61)), and tongue biting (OR 0.22 (95% CI 0.03–0.91)) remained independently associated with ongoing PNES activity after adjustment. Sensitivity analysis (n = 63) revealed depressive disorder (OR 0.03 (95% CI 0.003–0.34)) instead of anxiety as independent predictor, while this seemed relevant only in patients older than 26 years at onset (OR 0.04 (95% CI 0.002–0.78) versus OR 0.21 (95% CI 0.02–1.84) in patients younger than 26 years). PNES cessation was associated with increased median QoL (8 (IQR 7–9) versus 5.5 (IQR 4–7); p <.001) and an increased frequency of financial independency (14 (56%) versus 21 (28%); p =.01). Conclusions: We found poor outcomes in PNES especially in older patients at onset with comorbid depressive disorder. Comorbid epilepsy also seems to be a major risk factor of ongoing PNES activity, which in turn affects patients’ daily living.
CRIS-Team Scopus Importer:2022-04-22
Keywords: activities of daily living; mental disorders; nonepileptic seizures; patient-relevant outcome; prognosis

Psychological distress after subarachnoid hemorrhage: patient support groups can help us better detect it - Noble, Adam J.; Schenk, Thomas (Journal of the Neurological Sciences, 2014)
One-quarter of subarachnoid hemorrhage (SAH) survivors develop psychological distress. This impedes recovery. Limitations to existing care pathways mean that distress often goes undetected. We need to know how to better identify it.Support groups for SAH exist in many countries. No research has been conducted on them. Distressed patients might be concentrated amongst them. If true, this could offer a low-cost way to help better identify distress. We conducted the first study to determine which survivors access such groups, their needs and compared them to the wider SAH population.414 UK SAH survivors affiliated with national support groups were recruited. They completed a questionnaire, including validated measures of anxiety, depression and posttraumatic stress, and asked whether they had been examined or treated for distress post-SAH. Regression established factors associated with treatment.Participants' mean age at SAH was 44.6 and 312 (75%) were female. Most (68.4%) reported a cerebral aneurysm as their SAH's cause and were treated with coiling. Median years since SAH were three. Over three-quarters of participants were experiencing clinical distress. Regression found distressed participants were twice as likely to have been examined and treated for distress. Nevertheless, 47% of distressed participants had not been examined for distress post-SAH and 55% had not been offered treatment.Psychological distress is overrepresented amongst support groups. Members also tend to be younger and female. Establishing referral pathways from support groups to health-systems might improve detection of distress and allow the benefits of improved survival from SAH to be fully realized.
EVALuna2:22320

Psychological long-term outcome in patients with psychogenic nonepileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Kasper, Burkhard; Kurzbuch, Katrin; Lang, Johannes; Schwab, Stefan; Schwarz, Michael; Hamer, Hajo (Epilepsia, 2019)
Objective To examine the long-term outcome of psychological status, personality, and health-related quality of life (HRQoL) in patients with psychogenic nonepileptic seizures (PNES) and to define predictors of favorable outcome of cessation of PNES. Method Patients diagnosed with PNES during video-electroencephalography (EEG) monitoring at the Erlangen Epilepsy Center were contacted 1-16 years after communicating the diagnosis. Follow-up information from each participant was obtained by interview (PNES outcome) and by self-reported questionnaires of psychological symptoms (Beck Depression Inventory-II, Symptom Checklist-90-Standard, Dissociative Symptoms questionnaire), personality traits (Freiburg Personality Inventory-Revised), and HRQoL (36-Item Short Form Health Survey). Results Fifty-two patients participated in the study (mean age +/- standard deviation [SD] 40.5 +/- 14.0 years; 75% female, follow-up: 5.3 +/- 4.2 years). Nineteen patients (37%) were free of PNES for the past 12 months. Patients with persisting PNES were older at disease onset (32.9 vs 22.3 years, P < 0.01) and diagnosis (40.5 vs 27.2 years, P < 0.001), and showed worse psychological functioning, lower extraversion and life satisfaction, and higher inhibitedness and worse HRQoL than PNES-free patients. Patients with cessation of PNES were within the normal range in all dimensions. Cessation of PNES was best predicted by younger age at PNES onset and higher extraversion. Significance Outcome of PNES is poor, psychopathology is high, and HRQoL is low in patients with persistent PNES but may normalize with PNES cessation. High introversion and older age at PNES onset are risk factors for persistent PNES.
CRIS-Team WoS Importer:2019-04-16

Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life

Psychosocial outcome in epilepsy after extratemporal surgery - Walther, Katrin; Onugoren, Muejgan Dogan; Buchfelder, Michael; Gollwitzer, Stephanie; Graf, Wolfgang; Kasper, Burkhard; Kriwy, Peter; Kurzbuch, Katrin; Lang, Johannes; Roessler, Karl; Schwab, Stefan; Schwarz, Michael; et al. (Epilepsy and Behavior, 2018)
OBJECTIVE: Only limited data exist on psychosocial long-term outcome after epilepsy surgery in patients with extratemporal epilepsy. The aim of this study was to investigate psychosocial outcome after extratemporal epilepsy surgery and to assess factors predicting favorable outcome. METHOD: Sixty-five out of 104 eligible patients who had undergone extratemporal epilepsy surgery at our epilepsy center between 1990 and 2015 (mean age: 42.2. years; 75% of the resections in the frontal lobe) completed a questionnaire asking about seizure status, employment status, marital and living situation, driving status, depressive symptoms, and quality of life (QOL). Follow-up was on average 9.2years after surgery (range: 1-26years). RESULTS: Thirty-eight (58%) patients were free of disabling seizures (Engel class I), and 28 (43%) have not experienced any seizures after surgery (Engel class IA). Employment rate in the primary labor market remained at 45%, but more patients lost employment (14%) than gained employment (8%). Postoperative employment was predicted by preoperative employment (p=.007), seizure freedom (p=.025), older age at seizure onset (p=.018), younger age at follow-up (p=.035), and female gender (p=.048). Seizure-free patients were more likely to be driving; have a partner, particularly in males; and have lower depressive scores. Quality of life at follow-up was best predicted by employment (p=.012), partnership (p=.025), and seizure freedom (p=.025). In contrast, recurrence of seizures and early seizure onset were associated with poor psychosocial outcome, particularly in men. CONCLUSION: The study provides support that extratemporal surgery can lead to improved QOL and favorable psychosocial outcome. Seizure freedom is important but not the only determinant of good psychosocial outcome.
EVALuna2:35520

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity

Quality of life and correlating factors in children, adolescents with epilepsy, and their caregivers: A cross-sectional multicenter study from Germany - Riechmann, Janna; Willems, Laurent M.; Boor, Rainer; Kieslich, Matthias; Knake, Susanne; Langner, Cornelia; Neubauer, Bernd A.; Oberman, Bettina; Philippi, Heike; Reese, Jens P.; Rochel, Michael; Schubert-Bast, Susanne; et al. (Seizure-European Journal of Epilepsy, 2019)
Purpose: To identify factors correlating with poorer quality of life (QoL) in children and adolescents with epilepsy and regarding QoL and depression of their caregivers in Germany. Method: A cross-sectional multicenter study on QoL and depression was performed in two representative German states (Hessen and Schleswig-Holstein). Variance analysis, linear regression, and bivariate correlation were used to identify correlating factors for poorer QoL and symptoms of depression. Results: Data from 489 children and adolescents (mean age 10.4 ± 4.2 years, range 0.5–17.8; 54.0% male) and their caregivers were collected. We identified missing seizure freedom (p = 0.046), concomitant diseases (p = 0.007), hospitalization (p = 0.049), recent status epilepticus (p = 0.035), living in a nursing home or with foster parents (p = 0.049), and relevant degree of disability (p = 0.007) to correlate with poorer QoL in children and adolescents with epilepsy. Poorer QoL of caregivers was associated with longer disease duration (p = 0.004), non-idiopathic (mainly structural-metabolic) epilepsy (p = 0.003), ongoing seizures (p = 0.003), concomitant diseases (p = 0.003), relevant disability (p = 0.003), or status epilepticus (p = 0.003) as well as with unemployment of the primary caretaker (p = 0.010). Symptoms of depression of caregivers were associated with non-idiopathic epilepsy (p = 0.003), concomitant diseases (p = 0.003), missing seizure freedom (p = 0.007), status epilepticus (p = 0.004), or a relevant disability (p = 0.004) of their ward. A poorer QoL value of the children and adolescents correlated with a poorer QoL value of the caregivers (p < 0.001). Conclusions: Epilepsy shows a considerable impact on QoL and symptoms of depression. Early and effective therapy should focus on reduction of seizure frequency and the probability for developing status epilepticus. Furthermore, comprehensive care should pay attention at comorbidities, consequences of disability and dependency on others.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Anticonvulsants; Antiepileptic drug; Depression; Seizure; Status epilepticus

Quantitative 1H and 23Na muscle MRI in Facioscapulohumeral muscular dystrophy patients - Gerhalter, Teresa; Marty, Benjamin; Gast, Lena; Porzelt, Katharina; Heiß, Rafael; Uder, Michael; Schwab, Stefan; Carlier, Pierre G.; Nagel, Armin Michael; Türk, Matthias (Journal of Neurology, 2020)
Objective: Our aim was to assess the role of quantitative 1H and 23Na MRI methods in providing imaging biomarkers of disease activity and severity in patients with Facioscapulohumeral muscular dystrophy (FSHD). Methods: We imaged the lower leg muscles of 19 FSHD patients and 12 controls with a multimodal MRI protocol to obtain STIR-T2w images, fat fraction (FF), water T2 (wT2), water T1 (wT1), tissue sodium concentration (TSC), and intracellular-weighted sodium signal (inversion recovery (IR) and triple quantum filter (TQF) sequence). In addition, the FSHD patients underwent muscle strength testing. Results: Imaging biomarkers related with water mobility (wT1 and wT2) and ion homeostasis (TSC, IR, TQF) were increased in muscles of FSHD patients. Muscle groups with FF > 10% had higher wT2, wT1, TSC, IR, and TQF values than muscles with FF < 10%. Muscles with FF < 10% resembled muscles of healthy controls for these MRI disease activity measures. However, wT1 was increased in few muscles without fat replacement. Furthermore, few STIR-negative muscles (n = 11/76) exhibited increased wT1, TSC, IR or TQF. Increased wT1 as well as 23Na signals were also present in muscles with normal wT2. Muscle strength was related to the mean FF and all imaging biomarkers of tibialis anterior except wT2 were correlated with dorsal flexion. Conclusion: The newly evaluated imaging biomarkers related with water mobility (wT1) and ion homeostasis (TSC, IR, TQF) showed different patterns compared to the established markers like FF in muscles of FSHD patients. These quantitative biomarkers could thus contain valuable complementary information for the early characterization of disease progression.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Facioscapulohumeral muscular dystrophy; Quantitative MRI; Sodium MRI; Triple quantum filter; Water T

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage - Volbers, Bastian; Mennecke, Angelika; Kästle, Nicola; Huttner, Hagen; Schwab, Stefan; Schmidt, Manuel; Engelhorn, Tobias Martin; Dörfler, Arnd (Translational Stroke Research, 2020)
Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic reconstruction was performed using DSI Studio, and quantitative anisotropy (QA) was calculated. The CST was reconstructed based on QA. The dichotomized modified Rankin Scale score on day 90 (favorable outcome = 0–2) and Barthel Index (favorable recovery = 100 on day 90 or improvement between discharge and day 90 > 60%) were assessed. Thirty-three patients, median age 72 years (interquartile range (IQR) 64–83), 21 female (64%), 21 (64%) with lobar hemorrhage, median ICH volume on admission 15.0 (IQR 7.0–27.4) mL, were included. Sixteen patients (48%) had a favorable outcome and 24 (73%) had a favorable recovery. The mean number of ipsilesional reconstructed CST fiber pathways was higher in patients with favorable outcomes (153 (standard deviation (SD) 103) vs. 60 (SD 39), p = 0.003) and predicted outcome after adjustment (Exp(B) = 1.016 (95% CI = 1.002–1.030)). QA in the ipsilesional posterior limb of the internal capsule showed a trend towards an association with favorable outcome (Exp(B) = 1.194 (95% CI = 0.991–1.439 (adjusted))). The total (ipsilesional + contralesional) number of reconstructed fiber pathways was associated with favorable recovery (Exp(B) = 1.025 (95% CI = 1.003–1.047 (adjusted))). Quantitative tractography parameters assessed in the acute phase of ICH may represent a promising predictor of long-term outcome and recovery. This might facilitate prognostic evaluation and organization of rehabilitation.
CRIS-Team Scopus Importer:2020-10-02
Keywords: All rehabilitation; DWI; Intracerebral hemorrhage; MRI; Outcome research

Quantitative EEG After Subarachnoid Hemorrhage Predicts Long-Term Functional Outcome - Gollwitzer, Stephanie; Müller, Tamara; Hopfengärtner, Rüdiger; Rampp, Stephan; Merkel, Jasmin; Hagge, Mareike; Jukic, Jelena; Lang, Johannes; Madžar, Dominik; Onugoren, Müjgan Dogan; Huttner, Hagen; Schwab, Stefan; et al. (Journal of Clinical Neurophysiology, 2019)
PURPOSE: Delayed cerebral ischemia is a major complication after subarachnoid hemorrhage. Our previous study showed that alpha power reduction in continuous quantitative EEG predicts delayed cerebral ischemia. In this prospective cohort, we aimed to determine the prognostic value of alpha power in quantitative EEG for the long-term outcome of patients with subarachnoid hemorrhage. METHODS: Adult patients with nontraumatic subarachnoid hemorrhage were included if admitted early enough for EEG to start within 72 hours after symptom onset. Continuous six-channel EEG was applied. Unselected EEG signals underwent automated artifact rejection, power spectral analysis, and detrending. Alpha power decline of ≥40% for ≥5 hours was defined as critical EEG event based on previous findings. Six-month outcome was obtained using the modified Rankin scale. RESULTS: Twenty-two patients were included (14 male; mean age, 59 years; Hunt and Hess grade I-IV; duration of EEG monitoring, median 14 days). Poor outcome (modified Rankin scale, 2-5) was noted in 11 of 16 patients (69%) with critical EEG events. All six patients (100%) without EEG events achieved an excellent outcome (modified Rankin scale 0, 1) (P = 0.0062; sensitivity 100%, specificity 54.5%). Vasospasm detected with transcranial Doppler/Duplex sonography appeared 1.5 days after EEG events and showed weaker association with outcome (P = 0.035; sensitivity 100%, specificity 45.5%). There was no significant association between EEG events and ischemic lesions on imaging (P = 0.1). Also, no association between ischemic lesions and outcome was seen (P = 0.64). CONCLUSIONS: Stable alpha power in quantitative EEG reflects successful therapy and predicts good functional outcome after subarachnoid hemorrhage. Critical alpha power reduction indicates an increased risk of poor functional outcome.
CRIS-Team Scopus Importer:2019-05-03

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

Radiopacity of intracerebral hemorrhage correlates with perihemorrhagic edema - Wagner, Irina; Volbers, Bastian; Hilz, Max-Josef; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background: Experimental evidence indicates that iron plays a key role in edema formation after intracerebral hemorrhage (ICH). We investigated the relationship between ICH radiopacity on CT as a marker of hematoma iron content and perihemorrhagic edema (PHE) after ICH. Methods: We retrospectively investigated patients with spontaneous lobar and ganglionic supratentorial ICH who received follow-up CT scans during the first 7days after symptom onset (d1, d2-4, d5-7). Measurements of ICH and edema volumes were taken using a semiautomatic threshold-based volumetric algorithm. Radiopacity of the blood clot was determined using the mean Hounsfield unit (HU) count of the ICH. Results: A total of 117 patients aged 71.92±11.55years with spontaneous ICH (34.63±32.44ml) were included in the analysis. Mean ICH radiopacity was 59.7±3.4HU. We found significantly larger relative PHE at d2-4 (1.7±0.9 vs. 1.3±0.8; P=0.032) and d5-7 (2.0±1.3 vs. 1.3±0.9; P=0.007) and larger peak relative PHE (2.3±1.6 vs. 1.6±1.1; P=0.006) in patients with ICH radiopacity >60HU (n=59), as compared to patients with ICH radiopacity <60HU (n=58). Conclusions: Higher ICH radiopacity, reflecting higher in vivo hematoma iron content, is associated with more PHE after ICH. © 2011 The Author(s). European Journal of Neurology © 2011 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Intracerebral hemorrhage; Perihemorrhagic edema; Radiopacity

Rapid recovery of poststroke cardiac autonomic dysfunction: Causes to be considered - Wang, Ruihao; Moeller, Sebastian; Akhundova, Aynur; Marthol, Harald; Kollmar, Rainer; Köhrmann, Martin; Hilz, Max-Josef (European Journal of Neurology, 2023)
Background and purpose: Acute stroke frequently causes cardiovascular–autonomic dysfunction (CAD). Studies of CAD recovery are inconclusive, whereas poststroke arrhythmias may wane within 72 h. We evaluated whether poststroke CAD recovers within 72 h upon stroke onset in association with neurological improvement or increased use of cardiovascular medication. Methods: In 50 ischemic stroke patients (68 ± 13 years old) who—prior to hospital-admission—had no known diseases nor took medication affecting autonomic modulation, we assessed National Institutes of Health Stroke Scale (NIHSS) scores, RR intervals (RRIs), systolic and diastolic blood pressure (BP), respiration rate, parameters reflecting total autonomic modulation (RRI SD, RRI total powers), sympathetic modulation (RRI low-frequency powers, systolic BP low-frequency powers), and parasympathetic modulation (square root of mean squared differences of successive RRIs [RMSSD], RRI high-frequency powers), and baroreflex sensitivity within 24 h (Assessment 1) and 72 h after stroke onset (Assessment 2) and compared data to those of 31 healthy controls (64 ± 10 years). We correlated delta NIHSS values (Assessment 1 – Assessment 2) with delta values of autonomic parameters (Spearman rank correlation tests; significance: p < 0.05). Results: At Assessment 1, patients were not yet on vasoactive medication and had higher systolic BP, respiration rate, and heart rate, that is, lower RRIs, but lower RRI SD, RRI coefficient of variance, RRI low-frequency powers, RRI high-frequency powers, RRI total powers, RMSSDs, and baroreflex sensitivity. At Assessment 2, patients were on antihypertensives, had higher RRI SD, RRI coefficient of variance, RRI low-frequency powers, RRI high-frequency powers, RRI total powers, RMSSDs, and baroreflex sensitivity but lower systolic blood pressure and NIHSS values than at Assessment 1; values no longer differed between patients and controls except for lower RRIs and higher respiration rate in patients. Delta NIHSS scores correlated inversely with delta values of RRI SD, RRI coefficient of variance, RMSSDs, RRI low-frequency powers, RRI high-frequency powers, RRI total powers, and baroreflex sensitivity. Conclusions: In our patients, CAD recovery was almost complete within 72 h after stroke onset and correlated with neurological improvement. Most likely, early initiation of cardiovascular medication and probably attenuating stress supported rapid CAD recovery.
CRIS-Team Scopus Importer:2023-06-02
Keywords: autonomic recovery; cardiovascular autonomic dysregulation; cardiovascular medication; ischemic stroke; stroke severity

Rapid titration protocol – Experiences with a dynamic novel titration regime for vagus nerve stimulation in a group of depressive patients - Moeller, Sebastian; Wang, Ruihao; Aydin, M.; Lam, Alexandra P.; Sitter, Aileen; Grüter, J.; Philipsen, Alexandra; Müller, Helge H.O. (Journal of Clinical Neuroscience, 2019)
Vagus nerve stimulation (VNS) is an established tool in the psychiatric armamentarium for patients with therapy-resistant depression (TRD) with response rates of approximately 60%. So far, VNS is titrated slowly during ambulatory in-office visits. Thus, antidepressive effects can be expected after approximately six months. We report our experiences with a rapid dosing regime (RDR) with titration start shortly after VNS-implantation. We retrospectively analysed data of six patients with TRD who received VNS. Stimulation parameters were evaluated with regard to clinical side effects, heart rates (HR) and blood pressures (BP). Depressive symptoms were measured by Montgomery-Asberg Depression Rating Scale (MADRS) one week before and three months after implantation of the VNS. All patients received first stimulation between one and four days after surgery. We elevated output current using 0.25 mA titration steps. We increased output current between one and four days after the last titration. All patients received 1.0 mA output current after eight to 14 days post-surgery. HR and BP remained stable in all patients. All side effects were mild and temporary. MADRS scores were significantly lower three months after VNS-implantation (24 ± 8) than one week before VNS-implantation (42 ± 4; p = 0.028). The therapeutic range of VNS-parameters for antidepressive effect was reached quicker without finding increased numbers of side effects. Consequently, by using RDR the antidepressive effect of VNS-therapy for patients with TRD could be reached earlier than using slow titration. Our presented RDR might be able to significantly shorten the “clinical effect gap” due to the neurobiological and titration-related latency.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Dosing; Therapy-resistant depression; TRD; Vagus nerve; Vagus nerve stimulation; VNS

Rare meets rarer: anti-synthetase syndrome in a patient with facio-scapulo-humeral muscular dystrophy - Valor-Mendez, Larissa; Manger, Bernhard; Winterholler, Martin; Schett, Georg; Tuerk, Mattias; Knitza, Johannes (Rheumatology, 2022)
CRIS-Team WoS Importer:2022-07-08

Real-Time, In Vivo Monitoring, and Quantitative Assessment of Intra-Arterial Vasospasm Therapy - Gölitz, Philipp; Kaschka, Iris; Lang, Stefan; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd (Neurocritical Care, 2016)
Our study aimed to evaluate whether the effect of an intra-arterial vasospasm therapy can be assessed quantitatively by in vivo blood flow analysis using the postprocessing algorithm parametric color coding (PCC).We evaluated 17 patients presenting with acute clinical deterioration due to vasospasm following subarachnoidal hemorrhage treated with intra-arterial nimodipine application. Pre- and post-interventional DSA series were post-processed by PCC. The relative time to maximum opacification (rTmax) was calculated in 14 arterially and venously located points of interest. From that data, the pre- and post-interventional cerebral circulation time (CirT) was calculated. Additionally, the arterial vessel diameters were measured. Pre- and post-interventional values were compared and tested for significance, respectively.Flow analysis revealed in all arterial vessel segments a non-statistically significant prolongation of rTmax after treatment. The mean CirT was 5.62 s (±1.19 s) pre-interventionally and 5.16 s (±0.81 s) post-interventionally, and the difference turned out as statistically significant (p = 0.039). A significantly increased diameter was measurable in all arterial segments post-interventionally.PCC is a fast applicable imaging technique that allows via real-time and in vivo blood flow analysis a quantitative assessment of the effect of intra-arterial vasospasm therapy. Our results seem to validate in vivo that an intra-arterial nimodipine application induces not only vasodilatation of the larger vessels, but also improves the microcirculatory flow, leading to a shortened cerebral CirT that reaches normal range post-interventionally. Procedural monitoring via PCC offers the option to compare quantitatively different therapy regimes, which allows optimization of existing approaches and implementation of individualized treatment strategies.
EVALuna2:22520

Real world application of ocrelizumab in multiple sclerosis: Single-center experience of 128 patients - Prockl, Victoria; Nickel, Franziska; Utz, Kathrin S.; Fröhlich, Kilian; Engelhorn, Tobias; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf; Huhn, Konstantin (Journal of the Neurological Sciences, 2020)
Background: Pivotal trials showed good clinical efficiency of the monoclonal antibody ocrelizumab while being well tolerated and manageable in multiple sclerosis (MS). However, data on adverse events in everyday practice are scarce. Hence, our study aims at investigating short-term tolerability of ocrelizumab in a “real-world” setting. Methods: In this retrospective cohort study, data of 128 (86 relapsing-remitting, 42 progressive) MS patients at initiation of ocrelizumab were analyzed at the MS center of the University of Erlangen, Germany. Additionally, follow-up data of 68 patients at 6-months retreatment were analyzed. Structured phone interviews were applied after ocrelizumab initiation to report undocumented side effects. Results: Patients predominantly switched from monoclonal antibodies (46%), orals (20%), injectables (10%), steroids or immunosuppressants (each 8%), with a mean interval of 9.0 months after the last application of the previous immunotherapy. Applying a combined premedication with steroids, antihistamines and antipyretics for >90% of patients, ocrelizumab treatment was well tolerated and mainly comprised mild (n = 59/128 at initiation, n = 5/68 at 6 months retreatment) and rarely moderate (n = 7/128 at initiation, n = 2/68 at 6 months) side effects. Predominantly mild infusion related reactions (IRR) were reported with a declining percentage over the follow-up applications. Infections occurred rarely. No severe side effects were observed. Secondary, treatment appeared efficient when looking at clinical surrogates of stable disease. Discussion: Our study delineates good short-term tolerability of ocrelizumab in a miscellaneous “real-world” MS cohort. Additional studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.
CRIS-Team Scopus Importer:2020-06-26
Keywords: B-cell depletion; CD 20; Immunomodulatory treatment; Monoclonal antibody; Multiple sclerosis; Ocrelizumab; Side effects

Recommendations for the management of cerebral and cerebellar infarction with swelling: a statement for healthcare professionals from the American Heart Association/American Stroke Association - Wijdicks, Eelco F. M.; Sheth, Kevin N.; Carter, Bob S.; Greer, David M.; Kasner, Scott E.; Kimberly, W. Taylor; Schwab, Stefan; Smith, Eric E.; Tamargo, Rafael J.; Wintermark, Max (Stroke, 2014)
There are uncertainties surrounding the optimal management of patients with brain swelling after an ischemic stroke. Guidelines are needed on how to manage this major complication, how to provide the best comprehensive neurological and medical care, and how to best inform families facing complex decisions on surgical intervention in deteriorating patients. This scientific statement addresses the early approach to the patient with a swollen ischemic stroke in a cerebral or cerebellar hemisphere.The writing group used systematic literature reviews, references to published clinical and epidemiology studies, morbidity and mortality reports, clinical and public health guidelines, authoritative statements, personal files, and expert opinion to summarize existing evidence and to indicate gaps in current knowledge. The panel reviewed the most relevant articles on adults through computerized searches of the medical literature using MEDLINE, EMBASE, and Web of Science through March 2013. The evidence is organized within the context of the American Heart Association framework and is classified according to the joint American Heart Association/American College of Cardiology Foundation and supplementary American Heart Association Stroke Council methods of classifying the level of certainty and the class and level of evidence. The document underwent extensive American Heart Association internal peer review.Clinical criteria are available for hemispheric (involving the entire middle cerebral artery territory or more) and cerebellar (involving the posterior inferior cerebellar artery or superior cerebellar artery) swelling caused by ischemic infarction. Clinical signs that signify deterioration in swollen supratentorial hemispheric ischemic stroke include new or further impairment of consciousness, cerebral ptosis, and changes in pupillary size. In swollen cerebellar infarction, a decrease in level of consciousness occurs as a result of brainstem compression and therefore may include early loss of corneal reflexes and the development of miosis. Standardized definitions should be established to facilitate multicenter and population-based studies of incidence, prevalence, risk factors, and outcomes. Identification of patients at high risk for brain swelling should include clinical and neuroimaging data. If a full resuscitative status is warranted in a patient with a large territorial stroke, admission to a unit with neurological monitoring capabilities is needed. These patients are best admitted to intensive care or stroke units attended by skilled and experienced physicians such as neurointensivists or vascular neurologists. Complex medical care includes airway management and mechanical ventilation, blood pressure control, fluid management, and glucose and temperature control. In swollen supratentorial hemispheric ischemic stroke, routine intracranial pressure monitoring or cerebrospinal fluid diversion is not indicated, but decompressive craniectomy with dural expansion should be considered in patients who continue to deteriorate neurologically. There is uncertainty about the efficacy of decompressive craniectomy in patients >=60 years of age. In swollen cerebellar stroke, suboccipital craniectomy with dural expansion should be performed in patients who deteriorate neurologically. Ventriculostomy to relieve obstructive hydrocephalus after a cerebellar infarct should be accompanied by decompressive suboccipital craniectomy to avoid deterioration from upward cerebellar displacement. In swollen hemispheric supratentorial infarcts, outcome can be satisfactory, but one should anticipate that one third of patients will be severely disabled and fully dependent on care even after decompressive craniectomy. Surgery after a cerebellar infarct leads to acceptable functional outcome in most patients.Swollen cerebral and cerebellar infarcts are critical conditions that warrant immediate, specialized neurointensive care and often neurosurgical intervention. Decompressive craniectomy is a necessary option in many patients. Selected patients may benefit greatly from such an approach, and although disabled, they may be functionally independent.
EVALuna2:22286

Recommendations for tilt table testing and other provocative cardiovascular autonomic tests in conditions that may cause transient loss of consciousness : Consensus statement of the European Federation of Autonomic Societies (EFAS) endorsed by the American Autonomic Society (AAS) and the European Academy of Neurology (EAN). - Thijs, Roland D.; Brignole, Michele; Falup-Pecurariu, Cristian; Fanciulli, Alessandra; Freeman, Roy; Guaraldi, Pietro; Jordan, Jens; Habek, Mario; Hilz, Max-Josef; Pavy-Letraon, Anne; Stankovic, Iva; Struhal, Walter; et al. (Autonomic Neuroscience-Basic & Clinical, 2021)
An expert committee was formed to reach consensus on the use of Tilt Table Testing (TTT) in the diagnosis of disorders that may cause transient loss of consciousness (TLOC) and to outline when other provocative cardiovascular autonomic tests are needed. While TTT adds to history taking, it cannot be a substitute for it. An abnormal TTT result is most meaningful if the provoked event is recognised by patients or eyewitnesses as similar to spontaneous ones. The minimum requirements to perform TTT are a tilt table, a continuous beat-to-beat blood pressure monitor, at least one ECG lead, protocols for the indications stated below and trained staff. This basic equipment lends itself to perform (1) additional provocation tests, such as the active standing test carotid sinus massage and autonomic function tests; (2) additional measurements, such as video, EEG, transcranial Doppler, NIRS, end-tidal CO2 or neuro-endocrine tests; (3) tailor-made provocation procedures in those with a specific and consistent trigger of TLOC. TTT and other provocative cardiovascular autonomic tests are indicated if the initial evaluation does not yield a definite or highly likely diagnosis, but raises a suspicion of (1) reflex syncope, (2) the three forms of orthostatic hypotension (OH), i.e. initial, classic and delayed OH, as well as delayed orthostatic blood pressure recovery, (3) postural orthostatic tachycardia syndrome or (4) psychogenic pseudosyncope. A therapeutic indication for TTT is to teach patients with reflex syncope and OH to recognise hypotensive symptoms and to perform physical counter manoeuvres.
EVALuna2:429865

Recommendations for tilt table testing and other provocative cardiovascular autonomic tests in conditions that may cause transient loss of consciousness Consensus statement of the European Federation of Autonomic Societies (EFAS) endorsed by the American Autonomic Society (AAS) and the European Academy of Neurology (EAN) - Thijs, Roland D.; Brignole, Michele; Falup-Pecurariu, Cristian; Fanciulli, Alessandra; Freeman, Roy; Guaraldi, Pietro; Jordan, Jens; Habek, Mario; Hilz, Max-Josef; Traon, Anne Pavy-Le; Stankovic, Iva; Struhal, Walter; et al. (Clinical Autonomic Research, 2021)
An expert committee was formed to reach consensus on the use of tilt table testing (TTT) in the diagnosis of disorders that may cause transient loss of consciousness (TLOC) and to outline when other provocative cardiovascular autonomic tests are needed. While TTT adds to history taking, it cannot be a substitute for it. An abnormal TTT result is most meaningful if the provoked event is recognised by patients or eyewitnesses as similar to spontaneous events. The minimum requirements to perform TTT are a tilt table, a continuous beat-to-beat blood pressure monitor, at least one ECG lead, protocols for the indications stated below and trained staff. This basic equipment lends itself to the performance of (1) additional provocation tests, such as the active standing test, carotid sinus massage and autonomic function tests; (2) additional measurements, such as video, EEG, transcranial Doppler, NIRS, end-tidal CO2 or neuro-endocrine tests; and (3) tailor-made provocation procedures in those with a specific and consistent trigger of TLOC. TTT and other provocative cardiovascular autonomic tests are indicated if the initial evaluation does not yield a definite or highly likely diagnosis, but raises a suspicion of (1) reflex syncope, (2) the three forms of orthostatic hypotension (OH), i.e. initial, classic and delayed OH, as well as delayed orthostatic blood pressure recovery, (3) postural orthostatic tachycardia syndrome or (4) psychogenic pseudosyncope. A therapeutic indication for TTT is to teach patients with reflex syncope and OH to recognise hypotensive symptoms and to perform physical counter manoeuvres.
CRIS-Team WoS Importer:2021-04-02

Recommendations on the structure, personal, and organization of intensive care units - Waydhas, Christian; Riessen, Reimer; Markewitz, Andreas; Hoffmann, Florian; Frey, Lorenz; Böttiger, Bernd W.; Brenner, Sebastian; Brenner, Thorsten; Deffner, Teresa; Deininger, Matthias M.; Janssens, Uwe; Kluge, Stefan; et al. (Frontiers in Medicine, 2023)
Background: Intensive care units (ICU) are central facilities of medical care in hospitals world-wide and pose a significant financial burden on the health care system. Objectives: To provide guidance and recommendations for the requirements of (infra)structure, personal, and organization of intensive care units. Design and setting: Development of recommendations based on a systematic literature search and a formal consensus process from a group of multidisciplinary and multiprofessional specialists from the German Interdisciplinary Association of Intensive Care and Emergency Medicine (DIVI). The grading of the recommendation follows the report from an American College of Chest Physicians Task Force. Results: The recommendations cover the fields of a 3-staged level of intensive care units, a 3-staged level of care with respect to severity of illness, qualitative and quantitative requirements of physicians and nurses as well as staffing with physiotherapists, pharmacists, psychologists, palliative medicine and other specialists, all adapted to the 3 levels of ICUs. Furthermore, proposals concerning the equipment and the construction of ICUs are supplied. Conclusion: This document provides a detailed framework for organizing and planning the operation and construction/renovation of ICUs.
CRIS-Team Scopus Importer:2023-09-29
Keywords: guideline; intensive care medicine; organization; personal; quality of care; recommendation; structural requirements

Reduced pupillary modulation in patients with relapsing-remitting Multiple Sclerosis is associated with longer disease duration and higher disease severity - Wang, Ruihao; Roy, Sankanika; de Rojas Leal, Carmen; Liu, Mao; Hoesl, K.; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (2018)
EVALuna2:201950

Re-evaluation of the stroke prognostication using age and NIH Stroke Scale index (SPAN-100 index) in IVT patients - the-SPAN 10065 index - Möbius, Cornelia; Blinzler, Christian; Schwab, Stefan; Koehrmann, Martin; Breuer, Lorenz (BMC Neurology, 2018)
BACKGROUND: The SPAN-100 index adds patient age and baseline NIHSS-score and was introduced to predict clinical outcome after acute ischemic stroke (AIS). Even with high NIHSS-scores younger patients cannot reach a SPAN-100-positive status (index ≥100). We aimed to evaluate the SPAN-100 index among a large, contemporary cohort of i.v.-thrombolysed AIS-patients and exclusively among older patients who can at least theoretically achieve SPAN-100-positivity. METHODS: The SPAN-100 index was applied to AIS-patients receiving i.v.-thrombolysis (IVT) in our institution between 01/2006 and 01/2013. Clinical outcome and symptomatic intracerebral hemorrhage rates were compared between SPAN-100-positive and -negative patients. Furthermore we excluded patients < 65 years, without any theoretical chance to achieve SPAN-100-positivity, and re-evaluated the index (SPAN65-100 index). RESULTS: SPAN-100-positive IVT-patients (124/1002) had a 9-fold increased risk for unfavorable outcome compared to SPAN-negative patients (OR 9.39; 95% CI 5.87-15.02; p < 0.001). The odds ratio for mortality was 7.48 (95% CI 4.90-11.43; p < 0.001). No association was found between SPAN-100-positivity and sICH-incidence (OR 0.88; 95% CI 0.31-2.53; p = 0.810). SPAN65-100-positivity (124/741) was associated with an 8-fold increased risk for unfavorable outcome (OR 7.6; 95% CI 4.71-12.22; p < 0.001) but not associated with higher sICH-rates (OR 0.86; 95% CI 0.29-2.53; p < 0.001). CONCLUSIONS: Also for patients ≥65 years the SPAN-100 index can be a fast, easy method to predict clinical outcome of IVT-patients in everyday practice. However, it should not be used to determine the risk of sICH after IVT. Based on a SPAN-positive status IVT should not be withheld from AIS-patients merely because of feared sICH-complications.
EVALuna2:35513

Regional Differences in Thrombectomy Rates : Secondary use of Billing Codes in the MIRACUM (Medical Informatics for Research and Care in University Medicine) Consortium - Haverkamp, Christian; Ganslandt, Thomas; Horki, Petar; Boeker, Martin; Dörfler, Arnd; Schwab, Stefan; Berkefeld, Joachim; Pfeilschifter, Waltraud; Niesen, Wolf-Dirk; Egger, Karl; Kaps, Manfred; Brockmann, Marc A.; et al. (Clinical Neuroradiology, 2018)
Mechanical thrombectomy, in addition to intravenous (i.v.) thrombolysis is recommended for treatment of acute stroke in patients with large vessel occlusions (LVO) in the anterior circulation up to 6 h after symptom onset. We compared thrombectomy rates of eight university hospitals of the MIRACUM consortium to analyze the implementation of this guideline in clinical routine.Anonymized billing data in a standardized format were loaded into a local i2b2 data warehouse by applying already existing extract, transform and load (ETL) routines. A locally executed uniform SQL (structured query language) query delivered aggregated site data for all inpatients with a discharge diagnosis of ischemic stroke (ICD-10 I63) containing counts for type of acute treatment, type of admission and age groups, which were centrally analyzed with R.From 2014 to 2016, the thrombectomy rate almost doubled from a mean of 4.7% to 9.6%, although significant differences between centers exist (range in 2016: 5.8-17%). The number of drip-and-ship procedures increased in 3 out of 8 centers. There was no evidence for a decrease in thrombectomy rates during weekends/holiday or among patients older than 80 years, but this age group is more likely to receive i.v. recombinant tissue plasminogen activator (rtPA).The observed increase of thrombectomy rates and drip-and-ship procedures without a significant difference between weekdays and weekends or patients of different ages is substantiating a rapid implementation of stroke guidelines within the analyzed neurovascular centers. The prototype of the MIRACUM Data Integration Center already contributes to health services research in Germany.
EVALuna2:196

Regulation of the programmed cell death protein 1/programmed cell death ligand 1 axis in relapsing-remitting multiple sclerosis - Tsaktanis, Thanos; Linnerbauer, Mathias; Lößlein, Lena; Farrenkopf, Daniel; Vandrey, Oliver; Peter, Anne; Cirac, Ana; Beyer, Tobias; Nirschl, Lucy; Grummel, Verena; Mühlau, Mark; Bussas, Matthias; et al. (Brain Communications, 2023)
The programmed cell death protein 1/programmed cell death ligand 1 axis plays an important role in the adaptive immune system and has influence on neoplastic and inflammatory diseases, while its role in multiple sclerosis is unclear. Here, we aimed to analyse expression patterns of programmed cell death protein 1 and programmed cell death ligand 1 on peripheral blood mononuclear cells and their soluble variants in multiple sclerosis patients and controls, to determine their correlation with clinical disability and disease activity. In a cross-sectional study, we performed in-depth flow cytometric immunophenotyping of peripheral blood mononuclear cells and analysed soluble programmed cell death protein 1 and programmed cell death ligand 1 serum levels in patients with relapsing-remitting multiple sclerosis and controls. In comparison to control subjects, relapsing-remitting multiple sclerosis patients displayed distinct cellular programmed cell death protein 1/programmed cell death ligand 1 expression patterns in immune cell subsets and increased soluble programmed cell death ligand 1 levels, which correlated with clinical measures of disability and MRI activity over time. This study extends our knowledge of how programmed cell death protein 1 and programmed cell death ligand 1 are expressed in the membranes of patients with relapsing-remitting multiple sclerosis and describes for the first time the elevation of soluble programmed cell death ligand 1 in the blood of multiple sclerosis patients. The distinct expression pattern of membrane-bound programmed cell death protein 1 and programmed cell death ligand 1 and the correlation between soluble programmed cell death ligand 1, membrane-bound programmed cell death ligand 1, disease and clinical factors may offer therapeutic potential in the setting of multiple sclerosis and might improve future diagnosis and clinical decision-making.
CRIS-Team Scopus Importer:2023-09-15
Keywords: autoimmunity; checkpoint; co-regulation; neuroinflammation; PBMCs

Relevance of sonography for botulinum toxin treatment of cervical dystonia: an expert statement - Schramm, Axel; Baeumer, Tobias; Fietzek, Urban; Heitmann, Susanne; Walter, Uwe; Jost, Wolfgang H. (Journal of Neural Transmission, 2015)
Botulinum neurotoxin A (BoNT A) is the first-line treatment for cervical dystonia. However, although BoNT A has a favorable safety profile and is effective in the majority of patients, in some cases the treatment outcome is disappointing or side effects occur when higher doses are used. It is likely that in such cases either the target muscles were not injected accurately or unintended weakness of non-target muscles occurred. It has been demonstrated in clinical trials for spastic movement disorders that sonography-guided BoNT A injections could improve treatment outcome. As the published evidence for a benefit of sonography-guided BoNT injection in patients with cervical dystonia is scarce, it is the aim of this review to discuss the relevance of sonography in this indication and provide a statement from clinical experts for its use. The clear advantage of sonography-guided injections is non-invasive, real-time visualization of the targeted muscle, thus improving the precision of injections and potentially the treatment outcomes as well as avoiding adverse effects. Other imaging techniques are of limited value due to high costs, radiation exposure or non-availability in clinical routine. In the hands of a trained injector, sonography is a quick and non-invasive imaging technique. Novel treatment concepts of cervical dystonia considering the differential contributions of distinct cranial and cervical muscles can reliably be implemented only by use of imaging-guided injection protocols.
EVALuna2:22342

Reliability and limitations of automated arrhythmia detection in telemetric monitoring after stroke - Kurka, Natalia; Bobinger, Tobias; Kallmünzer, Bernd; Koehn, Julia; Schellinger, Peter D.; Schwab, Stefan; Köhrmann, Martin (Stroke, 2015)
Guidelines recommend continuous ECG monitoring in patients with cerebrovascular events. Studies on intensive care units (ICU) demonstrated high sensitivity but high rates of false alarms of monitoring systems resulting in desensitization of medical personnel potentially endangering patient safety. Data on patients with acute stroke are lacking.One-hundred fifty-one consecutive patients with acute cerebrovascular events were prospectively included. Automatically identified arrhythmia events were analyzed by manual ECG analysis. Muting of alarms was registered. Sensitivity was evaluated by beat-to-beat analysis of the entire recorded ECG data in a subset of patients. Ethics approval was obtained by University of Erlangen-Nuremberg.A total of 4809.5 hours of ECG registration and 22 509 alarms were analyzed. The automated detection algorithm missed no events but the overall rate of false alarms was 27.4%. Only 0.6% of all alarms indicated acute life-threatening events and 91.4% of these alarms were incorrect. Transient muting of acoustic alarms was observed in 20.5% patients.Continuous ECG monitoring using automated arrhythmia detection is highly sensitive in acute stroke. However, high rates of false alarms and alarms without direct therapeutic consequence cause desensitization of personnel. Therefore, acoustic alarms may be limited to life-threatening events but standardized manual evaluation of all alarms should complement automated systems to identify clinically relevant arrhythmias.
EVALuna2:22266

Reliability and validity of a new, sensor-based system for gait analysis in patients with multiple sclerosis - Flachenecker, F.; Gaßner, Heiko; Lee, De-Hyung; Eskofier, Björn; Klucken, Jochen; Flachenecker, P.; Linker, Ralf (2017)
EVALuna2:22575

Reply: Beneficial effects of exogenous CDP-choline (citicoline) in EAE - Skripuletz, Thomas; Gudi, Viktoria; Baumgärtner, Wolfgang; Linker, Ralf A.; Stangel, Martin (Brain, 2015)
EVALuna2:22430

Reply: Is there evidence of a subordinate role of the hippocampal CA1 field for declarative memory formation? - Coras, Roland; Pauli, Elisabeth; Blümcke, Ingmar (Brain, 2015)
EVALuna2:7265

Reply to "Laterality of motor control as revealed in biceps electromyography: Why seizures always start in the major hemisphere" - Hagge, Mareike; Hamer, Hajo (Clinical Neurophysiology, 2016)
EVALuna2:22450

Resection of cerebral gangliogliomas causing drug-resistant epilepsy: short- and long-term outcomes using intraoperative MRI and neuronavigation - Sommer, Bjoern; Wimmer, Cornelia; Coras, Roland; Blümcke, Ingmar; Lorber, Bogdan; Hamer, Hajo; Stefan, Hermann; Buchfelder, Michael; Roessler, Karl (Neurosurgical Focus, 2015)
OBJECT Cerebral gangliogliomas (GGs) are highly associated with intractable epilepsy. Incomplete resection due to proximity to eloquent brain regions or misinterpretation of the resection amount is a strong negative predictor for local tumor recurrence and persisting seizures. A potential method for dealing with this obstacle could be the application of intraoperative high-field MRI (iopMRI) combined with neuronavigation. METHODS Sixty-nine patients (31 female, 38 male; median age 28.5 ± 15.4 years) suffering from cerebral GGs were included in this retrospective study. Five patients received surgery twice in the observation period. In 48 of the 69 patients, 1.5-T iopMRI combined with neuronavigational guidance was used. Lesions close to eloquent brain areas were resected with the implementation of preoperative diffusion tensor imaging tractography and blood oxygenation level-dependent functional MRI (15 patients). RESULTS Overall, complete resection was accomplished in 60 of 69 surgical procedures (87%). Two patients underwent biopsy only, and in 7 patients, subtotal resection was accomplished because of proximity to critical brain areas. Excluding the 2 biopsies, complete resection using neuronavigation/iopMRI was documented in 33 of 46 cases (72%) by intraoperative imaging. Remnant tumor mass was identified intraoperatively in 13 of 46 patients (28%). After intraoperative second-look surgery, the authors improved the total resection rate by 9 patients (up to 91% [42 of 46]). Of 21 patients undergoing conventional surgery, 14 (67%) had complete resection without the use of iopMRI. Regarding epilepsy outcome, 42 of 60 patients with seizures (70%) became completely seizure free (Engel Class IA) after a median follow-up time of 55.5 ± 36.2 months. Neurological deficits were found temporarily in 1 (1.4%) patient and permanently in 4 (5.8%) patients. CONCLUSIONS Using iopMRI combined with neuronavigation in cerebral GG surgery, the authors raised the rate of complete resection in this series by 19%. Given the fact that total resection is a strong predictor of long-term seizure control, this technique may contribute to improved seizure outcome and reduced neurological morbidity.
EVALuna2:7260

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Resective surgery for medically refractory epilepsy using intraoperative MRI and functional neuronavigation: the Erlangen experience of 415 patients - Roessler, Karl; Hofmann, Andrea; Sommer, Bjoern; Grummich, Peter; Coras, Roland; Kasper, Burkhard; Hamer, Hajo; Blümcke, Ingmar; Stefan, Hermann; Nimsky, Christopher; Buchfelder, Michael (Neurosurgical Focus, 2016)
Intraoperative overestimation of resection volume in epilepsy surgery is a well-known problem that can lead to an unfavorable seizure outcome. Intraoperative MRI (iMRI) combined with neuronavigation may help surgeons avoid this pitfall and facilitate visualization and targeting of sometimes ill-defined heterogeneous lesions or epileptogenic zones and may increase the number of complete resections and improve seizure outcome.To investigate this hypothesis, the authors conducted a retrospective clinical study of consecutive surgical procedures performed during a 10-year period for epilepsy in which they used neuronavigation combined with iMRI and functional imaging (functional MRI for speech and motor areas; diffusion tensor imaging for pyramidal, speech, and visual tracts; and magnetoencephalography and electrocorticography for spike detection). Altogether, there were 415 patients (192 female and 223 male, mean age 37.2 years; 41% left-sided lesions and 84.9% temporal epileptogenic zones). The mean preoperative duration of epilepsy was 17.5 years. The most common epilepsy-associated pathologies included hippocampal sclerosis (n = 146 [35.2%]), long-term epilepsy-associated tumor (LEAT) (n = 67 [16.1%]), cavernoma (n = 45 [10.8%]), focal cortical dysplasia (n = 31 [7.5%]), and epilepsy caused by scar tissue (n = 23 [5.5%]).In 11.8% (n = 49) of the surgeries, an intraoperative second-look surgery (SLS) after incomplete resection verified by iMRI had to be performed. Of those incomplete resections, LEATs were involved most often (40.8% of intraoperative SLSs, 29.9% of patients with LEAT). In addition, 37.5% (6 of 16) of patients in the diffuse glioma group and 12.9% of the patients with focal cortical dysplasia underwent an SLS. Moreover, iMRI provided additional advantages during implantation of grid, strip, and depth electrodes and enabled intraoperative correction of electrode position in 13.0% (3 of 23) of the cases. Altogether, an excellent seizure outcome (Engel Class I) was found in 72.7% of the patients during a mean follow-up of 36 months (range 3 months to 10.8 years). The greatest likelihood of an Engel Class I outcome was found in patients with cavernoma (83.7%), hippocampal sclerosis (78.8%), and LEAT (75.8%). Operative revisions that resulted from infection occurred in 0.3% of the patients, from hematomas in 1.6%, and from hydrocephalus in 0.8%. Severe visual field defects were found in 5.2% of the patients, aphasia in 5.7%, and hemiparesis in 2.7%, and the total mortality rate was 0%.Neuronavigation combined with iMRI was beneficial during surgical procedures for epilepsy and led to favorable seizure outcome with few specific complications. A significantly higher resection volume associated with a higher chance of favorable seizure outcome was found, especially in lesional epilepsy involving LEAT or diffuse glioma.
EVALuna2:7327

Response to Gurevich and colleagues: The effect of enzyme replacement therapy on clinical outcomes in male patients with Fabry disease: a systematic literature review by a European panel of experts - Germain, Dominique P.; Falissard, B.; Hilz, Max-Josef; Spada, M.; Wanner, Christoph; Elliott, Perry M. (Molecular Genetics and Metabolism Reports, 2019)
CRIS-Team Scopus Importer:2019-08-30
Keywords: Agalsidase alfa; Agalsidase beta; Enzyme replacement therapy; Fabry disease

Restarting Therapeutic Anticoagulation in Patients with Intracerebral Hemorrhage and Mechanical Heart Valves - Kuramatsu, Joji; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (2018)
EVALuna2:35518

Retention, dosing, tolerability and patient reported seizure outcome of Zonisamide as only add-on treatment under real-life conditions in adult patients with partial onset seizures: Results of the observational study ZOOM - Hamer, Hajo; Baulac, Michel; Mcmurray, Rob; Kockelmann, Edgar (Seizure-European Journal of Epilepsy, 2016)
Zonisamide is licensed for adjunctive therapy for partial-onset seizures with or without secondary generalisation in patients 6 years and older and as monotherapy for the treatment of partial seizures in adult patients with newly diagnosed epilepsy, and shows a favourable pharmacokinetic profile with low interaction potential with other drugs. The aim of the present study was to gather real-life data on retention and modalities of zonisamide use when administered as only add-on treatment to a current AED monotherapy in adult patients with partial-onset seizures.This multicenter observational study was performed in 4 European countries and comprised three visits: baseline, and after 3 and 6 months. Data on patients' retention, reported efficacy, tolerability and safety, and quality of life was collected. Of 100 included patients, 93 could be evaluated.After 6 months, the retention rate of zonisamide add-on therapy was 82.8%. At this time, a reduction of seizure frequency of at least 50% was observed in 79.7% of patients, with 43.6% reporting seizure freedom over the last 3 months of the study period. Adverse events were reported by 19.4% of patients, with fatigue, agitation, dizziness, and headache being most frequent. Approximately 25% of patients were older than 60 years, many of whom suffered from late-onset epilepsy. Compared to younger patients, these patients showed considerable differences with regard to their antiepileptic drug regimen at baseline, and slightly higher responder and retention rates at 6 months.Despite limitations due to the non-interventional open-label design and the low sample size, the results show that zonisamide as only add-on therapy is well retained, indicating effectiveness in the majority of patients under real-life conditions.
EVALuna2:22377

Retinal imaging and axonal degeneration in later onset multiple sclerosis - Huhn, Konstantin; Lämmer, Robert; Meng, Hanna Zimmermann; Laemmer, Alexandra; Waschbisch, Anne; Utz, Kathrin; Giess, Rene Markus; Paul, Friedemann; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2016)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the CNS typically affecting younger adults and resulting in neuro-axonal degeneration already at early stages of the disease. Less is known about the effects of a later disease onset (LOMS, onset >50years of age). Analysis of retinal layers by optical coherence tomography (OCT) is a non-invasive method to investigate retinal and neuro-axonal degeneration. We applied OCT to detect differences in retinal damage depending on a later disease manifestation.14 LOMS patients, 14 age- and 14 disease duration-matched normal onset (NOMS) patients with a relapsing remitting disease course and 15 healthy controls (HC) were included. OCT measurement of peripapillary retinal nerve fiber layer (RNFL), total macular volume (TMV), combined ganglion cell/inner plexiform layer (GCIPL), inner nuclear layer (INL) and outer retinal layers (ORL) was conducted. Furthermore, analysis of clinical features and of effects of previous optic neuritis (ON) was performed RESULTS: In a GEE based analysis of age- and disease duration matched NOMS, LOMS patients show no significant differences in retinal layer thickness whereas ON significantly reduced thickness of retinal layers. All MS groups display lower retinal layer thickness as compared to HC independently of type of onset.Our LOMS findings are well in line with published OCT data of normal onset MS. As the degree of retinal layer thinning was similar in MS subgroups, retinal neurodegeneration in MS may occur independently of time of disease onset.
EVALuna2:21282

Reversal of oral anticoagulation in patients with acute intracerebral hemorrhage - Kuramatsu, Joji; Sembill, Jochen; Huttner, Hagen (Critical Care, 2019)
In light of an aging population with increased cardiovascular comorbidity, the use of oral anticoagulation (OAC) is steadily expanding. A variety of pharmacological alternatives to vitamin K antagonists (VKA) have emerged over recent years (direct oral anticoagulants, DOAC, i.e., dabigatran, rivaroxaban, apixaban, and edoxaban) which show a reduced risk for the occurrence of intracerebral hemorrhage (ICH). Yet, in the event of ICH under OAC (OAC-ICH), hematoma characteristics are similarly severe and clinical outcomes likewise substantially limited in both patients with VKA- and DOAC-ICH, which is why optimal acute hemostatic treatment in all OAC-ICH needs to be guaranteed. Currently, International Guidelines for the hemostatic management of patients with OAC-ICH are updated as several relevant large-sized observational studies and recent trials have established treatment approaches for both VKA- and DOAC-ICH. While the management of VKA-ICH is mainly based on the immediate reversal of elevated levels of international normalized ratio using prothrombin complex concentrates, hemostatic management of DOAC-associated ICH is challenging requiring specific antidotes, notably idarucizumab and andexanet alfa. This review will provide an overview of the latest studies and trials on hemostatic reversal agents and timing and summarizes the effects on hemorrhage progression and clinical outcomes in patients with OAC-ICH.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Anticoagulation reversal; Ciraparantag; Desmopressin; Intracerebral hemorrhage; Tranexamic acid

Risk reduction in dominant temporal lobe epilepsy surgery combining fMRI/DTI maps, neuronavigation and intraoperative 1.5-Tesla MRI - Roessler, Karl; Sommer, Bjoern; Grummich, Peter; Hamer, Hajo; Pauli, Elisabeth; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael (Stereotactic and Functional Neurosurgery, 2015)
In dominant temporal lobe epilepsy surgery, speech, memory and visual systems are at risk.Functional magnetic resonance imaging (fMRI) and diffusion tensor imaging combined with intraoperative neuronavigation and MRI were investigated retrospectively regarding risk reductions for favorable neurological and seizure outcome.Functional imaging risk maps were generated for 14 patients suffering from dominant temporal lobe epilepsy [7 with hippocampal sclerosis (HS), 7 with various lesions] and used for neuronavigation-guided tailored resection. Postoperative neurological and seizure outcome and complications were evaluated.None of the patients had postoperative speech dysfunction despite 2.3/3.6-cm mean hippocampal/neocortical resection. Verbal memory decline was found in 2 of the 14 (14.3%) patients, correlating with surgical lesions in fMRI memory-activated functional areas in the dominant posterior parahippocampal gyrus. Verbal memory scores did not statistically differ between the HS and the lesional group, neither pre- nor postoperatively. A contralateral visual field defect occurred in 1 patient (7.1%). An Engel class I seizure outcome was found in 12 patients (85.7%), and 11 were completely seizure free (78.6%) at a mean follow-up of 19.5 months.This retrospectively investigated protocol led to an excellent neurological and seizure outcome and a low complication rate in dominant temporal lobe epilepsy surgery.
EVALuna2:7287

Role of glial 14-3-3 gamma protein in autoimmune demyelination - Lee, De-Hyung; Steinacker, Petra; Seubert, Silvia; Turnescu-Uzat, Tanja; Melms, Arthur; Manzel, Arndt; Otto, Markus; Linker, Ralf (Journal of Neuroinflammation, 2015)
The family of 14-3-3 proteins plays an important role in the regulation of cell survival and death. Here, we investigate the role of the 14-3-3 gamma (14-3-3 ?) subunit for glial responses in autoimmune demyelination.Expression of 14-3-3 ? in glial cell culture was investigated by reverse transcription polymerase chain reaction (RT-PCR) and immunocytochemistry. 14-3-3 ? knockout mice were subjected to murine myelin oligodendrocyte-induced experimental autoimmune encephalomyelitis (MOG-EAE), an animal model mimicking inflammatory features and neurodegenerative aspects of multiple sclerosis (MS).Expression studies in cell culture confined expression of 14-3-3 ? to both, oligodendrocytes (OL) and astrocytes. RT-PCR analysis revealed an increased expression of 14-3-3 ? mRNA in the spinal cord during the late chronic phase of MOG-EAE. At that stage, EAE was more severe in 14-3-3 ? knockout mice as compared to age- and gender-matched controls. Histopathological analyses on day 56 post immunization (p.i.) revealed significantly enhanced myelin damage as well as OL injury and secondary, an increase in axonal injury and gliosis in 14-3-3 ? -/- mice. At the same time, deficiency in 14-3-3 ? protein did not influence the immune response. Further histological studies revealed an increased susceptibility towards apoptosis in 14-3-3 ?-deficient OL in the inflamed spinal cord.These data argue for a pivotal role of 14-3-3 ?-mediated signalling pathways for OL protection in neuroinflammation.
EVALuna2:22340

Role of Nuclear Factor (Erythroid-Derived 2)-Like 2 Signaling for Effects of Fumaric Acid Esters on Dendritic Cells - Hammer, Anna; Waschbisch, Anne; Knippertz, Ilka; Zinser, Elisabeth; Berg, Johannes; Joerg, Stefanie; Kuhbandner, Kristina; David, Christina; Pi, Jingbo; Bayas, Antonios; Lee, De-Hyung; Haghikia, Aiden; et al. (Frontiers in Immunology, 2017)
To date, the intracellular signaling pathways involved in dendritic cell (DC) function are poorly understood. The antioxidative transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) has been shown to affect maturation, function, and subsequent DC-mediated T cell responses of murine and human DCs. In experimental autoimmune encephalomyelitis (EAE), as prototype animal model for a T helper cell-mediated autoimmune disease, antigen presentation, cytokine production, and costimulation by DCs play a major role. We explore the role of Nrf2 in DC function, and DC-mediated T cell responses during T cell-mediated autoimmunity of the central nervous system using genetic ablation and pharmacological activation in mice and men to corroborate our data in a translational setting. In murine and human DCs, monomethyl fumarate induced Nrf2 signaling inhibits DC maturation and DC-mediated T cell proliferation by reducing inflammatory cytokine production and expression of costimulatory molecules. In contrast, Nrf2-deficient DCs generate more activated T helper cells (Th1/Th17) but fewer regulatory T cells and foster T cell proliferation. Transfer of DCs with Nrf2 activation during active EAE reduces disease severity and T cell infiltration. Our data demonstrate that Nrf2 signaling modulates autoimmunity in murine and human systems via inhibiting DC maturation and function thus shedding further light on the mechanism of action of antioxidative stress pathways in antigen-presenting cells.
EVALuna2:22557

Role of occupational therapy in epilepsy patients after left temporal lobe surgery - Schwarz, Michael; Geismar, Lisa; Schneider, Katrin; Kasper, Burkhard; Walther, Katrin; Hamer, Hajo (British Journal of Occupational Therapy, 2022)
There is a relevant risk of psychosocial as well as cognitive impairments in epilepsy patients with resective surgery in the left temporal lobe. Surgery in the speech-dominant hemisphere can be associated with deterioration of speech related functions including verbal memory. There are only limited studies addressing the impact of occupational therapy in postoperative rehabilitation of epilepsy patients.Method: In this study, a mixed-methods design based on the grounded theory concept was administered. Seven patients with left temporal lobe epilepsy and a risk profile for postoperative cognitive decline were investigated over various time points. Neuropsychological assessments occurred before surgery, 1 week, 3 months, and 6 months postoperatively. According to our rehabilitation concept, every patient started occupational therapy 1 month before surgery. Therapy lasted for at least 6 months after surgery. For all patients, extensive qualitative interviews with the occupational therapists and anamnestic data were analyzed.Results: In all patients, postoperative psychosocial difficulties emerged. Language and memory tests showed a decline after 6 months specifically for name retrieval. Occupational therapy was adapted to find individual solutions for the patients problems and to implement effective coping strategies.Conclusion: Cognitive training lead to consistent improvements over time. The results show that occupational therapy can be an efficient tool in the treatment of psychosocial and cognitive impairments after epilepsy surgery.
CRIS-Team WoS Importer:2022-03-04

Role of the receptor Mas in macrophage-mediated inflammation in vivo - Hammer, Anna; Yang, Guang; Friedrich, Juliane; Kovacs, Agnes; Lee, De-Hyung; Grave, Katharina; Joerg, Stefanie; Alenina, Natalia; Grosch, Janina; Winkler, Jürgen; Gold, Ralf; Bader, Michael; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Recently, an alternative renin-angiotensin system pathway has been described, which involves binding of angiotensin-(1-7) to its receptor Mas. The Mas axis may counterbalance angiotensin-II-mediated proinflammatory effects, likely by affecting macrophage function. Here we investigate the role of Mas in murine models of autoimmune neuroinflammation and atherosclerosis, which both involve macrophage-driven pathomechanisms. Mas signaling affected macrophage polarization, migration, and macrophage-mediated T-cell activation. Mas deficiency exacerbated the course of experimental autoimmune encephalomyelitis and increased macrophage infiltration as well as proinflammatory gene expression in the spleen and spinal cord. Furthermore, Mas deficiency promoted atherosclerosis by affecting macrophage infiltration and migration and led to increased oxidative stress as well as impaired endothelial function in ApoE-deficient mice. In summary, we identified the Mas axis as an important factor in macrophage function during inflammation of the central nervous and vascular system in vivo. Modulating the Mas axis may constitute an interesting therapeutic target in multiple sclerosis and/or atherosclerosis.
EVALuna2:22496

Role of "Western diet" in inflammatory autoimmune diseases - Manzel, Arndt; Muller, Dominik N.; Hafler, David A.; Erdman, Susan E.; Linker, Ralf; Kleinewietfeld, Markus (Current Allergy and Asthma Reports, 2014)
Developed societies, although having successfully reduced the burden of infectious disease, constitute an environment where metabolic, cardiovascular, and autoimmune diseases thrive. Living in westernized countries has not fundamentally changed the genetic basis on which these diseases emerge, but has strong impact on lifestyle and pathogen exposure. In particular, nutritional patterns collectively termed the "Western diet", including high-fat and cholesterol, high-protein, high-sugar, and excess salt intake, as well as frequent consumption of processed and 'fast foods', promote obesity, metabolic syndrome, and cardiovascular disease. These factors have also gained high interest as possible promoters of autoimmune diseases. Underlying metabolic and immunologic mechanisms are currently being intensively explored. This review discusses the current knowledge relative to the association of "Western diet" with autoimmunity, and highlights the role of T cells as central players linking dietary influences to autoimmune pathology.
EVALuna2:22289

Rotational coherent dot movement normalizes spatial disorientation of the subjective visual vertical in patients with rightsided stroke - Reinhart, S.; Schaadt, A. K.; Keller, I.; Hildebrandt, H.; Kerkhoff, G.; Utz, K. (Neuropsychologia, 2016)
Studies in healthy individuals indicate a significant influence of rotating visual motion on judgments of the subjective visual vertical (SVV). Moreover, sensory stimulation manoeuvres like horizontal coherent dot movement significantly modulate horizontal spatial deficits in patients with rightsided stroke. Here, we investigated whether rotational coherent dot movement (RCDM) modulates spatial orientation deficits of the SVV in the roll plane in right hemispheric stroke. We tested the perceptual judgment of the SVV in 20 patients with right-hemispheric, first ever stroke (10 of them with a disorder of the SVV and 10 without a disorder), and 10 healthy, age-matched subjects under three experimental conditions: (1) with a static background of small white dots, (2) with slow clockwise or (3) counterclockwise circular RCDM of these background stimuli. In the baseline condition with static background, the impaired patient group showed a counterclockwise tilt of the SVV. Clockwise RCDM normalized this deficit completely, while with counterclockwise RCDM a slight aggravation was observed. Similar but quantitatively much smaller effects were obtained in the SVV-unimpaired patients and the healthy individuals. These results demonstrate a strong modulatory effect of RCDM on the SVV in patients with a tilt of the SVV due to right-sided stroke. RCDM thus appears to influence higher spatial representations devoted to visuospatial perception of the SVV. Possible mechanisms as well as clinical implications for therapy of visuospatial disorientation (self-orientation in space) after stroke are discussed.
EVALuna2:22541

Routine diagnostics for neural antibodies, clinical correlates, treatment and functional outcome - Bien, Christian G.; Bien, Corinna I.; Onugoren, Muejgan; De Simoni, Desiree; Eigler, Verena; Haensch, Carl-Albrecht; Holtkamp, Martin; Ismail, Fatme S.; Kurthen, Martin; Melzer, Nico; Mayer, Kristina; Von Podewils, Felix; et al. (Journal of Neurology, 2020)
Objective To determine frequencies, interlaboratory reproducibility, clinical ratings, and prognostic implications of neural antibodies in a routine laboratory setting in patients with suspected neuropsychiatric autoimmune conditions. Methods Earliest available samples from 10,919 patients were tested for a broad panel of neural antibodies. Sera that reacted with leucine-rich glioma-inactivated protein 1 (LGI1), contactin-associated protein-2 (CASPR2), or the voltage-gated potassium channel (VGKC) complex were retested for LGI1 and CASPR2 antibodies by another laboratory. Physicians in charge of patients with positive antibody results retrospectively reported on clinical, treatment, and outcome parameters. Results Positive results were obtained for 576 patients (5.3%). Median disease duration was 6 months (interquartile range 0.6-46 months). In most patients, antibodies were detected both in CSF and serum. However, in 16 (28%) patients with N-methyl-d-aspartate receptor (NMDAR) antibodies, this diagnosis could be made only in cerebrospinal fluid (CSF). The two laboratories agreed largely on LGI1 and CASPR2 antibody diagnoses (kappa = 0.95). The clinicians (413 responses, 71.7%) rated two-thirds of the antibody-positive patients as autoimmune. Antibodies against the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR), NMDAR (CSF or high serum titer), gamma-aminobutyric acid-B receptor (GABABR), and LGI1 had >= 90% positive ratings, whereas antibodies against the glycine receptor, VGKC complex, or otherwise unspecified neuropil had <= 40% positive ratings. Of the patients with surface antibodies, 64% improved after >= 3 months, mostly with >= 1 immunotherapy intervention. Conclusions This novel approach starting from routine diagnostics in a dedicated laboratory provides reliable and useful results with therapeutic implications. Counseling should consider clinical presentation, demographic features, and antibody titers of the individual patient.
CRIS-Team WoS Importer:2020-04-14

S1-Guideline for Diagnosis and Treatment of Erectile Dysfunction [S1-Leitlinie Diagnostik und Therapie der erektilen Dysfunktion] - Haensch, Carl Albrecht; Hilz, Max-Josef; Jost, Wolfgang; Kaufmann, Albert; Kessler, Thomas; Lahrmann, Heinz (Fortschritte der Neurologie - Psychiatrie, 2019)
The S1-Guideline Diagnosis and Therapy of Erectile Dysfunction (Association of the Scientific Medical Societies in Germany (AWMF) registration number 030/112) is available in a completely revised version. Erectile dysfunction (ED) is defined as the persistent or recurrent inability to acquire or sustain an erection of sufficient rigidity and duration for sexual intercourse. There is a high prevalence of ED in the general population in Germany. The frequency of sexual activity decreases with age, and sexual problems become more common with aging. Overall, the prevalence of ED is 2.3 % in men 20 to 30 years of age and 53.4 % in men in their 7th decade of life. The guideline offers firm recommendations for the diagnosis and treatment of patients suffering from ED. The introduction of new oral therapies has completely changed the diagnostic and therapeutic approach to ED, which is often carried out in a uncritical way.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Erectile dysfunction; PDE-5 inhibitors; Sexual activity

Safety of Heparin for Prophylaxis of Venous Thromboembolism in Oral Anticoagulation-Associated Intracerebral Hemorrhage. - Sembill, Jochen; Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Salt-responsive gut commensal modulates TH17 axis and disease - Wilck, Nicola; Matus, Mariana G.; Kearney, Sean M.; Olesen, Scott W.; Forslund, Kristoffer; Bartolomaeus, Hendrik; Haase, Stefanie; Maehler, Anja; Balogh, Andras; Marko, Lajos; Vedenskaya, Olga V.; Kleiner, Friedrich H.; et al. (Nature, 2017)
A Western lifestyle with high salt consumption can lead to hypertension and cardiovascular disease. High salt may additionally drive autoimmunity by inducing T helper 17 (TH17) cells, which can also contribute to hypertension. Induction of TH17 cells depends on gut microbiota; however, the effect of salt on the gut microbiome is unknown. Here we show that high salt intake affects the gut microbiome in mice, particularly by depleting Lactobacillus murinus. Consequently, treatment of mice with L. murinus prevented salt-induced aggravation of actively induced experimental autoimmune encephalomyelitis and salt-sensitive hypertension by modulating TH17 cells. In line with these findings, a moderate high-salt challenge in a pilot study in humans reduced intestinal survival of Lactobacillus spp., increased TH17 cells and increased blood pressure. Our results connect high salt intake to the gut-immune axis and highlight the gut microbiome as a potential therapeutic target to counteract salt-sensitive conditions.
EVALuna2:22563

Satisfaction with and reliability of in-hospital video-EEG monitoring systems in epilepsy diagnosis – A German multicenter experience - Willems, Laurent M.; Baier, Hartmut; Bien, Christian G.; Bösebeck, Frank; Dümpelmann, Matthias; Hamer, Hajo; Kellinghaus, Christoph; Knake, Susanne; Schreiber, Melanie; Staack, Anke Maren; Surges, Rainer; Tergau, Frithjof; et al. (Clinical Neurophysiology, 2021)
Objective: To analyze satisfaction with and reliability of video-electroencephalography-monitoring systems (VEMS) in epilepsy diagnostics. Methods: A survey was conducted between December 2020 and January 2021 among German epilepsy centers using well-established customer satisfaction (CS) and quality assurance metrics. Results: Among 16 participating centers, CS with VEMS was low, with only 13% of customers actively recommending their system. Only 50% of users were satisfied with the overall performance of their VEMS, and a low 18% were satisfied with the manufacturer's customer service. User interface, software stability, lack of regular updates, and missing customer-oriented improvements were reported as frequent problems jeopardizing diagnosis in approximately every 10th patient. The greatest potential for improvement was identified for software and hardware stability as well as customer service. Conclusion: Satisfaction with VEMS and their customer service was low, and diagnostics were regularly affected by software or hardware errors. Even if this can be partly explained by the technical complexity of VEMS, there is an urgent need for improvements with regard to the reliability and durability of system components as well as signal synchrony and data management. Significance: This analysis highlights low consumer satisfaction of users with VEMS and uncovers frequent problems and potential for improvement.
CRIS-Team Scopus Importer:2021-07-02
Keywords: EEG; Medical technology; Quality; Safety; Telemedicine

Seizures among long-term survivors of conservatively treated ICH patients: incidence, risk factors, and impact on functional outcome - Madzar, Dominik; Kuramatsu, Joji; Gollwitzer, Stephanie; Lücking, Hannes; Kloska, Stephan; Hamer, Hajo; Köhrmann, Martin; Huttner, Hagen (Neurocritical Care, 2014)
Seizures are a common complication after intracerebral hemorrhage (ICH) but there is a substantial lack of information on the long-term incidence in ICH survivors and whether post-ICH seizures affect functional long-term outcome.Over a five-year period 464 consecutive patients with spontaneous ICH were analyzed. Focussing on 1-year ICH survivors, clinical, and radiological parameters were retrieved from institutional prospective databases. The occurrence of seizures was categorized as early (<=7 days) or late (>7 days). Functional outcome was assessed by mailed questionnaires and telephone interviews, and was categorized into good vs. poor (mRS: 0-2 vs. 3-5) and favorable vs. unfavorable (mRS: 0-3 vs. 4-5). Multivariate regression models were calculated to investigate risk factors associated with post-ICH seizures including an a priori defined subgroup analysis of lobar ICH patients.Among 203 long-term ICH survivors, 19.7 % developed seizures of which 55 % occurred late. Factors associated with seizures were lobar location (OR 8.10; 95 % CI 3.04-21.59; p < 0.001), sepsis (OR 4.59; 95 % CI 1.20-17.53; p = 0.026), and history of alcohol abuse (OR 3.36; 95 % CI 1.25-9.06; p = 0.017). Subgroup analysis of lobar ICH patients revealed history of alcohol abuse as the only independent predictor of post-ICH seizures (OR 5.22; 95 % CI 1.25-21.78; p = 0.024). Functional long-term outcome among survivors was slightly worse in patients with post-ICH seizures (p = 0.059). In multivariate regression modeling for prediction of poor outcome, the parameter "post-ICH seizures" again reached a statistical trend (p = 0.065), and established parameters such as age, GCS, and hemorrhage volume were independently related to poor outcome.Post-ICH seizures among long-term ICH survivors are common and may contribute to unfavorable functional outcome. Especially lobar ICH patients with a history of alcohol abuse are at risk to develop post-ICH seizures. Therefore, this subgroup may represent a target population for a prophylactic anticonvulsive treatment approach, preferably investigated in a prospective randomized trial.
EVALuna2:22307

Sensory stimulation in post-stroke postural imbalance: A novel treatment approach? - Schmidt, Lena; Kerkhoff, Georg; Utz, Kathrin S. (Clinical Neurophysiology, 2016)

Serelaxin activates eNOS, suppresses inflammation, attenuates developmental delay and improves cognitive functions of neonatal rats after germinal matrix hemorrhage - Xu, Ming M.; Seyler, L.; Bäuerle, Tobias; Kalinichenko, Liubov; Müller, Christian P.; Huttner, Hagen; Schwab, Stefan; Manaenko, A. (Scientific Reports, 2020)
Germinal matrix hemorrhage (GMH) is a detrimental form of neonatal CNS injury. Following GMH-mediated eNOS inhibition, inflammation arises, contributing to GMH-induced brain injury. We investigated the beneficial effects of Serelaxin, a clinical tested recombinant Relaxin-2 protein, on brain injury after GMH in rats. We investigated whether effects of Serelaxin are mediated by its ability to activate the GMH-suppressed eNOS pathway resulting in attenuation of inflammatory marker overproduction. GMH was induced by intraparenchymal injection of bacterial collagenase (0.3U). Seven day old Sprague–Dawley rat pups (P7) were used (n = 63). GMH animals were divided in vehicle or serelaxin treated (3 µg once, 30 µg once, 30 µg multiple, i.p., starting 30 after GMH and then daily). Sham operated animals were used. We monitored the developmental profile working memory and spatial function (T-maze and open field test respectively). At day 28, all rats underwent MRI-scans for assessment of changes in cortical thickness and white matter loss. Effects of Serelaxin on eNOS pathway activation and post-GMH inflammation were evaluated. We demonstrated that Serelaxin dose-dependently attenuated GMH-induced developmental delay, protected brain and improved cognitive functions of rats after GMH. That was associated with the decreased post-GMH inflammation, mediated at least partly by amelioration of GMH-induced eNOS inhibition.
CRIS-Team Scopus Importer:2020-05-29

Serial Pupillometer Readings Predicting Intracranial Pressure Crisis - Giede-Jeppe, Antje; Koehn, Julia; Gerner, Stefan; Kuramatsu, Joji; Huttner, Hagen; Schwab, Stefan (2018)
EVALuna2:35517

Serotonin transporter gene and stress reactivity in unipolar depression : Role of the HPA system as endophenotype of the SLC6A4 gene - Welper, H.; Aller, A.; Guttenthaler, V.; Hoefels, S.; Lennertz, L.; Pfeiffer, U.; Schwab, Stefan; Zobel, A. (Der Nervenarzt, 2014)
A length polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) is associated with both depression and hypothalamic-pituitary-adrenal (HPA) system activity. A dysregulation of the HPA system is considered to be a candidate endophenotype of depression. The objective of the present study was an investigation of a possible gene-endophenotype-interaction between 5-HTTLPR and HPA system activity in a sample of inpatients with major depression.A total of 237 inpatients with major depression were genotyped for 5-HTTLPR and participated in a combined dexamethasone-corticotropin-releasing hormone test (Dex-CRH test) as well as using the Hamilton score (Hamilton rating scale for depression) to determine the severity of the psychopathology.Patients with the ss-genotype showed a significantly higher HPA -system activity in comparison to patients with the lI-genotype, but no association between 5-HTTLPR and the severity of psychopathology could be detected.The results of the current study demonstrate an influence of 5-HTTLPR on dysregulation of the HPA system in patients with major depression and support the hypothesis that 5-HTTLPR- and HPA-system-interaction constitutes an important component in the pathogenesis of depression.
EVALuna2:23614

Severity assessment in maximally treated ICH patients: The max-ICH score - Sembill, Jochen; Gerner, Stefan; Volbers, Bastian; Bobinger, Tobias; Lücking, Hannes; Kloska, Stephan; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, 2017)
As common prognostication models in intracerebral hemorrhage (ICH) are developed variably including patients with early (<24 hours) care limitations (ECL), we investigated its interaction with prognostication in maximally treated patients and sought to provide a new unbiased severity assessment tool.This observational cohort study analyzed consecutive ICH patients (n = 583) from a prospective registry over 5 years. We characterized the influence of ECL on overall outcome by propensity score matching and on conventional prognostication using receiver operating characteristic analyses. We established the max-ICH score based on independent predictors of 12-month functional outcome in maximally treated patients and compared it to existing models.Prevalence of ECL was 19.2% (n = 112/583) and all of these patients died. Yet propensity score matching displayed that 50.7% (n = 35/69) theoretically could have survived, with 18.8% (n = 13/69) possibly reaching favorable outcome (modified Rankin Scale score 0-3). Conventional prognostication seemed to be confounded by ECL, documented by a decreased predictive validity (area under the curve [AUC] 0.67, confidence interval [CI] 0.61-0.73 vs AUC 0.80, CI 0.76-0.83; p < 0.01), overestimating poor outcome (mortality by 44.8%, unfavorable outcome by 10.1%) in maximally treated patients. In these patients, the novel max-ICH score (0-10) integrates strength-adjusted predictors, i.e., NIH Stroke Scale score, age, intraventricular hemorrhage, anticoagulation, and ICH volume (lobar and nonlobar), demonstrating improved predictive accuracy for functional outcome (12 months: AUC 0.81, CI 0.77-0.85; p < 0.01). The max-ICH score may more accurately delineate potentials of aggressive care, showing favorable outcome in 45.4% (n = 214/471) and a long-term mortality rate of only 30.1% (n = 142/471).Care limitations significantly influenced the validity of common prognostication models resulting in overestimation of poor outcome. The max-ICH score demonstrated increased predictive validity with minimized confounding by care limitations, making it a useful tool for severity assessment in ICH patients.
EVALuna2:22564

Severity of traumatic brain injury correlates with long-term cardiovascular autonomic dysfunction - Hilz, Max J.; Wang, Ruihao; Markus, Jörg; Ammon, Fabian; Hoesl, Katharina M.; Flanagan, Steven R.; Winder, Klemens; Koehn, Julia (Journal of Neurology, 2017)
After traumatic brain injury (TBI), central autonomic dysfunction might contribute to long-term increased mortality rates. Central autonomic dysfunction might depend on initial trauma severity. This study was performed to evaluate differences in autonomic modulation at rest and upon standing between patients with a history of mild TBI (post-mild-TBI patients), moderate or severe TBI (post-moderate-severe-TBI patients), and healthy controls. In 20 post-mild-TBI patients (6-78 months after TBI), age-matched 20 post-moderate-severe-TBI patients (6-94 months after TBI) and 20 controls, we monitored respiration, RR intervals (RRI) and systolic blood pressure (BPsys) at supine rest and upon standing. We determined mainly sympathetic low (LF) and parasympathetic high (HF) frequency powers of RRI fluctuations, sympathetically mediated LF-BPsys powers, LF/HF-RRI ratios, normalized (nu) LF-RRI and HF-RRI powers, and compared data between groups, at rest and upon standing (ANOVA with post hoc testing). We correlated autonomic parameters with initial Glasgow Coma Scale (GCS) scores (Spearman test; significance: p < 0.05). Supine BPsys and LFnu-RRI powers were higher while HFnu-RRI powers were lower in post-moderate-severe-TBI patients than post-mild-TBI patients and controls. LFnu-RRI powers were higher and HFnu-RRI powers were lower in post-mild-TBI patients than controls. Upon standing, only post-mild-TBI patients and controls increased LF-BPsys powers and BPsys and decreased HF-RRI powers. GCS scores correlated positively with LFnu-RRI powers, LF/HF-RRI ratios, and inversely with HFnu-RRI powers, at standing position. More than 6 months after TBI, there is autonomic dysfunction at rest and upon standing which is more pronounced after moderate-severe than mild TBI and in part correlates with initial trauma severity.
EVALuna2:22558

Sex differences in perihemorrhagic edema evolution after spontaneous intracerebral hemorrhage - Wagner, Irina; Volbers, Bastian; Kloska, Stephan; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background and purpose: Clinical data on sex differences in perihemorrhagic edema (PHE) after intracerebral hemorrhage (ICH) are lacking. Methods: Patients with spontaneous supratentorial ICH who had received standard conservative treatment were identified retrospectively. PHE development was assessed over a 14-day period on follow-up CT scans (days 1, 2-4, 5-7, 8-11, and 12-14). ICH and PHE volumes were assessed semiautomatically and compared between men and women. Results: A total of 387 patients (233 men) were included. Starting at days 2-4, women showed lower PHE values (P<0.05;/ days 2-4, 8-11) or a trend toward significance (P≤0.1; days 5-7, 12-14). Conclusions: Female sex may predict lower PHE volumes. © 2012 The Author(s) European Journal of Neurology © 2012 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Gender; Intracerebral hemorrhage; Perihemorrhagic edema

Sexual Dysfunction Seems to Trigger Depression in Female Multiple Sclerosis Patients - Hoesl, Katharina M.; Deutsch, Martina; Wang, Ruihao; Roy, Sankanika; Winder, Klemens; Niklewski, Guenter; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (European neurology, 2018)
BACKGROUND: In women with multiple sclerosis (MS), depression and sexual dysfunction (SD) are common. Whether SD promotes depression or vice versa remains unclear despite therapeutic relevance. Therefore, we aimed to assess whether SD more likely triggers depression or vice versa. METHODS: In 83 female MS patients and 21 age-matched healthy women, we assessed depression, using the Beck Depression Inventory-V (BDI-V), and SD using the Female Sexual Function Index (FSFI). We diagnosed depression with BDI-V-scores >35 and SD with FSFI scores < 26.55. We divided patients into groups with and without SD, with and without depression. Between groups, we compared prevalence of SD and depression (Fisher's-exact-test), age, MS-duration, MS-severity, BDI-V-, and FSFI scores (Mann-Whitney U-test; significance: p < 0.05). RESULTS: A total of 37/83 MS patients and 1/21 controls had SD; 28/83 patients and 3/21 controls had depression; 51.4% patients with SD but only 19.6% without SD had depression (p = 0.003). SD was present in 67.9% depressed and 32.7% non-depressed patients. BDI-V-scores were higher in patients with SD than in patients without SD. FSFI scores were lower in depressed than non-depressed patients. CONCLUSION: In conclusion, SD was more common than depression. SD afflicted 67.9% depressed MS patients and was also more common in non-depressed MS patients than controls. SD may occur independently from depression while increased depressiveness seems linked to coexistent SD.
EVALuna2:35522

Short inertial sensor-based gait tests reflect perceived state fatigue in multiple sclerosis - Ibrahim, Alzhraa; Flachenecker, Felix; Gaßner, Heiko; Rothammer, Veit; Klucken, Jochen; Eskofier, Björn; Kluge, Felix (Multiple Sclerosis and Related Disorders, 2022)
Background: Multiple sclerosis (MS) is a chronic autoimmune inflammatory disease of the central nervous system, affecting more than 2.3 million people worldwide. Fatigue is among the most common symptoms in MS, resulting in reduced mobility and quality of life. The six-minute walking test (6MWT) is commonly used as a measure of fatigability for the assessment of state fatigue throughout treatment or rehabilitation programs. This ‘gold standard’ test is time-consuming and can be difficult and exhausting for some patients with high levels of disability or high rates of fatigue. Research question: Can short inertial sensor-based gait tests assess perceived state fatigue in MS patients? Methods: Sixty-five MS patients equipped with one sensor on each foot performed the 6 min walk test (6MWT) and the 25-foot walk (25FW, at both preferred and fastest speed). Perceived state fatigue was measured after each minute of the 6MWT, using the Borg rating. The highest of these ratings served as a measure of overall perceived state fatigue. Stride-wise spatio-temporal gait parameters were extracted from the 25FW and from the first minute, first 2 min, and first 4 min of the 6MWT. Principal component analysis was performed. Perceived state fatigue was predicted in a regression analysis, using the principal components of gait parameters as predictors. Statistical tests evaluated differences in performance between the full 6MWT, the shortened 6MWT, and the 25FW. Results: A mean absolute error of less than 2 points on the Borg rating was obtained using the shortened 6MWT and the 25FW. There were no significant differences between the prediction accuracy of the full 6MWT and that of the shortened gait tests. Significance: It is possible to use shortened gait tests when evaluating perceived state fatigue in MS patients using inertial sensors. Substituting them for long gait tests may reduce the burden of the testing on both patients and clinicians. Further, the approach taken here may prompt future work to explore the use of short bouts of real-world walking with unobtrusive inertial sensors for state fatigue assessment.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Accelerometer; Fatigue; IMU; MS; Short gait test

Should non-convulsive Seizures and non-convulsive Status epilepticus be treated aggressively in the ICU: A Debate Comment - Madzar, D.; Hamer, Hajo (Klinische Neurophysiologie, 2020)
CRIS-Team WoS Importer:2021-01-08

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Siponimod reduces perihemorrhagic edema and improves neurological outcome in experimental intracerebral hemorrhage - Bobinger, Tobias; Manaenko, A.; Baeurele, T.; Seyler, L.; Nagel, Armin Michael; Engelhorn, Tobias; Dörfler, Arnd; Kuramatsu, J. B.; Schwab, Stefan; Huttner, Hagen (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Site and size of multiple sclerosis lesions predict enhanced or decreased female orgasmic function - Winder, Klemens; Seifert, Frank; Koehn, Julia; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (Journal of Neurology, 2015)
Neuroimaging identified brain areas involved in female orgasm. In women with multiple sclerosis (MS), associations between orgasmic function and the site and size of MS-related magnetic resonance imaging (MRI) changes are undetermined. This study intended to correlate MS-associated cerebral lesion load and location with clinical scores of female orgasmic function. In 50 women with MS (mean age 37.0 ± 9.9 years), we assessed Female Sexual Function Index (FSFI) scores for orgasmic frequency, difficulty and satisfaction. We determined disease duration, Expanded Disability Status Scale (EDSS) scores, and cerebral MS-lesion load and location using T2-weighed 1.5 T MRIs. We correlated FSFI scores for orgasm with patient age, disease duration, EDSS scores, and cerebral MS-lesion load (Spearman rank correlation; significance: p < 0.05). FSFI scores for orgasm correlated inversely with MS-lesion load in the left temporal periventricular white matter and right middle-inferior occipital area, but directly with MS-lesion load in the right frontal primary motor cortex, left prefrontal/inferior frontal cortex, right amygdala, left temporal middle-inferior and fusiform areas, and midbrain. FSFI scores for orgasm did not correlate with patient age, disease duration and EDSS scores (p > 0.05). In conclusion, our results indicate that MS-lesions in left temporal periventricular and right visual association areas deteriorate orgasmic function. In contrast, direct correlations between frontotemporal or midbrain lesions and higher FSFI scores, indicating enhanced or disinhibited orgasmic function, suggest that these brain regions normally buffer orgasmic responses. Moreover, our results indicate that orgasmic dysfunction in women with MS evolves independently of disease duration and physical disability.
EVALuna2:22361

Situation of breastfeeding in multiple sclerosis - a questionnaire survey in Germany - Aigner, S.; Huhn, Konstantin; Cepek, L.; Hellwig, K.; Nickel, Florian; Bayas, A. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Skin sodium is increased in male patients with multiple sclerosis and related animal models - Huhn, Konstantin; Linz, Peter; Pemsel, Franziska; Michalke, Bernhard; Seyferth, Stefan; Kopp, Christoph; Chaudri, Mohammad Anwar; Rothhammer, Veit; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.; Müller, Dominik N.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Novel MRI techniques allow a noninvasive quantification of tissue sodium and reveal the skin as a prominent compartment of sodium storage in health and disease. Since multiple sclerosis (MS) immunopathology is initiated in the periphery and increased sodium concentrations induce proinflammatory immune cells, the skin represents a promising compartment linking high sodium concentrations and MS immunopathology. We used a 7-T sodium MRI (23Na-MRI) and inductively coupled plasma mass spectrometry to investigate the skin sodium content in two mouse models of MS. We additionally performed 3-T 23Na-MRI of calf skin and muscles in 29 male relapsing-remitting MS (RRMS) patients and 29 matched healthy controls. Demographic and clinical information was collected from interviews, and disease activity was assessed by expanded disability status scale scoring. 23Na-MRI and chemical analysis demonstrated a significantly increased sodium content in the skin during experimental autoimmune encephalomyelitis independent of active immunization. In male patients with RRMS, 23Na-MRI demonstrated a higher sodium signal in the area of the skin compared to age- and biological sex-matched healthy controls with higher sodium, predicting future disease activity in cranial MRI. In both studies, the sodium enrichment was specific to the skin, as we found no alterations of sodium signals in the muscle or other tissues. Our data add to the recently identified importance of the skin as a storage compartment of sodium and may further represent an important organ for future investigations on salt as a proinflammatory agent driving autoimmune neuroinflammation such as that in MS.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Skin; Sodium magnetic resonance imaging

Slow-theta power decreases during item-place encoding predict spatial accuracy of subsequent context recall - Crespo-Garcia, Maite; Zeiller, Monika; Leupold, Claudia; Kreiselmeyer, Gernot; Rampp, Stefan; Hamer, Hajo; Dalal, Sarang S. (NeuroImage, 2016)
Human hippocampal theta oscillations play a key role in accurate spatial coding. Associative encoding involves similar hippocampal networks but, paradoxically, is also characterized by theta power decreases. Here, we investigated how theta activity relates to associative encoding of place contexts resulting in accurate navigation. Using MEG, we found that slow-theta (2-5Hz) power negatively correlated with subsequent spatial accuracy for virtual contextual locations in posterior hippocampus and other cortical structures involved in spatial cognition. A rare opportunity to simultaneously record MEG and intracranial EEG in an epilepsy patient provided crucial insights: during power decreases, slow-theta in right anterior hippocampus and left inferior frontal gyrus phase-led the left temporal cortex and predicted spatial accuracy. Our findings indicate that decreased slow-theta activity reflects local and long-range neural mechanisms that encode accurate spatial contexts, and strengthens the view that local suppression of low-frequency activity is essential for more efficient processing of detailed information.
EVALuna2:22490

Sociodemographic disparities in administration of antiepileptic drugs to adults with epilepsy in Germany: a retrospective, database study of drug prescriptions - Hamer, Hajo; Kostev, Karel (Cns Drugs, 2014)
Large epidemiological databases facilitate the study of medical care in different subgroups of the population and how such care compares with standard treatment guidelines. This study aimed for such analyses regarding utilization of antiepileptic drugs (AEDs) for epilepsy in Germany.The data source was the Disease Analyzer(®) database that is representative for the German population and assembles anonymous demographic and medical (diagnoses, prescriptions) data obtained from the practice computer system of general practitioners and specialists throughout Germany. A total of 43,712 adult patients with an epilepsy diagnosis (International Classification of Diseases, 10th edition [ICD10] code: G40.X) seen in 2010-2012 by 346 neurologists were retrospectively analysed according to sociodemographic characteristics, comorbidity, and AED treatment. Multivariate logistic regression was applied to calculate adjusted odds ratios (ORs) with 95 % confidence intervals (CIs).As compared with women, men were less likely to receive lamotrigine (OR 0.68; 95 % CI 0.65-0.72; p < 0.001) and were treated preferably with carbamazepine (OR 1.29; 95 % CI 1.23-1.35; p < 0.001). As compared with patients covered by private health insurance (PHI), patients with statutory health insurance (SHI) were treated more often with valproate (OR 1.19; 95 % CI 1.07-1.31; p < 0.001) and showed a higher rate of obesity (SHI: 3.1 %; PHI: 1.6 %; p < 0.001), while PHI was associated with administration of levetiracetam (OR 1.27; 95 % CI 1.16-1.4; p < 0.001). Carbamazepine (OR 1.25; 95 % CI 1.17-1.31; p < 0.001) and primidone (OR 1.23; 95 % CI 1.08-1.38; p < 0.001) were administered to a larger extent in rural versus urban areas. Lamotrigine (OR 1.31; 95 % CI 1.23-1.39; p < 0.001) was used more often in West than in East Germany. Living in an urban community raised the likelihood of being treated with levetiracetam (OR 1.23; 95 % CI 1.17-1.28; p < 0.001).In spite of common guidelines, AED treatment differed significantly among adults with epilepsy in Germany. Besides gender, type of health insurance and place of residence strongly influenced AED administration.
EVALuna2:22317

Sodium chloride triggers Th17 mediated autoimmunity - Haase, Stefanie; Wilck, Nicola; Kleinewietfeld, Markus; Mueller, Dominik N.; Linker, Ralf (Journal of Neuroimmunology, 2019)
The detrimental effects of a high-salt diet on human health have received much attention in the past few years. While it has been well established that high dietary salt intake is related to cardiovascular diseases, there is growing evidence that excess salt also affects the immune system and might be considered as a risk factor in autoimmune diseases such as multiple sclerosis (MS). Several studies have implicated T helper 17 cells (Th17) in the pathogenesis of MS. We and others recently demonstrated that excessive salt enhances the differentiation of Th17 cells, inducing a highly pathogenic phenotype that aggravates experimental neuroinflammation. Moreover, a diet rich in sodium affects intestinal microbiota alongside increased intestinal Th17 cells, thus linking the detrimental effects of high salt consumption to the gut-immune axis. First human studies revealed an association of increased MS disease activity with elevated sodium chloride consumption, while more recent epidemiology studies in larger cohorts suggest no correlation between salt intake and MS. However, it is known that ordinary urinary sodium analyses and nutritional questionnaires do not necessarily correspond to the actual sodium load and more sophisticated analyses are needed. Moreover, studies revealed that sodium can temporarily be stored in the body. This review summarizes recent findings on the impact of salt on the immune system and discusses potential challenges investigating dietary salt intake as a risk factor in MS.
CRIS-Team WoS Importer:2019-04-09

Sollte man nicht konvulsive Anfälle und den nicht konvulsiven Status epilepticus auf der Intensivstation aggressiv behandeln: Eine Debatte - Madzar, Dominik; Hamer, Hajo (Klinische Neurophysiologie, 2020)
CRIS-Team Scopus Importer:2021-04-19

Spasticity treatment with onabotulinumtoxin A: data from a prospective German real-life patient registry - Schramm, Axel; Ndayisaba, Jean-Pierre; Brinke, Matthias Auf Dem; Hecht, Martin; Herrmann, Christoph; Huber, Martin; Lobsien, Elmar; Mehnert, Sabine; Reuter, Iris; Stenner, Andrea; Van Der Ven, Christian; Winterholler, Martin; et al. (Journal of Neural Transmission, 2014)
This study aimed at providing real-life baseline, injection and outcome data for the treatment of various forms of spasticity with onabotulinumtoxin A in Germany. Prospective data were collected in an open multicenter patient registry from 2005 until 2010, encompassing the experience of ten specialized German centers in the treatment of spasticity using onabotulinumtoxin A in 508 patients with a total of 2005 treatment sessions. Disease entities comprised spasticity following stroke (both ischemic and hemorrhagic), traumatic brain injury, multiple sclerosis, cerebral palsy, and anoxia. Sustained improvement was observed in a variety of outcome parameters including goal attainment and motor performance scores for up to five repeated injection sessions. No significant differences between disease entities or between upper and lower limb treatment were observed with regard to efficacy and safety following onabotulinumtoxin A treatment. Minor to moderate side effects were reported in <1 % of the study population. We conclude that repetitive treatment of focal and multifocal spasticity with onabotulinumtoxin A provides a safe and efficacious therapeutic strategy for patients with different disease entities of the central nervous system.
EVALuna2:22323

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Möller, Sebastian; Huber, Angelika; Lücking, Hannes; Kloska, Stephan; Madzar, Dominik; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (Stroke, 2017)
Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established.Conservatively treated patients with supratentorial ICH, admitted to our hospital over a 5-year period (2008-2012), were retrospectively analyzed. Lobar patients were classified as isolated or overlapping ICH according to affected lobes. Demographic, clinical, and radiological characteristics were recorded and compared among lobar ICH patients using above subclassification. Functional outcome-dichotomized into favorable (modified Rankin Scale, 0-3) and unfavorable (modified Rankin Scale, 4-6)-was assessed after 3 and 12 months. Multivariate regression analysis was performed to identify predictors for favorable outcome.Of overall 553 patients, 260 had lobar ICH. In isolated lobar ICH, median hematoma-volume decreased from rostral (frontal, 22.4 mL [7.3-55.5 mL]) to caudal (occipital, 7.1 mL [5.2-16.4 mL]; P=0.045), whereas the proportion of patients with favorable outcome increased (frontal: 23/63 [36.5%] versus occipital: 10/12 [83.3%]; P=0.003). Patients with overlapping lobar ICH had larger ICH volumes than isolated lobar ICH (overlapping, 48.9 mL [22.6-78.5 mL] versus 15.3 mL [5.0-44.6 mL]; P<0.001) and poorer clinical status on admission (Glasgow Coma Scale and National Institutes of Health Stroke Scale). Correlations with anatomic aspects provided evidence of a rostrocaudal gradient with increasing gray/white-matter ratio and decreasing hematoma-volume and rate of hematoma enlargement from frontal to occipital ICH location. Multivariate analysis revealed affection of occipital lobe (odds ratio, 3.75 [1.38-10.22]) and affection of frontal lobe (odds ratio, 0.52 [0.28-0.94]) to be independent predictors for favorable outcome and unfavorable outcome, respectively.Among patients with lobar ICH radiological and outcome characteristics differed according to location. Especially affection of the frontal lobe was frequent and associated with unfavorable outcome after 3 months.
EVALuna2:22482

Spectral fingerprints or spectral tilt? Evidence for distinct oscillatory signatures of memory formation - Fellner, Marie-Christin; Gollwitzer, Stephanie; Rampp, Stefan; Kreiselmeyr, Gernot; Bush, Daniel; Diehl, Beate; Axmacher, Nikolai; Hamer, Hajo; Hanslmayr, Simon (Plos Biology, 2019)
Decreases in low-frequency power (2-30 Hz) alongside high-frequency power increases (>40 Hz) have been demonstrated to predict successful memory formation. Parsimoniously, this change in the frequency spectrum can be explained by one factor, a change in the tilt of the power spectrum (from steep to flat) indicating engaged brain regions. A competing view is that the change in the power spectrum contains several distinct brain oscillatory fingerprints, each serving different computations. Here, we contrast these two theories in a parallel magnetoencephalography (MEG)-intracranial electroencephalography (iEEG) study in which healthy participants and epilepsy patients, respectively, studied either familiar verbal material or unfamiliar faces. We investigated whether modulations in specific frequency bands can be dissociated in time and space and by experimental manipulation. Both MEG and iEEG data show that decreases in alpha/beta power specifically predicted the encoding of words but not faces, whereas increases in gamma power and decreases in theta power predicted memory formation irrespective of material. Critically, these different oscillatory signatures of memory encoding were evident in different brain regions. Moreover, high-frequency gamma power increases occurred significantly earlier compared to low-frequency theta power decreases. These results show that simple spectral tilt cannot explain common oscillatory changes and demonstrate that brain oscillations in different frequency bands serve different functions for memory encoding.
CRIS-Team WoS Importer:2019-08-23

Sport and Physical Activity in Epilepsy - van den Bogard, Fanziska; Hamer, Hajo; Sassen, Robert; Reinsberger, Claus (Deutsches Ärzteblatt international, 2020)
BACKGROUND: For many years, people with epilepsy were advised not to engage in sports. In this systematic review, we investigated whether persons with epilepsy exercise less than the general population, and what effect physical activity has on epilepsy. METHODS: A literature search was carried out in PubMed and the Web of Science, and 14 269 studies were entered into the selection process. The selected studies were assessed for their methodological quality and accordingly assigned an evidence level. RESULTS: 42 studies were included in the review; 10 were classified as evidence level 3, 27 as evidence level 2-, 2 as evidence level 2+, and 3 as evidence level 1-. Persons with epilepsy are less physically active and less physically fit than the general population. Reduced physical activity is associ- ated with a higher frequency of comorbidities and lower quality of life. Physical interventions can improve quality of life. In most cases, physical exercise did not increase seizure frequency. CONCLUSION: There is no reason to forbid persons with epilepsy to participate in sports; they should, rather, be encour- a particular type of sport should, however, be taken individually in each case.
CRIS-Team Scopus Importer:2020-02-11

Statistical analysis plan for the EuroHYP-1 trial: European multicentre, randomised, phase III clinical trial of the therapeutic hypothermia plus best medical treatment versus best medical treatment alone for acute ischaemic stroke - Winkel, Per; Bath, Philip M.; Gluud, Christian; Lindschou, Jane; Van Der Worp, H. Bart; Macleod, Malcolm R.; Szabo, Istvan; Durand-Zaleski, Isabelle; Schwab, Stefan (Trials, 2017)
BACKGROUND: Cooling may reduce infarct size and improve neurological outcomes in patients with ischaemic stroke. In phase II trials, cooling awake patients with ischaemic stroke has been shown to be feasible and safe, but the effects in functional outcomes has not yet been investigated in an adequately sized randomised clinical trial. METHODS/DESIGN: The EuroHYP-1 trial is a multinational, randomised, superiority phase III clinical trial with masked outcome assessment testing the benefits and harms of therapeutic cooling in awake adult patients with acute ischaemic stroke. The outcomes dealt with here include the primary outcome the Rankin score (mRS) at day 91 +/-14 days after randomisation. The secondary and exploratory outcomes at day 91 +/-14 days unless otherwise stated encompassing: (1) death or dependency, defined as mRS score > 2; (2) death; (3) National Institutes of Health Stroke Score; (4) brain infarct size at 48 +/-24 hours; (5) EQ-5D-5 L score, and (6) WHODAS 2.0 score. Other outcomes are: the primary safety outcome serious adverse events; and the incremental cost-effectiveness, and cost utility ratios. The analysis sets include (1) the intention-to-treat population, and (2) the per protocol population. The sample size is estimated to 800 patients (5% type 1 and 20% type 2 errors). All analyses are adjusted for the protocol-specified stratification variables (nationality of centre), and the minimisation variables. In the analysis, we use ordinal regression (the primary outcome), logistic regression (binary outcomes), general linear model (continuous outcomes), and the Poisson or negative binomial model (rate outcomes). DISCUSSION: Major adjustments compared with the original statistical analysis plan encompass: (1) adjustment of analyses by nationality; (2) power calculations for the secondary outcomes; (3) to address the multiplicity problem using of a fixed-sequence testing procedure starting with the primary outcome followed by the secondary outcomes ordered according to falling power; (4) assignment of worst possible score to patients who are not alive at the planned date of measurement of the continuous scores; (5) improved imputations; (6) outline of a supplementary exploratory analysis of the temperature measurements and time to death; and (7) substantial reduction of sample size. TRIAL REGISTRATION: Clinicaltrials.gov, identifier: NCT01833312 . 4 April 2013.
EVALuna2:33128

Status epilepticus-Detection and treatment in the intensive care unit - Reindl, Caroline; Madzar, Dominik; Hamer, Hajo (Der Nervenarzt, 2022)
Status epilepticus is characterized by persistent or repetitive seizures which, without successful treatment, can lead to neuronal damage, neurological deficits and death of the patient. While status epilepticus with motor symptoms can usually be clinically diagnosed, nonconvulsive status epilepticus is often clinically overlooked due to its ambiguous semiology, so that electroencephalography (EEG) recording is necessary. The treatment of status epilepticus is performed in four treatment steps, whereby a difficult to treat status epilepticus is present from the third step at the latest and intensive medical care of the patient is necessary. Timely initiation of treatment and sufficient dosage of anticonvulsive medication are decisive for the success of treatment. There is little evidence for the "late " stages of treatment. Intensive medical measures pose the risk of complications that worsen the prognosis. Especially in nonconvulsive status epilepticus, the use of anesthetics must be weighed against possible complications of mechanical ventilation.
CRIS-Team WoS Importer:2023-01-13

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Status of clinical research in neurology in Germany—A national survey - Lohmann, Lisa; Lammerskitten, Anna; Korsen, Melanie; Dodel, Richard; Gaul, Charly; Hamer, Hajo; Kleineberg, Nina N.; Ludolph, Albert C.; Mayer, Geert; Poli, Sven; Saur, Dorothee; Steinhoff, Bernhard J.; et al. (European Journal of Neurology, 2021)
Background and purpose: To provide an overview on the status of clinical research in neurology in Germany. Methods: German university hospitals, nonuniversity hospitals, and neurological medical practices were surveyed regarding their clinical research activities during the period 2013 to 2017. Results: Fifty percent of university hospitals, 10.6% of nonuniversity hospitals, and 5.2% of medical practices in Germany responded to our questionnaire. More than 80% of the clinical studies conducted have been phase III/IV and noninterventional trials (NISs), whereas <1% have been phase I and 3.5% investigator-initiated trials (IITs). University hospitals have conducted most of the phase II–IV trials. NISs have been predominantly performed by medical practices. Fifty-six percent of the university hospitals and less of the nonuniversity institutions confirmed the implementation of standard operating procedures (SOPs). In university hospitals, on average, 11 physicians had acquired a good clinical practice certificate. Overall, 43% of all trials have been performed in neuroimmunology. Conclusions: The status of clinical research in neurology in Germany is predominated by NISs and late-phase trials, potentially due to a general lack of easily accessible funding, which leads to a highly competitive environment and fewer opportunities to perform early-phase clinical trials as well as IITs. Our results indicate that there is substantial need for structured support for creating and implementing SOPs to maintain quality standards and guarantee uniformity of performance. This survey assessed many aspects of clinical research and serves as guidance for providing ideas for structured improvement of clinical research in neurology in Germany.
CRIS-Team Scopus Importer:2021-03-19
Keywords: clinical research; Germany; good clinical practice; survey

Stent-Assisted Coiling Using Leo+ Baby Stent: Immediate and Mid-Term Results - Lücking, Hannes; Struffert, Tobias; Gölitz, Philipp; Engelhorn, Tobias; Brandner, Sebastian; Kuramatsu, Joji; Lang, Stefan; Schmidt, Manuel; Dörfler, Arnd (Clinical Neuroradiology, 2020)
Background: Stent-assisted coiling is well-established for treatment of cerebral aneurysms. The technique enables treatment of wide-neck, bifurcation and recurrent aneurysms with high packing rates. While described in extenso for laser cut stents, the results of patients treated with the Leo+ Baby (Balt, Montmorency, France) braided microstent are presented. Material and Methods: Patients were included if treated with a Leo+ Baby and with digital subtraction angiography (DSA) follow-up available of at least 6 months. Data were evaluated for successful deployment, aneurysm occlusion according to the modified Raymond-Roy classification (MRRC), stent patency and procedure-related morbidity and mortality. Results: A total of 81 patients were included and Leo+ Baby deployment was successful in all cases. Coils were used in 80 cases. In 1 case 2 stents were used stent-in-stent without additional coiling. Initial aneurysm occlusion rates were MRRCi1 51.9%, MRRCi2 11.1%, MRRCi3a 24.7% and MRRCi3b 12.3%. Occlusion rates after 6 months were MRRC6m1 78.9%, MRRC6m2 3.9%, MRRC6m3a 6.6% and MRRC6m3b 10.5%. Procedure-related morbidity was 1 case of acute stent thrombosis successfully treated with tirofiban and 1 case with transient hemiparesis due to stent thrombosis after 4 months. There was 1 case of coil-associated subarachnoid hemorrhage (SAH) which caused prolonged hospitalization. No procedure-related mortality was observed. Conclusion: The results confirm that stent-assisted coiling with the Leo+ Baby stent is safe and efficient for treatment of wide neck or recurrent cerebral aneurysms. Spontaneous progressive aneurysm occlusion over 6 months supports the theory of considerable flow-modulating effects of Leo+ Baby.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Bifurcation aneurysm; Braided stent; Cerebral aneurysm; Coiling; Low profile stent

Stress, seizures, and epilepsy: Patient narratives - Lang, Johannes D.; Taylor, David C.; Kasper, Burkhard (Epilepsy and Behavior, 2018)
In epilepsy, individual seizures can be triggered by a variety of external and internal stimuli. One of the most common trigger factors reported by patients is stress. However prevalent, stress-related triggering of episodes seems underappreciated in epilepsy for various reasons, and its misinterpretation often leads to other diagnoses, e.g., psychogenic nonepileptic seizures (PNES) or normal reactions. This article illustrates the significant role of stress as a seizure-provoking factor by referring to nine patient narratives. From this perspective, it appears that there are characteristic patterns of stress triggering, e.g., stress-induced sleep disruption, forms of acute stress, or relaxation after stress. Sometimes seizures are mistaken as symptoms of stress. Patient narratives contain interesting clues relating reports about stress and seizure histories to different epilepsy syndromes as well as nonepileptic episodes in a way that can strongly support the diagnostic process. A narrative approach is particularly valuable in this context. Therefore, accounts of stress triggering in seizures and other episodes should not be neglected, but rather taken seriously, sought and actively explored as a crucial element when taking clinical histories in patients with episodic attacks.
EVALuna2:201938

STROKE CARE PERFORMANCE MEASURES DURING THE COVID-19 PANDEMIC - OVER THE WAVES - Gaßmann, Luise; Haupenthal, David; Kallmünzer, Bernd; Köhn, Julia; Schwab, Stefan; Kuramatsu, Joji (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

STROKE SIMULATION TRAINING IN A RURAL TELESTROKE NETWORK SETTING IN NORTHERN BAVARIA (STENO): PRELIMINARY RESULTS - Volbers, Bastian; Schwab, Stefan (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Stroma cells promote a S100A8/A9(high) subset of chemoresistant AML blasts with distinct metabolic features in a Jak/STAT-dependent manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, K.; Popp, Sebastian; Geyh, S.; Jaeger, P.; Schroeder, T.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Subliminal galvanic-vestibular stimulation recalibrates the distorted visual and tactile subjective vertical in right-sided stroke - Oppenlaender, Karin; Utz, Kathrin S.; Reinhart, Stefan; Keller, Ingo; Kerkhoff, Georg; Schaadt, Anna-Katharina (Neuropsychologia, 2015)
Stroke of the right cerebral hemisphere often causes deficits in the judgement of the subjective visual vertical (SVV) and subjective tactile vertical (STV) which are related to central vestibular functioning. Clinically, deficits in the SVV/STV are linked to balance problems and poor functional outcome. Galvanic Vestibular Stimulation (GVS) is a non-invasive, save stimulation technique that induces polarity-specific changes in the cortical vestibular systems. Subliminal GVS induces imperceptible vestibular stimulation without unpleasant side effects. Here, we applied bipolar subliminal GVS over the mastoids (mean intensity: 0.7 mA, 20 min duration per session) to investigate its online-influence on constant errors, difference thresholds and range values in the SVV and STV. 24 patients with subacute, single, unilateral right hemisphere stroke were studied and assigned to two patient groups (impaired vs. normal in the SVV and STV) on the basis of cut-off scores from healthy controls. Both groups performed these tasks under three experimental conditions on three different days: a) sham GVS where electric current was applied only for 30s and then turned off, b) left-cathodal GVS and c) right-cathodal GVS, for a period of 20 min per session. Left-cathodal GVS, but not right-cathodal GVS significantly reduced all parameters in the SVV. Concerning STV GVS also reduced constant error and range numerically, though not significantly. These effects occurred selectively in the impaired patient group. In conclusion, we found that GVS rapidly influences poststroke verticality deficits in the visual and tactile modality, thus highlighting the importance of the vestibular system in the multimodal elaboration of the subjective vertical.
EVALuna2:22409

SUDEP kompakt – praxisrelevante Erkenntnisse und Empfehlungen zum plötzlichen, unerwarteten Tod bei Epilepsie - Surges, Rainer; Conrad, Stefan; Hamer, Hajo; Schulze-Bonhage, Andreas; Staack, Anke M.; Steinhoff, Bernhard J.; Strzelczyk, Adam; Trinka, Eugen (Der Nervenarzt, 2021)
Sudden unexpected death in epilepsy (SUDEP) is the sudden and unexpected death of an epilepsy patient, which occurs under benign circumstances without evidence of typical causes of death. SUDEP concerns all epilepsy patients. The individual risk depends on the characteristics of the epilepsy and seizures as well as on living conditions. Focal to bilateral and generalized tonic-clonic seizures (TCS), nocturnal seizures and lack of nocturnal supervision increase the risk. Most SUDEP cases are due to a fatal cascade of apnea, hypoxemia and asystole in the aftermath of a TCS. Two thirds of SUDEP cases in unsupervised epilepsy patients with TCS could probably be prevented. Wearables can detect TCS and alert caregivers. SUDEP information is desired by most patients and relatives, has a favorable impact on treatment adherence and behavior and has no negative effects on mood and quality of life. Recommendations of the committee on patient safety of the German Society of Epileptology: the ultimate treatment goal is seizure freedom. If this cannot be achieved, control of TCS should be sought. All epilepsy patients and their relatives should be informed about SUDEP and risk factors. Patients and relatives should be informed about measures to counteract the elevated risk and imminent SUDEP. The counselling should be performed during a face-to-face discussion, at the time of first diagnosis or during follow-up visits. The counselling should be documented. Wearables for TCS detection can be recommended. If TCS persist, therapeutic efforts should be continued. The bereaved should be contacted after a SUDEP.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Asystole; Counselling; Premature mortality; Sudden death in epilepsy; Wearables

Supratentorial lesions contribute to trigeminal neuralgia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank (Cephalalgia, 2018)
Background It has been proposed that multiple sclerosis lesions afflicting the pontine trigeminal afferents contribute to trigeminal neuralgia in multiple sclerosis. So far, there are no imaging studies that have evaluated interactions between supratentorial lesions and trigeminal neuralgia in multiple sclerosis patients. Methods We conducted a retrospective study and sought multiple sclerosis patients with trigeminal neuralgia and controls in a local database. Multiple sclerosis lesions were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed a voxel-wise subtraction analysis. Secondly, we conducted a voxel-wise non-parametric analysis using the Liebermeister test. Results From 12,210 multiple sclerosis patient records screened, we identified 41 patients with trigeminal neuralgia. The voxel-wise subtraction analysis yielded associations between trigeminal neuralgia and multiple sclerosis lesions in the pontine trigeminal afferents, as well as larger supratentorial lesion clusters in the contralateral insula and hippocampus. The non-parametric statistical analysis using the Liebermeister test yielded similar areas to be associated with multiple sclerosis-related trigeminal neuralgia. Conclusions Our study confirms previous data on associations between multiple sclerosis-related trigeminal neuralgia and pontine lesions, and showed for the first time an association with lesions in the insular region, a region involved in pain processing and endogenous pain modulation.
EVALuna2:34503

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Surgical management of epilepsy due to cerebral cavernomas using neuronavigation and intraoperative MR imaging - Sommer, Bjoern; Kasper, Burkhard S.; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2013)
Objectives: Cure from seizures due to cavernomas might be surgically achieved dependent on both, the complete removal of the cavernoma as well as its surrounding hemosiderin rim. High field intraoperative MRI imaging (iopMRI) and neuronavigation might play a crucial role to achieve both goals. We retrospectively investigated the long-term results and impact of intraoperative 1.5T MRI (iopMRI) and neuronavigation on the completeness of surgical removal of a cavernous malformation (CM) and its perilesional hemosiderin rim as well as reduction of surgical morbidity. Methods: 26 patients (14 female, 12 male, mean age 39.1 years, range: 17-63 years) with CM related epilepsy were identified. Eighteen patients suffered from drug resistant epilepsy (69.2%). Mean duration of epilepsy was 11.9 years in subjects with drug resistant epilepsy (n = 18) and 0.3 years in subjects presenting with first-time seizures (n = 8). We performed 24 lesionectomies and two lesionectomies combined with extended temporal resections. Seven lesions were located extratemporally. Results: Complete CM removal was documented by postsurgical MRI in all patients. As direct consequence of iopMRI, refined surgery was necessary in 11.5% of patients to achieve complete cavernoma removal and in another 11.5% for complete resection of additional adjacent epileptogenic cortex. Removal of the hemosiderin rim was confirmed by iopMRI in 92% of patients. Two patients suffered from mild (7.7%) and one from moderate (3.8%) visual field deficits. Complete seizure control (Engel class 1A) was achieved in 80.8% of patients with a mean follow-up period of 47.7 months. Discussion: We report excellent long-term seizure control with minimal surgical morbidity after complete resection of CM using our multimodal approach. © W. S. Maney & Son Ltd 2013.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cavernous hemangioma; Epilepsy outcome; Intraoperative high field MRI; Surgical morbidity

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Switching the manufacturer of antiepileptic drugs is associated with higher risk of seizures: A nationwide study of prescription data in Germany - Lang, Johannes D.; Kostev, Karel; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Graf, Wolfgang; Müller, Tamara; Olmes, David G.; Hamer, Hajo (Annals of Neurology, 2018)
OBJECTIVE: Despite bioequivalence, the exchangeability of antiepileptic drugs in clinical settings is disputed. Therefore, we investigated the risk for recurrent seizures after switching the manufacturer of the same drug in a large German cohort. METHODS: Anonymous patient data from practice neurologists throughout Germany between 2011 and 2016 were collected using the IMS Disease Analyzer database (QuintilesIMS, Frankfurt, Germany). People with epilepsy were included if at least 2 prescriptions within 360 days and 1 within 180 days prior to the index date were available. The cohort was separated into a seizure group and seizure-free controls. Both groups were matched 1:1 according to age, gender, insurance status, and treating physician. The risk for breakthrough seizures after a manufacturer switch of the same antiepileptic drug was analyzed using multivariate regression models. RESULTS: A total of 3,530 people with epilepsy were included (each group, n = 1,765; age = 53.7 ± 19.8 years). Patients with seizures had switched the drug manufacturer more often than controls (26.8% vs 14.2%; odds ratio [OR] = 1.35, 95% confidence interval [CI] = 1.08-1.69, p = 0.009), both from branded to generic (5.5% vs 2.4%; OR = 1.85, 95% CI = 1.30-2.64, p < 0.001) and between generic drugs (14.7% vs 7.1%; OR = 1.45, 95% CI = 1.13-1.87, p = 0.004). INTERPRETATION: In previously seizure-free patients, switching the manufacturer of antiepileptic medications was associated with a higher risk for seizure recurrence. Our retrospective approach does not allow us to determine whether other changes in medical care at the same time could contribute to the recurrence. However, it would be prudent to avoid switching the manufacturer of anticonvulsants in seizure-free patients. Ann Neurol 2018;84:918-925.
EVALuna2:201934

Symmetric tract-based spatial statistics of patients with left versus right mesial temporal lobe epilepsy with hippocampal sclerosis - Mennecke, Angelika; Rösch, Julie; Kasper, Burkhard; Schmidt, Manuel; Roessler, Karl; Coras, Roland; Hamer, Hajo; Dörfler, Arnd; Laun, Frederik Bernd (NeuroReport, 2018)
This study aims to investigate the diffusion metrics of left versus right temporal lobe epilepsy in a well-defined subgroup of patients with mesial temporal lobe epilepsy (mTLE) because of unilateral hippocampal sclerosis while taking into account interhemispheric differences. Eighteen patients with TLE [nine left temporal lobe epilepsy (LTLE) and nine right temporal lobe epilepsy (RTLE)] and a norm group of 36 nonepileptic individuals were scanned with a multiband accelerated diffusion tensor imaging protocol at 3T. The scalar diffusion tensor parameters fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) and, after projection on a symmetric skeleton, their hemispheric difference (dFA, dMD, and dRD) were analyzed using tract-based spatial statistics. In the cluster with significantly (P<0.008) different dFA, dMD, and dRD between right TLE and left TLE, the hemispheric difference in the mean scalar indices (dmFA, dmMD, and dmRD) was assessed and tested for differences using a one-way analysis of variance and for correlation with patient age, seizure onset, or duration of epilepsy using Pearson's correlation. Patients with LTLE showed lower dFA, higher dMD, and higher dRD (P<0.008) compared with patients with RTLE in a cluster including parts of the uncinated and inferior longitudinal fasciculus and the inferior fronto-occipital fasciculus. dmFA, dmMD, and dmRD differed significantly between groups (P<10, corrected) and showed no correlation with patient age, seizure onset, or duration of epilepsy. The exclusion of bilateral interindividual variance through the calculation of the hemispheric difference of the diffusion metrics by the symmetric variant of tract-based spatial statistics allows for a sensitive differentiation of LTLE and RTLE with unilateral hippocampal sclerosis.
EVALuna2:34910

Systemic inflammatory response syndrome and long-term outcome after intracerebral hemorrhage - Hagen, Manuel; Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Lücking, Hannes; Hölter, Philip; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, Neuroimmunology and Neuroinflammation, 2019)
ObjectiveTo investigate whether the systemic inflammatory response syndrome (SIRS) without infection as surrogate of a systemic immune response is associated with poor long-term functional outcome in patients with spontaneous intracerebral hemorrhage (ICH).MethodsWe analyzed consecutive patients with spontaneous ICH from our prospective cohort study (2018-2015). SIRS was defined according to standard criteria: i.e., 2 or more of the following parameters during hospitalization: body temperature <36°C or >38°C, respiratory rate >20 per minute, heart rate >90 per minute, or white blood cell count <4,000/L or >12,000/L in the absence of infection. The primary outcome consisted of the modified Rankin Scale (mRS) at 3 and 12 months investigated by adjusted ordinal shift analyses. Bias and confounding were addressed by propensity score matching and multivariable regression models.ResultsOf 780 patients with ICH, 21.8% (n = 170) developed SIRS during hospitalization. Patients with SIRS showed more severe ICH compared with those without; i.e., larger ICH volumes (18.3 cm3, interquartile range [IQR 4.6-47.2 cm3] vs 7.4 cm3, IQR [2.4-18.6 cm3]; p < 0.01), increased intraventricular hemorrhage (57.6%, n = 98/170 vs 24.8%, n = 79/319; p < 0.01), and poorer neurologic admission status (NIH Stroke Scale score 16, IQR [7-30] vs 6, IQR [3-12]; p < 0.01). ICH severity-adjusted analyses revealed an independent association of SIRS with poorer functional outcome after 3 (OR 1.80, 95% CI [1.08-3.00]; p = 0.025) and 12 months (OR 1.76, 95% CI [1.04-2.96]; p = 0.034). Increased ICH volumes on follow-up imaging (OR 1.38, 95% CI [1.01-1.89]; p = 0.05) and previous liver dysfunction (OR 3.01, 95% CI [1.03-10.19]; p = 0.04) were associated with SIRS.ConclusionsIn patients with ICH, we identified SIRS to be predictive of poorer long-term functional outcome over the entire range of mRS estimates. Clinically relevant associations with SIRS were documented for previous liver dysfunction and hematoma enlargement.
CRIS-Team Scopus Importer:2019-10-29

T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29

Targeted Temperature Management: Peltier's Element-Based Focal Brain Cooling Protects Penumbra Neurons from Progressive Damage in Experimental Cerebral Ischemia - Tauchi, Miyuki; De Rink, Maria Mercedes Tejada; Fujioka, Hiroshi; Okayama, Satoko; Nakamura, Kei-Ichiro; Dietel, Barbara; Achenbach, Stephan; Kollmar, Rainer; Schwab, Stefan; Ushijima, Kazuo; Harada, Hideki (Therapeutic Hypothermia and Temperature Management, 2018)
Targeted temperature management (TTM), or therapeutic hypothermia, is one of the most potent neuroprotective approaches after ischemic and traumatic brain injuries. TTM has been applied clinically with various methods, but effective achievement and maintenance of the target temperature remain challenging. Furthermore, timing of cooling and target body and brain temperature to optimize effectiveness for neuroprotection and to minimize side effects are yet to be standardized. Focal brain cooling is a potential strategy to minimize adverse effects of systemic TTM. In this study, we report on a focal brain cooling device for animals and its effectiveness of focal cooling in several animal models of ischemic cerebral stroke. A focal brain cooling device was constructed using a Peltier's element, a thermoelectric heat pump. The device was validated for its cooling ability, and optimal settings to induce an effective intracranial temperature were determined using male Sprague-Dawley rats. Transient and permanent middle cerebral artery occlusions were experimentally induced, and focal brain cooling was applied using the device varying the timing and duration of cooling. The stroke-induced infarct and edema volumes were evaluated from Nissl-stained cryosections. The focal brain cooling device was able to decrease and subsequently maintained cerebral hypothermia in free-moving rats without altering the core temperature. The device with validated intracranial temperatures produced neuroprotective effects in the acute phase of ischemic neural death, reperfusion injury, progressing damage to the penumbra, and edema formation. In conclusion, our validated focal cooling device enabled rapid and accurate cerebral TTM in rats. Using this device, we were able to test the neuroprotective effect of focal TTM in several pathological stages of cerebral ischemia, which warrants further studies to develop clinically feasible TTM procedures for patients with cerebral stroke.
EVALuna2:36338

Teaching Video NeuroImages: Facial myokymia and myorhythmia in anti-IgLON5 disease: The bitten lip - Vetter, Elena; Olmes, David G.; Linker, Ralf; Seifert, Frank (Neurology, 2018)
EVALuna2:35511

Technical Modification of Amygdalo-Hippocampectomy in Temporal Lobe Epilepsy Surgery to Further Reduce Severe Neurological Complications: A Clinical-Anatomical Study - Roessler, Karl; Kasper, Burkhard; Coras, Roland; Arinrad, Soheil; Scholz, Michael; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (World Neurosurgery, 2018)
BACKGROUND: Temporal lobe resection (TLR) including amygdalohippocampectomy (AHE) is the most frequent performed procedure in epilepsy surgery. Owing to the close anatomic relationship of the mesial temporal structures and the midbrain and choroidal fissure, the incidence of severe complications, such as postoperative stroke, is as high as 2.5%. METHODS: We developed a modification of the classical technique for AHE that involves entering the choroidal fissure early via the anterior part of the frontomesial temporal horn cleft to identify the crus cerebri, posterior cerebri artery, and oculomotor nerve. In a second step, after visualization of the cleavage plane between the midbrain and middle cerebral artery, the uncus and amygdala are removed. RESULTS: A total of 81 patients (47 females and 34 males; mean age at surgery, 40 years) underwent TLR including AHE with our surgical modification to treat heterogeneous pathologies. The cohort included 45 patients with hippocampal sclerosis, 11 with ganglioglioma, 2 with dysembryoplastic neuroepithelioma, 2 with diffuse glioma, and 21 with other pathologies, including cavernoma, scar tissue, and mild cortical dysplasia, among others. In all patients, anterior temporal resection was performed via AHE using our modified technique. Seizure outcome was favorable after a mean follow-up of 27 months (range, 3-56 months); 64% of the patients were completely seizure-free (Engel class 1A), and 75% had an Engel class 1 outcome. There was no mortality or permanent severe neurologic complications, and the rate of surgical complications was 3.7%. CONCLUSIONS: Our modified AHE technique is associated with a low rate of complications in TLR for medically refractory temporal lobe epilepsy, and helps avoid permanent severe neurologic complications.
EVALuna2:34587

Tele-EEG: Current Applications, Challenges, and Technical Solutions - Rosenow, Felix; Audebert, Heinrich J.; Hamer, Hajo; Hinrichs, Hermann; Kessler-Uberti, Stephanie; Kluge, Tilmann; Noachtar, Soheyl; Remi, Jan; Sotoodeh, Ali; Strzelczyk, Adam; Weber, Joachim E.; Zoellner, Johann Philipp (Klinische Neurophysiologie, 2018)
Telemedicine for people with epilepsy aims to facilitate a thorough diagnosis and therapy regardless of regional constraints. In Germany, this is especially important in rural regions. This review aims to outline current tele-epileptological applications, with a special regard to the individual frameworks, demands, challenges and technical solutions. The requirements of pediatric tele-epileptology are explored. Special considerations are given to the technical and diagnosis guidelines required to review tele-EEG. Projects conducted in the recent past demonstrate positive results in patient care.
EVALuna2:201946

Telemedicine in epilepsy care: doc-to-doc applications Part I: State of the art, challenges, and perspectives - Mues, Sigrid; Hamer, Hajo; Von Podewils, Felix; Sotoodeh, Ali; Rosenow, Felix; Wellmer, Joerg; Zoellner, Johann Philipp (Zeitschrift für Epileptologie, 2021)
Telemedical doc-to-doc applications in epilepsy care can help to provide the special expertise of adult or pediatric epileptologists area wide, as they make it possible to provide medical services across spatial distances. Various solutions are being developed both nationally and internationally for this purpose; however, there are organizational, technical, legal and economic challenges. The long-term perspective of the various current approaches is unclear. Ultimately, business models will have to be developed in which all players (consultation providers and requesting physician, patients, health insurers, operators of telemedical platforms and, if necessary, the respective professional associations) weigh up the specific benefits and risks.
CRIS-Team WoS Importer:2021-07-23

Telemedicine in epilepsy care: doc-to-doc applications: Part I: State of the art, challenges, and perspectives Telemedizin in der Epilepsieversorgung: Arzt-zu-Arzt-Anwendungen: Teil I: State-of-the-Art, Herausforderungen, Perspektiven - Mues, Sigrid; Hamer, Hajo; Von Podewils, Felix; Sotoodeh, Ali; Rosenow, Felix; Wellmer, Joerg; Zoellner, Johann Philipp (Zeitschrift für Epileptologie, 2021)
Telemedical doc-to-doc applications in epilepsy care can help to provide the special expertise of adult or pediatric epileptologists area wide, as they make it possible to provide medical services across spatial distances. Various solutions are being developed both nationally and internationally for this purpose; however, there are organizational, technical, legal and economic challenges. The long-term perspective of the various current approaches is unclear. Ultimately, business models will have to be developed in which all players (consultation providers and requesting physician, patients, health insurers, operators of telemedical platforms and, if necessary, the respective professional associations) weigh up the specific benefits and risks.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Clinical competence; Communication; Digitalization; Funding; Tele-EEG

Teleneurology in stroke management: costs of service in different organizational models - Handschu, Rene; Scibor, Mateusz; Nueckel, Martin; Asshoff, Dirk; Willaczek, Barbara; Erbguth, Frank; Schwab, Stefan; Daumann, Frank (Journal of Neurology, 2014)
Telemedicine is in increasing use in clinical neuroscience such as acute stroke care, especially by applying remote audiovisual communication for patient evaluation. However, telephone consultation was also used linking stroke centres to smaller hospitals. We compared costs of telestroke services using audiovisual and telephone communication in different organizational models. Within a small network in Northern Bavaria video-based teleconsultation (VTC) and telephone advice (TA) was provided for evaluation of acute stroke patients on a weekly rotation. The costs of the admissions process with or without one of both methods of telemedicine were calculated and compared from the perspective of the spoke hospital. Different levels of service and network size were modelled and costs of transfers as well as loss of revenues were calculated. Yearly total labour costs were 415,000 EUR for an on-site service VTC-service compared to 61,000 EUR in an on-call service. Additional costs for one teleconsultation were 109.55 EUR in VTC and 49.82 EUR in TA (VTC/TA ratio 2.2). The ratio decreased to 0.8 when accounting for costs of transfer and loss of reimbursement for all patients transferred as transfer of patients to the stroke centre was more frequent after TA (9.1 vs. 14.9%full-time on-site ser). Costs of one QALY gained by using VTC instead of TA ranged from 115.00 EUR to 515.86 EUR depending on the different models. In the first view TA looks like the less expensive method as it is easy to access and works without additional costs. When accounting for all disadvantages TA becomes slightly more expensive. In telestroke care VTC should be recommended as the method of choice also from an economic perspective.
EVALuna2:22264

Testosterone Differentially Affects T Cells and Neurons in Murine and Human Models of Neuroinflammation and Neurodegeneration - Massa, Megan G.; David, Christina; Joerg, Stefanie; Berg, Johannes; Gisevius, Barbara; Hirschberg, Sarah; Linker, Ralf; Gold, Ralf; Haghikia, Aiden (American Journal of Pathology, 2017)
The high female-to-male sex ratio of multiple sclerosis (MS) prevalence has continuously confounded researchers, especially in light of male patients' accelerated disease course at later stages of MS. Although multiple studies have concentrated on estrogenic mechanisms of disease modulation, fairly little attention has been paid to androgenic effects in a female system, and even fewer studies have attempted to dissociate hormonal effects on the neurodegenerative and neuroinflammatory processes of MS. Herein, we demonstrate the differential effects of hormone treatment on the acute inflammatory and chronic neurodegenerative phases of murine experimental autoimmune encephalomyelitis. Although s.c. treatment with testosterone and aromatase inhibitor applied beginning on the day of immunization ameliorated initial course of disease, similar treatment administered therapeutically exacerbated chronic disease course. Spinal cord analyses of axonal densities reflected the clinical scores of the chronic phase. In vitro, testosterone treatment not only decreased Th1 and Th17 differentiation in an aromatase-independent fashion, but also exacerbated cell death in induced pluripotent stem cell-derived primary human neurons under oxidative stress conditions in an aromatase inhibitor-dependent manner. Thus, through the alleviation of inflammatory processes and the exacerbation of neurodegenerative processes, androgens may contribute to the epidemiologic sex differentials observed in MS prevalence and course.
EVALuna2:22495

The age and genomic integrity of neurons after cortical stroke in humans - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; Racz, Attila; Tatarishvili, Jemal; Lindgren, Emma; Csonka, Tamas; Csiba, Laszlo; Hortobagyi, Tibor; Mehes, Gabor; Englund, Elisabet; Solnestam, Beata Werne; et al. (Nature Neuroscience, 2014)
It has been unclear whether ischemic stroke induces neurogenesis or neuronal DNA rearrangements in the human neocortex. Using immunohistochemistry; transcriptome, genome and ploidy analyses; and determination of nuclear bomb test-derived (14)C concentration in neuronal DNA, we found neither to be the case. A large proportion of cortical neurons displayed DNA fragmentation and DNA repair a short time after stroke, whereas neurons at chronic stages after stroke showed DNA integrity, demonstrating the relevance of an intact genome for survival.
EVALuna2:22305

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The debate: Treatment after the first seizure-The PRO - Olmes, David G.; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2017)
According to current diagnosis criteria, first seizures constitute beginning epilepsy when they carry recurrence risks of >=60% over the next 10 years. This is frequently the case and warrants AED treatment. Evidence argues against deferring treatment when provoking factors such as sleep deprivation are reported. There are several characteristics of first seizures which markedly increase recurrence risk but not clearly beyond 60%. This includes status epilepticus or seizure flurries at first manifestation or focal semiology indicating focal epilepsy. In this situation, there are still various medical, social and individual aspects supporting early initiation of AED. Modern AED allow this safely and at low dosages.
EVALuna2:22486

The delta between postoperative seizure freedom and persistence: Automatically detected focal slow waves after epilepsy surgery - Schoenherr, Margit; Stefan, Hermann; Hamer, Hajo; Roessler, Karl; Buchfelder, Michael; Rampp, Stefan (NeuroImage: Clinical, 2017)
In this study, we use a novel automated method for localization and quantitative comparison of magnetoencephalographic (MEG) delta activity in patients with and without recurrent seizures after epilepsy surgery as well as healthy controls.We identified the generators of delta activity by source location in frequency domain between 1 and 4 Hz in spontaneous MEG data. Comparison with healthy control subjects by z-transform emphasized relative changes of activation in patients. The individual results were compared to spike localizations and statistical group analysis was performed. Additionally, MEG results were compared to 1-4 Hz activity in invasive EEG (iEEG) in two patients, in whom this data was available.Patients with recurrent seizures exhibited significantly increased focal MEG delta activity both in comparison to healthy controls and seizure free patients. This slow activity showed a correlation to interictal epileptic activity and was not explained by consequences of the resection alone. In two patients with iEEG, iEEG analysis was concordant with the MEG findings.The quantity of delta activity could be used as a diagnostic marker for recurrent seizures. The close relation to epileptic spike localizations and the resection volume of patients with successful second surgery imply involvement in seizure recurrence. This initial evidence suggests a potential application in the planning of second epilepsy surgery.
EVALuna2:22488

The Effect of Climatic Factors on the Provocation of Epileptic Seizures - Treib, Philipp; Treib, Sebastian; Adler, Werner; Hamer, Hajo; Schwab, Stefan; Stefan, Hermann; Hammen, Thilo; Treib, Johannes (Deutsches Ärzteblatt international, 2021)
CRIS-Team WoS Importer:2022-03-04

The effect of enzyme replacement therapy on clinical outcomes in female patients with Fabry disease - A systematic literature review by a European panel of experts. - Germain, Dominique P.; Arad, Michael; Burlina, Alessandro; Elliott, Perry M.; Falissard, Bruno; Feldt-Rasmussen, Ulla; Hilz, Max-Josef; Hughes, Derralynn A.; Ortiz, Alberto; Wanner, Christoph; Weidemann, Frank; Spada, Marco (Molecular Genetics and Metabolism, 2019)
BACKGROUND: Heterozygous females with Fabry disease have a wide range of clinical phenotypes depending on the nature of their mutation and their X-chromosome inactivation pattern; it is therefore important to examine outcomes of enzyme replacement therapy (ERT) in the female patient population specifically. This paper presents the findings of a systematic literature review of treatment outcomes with ERT in adult female patients. METHODS: A comprehensive systematic literature review was conducted through January 2017 to retrieve published papers with original data on ERT in the treatment of Fabry disease. The review included all original articles that presented ERT outcomes data on patients with Fabry disease, irrespective of the study type. RESULTS: Clinical evidence for the efficacy of ERT in female patients was available from 67 publications including six clinical trial publications, and indicates significant reductions in plasma and urine globotriaosylceramide (GL-3) accumulation (in female patients with elevated pre-treatment levels) and improvements in cardiac parameters and quality of life (QoL). To date, data are insufficient to conclude on the effects of ERT on the nervous system, gastrointestinal manifestations, and pain in female patients with Fabry disease. CONCLUSIONS: This review of available literature data demonstrates that ERT in adult female patients with Fabry disease has a beneficial effect on GL-3 levels and cardiac outcomes. The current evidence also suggests that ERT may improve QoL in this patient population, though further studies are needed to examine these results.
EVALuna2:206762

The effect of enzyme replacement therapy on clinical outcomes in male patients with Fabry disease: A systematic literature review by a European panel of experts. - Germain, Dominique P.; Elliott, Perry M.; Falissard, Bruno; Fomin, Victor V.; Hilz, Max-Josef; Jovanovic, Ana; Kantola, Ilkka; Linhart, Ales; Mignani, Renzo; Namdar, Mehdi; Nowak, Albina; Oliveira, Joao-Paulo; et al. (Molecular Genetics and Metabolism Reports, 2019)
Background: Enzyme replacement therapy (ERT) with recombinant human α-galactosidase has been available for the treatment of Fabry disease since 2001 in Europe and 2003 in the USA. Treatment outcomes with ERT are dependent on baseline patient characteristics, and published data are derived from heterogeneous study populations. Methods: We conducted a comprehensive systematic literature review of all original articles on ERT in the treatment of Fabry disease published up until January 2017. This article presents the findings in adult male patients. Results: Clinical evidence for the efficacy of ERT in adult male patients was available from 166 publications including 36 clinical trial publications. ERT significantly decreases globotriaosylceramide levels in plasma, urine, and in different kidney, heart, and skin cell types, slows the decline in estimated glomerular filtration rate, and reduces/stabilizes left ventricular mass and cardiac wall thickness. ERT also improves nervous system, gastrointestinal, pain, and quality of life outcomes. Conclusions: ERT is a disease-specific treatment for patients with Fabry disease that may provide clinical benefits on several outcomes and organ systems. Better outcomes may be observed when treatment is started at an early age prior to the development of organ damage such as chronic kidney disease or cardiac fibrosis. Consolidated evidence suggests a dose effect. Data described in male patients, together with female and paediatric data, informs clinical practice and therapeutic goals for individualized treatment.
EVALuna2:206759

The effect of enzyme replacement therapy on clinical outcomes in paediatric patients with Fabry disease - A systematic literature review by a European panel of experts - Spada, Marco; Baron, Ralf; Elliott, Perry M.; Falissard, Bruno; Hilz, Max-Josef; Monserrat, Lorenzo; Tondel, Camilla; Tylki-Szymariska, Anna; Wanner, Christoph; Germain, Dominique P. (Molecular Genetics and Metabolism, 2019)
Background: Fabry disease is caused by a deficiency of the lysosomal enzyme alpha-galactosidase, resulting in progressive accumulation of globotriaosylceramide (GL-3). The disease can manifest early during childhood and adolescence. Enzyme replacement therapy (ERT) with recombinant human alpha-galactosidase is the first specific treatment for Fabry disease and has been available in Europe since 2001. This paper presents the findings of a systematic literature review of clinical outcomes with ERT in paediatric patients with Fabry disease.
CRIS-Team WoS Importer:2019-04-18

The effect of rotating random dot motion on visuospatial line orientation in patients with right-sided stroke - Schaadt, A. K.; Reinhart, S.; Keller, I.; Hildebrandt, H.; Kerkhoff, G.; Utz, K. S. (Neuropsychologia, 2016)
Spatial deficits are frequent after brain damage, particularly right hemisphere stroke. Visual judgments of line orientation (LINE) are often impaired after right parietal lesions. Perception of line orientation is an important visuoperceptual component of visuoconstructive capacities. Yet, little is known about modulating factors in LINE and effective treatments are rare for this disorder. Studies in patients with spatial neglect show that horizontal random dot motion (RDM) significantly modulates horizontal spatial disorders, both transiently and permanently after treatment. In the current study, we investigated whether rotational RDM modulates judgements in an oblique LINE task in 20 patients with right-hemispheric first ever stroke (10 of them with a disorder in LINE and 10 without such a disorder), and 10 healthy, age-matched subjects. Subjects were tested under three experimental conditions: (1) with a static background of small white dots, (2) with slow clockwise or (3) counterclockwise circular RDM of these background stimuli, while they performed the LINE task. In the baseline condition with static background, the impaired patient group showed a significant counterclockwise tilt. Clockwise rotating RDM normalized this deficit transiently but completely, while counterclockwise rotating RDM slightly aggravated it, though not significantly. Tilts in the LINE task were significantly correlated with left visuospatial neglect. Similar but much smaller effects were obtained in the spatially unimpaired patients and the normal controls. These results show that rotational RDM modulates deficits of line orientation in patients with right-sided stroke, possibly by influencing higher spatial representations devoted to the perception of oblique lines.
EVALuna2:22542

The genomic landscape across 474 surgically accessible epileptogenic human brain lesions - A López-Rivera, Javier; Leu, Costin; Macnee, Marie; Khoury, Jean; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Bhattarai, Nisha; Pérez-Palma, Eduardo; Hamer, Hajo; Brandner, Sebastian; Roessler, Karl; et al. (Brain, 2022)
Understanding the exact molecular mechanisms involved in the etiology of epileptogenic pathologies with or without tumor activity is essential for improving treatment of drug-resistant focal epilepsy. Here, we characterize the landscape of somatic genetic variants in resected brain specimens from 474 individuals with drug-resistant focal epilepsy using deep whole-exome sequencing (>350×) and whole-genome genotyping. Across the exome, we observe a greater number of somatic single-nucleotide variants (SNV) in low-grade epilepsy-associated tumors (LEAT; 7.92 ± 5.65 SNV) than in brain tissue from malformations of cortical development (MCD; 6.11 ± 4 SNV) or hippocampal sclerosis (HS; 5.1 ± 3.04 SNV). Tumor tissues also had the largest number of likely pathogenic variant carrying cells. LEAT had the highest proportion of samples with one or more somatic copy number variants (CNV; 24.7%), followed by MCD (5.4%) and HS (4.1%). Recurring somatic whole chromosome duplications affecting Chromosome 7 (16.8%), chromosome 5 (10.9%), and chromosome 20 (9.9%) were observed among LEAT. For germline variant-associated MCD genes such as TSC2, DEPDC5, and PTEN, germline SNV were frequently identified within large loss of heterozygosity regions, supporting the recently proposed ‘second hit’ disease mechanism in these genes. We detect somatic variants in twelve established lesional epilepsy genes and demonstrate exome-wide statistical support for three of these in the etiology of LEAT (e.g., BRAF) and MCD (e.g., SLC35A2 and MTOR). We also identify novel significant associations for PTPN11 with LEAT and NRAS Q61 mutated protein with a complex MCD characterized by polymicrogyria and nodular heterotopia. The variants identified in NRAS are known from cancer studies to lead to hyperactivation of NRAS, which can be targeted pharmacologically. We identify large recurrent 1q21-q44 duplication including AKT3 in association with focal cortical dysplasia type 2a with hyaline astrocytic inclusions, another rare and possibly under-recognized brain lesion. The clinical genetic analyses showed that the numbers of somatic SNV across the exome and the fraction of affected cells were positively correlated with the age at seizure onset and surgery in individuals with LEAT. In summary, our comprehensive genetic screen sheds light on the genome-scale landscape of genetic variants in epileptic brain lesions, informs the design of gene panels for clinical diagnostic screening, and guides future directions for clinical implementation of epilepsy surgery genetics.<br
Keywords: epilepsy; malformation of cortical development; low-grade epilepsy-associated tumor; hippocampal sclerosis; genetics

The gut-brain axis in inflammatory bowel disease—current and future perspectives - Günther, Claudia; Rothhammer, Veit; Karow, Marisa; Neurath, Markus; Winner, Beate (International Journal of Molecular Sciences, 2021)
The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, epidemiological and experimental data have demonstrated that IBD predisposes a person to pathologies of the central nervous system (CNS). Likewise, a number of neurological disorders are associated with changes in the intestinal environment, which are indicative for disease-mediated gut–brain inter-organ communication. Although this axis was identified more than 20 years ago, the sequence of events and underlying molecular mechanisms are poorly defined. The emergence of precision medicine has uncovered the need to take into account non-intestinal symptoms in the context of IBD that could offer the opportunity to tailor therapies to individual patients. The aim of this review is to highlight recent findings supporting the clinical and biological link between the gut and brain, as well as its clinical significance for IBD as well as neurodegeneration and neuroinflammation. Finally, we focus on novel human-specific preclinical models that will help uncover disease mechanisms to better understand and modulate the function of this complex system.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ex vivo organ models; Gut-brain axis; IBD; MS; PD

The hyperintense acute reperfusion marker on fluid-attenuated inversion recovery magnetic resonance imaging is caused by gadolinium in the cerebrospinal fluid - Köhrmann, Martin; Struffert, Tobias; Frenzel, Thomas; Schwab, Stefan; Dörfler, Arnd (Stroke, 2012)
Background and PurposeS-: The hyperintense acute reperfusion marker (HARM) on fluid-attenuated inversion recovery MRI is believed to be caused by gadolinium-based contrast agents crossing a disrupted blood-brain barrier. However, this hypothesis has never been directly verified in humans. Methods-: In this study, we analyzed cerebrospinal fluid samples of patients with HARM on imaging regarding the presence and concentration of gadolinium-based contrast agents. Results-: Gadobutrol was found in concentrations of approximately 50 μmol/L. Using phantom MRI experiments, we demonstrate that the detected concentrations are consistent with the observed HARM imaging pattern. Conclusions-: Our study yields first direct evidence in humans that the imaging phenomenon HARM is indeed caused by leakage of gadolinium-based contrast agents into the cerebrospinal fluid. © 2011 American Heart Association. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: FLAIR; hyperintensive acute reperfusion marker; MRI

The Impact of Burst Motor Cortex Stimulation on Cardiovascular Autonomic Modulation in Chronic Pain: A Feasibility Study for a New Approach to Objectively Monitor Therapeutic Effects - Borutta, Matthias; Köhn, Julia; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Engelhorn, Tobias; Schwab, Stefan; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2023)
Introduction: Chronic refractory pain of various origin occurs in 30–45% of pain patients, and a considerable proportion remains resistant to pharmacological and behavioral therapies, requiring adjunctive neurostimulation therapies. Chronic pain is known to stimulate sympathetic outflow, yet the impact of burst motor cortex stimulation (burstMCS) on objectifiable autonomic cardiovascular parameters in chronic pain remains largely unknown. Methods: In three patients with chronic pain (2 facial pain/1 post-stroke pain), we compared pain intensity using a visual analog scale (VAS 1–10) and parameters of autonomic cardiovascular modulation at supine rest, during parasympathetic challenge with six cycles per minute of metronomic deep breathing, and during sympathetic challenge (active standing) at baseline and after 4 months of burstMCS compared to age-/gender-matched healthy controls. Results: While two out of three patients were responsive after 4 months of adjunctive burstMCS (defined as pain reduction of > 30%), no differences were found in any of the three patients regarding the R-R intervals of adjacent QRS complexes (RRI, 642 vs. 676 ms) and blood pressure (BP, 139/88 vs. 141/90 mmHg). Under resting conditions, parameters of parasympathetic tone [normalized units of high-frequency oscillations of RRI (RRI-HFnu power) 0.24 vs. 0.38, root-mean-square differences of successive RRI (RRI-RMSSD) 7.7 vs. 14.7 ms], total autonomic cardiac modulation [RRI total power 129.3 vs. 406.2 ms2, standard deviation of RRI (RRI-SD) 11.6 vs. 18.5 ms, coefficient of variation of RRI (RRI-CV) 1.9 vs. 3.7%], and baroreceptor reflex sensitivity (BRS, 1.9 vs. 2.3 ms/mmHg) increased, and parameters of sympathetic tone [normalized units of low-frequency oscillations of RRI (RRI-LFnu power) 0.76 vs. 0.62] and sympatho-vagal balance [ratio of RR-LF to RRI-HF power (RRI-LF/HF ratio) 3.4 vs. 1.9] decreased after 4 months of burstMCS. Low-frequency oscillations of systolic blood pressure (SBP-LF power), a parameter of sympathetic cardiovascular modulation, increased slightly (17.6 vs. 20.4 mmHg2). During parasympathetic stimulation, the expiratory–inspiratory ratio (E/I ratio) increased slightly, while upon sympathetic stimulation, the ratio between the shortest RRI around the 15th heartbeat and the longest RRI around the 30th heartbeat after standing up (RRI 30/15 ratio) remained unchanged. Conclusion: Four months of adjunctive burstMCS was associated with an increase in parameters reflecting both total and parasympathetic autonomic modulation and baroreceptor reflex sensitivity. In contrast, sympathetic tone declined in our three patients, suggesting stimulation-associated improvement not only in subjectively perceived VAS pain scores, but also in objectifiable parameters of autonomic cardiovascular modulation.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Autonomic cardiovascular modulation; Burst motor cortex stimulation; Chronic post stroke pain; Objective outcome measures

The impact of the coronavirus disease (COVID-19) pandemic on outpatient epilepsy care: An analysis of physician practices in Germany - Müller, Tamara; Kostev, Karel; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Westermayer, Vivien; Reindl, Caroline; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: To gain insight into epilepsy care during coronavirus disease (COVID-19) pandemic, we analyzed prescription data of a large cohort of persons with epilepsy (PWE) during lockdown in Germany. Methods: Information was obtained from the Disease Analyzer database, which collects anonymous demographic and medical data from practice computer systems of general practitioners (GP) and neurologists (NL) throughout Germany. We retrospectively compared prescription data for anti-seizure medication (ASM) and physicians’ notes of “known” and “new” PWE from January 2020 until May 2020 with the corresponding months in the three preceding years 2017–2019. Adherence was estimated by calculating the proportion of patients with follow-up prescriptions within 90 days after initial prescriptions in January or February. We additionally analyzed hospital referrals of PWE. The significance level was set to 0.01 to adjust for multiple comparisons. Results: A total of 52,844 PWE were included. Anti-seizure medication prescriptions for known PWE increased in March 2020 (GP + 36%, NL + 29%; P < 0.01). By contrast, a decrease in prescriptions to known and new PWE was observed in April and significantly in May 2020 ranging from −16% to −29% (P < 0.01). The proportion of PWE receiving follow-up prescriptions was slightly higher in 2020 (73.5%) than in 2017–2019 (70.7%, P = 0.001). General practitioners and NL referred fewer PWE to hospitals in March 2020 (GP: −30%, P < 0.01; NL: −12%), April 2020 (GP: −29%, P < 0.01; NL: −37%), and May 2020 (GP: −24%, P < 0.01; NL: −16%). Conclusion: Adherence of known PWE to ASM treatment appeared to remain stable during lockdown in Germany. However, this study revealed findings which point to reduced care for newly diagnosed PWE as well as fewer hospital admissions. These elements may warrant consideration during future lockdown situations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Anti-seizure drugs; COVID-19; Epilepsy care

The impact of the DWI-FLAIR-mismatch in the ECASS-4 trial – A post hoc analysis - Pfaff, Johannes A. R.; Bendszus, Martin; Donnan, Geoffrey; Molina, Carlos; Leys, Didier; Schellinger, Peter D.; Schwab, Stefan; Toni, Danilo; Wahlgren, Nils; Hacke, Werner; Ringleb, Peter Arthur (European Stroke Journal, 2020)
Introduction: To investigate the impact of a mismatch between diffusion-weighted imaging (DWI) and fluid attenuated inversion recovery (FLAIR) on functional outcome in patients with acute stroke in a prolonged time window or unknown time of symptom onset randomized to intravenous thrombolysis or placebo. Patients and Methods: We performed a post-hoc analysis of the European Cooperative Acute Stroke Study-4 (ECASS-4) trial. ECASS-4 was an investigator driven, phase 3, multi-center, double-blind, placebo-controlled study which randomized ischemic stroke patients presenting within 4.5 and 9h of stroke onset or unknown time-window to either rt-PA or placebo after MR-imaging. Two subgroups “no mismatch” (nMM) and “any mismatch” (aMM) were created by applying a DWI-FLAIR-mismatch criterion. We calculated frequency of nMM and aMM and performed a univariate analysis (Fisher's Test) for excellent clinical outcome (mRS 0-1) and mortality (mRS=6). Results: MR-Imaging of n=111/119 (93.2%) patients was suitable for this analysis. DWI-FLAIR mismatch was found in 49 patients (44.1%). Proportions of mismatch nMM and aMM were comparable in treatment-groups (aMM: Placebo 46.3%, Alteplase 42.1%; p=0.70). Patients with nMM showed no benefit of rt-PA-treatment (OR (95%CI) mRS 0-1: 0.95 (0.29-3.17)). Patients with aMM showed a point estimate of the odds ratio in favour of a treatment benefit of rt-PA (mRS 0-1: OR (95%CI) 2.62 (0.68-11.1)). Mortality within 90 days was not different in patients treated with rt-PA if nMM (15.2%) or aMM (12.5%) was present. Discussion: In this analysis no significant evidence, but subtle indication towards patients treated with rt-PA in a prolonged time window reaching an excellent clinical outcome if a DWI-FLAIR-mismatch is present on initial stroke MR-imaging. Conclusion: A DWI-FLAIR mismatch in the region of ischemia as imaging based surrogate parameter for patient selection for i.v. rt-PA should be strongly pursued.
CRIS-Team Scopus Importer:2020-05-08
Keywords: acute ischemic stroke; diffusion-weighted imaging; DWI-FLAIR-mismatch; European Cooperative Acute Stroke Study-4; fluid-attenuated inversion recovery; magnetic resonance imaging; Thrombolysis

The long-term course of temporal lobe epilepsy: From unilateral to bilateral interictal epileptiform discharges in repeated video-EEG monitorings - Gollwitzer, Stephanie; Scott, Catherine A.; Farrell, Fiona; Bell, Gail S.; De Tisi, Jane; Walker, Matthew C.; Wehner, Tim; Sander, Josemir W.; Hamer, Hajo; Diehl, Beate (Epilepsy and Behavior, 2017)
Bilateral interictal epileptiform discharges (IED) and ictal patterns are common in temporal lobe epilepsy (TLE) and have been associated with decreased chances of seizure freedom after epilepsy surgery. It is unclear whether secondary epileptogenesis, although demonstrated in experimental models, exists in humans and may account for progression of epilepsy.We reviewed consecutive video-EEG recordings from 1992 to 2014 repeated at least two years apart (mean interval 6.14years) in 100 people diagnosed with TLE.Ictal EEG patterns and IED remained restricted to one hemisphere in 36 people (group 1), 46 exhibited bilateral abnormalities from the first recording (group 2), 18 progressed from unilateral to bilateral EEG pathology over time (group 3). No significant differences between the three groups were seen with respect to age at epilepsy onset, duration, or underlying pathology. Extra-temporal IED during the first EEG recording were associated with an increased risk of developing bilateral epileptiform changes over time (hazard ratio 3.67; 95% CI 1.4, 9.4).Our findings provide some support of progression in TLE and raise the possibility of secondary epileptogenesis in humans. The development of an independent contra-lateral epileptogenic focus is known to be associated with a less favorable surgical outcome. We defined reliable EEG markers for an increased risk of progression to more widespread or independent bitemporal epileptogenicity at an early stage, thus allowing for individualized pre-surgical counselling.
EVALuna2:22487

The NRF2 pathway as potential biomarker for dimethyl fumarate treatment in multiple sclerosis - Hammer, Anna; Waschbisch, Anne; Kuhbandner, Kristina; Bayas, Antonios; Lee, De-Hyung; Duscha, Alexander; Haghikia, Aiden; Gold, Ralf; Linker, Ralf (Annals of Clinical and Translational Neurology, 2018)
Objective: Immunological studies have demonstrated a plethora of beneficial effects of dimethyl fumarate (DMF) on various cell types. However, the cellular and molecular targets are incompletely understood and response markers are scarce. Here, we focus on the relation between nuclear factor (erythroid-derived 2)-like 2 (NRF2) pathway induction under DMF therapy and the composition of the blood immune cell compartment and clinical efficacy in relapsing-remitting multiple sclerosis (MS) patients. Methods: We explored effects of DMF on peripheral immune cell subsets by flow cytometric and transcriptional analysis of serial blood samples obtained from 43 MS patients during the first year of therapy. Results: Gene expression analysis proved activation of NRF2 signaling under DMF therapy that was paralleled by a temporal expansion of FoxP3+ regulatory T cells, CD56bright natural killer cells, plasmacytoid dendritic cells, and a decrease in CD8+ T cells, B cells, and type 1 myeloid dendritic cells. In a subgroup of 28 patients with completely available clinical data, individuals with higher levels of the NRF2 target gene NAD(P)H quinone dehydrogenase 1 (NQO1) 4-6 weeks after DMF therapy initiation were more likely to achieve no evidence of disease activity status 1 year later. The degree of NQO1 induction further correlated with patient age. Interpretation: We demonstrate that positive effects of DMF on the clinical outcome are paralleled by induction of the antioxidant NRF2 transcriptional pathway and a shift toward regulatory immune cell subsets in the periphery. Our data identify a role of the NRF2 pathway as potential biomarker for DMF treatment in MS.
EVALuna2:35516

Therapeutic goals in Fabry disease: Recommendations of a European expert panel, based on current clinical evidence with enzyme replacement therapy - Wanner, Christoph; Gerrnain, Dominique P.; Hilz, Max-Josef; Spada, Marco; Falissard, Bruno; Elliott, Perry M. (Molecular Genetics and Metabolism, 2019)
CRIS-Team WoS Importer:2019-04-18

Therapeutic hypothermia for acute ischaemic stroke. Results of a European multicentre, randomised, phase III clinical trial - Van Der Worp, H. Bart; Macleod, Malcolm R.; Bath, Philip M. W.; Bathula, Raj; Christensen, Hanne; Colam, Bridget; Cordonnier, Charlotte; Demotes-Mainard, Jacques; Durand-Zaleski, Isabelle; Gluud, Christian; Jakobsen, Janus Christian; Kallmünzer, Bernd; et al. (European Stroke Journal, 2019)
Introduction We assessed whether modest systemic cooling started within 6 hours of symptom onset improves functional outcome at three months in awake patients with acute ischaemic stroke. Patients and methods In this European randomised open-label clinical trial with blinded outcome assessment, adult patients with acute ischaemic stroke were randomised to cooling to a target body temperature of 34.0-35.0 degrees C, started within 6 h after stroke onset and maintained for 12 or 24 h , versus standard treatment. The primary outcome was the score on the modified Rankin Scale at 91 days, as analysed with ordinal logistic regression. Results The trial was stopped after inclusion of 98 of the originally intended 1500 patients because of slow recruitment and cessation of funding. Forty-nine patients were randomised to hypothermia versus 49 to standard treatment. Four patients were lost to follow-up. Of patients randomised to hypothermia, 15 (31%) achieved the predefined cooling targets. The primary outcome did not differ between the groups (odds ratio for good outcome, 1.01; 95% confidence interval, 0.48-2.13; p = 0.97). The number of patients with one or more serious adverse events did not differ between groups (relative risk, 1.22; 95% confidence interval, 0.65-1.94; p = 0.52). Discussion In this trial, cooling to a target of 34.0-35.0 degrees C and maintaining this for 12 or 24 h was not feasible in the majority of patients. The final sample was underpowered to detect clinically relevant differences in outcomes. Conclusion Before new trials are launched, the feasibility of cooling needs to be improved.
CRIS-Team WoS Importer:2019-10-01

The Role of Gut and Oral Microbiota in the Formation and Rupture of Intracranial Aneurysms: A Literature Review. - Joerger, Ann Kathrin; Albrecht, Carolin; Rothhammer, Veit; Neuhaus, Klaus; Wagner, Arthur; Meyer, Bernhard; Wostrack, Maria (International Journal of Molecular Sciences, 2023)
In recent years, there has been a growing interest in the role of the microbiome in cardiovascular and cerebrovascular diseases. Emerging research highlights the potential role of the microbiome in intracranial aneurysm (IA) formation and rupture, particularly in relation to inflammation. In this review, we aim to explore the existing literature regarding the influence of the gut and oral microbiome on IA formation and rupture. In the first section, we provide background information, elucidating the connection between inflammation and aneurysm formation and presenting potential mechanisms of gut-brain interaction. Additionally, we explain the methods for microbiome analysis. The second section reviews existing studies that investigate the relationship between the gut and oral microbiome and IAs. We conclude with a prospective overview, highlighting the extent to which the microbiome is already therapeutically utilized in other fields. Furthermore, we address the challenges associated with the context of IAs that still need to be overcome.
EVALuna2:552389

The role of midkine in health and disease - Neumaier, Emely; Rothhammer, Veit; Linnerbauer, Mathias (Frontiers in Immunology, 2023)
Midkine (MDK) is a neurotrophic growth factor highly expressed during embryogenesis with important functions related to growth, proliferation, survival, migration, angiogenesis, reproduction, and repair. Recent research has indicated that MDK functions as a key player in autoimmune disorders of the central nervous system (CNS), such as Multiple Sclerosis (MS) and is a promising therapeutic target for the treatment of brain tumors, acute injuries, and other CNS disorders. This review summarizes the modes of action and immunological functions of MDK both in the peripheral immune compartment and in the CNS, particularly in the context of traumatic brain injury, brain tumors, neuroinflammation, and neurodegeneration. Moreover, we discuss the role of MDK as a central mediator of neuro-immune crosstalk, focusing on the interactions between CNS-infiltrating and -resident cells such as astrocytes, microglia, and oligodendrocytes. Finally, we highlight the therapeutic potential of MDK and discuss potential therapeutic approaches for the treatment of neurological disorders.
CRIS-Team Scopus Importer:2023-12-22
Keywords: CNS; inflammation; injury; malignancy; midkine

The serotonin receptor 2A (HTR2A) rs6313 variant is associated with higher ongoing pain and signs of central sensitization in neuropathic pain patients - Sachau, Juliane; Bruckmueller, Henrike; Gierthmühlen, Janne; Magerl, Walter; May, Denisa; Binder, Andreas; Forstenpointner, Julia; Koetting, Judith; Maier, Christoph; Tölle, Thomas R.; Treede, Rolf Detlef; Berthele, Achim; et al. (European Journal of Pain, 2020)
Background: The serotonin receptor 2A (HTR2A) has been described as an important facilitation mediator of spinal nociceptive processing leading to central sensitization (CS) in animal models of chronic pain. However, whether HTR2A single nucleotide variants (SNVs) modulate neuropathic pain states in patients has not been investigated so far. The aim of this study was to elucidate the potential association of HTR2A variants with sensory abnormalities or ongoing pain in neuropathic pain patients. Methods: At total of 240 neuropathic pain patients and 253 healthy volunteers were included. Patients were phenotypically characterized using standardized quantitative sensory testing (QST). Patients and controls were genotyped for HTR2A g.-1438G > A (rs6311) and c.102C > T (rs6313). Genotype-related differences in QST parameters were assessed considering QST profile clusters, principal somatosensory components and sex. Results: There was an equal distribution of rs6313 and linked rs6311 between patients and controls. However, the rs6313 variant was significantly associated with a principal component of pinprick hyperalgesia and dynamic mechanical allodynia, indicating enhanced CS in patients with sensory loss (−0.34 ± 0.15 vs. +0.31 ± 0.11 vs., p <.001). In this cluster, the variant allele was also associated with single QST parameters of pinprick hyperalgesia (MPT, +0.64 ± 0.18 vs. −0.34 ± 0.23 p =.002; MPS, +0.66 ± 0.17 vs. −0.09 ± 0.23, p =.009) and ongoing pain was increased by 30%. Conclusions: The specific association of the rs6313 variant with pinprick hyperalgesia and increased levels of ongoing pain suggests that the HTR2A receptor might be an important modulator in the development of CS in neuropathic pain. Significance: This article presents new insights into serotonin receptor 2A-mediating mechanisms of central sensitization in neuropathic pain patients. The rs6313 variant allele was associated with increased mechanical pinprick sensitivity and increased levels of ongoing pain supporting a contribution of central sensitization in the genesis of ongoing pain providing a possible route for mechanism-based therapies.
CRIS-Team Scopus Importer:2020-12-11

The Subarachnoid Hemorrhage International Trialists (SAHIT) Repository: advancing clinical research in subarachnoid hemorrhage - Jaja, Blessing N. R.; Attalla, Daniel; Macdonald, R. Loch; Schweizer, Tom A.; Cusimano, Michael D.; Etminan, Nima; Hanggi, Daniel; Hasan, David; Johnston, S. Claiborne; Le Roux, Peter; Lo, Benjamin; Louffat-Olivares, Ada; et al. (Neurocritical Care, 2014)
Researchers and other stakeholders continue to express concern about the failure of randomized clinical trials (RCT) in subarachnoid hemorrhage (SAH) to show efficacy of new treatments. Pooled data may be particularly useful to generate hypotheses about causes of poor outcomes and reasons for failure of RCT in SAH, and strategies to improve them. Investigators conducting SAH research collaborated to share data with the intent to develop a large repository of pooled individual patient data for exploratory analysis and testing of new hypotheses relevant to improved trial design and analysis in SAH. This repository currently contains information on 11,443 SAH patients from 14 clinical databases, of which 9 are datasets of recent RCTs and 5 are datasets of prospective observational studies and hospital registries. Most patients were managed in the last 15 years. Data validation and quality checks have been conducted and are satisfactory. Data is available on demographic, clinical, neuroimaging, and laboratory results and various outcome measures. We have compiled the largest known dataset of patients with SAH. The SAHIT repository may be an important resource for advancing clinical research in SAH and will benefit from contributions of additional datasets.
EVALuna2:22319

Theta rhythmicity governs human behavior and hippocampal signals during memory-dependent tasks - Ter Wal, Marije; Linde-Domingo, Juan; Lifanov, Julia; Roux, Frederic; Kolibius, Luca D.; Gollwitzer, Stephanie; Lang, Johannes; Hamer, Hajo; Rollings, David; Sawlani, Vijay; Chelvarajah, Ramesh; Staresina, Bernhard; et al. (Nature Communications, 2021)
Memory formation and reinstatement are thought to lock to the hippocampal theta rhythm, predicting that encoding and retrieval processes appear rhythmic themselves. Here, we show that rhythmicity can be observed in behavioral responses from memory tasks, where participants indicate, using button presses, the timing of encoding and recall of cue-object associative memories. We find no evidence for rhythmicity in button presses for visual tasks using the same stimuli, or for questions about already retrieved objects. The oscillations for correctly remembered trials center in the slow theta frequency range (1-5 Hz). Using intracranial EEG recordings, we show that the memory task induces temporally extended phase consistency in hippocampal local field potentials at slow theta frequencies, but significantly more for remembered than forgotten trials, providing a potential mechanistic underpinning for the theta oscillations found in behavioral responses.
CRIS-Team Scopus Importer:2021-12-17

Thrombocytopenia and Clinical Outcomes in Intracerebral Hemorrhage: A Retrospective Multicenter Cohort Study - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of platelets on hematoma enlargement (HE) of intracerebral hemorrhage (ICH) is not yet sufficiently elucidated. Especially the role of reduced platelet counts on HE and clinical outcomes is still poorly understood. This study investigated the influence of thrombocytopenia on HE, functional outcome, and mortality in patients with ICH with or without prior antiplatelet therapy (APT). METHODS: Individual participant data of multicenter cohort studies (multicenter RETRACE program [German-Wide Multicenter Analysis of Oral Anticoagulation-Associated Intracerebral Hemorrhage] and single-center UKER-ICH registry [Universitätsklinikum Erlangen Cohort of Patients With Spontaneous ICH]) were grouped into APT and non-APT ICH patients according to the platelet count, that is, with or without thrombocytopenia (cells <150×109/L). Of all patients, 51.5% (1124 of 2183) were on vitamin K antagonist. Imbalances in baseline characteristics including proportions of vitamin K antagonist patients were addressed using propensity score matching. Outcome analyses included HE (>33%), as well as mortality and functional outcome, after 3 months using the modified Rankin Scale, dichotomized into favorable (modified Rankin Scale score, 0-3) and unfavorable (modified Rankin Scale score, 4-6). RESULTS: Of overall 2252 ICH patients, 11.4% (52 of 458) under APT and 14.0% (242 of 1725) without APT presented with thrombocytopenia on admission. The proportion of patients with HE was not significantly different between patients with or without thrombocytopenia among APT and non-APT ICH patients after propensity score matching (HE: APT patients: 9 of 40 [22.5%] thrombocytopenia versus 27 of 115 [23.5%] nonthrombocytopenia, P=0.89; non-APT patients: 54 of 174 [31.0%] thrombocytopenia versus 106 of 356 [29.8%] nonthrombocytopenia, P=0.77). In both (APT and non-APT) propensity score matching cohorts, there were no significant differences regarding functional outcome. Mortality after 3 months did not differ among non-APT patients, whereas the mortality rate was significantly higher for APT patients with thrombocytopenia versus APT patients with normal platelet count (APT: 29 of 46 [63.0%] thrombocytopenia versus 58 of 140 [41.4%] nonthrombocytopenia, P=0.01; non-APT: 95 of 227 [41.9%] thrombocytopenia versus 178 of 455 [39.1%] nonthrombocytopenia, P=0.49). CONCLUSIONS: Our study implies that thrombocytopenia does not affect rates of HE and functional outcome among ICH patients, neither in patients with nor without APT. In light of increased mortality, the significance of platelet transfusions for ICH patients with thrombocytopenia and previous APT should be explored in future studies.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cohort studies; hematoma enlargement; intracerebral hemorrhage; platelet count; thrombocytopenia

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Time trends in incidence of pathological and etiological stroke subtypes during 16 years: the Erlangen Stroke Project - Kolominsky-Rabas, Peter; Wiedmann, Silke; Weingärtner, Michael; Liman, Thomas G.; Endres, Matthias; Schwab, Stefan; Buchfelder, Michael; Heuschmann, Peter U. (Neuroepidemiology, 2015)
Population-based data, which continuously monitors time trends in stroke epidemiology are limited. We investigated the incidence of pathological and etiological stroke subtypes over a 16 year time period.Data were collected within the Erlangen Stroke Project (ESPro), a prospective, population-based stroke register in Germany covering a total study population of 105,164 inhabitants (2010). Etiology of ischemic stroke was classified according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria.Between January 1995 and December 2010, 3,243 patients with first-ever stroke were documented. The median age was 75 and 55% were females. The total stroke incidence decreased over the 16 year study period in men (Incidence Rate Ratio 1995-1996 vs. 2009-2010 (IRR) 0.78; 95% CI 0.58-0.90) but not in women. Among stroke subtypes, a decrease in ischemic stroke incidence (IRR 0.73; 95% CI 0.57-0.93) and of large artery atherosclerotic stroke (IRR 0.27; 95% CI 0.12-0.59) was found in men and an increase of stroke due to small artery occlusion in women (IRR 2.33; 95% CI 1.39-3.90).Variations in time trends of pathological and etiological stroke subtypes were found between men and women that might be linked to gender differences in the development of major vascular risk factors in the study population.
EVALuna2:22434

"TORNADO" - Theranostic One-Step RNA Detector; microfluidic disc for the direct detection of microRNA-134 in plasma and cerebrospinal fluid - Mcardle, Hazel; Jimenez-Mateos, Eva M.; Raoof, Rana; Carthy, Eadaoin; Boyle, David; Elnaggar, Hany; Delanty, Norman; Hamer, Hajo; Dogan, Muejgdan; Huchtemann, Tessa; Koertvelyessy, Peter; Rosenow, Felix; et al. (Scientific Reports, 2017)
Diagnosis of seizure disorders such as epilepsy currently relies on clinical examination and electroencephalogram recordings and is associated with substantial mis-diagnosis. The miRNA, miR-134 (MIR134 in humans), has been found to be elevated in brain tissue after experimental status epilepticus and in human epilepsy cells and their detection in biofluids may serve as unique biomarkers. miRNAs from unprocessed human plasma and human cerebrospinal fluid samples were used in a novel electrochemical detection based on electrocatalytic platinum nanoparticles inside a centrifugal microfluidic device where the sandwich assay is formed using an event triggered release system, suitable for the rapid point-of-care detection of low abundance biomarkers of disease. The device has the advantage of controlling the rotation speed of the centrifugal device to pump nanoliter volumes of fluid at a set time and manipulate the transfer of liquids within the device. The centrifugal platform improves reaction rates and yields by proposing efficient mixing strategies to overcome diffusion-limited processes and improve mass transport rates, resulting in reduced hybridization times with a limit of detection of 1 pM target concentration. Plasma and cerebrospinal fluid samples (unprocessed) from patients with epilepsy or who experienced status epilepticus were tested and the catalytic response obtained was in range of the calibration plot. This study demonstrates a rapid and simple detection for epilepsy biomarkers in biofluid.
EVALuna2:22536

Towards a multi-sensor system for the diagnosis of neurological disorders - Tenner, Felix; Schramm, Axel; Söhle, Mona; Regensburger, Martin; Wirthmann, Elisa; Zalevsky, Zeev; Schmidt, Michael (2016 IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2016)

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

Transcutaneous vagus nerve stimulation - A brief introduction and overview - Hilz, Max-Josef (Autonomic Neuroscience-Basic & Clinical, 2022)
Invasive cervical vagus nerve stimulation (VNS) is approved for the treatment of epilepsies, depression, obesity, and for stroke-rehabilitation. The procedure requires surgery, has side-effects, is expensive and not readily available. Consequently, transcutaneous VNS (tVNS) has been developed 20 years ago as non-invasive, less expensive, and easily applicable alternative. Since the vagus nerve reaches the skin at the outer acoustic canal and ear, and reflex-responses such as the ear-cough-reflex or the auriculo-cardiac reflex have been observed upon auricular stimulation, the ear seems well suited for tVNS. However, several sensory nerves with variable fiber-density and significant overlap innervate the outer ear: the auricular branch of the vagus nerve (ABVN), the auriculotemporal nerve, greater auricular nerve, and to some extent the lesser occipital nerve. VNS requires activation of Aβ-fibers which are far less present in the ABVN than the cervical vagus nerve. Thus, optimal stimulation sites and parameters, and tVNS-algorithms need to be further explored. Unravelling central pathways and structures that mediate tVNS-effects is another challenge. tVNS impulses reach the nucleus of the solitary tract and activate the locus-coeruleus-norepinephrine system. However, many more brain areas are activated or deactivated upon VNS, including structures of the central autonomic network and the limbic system. Still, the realm of therapeutic tVNS applications grows rapidly and includes medication-refractory epilepsies, depressive mood disorders, headaches including migraine, pain, heart failure, gastrointestinal inflammatory diseases and many more. tVNS might become a standard tool to enhance autonomic balance and function in various autonomic, neurological, psychiatric, rheumatologic, as well as other diseases.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Auricular branch of the vagus nerve; Concha cymba; Locus coeruleus; Nucleus tractus solitarii; Tragus; Transcutaneous vagus nerve stimulation

Transcutaneous vagus nerve stimulation and the realm of its therapeutic hopes and physiologic enigmas - Hilz, Max-Josef; Bolz, Armin (Autonomic Neuroscience-Basic & Clinical, 2022)
Vagus nerve stimulation (VNS) is an established treatment option for patients with treatment resistant epilepsy and depression. However, the procedure is invasive and has side-effects. Transcutaneous vagus nerve stimulation (tVNS) is a non-invasive alternative. Particularly transcutaneous stimulation at the outer ear is gaining increasing interest. While the scope of therapeutic tVNS applications is expanding, there are still questions regarding the optimal stimulation parameters and site as well as the physiology and pathways of auricular tVNS. This Special Issue of Autonomic Neuroscience: Basic & Clinical provides an introduction and overview on basic aspects as well as special topics of tVNS.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Auricular branch of the vagus nerve; Concha cymba; Locus coeruleus; Nucleus tractus solitarii; Tragus; Transcutaneous vagus nerve stimulation

Transcutaneous Vagus Nerve Stimulation (tVNS) for Treatment of Drug-Resistant Epilepsy: A Randomized, Double-Blind Clinical Trial (cMPsE02) - Bauer, S.; Baier, H.; Baumgartner, C.; Bohlmann, K.; Fauser, S.; Graf, Wolfgang; Hillenbrand, B.; Hirsch, M.; Last, C.; Lerche, H.; Mayer, T.; Schulze-Bonhage, A.; et al. (Brain Stimulation, 2016)
Various brain stimulation techniques are in use to treat epilepsy. These methods usually require surgical implantation procedures. Transcutaneous vagus nerve stimulation (tVNS) is a non-invasive technique to stimulate the left auricular branch of the vagus nerve at the ear conch.We performed a randomized, double-blind controlled trial (cMPsE02) to assess efficacy and safety of tVNS vs. control stimulation in patients with drug-resistant epilepsy.Primary objective was to demonstrate superiority of add-on therapy with tVNS (stimulation frequency 25 Hz, n = 39) versus active control (1 Hz, n = 37) in reducing seizure frequency over 20 weeks. Secondary objectives comprised reduction in seizure frequency from baseline to end of treatment, subgroup analyses and safety evaluation.Treatment adherence was 84% in the 1 Hz group and 88% in the 25 Hz group, respectively. Stimulation intensity significantly differed between the 1 Hz group (1.02 ± 0.83 mA) and the 25 Hz group (0.50 ± 0.47 mA; p = 0.006). Mean seizure reduction per 28 days at end of treatment was -2.9% in the 1 Hz group and 23.4% in the 25 Hz group (p = 0.146). In contrast to controls, we found a significant reduction in seizure frequency in patients of the 25 Hz group who completed the full treatment period (20 weeks; n = 26, 34.2%, p = 0.034). Responder rates (25%, 50%) were similar in both groups. Subgroup analyses for seizure type and baseline seizure frequency revealed no significant differences. Adverse events were usually mild or moderate and comprised headache, ear pain, application site erythema, vertigo, fatigue, and nausea. Four serious adverse events were reported including one sudden unexplained death in epilepsy patients (SUDEP) in the 1 Hz group which was assessed as not treatment-related.tVNS had a high treatment adherence and was well tolerated. Superiority of 25 Hz tVNS over 1 Hz tVNS could not be proven in this relatively small study, which might be attributed to the higher stimulation intensity in the control group. Efficacy data revealed results that justify further trials with larger patient numbers and longer observation periods.
EVALuna2:22447

Transient naming deficits associated with insular lesions in a patient with encephalitis - Marxreiter, Franz; Utz, Kathrin; Schlachetzki, Johannes; Seifert, Frank; Schmidt, Manuel; Dörfler, Arnd; Schwab, Stefan; Schenk, Thomas (Neurocase, 2019)
We describe a patient with acute herpes simplex encephalitis with left-hemispheric hippocampal, parahippocampal and insular lesions. Although prototypic language areas were unaffected, the patient suffered from an inability to name objects or animals displayed on pictures. This deficit was transient and gradually disappeared 8 weeks after the initial diagnosis. Our findings are in line with a previous report showing similar deficits in a patient with a comparable lesion pattern and support the hypothesis that left insular lesions can produce severe naming deficits. Using FDG-PET we ruled out that functional deactivation in classical language areas account for the observed naming deficits.
EVALuna2:204482

Treatment of established status epilepticus in the elderly - a study protocol for a prospective multicenter double-blind comparative effectiveness trial (ToSEE) - Müller, Annekatrin; Schmiedeknecht, Anett; Mende, Meinhard; Awissus, Carolin; Rosenow, Felix; Hamer, Hajo; Classen, Joseph (BMC Neurology, 2020)
Background: Status epilepticus (SE) is a common neurological emergency condition that especially affects the elderly and old population. Older people with SE frequently have non-convulsive SE (NCSE) and are also at special risk of suffering a poor outcome. The application of benzodiazepines fails to control SE in about one third of the cases. For benzodiazepine refractory SE (BRSE) in elderly, there is little evidence that would justify the choice of one of the commonly used antiepileptic drugs. The present study aims to generate evidence for the treatment of BRSE in this age group. Methods: We will conduct a prospective, randomized, double-blind comparative effectiveness study in more than twenty hospitals in Germany over a four-year period. Four hundred and seventy-seven elderly patients (≥ 65 years old) diagnosed with BRSE will be allocated by 1:1 randomization to receive either levetiracetam or valproate. All types of SE will be considered. For the diagnosis NCSE a verification by EEG is required. Levetiracetam or valproate will be administered in one single infusion. The primary endpoint is the stable cessation of ictal activity 15 min after the start of infusion persisting for the following 45 min of observation. EEG recording is maintained over the whole observation period, clinical examinations are conducted in predefined intervals. In case of treatment success patients and study staff remain blinded until 60 min after the start of the infusion. Adverse events will be recorded until the end of the study. EEG data will be reviewed by two external independent experts. To obtain data about the further treatment of SE, intrahospital complications and the functional outcome in the short term the study participants will be observed until the day of discharge or day 30 whichever is earliest. Discussion: ToSEE is the first study which shall deliver evidence for the SE-therapy in the elderly and old population in a controlled prospective comparator study. By design it also shall collect information about therapy regimes and outcome aspects of this disease. Trial registration: The trial has been registered at the German Clinical Trials Register on 3 July, 2020 (DRKS00022308, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00022308).
CRIS-Team Scopus Importer:2020-12-11
Keywords: Benzodiazepine refractory status epilepticus; Elderly; Levetiracetam; Valproate

Treatment of optic neuritis with erythropoietin (TONE): a randomised, double-blind, placebo-controlled trial-study protocol - Diem, Ricarda; Molnar, Fanni; Beisse, Flemming; Gross, Nikolai; Drueschler, Katharina; Heinrich, Sven P.; Joachimsen, Lutz; Rauer, Sebastian; Pielen, Amelie; Suehs, Kurt-Wolfram; Linker, Ralf; Huchzermeyer, Cord; et al. (BMJ Open, 2016)
Optic neuritis leads to degeneration of retinal ganglion cells whose axons form the optic nerve. The standard treatment is a methylprednisolone pulse therapy. This treatment slightly shortens the time of recovery but does not prevent neurodegeneration and persistent visual impairment. In a phase II trial performed in preparation of this study, we have shown that erythropoietin protects global retinal nerve fibre layer thickness (RNFLT-G) in acute optic neuritis; however, the preparatory trial was not powered to show effects on visual function.Treatment of Optic Neuritis with Erythropoietin (TONE) is a national, randomised, double-blind, placebo-controlled, multicentre trial with two parallel arms. The primary objective is to determine the efficacy of erythropoietin compared to placebo given add-on to methylprednisolone as assessed by measurements of RNFLT-G and low-contrast visual acuity in the affected eye 6 months after randomisation. Inclusion criteria are a first episode of optic neuritis with decreased visual acuity to <= 0.5 (decimal system) and an onset of symptoms within 10 days prior to inclusion. The most important exclusion criteria are history of optic neuritis or multiple sclerosis or any ocular disease (affected or non-affected eye), significant hyperopia, myopia or astigmatism, elevated blood pressure, thrombotic events or malignancy. After randomisation, patients either receive 33,000 international units human recombinant erythropoietin intravenously for 3 consecutive days or placebo (0.9% saline) administered intravenously. With an estimated power of 80%, the calculated sample size is 100 patients. The trial started in September 2014 with a planned recruitment period of 30 months.TONE has been approved by the Central Ethics Commission in Freiburg (194/14) and the German Federal Institute for Drugs and Medical Devices (61-3910-4039831). It complies with the Declaration of Helsinki, local laws and ICH-GCP.NCT01962571.
EVALuna2:21279

Trends in resource utilization and cost of illness in patients with active epilepsy in Germany from 2003 to 2020 - Willems, Laurent M.; Hochbaum, Maja; Zöllner, Johann Philipp; Schulz, Juliane; Menzler, Katja; Langenbruch, Lisa; Kovac, Stjepana; Knake, Susanne; von Podewils, Felix; Hamacher, Mario; Hamer, Hajo; Reese, Jens Peter; et al. (Epilepsia, 2022)
Objective: This study was undertaken to calculate epilepsy-related direct, indirect, and total costs in adult patients with active epilepsy (ongoing unprovoked seizures) in Germany and to analyze cost components and dynamics compared to previous studies from 2003, 2008, and 2013. This analysis was part of the Epi2020 study. Methods: Direct and indirect costs related to epilepsy were calculated with a multicenter survey using an established and validated questionnaire with a bottom-up design and human capital approach over a 3-month period in late 2020. Epilepsy-specific costs in the German health care sector from 2003, 2008, and 2013 were corrected for inflation to allow for a valid comparison. Results: Data on the disease-specific costs for 253 patients in 2020 were analyzed. The mean total costs were calculated at €5551 (±€5805, median = €2611, range = €274–€21 667) per 3 months, comprising mean direct costs of €1861 (±€1905, median = €1276, range = €327–€13 158) and mean indirect costs of €3690 (±€5298, median = €0, range = €0–€11 925). The main direct cost components were hospitalization (42.4%), antiseizure medication (42.2%), and outpatient care (6.2%). Productivity losses due to early retirement (53.6%), part-time work or unemployment (30.8%), and seizure-related off-days (15.6%) were the main reasons for indirect costs. However, compared to 2013, there was no significant increase of direct costs (−10.0%), and indirect costs significantly increased (p <.028, +35.1%), resulting in a significant increase in total epilepsy-related costs (p <.047, +20.2%). Compared to the 2013 study population, a significant increase of cost of illness could be observed (p =.047). Significance: The present study shows that disease-related costs in adult patients with active epilepsy increased from 2013 to 2020. As direct costs have remained constant, this increase is attributable to an increase in indirect costs. These findings highlight the impact of productivity loss caused by early retirement, unemployment, working time reduction, and seizure-related days off.
CRIS-Team Scopus Importer:2022-04-15
Keywords: antiseizure medication; cost of illness; economic burden; health care; seizure

Trends in the neurological emergency room, focusing on persons with seizures - Welte, Tamara; Ernst, Sebastian; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Sprügel, Maximilian; Olmes, David; Schwab, Stefan; Blinzler, Christian; Hamer, Hajo (European Journal of Neurology, 2023)
Background and purpose: Previous studies in neurological emergency rooms (nERs) have reported many non-acute, self-presenting patients, patients with delayed presentation of stroke, and frequent visits of persons with seizures (PWS). The aim of this study was to evaluate trends during the last decade, with special focus on PWS. Methods: We retrospectively analyzed patients who presented to our specialized nER during the course of 5 months in 2017 and 2019, and included information on admission/referral, hospitalization, discharge diagnosis, and diagnostic tests/treatment in the nER. Results: A total of 2791 patients (46.6% male, mean age 57 ± 21 years) were included. The most common diagnoses were cerebrovascular events (26.3%), headache (14.1%), and seizures (10.5%). Most patients presented with symptoms lasting >48 h (41.3%). The PWS group included the largest proportion of patients presenting within 4.5 h of symptom onset (171/293, 58.4%), whereas only 37.1% of stroke patients presented within this time frame (273/735). Self-presentation was the most common admission pathway (31.1%), followed by emergency service referral (30.4%, including the majority of PWS: 197/293, 67.2%). Despite known diagnosis of epilepsy in 49.2%, PWS more often underwent accessory diagnostic testing including cerebral imaging, compared to the overall cohort (accessory diagnostics 93.9% vs. 85.4%; cerebral imaging 70.1% vs. 64.1%). Electroencephalography in the nER was only performed in 20/111 patients (18.0%) with a first seizure. Nearly half of the patients (46.7%) were discharged home after nER work-up, including most self-presenters (632/869, 72.7%) and headache patients (377/393, 88.3%), as well as 37.2% (109/293) of PWS. Conclusion: After 10 years, nER overuse remains a problem. Stroke patients still do not present early enough, whereas PWS, even those with known epilepsy, often seek acute and extensive assessment, indicating gaps in pre-hospital management and possible over-assessment.
CRIS-Team Scopus Importer:2023-09-15
Keywords: epilepsy; headache; neurological emergency room; seizures; stroke

Twenty-Year Time Trends in Long-Term Case-Fatality and Recurrence Rates After Ischemic Stroke Stratified by Etiology - Rücker, Viktoria; Heuschmann, Peter U.; O'Flaherty, Martin; Weingärtner, Michael; Hess, Manuela; Sedlak, Claudia; Schwab, Stefan; Kolominsky-Rabas, Peter (Stroke, 2020)
BACKGROUND AND PURPOSE: Data on long-term survival and recurrence after stroke are lacking. We investigated time trends in ischemic stroke case-fatality and recurrence rates over 20-years stratified by etiological subtype according to the Trial of ORG 10172 in Acute Stroke Treatment classification within a population-based stroke register in Germany. METHODS: Data was collected within the Erlangen Stroke Project, a prospective, population-based stroke register covering a source population of 105 164 inhabitants (2010). Case fatality and recurrence rates for 3 months, 1 year, and 5 years were estimated with Kaplan-Meier estimates. Sex-specific time trends for case-fatality and recurrence rates were estimated with Cox regression. We adjusted for age, sex, and year of event and stratified for etiological subtypes. A sensitivity analysis with competing risk analysis for time trends in recurrence were performed. RESULTS: Between 1996 and 2015, 3346 patients with first ischemic stroke were included; age-standardized incidence per 100 000 was 75.8 in women and 131.6 in men (2015). Overall, 5-year survival probabilities were 50.4% (95% CI, 47.9-53.1) in women and 59.2% (95% CI, 56.4-62.0) in men; 5-year survival was highest in patients with first stroke due to small-artery occlusion (women, 71.8% [95% CI, 67.1-76.9]; men, 75.9% [95% CI, 71.3-80.9]) and lowest in cardioembolic stroke (women, 35.7% [95% CI, 31.0-41.1]; men, 47.8% [95% CI, 42.2-54.3]). Five-year recurrence rates were 20.1% (95% CI, 17.5-22.6) in women and 20.1% (95% CI, 17.5-22.7) in men; 5-year recurrence rate was lowest in women in stroke due to small artery occlusion 16.0% (95% CI, 11.7-20.1) and in men in large-artery atherosclerosis 16.6% (95% CI, 8.7-23.9); highest risk of recurrence was observed in undefined strokes (women, 22.3% [95% CI, 17.8-26.6]; men, 21.4% [95% CI, 16.7-25.9]). Cox regression revealed improvements in case-fatality rates over time with differences in stroke causes. No time trends in recurrence rates were observed. CONCLUSIONS: Long-term survival and recurrence varied substantially by first stroke cause. Survival probabilities improved over the past 2 decades; no major trends in stroke recurrence rates were observed.
CRIS-Team Scopus Importer:2020-09-04
Keywords: arteries; atherosclerosis; incidence; mortality; recurrence

Ultraearly assessed reperfusion status after middle cerebral artery recanalization predicting clinical outcome - Gölitz, Philipp; Mühlen, Iris; Gerner, Stefan; Knossalla, F.; Dörfler, Arnd (Acta Neurologica Scandinavica, 2018)
Objectives: Mechanical thrombectomy has high evidence in stroke therapy; however, successful recanalization guarantees not a favorable clinical outcome. We aimed to quantitatively assess the reperfusion status ultraearly after successful middle cerebral artery (MCA) recanalization to identify flow parameters that potentially allow predicting clinical outcome. Materials and Methods: Sixty-seven stroke patients with acute MCA occlusion, undergoing recanalization, were enrolled. Using parametric color coding, a post-processing algorithm, pre-, and post-interventional digital subtraction angiography series were evaluated concerning the following parameters: pre- and post-procedural cortical relative time to peak (rTTP) of MCA territory, reperfusion time, and index. Functional long-term outcome was assessed by the 90-day modified Rankin Scale score (mRS; favorable: 0-2). Results: Cortical rTTP was significantly shorter before (3.33 +/- 1.36seconds; P = .03) and after intervention (2.05 +/- 0.70seconds; P=.003) in patients with favorable clinical outcome. Additionally, age (P=.005) and initial National Institutes of Health Stroke Scale score (P = .02) were significantly different between the patients, whereas reperfusion index and time as well as initially estimated infarct size were not. In multivariate analysis, only post-procedural rTTP (P=.005) was independently associated with favorable clinical outcome. 2.29seconds for post-procedural rTTP might be a threshold to predict favorable clinical outcome. Conclusions: Ultraearly quantitative assessment of reperfusion status after successful MCA recanalization reveals post-procedural cortical rTTP as possible independent prognostic value in predicting favorable clinical outcome, even determining a threshold value might be possible. In consequence, focusing stroke therapy on microcirculatory patency could be valuable to improve outcome.
EVALuna2:34935

Ultra-early Detection of Microcirculatory Injury as Predictor of Developing Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Gölitz, Philipp; Rösch, Julie; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2018)
Purpose Delayed cerebral ischemia (DCI) still remains amajor complication after subarachnoid hemorrhage (SAH). The aim of our study was to evaluate whether flow analysis of admission digital subtraction angiography (DSA) using parametric color coding (PCC), apostprocessing algorithm, allows ultra-early identification of SAH patients at risk for developing subsequent symptomatic vasospasm. Methods In this study 52patients who suffered SAH from aneurysm rupture, were retrospectively enrolled. Of the patients 26 developed DCI and angiographically proven cerebral vasospasm and 26age, gender-and clinical status-matched SAH patients without DCI served as controls. Using PCC, the following flow parameters were calculated: cerebral circulation time (CirT), cortical relative time to peak (rTTP) and microvascular transit time (TT). Results Mean cerebral CirT and cortical rTTP were longer in the DCI group (6.42s +/- 1.54 and 3.16s +/- 0.86, respectively) than in the non-DCI group (5.77s +/- 1.86 and 3.11s +/- 1.41, respectively), but without statistical significance. The mean microvascular TT was statistically significantly (p = 0.04) longer in the DCI group (3.19s +/- 0.78) than in the non-DCI group (2.67s +/- 0.73). Conclusion Angiographic flow analysis might be suitable for ultra-early detection and quantitative assessment of microcirculatory injury in SAH patients, predictive of developing subsequent DCI. Prolonged microvascular TT seems to be asignificant independent factor positively associated with DCI development. Identifying SAH patients at risk for DCI ultra-early after ictus might contribute to initiate prophylactic therapies before clinical deterioration.
EVALuna2:34933

Ultrasound and electrophysiologic findings in patients with Guillain-Barré syndrome at disease onset and over a period of six months - Grimm, Alexander; Decard, Bernhard F.; Schramm, Axel; Proebstel, Anne-Katrin; Rasenack, Maria; Axer, Hubertus; Fuhr, Peter (Clinical Neurophysiology, 2016)
To investigate cross-sectional areas (CSAs) of several peripheral nerves including the vagus nerve and the diameter of spinal nerves as measured by nerve ultrasound (NUS) and nerve conduction studies (NCS) in Guillain-Barré syndrome (GBS) patients over at least six months compared to healthy controls.NUS and/or NCS of several nerves, the vagus nerve, and the 5th/6th cervical spinal nerves were performed in patients with GBS at days 2-3 after symptom onset, at days 10-14 after immunoglobulin therapy and after six months compared to healthy controls.27 GBS-patients and 31 controls were included. Using NUS significant enlargement was found in all measured nerves (P<0.001), except the sural nerve (P=0.086) compared to the controls at onset. The vagus (median 3.0mm(2) vs. 2.0mm(2), P<0.0001) and the cervical spinal nerves were significantly enlarged (median 3.5/4.0mm vs. 2.6/3.2mm, p<0.0001), the vagus most obviously in patients with autonomic dysregulation (AD, 4.0mm(2)). Six months later, NCS showed persisting pathology in CMAP-amplitudes with amelioration of F-wave pathology. NUS showed restitution in the spinal nerves (median 2.6/3.2mm) and the vagus (median 2.0mm(2)) in all patients excluding the vagus in those with persistent AD (median 4.0mm(2)). The peripheral nerves did not change significantly (P>0.05).Ultrasonographic detection of cervical spinal nerve enlargement supports the diagnosis of GBS in the early phase. Its regression may be a good parameter for the clinical restitution over time. Vagus enlargement may be a risk marker for development of AD.Ultrasound is a reliable diagnostic follow-up tool in early GBS.
EVALuna2:22272

Ultrasound in dual nerve impairment after proximal radial nerve lesion - Laemmer, Alexandra B.; Schwab, Stefan; Schramm, Axel (PLoS ONE, 2015)
Sonography in classical nerve entrapment syndromes is an established and validated method. In contrast, few publications highlight lesions of the radial nerve, particularly of the posterior interosseus nerve (PIN).Five patients with a radial nerve lesion were investigated by electromyography, nerve conduction velocity and ultrasound. Further normative values of 26 healthy subjects were evaluated.Four patients presented a clinical and electrophysiological proximal axonal radial nerve lesion and one patient showed a typical posterior interosseous nerve syndrome (PINS). The patient with PINS presented an enlargement of the PIN anterior to the supinator muscle. However four patients with proximal lesions showed an unexpected significant enlargement of the PIN within the supinator muscle.High-resolution sonography is a feasible method to demonstrate the radial nerve including its distal branches. At least in axonal radial nerve lesions, sonography might reveal abnormalities far distant from a primary proximal lesion site clearly distinct from the appearance in classical PINS.
EVALuna2:22367

Unmeasured Confounding in Observational Studies of Management of Cerebellar Intracranial Hemorrhage-Reply - Kuramatsu, Joji; Sheth, Kevin N.; Huttner, Hagen (Journal of the American Medical Association, 2020)
CRIS-Team Scopus Importer:2020-02-28

Usage of antiepileptic drugs in different diseases in Germany – A retrospective study - Scholten, Jerome; Hamer, Hajo; Kostev, Karel (Epilepsy & Behavior, 2020)
Aim: The goal of this study was to analyze and quantify the usage of antiepileptic drugs (AEDs) in different diseases and settings in Germany. Methods: This retrospective study, based on data from the Disease Analyzer database (IQVIA), included patients from 550 general practices (GP) and 73 neurological practices. Patients who had received at least one prescription for AED from one of these practices between January 2009 and December 2011 (time period 1, n = 39,434) or between January 2016 and December 2018 (time period 2, n = 49,128) were analyzed. Results: In patients who received AED prescriptions from neurologists, epilepsy (43%) was the most common diagnosis and did not change over time. The proportion of pain diagnoses slightly decreased from 35% in the period from 2009 to 2011 to 34% in the period from 2016 to 2018, while psychiatric disorders increased from 13% to 15%. In GPs, 58% of patients received their AED prescriptions for pain disorders, followed by epilepsy (29%) in the period from 2009 to 2011. The proportion of pain patients slightly increased to 60%, while that of patients with epilepsy slightly decreased to 27%. Conclusions: The main indications for which AEDs are prescribed vary with the type of medical practice. The different indications for different AEDs changed between the two time periods, which is in line with the state of the research.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Antiepileptic drugs; Epilepsy; Pain; Psychiatric condition

Use of a German longitudinal prescription database (LRx) in pharmacoepidemiology - Richter, Hartmut; Dombrowski, Silvia; Hamer, Hajo; Hadji, Peyman; Kostev, Karel (GMS German Medical Science, 2015)
Large epidemiological databases are often used to examine matters pertaining to drug utilization, health services, and drug safety. The major strength of such databases is that they include large sample sizes, which allow precise estimates to be made. The IMS® LRx database has in recent years been used as a data source for epidemiological research. The aim of this paper is to review a number of recent studies published with the aid of this database and compare these with the results of similar studies using independent data published in the literature. In spite of being somewhat limited to studies for which comparative independent results were available, it was possible to include a wide range of possible uses of the LRx database in a variety of therapeutic fields: prevalence/incidence rate determination (diabetes, epilepsy), persistence analyses (diabetes, osteoporosis), use of comedication (diabetes), drug utilization (G-CSF market) and treatment costs (diabetes, G-CSF market). In general, the results of the LRx studies were found to be clearly in line with previously published reports. In some cases, noticeable discrepancies between the LRx results and the literature data were found (e.g. prevalence in epilepsy, persistence in osteoporosis) and these were discussed and possible reasons presented. Overall, it was concluded that the IMS® LRx database forms a suitable database for pharmacoepidemiological studies.
EVALuna2:22376

Use of a telestroke service for evaluation of non-stroke neurological cases - Handschu, Rene; Wacker, Angela; Scibor, Mateusz; Sancu, Camelia; Schwab, Stefan; Erbguth, Frank; Oschmann, Patrick; Stark, David Rianto; Marquardt, Lars (Journal of Neurology, 2015)
Telemedicine is a growing field in many medical specialties. Within clinical neurosciences one of its largest applications is in acute stroke care. However, little is known about its value and effect in general neurology, despite stroke. In a retrospective survey of 1500 teleconsultations over a time period of 12 months from October 2008 to September 2009, from a large telestroke network in Germany, we evaluated 352 cases with a non-stroke diagnosis. Duration and methods of teleconsultation as well as neurological consultations at bedside and discharge diagnosis were analyzed and compared to stroke cases. Discharge diagnosis was not identical to teleconsultation diagnosis in 48.9% of all non-stroke cases compared to 12.5% of all stroke cases. Duration of teleconsultation was 26.5 min in non-stroke cases compared to 14.3 min for stroke cases. In non-stroke cases other parts of the neurological examination were added to the pure administration of a stroke scale. There were no significant differences between non-stroke cases with correct and incorrect consultation diagnoses concerning in-hospital mortality (4.6 vs. 5.0%) and length of hospital stay (8.3 vs. 7.6 days). We conclude that diagnostic accuracy and protocol routine is not as exact in non-stroke cases compared to acute stroke cases. Other neurologic conditions may need different algorithms for a telemedicine service. Thus experience from a telestroke service cannot be transferred to other neurologic conditions on a routine basis.
EVALuna2:22364

Vagomimetic Fingolimod effects are compensated by central up-regulation of cardiovagal withdrawal upon rapid blood pressure decrease - Roy, Sankanika; Wang, Ruihao; de Rojas Leal, Carmen; Liu, Mao; Hoesl, K.; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (2018)
EVALuna2:201951

Validation of automatic MRI hippocampal subfield segmentation by histopathological evaluation in patients with temporal lobe epilepsy - Menzler, Katja; Hamer, Hajo; Mross, Peter; Rosenow, Felix; Deichmann, Ralf; Wagner, Marlies; Gracien, René Maxime; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Belke, Marcus; Knake, Susanne (Seizure-European Journal of Epilepsy, 2021)
Objective: The present study validates the results of automated hippocampal subfield segmentation with histopathology in epilepsy patients undergoing epilepsy surgery. Methods: We performed an automated hippocampal subfield segmentation on presurgical three-dimensional, T1-weighted magnetization Prepared Rapid Acquisition of Gradient Echoes Magnetic Resonance Imaging (MRI) data of 25 patients with unilateral mesial temporal lobe epilepsy due to hippocampal sclerosis (HS), using Freesurfer Version 6.0. The resulting volumes of cornu ammonis (CA) subfields CA1, CA2/3, CA4 and the dentate gyrus (DG) were compared to the histopathological cell count. Results: We found a significant correlation between histopathology in subregion CA2 and automated segmentation of subregion CA1 (p = 0.0062), CA2/3 (p = 0.004), CA4 (p = 0.0062) and the DG (p = 0.0054), between histopathology in CA3 and automated segmentation of CA1 (p = 0.0132), CA2/3 (p = 0.0004), CA4 (p = 0.0032) and the DG (p = 0.0037), as well as between histopathology in the DG and automated segmentation of CA1 (p = 0.0115), CA2/3 (p < 0.0001), CA4 (p < 0.0001) and the DG (p = 0.0001). The histopathological finding of HS type 1 could correctly be classified in all cases on MRI. Significance: The present study shows significant correlations between histopathological evaluation and results of the automated segmentation of the hippocampus, thereby validating the automated segmentation method. As the differential involvement of different hippocampal subfields may be associated with clinical parameters and the outcome after epilepsy surgery, the automated segmentation is also promising for prognostic purposes.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Automated segmentation; Hippocampal subfields; Mesiotemporal sclerosis; Mri

Validation of the Composite Autonomic Symptom Score 31 in the German language - Hilz, Max-Josef; Wang, Ruihao; Singer, Wolfgang (Neurological Sciences, 2021)
Background The Composite Autonomic Symptom Score 31 (COMPASS 31) is a validated, 31-item self-assessment questionnaire assessing autonomic symptoms in six domains, orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, bladder, and pupillomotor function. So far, there is no validated German COMPASS 31 version. This study aimed at developing and validating a German COMPASS 31. Methods Two autonomic experts with command of German and English independently translated the English COMPASS 31 into German. One agreed-upon German version was translated back into English to assure conformity with the original version. Twenty patients with possible autonomic symptoms and 20 age- and gender-matched healthy persons completed the English and German COMPASS 31 in a randomized order with a 4-week interval. To evaluate reliability of the German COMPASS 31, total scores and sub-scores of the domains assessed with the German version were correlated with corresponding scores of the English version using Pearson's or Spearman's test. The Cronbach alpha-coefficient evaluated the internal consistency of the questions. Total- and sub-scores of both COMPASS 31 versions were compared between patients and controls by analysis of variance with post-hoc analysis (significance: p < 0.05). Results Total scores and sub-scores of the German and English COMPASS 31 correlated significantly (p < 0.001) and closely (correlation coefficients: 0.757-0.934). Cronbach alpha-coefficients were above 0.7 in all domains except for the secretomotor domain. In the German and English COMPASS 31, total scores were significantly higher in patients than controls. Conclusions The German COMPASS 31 is reliable, internally consistent, and valid to detect and quantify autonomic symptoms in patients with neurological disorders.
CRIS-Team WoS Importer:2021-12-03

Valsalva maneuver unveils central baroreflex dysfunction with altered blood pressure control in persons with a history of mild traumatic brain injury - Hilz, Max-Josef; Liu, Mao; Koehn, Julia; Wang, Ruihao; Ammon, Fabian; Flanagan, Steven R.; Hoesl, Katharina M. (BMC Neurology, 2016)
Patients with a history of mild TBI (post-mTBI-patients) have an unexplained increase in long-term mortality which might be related to central autonomic dysregulation (CAD). We investigated whether standardized baroreflex-loading, induced by a Valsalva maneuver (VM), unveils CAD in otherwise healthy post-mTBI-patients.In 29 healthy persons (31.3 ± 12.2 years; 9 women) and 25 post-mTBI-patients (35.0 ± 13.2 years, 7 women, 4-98 months post-injury), we monitored respiration (RESP), RR-intervals (RRI) and systolic blood pressure (BP) at rest and during three VMs. At rest, we calculated parameters of total autonomic modulation [RRI-coefficient-of-variation (CV), RRI-standard-deviation (RRI-SD), RRI-total-powers], of sympathetic [RRI-low-frequency-powers (LF), BP-LF-powers] and parasympathetic modulation [square-root-of-mean-squared-differences-of-successive-RRIs (RMSSD), RRI-high-frequency-powers (HF)], the index of sympatho-vagal balance (RRI LF/HF-ratios), and baroreflex sensitivity (BRS). We calculated Valsalva-ratios (VR) and times from lowest to highest RRIs after strain (VR-time) as indices of parasympathetic activation, intervals from highest systolic BP-values after strain-release to the time when systolic BP had fallen by 90 % of the differences between peak-phase-IV-BP and baseline-BP (90 %-BP-normalization-times), and velocities of BP-normalization (90 %-BP-normalization-velocities) as indices of sympathetic withdrawal. We compared patient- and control-parameters before and during VM (Mann-Whitney-U-tests or t-tests; significance: P < 0.05).At rest, RRI-CVs, RRI-SDs, RRI-total-powers, RRI-LF-powers, BP-LF-powers, RRI-RMSSDs, RRI-HF-powers, and BRS were lower in patients than controls. During VMs, 90 %-BP-normalization-times were longer, and 90 %-BP-normalization-velocities were lower in patients than controls (P < 0.05).Reduced autonomic modulation at rest and delayed BP-decrease after VM-induced baroreflex-loading indicate subtle CAD with altered baroreflex adjustment to challenge. More severe autonomic challenge might trigger more prominent cardiovascular dysregulation and thus contribute to increased mortality risk in post-mTBI-patients.
EVALuna2:22445

Value of initial C-reactive protein levels in status epilepticus outcome prediction - Madzar, Dominik; Reindl, Caroline; Mrochen, Anne; Hamer, Hajo; Huttner, Hagen (Epilepsia, 2021)
The role of neuroinflammation in the pathophysiology of seizures is increasingly recognized, and the evaluation of potential biochemical markers of inflammatory processes in seizures and status epilepticus (SE), such as C-reactive protein (CRP), has gained attention. The present study assessed the first CRP level obtained in an SE episode regarding its value for SE outcome prediction. Among 362 admissions for SE during the study period, 231 episodes satisfied the inclusion criteria. Higher initial CRP concentrations were independently associated with in-hospital mortality and poor functional outcome at discharge in logistic regression models adjusting for SE severity, severity of SE etiology, and development of treatment refractoriness. Therefore, initial CRP levels may add to the prediction of SE prognosis. The pathomechanisms through which CRP is linked with the prognosis of SE, however, remain to be established.
CRIS-Team Scopus Importer:2021-03-05
Keywords: acute phase proteins; C-reactive protein; inflammation; laboratory parameters; outcome; status epilepticus

Vanilla-stimulation suggests subtle central autonomic dysfunction in patients with a history of mild traumatic brain injury - Liu, Mao; Roy, Sankanika; Wang, Ruihao; de Rojas Leal, Carmen; Hoesl, K.; Hummel, T.; Hilz, M. J. (2017)
EVALuna2:22571

Variation of membrane particle–bound CD133 in cerebrospinal fluid of patients with subarachnoid and intracerebral hemorrhage - Bobinger, Tobias; Röder, Sebastian; Sprügel, Maximilian; Fröhlich, Kilian; Beuscher, Vanessa; Hölter, Philip; Lücking, Hannes; Corbeil, Denis; Huttner, Hagen (Journal of Neurosurgery, 2021)
OBJECTIVE Previous studies have demonstrated that human CSF contains membrane particles carrying the stem cell antigenic marker CD133 (prominin-1). Here, the authors analyzed the variation of the amount of these CD133-positive particles in the CSF of patients with subarachnoid hemorrhage (SAH) and intracerebral hemorrhage (ICH). METHODS Consecutive CSF samples from 47 patients with SAH or ICH were compared to 14 healthy control patients. After differential ultracentrifugation of CSF, the membrane particle fraction was separated on gel electrophoresis and its CD133 content was probed by immunoblotting using the mouse monoclonal antibody 80B258 directed against human CD133. The antigen-antibody complexes were detected by chemiluminescence reagents and quantified using human Caco-2 cell extract as positive control with a standardized curve. RESULTS As compared to healthy controls (6.3 ± 0.5 ng of bound CD133 antibody; n = 14), the amount of membrane particle–associated CD133 immunoreactivities was significantly elevated in patients with SAH and ICH (38.2 ± 6.6 ng and 61.3 ± 11.0 ng [p < 0.001] for SAH [n = 18] and ICH [n = 29], respectively). In both groups the CD133 level dropped during the first 7 days (i.e., day 5–7: SAH group, 24.6 ± 10.1 ng [p = 0.06]; ICH group, 25.0 ± 4.8 ng [p = 0.002]). Whereas changes in the amount of CD133-positive membrane particles between admission and day 5–7 were not associated with clinical outcomes in patients with ICH (modified Rankin Scale [mRS] scores 0–3, −30.9 ± 12.8 ng vs mRS scores 4–6, −21.8 ± 10.7 ng; p = 0.239), persistent elevation of CD133 in patients with SAH was related to impaired functional outcome 3 months after ictus (mRS scores 0–2, −29.9 ± 8.1 ng vs mRS scores 3–6, 7.6 ± 20.3 ng; p = 0.027). These data are expressed as the mean ± standard error of the mean (SEM). CONCLUSIONS Levels of membrane particle–associated CD133 in the CSF of patients with SAH and ICH are significantly increased in comparison to healthy patients, and they decline during the hospital stay. Specifically, the persistent elevation of CD133-positive membrane particles within the first week may represent a possible surrogate measure for impaired functional outcome in patients with SAH.
CRIS-Team Scopus Importer:2021-04-09
Keywords: CD133; Intracerebral hemorrhage; Membrane particles; Prominin-1; Stem cells; Subarachnoid hemorrhage; Vascular disorders

Varicella Zoster Virus-Specific Hyperimmunoglobulin in the Adjuvant Treatment of Immunocompromised Herpes Zoster Patients: A Case Series - Terheyden, Patrick; Sunderkötter, Cord; Söhngen, Franz Dietmar; Golle, Linda; Schimo, Sonja; Baron, Ralf; Maihöfner, Christian; Binder, Andreas; Pönisch, Wolfram (Dermatology and Therapy, 2023)
Introduction: Immunocompromised patients are at increased risk for herpes zoster (HZ)-associated complications. Despite standard therapy with systemic antiviral drugs and analgesics, complications are frequently encountered, including generalization of lesions or persistent neuropathic pain, so-called post-herpetic neuralgia (PHN). Given the scarcity of literature and awareness of therapeutic options to improve patient outcomes, especially for vulnerable patient groups, here we describe a strategy based on early intensification of treatment with a varicella zoster virus-specific hyperimmunoglobulin (VZV-IgG), which is approved in the adjuvant treatment of HZ. Methods: For this case series, we selected four cases of HZ in patients with impaired immunity due to hemato-oncologic disease or immunosuppressive treatment who presented with either existing generalized lesions and/or severe pain or with other risk factors for a complicated HZ course such as PHN. They were considered to be representative examples of different patient profiles eligible for intensification of treatment by the addition of VZV-IgG to virostatic therapy. Case Report: All patients showed a rapid response to combined treatment with VZV-IgG and a virostatic agent. In two patients who had generalized lesions, the formation of new lesions ceased 1 day after VZV-IgG infusion. One patient, with mantle cell lymphoma, achieved complete healing of the lesions 9 days after diagnosis of HZ, a rare occurrence compared to similar cases or cohorts. A patient with HZ in the cervical region showed a good response after a single dose of VZV-IgG. None of the patients developed post-zoster-related complications. Combination therapy of a virostatic agent and VZV-IgG was well tolerated in these four cases. Conclusion: This case series demonstrates highly satisfactory treatment effectiveness and tolerability for VZV-IgG in the adjuvant treatment of immunocompromised HZ patients and supports early intensification of HZ therapy in patients at high risk of severe disease progression.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Generalized lesions; Herpes zoster; Hyperimmunoglobulin; Immunocompromised; Varitect CP; VZV; VZV-IgG

Vasospasm in intracerebral hemorrhage with ventricular involvement: a prospective pilot transcranial Doppler sonography study - Kiphuth, Ines C.; Huttner, Hagen; Breuer, Lorenz; Engelhorn, Tobias; Schwab, Stefan; Köhrmann, Martin (Cerebrovascular Diseases, 2011)
Cerebral vasospasm (VSP) is a common complication after subarachnoid hemorrhage (SAH), but has rarely been reported after intracerebral hemorrhage (ICH) without subarachnoidal bleeding. The underlying pathophysiological mechanism is mainly mediated by circulating heme products within the cerebrospinal fluid, and thus patients with ICH and ventricular involvement (IVH) may also be in danger of developing VSP. The incidence and role of VSP in IVH, however, have not been systematically studied.We prospectively enrolled 115 patients with ICH with or without IVH into the study between April 2009 and April 2010. All patients received serial extracranial and transcranial Doppler sonography (TCD) at baseline, on days 3-5 and 7-9 to detect and monitor VSP. In addition, CT scans taken on admission, after 24 h and before discharge were evaluated for the occurrence of delayed cerebral ischemia.Three out of 53 patients (5.7%) with IVH showed a significant elevation of flow velocities over the examined timeframe. One of these patients developed severe VSP resulting in secondary ischemic infarction. None of the ICH patients without IVH showed significantly elevated flow velocities or secondary infarction.Cerebral VSP with secondary infarction may occur in patients with spontaneous IVH, though far less frequently than in SAH; thus, systematic screening of all patients with IVH may not be warranted. However, serial TCD should be considered in patients with secondary clinical worsening or extensive IVH.
EVALuna2:21961

Violations of Weber's law tell us more about methodological challenges in sensorimotor research than about the neural correlates of visual behaviour - Schenk, Thomas; Utz, Kathrin S.; Hesse, Constanze (Vision research, 2017)
The violation of Weber's law in grasping has been presented as evidence for the claim that grasping is guided by visual information which is distinct from the information used in perceptual tasks. Previously, we contested this claim and argued that biomechanical constraints of the hand might explain why Weber's law cannot be reliably uncovered in grasping movements. In a recent article Manzone and colleagues (2017) show that pantomime grasping follows Weber's law even with objects whose width is close to the hand's biomechanical limit. In this commentary we explain why the biomechanical account does not necessarily predict the violation of Weber's law in a pantomime grasping task and why it seems problematic to use adherence or violation of Weber's law as a criterion to assign tasks to different anatomical pathways.
EVALuna2:35712

Visual and semiautomated evaluation of epileptogenicity in focal cortical dysplasias - An intracranial EEG study - Gollwitzer, Stephanie; Valente, Ivan; Rodionov, Roman; Scott, Catherine; Ritter, Laura Mantoan; Wehner, Tim; Hamer, Hajo; Bartolomei, Fabrice; Diehl, Beate (Epilepsy and Behavior, 2016)
The aim of the study was the evaluation of the added value of depth to subdural electrodes in delineating epileptogenicity of focal cortical dysplasias (FCDs) and to test the Epileptogenicity Index (EI) in this setting.Fifteen patients with FCD underwent iEEG with subdural and depth electrodes. Visual/EI analysis was performed in up to three habitual seizures per patient.Visual analysis: Grid onset seizures (n=10) started in electrodes overlying the lesion in 7 and remote from it in 3 cases. Depth onset seizures (n=7) affected only intralesional contacts in 4, intra- and extralesional in 2, and exclusively extralesional in 1 patient. Seizures started in depth and grid contacts simultaneously in 2 cases. EI analysis: The EI completely confirmed visual localization of seizure onset in 8 cases and depicted ictal onset-time accurately in 13. Beta/gamma ictal patterns were most reliably captured. Impact on surgical decision: Resection outline differed from MRI lesion in 7 patients based on grid and in three based on depth electrode information.In FCD, seizures can be generated within gyral/deep tissue appearing normal on imaging.Investigating FCD with subdural and depth electrodes is efficient to outline the seizure onset zone. The EI is a helpful additional tool to quantify epileptogenicity. Specific ictal patterns are prerequisite for reliable results.
EVALuna2:22453

Visual feedback explains why propointing is better than antipointing in spatial neglect - Utz, Kathrin S.; Hesse, Constanze; Hintz, Annika; Grüneberger, Daniela; Kulke, Hartwig; Roth, Inga; Klos, Thomas; Kromichal, Vaclav; Melms, Arthur; Schupp, Wilfried; Kohl, Detlef; Schenk, Thomas (Cortex, 2017)
Rossit et al. (2011) showed that neglect patients perform normally in a propointing task but not in an antipointing task which requires pointing towards the mirrored position of a target. It is assumed that antipointing relies on information from the perceptual pathway of our visual brain. Therefore, this finding supports the notion that neglect is a disorder that primarily affects perceptual spatial representations within the brain leaving spatial maps used for visuomotor guidance intact. Alternatively, performance of patients might be compromised in both tasks, but only obviously so in tasks in which online corrections are made more difficult. It can be argued that online-corrections via visual feedback are less effective in antipointing because a direct comparison between hand and target is not possible in this condition. Secondly, it is also known that neglect patients have a pronounced egocentric bias which is assumed to be associated with a deviation of the perceived body midline. Since the midline is used to compute the end-position in the antipointing task this could also explain why patients are worse in antipointing. We investigated the influence of visual feedback on pro- and antipointing and the effect of providing a visual reference line for the antipointing task in right-brain damaged patients with neglect (n = 20), right-brain damaged patients without neglect (n = 23) and in a group of healthy participants (n = 22). The withdrawal of visual feedback had a stronger effect on propointing compared to antipointing. This effect was stronger in neglect patients than in patients without neglect or healthy controls. The introduction of a reference line reduced errors in antipointing performance, particularly in neglect patients with a strong egocentric bias. The results support our alternative account and challenge the hypothesis that the spatial disorder in neglect affects primarily perceptual maps within the visual system.
EVALuna2:22443

Visualization of large vessel occlusion, clot extent, and collateral supply using volume perfusion flat detector computed tomography in acute stroke patients - Gölitz, Philipp; Lang, Stefan; Lücking, Hannes; Kalmuenzer, Bernd; Struffert, Tobias; Dörfler, Arnd; Hölter, Philip (Acta Radiologica, 2019)
Background: Flat detector computed tomography angiography (FDCTA) can be reconstructed from volume perfusion flat detector computed tomography (VP-FDCT). Thus, CTA equivalent stroke imaging might be feasible within the angio suite. Purpose: To evaluate the diagnostic accuracy of FDCTA in detecting large vessel occlusion (LVO) and collateral supply in acute stroke patients. Material and Methods: Sixteen patients with LVO of the anterior circulation were analyzed retrospectively. Each patient underwent a multimodal CT stroke protocol, subsequent VP-FDCT, and digital subtraction angiography (DSA) for endovascular stroke therapy. Angiographic images reconstructed secondarily from VP-FDCT were evaluated with regard to visualization of LVO, Collateral Score (CS), Clot Burden Score (CBS), and image quality. Results: Image quality of FDCTA was sufficient for diagnosis with a strong correlation between CTA and FDCTA (median score: CTA = 4 ± 0.447; FDCTA = 4 ± 0.5). Detection of LVO could be achieved with high sensitivity and specificity for FDCTA and CTA (97.9%, 95% confidence interval [CI] = 96.0–99.9; 92.6%, 95% CI = 84.3–100.0 vs. 96.8%, 95% CI = 93.2–100.0; 86.3%, 95% CI = 88.2–95.2). CBS and CS assessment showed no significant difference between FDCTA and CTA for both readers (reader1 CBS : P = 0.751, reader1 CS : P = 0.718; reader2 CBS : P = 0.164; reader2 CS : P = 0.582) and an excellent interrater agreement (CTA CBS ICC = 0.984, FDCTA CBS ICC = 0.951; CTA CS ICC = 0.754, FDCTA CS ICC = 0.789). Conclusion: FDCTA, reconstructed from VP-FDCT data, allows reliable detection of ICA or MCA M1 segment occlusion comparable to CTA and may provide information concerning the clot extent with sufficient image quality.
CRIS-Team Scopus Importer:2019-10-11
Keywords: Central nervous system; flat detector computed tomography; interventional; stroke

Visualizing transfer of microbial biomolecules by outer membrane vesicles in microbe-host-communication in vivo - Bittel, Miriam; Reichert, Patrick; Sarfati, Ilann; Dressel, Anja; Leikam, Stefanie; Uderhardt, Stefan; Stolzer, Iris; Phu, Tuan Anh; Ng, Martin; Vu, Ngan K.; Tenzer, Stefan; Distler, Ute; et al. (Journal of Extracellular Vesicles, 2021)
The intestinal microbiota influences mammalian host physiology in health and disease locally in the gut but also in organs devoid of direct contact with bacteria such as the liver and brain. Extracellular vesicles (EVs) or outer membrane vesicles (OMVs) released by microbes are increasingly recognized for their potential role as biological shuttle systems for inter-kingdom communication. However, physiologically relevant evidence for the transfer of functional biomolecules from the intestinal microbiota to individual host cells by OMVs in vivo is scarce. By introducing Escherichia coli engineered to express Cre-recombinase (E. coliCre) into mice with a Rosa26.tdTomato-reporter background, we leveraged the Cre-LoxP system to report the transfer of bacterial OMVs to recipient cells in vivo. Colonizing the intestine of these mice with E. coliCre, resulted in Cre-recombinase induced fluorescent reporter gene-expression in cells along the intestinal epithelium, including intestinal stem cells as well as mucosal immune cells such as macrophages. Furthermore, even far beyond the gut, bacterial-derived Cre induced extended marker gene expression in a wide range of host tissues, including the heart, liver, kidney, spleen, and brain. Together, our findings provide a method and proof of principle that OMVs can serve as a biological shuttle system for the horizontal transfer of functional biomolecules between bacteria and mammalian host cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Cre-Loxp; extracellular vesicles; inflammation; intestinal stem cells; microbiome; outer membrane vesicles

Visual search as a tool for a quick and reliable assessment of cognitive functions in patients with multiple sclerosis - Utz, Kathrin S.; Hankeln, Thomas; Jung, Lena; Laemmer, Alexandra; Waschbisch, Anne; Lee, De-Hyung; Linker, Ralf; Schenk, Thomas (PLoS ONE, 2013)
Despite the high frequency of cognitive impairment in multiple sclerosis, its assessment has not gained entrance into clinical routine yet, due to lack of time-saving and suitable tests for patients with multiple sclerosis.The aim of the study was to compare the paradigm of visual search with neuropsychological standard tests, in order to identify the test that discriminates best between patients with multiple sclerosis and healthy individuals concerning cognitive functions, without being susceptible to practice effects.Patients with relapsing remitting multiple sclerosis (n = 38) and age-and gender-matched healthy individuals (n = 40) were tested with common neuropsychological tests and a computer-based visual search task, whereby a target stimulus has to be detected amongst distracting stimuli on a touch screen. Twenty-eight of the healthy individuals were re-tested in order to determine potential practice effects.Mean reaction time reflecting visual attention and movement time indicating motor execution in the visual search task discriminated best between healthy individuals and patients with multiple sclerosis, without practice effects.Visual search is a promising instrument for the assessment of cognitive functions and potentially cognitive changes in patients with multiple sclerosis thanks to its good discriminatory power and insusceptibility to practice effects.
EVALuna2:22182

Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12

WADA test for postoperative memory prediction in left TLE. Is it still useful in the 21st century? - Bruzsa, Ann Kathrin; Walther, Katrin; Kasper, Burkhard; Gollwitzer, Stefanie; Hamer, Hajo; Schwarz, Michael (Clinical Neurology and Neurosurgery, 2023)
Background: Epilepsy surgery offers an effective treatment to achieve seizure freedom in refractory temporal lobe epilepsy. Since left temporal lobe surgery can be associated with verbal memory deterioration, control of cognitive decline is a main goal of therapy. This study analyzes the prognostic value of intracarotid amobarbital procedure (Wada test) in addition to specific neuropsychological and clinical variables for postoperative memory changes. Method: Between 2013 and 2021 thirty-six patients (18 females, 18 males, mean age 41.0 years) from the Epilepsy Center Erlangen (ECE) with left hemispheric temporal lobe epilepsy underwent neuropsychological assessment preoperatively – including the Wada test – and six months postoperatively. In addition, a group of 92 patients (40 females, 52 males, mean age 36.1 years) with left or right hemispheric focus who underwent Wada test and surgery before 2013 was included as a standardization group. In all patients Wada test was carried out preoperatively to determine language dominance and memory capacity. Results: Postoperative verbal memory scores showed no significant difference from preoperative performance. Preoperative verbal memory performance as well as the hippocampal resection extent is particularly important in predicting postoperative verbal memory change. After left temporal lobe surgery, a significantly higher postoperative functional level was shown for figural memory. Specifically, a good contralateral hemispheric performance level assessed by the Wada test proved to be a compensatory factor for postoperative losses. Conclusion: The Wada test is no longer necessary as a diagnostic tool for a broad group of patients with temporal lobe epilepsy. However, it can be useful for a subgroup of patients with clinical indicators such as nonspecific or incongruent preoperative verbal and figural memory impairments. In this study, Wada test data about the functional level of the contralateral hemisphere specifically allowed estimation of postoperative figural memory changes.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Epilepsy surgery; Memory changes; Temporal lobe epilepsy; Wada test

Why Does It Shine?-A Prognostic Analysis about Predisposing Factors for Blood-Brain Barrier Damage after Revascularisation of Cerebral Large-Vessel Occlusion. - Knott, Michael; Hock, Stefan; Soder, Liam; Mühlen, Iris; Kremer, Svenja; Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Journal of Cardiovascular Development and Disease, 2023)
BACKGROUND: Hyperdense lesions in CT after EVT of LVO are common. These lesions are predictors for haemorrhages and an equivalent of the final infarct. The aim of this study based on FDCT was the evaluation of predisposing factors for these lesions. METHODS: Using a local database, 474 patients with mTICI ≥ 2B after EVT were recruited retrospectively. A postinterventional FDCT after recanalisation was analysed regarding such hyperdense lesions. This was correlated with a variety of items (demographics, past medical history, stroke assessment/treatment and short-/long-term follow-up). RESULTS: Significant differences were present in NHISS at admission, regarding time window, ASPECTS in initial NECT, location of the LVO, CT-perfusion (penumbra, mismatch ratio), haemostatic parameters (INR, aPTT), duration of EVT, number of EVT attempts, TICI, affected brain region, volume of demarcation and FDCT-ASPECTS. The ICH-rate, the volume of demarcation in follow-up NECT and the mRS at 90 days differed in association with these hyperdensities. INR, the location of demarcation, the volume of demarcation and the FDCT-ASPECTS could be demonstrated as independent factors for the development of such lesions. CONCLUSION: Our results support the prognostic value of hyperdense lesions after EVT. We identified the volume of the lesion, the affection of grey matter and the plasmatic coagulation system as independent factors for the development of such lesions.
EVALuna2:536989

Why systematic literature reviews in Fabry disease should include all published evidence - Elliott, Perry M.; Germain, Dominique P.; Hilz, Max-Josef; Spada, Marco; Wanner, Christoph; Falissard, Bruno (European Journal of Medical Genetics, 2019)
Fabry disease is an X-linked inherited, progressive disorder of lipid metabolism resulting from the deficient activity of the enzyme α-galactosidase. Enzyme replacement therapy (ERT) with recombinant agalsidase, with intravenous infusions of either agalsidase beta or agalsidase alfa, is available and clinical experience now exceeds 15 years. There are very few randomised, placebo-controlled clinical trials evaluating the outcomes of ERT. Data are often derived from observational, registry-based studies and case reports. Pooled analysis of data from different sources may be limited by the heterogeneity of the patient populations, outcomes and treatment. Therefore, comprehensive systematic literature reviews of unpooled data are needed to determine the effects of ERT on disease outcomes. A systematic literature search was conducted in the Embase and PubMed (MEDLINE) databases to retrieve original articles that evaluated outcomes of ERT in patients with Fabry disease; the outcome data were analysed unpooled. The literature analysis included the full range of published literature including observational studies and case series/case reports. Considerable heterogeneity was found among the studies, with differences in sample size, statistical methods, ERT regimens and patient demographic and clinical characteristics. We have demonstrated the value of performing an unpooled systematic literature review of all published evidence of ERT outcomes in Fabry disease, highlighting that in a rare genetic disorder like Fabry disease, which is phenotypically diverse, different patient populations can require different disease management and therapeutic goals depending on age, genotype, and disease severity/level of organ involvement. In addition, these findings are valuable to guide the design and reporting of new clinical studies.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Enzyme replacement therapy; Fabry disease; Systematic literature review

Woman with sudden-onset speech difficulties. - To, Vi Tuong Daniel; Marterstock, Dominique; Madžar, Dominik (Journal of the American College of Emergency Physicians Open, 2023)
EVALuna2:540367

α-Synuclein deficiency promotes neuroinflammation by increasing Th1 cell-mediated immune responses - Ettle, Benjamin; Kuhbandner, Kristina; Joerg, Stefanie; Hoffmann, Alana; Winkler, Jürgen; Linker, Ralf (Journal of Neuroinflammation, 2016)
Increased ?-synuclein immunoreactivity has been associated with inflammatory activity in multiple sclerosis (MS) lesions, but the function of ?-synuclein in neuroinflammation remains unknown. The aim of this study was to examine the role of ?-synuclein in immunological processes in murine experimental autoimmune encephalomyelitis (EAE) as a model of MS.We studied EAE in wildtype (aSyn(+/+)) and ?-synuclein knockout (aSyn(-/-)) mice on a C57BL/6N background. In the spleen and spinal cord of aSyn(+/+) mice, we observed a gradual reduction of ?-synuclein expression during EAE, starting already in the pre-symptomatic disease phase. Compared to aSyn(+/+) mice, aSyn(-/-) mice showed an earlier onset of symptoms but no differences in symptom severity at the peak of disease. Earlier symptom onset was accompanied by increased spinal cord infiltration of CD4(+) T cells, predominantly of interferon-?-producing T helper 1 (Th1) cells, and reduced infiltration of regulatory T cells, whereas antigen-presenting cells were unaltered. Pre-symptomatically, aSyn(-/-) mice exhibited hyperproliferative CD4(+) splenocytes consistent with increased splenic interleukin-2 mRNA expression, resulting in increased numbers of Th1 cells in the spleen at the onset of symptoms.Our findings indicate a functional role of ?-synuclein in early EAE by increasing Th1 cell-mediated immune response.
EVALuna2:22458

A prospective, multisite, international validation of the Complex Regional Pain Syndrome Severity Score - Harden, R. Norman; Maihofner, Christian; Abousaad, Elias; Vatine, Jean-Jacques; Kirsling, Amy; Perez, Roberto S. G. M.; Kuroda, Maxine; Brunner, Florian; Stanton-Hicks, Michael; Marinus, Johan; Van Hilten, Jacobus J.; Mackey, Sean; et al. (Pain, 2017)
Clinical diagnosis of complex regional pain syndrome (CRPS) is a dichotomous (yes/no) categorization, a format necessary for clinical decision making. Such dichotomous diagnostic categories do not convey an individual's subtle gradations in the severity of the condition over time and have poor statistical power when used as an outcome measure in research. This prospective, international, multicenter study slightly modified and further evaluated the validity of the CRPS Severity Score (CSS), a continuous index of CRPS severity. Using a prospective design, medical evaluations were conducted in 156 patients with CRPS to compare changes over time in CSS scores between patients initiating a new treatment program and patients on stable treatment regimens. New vs stable categorizations were supported by greater changes in pain and function in the former. Results indicated that CSS values in the stable CRPS treatment group exhibited much less change over time relative to the new treatment group, with intraclass correlations nearly twice as large in the former. A calculated smallest real difference value revealed that a change in the CSS of ≥4.9 scale points would indicate real differences in CRPS symptomatology (with 95% confidence). Across groups, larger changes in CRPS features on the CSS over time were associated in the expected direction with greater changes in pain intensity, fatigue, social functioning, ability to engage in physical roles, and general well-being. The overall pattern of findings further supports the validity of the CSS as a measure of CRPS severity and suggests it may prove useful in clinical monitoring and outcomes research.
EVALuna2:36359

Characterization of somatosensory profiles in patients with Crohn's disease - Münster, Tino; Eckl, Stefanie; Leis, Stefan; Goehring-Waldeck, Gabriele; Ihmsen, Harald; Maihöfner, Christian (Pain Practice, 2015)
Crohn's disease (CD) is a painful chronic inflammatory bowel disease. It primarily affects terminal ileum, but the involvement of large and small intestines or extraintestinal manifestations is very common. CD may go along with neurogenic inflammation, mediated by substance P and CGRP, which are also key players in pain transmission. This may in turn contribute to hyperalgesia and altered somatosensory function in CD.One hundred and three (103) patients with CD and 80 healthy volunteers were enrolled. Patient characteristics and disease history were documented. We used quantitative sensory testing (QST) to investigate the somatosensory profile in patients and volunteers. We also calculated z-scores for the QST results of the patients with CD based on the data of our control group. A 2-step cluster analysis, using all QST data, was performed to find subgroups within patients and volunteers.Thresholds of warm detection, mechanical pain, and vibration detection did significantly differ between patients with CD and volunteers. Z-scores indicated a general trend of sensory loss in CD patients with a significant relationship between patients with a sensory loss for cold and warm detection. In the hyposensitive cluster of the CD cohort, patients were more frequently male, had a higher incidence of extraintestinal manifestations, and suffered longer from CD.Our findings are consistent with the presence of a subclinical small fiber neuropathy. The group of CD patients with pronounced neuropathy findings were predominantly males, had a higher incidence of extraintestinal manifestations, and tended to have a longer history of disease duration.
EVALuna2:16687

Efficacy of Cladribine Tablets in high disease activity subgroups of patients with relapsing multiple sclerosis: A post hoc analysis of the CLARITY study - Giovannoni, Gavin; Sorensen, Per Soelberg; Cook, Stuart; Rammohan, Kottil W.; Rieckmann, Peter; Comi, Giancarlo; Dangond, Fernando; Hicking, Christine; Vermersch, Patrick (Multiple sclerosis journal, 2019)
Background: In the CLARITY (CLAdRIbine Tablets treating multiple sclerosis orallY) study, Cladribine Tablets significantly improved clinical and magnetic resonance imaging (MRI) outcomes (vs placebo) in patients with relapsing-remitting multiple sclerosis. Objective: Describe two clinically relevant definitions for patients with high disease activity (HDA) at baseline of the CLARITY study (utility verified in patients receiving placebo) and assess the treatment effects of Cladribine Tablets 3.5 mg/kg compared with the overall study population. Methods: Outcomes of patients randomised to Cladribine Tablets 3.5 mg/kg or placebo were analysed for subgroups using HDA definitions based on high relapse activity (HRA; patients with > 2 relapses during the year prior to study entry, whether on DMD treatment or not) or HRA plus disease activity on treatment (HRA + DAT; patients with > 2 relapses during the year prior to study entry, whether on DMD treatment or not, PLUS patients with > 1 relapse during the year prior to study entry while on therapy with other DMDs and > 1 T1 Gd+ or > 9 T2 lesions). Results: In the overall population, Cladribine Tablets 3.5 mg/kg reduced the risk of 6-month-confirmed Expanded Disability Status Scale (EDSS) worsening by 47% vs placebo. A risk reduction of 82% vs placebo was seen in both the HRA and HRA + DAT subgroups (vs 19% for non-HRA and 18% for non-HRA + DAT), indicating greater responsiveness to Cladribine Tablets 3.5 mg/kg in patients with HDA. There were consistent results for other efficacy endpoints. The safety profile in HDA patients was consistent with the overall CLARITY population. Conclusion: Patients with HDA showed clinical and MRI responses to Cladribine Tablets 3.5 mg/kg that were generally better than, or at least comparable with, the outcomes seen in the overall CLARITY population.
CRIS-Team WoS Importer:2019-04-25

Expert opinion consensus on recommendations for treating relapsing multiple sclerosis with cladribine tablets in daily clinical practice - Sorensen, P. Soelberg; Centonze, D.; Giovannoni, G.; Montalban, X.; Selchen, D.; Vermersch, P.; Wiendl, H.; Yamout, B.; Salloukh, H.; Rieckmann, P. (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Long-term disease stability assessed by the expanded disability status scale in patients treated with Cladribine tablets in the CLARITY and CLARITY extension studies - Giovannoni, G.; Comi, G.; Rammohan, K.; Rieckmann, P.; Vermersch, P.; Dangond, F.; Keller, B.; Jack, D. (MULTIPLE SCLEROSIS JOURNAL, 2019)
CRIS-Team WoS Importer:2019-10-11